Accelerating Distributed Optimization via Over-the-Air Computing - Mitsiou, Nikos A.; Bouzinis, Pavlos S.; Diamantoulakis, Panagiotis D.; Schober, Robert; Karagiannidis, George K. (IEEE Transactions on Communications, 2023)
Distributed optimization is ubiquitous in emerging applications, such as robust sensor network control, smart grid management, machine learning, resource slicing, and localization. However, the extensive data exchange among local and central nodes may cause a severe communication bottleneck. To overcome this challenge, over-the-air computing (AirComp) is a promising medium access technology, which exploits the superposition property of the wireless multiple access channel (MAC) and offers significant bandwidth savings. In this work, we propose an AirComp framework for general distributed convex optimization problems. Specifically, a distributed primal-dual (DPD) subgradient method is utilized for the optimization procedure. Under general assumptions, we prove that DPD-AirComp can asymptotically achieve zero expected constraint violation. Therefore, DPD-AirComp ensures the feasibility of the original problem, despite the presence of channel fading and additive noise. Moreover, with proper power control of the users’ signals, the expected non-zero optimality gap can also be mitigated. Two practical applications of the proposed framework are presented, namely, smart grid management and wireless resource allocation. Finally, numerical results confirm DPD-AirComp’s excellent performance, while it is also shown that DPD-AirComp converges an order of magnitude faster compared to two digital orthogonal multiple access schemes, specifically, time-division multiple access (TDMA), and orthogonal frequency-division multiple access (OFDMA).
CRIS-Team Scopus Importer:2023-07-07
Keywords: 6G; 6G mobile communication; Convergence; distributed optimization; large-scale optimization; Linear programming; non-orthogonal multiple access; Optimization; Over-the-air computing; primal-dual; Resource management; Servers; Smart grids; subgradient method

A Chemical Master Equation Model for Synaptic Molecular Communication - Lotter, Sebastian; Schäfer, Maximilian; Schober, Robert (2022 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2022)
CRIS-Team WoS Importer:2022-08-12

Achievable Rate of the Half-Duplex Multi-Hop Buffer-Aided Relay Channel With Block Fading - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Shoukry, Hebatallah; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
The half-duplex (HD) multi-hop relay channel consists of a source, multiple HD relays connected in series, and a destination where links are present only between adjacent nodes. In this paper, we focus on decode-and-forward relays and assume that the links are impaired by block fading and additive white Gaussian noise. We design a new protocol which, unlike the conventional protocols for the multi-hop relay channel, does not adhere to a fixed and predefined pattern of using the transmit, receive, and silent states of the nodes. In particular, the proposed protocol selects the optimal states of the nodes and the corresponding optimal transmission rates based on the instantaneous channel state information (CSI) of the involved links in each fading block such that the achievable average rate from source to destination is maximized. To enable adaptive scheduling of the states of the nodes, the relay nodes have to be equipped with buffers for temporary storage of the information received from the preceding node. Additionally, we discuss and address two practical challenges arising in the implementation of the optimal protocol, namely the unconstrained end-to-end delay due to data buffering at the relays and the required CSI overhead. Numerical results confirm the superiority of the proposed buffer-aided protocols compared to existing multi-hop relaying protocols.<br
Keywords: Relays; Protocols; High definition video; Fading; Buffer storage; Interference; Optimization

Achievable Rate Region of the Bidirectional Buffer-Aided Relay Channel With Block Fading - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Ikhlef, Aissa; Schober, Robert (IEEE Transactions on Information Theory, 2014)
The bidirectional relay channel, in which two users communicate with each other through a relay node, is a simple but fundamental and practical network architecture. In this paper, we consider the block fading bidirectional relay channel with a decode-and-forward relay and propose efficient transmission strategies that exploit the block fading property of the channel. We assume that a direct link between the two users is not present and consider two transmission modes: 1) the multiple-access mode (both users transmit to the relay) and 2) the broadcast mode (the relay transmits to both users). Most existing relaying protocols assume a fixed schedule for using these transmission modes. In contrast, we abandon the restriction of having a fixed and predefined schedule and propose to optimize the selection of the transmission modes and the associated transmission rates based on the instantaneous channel state information (CSI) of the involved links. Thereby, we consider two different types of transmit power constraints: 1) a fixed transmit power for each node and 2) a per-node long-term power constraint. To enable the use of a nonpredefined schedule for transmission mode selection, the relay has to be equipped with two buffers for storage of the information received from both users. We develop new relaying protocols based on adaptive mode selection and provide the corresponding achievable long-term rate regions. In particular, based on the CSI of the involved links, the optimal transmission mode as well as the optimal transmission rates and/or the transmit powers of the nodes are chosen in each time slot to maximize the weighted sum rate of both users. By varying the weights assigned to the users, the boundary surface of the achievable long-term rate region of the proposed protocol can be obtained. In addition, we discuss and address two practical challenges for the implementation of the proposed protocols, namely, the availability of the knowledge of the channel statistics required for the implementation of the optimal protocols, and the increase of the end-to-end delay due to the data buffering. Numerical results confirm the superiority of the proposed buffer-aided protocols compared with existing bidirectional relaying protocols.<br
Keywords: Relays; Protocols; Fading; Buffer storage; Optimization; Schedules; Decoding

Achievable Rates for the Fading Half-Duplex Single Relay Selection Network Using Buffer-Aided Relaying - Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
In the half-duplex single relay selection network, comprised of a source, M half-duplex relays, and a destination, only one relay is active at any given time, i.e., only one relay receives or transmits, and the other relays are inactive, i.e., they do not receive nor transmit. The capacity of this network, when all links are affected by independent slow time-continuous fading and additive white Gaussian noise (AWGN) , is still unknown, and only achievable average rates have been reported in the literature so far. In this paper, we present new achievable average rates for this network, which are larger than the best known average rates. These new average rates are achieved with a buffer-aided relaying protocol. Since the developed buffer-aided protocol introduces unbounded delay, we also devise a buffer-aided protocol which limits the delay at the expense of a decrease in rate. Moreover, we discuss the practical implementation of the proposed buffer-aided relaying protocols and show that they do not require more resources for channel state information acquisition than the existing relay selection protocols.<br
Keywords: Relays; Protocols; Delays; High definition video; Wireless communication; Rayleigh channels

Achievable rates for the fading three-hop half-duplex relay network using buffer-aided relaying - Shoukry, Hebatallah; Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
The fading three-hop half-duplex relay network consists of a source, two half-duplex relays, and a destination connected in series where links are present only between adjacent nodes. We assume that the links are impaired by time-continuous fading and additive white Gaussian noise. For this network, we design new protocols based on buffer-aided relaying and derive their achievable average rates. We first develop a buffer-aided protocol which maximizes the average rate, but, as a side effect, introduces unbounded delay. Therefore, we also design a buffer-aided protocol which constrains the average delay, but at the expense of decrease of rate. Our numerical results show that the maximum average rate achieved with the developed buffer-aided protocol is larger than that of existing protocols for the considered network. Moreover, given a sufficiently large permissible average delay, the average rate achieved with the buffer-aided protocol with a delay constraint approaches the maximum average rate achieved without a delay constraint.<br
Keywords: Protocols; Delays; Fading; Relay networks (telecommunications); Spread spectrum communication; Switches

Achievable Throughput of Magnetic Induction based Sensor Networks for the Underground Communications - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (Wireless Sensor Systems for Extreme Environments. Space, Underwater, Underground and Industrial, 2017)

ACM NANOCOM 2018: 5th ACM international conference on nanoscale computing and communication: Reykjavik, Iceland, September 5-7, 2018 - Benediktsson, Jon Atli; Dressler, Falko; Payne, Gregory F.; Juntti, Markku; Schober, Robert; Tentzeris, Emmanouil M.; Kokkoniemi, Joonas; Balasingham, Ilangko; Jornet, Josep M.; Han, Chong; Feng, Liang; Barros, Michael; et al. (Proceedings of the 5th ACM International Conference on Nanoscale Computing and Communication, NANOCOM 2018, 2018)
CRIS-Team Scopus Importer:2022-06-05

A Comprehensive Overview on 5G-and-Beyond Networks with UAVs: From Communications to Sensing and Intelligence - Wu, Qingqing; Xu, Jie; Zeng, Yong; Ng, Derrick Wing Kwan; Al-Dhahir, Naofal; Schober, Robert; Swindlehurst, A. Lee (IEEE Journal on Selected Areas in Communications, 2021)
Due to the advancements in cellular technologies and the dense deployment of cellular infrastructure, integrating unmanned aerial vehicles (UAVs) into the fifth-generation (5G) and beyond cellular networks is a promising solution to achieve safe UAV operation as well as enabling diversified applications with mission-specific payload data delivery. In particular, 5G networks need to support three typical usage scenarios, namely, enhanced mobile broadband (eMBB), ultra-reliable low-latency communications (URLLC), and massive machine-type communications (mMTC). On the one hand, UAVs can be leveraged as cost-effective aerial platforms to provide ground users with enhanced communication services by exploiting their high cruising altitude and controllable maneuverability in three-dimensional (3D) space. On the other hand, providing such communication services simultaneously for both UAV and ground users poses new challenges due to the need for ubiquitous 3D signal coverage as well as the strong air-ground network interference. Besides the requirement of high-performance wireless communications, the ability to support effective and efficient sensing as well as network intelligence is also essential for 5G-and-beyond 3D heterogeneous wireless networks with coexisting aerial and ground users. In this paper, we provide a comprehensive overview of the latest research efforts on integrating UAVs into cellular networks, with an emphasis on how to exploit advanced techniques (e.g., intelligent reflecting surface, short packet transmission, energy harvesting, joint communication and radar sensing, and edge intelligence) to meet the diversified service requirements of next-generation wireless systems. Moreover, we highlight important directions for further investigation in future work.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 5G-and-beyond 3D cellular networks; aerial-terrestrial integration; Cellular networks; communication; Drones; Interference; network intelligence; sensing; Sensors; Three-dimensional displays; Unmanned aerial vehicle (UAV); Wireless fidelity; Wireless sensor networks

A construction of turbo-like codes for iterative channel estimation based on probabilistic bias - Takeuchi, Keigo; Müller, Ralf; Vehkaperä, Mikko (54th Annual IEEE Global Telecommunications Conference: "Energizing Global Communications", GLOBECOM 2011, 2011)
A novel signaling scheme for iterative channel estimation and data decoding is proposed. In the proposed scheme, the occurrence probability of transmitted symbols is biased. A priori information about the bias is utilized for the initial channel estimation. The proposed scheme is based on parallel concatenation of two biased convolutional codes (BCCs), which are constructed as systematic recursive convolutional codes with state-dependent puncturing. The BCCs can be regarded as a joint coding scheme that determines the insertion positions of pilot symbols according to information bits. The proposed scheme is numerically shown to outperform conventional pilot-based schemes in the waterfall region, while it is inferior to the conventional schemes in the error-floor region. © 2011 IEEE.

Active IRS Design for RSMA-based Downlink URLLC Transmission - Darabi, Mostafa; Ghanem, Walid; Jamali, Vahid; Lampe, Lutz; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2023)
Rate-splitting multiple access (RSMA) has been proposed as a flexible multiple access scheme for improving interference management in sixth-generation (6G) networks. In particular, the low latency facilitated by RSMA and its robustness against user mobility and imperfect channel state information make it an ideal candidate for the ultra-reliable and low-latency (URLLC) use case in 6G networks. However, since the common message in RSMA needs to be decoded by all the users, the achievable rate of the common message is determined by the user with the poorest channel quality. To overcome this bottleneck, an active intelligent reflecting surface (IRS) can be deployed to enhance the achievable rate of the common stream. However, this comes at the expense of additional power consumption due to the active IRS. In this paper, we consider an active IRS-aided RSMA-based downlink URLLC system and study the resource allocation design for minimization of the power consumption of the base station and the active IRS under quality-of-service constraints for the URLLC users. Our simulation results reveal that active IRSs yield a lower overall power consumption and require a smaller surface size compared to passive IRSs in RSMA-based URLLC systems. Moreover, we show that active IRS-aided RSMA systems consume less power than active IRS-aided space division multiple access (SDMA) systems.
CRIS-Team Scopus Importer:2023-06-02
Keywords: 6G cellular networks; Active IRS; power consumption minimization; RSMA; URLLC

Active RIS Aided ISAC Systems: Beamforming Design and Performance Analysis - Yu, Zhiyuan; Ren, Hong; Pan, Cunhua; Zhou, Gui; Wang, Boshi; Dong, Mianxiong; Wang, Jiangzhou (IEEE Transactions on Communications, 2023)
This paper considers an active reconfigurable intelligent surface (RIS)-aided integrated sensing and communication (ISAC) system. We aim to maximize radar signal-to-interference-plus-noise-ratio (SINR) by jointly optimizing the beamforming matrix at the dual-function radar-communication (DFRC) base station (BS) and the reflecting coefficients at the active RIS subject to the quality of service (QoS) constraints of communication users (UE) and the transmit power constraints of active RIS and DFRC BS. To tackle the optimization problem, the majorization-minimization (MM) algorithm is applied to address the nonconvex radar SINR objective function, and the resulting quartic problem is solved by developing an semidefinite relaxation (SDR)-based approach. Moreover, we derive the scaling order of the radar SINR with a large number of reflecting elements. Next, the transmit power allocation problem and the deployment strategy of the active RIS are studied with a moderate number of reflecting elements. Finally, we validate the potential of the active RIS in ISAC systems compared to passive RIS. Additionally, we deliberate on several open problems that remain for future research.
CRIS-Team Scopus Importer:2023-12-15
Keywords: active RIS; dual-function radar-communication (DFRC); integrated sensing and communication (ISAC); intelligent reflecting surface (IRS); Reconfigurable intelligent surface (RIS)

Active RISs: Signal Modeling, Asymptotic Analysis, and Beamforming Design - Zhang, Zijian; Dai, Linglong; Chen, Xibi; Liu, Changhao; Yang, Fan; Schober, Robert; Poor, H. Vincent (2022 IEEE Global Communications Conference, GLOBECOM 2022 - Proceedings, 2022)
Reconfigurable intelligent surfaces (RISs) have emerged as a candidate technology for future 6G networks. However, due to the 'multiplicative fading' effect, the existing passive RISs only achieve a negligible capacity gain in environments with strong direct links. In this paper, the concept of active RISs is studied to overcome this fundamental limitation. Unlike the existing passive RISs that reflect signals without amplification, active RISs can amplify the reflected signals via amplifiers integrated into their elements. To characterize the signal amplification and incorporate the noise introduced by the active components, we verify the signal model of active RISs through the experimental measurements on a fabricated active RIS element. Based on the verified signal model, we formulate the sum-rate maximization problem for an active RIS aided multi-user multiple-input single-output (MU-MISO) system and a joint transmit precoding and reflect beamforming algorithm is proposed to solve this problem. Simulation results show that, in a typical wireless system, the existing passive RISs can realize only a negligible sum-rate gain of 3%, while the active RISs can achieve a significant sum-rate gain of 62%, thus over coming the 'multiplicative fading' effect. Finally, we develop a 64-element active RIS aided wireless communication prototype, and the significant gain of active RISs is validated by field test.
CRIS-Team Scopus Importer:2023-03-07

Active RIS vs. Passive RIS: Which Will Prevail in 6G? - Zhang, Zijian; Dai, Linglong; Chen, Xibi; Liu, Changhao; Yang, Fan; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2022)
As a revolutionary paradigm for controlling wireless channels, reconfigurable intelligent surfaces (RISs) have emerged as a candidate technology for future 6G networks. However, due to the “multiplicative fading” effect, the existing passive RISs only achieve limited capacity gains in many scenarios with strong direct links. In this paper, the concept of active RISs is proposed to overcome this fundamental limitation. Unlike passive RISs that reflect signals without amplification, active RISs can amplify the reflected signals via amplifiers integrated into their elements. To characterize the signal amplification and incorporate the noise introduced by the active components, we develop and verify the signal model of active RISs through the experimental measurements based on a fabricated active RIS element. Based on the verified signal model, we further analyze the asymptotic performance of active RISs to reveal the substantial capacity gain they provide for wireless communications. Finally, we formulate the sum-rate maximization problem for an active RIS aided multi-user multiple-input single-output (MU-MISO) system and a joint transmit beamforming and reflect precoding scheme is proposed to solve this problem. Simulation results show that, in a typical wireless system, passive RISs can realize only a limited sum-rate gain of 22%, while active RISs can achieve a significant sum-rate gain of 130%, thus overcoming the “multiplicative fading” effect.
CRIS-Team Scopus Importer:2023-03-07
Keywords: active RIS; Array signal processing; beamforming; Fading channels; Propagation losses; Receivers; Reconfigurable intelligent surface (RIS); signal model; Signal to noise ratio; Transmitters; Wireless communication

Adaptive Joint Interference Cancellation and Space-Time Block Decoding for IEEE 802.11b WLAN Systems - Jonietz, Christof; Gerstacker, Wolfgang; Rohde, Christian; Koch, Wolfgang; Schober, Robert (Conference Proceedings, 2006)
Digital transmission in wireless local area networks (WLANs) according to the IEEE 802.11b standard suffers from fading, intersymbol interference (ISI), and co-channel interference (CCI). In this paper, receivers with joint interference cancellation and time-reversal space-time block decoding (JICSTD) are proposed for an enhanced version of the IEEE 802.11b WLAN standard with space-time coded transmission. In IEEE 802.11b, complementary code keying (CCK) with a maximum data rate of 11 Mbit/s is employed as modulation format. The proposed receivers perform JICSTD in a first stage and equalization in a second stage. Minimum mean-squared error (MMSE-)JICSTD presuming perfect channel knowledge for all users and a training based least-squares (LS-)JICSTD for asynchronous interference are investigated, respectively. For subsequent equalization block-based reduced-state sequence estimation (RSSE) tailored for CCK transmission is used.<br
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.mobilk.adapti
Keywords: Silicon; Adaptation model

Adaptive mode selection for bidirectional relay networks - Fixed rate transmission - Jamali, Vahid; Zlatanov, Nikola; Schober, Robert (2014 IEEE International Conference on Communications, ICC 2014, 2014)
In this paper, we consider the problem of sum throughput maximization for bidirectional relay networks with block fading. Thereby, user 1 and user 2 exchange information only via a relay node, i.e., a direct link between both users is not present. We assume that channel state information at the transmitter (CSIT) is not available and/or only one coding and modulation scheme is used at the transmitters due to complexity constraints. Thus, the nodes transmit with a fixed predefined rate regardless of the channel state information (CSI). In general, the nodes in the network can assume one of three possible states in each time slot, namely the transmit, receive, and silent state. Most of the existing protocols assume a fixed schedule for the sequence of the states of the nodes. In this paper, we abandon the restriction of having a fixed and predefined schedule and propose a new protocol which, based on the CSI at the receiver (CSIR), selects the optimal states of the nodes in each time slot such that the sum throughput is maximized. To this end, the relay has to be equipped with two buffers for storage of the information received from the two users. Numerical results show that the proposed protocol significantly outperforms the existing protocols. © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Adaptive mode selection in bidirectional buffer-aided relay networks with fixed transmit powers - Jamali, Vahid; Zlatanov, Nikola; Ikhlef, Aissa; Schober, Robert (European Signal Processing Conference, 2013)
We consider a bidirectional network in which two users exchange information with the help of a buffer-aided relay. In such a network without direct link between user 1 and user 2, there exist six possible transmission modes, i.e., four point-to-point modes (user 1-to-relay, user 2-to-relay, relay-to-user 1, relay-to-user 2), a multiple access mode (both users to the relay), and a broadcast mode (the relay to both users). Because of the buffering capability at the relay, the transmissions in the network are not restricted to adhere to a predefined schedule, and therefore, all the transmission modes in the bidirectional relay network can be used adaptively based on the instantaneous channel state information (CSI) of the involved links. For the considered network, assuming fixed transmit powers for both the users and the relay, we derive the optimal transmission mode selection policy which maximizes the sum rate. The proposed policy selects one out of the six possible transmission modes in each time slot based on the instantaneous CSI. Simulation results confirm the effectiveness of the proposed protocol compared to existing protocols. © 2013 EURASIP.
CRIS-Team Scopus Importer:2020-02-03

Adaptive relay selection protocol for the parallel hybrid RF/FSO relay channel - Najafi Kalyani, Marzieh; Jamali Kooshkghazi, Vahid; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
Hybrid radio frequency (RF)/free space optical (FSO) systems are among the candidate enabling technologies for the next generation of wireless networks since they benefit from the advantages of both the FSO subsystem, e.g. high data rates, and the RF subsystem, e.g. high reliability in terms of link connectivity. In this paper, we focus on the problem of throughput maximization in the parallel hybrid RF/FSO relay channel. In the parallel hybrid RF/FSO relay channel, a source node sends its data to a destination node with the help of multiple relay nodes. Thereby, the source-relay and the relay-destination FSO links are orthogonal with respect to each other due to the narrow beam employed for FSO transmission whereas the RF links are half duplex with respect to each other due to the broadcast nature of RF signals. We derive the optimal relay selection policies for transmission and reception for the RF and FSO links and the optimal time allocation policy to the RF relay reception and transmission links. Simulation results demonstrate that a considerable gain can be achieved by the proposed adaptive protocol in comparison with benchmark schemes from the literature.<br
Keywords: Radio frequency; Relays; Optical Transmitters; Protocols; Throughput; RF Signals; Receivers

Adaptive resource allocation for the fading interference channel with source cooperation - Najafi Kalyani, Marzieh; Jamah, Vahid; Schober, Robert (2015 Iran Workshop on Communication and Information Theory (IWCIT), 2015)
In this paper, we consider the Gaussian interference channel consisting of two source-destination pairs where the sources cooperate to transmit their messages to their respective destination. We assume block fading and that the nodes are constrained to half-duplex operation. For this channel, assuming availability of channel state information (CSI), we determine the optimal adaptive scheduling of reception and transmission at the source nodes. Thereby, the proposed protocol chooses one of the information flows, decides whether to transmit directly or cooperatively to the corresponding destination, and specifies the required transmission strategy such that the achievable ergodic rate region is maximized. Numerical results reveal that the proposed protocol can effectively realize the diversity offered by the fading processes of the different links in the interference channel.<br

A delay-constrained protocol with adaptive mode selection for bidirectional relay networks - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
In this paper, we consider a bidirectional relay network with half-duplex nodes and block fading where the nodes transmit with a fixed transmission rate. Thereby, user 1 and user 2 exchange information only via a relay node, i.e., a direct link between both users is not present. Recently in [1], it was shown that a considerable gain in terms of sum throughput can be obtained in bidirectional relaying by optimally selecting the transmission modes or, equivalently, the states of the nodes, i.e., the transmit, the receive, and the silent states, in each time slot based on the qualities of the involved links. To enable adaptive transmission mode selection, the relay has to be equipped with two buffers for storage of the data received from the two users. However, the protocol proposed in [1] was delay-unconstrained and provides an upper bound for the performance of practical delay-constrained protocols. In this paper, we propose a heuristic but efficient delay-constrained protocol which can approach the performance upper bound reported in [1]. Moreover, the average throughput and delay of the protocol are evaluated by analyzing the Markov chain of the states of the queues.<br
Keywords: Protocols; Delays; Relays; Signal to noise ratio; Throughput; Fading; Markov processes

A Diagnostic Method for Power Line Networks by Channel Estimation of PLC Devices - Lehmann, Andreas; Raab, Katrin; Gruber, Florian; Fischer, Erik; Müller, Ralf; Huber, Johannes (Proceedings of IEEE International Conference on Smart Grid Communications, 2016)

A distributed market framework for mobile data offloading - Wang, Kehao; Lau, Francis C. M.; Chen, Lin; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
We develop a distributed market framework to price the offloading service, and conduct a detailed analysis of the incentives for offloading service providers and conflicts arising from the interactions of different participators. Specifically, we formulate a multi-leader multi-follower Stackelberg game (MLMF-SG) to model the interactions between the offloading service providers and the offloading service consumers in the considered market framework, and investigate the cases where the offloading capacity of APs is unlimited and limited, respectively. For the case without capacity limit, we decompose the followers' game of the MLMF-SG (FG-MLMF-SG) into a number of simple follower games (FGs), and prove the existence and uniqueness of the equilibrium of the FGs from which the existence and uniqueness of the FG-MLMF-SG also follows. For the leaders' game of the MLMF-SG, we also prove the existence and uniqueness of the equilibrium. For the case with capacity limit, by considering a symmetric strategy profile, we establish the existence and uniqueness of the equilibrium of the corresponding MLMF-SG, and present a distributed algorithm that allows the leaders to achieve the equilibrium. Finally, extensive numerical experiments demonstrate that the Stackelberg equilibrium is very close to the corresponding social optimum for both considered cases.<br
Keywords: Games; Radio frequency; Mobile communication; Mobile computing; Pricing; Wireless communication; IEEE 802.11 Standard

Advanced optical wireless communication systems - Arnon, Shlomi; Barry, John R.; Karagiannidis, George K.; Schober, Robert; Uysal, Murat (Cambridge University Press, 2012)
Optical wireless communications is a dynamic area of research and development. Combining fundamental theory with a broad overview, this book is an ideal reference for anyone working in the field, as well as a valuable guide for self-study. It begins by describing important issues in optical wireless theory, including coding and modulation techniques for optical wireless, wireless optical CDMA communication systems, equalization and Markov chains in cloud channels and optical MIMO systems, as well as explaining key issues in information theory for optical wireless channels. The next section describes unique channels that could be found in optical wireless applications, such as NLOS UV atmospheric scattering channels, underwater communication links and a combination of hybrid RF/optical wireless systems. The final section describes applications of optical wireless technology, such as quantum encryption, visible light communication, IR links and sensor networks, with step-by-step guidelines to help reduce design time and cost.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Communications and Signal Processing; Engineering; Electronic; Optoelectronic Devices; Nanotechnology

Advanced Receiver Algorithms for LTE Control Channels in Presence of Parameter Estimation Errors and Inter-Cell Interference - Nair, Vinay (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Advanced target detection via molecular communication - Mosayebi, Reza; Wicke, Wayan; Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert; Nasiri-Kenari, Masouhmeh (IEEE GlobeCom 2018, 2018)

A Fair Comparison Between Spatial Modulation and Antenna Selection in Massive MIMO Systems - Gäde, Bernhard; Bereyhi, Ali; Asaad, Saba; Müller, Ralf (Workshop on Smart Antennas WSA 2019, 2019)
Both antenna selection and spatial modulation allow for low-complexity MIMO transmitters when the number of RF chains is much lower than the number of transmit antennas. In this manuscript, we present a quantitative performance comparison between these two approaches by taking into account implementational restrictions, such as antenna switching. We consider a band-limitedMIMO system, for which the pulse shape is designed, such that the outband emission satisfies a desired spectral mask. The bit error rate is determined for this system, considering antenna selection and spatial modulation. The results depict that for any array size at the transmit and receive sides, antenna selection outperforms spatial modulation, as long as the power efficiency is smaller than a certain threshold level. By passing this threshold, spatial modulation starts to perform superior. Our investigations show that the threshold takes smaller values, as the number of receive antennas grows large. This indicates that spatial modulation is an effective technique for uplink transmission in massive MIMO systems.<br
Keywords: Antenna selection; spatial modulation; band limitation

A Framework for Mutual Information-based MIMO Integrated Sensing and Communication Beamforming Design - Li, Jin; Zhou, Gui; Gong, Tantao; Liu, Nan (IEEE Transactions on Vehicular Technology, 2024)
Integrated sensing and communication (ISAC) unifies sensing and communication, and improves the efficiency of the spectrum, energy, and hardware. In this work, we investigate the ISAC beamforming design to maximize the mutual information between the target response matrix of a point radar target and the echo signals, while ensuring the data rate requirements of the communication users. The scenarios in this paper are considered from two perspectives: one is from the perspective of the number of communication users, and the other is from the perspective of the type of echo interference caused by other interfering scatterers. For the case of a single communication user, in order to reduce the complexity of the algorithm, we consider three types of echo interference, no interference, a point interference, and an extended interference. For the case of multiple communication users, the interference is also an extended one, and furthermore, each user's communication rate requirement needs to be satisfied. To find the optimal beamforming design in these problems, we provide a closed-form solution with low complexity, a semidefinite relaxation (SDR) method, a low-complexity algorithm based on the Majorization-Minimization (MM) method and the successive convex approximation (SCA) method, and an algorithm based on MM method and SCA method, respectively. Numerical results demonstrate that, compared to the ISAC beamforming schemes based on the Cramér-Rao bound (CRB) metric, the beampattern metric and the MSE metric, the proposed mutual information metric can bring better beampattern and root mean square error (RMSE) of angle estimation. Furthermore, our proposed schemes designed based on the mutual information metric can suppress the echo interference from interfering scatterers in the environment effectively.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Array signal processing; beamforming; Clutter; Integrated sensing and communication (ISAC); Majorization-Minimization (MM); Measurement; MIMO communication; Mutual information; mutual information; Radar; Sensors; signal-dependent radar clutter interference

A Framework for Transmission Design for Active RIS-Aided Communication with Partial CSI - Zhou, Gui; Pan, Cunhua; Ren, Hong; Xu, Dongfang; Zhang, Zaichen; Wang, Jiangzhou; Schober, Robert (IEEE Transactions on Wireless Communications, 2023)
Active reconfigurable intelligent surfaces (RISs) have recently been proposed to compensate for the severe multiplicative fading effect of conventional passive RIS-aided systems. Each reflecting element of active RISs is assisted by an amplifier such that the incident signal can be reflected and amplified instead of only being reflected as in passive RIS-aided systems. This work addresses the practical challenge that, on the one hand, in active RIS-aided systems the perfect individual channel state information (CSI) of the RIS-aided channels cannot be acquired due to the lack of signal processing power at the active RISs, but, on the other hand, this CSI is required to calculate the expected system data rate and RIS transmit power needed for transceiver design. To address this issue, we first derive closed-form expressions for the average achievable rate and the average RIS transmit power based on partial CSI of the RIS-aided channels. Then, we formulate an average achievable rate maximization problem for jointly optimizing the active beamforming at both the base station (BS) and the RIS. This problem is then tackled using the majorization–minimization (MM) algorithm framework, and, in each iteration low-complexity solutions for the BS and RIS beamforming are found based on the Karush-Kuhn-Tucker (KKT) conditions. To ensure the quality of service (QoS) of each user, we further formulate a rate outage constrained beamforming problem, which is solved using the Bernstein-Type inequality (BTI) and semidefinite relaxation (SDR) techniques. Numerical results show that the proposed algorithms can efficiently overcome the challenges imposed by imperfect CSI in active RIS-aided wireless systems.
CRIS-Team Scopus Importer:2023-06-16
Keywords: active RIS; beamforming; intelligent reflecting surface (IRS); partial channel state information (CSI); Reconfigurable intelligent surface (RIS)

A General MIMO Framework for NOMA Downlink and Uplink Transmission Based on Signal Alignment - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Wireless Communications, 2016)
The application of multiple-input multiple-output (MIMO) techniques to nonorthogonal multiple access (NOMA) systems is important to enhance the performance gains of NOMA. In this paper, a novel MIMO-NOMA framework for downlink and uplink transmission is proposed by applying the concept of signal alignment. By using stochastic geometry, closed-form analytical results are developed to facilitate the performance evaluation of the proposed framework for randomly deployed users and interferers. The impact of different power allocation strategies, namely fixed power allocation and cognitive radio inspired power allocation, on the performance of MIMO-NOMA is also investigated. Computer simulation results are provided to demonstrate the performance of the proposed framework and the accuracy of the developed analytical results.<br
Keywords: Base stations; Interference; Resource management; Downlink; MIMO; Antennas; Uplink

Age of Information: Can CR-NOMA Help? - Ding, Zhiguo; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2023)
The aim of this paper is to exploit cognitive-radio inspired NOMA (CR-NOMA) transmission to reduce the age of information in wireless networks. In particular, two CR-NOMA transmission protocols are developed by utilizing the key features of different data generation models and applying CR-NOMA as an add-on to a legacy orthogonal multiple access (OMA) based network. The fact that the implementation of CR-NOMA causes little disruption to the legacy OMA network means that the proposed CR-NOMA protocols can be practically implemented in various communication systems which are based on OMA. Closed-form expressions for the AoI achieved by the proposed NOMA protocols are developed to facilitate performance evaluation, and asymptotic studies are carried out to identify two benefits of using NOMA to reduce the AoI in wireless networks. One is that the use of NOMA provides users more opportunities to transmit, which means that the users can update their base station more frequently. The other is that the use of NOMA can reduce access delay, i.e., the users are scheduled to transmit earlier than in the OMA case, which is useful to improve the freshness of the data available in the wireless network.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Base stations; Data models; NOMA; Protocols; Signal to noise ratio; Time division multiple access; Wireless networks

Aggregate Preamble Sequence Design and Detection for Massive IoT with Deep Learning - Mostafa, Ahmed Elhamy; Wong, Vincent W.S.; Zhou, Yong; Schober, Robert; Luo, Zhe; Liao, Shuri; Ding, Mengying (IEEE Transactions on Vehicular Technology, 2021)
Massive Internet of Things (mIoT) is a major use case of the fifth generation (5G) wireless systems. mIoT aims to support a large number of connection requests from the IoT devices. However, the conventional Long Term Evolution (LTE) random access procedure hinders the support of mIoT due to the limited number of available preambles. In this paper, we propose to aggregate two Zadoff-Chu preamble sequences from two different roots to obtain a larger set of preambles by considering all possible combinations of preamble sequence pairs. Decoding the aggregate preambles is challenging because the receiver needs to decode two preamble sequences where each one is allocated half of the transmit power. We propose two receiver architectures for preamble decoding. The first one is a threshold-based receiver which only requires minor changes to the LTE preamble receiver architecture. The second proposed preamble decoder architecture exploits a deep neural network. Simulations show that the proposed aggregate preamble design results in a lower service time for backlogged IoT devices compared to existing collision avoidance techniques. Moreover, the proposed receiver architectures can decode the aggregate preambles with low probabilities of misdetection and false alarms (less than 11%), especially in the high signal-to-noise ratio (SNR) regime.
CRIS-Team Scopus Importer:2021-03-26
Keywords: 5G mobile communication; Aggregates; deep neural networks; Internet of Things; Long Term Evolution; Massive Internet of Things (mIoT); preamble sequence design; Radio transmitters; random access; Receivers; Signal to noise ratio

Aggregate Preamble Sequence Design for Massive Machine-Type Communications in 5G Networks - Mostafa, Ahmed Elhamy; Wong, Vincent W.S.; Liao, Shuri; Schober, Robert; Ding, Mengying; Wang, Fan (2018 IEEE Global Communications Conference, GLOBECOM 2018 - Proceedings, 2019)
Massive machine-type communications (mMTC) is a major use case in the fifth generation (5G) wireless networks. mMTC aims at supporting a large number of Internet of Things (IoT) connections within a coverage area. The current random access procedure in the Long Term Evolution (LTE) networks may not be able to handle a large number of simultaneous connection requests due to the limited number of random access preambles. Hence, it is essential to modify the random access procedure to support mMTC. In this paper, we propose a new preamble sequence design in which two Zadoff-Chu preamble sequences are aggregated together. This design enables us to have a larger set of random access preambles consisting of all combinations of pairing two Zadoff-Chu preamble sequences. Moreover, we consider a subset of all combinations that satisfy a certain maximum peak-to-average-power-ratio (PAPR) threshold criterion to reduce the energy consumption of the IoT devices. The proposed design requires only minor changes in the conventional transmitter and receiver design for generating and decoding the aggregated preamble sequences, respectively. Results show that the proposed design reduces the probability of preamble collision to less than 10--4, which is lower than LTE. Furthermore, it outperforms other collision avoidance techniques such as access class barring (ACB) in terms of a lower average total service time. The modified receiver detects the aggregated preambles successfully and avoids detecting false preambles. Both the probabilities of misdetection and false alarm are less than 10--3 when the signal-to-noise ratio (SNR) is larger than-7 dB.
CRIS-Team Scopus Importer:2019-05-02

AlexNet Classifier and Support Vector Regressor for Scheduling and Power Control in Multimedia Heterogeneous Networks - Zarini, Hosein; Khalili, Ata; Tabassum, Hina; Rasti, Mehdi; Saad, Walid (IEEE Transactions on Mobile Computing, 2023)
In this paper, the downlink transmission of a two-tier heterogeneous network (HetNet) is considered in which a macro base station (MBS) serves the macro users using orthogonal frequency division multiple access (OFDMA) and small base stations (SBSs) serve the small-cell users through multi-carrier non-orthogonal multiple access (MC-NOMA) and joint transmission (JT). In particular, assuming the subcarriers are already allocated to macro users, the problem of scheduling (i.e., joint user association and subcarrier allocation) and power control is studied with the goal of maximizing the total users' perceived quality-of -experience (QoE) for small-cell users, while a minimum data rate for macro users is guaranteed. To solve the joint optimization problem, a near-optimal and computationally efficient two-phase solution approach is proposed based on the tools from optimization and machine learning (ML). In the first phase, the optimization problem is solved to obtain the scheduling decisions and transmit power variables. In the second phase, the optimized scheduling decisions and transmit power variables serve as training samples for an AlexNet classifier and support vector regressor (SVR), respectively. Simulation results reveal that the integration of JT into MC-NOMA, outperforms the conventional MC-NOMA scheme by up to 24%, 19%, and 21% for the web, video and audio multimedia services, respectively. Compared to a conventional convolutional neural network, our results demonstrate that for the web, video, and audio-services, AlexNet increases the scheduling prediction accuracy up to 14%, 11%, and 17%, while SVR increases the power prediction accuracy up to 8%, 7%, and 12%, respectively.
CRIS-Team Scopus Importer:2023-04-28
Keywords: AlexNet; Heterogeneous network (HetNet); joint transmission (JT); multi-carrier non-orthogonal multiple access (MC-NOMA); quality of experience (QoE); support vector regressor (SVR)

A Low-Complexity Algorithmic Framework for Large-Scale IRS-Assisted Wireless Systems - Ma, Yifan; Shen, Yifei; Yu, Xianghao; Zhang, Jun; Song, S. H.; Letaief, Khaled B. (2020 IEEE Globecom Workshops, GC Wkshps 2020 - Proceedings, 2020)
Intelligent reflecting surfaces (IRSs) are revolutionary enablers for next-generation wireless communication networks, with the ability to customize the radio propagation environment. To fully exploit the potential of IRS-assisted wireless systems, reflective elements have to be jointly optimized with conventional communication techniques. However, the resulting optimization problems pose significant algorithmic challenges, mainly due to the large-scale non-convex constraints induced by the passive hardware implementations. In this paper, we propose a low-complexity algorithmic framework incorporating alternating optimization and gradient-based methods for largescale IRS-assisted wireless systems. The proposed algorithm provably converges to a stationary point of the optimization problem. Extensive simulation results demonstrate that the proposed framework provides significant speedups compared with existing algorithms, while achieving a comparable or better performance.
CRIS-Team Scopus Importer:2021-04-19

A low-complexity linear precoding and power allocation scheme for downlink massive MIMO systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2013 Asilomar Conference on Signals, Systems and Computers, 2014)
In this paper, we present a low-complexity linear precoding and power allocation scheme for downlink massive multiple-input multiple-output (MIMO) systems. The optimization criteria adopted for the proposed precoding and power allocation scheme are maximization of the sum rate and maximization of the minimum user rate, respectively. The presented precoder is based on a matrix polynomial and can closely approach the sum rate and the minimum user rate of the optimal regularized zero forcing (RZF) precoder, which requires a matrix inversion, and performs substantially better than the simple conjugate beamforming (BF) precoder. Our simulation results show that the proposed precoding scheme with a low order matrix polynomial can approach the sum rate and the minimum user rate of the optimal RZF precoder. We also present analytical results for the asymptotic sum rate and the asymptotic minimum user rat

A Minimum Error Probability NOMA Design - Wang, Yuan; Wang, Jiaheng; Ng, Derrick Wing Kwan; Schober, Robert; Gao, Xiqi (IEEE Transactions on Wireless Communications, 2021)
Non-orthogonal multiple access (NOMA) enables massive connectivity and achieves high spectral efficiency. The vast majority of the NOMA literature has adopted the ideal information rate as performance metric assuming perfect successive interference cancellation (SIC) without any error propagation, which, however, may lead to NOMA designs adverse to SIC. In this paper, we take into account imperfect SIC and practical modulation schemes for power-domain NOMA design. To characterize the error propagation, we derive the bit error rates (BERs) of the users for arbitrary-order quadrature amplitude modulation (QAM) schemes. Then, we propose a minimum error probability NOMA (MEP-NOMA) design, minimizing the average BER of the users via power allocation. Considering the complicated error probability expressions of the MEP-NOMA design, we derive lower and upper bounds on the average BER, based on which a simple closed-form power allocation is obtained. We show that the proposed power allocation minimizes both the lower and upper bounds on the average BER for a sufficiently large power budget and provides near-optimal error performance. On this basis, we theoretically prove the superiority of MEP-NOMA over existing OMA and NOMA schemes in terms of error performance. Comprehensive numerical results are provided to verify the accuracy of the error probability analysis of the considered practical NOMA scheme with imperfect SIC and to demonstrate the efficacy of the proposed MEP-NOMA design.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Error propagation; imperfect successive interference cancellation; minimum error probability; non-orthogonal multiple access; power allocation; quadrature amplitude modulation

A Molecular Communication Testbed Based on Proton Pumping Bacteria: Methods and Data - Grebenstein, Laura; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Fischer, Georg; Weigel, Robert; Burkovski, Andreas; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2019)
This paper presents a detailed description of a recent biological molecular communication (MC) testbed and provides a set of experimental measurement data. In particular, the MC testbed is realized using Escherichia coli (E. coli) bacteria that express the light-driven proton pump gloeorhodopsin (GR) from Gloeobacter violaceus (G. violaceus). Upon an external light stimulus, these bacteria (as the transmitter) export protons (as the signaling molecules) into the channel. This changes the pH level of the environment, which can be detected with a pH sensor (as the receiver). To facilitate future advancement in the experimentation of MC systems, in this paper, we explain the methodology used for the development of our testbed and discuss the reasoning behind the choices made throughout its evolution. Moreover, we provide different categories of measurement data obtained with the testbed. The data set is expected to facilitate and promote the experimental evaluation of communication schemes developed by the MC community.
CRIS-Team Scopus Importer:2021-04-20

Amplify-and-Forward Relaying in Two-Hop Diffusion-Based Molecular Communication Networks - Ahmadzadeh, Arman; Noel, Adam; Burkovski, Andreas; Schober, Robert (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
This paper studies a three-node network in which an intermediate nano-transceiver, acting as a relay, is placed between a nano-transmitter and a nano-receiver to improve the range of diffusion- based molecular communication. Motivated by the relaying protocols used in traditional wireless communication systems, we study amplify-and- forward (AF) relaying with fixed and variable amplification factor for use in molecular communication systems. To this end, we derive a closed-form expression for the expected end-to-end error probability. Furthermore, we derive a closed-form expression for the optimal amplification factor at the relay node for minimization of an approximation of the expected error probability of the network. Our analytical and simulation results show the potential of AF relaying to improve the overall performance of nano-networks.<br
Keywords: Relays; Error probability; Protocols; Molecular communication; Closed-form solutions; Numerical models; Microorganisms

An achievable rate of large block-fading MIMO systems with no CSI via successive decoding - Müller, Ralf; Takeuchi, Keigo; Vehkaperä, Mikko; Tanaka, Toshiyuki (2010 20th International Symposium on Information Theory and Its Applications, ISITA 2010 and the 2010 20th International Symposium on Spread Spectrum Techniques and Applications, ISSSTA 2010, 2010)
A Rayleigh block-fading multiple-input multiple-output (MIMO) channel with channel state information (CSI) available neither to the transmitter nor to the receiver is considered. A lower bound on the capacity is formulated based on a successive decoding (SD) scheme. An analytical expression of the lower bound is derived in the large-system limit, by using the replica method. Furthermore, the achievable rate of the linear minimum mean-squared error (LMMSE) receiver with SD is also evaluated in the large-system limit. The lower bound is superior to the lower bound derived by Hassibi and Hochwald for all signal-to-noise ratios (SNRs). © 2010 IEEE.
Keywords: Channel estimation; Receivers; Signal to noise Ratio; Covariance Matrix; MIMO; Detectors; Equations

An Adaptive Bayesian Framework for Recovery of Sources with Structured Sparsity - Bereyhi, Ali; Müller, Ralf (2019 IEEE 8TH INTERNATIONAL WORKSHOP ON COMPUTATIONAL ADVANCES IN MULTI-SENSOR ADAPTIVE PROCESSING (CAMSAP 2019), 2019)
CRIS-Team WoS Importer:2020-08-21

Analysis and Design of Secure Massive MIMO Systems in the Presence of Hardware Impairments - Zhu, Jun; Wing Kwan Ng, Derrick; Wang, Ning; Schober, Robert; Bhargava, Vijay Kishore (IEEE Transactions on Wireless Communications, 2017)
To keep the hardware costs of future communications systems manageable, the use of low-cost hardware components is desirable. This is particularly true for the emerging massive multiple-input multiple-output (MIMO) systems which equip base stations (BSs) with a large number of antenna elements. However, low-cost transceiver designs will further accentuate the hardware impairments, which are present in any practical communication system. In this paper, we investigate the impact of hardware impairments on the secrecy performance of downlink massive MIMO systems in the presence of a passive multiple-antenna eavesdropper. Thereby, for the BS and the legitimate users, the joint effects of multiplicative phase noise, additive distortion noise, and amplified receiver noise are taken into account, whereas the eavesdropper is assumed to employ ideal hardware. We derive a lower bound for the ergodic secrecy rate of a given user when matched filter data precoding and artificial noise (AN) transmission are employed at the BS. Based on the derived analytical expression, we investigate the impact of the various system parameters on the secrecy rate and optimize both the pilot sets used for uplink training and the AN precoding. Our analytical and simulation results reveal that: 1) the additive distortion noise at the BS may be beneficial for the secrecy performance, especially if the power assigned for AN emission is not sufficient; 2) all other hardware impairments have a negative impact on the secrecy performance; 3) despite their susceptibility to pilot interference in the presence of phase noise, so-called spatially orthogonal pilot sequences are preferable unless the phase noise is very strong; and 4) the proposed generalized null-space AN precoding method can efficiently mitigate the negative effects of phase noise.<br
Keywords: MIMO; Phase noise; Hardware; Distortion; Precoding; Additives; Physical layer

Analysis and design of two-hop diffusion-based molecular communication networks - Ahmadzadeh, Arman; Noel, Adam; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
In this paper, we consider a two-hop molecular communication network consisting of one nanotransmitter, one nanoreceiver, and one nanotransceiver acting as a relay. We consider two different schemes for relaying to improve the range of diffusion-based molecular communication. In the first scheme, two different types of messenger molecules are utilized at the relay node for transmission and detection. In the second scheme, we assume that there is only one type of molecule available to be used as an information carrier. We identify self-interference as the performance-limiting effect for the second relaying scheme. Self-interference occurs when the relay must detect the same type of molecule that it also emits. Furthermore, we consider two relaying modes analogous to those used in wireless communication systems, i.e., full-duplex and half-duplex. In particular, while our main focus is on full-duplex relaying, half-duplex relaying is employed as a means to mitigate self-interference. In addition, we propose the adaptation of the decision threshold as an effective mechanism to mitigate self-interference at the relay for full-duplex transmission. We derive closed-form expressions for the expected error probability of the network for both considered relaying schemes.<br
Keywords: Relays; Error probability; Nanobioscience; Random variables; Protocols; Numerical models

Analysis and Optimization of RIS-Aided Massive MIMO with ZF Detectors and Imperfect CSI - Zhi, Kangda; Pan, Cunhua; Zhou, Gui; Ren, Hong; Elkashlan, Maged; Schober, Robert (IEEE International Conference on Communications, 2022)
This paper analyzes and optimizes the reconfigurable intelligent surface (RIS)-aided massive multiple-input multiple-output (MIMO) systems with zero-forcing (ZF) detectors under imperfect channel state information (CSI). We first propose a low-overhead minimum mean square error (MMSE) channel estimator, and then derive and analyze closed-form expressions for the uplink achievable rate. Our analytical results prove that: 1) regardless of the RIS phase shift design, the rate of all users scales at least on the order of mathcalOleft( log _2(MN) right), where M and N are the numbers of antennas and reflecting elements, respectively; 2) by aligning the RIS phase shifts to one user, the rate of this user can at most scale on the order of mathcalOleft( log _2(MN) right). Furthermore, we propose a low-complexity majorization-minimization (MM)-based algorithm to optimize the sum user rate, where closed-form solutions are obtained in each iteration. Finally, simulation results validate all derived analytical results. Our simulation results also show that the maximum sum rate can be closely approached by simply aligning the RIS phase shifts to an arbitrary user.
CRIS-Team Scopus Importer:2022-09-16
Keywords: imperfect CSI; intelligent reflecting surface (IRS); majorization-minimization (MM); massive MIMO; Reconfigurable intelligent surface (RIS); ZF

Analysis of blind pilot decontamination - Müller, Ralf; Vehkaperä, Mikko; Cottatellucci, Laura (2013 47th Asilomar Conference on Signals, Systems and Computers, 2013)
A nonlinear channel estimation scheme proposed by the authors in earlier work is shown to overcome the pilot contamination problem in massive multiple-input multiple-output (MIMO) systems. The method is based on a subspace projection using a singular value decomposition and is studied both by analytical and simulative means. The analysis presented in this paper is a refined version of an earlier work by the same authors. In addition, simulations based on a cellular network model show that the benefits of the proposed scheme are retained also in more realistic settings. © 2013 IEEE.
Keywords: channel estimation; massive MIMO; Multiple antennas; multiple-input multiple-output (MIMO) systems; principal component analysis; random matrix theory

Analysis of Coverage in Heterogeneous Cellular Networks - Lee, Woongsup; Schober, Robert (IEEE Communications Letters, 2016)
In this letter, we study the coverage of base stations (BSs) in heterogeneous cellular networks, where BSs with different transmit powers are randomly deployed. Specifically, the boundary of coverage is formulated analytically as the intersection of circles when a multiplicative bias is applied for BS association. Moreover, the effect of the transmit power and the path loss exponent on the coverage is investigated. Furthermore, for femto BSs with low transmit powers which are deployed to offload the traffic of the cellular system, it is shown that the expected number of offloaded users is concave with respect to the transmit power. Finally, the coverage of BSs is evaluated through simulations, which verify the accuracy of the presented analysis.<br
Keywords: Mobile communication; Analytical models; MIMO; Base stations; Received signal strength indicator; Propagation losses; Indexes

Analysis of large MIMO DS-CDMA systems with imperfect CSI and spatial correlation - Vehkaperä, Mikko; Takeuchi, Keigo; Müller, Ralf; Tanaka, Toshiyuki (2010 IEEE International Symposium on Information Theory, ISIT 2010, 2010)
The large system analysis of randomly spread MIMO DS-CDMA systems is provided. Correlated Rayleigh fading MIMO channels are assumed for all users. Linear multiuser detection with separate decoding and pilot-aided channel estimation are used. The results imply that with channel estimation, the performance can improve significantly as the correlation between the transmit antennas increases. No channel information at the transmitter is required, but the channel estimator needs knowlegde of the long term transmit correlation in advance. The numerical results demonstrate that in a 4 × 4 MIMO DS-CDMA system with two users per chip, high antenna correlation at the transmitter can double the ergodic spectral efficiency compared to the case of uncorrelated transmit antennas. © 2010 IEEE.
Keywords: MIMO; Multiaccess communication; Transmitting antennas; Multiuser detection; Channel estimation; Informatics; Fading; Decoding; Transmitters; Physics

Analysis of MC Systems Employing Receivers Covered by Heterogeneous Receptors - Huang, Xinyu; Fang, Yuting; Johnston, Stuart T.; Faria, Matthew; Yang, Nan; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
This paper investigates the channel impulse response (CIR), i.e., the molecule hitting rate, of a molecular communication (MC) system employing an absorbing receiver (RX) covered by multiple non-overlapping receptors. In this system, receptors are heterogeneous, i.e., they may have different sizes and arbitrary locations. Furthermore, we consider two types of transmitter (TX), namely a point TX and a membrane fusion (MF)-based spherical TX. We assume the point TX or the center of the MF-based TX has a fixed distance to the center of the RX. Given this fixed distance, the TX can be at different locations and the CIR of the RX depends on the exact location of the TX. By averaging over all possible TX locations, we analyze the expected molecule hitting rate at the RX as a function of the sizes and locations of the receptors, where we assume molecule degradation may occur during the propagation of the signaling molecules. Notably, our analysis is valid for different numbers, a wide range of sizes, and arbitrary locations of the receptors, and its accuracy is confirmed via particle-based simulations. Exploiting our numerical results, we show that the expected number of absorbed molecules at the RX increases with the number of receptors, when the total area on the RX surface covered by receptors is fixed. Based on the derived analytical expressions, we compare different geometric receptor distributions by examining the expected number of absorbed molecules at the RX. We show that evenly distributed receptors result in a larger number of absorbed molecules than other distributions. We further compare three models that combine different types of TXs and RXs. Compared to the ideal model with a point TX and a fully absorbing RX, the practical model with an MF-based TX and an RX with heterogeneous receptors yields a lower peak CIR, suffers from more severe inter-symbol interference, and gives rise to a higher average bit error rate (BER). This underlines the importance of our analysis of practical TX-RX models since the existing CIR and BER analyses based on the ideal model do not reflect the performance achievable in practice. Numerical results show that different vesicle generation rate results in the same number of molecules harvested by the TX, but a different peak received signal at the RX.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Analytical models; Bit error rate; Cells (biology); channel impulse response; Error probability; heterogeneous receptors; Molecular communications; Numerical models; Receivers; spherical transmitter; Transmitters

Analysis of Neural Image Compression Networks for Machine-to-Machine Communication - Fischer, Kristian; Forsch, Christian; Herglotz, Christian; Kaup, André (IEEE International Conference on Image Processing (ICIP), 2021)
Video and image coding for machines (VCM) is an emerging field that aims to develop compression methods resulting in optimal bitstreams when the decoded frames are analyzed by a neural network. Several approaches already exist improving classic hybrid codecs for this task. However, neural compression networks (NCNs) have made an enormous progress in coding images over the last years. Thus, it is reasonable to consider such NCNs, when the information sink at the decoder side is a neural network as well. Therefore, we build-up an evaluation framework analyzing the performance of four state-of-the-art NCNs, when a Mask R-CNN is segmenting objects from the decoded image. The compression performance is measured by the weighted average precision for the Cityscapes dataset. Based on that analysis, we find that networks with leaky ReLU as non-linearity and training with SSIM as distortion criteria results in the highest coding gains for the VCM task. Furthermore, it is shown that the GAN-based NCN architecture achieves the best coding performance and even out-performs the recently standardized Versatile Video Coding (VVC) for the given scenari
Keywords: Neural Compression Networks; Video Coding for Machines; Machine-to-Machine Communication

Analysis of pilot decontamination based on power control - Cottatellucci, Laura; Müller, Ralf; Vehkapera, Mikko (2013 IEEE 77th Vehicular Technology Conference, VTC Spring 2013, 2013)
A subspace method for channel estimation is proposed for asymmetric antenna array systems. The so-called pilot contamination problem reported in [1] is found to be due to the linearity of channel estimation in [2]. We show that it does not occur in cellular systems with power control and power-controlled handoff when the nonlinear channel estimation method proposed in this paper is used. Power-control hand-off is needed to guarantee separability between signal and interference subspaces. We derive the transmission conditions for subspace separability based on free probability and perturbation theory. © 2013 IEE
Keywords: Channel estimation; Massive MIMO; Multiple antennas; Multiple-input multiple-output (MIMO) systems; Principal component analysis; Spread-spectrum

Analysis of Receiver Covered by Heterogeneous Receptors in Molecular Communications - Huang, Xinyu; Fang, Yuting; Johnston, Stuart T.; Faria, Matthew; Yang, Nan; Schober, Robert (IEEE International Conference on Communications, 2022)
This paper analyzes the channel impulse response of an absorbing receiver (RX) covered by multiple non-overlapping heterogeneous receptors with different sizes and arbitrary locations in a molecular communication system. In this system, a point transmitter (TX) is assumed to be uniformly located on a virtual sphere at a fixed distance from the RX. Considering molecule degradation during the propagation from the TX to the RX, the expected molecule hitting rate at the RX over varying locations of the TX is analyzed as a function of the size and location of each receptor. Notably, this analytical result is applicable for different numbers, sizes, and locations of receptors, and its accuracy is demonstrated via particle-based simulations. Numerical results show that (i) the expected number of absorbed molecules at the RX increases with an increasing number of receptors, when the total area of receptors on the RX surface is fixed, and (ii) evenly distributed receptors lead to the largest expected number of absorbed molecules.
CRIS-Team Scopus Importer:2022-09-16
Keywords: channel modeling; location of receptors; Molecular communication; size of receptors

Analysis of Sparse Recovery Algorithms via the Replica Method - Bereyhi, Ali; Müller, Ralf; Schulz-Baldes, Hermann (Compressed Sensing in Information Processing, 2022)
This chapter goes through the fundamental connections between statistical mechanics and estimation theory by focusing on the particular problem of compressive sensing. We first show that the asymptotic analysis of a sparse recovery algorithm is mathematically equivalent to the problem of calculating the free energy of a spin glass in the thermodynamic limit. We then use the replica method from statistical mechanics to evaluate the performance in the asymptotic regime. The asymptotic results have several applications in communications and signal processing. We briefly go through two instances of these applications: Characterization of joint sparse recovery algorithms used in distributed compressive sensing and tuning of receivers employed for detection of spatially modulated signals.
CRIS-Team Scopus Importer:2022-11-04

Analysis of the behavior of electric vehicle charging stations with renewable generations - Lee, William; Xiang, Lin; Schober, Robert; Wong, Vincent W.S. (2013 IEEE International Conference on Smart Grid Communications, SmartGridComm 2013, 2013)
In this paper, we study the competitive interactions between electric vehicle charging stations (EVCSs) with renewable electricity generation facilities (REGFs). As electric vehicles (EVs) become more popular, there will be a competition between neighboring EVCSs to attract more EVs. Therefore, an EVCS is likely to set its electricity price by taking into account the competition with neighboring EVCSs, such that its revenue is maximized. We model the competitive interactions between EVCSs by using game theory. In this paper, we show that the game played by EVCSs is a supermodular game and there exists a unique pure Nash equilibrium for best response algorithms with arbitrary initial policy. Simulation results confirm the convergence of the game between EVCSs. The results also verify that it is beneficial for both EVs and EVCSs to have REGFs and all EVCSs will have REGFs in the long run. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Analysis of THz Communications in the Finite Blocklength Regime - Schram, Viktoria; Gerstacker, Wolfgang (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2019)
The theory of finite blocklength coding provides powerful tools to approximate the maximum achievable rate for short blocklength coding. In this work, the normal approximation is applied for the transmission over the THz channel assuming a point-to-point single-carrier system. Here, a transmission with bit interleaved coded modulation (BICM) is assumed and compared to coded modulation (CM). The performance is analysed for higher order modulations considering PSK and QAM. These results are verified by simulations, considering terminated convolutional codes with different coding rates, minimum mean-squared error linear equalization (MMSE-LE) and soft decision decoding. Our simulation results show that a rate of about 100 Gbps is achievable for 32QAM with a blocklength of 100 and a bit error rate of 10-3.
CRIS-Team Scopus Importer:2019-09-27
Keywords: BICM; finite blocklength; MMSE-LE; normal approximation; THz

Analytical Models for Particle Diffusion and Flow in a Horizontal Cylinder with a Vertical Force - Schäfer, Maximilian; Wicke, Wayan; Rabenstein, Rudolf; Schober, Robert (IEEE International Conference on Communications (ICC), 2019)
This paper considers particle propagation in a cylindrical molecular communication channel, e.g. a simplified model of a blood vessel. Emitted particles are influenced by diffusion, flow, and a vertical force induced e.g. by gravity or magnetism. The dynamics of the diffusion process are modeled by multi-dimensional transfer functions in a spatio-temporal frequency domain. Realistic boundary conditions are incorporated by the design of a feedback loop. The result is a discrete-time semi-analytical model for the particle concentration in the channel. The model is validated by comparison to particle-based simulations. These numerical experiments reveal that the particle concentration of the proposed semi-analytical model and the particle-based model are in excellent agreement. The analytical form of the proposed solution provides several benefits over purely numerical models, e.g. high variability, existence of low run-time algorithms, extendability to several kinds of boundary conditions, and analytical connection to parameters from communication theor
Keywords: Numerical models; Eigenvalues and eigenfunctions; Boundary conditions; Diffusion processes; Receivers; Transfer functions; Magnetic forces

An Analysis of Price Competition in Heterogeneous Electric Vehicle Charging Stations - Lee, Woongsup; Schober, Robert; Wong, Vincent W.S. (IEEE Transactions on Smart Grid, 2019)
In this paper, we investigate the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). Both a large-sized EVCS (L-EVCS) and small-sized EVCSs (S-EVCSs), which have different capacities, are considered. Moreover, the price elasticity of electric vehicles (EVs), the effect of the distance between an EV and the EVCSs, and the impact of the number and type of charging outlets at the EVCSs on the behavior of EVs are taken into account. The electricity demand of the EVCSs is modeled and analyzed using a multiplicatively weighted Voronoi diagram. The price competition between EVCSs is studied by using a Stackelberg game and the electricity price is determined. Through simulations, the correctness of our analysis is validated and the payoff of the EVCSs is examined for various environments. Our results reveal that although the payoff of the EVCSs is generally small, it is higher than when the electricity from the RPGs is directly sold to the power grid. We also find that the payoff of the EVCSs is significantly affected by the elasticity of the electricity demand of the EVs. Furthermore, the payoff of the L-EVCS is inversely proportional to that of the S-EVCSs.
CRIS-Team Scopus Importer:2019-07-02
Keywords: electric vehicle; Electric vehicle charging station; pricing; renewable power generation; Voronoi diagram

An Analysis of Price Competition in Heterogeneous Electric Vehicle Charging Stations - Lee, Woongsup; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Smart Grid, 2018)
In this paper, we investigate the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). Both a large-sized EVCS (L-EVCS) and small-sized EVCSs (S-EVCSs), which have different capacities, are considered. Moreover, the price elasticity of electric vehicles (EVs), the effect of the distance between an EV and the EVCSs, and the impact of the number and type of charging outlets at the EVCSs on the behavior of EVs are taken into account. The electricity demand of the EVCSs is modeled and analyzed using a multiplicatively weighted Voronoi diagram. The price competition between EVCSs is studied by using a Stackelberg game and the electricity price is determined. Through simulations, the correctness of our analysis is validated and the payoff of the EVCSs is examined for various environments. Our results reveal that although the payoff of the EVCSs is generally small, it is higher than when the electricity from the RPGs is directly sold to the power grid. We also find that the payoff of the EVCSs is significantly affected by the elasticity of the electricity demand of the EVs. Furthermore, the payoff of the L-EVCS is inversely proportional to that of the S-EVCSs.<br
Keywords: Elasticity; Games; Electric vehicle charging; Plugs; Analytical models; Power grids; Pricing

An End-to-End Deep Learning Framework for Wideband Signal Recognition - Vagollari, Adela; Hirschbeck, Martin; Gerstacker, Wolfgang (IEEE Access, 2023)
Successful management of the radio spectrum requires, as a first step, detailed information about spectrum occupancy. In this work, we present an end-to-end deep learning (DL) based framework to obtain information from wide spectrum bands through signal detection, localization, and modulation classification. By visually representing the radio signals in spectrograms, we formulate the wideband detection problem as an object detection task from the computer vision field. To this end, the proposed framework consists of two cascaded modules: an object detection network repurposed to detect and classify distinctive signals in wideband spectrograms, and a convolutional neural network (CNN) designed to extend the classification capabilities to support a wide range of analog and digital modulation schemes. To evaluate our framework, we use a public wideband recognition dataset, which we carefully analyze and curate through a series of preprocessing techniques. To tackle the challenges of insufficient training data and class imbalance observed in the dataset, we suggest a training strategy that includes data mixing and transfer learning. Our experimental results on a general test set demonstrate that the proposed approach can detect and classify a variety of narrowband signals with simultaneously high precision (77.1%), recall (81.8%), and localization accuracy, as indicated by an average Intersection over Union (IoU) of 86%.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Automatic modulation classification; Detectors; Location awareness; Modulation; Narrowband; Radio frequency; RF spectrum monitoring; Spectrogram; spectrum sensing; Wideband; wideband recognition dataset; wideband signal detection; YOLO object detector

A new class of distributed space-time trellis codes - Yiu, S.; Schober, Robert (2006 International Waveform Diversity and Design Conference, WDD 2006 - Proceedings, 2018)
In this paper, we develop a new class of distributed space-time trellis codes (DSTTCs). These DSTTCs are designed for wireless networks which have a large set of nodes N but at any given time only a small, a priori unknown subset of nodes S -N can be active. Each node is equipped with a unique signature vector but all active nodes use the same STTC for encoding. Efficient methods for the optimization of the set of signature vectors are provided and it is shown that existing full-rank STTCs designed for Nc ≥ 2 co-located antennas are favorable choices for the trellis encoding. If properly designed, the proposed DSTTCs achieve a diversity order of d = minNc, NS if NS nodes are active. Furthermore, the decoding complexity of the proposed DSTTCs is independent of the number of nodes and identical to that of the underlying STTC. Simulation results show the superior performance of the novel DSTTC compared to distributed space-time filtering.
CRIS-Team Scopus Importer:2020-01-31

A new class of nonlinear precoders for hardware efficient massive MIMO systems - Sedaghat, Mohammad Ali; Bereyhi, Ali; Müller, Ralf (A New Class of Nonlinear Precoders for Hardware Efficient Massive MIMO Systems, 2017)
A general class of nonlinear Least Square Error (LSE) precoders in multi-user multiple-input multiple-output systems is analyzed using the replica method from statistical mechanics. A single cell downlink channel with N transmit antennas at the base station and K single-antenna users is considered. The data symbols are assumed to be i.i.d. Gaussian and the precoded symbols on each transmit antenna are restricted to be chosen from a predefined set X. The set X encloses several well-known constraints in wireless communications including signals with peak power, constant envelope signals and finite constellations such as Phase Shift Keying (PSK). We determine the asymptotic distortion of the LSE precoder under both the Replica Symmetry (RS) and the one step Replica Symmetry Breaking (1-RSB) assumptions. For the case of peak power constraint on each transmit antenna, our analyses under the RS assumption show that the LSE precoder can reduce the peak to average power ratio to 3 dB without any significant performance loss. For PSK constellations, as N/K grows, the RS assumption fails to predict the performance accurately and therefore, investigations under the 1-RSB assumption are further considered. The results show that the 1-RSB assumption is more accurate.
Keywords: MIMO precoding; MIMO; Replica method

A New Off-grid Channel Estimation Method with Sparse Bayesian Learning for OTFS Systems - Wei, Zhiqiang; Yuan, Weijie; Lit, Shuangyang; Yuant, Jinhong; Ngt, Derrick Wing Kwan (2021 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2021)
CRIS-Team WoS Importer:2022-05-27

A New QoS-Guarantee Strategy for NOMA Assisted Semi-Grant-Free Transmission - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Communications, 2021)
Semi-grant-free (SGF) transmission has recently received significant attention due to its capability to accommodate massive connectivity and reduce access delay by admitting grant-free users to channels that would otherwise be solely occupied by grant-based users. In this paper, a new SGF transmission scheme that exploits the flexibility in choosing the decoding order in non-orthogonal multiple access (NOMA) is proposed. Compared to existing SGF schemes, this new scheme can ensure that admitting the grant-free users is completely transparent to the grant-based users, i.e., the grant-based users’ quality-of-service experience is guaranteed to be the same as for orthogonal multiple access. In addition, compared to existing SGF schemes, the proposed SGF scheme can significantly improve the robustness of the grant-free users’ transmissions and effectively avoid outage probability error floors. To facilitate the performance evaluation of the proposed SGF transmission scheme, an exact expression for the outage probability is obtained and an asymptotic analysis is conducted to show that the achievable multi-user diversity gain is proportional to the number of participating grant-free users. Computer simulation results demonstrate the performance of the proposed SGF transmission scheme and verify the accuracy of the developed analytical results.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Base stations; Interference; machine-type communications; NOMA; Non-orthogonal multiple access; Power system reliability; Probability; Quality of service; semi grant free transmission; Silicon carbide; successive interference cancellation (SIC) decoding order

A new signaling scheme for large DS-CDMA channels without CSI - Takeuchi, Keigo; Müller, Ralf; Vehkapera, Mikko; Tanaka, Toshiyuki (2009 7th International Symposium on Modeling and Optimization in Mobile, Ad Hoc and Wireless Networks, WiOpt 2009, 2009)
We propose a novel signaling scheme for wireless communication systems without channel state information (CSI). In that scheme, a bias of the occurrence probabilities of constellation points is utilized as pilot information known to the receiver, whereas pilot signals known to the receiver are sent in conventional pilot-based approaches. We evaluate the performance of the new scheme and conventional pilot-based schemes for a large direct-sequence code-division multiple-access (DS-CDMA) system, by using the replica method. It is shown that the new scheme outperforms the conventional pilot-based scheme when the amount of pilot information is large.
Keywords: Multiaccess communication; Iterative Decoding; Multiple access interference; Multiuser detection; Detectors; Channel estimation; Covariance matrix; Channel state Information; Computational complexity; Performance analysis

A new signal model for MIMO communication with compact parasitic arrays - Barousis, Vlasis I.; Papadias, Constantinos B.; Müller, Ralf (6th International Symposium on Communications, Control and Signal Processing, ISCCSP 2014, 2014)
Significant research effort has been drawn over the last few years to reduce the hardware complexity and size of Multiple Input - Multiple Output (MIMO) systems and to push this promising technology even to lightweight and small portable devices. Among other architectures, single-fed MIMO systems with compact parasitic arrays are a possible candidate toward this goal. To facilitate the study and design of parasitic arrays for MIMO applications, this paper presents an alternative signal model considering the currents at the ports of the transmitting array as the input to the system. Based on this model, a novel parasitic array is designed that is able to multiplex 16-QAM signals with the aid of a single radio-frequency (RF) source. The proposed signal model can also be useful for the evaluation of large parasitic arrays in massive MIMO regime, with significantly reduce hardware burden. © 2014 IEEE.
Keywords: ESPAR; MIMO; Parasitic arrays; single RF

An nD Model for a Cylindrical Diffusion-Advection Problem with an Orthogonal Force Component - Schäfer, Maximilian; Wicke, Wayan; Rabenstein, Rudolf; Schober, Robert (23rd International Conference on Digital Signal Processing (DSP), 2018)
This paper presents a physical and algorithmic model for a complex propagation problem in a long cylinder, resembling a blood vessel or a pipeline. Particles are diffusing in the cylinder driven by a plug flow, in addition the particles are attracted by an orthogonal force, e.g. due to magnetism or gravity. The dynamics of this propagation problem are modeled by multidimensional (nD) transfer functions. They are established by suitable functional transformations in a spatio-temporal frequency domain by exploiting eigenfunctions of partial differential operators. Nontrivial boundary conditions are incorporated by the design of a feedback loop. The result is a discrete-time semianalytical model for the particle concentration.<br

An Outphasing MIMO Architecture Prototype - Gäde, Bernhard; Erhardt, Stefan; Fischer, Georg; Müller, Ralf (European Microwave Week 2020, 2021)
In this manuscript we present the first prototype of an Outphasing MIMO Architecture (OMA). The concept of this architecture is to replace many linear power amplifiers by a single and simple power oscillator and phase modulate the carrier directly in the analogue domain. The prototype is designed to support Phase-Shift Keying on the Hypersphere (PSKH) modulation, which is a recent modulation scheme optimised for load-modulated Multiple Input Multiple Output (MIMO) transmitters. It is shown by analysis of the steady state and dynamic behaviour of the prototype that OMA is suitable to implement direct carrier modulated PSKH at rates up to 50 MSym/s using stock components only.<br
Keywords: direct carrier modulation; OMA; MIMO; PSKH

A Novel Antenna Placement Algorithm for Compressive Sensing MIMO Radar - Eisele, Bastian; Bereyhi, Ali; Ullmann, Ingrid; Müller, Ralf (2023 IEEE Radar Conference (RadarConf23), 2023)
In colocated compressive sensing MIMO radar, the measurement matrix is specified by antenna placement. To guarantee an acceptable recovery performance, this measurement matrix should satisfy certain properties, e.g., a small coherence. Prior work in the literature often employs randomized placement algorithms which optimize the prior distribution of antenna locations. The performance of these algorithms is suboptimal, as they can be easily enhanced via expurgation. In this paper, we suggest an iterative antenna placement algorithm which determines the antenna locations deterministically. The proposed algorithm locates jointly the antenna elements on the transmit and receive arrays, such that the coherence of the resulting measurement matrix is minimized. Numerical simulations demonstrate that the proposed algorithm outperforms significantly the benchmark, even after expurgatio
Keywords: Compressive sensing; MIMO radar; Antenna placement; coherence

A Novel Fast Antenna Selection Algorithm in Massive MIMO Systems - Asaad, Saba; Rabiei, Amir Masoud (2020)

A Novel Hybrid Analog-Digital Transmitter for Multi-antenna Base Stations - Sedaghat, Mohammad Ali; Gäde, Bernhard; Müller, Ralf; Fischer, Georg (2017)
A new hybrid Analog-Digital (hybrid A-D) precoder is proposed for multi-antenna base stations in massive Multiple-Input Multiple-Output (MIMO) which allows a trade-off between the number of required RF-chains and the update rate of the analog part. It is shown that the number of RF-chains can be reduced even below the number of eigenmodes of the channel, thereby closing the gap between the standard hybrid A-D and the single-RF MIMO. This is achieved by dividing the input data streams into blocks and jointly optimizing the digital and the analog precoder parts for each block. The analog part of the precoder needs to be updated once per block and remains static over each block interval. Out of band radiation due to switching is resolved by inserting a short guard interval between blocks. It is shown the number of RF-chains can be any arbitrary positive integer to obtain zero distortion at the user terminals if the update rate is high enough. The proposed precoder offers a significant performance gain at the expenses of data dependent precoding and higher update rates of the analog part.

A Novel ISAC Transmission Framework based on Spatially-Spread Orthogonal Time Frequency Space Modulation - Li, Shuangyang; Yuan, Weijie; Liu, Chang; Wei, Zhiqiang; Yuan, Jinhong; Bai, Baoming; Ng, Derrick Wing Kwan (IEEE Journal on Selected Areas in Communications, 2022)
In this paper, we propose a novel integrated sensing and communication (ISAC) transmission framework based on the spatially spread orthogonal time frequency space (SS-OTFS) modulation by considering the fact that communication channel strengths cannot be directly obtained from radar sensing. We first propose the concept of SS-OTFS modulation, where the key novelty is the angular domain discretization enabled by the spatial spreading/de-spreading. This discretization gives rise to simple and insightful effective models for both radar sensing and communication, which results in simplified designs for the related estimation and detection problems. In particular, we design simple beam tracking, angle estimation, and power allocation schemes for radar sensing, by utilizing the special structure of the effective radar sensing matrix. Meanwhile, we provide a detailed analysis on the pair-wise error probability (PEP) for communication, which unveils the key conditions for both precoding and power allocation designs for communication. Based on those conditions, we design a symbol-wise precoding scheme for communication based only on the delay, Doppler, and angle estimates from radar sensing, without the a priori knowledge of the communication channel fading coefficients, and also propose a suitable power allocation. Furthermore, we notice that radar sensing and communication requires different power allocations. Therefore, we discuss the performances of both the radar sensing and communication with different power allocations and show that the power allocation should be designed leaning towards radar sensing in practical scenarios. The effectiveness of the proposed ISAC transmission framework is verified by our numerical results, which also agree with our analysis and discussions.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Channel estimation; ISAC; Modulation; OTFS; performance analysis; power allocation; precoding design; Radar; Radar antennas; Radar cross-sections; Resource management; Sensors; SS-OTFS

A novel modulation scheme for user devices equipped with a single-RF MIMO transmitter. - Sedaghat, Mohammad Ali; Müller, Ralf (19th Int’l ITG Workshop on Smart Antennas, 2015)

A Novel Single-RF Outphasing MIMO Architecture - Gäde, Bernhard; Sedaghat, Mohammad Ali; Rachinger, Christoph; Fischer, Georg; Müller, Ralf (WSA 2017; 21th International ITG Workshop on Smart Antennas; Proceedings of, 2017)

A novel single RF-transmitter for massive MIMO - Sedaghat, Mohammad Ali; Müller, Ralf; Fischer, Georg (18th Int’l ITG Workshop on Smart Antennas, 2014)

A Novel Tree-Based Algorithm for Device Coordination in Over-the-Air Federated Learning - Sedaghat, Mohammad Ali; Bereyhi, Ali; Müller, Ralf; Asaad, Saba (WSA and SCC 2023 - 26th International ITG Workshop on Smart Antennas and 13th Conference on Systems, Communications, and Coding, 2023)
This work studies the task of device coordination in wireless networks for over-the-air federated learning (OTA-FL). For conventional metrics of aggregation error, the task is shown to describe the zero-forcing (ZF) and minimum mean squared error (MMSE) schemes and reduces to the NP-hard problem of subset selection. We tackle this problem by studying properties of the optimal scheme. Our analytical results reveal that this scheme is found by searching among the leaves of a tree with favorable monotonic features. Invoking these features, we develop a lowcomplexity algorithm that approximates the optimal scheme by tracking a dominant path of the tree sequentially. Our numerical investigations show that the proposed algorithm closely tracks the optimal scheme.
CRIS-Team Scopus Importer:2023-08-18
Keywords: coordination; minimum mean squared error; Over-the-air federated learning; zero-forcing

A Novel Wireless Communication Paradigm for Intelligent Reflecting Surface Based Symbiotic Radio Systems - Hua, Meng; Wu, Qingqing; Yang, Luxi; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Signal Processing, 2022)
This paper investigates a novel intelligent reflecting surface (IRS)-based symbiotic radio (SR) system architecture consisting of a transmitter, an IRS, and an information receiver (IR). The primary transmitter communicates with the IR and at the same time assists the IRS in forwarding information to the IR. Based on the IRS's symbol period, we distinguish two scenarios, namely, commensal SR (CSR) and parasitic SR (PSR), where two different techniques for decoding the IRS signals at the IR are employed. We formulate bit error rate (BER) minimization problems for both scenarios by jointly optimizing the active beamformer at the base station and the phase shifts at the IRS, subject to a minimum primary rate requirement. Specifically, for the CSR scenario, a penalty-based algorithm is proposed to obtain a high-quality solution, where semi-closed-form solutions for the active beamformer and the IRS phase shifts are derived based on Lagrange duality and Majorization-Minimization methods, respectively. For the PSR scenario, we apply a bisection search-based method, successive convex approximation, and difference of convex programming to develop a computationally efficient algorithm, which converges to a locally optimal solution. Simulation results demonstrate the effectiveness of the proposed algorithms and show that the proposed SR techniques are able to achieve a lower BER than benchmark schemes.
CRIS-Team WoS Importer:2022-02-04

An Overview of Signal Processing Techniques for RIS/IRS-aided Wireless Systems - Pan, Cunhua; Zhou, Gui; Zhi, Kangda; Hong, Sheng; Wu, Tuo; Pan, Yijin; Ren, Hong; Renzo, Marco Di; Swindlehurst, A. Lee; Zhang, Rui; Zhang, Angela Yingjun (IEEE Journal of Selected Topics in Signal Processing, 2022)
In the past as well as present wireless communication systems,the wireless propagation environment is regarded as an uncontrollable black box that impairs the received signal quality, and its negative impacts are compensated for by relying on the design of various sophisticated transmission/reception schemes. However, the improvements through applying such schemes operating at two endpoints (i.e., transmitter and receiver) only are limited even after five generations of wireless systems.Reconfigurable intelligent surface (RIS) or intelligent reflecting surface (IRS) have emerged as a new and promising technology that can configure the wireless environment in a favorable manner by properly tuning the phase shifts of a large number of quasi passive and low-cost reflecting elements, thus standing out as a promising candidate technology for the next/sixth-generation (6G) wireless system. However, to reap the performance benefits promised by RIS/IRS, efficient signal processing techniques are crucial, for a variety of purposes such as channel estimation, transmission design, radio localization, and so on. In this paper, we provide a comprehensive overview of recent advances on RIS/IRS-aided wireless systems from the signal processing perspective.We also highlight promising research directions that are worthy of investigation in the future.
CRIS-Team Scopus Importer:2022-08-19
Keywords: 5G mobile communication; 6G mobile communication; Channel estimation; Costs; Hardware; Location awareness; Reconfigurable Intelligent Surface (RIS); Intelligent Reflecting Surface (IRS); channel estimation; transmission design; localization; wireless systems; 6G; Wireless communication

An Overview of Sustainable Green 5G Networks - Wu, Qingqing; Geoffrey Ye Li, Geoffrey Ye Li; Chen, Wen; Wing Kwan Ng, Derrick; Schober, Robert (IEEE Wireless Communications, 2017)
The stringent requirements of a 1000x increase in data traffic and 1 ms round-trip latency have made limiting the potentially tremendous ensuing energy consumption one of the most challenging problems for the design of the upcoming 5G networks. To enable sustainable 5G networks, new technologies have been proposed to improve the system energy efficiency, and alternative energy sources are introduced to reduce our dependence on traditional fossil fuels. In particular, various 5G techniques target the reduction of the energy consumption without sacrificing the quality of service. Meanwhile, energy harvesting technologies, which enable communication transceivers to harvest energy from various renewable resources and ambient radio frequency signals for communication, have drawn significant interest from both academia and industry. In this article, we provide an overview of the latest research on both green 5G techniques and energy harvesting for communication. In addition, some technical challenges and potential research topics for realizing sustainable green 5G networks are also identified.<br
Keywords: 5G mobile communication; Power demand; Antennas; Wireless networks; Wireless fidelity; Green products; Energy harvesting; Green communication; Sustainable development; Telecommunication traffic

An Ultra-Versatile Massive MIMO Transceiver Testbed for Multi-Gb/s Communication - Gröschel, Patrick; Hehn, Markus; Sippel, Erik; Schober, Robert; Weigel, Robert; Vossiek, Martin; Carlowitz, Christian (2019 IEEE 2nd 5G World Forum (5GWF), 2019)
Massive multiple-input multiple-output (MIMO) communication has gained huge attention throughout the last years as a key technology for fifth generation mobile communication systems, because they enable wide area coverage along with ultra-high data rates and low bit energy. Furthermore, for a high number of antennas, communication theory predicts nearly optimal performance using basic linear detection and precoding schemes. However, realizing such large-scale arrays (say 100 elements or more) is non-trivial and costly and hence, only few of them are available for public research. Most often, existing solutions are limited to the current mobile communication standards. We therefore propose the design and implementation of a low-cost ultra-versatile 120-antenna massive MIMO testbed applicable both in communication and localization research. An instantaneous bandwidth of 150 MHz at a center frequency of 5.8 GHz is covered. An indoor verification measurement with 24 parallel transmissions and a bandwidth of 125 MHz achieved a sum-rate of 22.8 Gb/s with only 1.02 % bit error rate resulting in an outstanding equivalent error-free spectral efficiency of 167.2 bit/s/Hz.<br
Keywords: Radio frequency; Antenna arrays; Antenna measurements; OFDM; Transceivers

AoI-Driven Client Scheduling for Federated Learning: A Lagrangian Index Approach - Ma, Manyou; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2023)
Federated learning (FL) is a distributed learning framework where clients jointly train a global model without sharing their local datasets. In randomized client sampling, a subset of clients are uniformly chosen to participate in training in each communication round of FL. Recent research has shown that by jointly considering the age of information (AoI) and channel state information (CSI) of each client, the convergence of FL can be improved. In this paper, we formulate a joint AoI and CSI-based client scheduling problem as a constrained Markov decision process. We propose a low-complexity and scalable algorithm based on the Lagrangian index approach. Simulation results show that the proposed Lagrangian index-based approach achieves near-optimal performance. For FL tasks with the CIFAR-10 dataset, our results show that the proposed algorithm can speed up the convergence of FL by 40%, by reducing the duration of uplink transmission, when compared with two state-of-the-art FL algorithms.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Training; Simulation; Markov processes; Linear programming; Indexes; Uplink; Task analysis

A Power Line Communication Topology Module for ns–3 and DCE - Gäde, Bernhard; Lehmann, Andreas; Deutschmann, Jörg; Huber, Johannes (Smart Grid Communications (SmartGridComm), 2017 IEEE International Conference on, 2017)
Protocol development for power line communications (PLC) relies heavily on testing and verification under various conditions. As it is very difficult to implement testbeds with large and flexible topologies, network simulation is usually the means of choice. It is of particular importance that the physical layer model is not only flexible and of limited complexity, but also provides a good degree of realism. Especially for PLC the topology has large impact. We introduce a new module for the simulation of PLC networks with network simulator 3 (ns-3) and Direct Code Execution (DCE) that is flexible and efficient but also offers accurate results. We present a detailed description of the module, its features and implementation. We provide a comparison with the output of the circuit simulator LTspice for verification.

Application of smart antenna technologies in simultaneous wireless information and power transfer - Ding, Zhiguo; Zhong, Caijun; Wing Kwan Ng, Derrick; Peng, Mugen; Suraweera, Himal A.; Schober, Robert; Poor, H. Vincent (IEEE Communications Magazine, 2015)
Simultaneous wireless information and power transfer (SWIPT) is a promising solution to increase the lifetime of wireless nodes and hence alleviate the energy bottleneck of energy constrained wireless networks. As an alternative to conventional energy harvesting techniques, SWIPT relies on the use of radio frequency signals, and is expected to bring some fundamental changes to the design of wireless communication networks. This article focuses on the application of advanced smart antenna technologies to SWIPT, including multiple-input multiple-output and relaying techniques. These smart antenna technologies have the potential to significantly improve the energy efficiency and also the spectral efficiency of SWIPT. Different network topologies with single and multiple users are investigated, along with some promising solutions to achieve a favorable trade-off between system performance and complexity. A detailed discussion of future research challenges for the design of SWIPT systems is also provided.<br
Keywords: Relays; MIMO; Receiving antennas; Wireless communication; Energy harvesting; Power transfer; Smart antennas

Appropriate antenna patterns for a compact MIMO receiver - Bains, Robert; Müller, Ralf (IEEE 2006 International Zurich Seminar on Digital Communications, 2006)
A compact MIMO receiver is reported previously [1] which uses only a single active receiving antenna and multiple passive elements to achieve spatial diversity. The passive elements are used to construct suitable antenna patterns which can be rotated 360 degrees around to achieve a MIMO effect. This paper discusses some antenna patterns which can be used for this purpose. An example of an antenna with one active dipole and 6 passive dipoles distributed on a circle around it is given. The distance between the active dipole and the passive elements is chosen to be λ/8, which means that the antenna system will have a diameter of approximately λ/4. Further the broadband properties of this antenna system is considered in terms of mutual information for different frequencies. © 2006 IEEE.
Keywords: Receiving antennas; MIMO; Directive antennas; Dipole antennas; Broadband antennas; Frequency; Narrowband; Appropriate Technology; Mutual Information; Connectors

A Probabilistic Approach to Modeling Users' Network Selection in the Presence of Heterogeneous Wireless Networks - Kumar, Abhinav; Mallik, Ranjan K.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2014)
In the presence of heterogeneous service provider (SP) networks such as wireless local area networks and cellular networks, users have to make a choice. The quality of service provided and the price charged by an SP play a crucial role in this decision process. In this paper, we study the network selection behavior of mobile users. A novel probabilistic framework is presented, with explicit analytical expressions for the transition and steady state network selection probabilities of the users. The proposed framework utilizes the price charged and the utility obtained at the SPs in obtaining the transition probabilities, even in the presence of multi-homing users. Furthermore, network-level parameters such as call blocking probabilities and throughput are obtained in terms of the steady state probabilities. Numerical results indicate that the prices and utilities at the heterogeneous SPs have considerable impact on the overall network performance.<br
Keywords: Wireless LAN; Quality of service; Probabilistic logic; Multiaccess communication; Steady-state; Wireless networks

A quadratic programming problem arising from vector precoding in wireless communications - Müller, Ralf; Guo, Dongning; Moustakas, Aris L. (Journal of Physics : Conference Series, 2008)
A quadratic programming problem is studied in the limit of asymptotically large kernel matrices by means of the replica method. It is found that inverse Wishart kernels are - within the validity range of the replica symmetric solution - asymptotically invariant to Cartesian relaxations. In the context of vector precoding for wireless communication systems with dual antenna arrays, so-called MIMO systems, this implies that adding more transmit antennas cannot reduce the minimum required transmit energy per bit significantly. By contrast, a new convex relaxation is proposed and shown to be a practical and useful method. © 2008 IOP Publishing Ltd.

A random matrix model for the antenna array channel with decaying power delay profile - Müller, Ralf (2001 IEEE Information Theory Workshop, ITW 2001, 2001)
The random matrix model for multipath propagation on the antenna array channel is generalised to decaying power delay profiles. Results are given in terms of Stieltjes transforms of the eigenvalue distributions of the channel's space-time covariance matrix.

A random matrix model of communication via antenna arrays - Müller, Ralf (IEEE Transactions on Information Theory, 2002)
A random matrix model is introduced that probabilistically describes the spatial and temporal multipath propagation between a transmitting and receiving antenna array with a limited number of scatterers for mobile radio and indoor environments. The model characterizes the channel by its richness delay profile which gives the number of scattering objects as a function of the path delay. Each delay is assigned the eigenvalue distribution of a random matrix that depends on the number of scatterers, receiving antennas, and transmitting antennas. The model allows one to calculate signal-to-interference-and-noise ratios (SINRs) and channel capacities for large antenna arrays analytically and quantifies to what extent rich scattering improves performance.
Keywords: Antenna arrays; Channel models; Eigenvalue distribution; Fading channels; Information rates; Intersymbol interference; Multiuser communications; Random matrices; Stieltjes transform

Area Rate Efficiency in Molecular Communications - Brand, Lukas; Lotter, Sebastian; Jamali, Vahid; Schober, Robert (PROCEEDINGS OF THE 8TH ACM INTERNATIONAL CONFERENCE ON NANOSCALE COMPUTING AND COMMUNICATION (ACM NANOCOM 2021), 2021)
We consider a multiuser diffusion-based molecular communication (MC) system where multiple spatially distributed transmitter (TX)-receiver (RX) pairs establish point-to-point communication links employing the same type of signaling molecules. To realize the full potential of such a system, an in-depth understanding of the interplay between the spatial user density and inter-user interference (IUI) and its impact on system performance in an asymptotic regime with large numbers of users is needed. In this paper, we adopt a three-dimensional (3-D) system model with multiple independent and spatially distributed point-to-point transmission links, where both the TXs and RXs are positioned according to a regular hexagonal grid, respectively. Based on this model, we first derive an expression for the channel impulse responses (CIRs) of all TX-RX links in the system. Then, we provide the maximum likelihood (ML) decision rule for the RXs and show that it reduces to a threshold-based detector. We derive an analytical expression for the corresponding detection threshold which depends on the statistics of the MC channel and the statistics of the IUI. Furthermore, we derive an analytical expression for the bit error rate (BER) and the achievable rate of a single transmission link. Finally, we propose a new performance metric, which we refer to as area rate efficiency (ARE), that captures the tradeoff between the user density and IUI. The ARE characterizes how efficiently given TX and RX areas are used for information transmission and is given in terms of bits per area unit. We show that there exists an optimal user density for maximization of the ARE. Results from particle-based and Monte Carlo simulations validate the accuracy of the expressions derived for the CIR, optimal detection threshold, BER, and ARE.<br
CRIS-Team WoS Importer:2022-03-25

Area Rate Efficiency in Multi-Link Molecular Communications - Brand, Lukas; Lotter, Sebastian; Jamali, Vahid; Schober, Robert; Schäfer, Maximilian (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
We consider a multi-link diffusion-based molecular communication (MC) system where multiple spatially distributed transmitter (TX)-receiver (RX) pairs establish point-to-point communication links employing the same type of signaling molecules. To exploit the full potential of such a system, an in-depth understanding of the interplay between the spatial link density and inter-link interference (ILI) and its impact on system performance is needed. In this paper, we consider a three-dimensional unbounded domain with multiple spatially distributed point-to-point non-cooperative transmission links, where both the TXs and RXs are positioned on a regular fixed grid. For this setup, we first derive an analytical expression for the channel impulse responses (CIRs) between the TXs and RXs in the system. Then, we derive the maximum likelihood (ML) detector for the RXs and show that it reduces to a thresholdbased detector. Moreover, we derive an analytical expression for the corresponding detection threshold which depends on the statistics of the desired signal from the dedicated TX, the statistics of the MC channel, and the statistics of the ILI. We also provide a low-complexity suboptimal decision threshold. Furthermore, we derive an analytical expression for the bit error rate (BER) and the achievable rate of a single transmission link. Finally, we propose two new performance metrics, namely area rate efficiency (ARE) and area and time rate efficiency (ARTE), suitable for holistically evaluating spatially distributed multi-link MC systems. In particular, ARE and ARTE capture the tradeoff between transmission link density and achievable rate per link and the tradeoff between transmission link density, achievable rate per link, and inter-symbol interference (ISI), respectively. Hence, ARE and ARTE can be exploited to determine the optimal transmission link density for maximizing the throughput of the entire system.
Created from Fastlane, Scopus look-up
Keywords: Detectors; Interference; Measurement; MIMO communication; Sensors; Signal to noise ratio; Wireless communication

A reference signal based GLRT for simultaneous sensing and reception in cognitive LTE-A systems - Karunakaran, Prasanth; Gerstacker, Wolfgang (2016 IEEE Wireless Communications and Networking Conference, 2016)
We explore the application of cognitive radio (CR) principles to 3GPP LTE-A. In such a system, a cognitive radio (CR), synchronized to the macro base station (BS), exploits the spectral holes in the orthogonal frequency division multiple access (OFDMA) time-frequency grid. Spectrum sharing between different network operators and device-to-device (D2D) communications in LTE-A are presented as potential applications. Sensing is expected to play a prominent role in such systems. We focus on simultaneous sensing and reception (SSR) that can avoid the overhead in sensing before transmission (SBT) protocols. Firstly, for a flat fading channel, we develop generalized likelihood ratio tests (GLRTs) based on the demodulation reference signals (DMRSs) of transmission mode 9 in LTE-A that do not require the knowledge of signal powers, channel statistics and noise parameters. Secondly, using a polynomial fitting, we extend the algorithm to frequency-selective fading scenarios. Simulation results are presented to compare the different algorithms which indicate that good performance can be achieved for SSR with full knowledge of the DMRS

A robust design of electric vehicle frequency regulation service - Yao, Enxin; Wong, Vincent W. S.; Schober, Robert (2014 IEEE International Conference on Smart Grid Communications (SmartGridComm), 2014)
Electric vehicles (EVs) have the potential to provide frequency regulation service to an independent system operator (ISO) by changing their real-time charging or discharging power according to an automatic generation control (AGC) signal. Recently, the Federal Energy Regulatory Commission has issued an order to ISOs to introduce a performance-based compensation paradigm. In this new compensation scheme, the ISOs make payments to the EVs for providing the frequency regulation capacity and the real-time dispatch when following the AGC signal. In this paper, we propose a robust EV frequency regulation (REF) algorithm to determine the hourly regulation capacity for each EV considering the randomness of the AGC signal. The proposed REF algorithm is based on a robust optimization problem formulation. It enables EVs to follow the random AGC signal reliably and to improve the EV frequency regulation revenue. Simulation results show that the proposed REF algorithm obtains a higher revenue compared with a benchmark algorithm from the literature under a performance-based compensation paradigm.<br
Keywords: Frequency control; Automatic generation control; ISO; Robustness; Bismuth; Real-time systems

A robust pilot decontamination method for massive MIMO systems - Yin, Haifan; Cottatellucci, Laura; Gesbert, David; Müller, Ralf; He, Gaoning (IEEE International Conference on Acoustics, Speech, and Signal Processing, 2016)

A Single Antenna Interference Cancellation Algorithm for GSM - Meyer, Raimund; Gerstacker, Wolfgang; Schober, Robert; Huber, Johannes (Conference Proceedings, 2005)
In mobile communication networks, system capacity is often limited by cochannel interference. Therefore, receiver algorithms for cancellation of cochannel interference have recently attracted much interest At the mobile terminal, algorithms can usually rely only on one received signal delivered by a single receive antenna. In this paper, a novel low-complexity single antenna interference cancellation (SAIC) algorithm for real-valued modulation formats referred to as mono interference cancellation (MIC) is introduced which is well suited for practical applications. By using this algorithm in the mobile terminals, capacity of GSM networks can be improved by up to 40-60 %. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.mobilk.asingl
Keywords: Cochannel interference; Equalization; GSM; Mobile communications

A Single Antenna Interference Cancellation Algorithm for Increased GSM Capacity - Meyer, Raimund; Gerstacker, Wolfgang; Schober, Robert; Huber, Johannes (IEEE Transactions on Wireless Communications, 2006)
In mobile communications networks, system capacity is often limited by cochannel interference. Therefore, receiver algorithms for cancellation of cochannel interference have recently attracted much interest. At the mobile terminal, algorithms can usually rely only on one received signal delivered by a single receive antenna. In this letter, a low-complexity single antenna interference cancellation (SAIC) algorithm for real-valued modulation formats referred to as mono interference cancellation (MIC) is introduced which is well suited for practical applications. Field trials in commercial GSM networks using prototype terminals with the proposed MIC algorithm have demonstrated that the novel concept may yield capacity improvements of up to 80%. The underlying principle is also beneficial for adjacent channel interference and receivers with multiple antennas. Furthermore, in coverage-limited scenarios, there is no performance degradation compared with conventional receivers. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.mobilk.asingl
Keywords: Cochannel interference; Equalization; GSM; Mobile communications

A Single-RF Architecture for Multiuser Massive MIMO Via Reflecting Surfaces - Bereyhi, Ali; Jamali, Vahid; Müller, Ralf; Tulino, Antonia M.; Fischer, Georg; Schober, Robert (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2020)
In this work, we propose a new single-RF MIMO architecture which enjoys high scalability and energy-efficiency. The transmitter in this proposal consists of a single RF illuminator radiating towards a reflecting surface. Each element on the reflecting surface re-transmits its received signal after applying a phase-shift, such that a desired beamforming pattern is obtained. For this architecture, the problem of beamforming is interpreted as linear regression and a solution is derived via the method of least-squares. Using this formulation, a fast iterative algorithm for tuning of the reflecting surface is developed. Numerical results demonstrate that the proposed architecture is fully compatible with current designs of reflecting surfaces.
CRIS-Team Scopus Importer:2020-09-18
Keywords: least-squares; massive MIMO; reflecting surfaces; Single-RF transmitter

Aspect-Level Sentiment Classification Based on Graph Attention Network with BERT - Zou, Jiajun; Wu, Sixing; Yang, Zhongliang; Chen, Chong; Sun, Yan; Jiang, Minghu; Huang, Yongfeng (Communications in Computer and Information Science, 2022)
With accelerated evolution of the internet, people can express their sentiments towards organizations, politics, products, events, etc. Analyzing these sentiments becomes very beneficial for businesses, government and individuals. To some extent, text sentiment analysis involves Internet content security. Aspect level sentiment classification aims to recognize the sentiment expressed towards a special target given a context sentence, which is more fine-grained than sentence level or document level sentiment analysis. Most previous works concentrate on the semantic information between the contexts and the aspect terms, but they ignore the structural information of the sentences. In this paper, we propose a new method based on Graph Attention Network (GAT) to deal with the complex connections among words in sentences through structural features. A lot of experiments are conducted on two datasets: Laptop and Restaurant from SemEval2014, the results show that our model outperforms other previous works, which confirms the effectiveness of taking sentence structural information into account.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Aspect-level sentiment classification; Deep learning; Graph attention network; Natural language processing

Association Extraction and Recognition of Multiple Emotion Expressed in Social Texts - Zou, Jiajun; Wu, Sixing; Yang, Zhongliang; Chen, Chong; Sun, Yan; Jiang, Minghu; Huang, Yongfeng (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2022)
Detecting the sentiment people present in social media such as tweets is important for politics, commerce, education and so on. The task of multiple emotion recognition in texts is to predict a set of emotion labels that expressed in sentences. There are still some shortcomings in the current works: 1) the dependencies among emotions are not well modeled due to the complex combinatorial features of them, 2) the semantics of emotion labels as well as the semantic correlations between emotion labels and sentences are not fully considered. In this paper, in the purpose of capturing the dependencies between emotions, we propose a new method by using Graph Convolutional Network (GCN) based on a label co-occurrence matrix building from the dataset, and a Convolutional Neural Network (CNN) is used to capture the syntactic and semantic information in the sentences through different convolutional filters, the outputs of GCN and CNN are multiplied together to fuse their features as the last output. Experiments on SemEval2018 Task1: E-c multi-label emotion recognition problem show that metrics have been significantly improved, and our approach obviously obtains the dependencies among emotions described by Pointwise Mutual Information (PMI) which measures the correlations between emotions both in the true test labels and predicted labels.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Deep learning; Graph convolutional network; Multi-label emotion recognition; Sentiment analysis

A State-of-the-Art Survey on Reconfigurable Intelligent Surface-Assisted Non-Orthogonal Multiple Access Networks - Ding, Zhiguo; Lv, Lu; Fang, Fang; Dobre, Octavia A.; Karagiannidis, George K.; Al-Dhahir, Naofal; Schober, Robert; Poor, H. Vincent (Proceedings of the IEEE, 2022)
Reconfigurable intelligent surfaces (RISs) and nonorthogonal multiple access (NOMA) have been recognized as key enabling techniques for the envisioned sixth generation (6G) of mobile communication networks. The key feature of RISs is to intelligently reconfigure the wireless propagation environment, which was once considered to be fixed and untunable. The key idea of NOMA is to utilize users' dynamic channel conditions to improve spectral efficiency and user fairness. Naturally, the two communication techniques are complementary to each other and can be integrated to cope with the challenging requirements envisioned for 6G mobile networks. This survey provides a comprehensive overview of the recent progress on the synergistic integration of RISs and NOMA. In particular, the basics of both techniques are introduced first, and then, the fundamentals of RIS-NOMA are discussed for two communication scenarios with different transceiver capabilities. Resource allocation is of paramount importance for the success of RIS-assisted NOMA networks, and various approaches, including artificial intelligence (AI)-empowered designs, are introduced. Security provisioning in RIS-NOMA networks is also discussed as wireless networks are prone to security attacks due to the nature of the shared wireless medium. Finally, the survey is concluded with detailed discussions of the challenges arising in the practical implementation of RIS-NOMA, future research directions, and emerging applications.
CRIS-Team Scopus Importer:2022-06-03
Keywords: 5G mobile communication; 6G mobile communication; Artificial intelligence (AI); Gain; multi-input multi-output (MIMO); NOMA; nonorthogonal multiple access (NOMA); Performance gain; reconfigurable intelligent surface (RIS); resource allocation; Resource management; Security; wireless security.

A Survey of Biological Building Blocks for Synthetic Molecular Communication Systems - Söldner, Christian; Socher, Eileen; Jamali, Vahid; Wicke, Wayan; Ahmadzadeh, Arman; Breitinger, Hans Georg; Burkovski, Andreas; Castiglione, Kathrin; Schober, Robert; Sticht, Heinrich (IEEE Communications Surveys & Tutorials, 2020)
Synthetic molecular communication (MC) is a new communication engineering paradigm which is expected to enable revolutionary applications such as smart drug delivery and real-time health monitoring. The design and implementation of synthetic MC systems (MCSs) at nano- and microscale is very challenging. This is particularly true for synthetic MCSs employing biological components as transmitters and receivers or as interfaces with natural biological MCSs. Nevertheless, since such biological components have been optimized by nature over billions of years, using them in synthetic MCSs is highly promising. This paper provides a survey of biological components that can potentially serve as the main building blocks, i.e., transmitter, receiver, and signaling particles, for the design and implementation of synthetic MCSs. Nature uses a large variety of signaling particles of different sizes and with vastly different properties for communication among biological entities. Here, we focus on three important classes of signaling particles: cations (specifically protons and calcium ions), neurotransmitters (specifically acetylcholine, dopamine, and serotonin), and phosphopeptides. These three classes have unique and distinct features such as their large diffusion coefficients, their specificity, and/or their uniqueness of signaling that make them suitable candidates for signaling particles in synthetic MCSs. For each of these candidate signaling particles, we present several specific transmitter and receiver structures mainly built upon proteins that are capable of performing the distinct physiological functionalities required from the transmitters and receivers of MCSs. Moreover, we present options for both microscale implementation of MCSs as well as the micro-to-macroscale interfaces needed for experimental evaluation of MCSs. One of the main advantages of employing proteins for signal emission and detection is that they can be modified with tools from synthetic biology and be tailored to a wide range of application needs. We discuss the properties, limitations, and applications of the proposed biological building blocks for synthetic MCSs in detail. Furthermore, we outline new research directions for the implementation and the theoretical design and analysis of the proposed transmitter and receiver architectures.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Molecular communications; signaling particles; synthetic biology; test-bed implementation; transmitter and receiver architecture

A Survey of Molecular Communication in Cell Biology: Establishing a New Hierarchy for Interdisciplinary Applications - Bi, Dadi; Almpanis, Apostolos; Noel, Adam; Deng, Yansha; Schober, Robert (IEEE Communications Surveys & Tutorials, 2021)
Molecular communication (MC) engineering is inspired by the use of chemical signals as information carriers in cell biology. The biological nature of chemical signaling makes MC a promising methodology for interdisciplinary applications requiring communication between cells and other microscale devices. However, since the life sciences and communications engineering fields have distinct approaches to formulating and solving research problems, the mismatch between them can hinder the translation of research results and impede the development and implementation of interdisciplinary solutions. To bridge this gap, this survey proposes a novel communication hierarchy for MC signaling in cell biology and maps phenomena, contributions, and problems to the hierarchy. The hierarchy includes: 1) the physical propagation of cell signaling at the Physical Signal Propagation level; 2) the generation, reception, and biochemical pathways of molecular signals at the Physical and Chemical Signal Interaction level; 3) the quantification of physical signals, including macroscale observation and control methods, and conversion of signals to information at the Signal-Data Interface level; 4) the interpretation of information in cell signals and the realization of synthetic systems to store, process, and communicate molecular signals at the Local Data Abstraction level; and 5) applications relying on communication with MC signals at the Application level. To further demonstrate the proposed hierarchy, it is applied to case studies on quorum sensing, neuronal signaling, and communication via DNA. Finally, several open problems are identified for each level and the integration of multiple levels. The proposed hierarchy provides language for communication engineers to study and interface with biological systems, and also helps biologists to understand how communications engineering concepts can be exploited to interpret, control, and manipulate signaling in cell biology.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Biology; Cell biology; chemical reactions; Chemicals; Computer architecture; diffusion; hierarchy; interdisciplinary applications; level; microfluidics; molecular communication; Protocols; Sensors; signaling pathways; Synthetic biology; synthetic biology.; Tools

A Survey on Millimeter-Wave Beamforming Enabled UAV Communications and Networking - Xiao, Zhenyu; Zhu, Lipeng; Liu, Yanming; Yi, Pengfei; Zhang, Rui; Xia, Xiang Gen; Schober, Robert (IEEE Communications Surveys & Tutorials, 2022)
Unmanned aerial vehicles (UAVs) have found widespread commercial, civilian, and military applications. Wireless communication has always been one of the core technologies for UAV. However, the communication capacity is becoming a bottleneck for UAV to support more challenging application scenarios. The heavily-occupied sub-6 GHz frequency band is not sufficient to meet the ultra high-data-traffic requirements. The utilization of the millimeter-wave (mmWave) frequency bands is a promising direction for UAV communications, where large antenna arrays can be packed in a small area on the UAV to perform three-dimensional (3D) beamforming. On the other hand, UAVs serving as aerial access points or relays can significantly enhance the coverage and quality of service of the terrestrial mmWave cellular networks. In this paper, we provide a comprehensive survey on mmWave beamforming enabled UAV communications and networking. The technical potential of and challenges for mmWave-UAV communications are presented first. Then, we provide an overview on relevant mmWave antenna structures and channel modeling. Subsequently, the technologies and solutions for UAV-connected mmWave cellular networks and mmWave-UAV ad hoc networks are reviewed, respectively. Finally, we present open issues and promising directions for future research in mmWave beamforming enabled UAV communications and networking.
CRIS-Team Scopus Importer:2022-03-11
Keywords: ad hoc network; antenna structure; beamforming; channel modeling; mmWave communications; UAV; UAV-connected mmWave cellular

A Survey on Non-Orthogonal Multiple Access for 5G Networks: Research Challenges and Future Trends - Ding, Zhiguo; Lei, Xianfu; Karagiannidis, George K.; Schober, Robert; Yuan, Jinhong; Bhargava, Vijay Kishore (IEEE Journal on Selected Areas in Communications, 2017)
Non-orthogonal multiple access (NOMA) is an essential enabling technology for the fifth-generation (5G) wireless networks to meet the heterogeneous demands on low latency, high reliability, massive connectivity, improved fairness, and high throughput. The key idea behind NOMA is to serve multiple users in the same resource block, such as a time slot, subcarrier, or spreading code. The NOMA principle is a general framework, and several recently proposed 5G multiple access schemes can be viewed as special cases. This survey provides an overview of the latest NOMA research and innovations as well as their applications. Thereby, the papers published in this special issue are put into the context of the existing literature. Future research challenges regarding NOMA in 5G and beyond are also discussed.<br
Keywords: NOMA; 5G mobile communication; Quality of service; Resource management; Millimeter wave communication; MIMO; Cognitive radio

Asymptotically Optimal Power Allocation for Energy Harvesting Communication Networks - Zlatanov, Nikola; Schober, Robert; Hadzi-Velkov, Zoran (IEEE Transactions on Vehicular Technology, 2017)
For a general energy harvesting (EH) communication network, i.e., a network where the nodes generate their transmit power through EH, we derive the asymptotically optimal online power allocation solution that optimizes a general utility function when the number of transmit time slots, N, and the battery capacities of the EH nodes, B max , satisfy N → ∞ and B max → ∞. The considered family of utility functions is general enough to include the most important performance measures in communication theory, such as the average data rate, outage probability, average bit-error probability, and average signal-to-noise ratio. The proposed power allocation solution is very simple. Namely, the asymptotically optimal power allocation for the EH network is identical to the optimal power allocation for an equivalent nonEH network whose nodes have infinite energy available but their average transmit power is constrained to be equal to the average harvested power and/or the maximum average transmit power of the corresponding nodes in the EH network. Moreover, the maximum average performance of a general EH network converges to the maximum average performance of the corresponding equivalent non-EH network, when N → ∞ and B max → ∞. Although the proposed solution is asymptotic in nature, it is applicable to EH systems transmitting in a large but finite number of time slots and having a battery capacity much larger than the average harvested power and/or the maximuma average transmit power.<br
Keywords: Batteries; Resource management; Transmitters; Energy harvesting; Battery charge measurement; Measurement uncertainty; Error probability

Asymptotically optimal power allocation for point-to-point energy harvesting communication systems - Zlatanov, Nikola; Hadzi-Velkov, Zoran; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2013)
For a point-to-point communication system generating its power via energy harvesting (EH), we derive the asymptotically optimal power allocation which optimizes a general utility function when the number of transmitted codewords N and the battery capacity Bmax satisfy N → ∞ and B max → ∞. The considered family of utility functions is general enough to include the most important performance measurements in communication theory such as ergodic rate, outage probability, average signal-to-noise ratio, etc. The discovered solution is very simple. Namely, the optimal power allocation for the EH system is identical to the optimal power allocation of an equivalent non-EH communication system with infinite available energy, under the constraint that both systems use identical average transmit powers. Although the proposed solution is asymptotic, it is applicable to EH systems transmitting a large but finite number of codewords and having a battery capacity much larger than the average harvested power and/or the maximum average transmit power. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Asymptotic analysis of iterative channel estimation and multiuser detection with soft feedback in multipath channels - Vehkaperä, Mikko; Takeuchi, Keigo; Müller, Ralf; Tanaka, Toshiyuki (16th European Signal Processing Conference, EUSIPCO 2008, 2008)
Large system analysis of a randomly spread direct-sequence code-division multiple-access system in a frequency-selective channel is considered. The receiver uses iterative channel estimation and multiuser detection (MUD) with soft feedback from single-user decoders to refine both the decisions of the linear minimum mean square error (LMMSE) MUD, and the initial pilot-based estimates of the LMMSE channel estimator. Replica method, a tool from statistical physics, and density evolution with Gaussian approximation are used to obtain the asymptotic performance of the LMMSE MUD with soft parallel interference cancellation. The results indicate that as the channel coherence time grows, the performance of corresponding single-user system having perfect channel state information can be approached even in an overloaded multiuser system using channel estimation and vanishing pilot overhead. copyright by EURASIP.
Keywords: Channel estimation; Multiuser detection; Multiaccess communication; Iterative Decoding; Fading; Signal to noise Ratio; Vectors

Asymptotic bounds on the Optimum Multiuser Efficiency of randomly spread CDMA - Sedaghat, Mohammad A.; Müller, Ralf; Marvasti, Farokh (2014 12th International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks, WiOpt 2014, 2014)
We derive some bounds on the Optimum Asymptotic Multiuser Efficiency (OAME) of randomly spread CDMA as extensions of the result by Tse and Verdú. To this end, random Gaussian and random binary antipodal spreading are considered. Furthermore, the input signal is assumed to be Binary Phase Shift Keying (BPSK). It is shown that in a CDMA system with K-user and N chips when K and N → 8 and the loading factor, K over N, grows logarithmically with K, the OAME converges to 1 almost surely under some condition. It is also shown that a Gaussian randomly spread CDMA system has a performance close to the single user system at high Signal to Noise Ratio (SNR) when the loading factor is kept less than log K over 2. Moreover, for random binary antipodal matrices, we show that the loading factor cannot grow faster than equation. © 2014 IFIP.
Keywords: Code division multiple access (CDMA); compressive sensing; detecting matrices; multiuser detection; optimum asymptotic multiuser efficiency (OAME); random spreading

Asymptotic Performance Analysis of GSVD-NOMA Systems With a Large-Scale Antenna Array - Chen, Zhuo; Ding, Zhiguo; Dai, Xuchu; Schober, Robert (IEEE Transactions on Wireless Communications, 2018)
This paper considers a multiple-input multipleoutput (MIMO) downlink communication scenario with one base station and two users, where each user is equipped with m antennas and the base station is equipped with n antennas. To efficiently exploit the spectrum resources, we propose a transmission protocol which combines generalized singular value decomposition (GSVD) and non-orthogonal multiple access (NOMA). The expected data rates achieved by the two users are adopted as performance metrics for the evaluation of the proposed GSVD-NOMA scheme. In particular, we first characterize the limiting distribution of the squared generalized singular values of the two users' channel matrices for the asymptotic case, where the numbers of transmit and receive antennas approach infinity. Then, we calculate the expected normalized individual rates of the users in the considered asymptotic regime. Furthermore, we extend the proposed GSVD-NOMA scheme to the general MIMO downlink communication scenario with more than two users. To this end, we propose a hybrid multiple access approach, where the base station divides the users into different groups, the proposed GSVD-NOMA scheme is implemented within each group, and different groups are allocated orthogonal bandwidth resources. Finally, numerical results are provided to validate the effectiveness of the proposed GSVD-NOMA protocol and the accuracy of the developed analytical results.<br
Keywords: NOMA; MIMO communication; Downlink; Base stations; Matrix decomposition; Receiving antennas

Asymptotic Performance Analysis of GSVD-NOMA Systems with a Large-Scale Antenna Array - Chen, Zhuo; Ding, Zhiguo; Dai, Xuchu; Schober, Robert (IEEE Transactions on Wireless Communications, 2019)
This paper considers a multiple-input multiple-output (MIMO) downlink communication scenario with one base station and two users, where each user is equipped with m antennas and the base station is equipped with n antennas. To efficiently exploit the spectrum resources, we propose a transmission protocol which combines generalized singular value decomposition (GSVD) and non-orthogonal multiple access (NOMA). The expected data rates achieved by the two users are adopted as performance metrics for the evaluation of the proposed GSVD-NOMA scheme. In particular, we first characterize the limiting distribution of the squared generalized singular values of the two users' channel matrices for the asymptotic case, where the numbers of transmit and receive antennas approach infinity. Then, we calculate the expected normalized individual rates of the users in the considered asymptotic regime. Furthermore, we extend the proposed GSVD-NOMA scheme to the general MIMO downlink communication scenario with more than two users. To this end, we propose a hybrid multiple access approach, where the base station divides the users into different groups, the proposed GSVD-NOMA scheme is implemented within each group, and different groups are allocated orthogonal bandwidth resources. Finally, numerical results are provided to validate the effectiveness of the proposed GSVD-NOMA protocol and the accuracy of the developed analytical results.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Generalized singular value decomposition (GSVD); multiple-input multiple-output (MIMO); non-orthogonal multiple access (NOMA)

Asymptotic Performance Analysis of Spatially Reconfigurable Antenna Arrays - Asaad, Saba; Bereyhi, Ali; Sedaghat, Mohammad Ali; Müller, Ralf; Rabiei, Amir Masoud (Proceedings of 21 International ITG Workshop on Smart Antennas (WSA), 2017)
A spatially reconfigurable antenna arrays consists of an antenna array of finite length and fixed geometry which is displaced within a given area. Using these reconfigurable components, the performance of MIMO systems is remarkably improved by effectively positioning the array in its displacement area. This paper studies the large-system performance of MIMO setups with spatially reconfigurable antenna arrays when the displacement area is large. Considering fading channels, the distribution of the input-output mutual information is derived, and the asymptotic hardening property is demonstrated to hold. As the size of the displacement area grows large, the mutual information is shown to converge in distribution to a type-one Gumbel random variable whose mean grows large proportional to the displacement size, and whose variance tends to zero. Our numerical investigations depict that the type-one Gumbel approximation closely tracks the empirical distribution even for a finite displacement siz
Keywords: Antenna selection; Millimeter waves; Spatially reconfigurable antenna arrays

Asymptotic performance bounds of joint channel estimation and multiuser detection in frequency-selective fading DS-CDMA channels - Takeuchi, Keigo; Vehkapera, Mikko; Tanaka, Toshiyuki; Müller, Ralf (2008 International Symposium on Information Theory and its Applications, ISITA2008, 2008)
We derive asymptotic upper bounds of the performance of a one-shot MMSE multiuser detector (MUD) and an optimal MUD in frequency-selective fading DS-CDMA channels with imperfect CSI at the receiver, using the replica method. We find that the performance bound of the one-shot MMSE MUD is indistinguishable from the performance of the one-shot LMMSE MUD analyzed by Evans and Tse when signal-to-noise ratio is high and the system load is small, and that the performance gap between the optimal MUD and the one-shot LMMSE MUD is also small on the same conditions.
Keywords: Channel estimation; Multiuser detection; Frequency estimation; Fading; Multiaccess communication; Upper bound; Detectors; Signal analysis; Performance analysis; Signal to noise ratio

Asymptotics of Nonlinear LSE Precoders with Applications to Transmit Antenna Selection - Bereyhi, Ali; Sedaghat, Mohammad Ali; Müller, Ralf (Proceedings of IEEE International Symposium on Information Theory (ISIT), 2017)
This paper studies the large-system performance of Least Square Error (LSE) precoders which minimize the input-output distortion over an arbitrary support subject to a general penalty function. The asymptotics are determined via the replica method in a general form which encloses the Replica Symmetric (RS) and Replica Symmetry Breaking (RSB) ansätze. As a result, the "marginal decoupling property" of LSE precoders for b-steps of RSB is derived. The generality of the studied setup enables us to address special cases in which the number of active transmit antennas are constrained. Our numerical investigations depict that the computationally efficient forms of LSE precoders based on "ℓ1-norm" minimization perform close to the cases with "zero-norm" penalty function which have a considerable improvements compared to the random antenna selection. For the case with BPSK signals and restricted number of active antennas, the results show that RS fails to predict the performance while the RSB ansatz is consistent with theoretical bounds.
Keywords: MIMO precoding; Replica method; Decoupling principle

Asymptotics of transmit antenna selection: Impact of multiple receive antennas - Asaad, Saba; Bereyhi, Ali; Müller, Ralf; Rabiei, Amir Masoud (Proceedings of IEEE International Conference on Communications (ICC), 2017)
Consider a fading Gaussian MIMO channel with Nt transmit and Nr receive antennas. The transmitter selects Lt antennas corresponding to the strongest channels. For this setup, we study the distribution of the input-output mutual information when Nt grows large. We show that, for any Nr and Lt, the distribution of the input-output mutual information is accurately approximated by a Gaussian distribution whose mean grows large and whose variance converges to zero. Our analysis depicts that, in the large limit, the gap between the expectation of the mutual information and its corresponding upper bound, derived by applying Jensen's inequality, converges to a constant which only depends on Nr and Lt. The result extends the scope of channel hardening to the general case of antenna selection with multiple receive and selected transmit antennas. Although the analyses are given for the large-system limit, our numerical investigations indicate the robustness of the approximated distribution even when the number of antennas is not large.
Keywords: Antenna selection; Channel hardening

Asynchronous CDMA systems with random spreadingpart I: Fundamental limits - Cottatellucci, Laura; Müller, Ralf; Debbah, Merouane (IEEE Transactions on Information Theory, 2010)
Spectral efficiency for asynchronous code division multiple access (CDMA) with random spreading is calculated in the large system limit allowing for arbitrary chip waveforms and frequency-flat fading. Signal-to-interference and noise ratios (SINRs) for suboptimal receivers, such as the linear minimum mean square error (MMSE) detectors, are derived. The approach is general and optionally allows even for statistics obtained by undersampling the received signal. All performance measures are given as a function of the chip waveform and the delay distribution of the users in the large system limit. It turns out that synchronizing users on a chip level impairs performance for all chip waveforms with bandwidth greater than the Nyquist bandwidth, e.g., positive roll-off factors. For example, with the pulse shaping demanded in the UMTS standard, user synchronization reduces spectral efficiency up to 12% at 10 dB normalized signal-to-noise ratio. The benefits of asynchronism stem from the finding that the excess bandwidth of chip waveforms actually spans additional dimensions in signal space, if and only if the users are desynchronized at chip-level. The analysis of linear MMSE detectors shows that the limiting interference effects can be decoupled both in the user domain and in the frequency domain such that the concept of effective interference spectral density arises. This generalizes and refines Tse and Hanly's concept of effective interference. In Part II, the analysis is extended to any linear detector that admits a representation as multistage detector and guidelines for the design of low complexity multistage detectors with universal weights are provided. © 2006 IEEE.
Keywords: Asynchronous code-division multiple access (CDMA); Channel capacity; Effective interference; Excess bandwidth; Minimum mean square error (MMSE) detector; Multiuser detection; Pulse shaping; Random matrix theory; Random spreading sequences; Spectral efficiency

Asynchronous CDMA systems with random spreadingpart II: Design criteria - Cottatellucci, Laura; Müller, Ralf; Debbah, Merouane (IEEE Transactions on Information Theory, 2010)
Totally asynchronous code-division multiple-access (CDMA) systems are addressed. In Part I, the fundamental limits of asynchronous CDMA systems are analyzed in terms of spectral efficiency and SINR at the output of the optimum linear detector. The focus of Part II is the design of low-complexity implementations of linear multiuser detectors in systems with many users that admit a multistage representation, e.g., reduced rank multistage Wiener filters, polynomial expansion detectors, weighted linear parallel interference cancellers. The effects of excess bandwidth, chip-pulse shaping, and time delay distribution on CDMA with suboptimum linear receiver structures are investigated. Recursive expressions for universal weight design are given. The performance in terms of SINR is derived in the large-system limit and the performance improvement over synchronous systems is quantified. The considerations distinguish between two ways of forming discrete-time statistics: chip-matched filtering and oversampling. © 2006 IEE
Keywords: Asynchronous code-division multiple-access (CDMA); Channel capacity; Effective interference; Minimum mean-square error (MMSE) detector; Multistage detector; Multiuser detection; Random matrix theory; Random spreading sequences

A systematic approach to multistage detectors in multipath fading channels - Cottatellucci, Laura; Müller, Ralf (IEEE Transactions on Information Theory, 2005)
We consider linear multistage detectors with universal (large system) weighting for synchronous code-division multiple access (CDMA) in multipath fading channels with many users. A convenient choice of the basis of the projection subspace allows a joint projection of all users. Taking advantage of this property, the complexity per bit of multistage detectors with universal weights scales linearly with the number of users on the uplink CDMA channel, while other known multistage detectors with universal weights and different bases of the projection subspace keep the same quadratic complexity order per bit as the linear minimum mean-square error (LMMSE) detector. We focus on the design of two kinds of detectors with linear complexity. The detector of Type I is obtained as an asymptotic approximation of the polynomial expansion detector proposed by Moshavi et al. The detector of Type II has the same performance as the multistage Wiener filter (MSWF) in large systems. Additionally, general performance expressions for large systems, applicable to any multistage detector with the same basis of the projection subspace (e.g., linear parallel interference canceling detectors), are derived. As a by-product, the performance analysis disproves the widespread belief that the MSWF and the polynomial expansion detector are equivalent. We show that, in general, the MSWF outperforms the latter one and they are equivalent only asymptotically in the case of equal received powers. © 2005 IEEE.
Keywords: Asymptotic weight; Code-division multiple-access (CDMA) system; Multipath fading channel; Multistage detector; Multistage Wiener filter (MSWF); Multiuser detection; Polynomial expansion detector; Random matrix; Random spreading

A System Concept for Online Calibration of Massive MIMO Transceiver Arrays for Communication and Localization - Gröschel, Patrick; Zarei, Shahram; Carlowitz, Christian; Lipka, Melanie; Sippel, Erik; Ali, Arslan; Weigel, Robert; Schober, Robert; Vossiek, Martin (IEEE Transactions on Microwave Theory and Techniques, 2017)
Massive multiple-input multiple-output (MIMO) techniques are being considered for the fifth generation (5G) mobile communication systems in order to deliver high multiplexing gain. However, hardware impairments like quadrature imbalance in mixers violate the requirement for channel reciprocity and may change, e.g., with temperature or while aging. In addition, advanced wireless localization techniques and the generation of predefined beam patterns require knowledge about all antenna phase center positions and the time and phase delay of all transmit and receive channels. Thus, an efficient online compensation method is needed that scales well for very large numbers of transceiver modules. We propose to extend the transmitter with a small measurement feature at the transmitter output based on one uncalibrated power detector per module as well as a single, external four-element backscatter array for the entire matrix. These enhancements facilitate a fast and efficient iterative calibration, which recognizes and mitigates all major error sources. Beside optimal communication throughput and energy efficiency, it thereby brings localization capabilities to mobile networks as an additional major benefit. For verification, a system of multiple cost-efficient 5.8-GHz massive MIMO transceivers with 150-MHz bandwidth and a backscatter array has been implemented. Measurement results demonstrate the capability of the proposed concept to efficiently compensate major error sources as well as its robustness.
elib2cris::1512001600,groeschel2017
Keywords: Backscatter transponder (BT); calibration; fifth generation (5G) mobile communication; massive multiple-input multiple-output (MIMO); wireless localization

A Tractable Framework for Coverage Analysis of Cellular-Connected UAV Networks - Yu, Xianghao; Zhang, Jun; Schober, Robert; Letaief, Khaled B. (2019 IEEE International Conference on Communications Workshops (ICC Workshops), 2019)
Unmanned aerial vehicles (UAVs) have recently found abundant applications in the public and civil domains. To ensure reliable control and navigation, connecting UAVs to controllers via existing cellular network infrastructure, i.e., ground base stations (GBSs), has been proposed as a promising solution. Nevertheless, it is highly challenging to characterize the communication performance of cellular-connected UAVs, due to their unique propagation conditions. This paper proposes a tractable framework for the coverage analysis of cellular-connected UAV networks, which consists of a new blockage model and an effective approach to handle general fading channels. In particular, a line-of-sight (LoS) ball model is proposed to capture the probabilistic propagation in UAV communication systems, and a tractable expression is derived for the Laplace transform of the aggregate interference with general Nakagami fading. This framework leads to a tractable expression for the coverage probability, which in turn helps to investigate the impact of the GBS density. Specifically, a tight lower bound on the optimal density that maximizes the coverage probability is derived. Numerical results show that the proposed LoS ball model is accurate, and the optimal GBS density decreases when the UAV altitude increases.<br

A tutorial to orthogonal time frequency space modulation for future wireless communications - Li, Shuangyang; Yuan, Weijie; Wei, Zhiqiang; He, Ruisi; Ai, Bo; Bai, Baoming; Yuan, Jinhong (2021 IEEE/CIC International Conference on Communications in China, ICCC Workshops 2021, 2021)
The recently proposed orthogonal time frequency space (OTFS) modulation has demonstrated superior performances over the conventional orthogonal frequency-division multiplexing (OFDM) modulation. In this paper, we provide a tutorial to the OTFS modulation for future wireless communications. We first revisit the properties of the wireless channels and then introduce the OTFS system models. In particular, we also discuss the characteristics of OTFS signals over different domains. Based on the OTFS characteristics, we briefly discuss the performances of OTFS modulation, including the performances of diversity and coding gain, channel estimation, and detection. Finally, we provide a discussion regarding the potential applications of OTFS modulation for wireless communications, where the research challenges are also highlighted.
CRIS-Team Scopus Importer:2021-12-03

A Unifying Model for External Noise Sources and ISI in Diffusive Molecular Communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2014)
This paper considers the impact of external noise sources, including interfering transmitters, on a diffusive molecular communication system, where the impact is measured as the number of noise molecules expected to be observed at a passive receiver. A unifying model for noise, multiuser interference, and intersymbol interference is presented, where, under certain circumstances, interference can be approximated as a noise source that is emitting continuously. The model includes the presence of advection and molecule degradation. The time-varying and asymptotic impact is derived for a series of special cases, some of which facilitate closed-form solutions. Simulation results show the accuracy of the expressions derived for the impact of a continuously-emitting noise source, and show how approximating old intersymbol interference as a noise source can simplify the calculation of the expected bit error probability of a weighted sum detector.<br
Keywords: Noise measurement; Receivers; Transmitters; Interference; Degradation; Detectors; Molecular communication

Autocorrelation Based Detection of Multicarrier Signals with Periodic Power Boosting - Karunakaran, Prasanth; Gerstacker, Wolfgang (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2018)
Given the prevalence of multicarrier waveforms in wireless systems, the sensing of such signals is of high importance for cognitive radio applications. In this work, we exploit periodic power boosting of subcarriers in multicarrier signals which is applied e.g. in LTE to improve the performance of sensing compared to state-of-the-art schemes under practical scenarios where noise uncertainties are present. First, we establish an analytical connection between the subcarrier power distribution and the autocorrelation function of a general multicarrier signal. Second, using this result, we demonstrate that periodic power boosting causes strong peaks in the magnitude of the autocorrelation function. The obtained analytical results match well with over-the-air measurement results corresponding to an orthogonal frequency division multiplexing (OFDM) signal of an LTE transmission. Here, the measurements indicate the presence of a boosting with a period of three subcarriers in the LTE signal which arises due to the cell-specific reference signals. Subsequently, a sensing algorithm exploiting the special features of the autocorrelation function resulting from periodic power boosting is developed which outperforms energy detection under realistic noise uncertainties and a state-of-the-art method that relies only on the cyclic prefi

Average Harvested Power in THz WPT Systems Employing Resonant-Tunnelling Diodes - Shanin, Nikita; Clochiatti, Simone; Mayer, Kenneth; Cottatellucci, Laura; Weimann, Nils; Schober, Robert (2023 6th International Workshop on Mobile Terahertz Systems, IWMTS 2023, 2023)
In this paper, we study terahertz (THz) wireless power transfer (WPT) systems, where a single-antenna transmitter sends an energy signal to a single-antenna receiver. Since Schottky diodes, which are utilized in GHz energy harvesting (EH) circuits, are not usable for THz EH, we adopt an EH circuit employing a resonant tunnelling diode (RTD) at the receiver. However, the electrical properties of Schottky diodes and RTDs are different, and unlike EH receivers based on a single Schottky diode, an accurate EH model for RTD-based EH receivers is not available. Therefore, we model the dependency between the instantaneous harvested power at the EH device and the instantaneous received power by a piecewise non-linear function, whose parameters are adjusted to fit circuit simulation data. We formulate an optimization problem for the maximization of the average power harvested at the EH receiver subject to constraints imposed on the average and peak transmit powers. Then, for the solution of the formulated problem, we propose an equivalent monotonic EH model and we show that the optimal transmit signal distribution for WPT employs at most two mass points, which can be obtained as the solution of a min-max optimization problem. Our simulation results reveal that RTDs with low leakage currents and high breakdown voltages are preferable for WPT when the received signal power is low and high, respectively. Furthermore, we demonstrate that the proposed optimal input distribution yields significantly higher average harvested powers compared to a baseline scheme employing Gaussian transmit signals.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Schottky diodes; Simulation; Circuit simulation; RLC circuits; Receivers; Wireless power transfer; Resonant tunneling devices

A Widely Linear DF-MMSE Receiver for DS-CDMA with BPSK Modulation - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (Conference Proceedings, 2003)
In this paper, we propose a widely linear (WL) decision-feedback (DF) minimum mean-squared error (MMSE) receiver for direct-sequence code-division multiple access (DS-CDMA) with binary phase-shift keying (BPSK) modulation. Both theoretical considerations and simulations show that the novel receiver yields significant performance gains over both WL receivers without feedback and conventional DF receivers. In particular, the proposed WL DF-MMSE receiver achieves a high performance even in overloaded systems. For efficient adaptation of the filter coefficients a WL least-mean-square (LMS) algorithm and a WL recursive least-squares (RLS) algorithm are devised.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.mobilk.awidel
Keywords: Binary phase shift keying; Direct-sequence code-division multiple Access; Multiaccess communication; Phase shift keying; Phase Modulation; Modulation coding; Performance gain; Feedback; Filters; Least squares approximation

A Widely Linear LMS Algorithm for MAI Suppression for DS-CDMA - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (Conference Proceedings, 2003)
In this paper, a novel data-aided stochastic gradient algorithm for adjustment of the widely linear (WL) minimum mean-squared error (MMSE) filter for multiple access interference (MAI) suppression for direct-sequence code-division multiple access (DS-CDMA) is introduced and analyzed. We give analytical expressions for the steady-state signal-to-interference-plus-noise ratio (SINR) of the proposed WL least-mean-square (LMS) algorithm, and we also investigate its speed of convergence. Both analytical considerations and simulations show in good agreement the superiority of the novel WL adaptive algorithm. Nevertheless, the computational complexity of the proposed algorithm is lower than that of the linear LMS algorithm.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.mobilk.awidel_3
Keywords: Least squares Approximation; Multiaccess communication; Multiple access interference; Algorithm design and Analysis; Stochastic processes; Nonlinear filters; Direct-sequence code-division multiple Access; Signal Analysis; Steady-state; Signal to noise ratio

A Wireless Joint Communication and Localization EMG-Sensing Concept for Movement Disorder Assessment - Brückner, Stefan; Weber, Jasmin; Michler, Fabian; Shanin, Nikita; Schober, Robert; Hagelauer, Amelie; Weigel, Robert; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Vossiek, Martin (IEEE Journal of Electromagnetics, RF and Microwaves in Medicine and Biology, 2023)
Real-time sensory recording of the musculoskeletal system function is an important tool for the diagnosis, treatment planning, and optimal treatment execution of diseases, such as Parkinson's disease and osteoarthritis. This article presents a new wireless joint communication and localization electromyography (EMG)-sensing concept. An on-body sensor beacon measures EMG signals and wirelessly transmits them. At the same time, the spatial position and movement of the beacon is determined with high precision in real time using these transmitted radio signals. The seamless integration of multiple sensors avoids the need to synchronize and individually set up multiple independently operating sensors. An outstanding feature of the radio localization approach is that it does not require proprietary ultra-wideband signals or complicated time synchronization protocols, allowing for small and energy-efficient implementation. To demonstrate this novel concept, a wireless 3D-localizable EMG sensor was developed and experimentally evaluated. This new type of sensing concept allows, for the first time, the time-synchronous measurement of muscle activity and the underlying movement of the associated body part. URL: https://ieeexplore.ieee.org/stamp/stamp.jsp?tp=&arnumber=10286030&isnumber=8000303<br
Keywords: Array signal processing; EMG; localization; radar tracking; radio communication

Bayesian Inference with Nonlinear Generative Models: Comments on Secure Learning - Bereyhi, Ali; Loureiro, Bruno; Krzakala, Florent; Müller, Ralf; Schulz-Baldes, Hermann (IEEE Transactions on Information Theory, 2023)
Unlike the classical linear model, nonlinear generative models have been addressed sparsely in the literature of statistical learning. This work aims to shed light on these models and their secrecy potential. To this end, we invoke the replica method to derive the asymptotic normalized cross entropy in an inverse probability problem whose generative model is described by a Gaussian random field with a generic covariance function. Our derivations further demonstrate the asymptotic statistical decoupling of the Bayesian estimator and specify the decoupled setting for a given nonlinear model. The replica solution depicts that strictly nonlinear models establish an all-or-nothing phase transition: there exists a critical load at which the optimal Bayesian inference changes from perfect to an uncorrelated learning. Based on this finding, we design a new secure coding scheme which achieves the secrecy capacity of the wiretap channel. This interesting result implies that strictly nonlinear generative models are perfectly secured without any secure coding. We justify this latter statement through the analysis of an illustrative model for perfectly secure and reliable inference.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Bayes methods; Bayesian inference; decoupling principle; Encoding; Gaussian random fields; Glass; Information theory; information-theoretically secure learning; Load modeling; Nonlinear generative models; Nonlinear optics; replica method; Statistical learning

Beamforming Design for Active IRS-Aided MIMO Integrated Sensing and Communication Systems - Li, Jin; Zhou, Gui; Gong, Tantao; Liu, Nan (IEEE Wireless Communications Letters, 2023)
This paper investigates active intelligent reconfigurable surface (IRS)-aided MIMO integrated sensing and communication (ISAC) systems. Different from passive IRS, an active IRS with amplifiers is deployed to overcome the product attenuation caused by the reflection of the IRS. We aim to maximize IRS beampattern towards the direction of a point sensing target, while guaranteeing the quality of service (QoS) requirement of the communication user. The target is sensed by the reflected sensing link, and the user can receive communication signals from both the direct link and the reflected link. To solve the formulated problem with coupled variables, an alternating optimization algorithm is proposed. Approximations such as the majorization-minimization (MM) method is used to tackle the BS beamforming subproblem, while some matrix transformations, the semidefinite relaxation and the Gaussian randomization method is applied to solve the reflection coefficient subproblem. Numerical results demonstrate that active IRS can greatly improve the sensing performance compared to passive IRS.
CRIS-Team Scopus Importer:2023-07-28
Keywords: active intelligent reconfigurable surface (IRS); Array signal processing; beamforming; Integrated sensing and communication (ISAC); Linear programming; majorization-minimization (MM); MIMO communication; Optimization; Radar; semidefinite relaxation (SDR); Sensors; Wireless sensor networks

Beamforming Design for Intelligent Reflecting Surface-Enhanced Symbiotic Radio Systems - Hu, Shaokang; Liu, Chang; Wei, Zhiqiang; Cai, Yuanxin; Kwan Ng, Derrick Wing; Yuan, Jinhong (IEEE International Conference on Communications, 2022)
This paper investigates multiuser multi-input single-output downlink symbiotic radio communication systems assisted by an intelligent reflecting surface (IRS). Different from existing methods ideally assuming the secondary user (SU) can jointly decode information symbols from both the access point (AP) and the IRS via multiuser detection, we consider a more practical SU that only non-coherent detection is available. To characterize the non-coherent decoding performance, a practical upper bound of the average symbol error rate (SER) is derived. Subsequently, we jointly optimize the beamformer at the AP and the phase shifts at the IRS to maximize the average sum-rate of the primary system taking into account the maximum tolerable SER constraint for the SU. To circumvent the couplings of variables, we exploit the Schur complement that facilitates the design of a suboptimal beamforming algorithm based on successive convex approximation. Our simulation results show that compared with various benchmark algorithms, the proposed scheme significantly improves the average sum-rate of the primary system, while guaranteeing the decoding performance of the secondary system.
CRIS-Team Scopus Importer:2022-09-16

Beamforming design for secure SWIPT systems under a non-linear energy harvesting model - Boshkovska, Elena; Zlatanov, Nikola; Chen, Xiaoming; Ng, Derrick Wing Kwan; Schober, Robert (Energy Harvesting for Wireless Sensor Networks: Technology, Components and System Design, 2018)
Simultaneous wireless information and power transfer (SWIPT) is an appealing solution to extend the lifetime of wireless nodes and, hence, alleviate the energy bottleneck of energy-constrained wireless communication networks. SWIPT advocates the dual use of radio frequency signals for conveying information and energy concurrently, which introduces a paradigm shift in system design. This chapter focuses on the use of multiple antennas to improve the efficiency of wireless power transfer (WPT) and secure information transmission. In particular, our objective is to maximize the secrecy rate of a SWIPT system via beamforming. To this end, we formulate a non-convex optimization problem based on a practical nonlinear energy harvesting model. The problem formulation allows for the use of an energy signal to improve WPT efficiency and to provide communication security. The globally optimal solution of the design problem is obtained via a one-dimensional search and semidefinite programming (SDP) relaxation. Numerical results demonstrate that the proposed design can achieve a significant gain in secrecy rate compared to two baseline schemes.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Beamforming; Nonlinear energy harvesting; Secure communication; Wireless information and power transfer

Beamforming for Cooperative Retransmission via User Relaying in Multiple-Antenna Cellular Systems - Ryu, Jong Yeol; Choi, Wan; Kim, Dong In; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
We propose a novel cooperative user relaying scheme for a two-user multiple-antenna downlink cellular system where each user has to receive a certain required amount of information. A user who successfully receives its required amount of information is supposed to help the other user in receiving its required amount of information through cooperative user relaying. For the proposed cooperative user relaying scheme, we jointly design linear beamformers at the base station over three transmission phases to minimize the total transmission time required for both users to receive their respective required amounts of information, which turn out to be approximated equivalent to the maximization of the sum throughput. In addition, considering a practical hybrid automatic repeat request (HARQ) protocol with user relaying, we modify the proposed scheme to minimize the required number of retransmissions. Our numerical results show that the proposed cooperative user relaying scheme achieves substantial gains over conventional transmission without user relaying in terms of both the average sum throughput and the transmission failure probability.<br
Keywords: Antennas; Throughput; Array signal processing; Silicon carbide; Downlink; Relays; Wireless communication

Beamforming for Energy Efficient Multiuser MIMO SC-FDMA Transmission with QoS Requirements - Gerstacker, Wolfgang; Ruder, Michael (IEEE Communications Letters, 2014)
In this letter we consider beamforming (BF) with per user Quality of Service (QoS) requirements for a single-carrier frequency-division multiple-access (SC-FDMA) transmission employing a linear equalizer at the receiver. A virtual multiple-input multiple-output (V-MIMO) uplink transmission with user pairing is studied. The problem of finding the optimum BF filter coefficients that minimize the transmit power is addressed. It is shown that the optimum solution for a given data rate requirement can be analytically determined for zero-forcing (ZF) equalization, which results in an expression related to the solution available for optimum transmitter-receiver design assuming conventional linear modulation. The transmit power savings of BF compared to constant power allocation (CPA) for all subcarriers are analyzed for user pairing in the uplink of LTE. Additionally, BF for minimum mean-squared error (MMSE) equalization is investigated, for which it turns out that a numerical search algorithm has to be used for coefficient optimization. Numerical results show that the transmit power can be significantly reduced with the proposed BF schem

Beamforming for Magnetic Induction based Wireless Power Transfer Systems with Multiple Receivers - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE Global Communications Conference (Globecom), 2015)

Beamforming for SC-FDMA transmission over MIMO ISI channels with decision-feedback equalization - Dang, Thi Uyen Ly; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2010 International ITG Workshop on Smart Antennas (WSA), 2010)
We consider transmit beamforming algorithms for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filters are designed for optimum performance of MIMO minimum mean-squared error decision-feedback equalization (MMSE-DFE). It turns out that eigenbeamforming diagonalizing the overall channel is optimum, and in addition an optimum power allocation has to be performed which is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Yang and Roy. Simulation results indicate that the proposed solution is beneficial for the block error rate performance of an SC-FDMA transmission scheme with strong channel coding and error-free decisions in the feedback path of MMSE-DFE, which can be guaranteed e.g. by equivalent Tomlinson-Harashima precoding at the transmitter sid

Bias-based training for iterative channel estimation and data decoding in fast fading channels - Takeuchi, Keigo; Müller, Ralf; Vehkapera, Mikko (IEICE Transactions on Communications, 2011)
A novel signaling scheme is proposed for iterative channel estimation and data decoding in fast fading channels. The basic idea is to bias the occurrence probability of transmitted symbols. A priori information about the bias is utilized for channel estimation. The bias-based scheme is constructed as a serially concatenated code, in which a convolutional code and a biased nonlinear block code are used as the outer and inner codes, respectively. This construction allows the receiver to estimate channel state information (CSI) efficiently. The proposed scheme is numerically shown to outperform conventional pilot-based schemes in terms of spectral efficiency for moderately fast fading channels. Copyright © 2011 The Institute of Electronics, Information and Communication Engineers.
Keywords: Belief propagation; Bias-based channel estimation; Fast fading channels; Iterative decoding

Bidirectional Buffer-Aided Relay Networks With Fixed Rate Transmission—Part II: Delay-Constrained Case - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
This is the second part of a two-part paper considering bidirectional relay networks with half-duplex nodes and block fading where the nodes transmit with a fixed transmission rate. In Part I, it was shown that a considerable gain in terms of sum throughput can be obtained by optimally selecting the transmission modes or, equivalently, the states of the nodes, i.e., the transmit, the receive, and the silent states, based on the qualities of the involved links. To enable adaptive transmission mode selection, the relay has to be equipped with two buffers for storage of the data received from the two users. The protocol proposed in Part I was delay unconstrained and provides an upper bound for the performance of practical delay-constrained protocols. In this paper, we propose two heuristic but efficient delay-constrained protocols, which can approach the performance upper bound reported in Part I, even in cases where only a small delay is permitted. The proposed protocols not only consider the instantaneous qualities of the involved links for adaptive mode selection but also take the states of the queues at the buffers into account, i.e., the number of packets in the queues. The average throughput and the average delay of the proposed delay-constrained protocols are evaluated by analyzing the Markov chain of the states of the queues. Numerical results show that the proposed protocols outperform existing bidirectional relaying protocols for delay-constrained transmission. <br
Keywords: Protocols; Delays; Throughput; Markov processes; Signal to noise ratio; Relay networks (telecommunications)

Bilinear Expectation Propagation for Distributed Semi-Blind Joint Channel Estimation and Data Detection in Cell-Free Massive MIMO - Karataev, Alexander; Forsch, Christian; Cottatellucci, Laura (IEEE Open Journal of Signal Processing, 2024)
We consider a cell-free massive multiple-input multiple-output (CF-MaMIMO) communication system in the uplink transmission and propose a novel algorithm for blind or semi-blind joint channel estimation and data detection (JCD). We formulate the problem in the framework of bilinear inference and develop a solution based on the expectation propagation (EP) method for both channel estimation and data detection. We propose a new approximation of the joint a posteriori distribution of the channel and data whose representation as a factor graph enables the application of the EP approach using the message-passing technique, local low-complexity computations at the nodes, and an effective modeling of channel-data interplay. The derived algorithm, called bilinear-EP JCD, allows for a distributed implementation among access points (APs) and the central processing unit (CPU) and has polynomial complexity. Our simulation results show that it outperforms other EP-based state-of-the-art polynomial time algorithms.
CRIS-Team Scopus Importer:2024-02-09
Keywords: approximate inference; Bayesian learning; bilinear inference; cell-free massive MIMO; distributed algorithms; Expectation propagation; joint channel estimation and data detection

Biological Optical-to-Chemical Signal Conversion Interface: A Small-scale Modulator for Molecular Communications - Grebenstein, Laura; Kirchner, Jens; Stavracakis Peixoto, Renata; Zimmermann, Wiebke; Wicke, Wayan; Ahmadzadeh, Arman; Jamali, Vahid; Fischer, Georg; Weigel, Robert; Burkovski, Andreas; Schober, Robert (ACM NANOCOM 2018: 5TH ACM INTERNATIONAL CONFERENCE ON NANOSCALE COMPUTING AND COMMUNICATION, 2018)
CRIS-Team WoS Importer:2019-02-22

Biological Optical-to-Chemical Signal Conversion Interface: A Small-scale Modulator for Molecular Communications - Grebenstein, Laura; Kirchner, Jens; Stavracakis Peixoto, Renata; Zimmermann, Wiebke; Irnstorfer, Florian; Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Fischer, Georg; Weigel, Robert; Burkovski, Andreas; Schober, Robert (IEEE Transactions on Nanobioscience, 2018)
Although many exciting applications of molecular communication (MC) systems are envisioned to be at microscale, the MC testbeds reported in the literature so far are mostly at macroscale. This may partially be due to the fact that controlling an MC system at microscale is challenging. To link the macroworld to the microworld, we propose and demonstrate a biological signal conversion interface that can also be seen as a microscale modulator. In particular, the proposed interface transduces an optical signal, which is controlled using a light-emitting diode (LED), into a chemical signal by changing the pH of the environment. The modulator is realized using Escherichia coli bacteria as microscale entity expressing the light-driven proton pump gloeorhodopsin from Gloeobacter violaceus. Upon inducing external light stimuli, these bacteria locally change their surrounding pH level by exporting protons into the environment. To verify the effectiveness of the proposed optical-to-chemical signal converter, we analyze the pH signal measured by a pH sensor, which serves as receiver. We develop an analytical parametric model for the induced chemical signal as a function of the applied optical signal. Using this model, we derive a training-based channel estimator which estimates the parameters of the proposed model to fit the measurement data based on a least square error approach. We further derive the optimal maximum likelihood detector and a suboptimal low-complexity detector to recover the transmitted data from the measured received signal. It is shown that the proposed parametric model is in good agreement with the measurement data. Moreover, for an example scenario, we show that the proposed setup is able to successfully convert an optical signal representing a sequence of binary symbols into a chemical signal with a bit rate of 1 bit/min and recover the transmitted data from the chemical signal using the proposed estimation and detection schemes. The proposed modulator may form the basis for future MC testbeds and applications at microscale.
Keywords: Microorganisms; Protons; Biomedical optical Imaging; Optical pumping; Optical Receivers; Optical sensors; Chemicals

Bit-interleaved coded modulation for phase shift keying on the hypersphere - Rachinger, Christoph; Müller, Ralf; Huber, Johannes (IEEE International Symposium on Information Theory, 2017)

Blanking Gaps in Uplink Cellular UMTS in the IMT-2000 Extension Band to Solve the Bluetooth Coexistence Problem - Konrad, Markus; Koch, Wolfgang (Conference Proceedings, 2006)
According to the ECC-PT1 the UMTS (Universal Mobile Telecommunications System) FDD (Frequency Division Duplex) uplink in the 2500-2690 MHz extension band starts at 2500 MHz. Bluetooth (BT) is operated in the 2.4 GHz ISM (Industrial, Scientific, and Medical) band. In [1] we have demonstrated that RF blocking is a severe source of interference to the BT technology if both technologies are co-located within the same terminal. Observing that Bluetooth devices transmit short packets followed by long transmission gaps and using the knowledge that the channel coded UMTS uplink spread spectrum signal is inherently robust to short gaps, we introduce the concept of UMTS uplink blanking gaps which refers to switching off the uplink transmission during mobile terminal BT reception as a solution to preventing RF receiver blocking by exploiting convolutions! coding (CC) and interleaving. By means of link level simulations the authors demonstrate that the loss due to blanking is comparable to the ĒB/N0 loss of UMTS compressed mode for both 12.2 kbit/s speech and 64.0 kbit/s data services and thus a reasonable solution to ensure coexistence. ©2006 IEEE.
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.mobilk.blanki
Keywords: Blanking; 3G mobile communication; Bluetooth; Radio frequency; Frequency conversion; Cellular networks; Radiofrequency interference; Spread spectrum communication; RF Signals; Robustness

Blind Channel Order Estimation Based on Second-Order Statistics - Gerstacker, Wolfgang; Taylor, Desmond (IEEE Signal Processing Letters, 2003)
For many existing blind channel estimation algorithms, accurate estimates of the channel order are a prerequisite. A novel scheme for blind channel order estimation using exclusively second-order statistics of the received signal is proposed, which can be embedded in channel estimation and is based on the examination of an indicator function constructed from initial channel estimates with overestimated order. It is demonstrated that significantly better order estimates can be obtained than by information-theoretic criteria like the minimum description length criterion.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.mobilk.blindc
Keywords: Blind channel estimation; Order determination; Second-order statistics

Blind Estimation of the Carrier Powers and SNRs in PCMA Satellite Signals by Cyclic Statistics - Feder, Andreas; Hirschbeck, Martin; Gerstacker, Wolfgang (Proceedings of the Military Communications Conference (MILCOM), MILCOM 2022 - 2022 IEEE, 2022)
A blind receiver for PCMA signals aims to detect the data symbols of the two carrier signals contained in the received aggregate signal. In order to execute a multi-user detection or sequence estimation scheme, the receiver needs to obtain knowledge on several signal and channel parameters. With the symbol rate, carrier frequencies and modulation schemes assumed to be known from prior processing steps, a blind estimation method for the powers of the carrier signals, and their respective individual signal-to-noise ratios, is proposed in this paper. The approach is based on the estimation of statistical features of the received signal that are selective w.r.t. the noise and the respective carrier signals by exploiting a sufficient deviation of their frequency offsets from each other. In particular, the cyclic correlation and the cyclic cumulants are estimated and used to infer the powers. Numerical simulation results demonstrate the usefulness of the proposed schem

Blind pilot decontamination - Müller, Ralf; Cottatellucci, Laura; Vehkapera, Mikko (IEEE Journal of Selected Topics in Signal Processing, 2014)
A subspace projection to improve channel estimation in massive multi-antenna systems is proposed and analyzed. Together with power-controlled hand-off, it can mitigate the pilot contamination problem without the need for coordination among cells. The proposed method is blind in the sense that it does not require pilot data to find the appropriate subspace. It is based on the theory of large random matrices that predicts that the eigenvalue spectra of large sample covariance matrices can asymptotically decompose into disjoint bulks as the matrix size grows large. Random matrix and free probability theory are utilized to predict under which system parameters such a bulk decomposition takes place. Simulation results are provided to confirm that the proposed method outperforms conventional linear channel estimation if bulk separation occurs.
Keywords: channel estimation; eigenvalue spectrum; free probability; massive MIMO; Multiple antennas; multiple-input multiple-output (MIMO) systems; principal component analysis; random matrices; spread-spectrum

Blind pilot decontamination - Müller, Ralf; Vehkaperä, Mikko; Cottatellucci, Laura (7th Int’l ITG Workshop on Smart Anten- nas, 2013)

Blind pilot decontamination in massive MIMO by independent component analysis - Amiri, Ebrahim; Müller, Ralf; Gerstacker, Wolfgang (IEEE Global Communications Conference, 2017)

Blind Symbol Rate and Frequency Offset Estimation for PCMA Signals via Cyclic Correlations - Feder, Andreas; Wicke, Wayan; Hirschbeck, Martin; Gerstacker, Wolfgang (Proceedings of the 2020 IEEE Global Communications Conference (GLOBECOM), 2020)
Many blind detection algorithms for paired carrier multiple access (PCMA) signals in satellite communications require information about the signal and channel parameters. A blind receiver needs to obtain knowledge of at least some of these prior to the symbol detection process. In this paper, schemes for the blind estimation of the symbol rates and carrier frequencies of the two overlapping co-channel signals in PCMA are proposed. The methods exploit the cyclic statistics of the PCMA signal for the estimation of the desired parameters. Effects of the mutual interference of the carriers in the estimation process are analyzed and the performance of the proposed methods is evaluated via numerical simulations.<br

Blind Symbol Timing and Carrier Phase Estimation for PCMA Satellite Signals via Cyclic Statistics - Feder, Andreas; Hirschbeck, Martin; Gerstacker, Wolfgang (GLOBECOM 2021 Proc. - Proceedings of the 2021 IEEE Global Communications Conference, 2021)
For the design of a blind receiver for paired carrier multiple access (PCMA) signals in satellite communications, several detection schemes have been proposed that require knowledge of the channel. In a frequency-nonselective environment, the overall channel is determined by the synchronization and transmit signal parameters of the respective carrier signals. In this paper, schemes for estimation of the carrier and symbol timing phases at the receiver are proposed, assuming that knowledge of the frequency offsets and symbol rate is obtained by previous estimations. Two different approaches for inferring the desired parameters are introduced. The proposed schemes exploit the cyclostationary nature of the respective carrier signals and the difference in their frequency offsets, and are based on estimates of the time-varying moments of the received signal and their cycle coefficients.<br
Keywords: Paired Carrier Multiple Access; Timing Phase Estimation; Carrier Phase Estimation; Blind Estimation; Cyclic Statistics

Blind upmix for applause-like signals based on perceptual plausibility criteria - Adami, Alexander; Brand, Lukas; Disch, Sascha; Herre, Jürgen (20th International Conference on Digital Audio Effects, DAFx 2017, 2017)
Vorträge und Veröffentlichungen auf Konferenzen_Applaus

Bounds on distance estimation via diffusive molecular communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
This paper studies distance estimation for diffusive molecular communication. The strength of the channel impulse response generally decreases with distance, so it is measured to estimate the distance. The Cramer-Rao lower bound on the variance of the distance estimation error is derived. The lower bound is derived for a physically unbounded environment with molecule degradation and steady uniform flow. The maximum likelihood distance estimator is derived and its accuracy is shown via simulation to perform very close to the Cramer-Rao lower bound. An existing protocol is shown to be equivalent to the maximum likelihood distance estimator if only one observation is made. Simulation results also show the accuracy of existing protocols with respect to the Cramer-Rao lower bound.<br
Keywords: Protocols; Maximum likelihood estimation; Degradation; Accuracy; Estimation error; Nanotechnology

Broadcast precoding for massive MIMO subject to an instantaneous total power constraint - Sedaghat, Mohammad A.; Müller, Ralf; Fischer, Georg (2014 IEEE Global Communications Conference, GLOBECOM 2014, 2014)
We design a new precoding scheme for massive multiple-input multiple-output (MIMO) systems subject to an instantaneous total power constraint. Unlike the classical way of designing precoders, we use a more realistic model for power amplifiers by considering their maximum power. The considered power constraint is applicable in the single-RF MIMO transmitter which has been proposed recently for massive MIMO systems. For sake of analysis, i.i.d. Gaussian signals are considered. It is shown that the designed precoding scheme results in a good performance in terms of signal to interference plus noise ratio (SINR) at the receivers and power efficiency at the transmitter. It is shown that the power efficiency utilizing this precoding scheme is almost equal to the case of constant envelope signals. Since the proposed precoding limits the total transmit power, there is no need for peak-to-average power ratio (PAPR) reduction algorithms.
Keywords: crest factor; massive MIMO; matching networks; Multiple antennas; multiple-input multiple-output (MIMO) systems; peak-to-average power ratio (PAPR)

Buffer-aided cooperative communications: Opportunities and challenges - Zlatanov, Nikola; Ikhlef, Aissa; Islam, Toufiqul; Schober, Robert (IEEE Communications Magazine, 2014)
Cooperative communication can increase the throughput and/or extend the coverage of wireless networks. However, in conventional cooperative networks, half-duplex relays transmit and receive under a prefixed schedule, which does not allow them to exploit the best receiving and transmitting channels, thus limiting performance. Recently, new protocols have been proposed that circumvent this problem by making use of the additional flexibility offered by relays with buffers. Compared to conventional relaying protocols, these buffer-aided protocols provide significant gains in terms of throughput, diversity, and signal-to-noise ratio. This article outlines several buffer-aided relaying protocols for different network topologies, including one-way single- and multi-relay networks as well as two-way single-relay networks. Moreover, some practical challenges inherent to buffer-aided relaying, such as increased delay and complexity, and topics for future research are discussed. Copyright © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Buffer-Aided Diamond Relay Network With Block Fading and Inter-Relay Interference - Simoni, Renato; Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert; Pierucci, Laura; Fantacci, Romano (IEEE Transactions on Wireless Communications, 2016)
A simple diamond half-duplex relay network composed of a source, two decode-and-forward half-duplex relays, and a destination is considered, where a direct link between the source and the destination does not exist. For this network, we study the case of buffer-aided relays, where the relays are equipped with buffers. Each relay can receive data from the source, store it in the buffer, and forward it to the destination, when the channel conditions are advantageous. Thereby, buffering enables adaptive scheduling of the transmissions and receptions over time, which allows the network to exploit the diversity offered by the fading channels. For the considered half-duplex network, four transmission modes are defined based on whether the relay nodes receive or transmit. In this paper, we derive the locally optimal scheduling of the transmission modes over time and investigate the achievable average rate, when the relays are affected by inter-relay interference. Since the proposed buffer-aided transmission policies introduce unbounded delay, we provide a sub-optimal buffer-aided transmission policy with limited delay. Moreover, for inter-relay interference cancellation, we consider two coding schemes with different complexities. In the first scheme, we employ dirty paper coding, which entails a high complexity, whereas in the second scheme, we adopt a low-complexity technique based on successive interference cancellation at the receiving relay nodes and optimal power allocation at the transmitting nodes. Our numerical results show that the proposed protocols, with and without delay constraints, outperform existing protocols for the considered network from the literature.<br
Keywords: Relays; Protocols; Interference; Diamond; Delays; Fading channels; Encoding

Buffer-Aided diamond relay network with block fading - Simoni, Renato; Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert; Pierucci, Laura; Fantacci, Romano (2015 IEEE International Conference on Communications (ICC), 2015)
A simple diamond half-duplex relay network composed of a source, two half-duplex relays, and a destination is considered, where no direct link between the source and the destination is exists. For this network, we investigate the achievable rate when the relays are equipped with buffers. Buffer-aided relays can receive data from the source, store it in their buffers, and forward it to the destination when the channel conditions are more advantageous. Thereby, buffering enables adaptive scheduling of the transmissions and receptions over time, which allows the network to better exploit the diversity offered by the fading channel. For the considered network, because of the half-duplex relays, four transmission modes are employed based on whether the relay nodes receive or transmit. Considering these four transmission modes, in this paper, we derive the optimal transmission mode selection policy such that the received data rate at the destination is maximized. Furthermore, based on numerical examples, we show that the proposed protocol outperforms the existing protocols for the considered network in the literature.<br
Keywords: Protocols; Delays; Fading; Diamonds; Relay networks (telecommunications); Signal to noise ratio

Buffer-aided half-duplex relaying can outperform ideal full-duplex relaying - Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2013)
We consider a three-node relay network comprised of a source, a relay, and a destination, and compare the throughputs of ideal full-duplex (FD) and half-duplex (HD) relaying. For FD relaying, we assume that the relay uses half of its antennas for reception and the other half for transmission. In contrast, for HD relaying, the relay uses all of its antennas for either reception or transmission and a buffer for data storage. Our results show that if the numbers of antennas at source and destination are equal to or larger than the number of antennas at the relay, HD relaying may achieve a similar, and in some cases even higher, throughput compared to ideal FD relaying. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: buffer-aided; full-duplex; Half-duplex; relaying

Buffer-aided relaying with adaptive link selection-fixed and mixed rate transmission - Zlatanov, Nikola; Schober, Robert (IEEE Transactions on Information Theory, 2013)
We consider a simple network consisting of a source, a half-duplex decode-and-forward relay with a buffer, and a destination. We assume that the direct source-destination link is not available and all links undergo fading. We propose two new buffer-aided relaying schemes with different requirements regarding the availability of channel state information at the transmitter (CSIT). In the first scheme, neither the source nor the relay has full CSIT, and consequently, both nodes are forced to transmit with fixed rates. In contrast, in the second scheme, the source does not have full CSIT and transmits with fixed rate but the relay has full CSIT and adapts its transmission rate accordingly. In the absence of delay constraints, for both fixed rate and mixed rate transmission, we derive the throughput-optimal buffer-aided relaying protocols which select either the source or the relay for transmission based on the instantaneous signal-to-noise ratios (SNRs) of the source-relay and relay-destination links. In addition, for the delay constrained case, we develop buffer-aided relaying protocols that achieve a predefined average delay. Compared to conventional relaying protocols, which select the transmitting node according to a predefined schedule independent of the instantaneous link SNRs, the proposed buffer-aided protocols with adaptive link selection achieve large performance gains. In particular, for fixed rate transmission, we show that the proposed protocol achieves a diversity gain of two as long as an average delay of more than three time slots can be afforded. Furthermore, for mixed rate transmission with an average delay of E{T} time slots, a multiplexing gain of r=1-1/(2E{T}) is achieved. As a by-product of the considered link-adaptive protocols, we also develop a novel conventional relaying protocol for mixed rate transmission, which yields the same multiplexing gain as the protocol with adaptive link selection. Hence, for mixed rate transmission, for sufficiently large average delays, buffer-aided half-duplex relaying with and without adaptive link selection does not suffer from a multiplexing gain loss compared to full-duplex relaying. © 1963-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Adaptive link selection; buffer-aided; delay; diversity gain; multiplexing gain; outage probability; relaying; throughput

Buffer-Aided Relaying with Adaptive Link Selection for Multihop Relay Networks - Shoukry, Hebatallah (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)

Buffer-Aided Relaying with Discrete Transmission Rates - Wicke, Wayan (2014)

Buffer-aided relaying with discrete transmission rates. - Wicke, Wayan; Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (Proc. CWIT, 2015)

Buffer-aided relaying with discrete transmission rates for the two-hop half-duplex relay network - Wicke, Wayan; Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)

Buffer-Aided Relaying with Imperfect CSI - Waly, Noha (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Cache-Aided Massive MIMO: Linear Precoding Design and Performance Analysis - Wei, Xiao; Xiang, Lin; Cottatellucci, Laura; Jiang, Tao; Schober, Robert (ICC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
In this paper, we propose a novel joint caching and massive multiple-input multiple-output (MIMO) transmission scheme, referred to as cache-aided massive MIMO, for advanced downlink cellular communications. In addition to reaping the conventional advantages of caching and massive MIMO, the proposed scheme also exploits the side information provided by cached files for interference cancellation at the receivers. This interference cancellation increases the degrees of freedom available for precoding design. In addition, the power freed by the cache-enabled offloading can benefit the transmissions to the users requesting non-cached files. The resulting performance gains are not possible if caching and massive MIMO are designed separately. We analyze the performance of cache-aided massive MIMO for cache-dependent maximum-ratio transmission (MRT), zero-forcing (ZF) precoding, and regularized zero-forcing (RZF) precoding. Lower bounds on the ergodic achievable rates are derived in closed form for MRT and ZF precoding. The ergodic achievable rate of RZF precoding is obtained for the case when the numbers of transmit antennas and users are large but their ratio is fixed. Compared to conventional massive MIMO, the proposed cache-aided massive MIMO scheme achieves a significantly higher ergodic rate especially when the number of users approaches the number of transmit antennas.<br
Keywords: MIMO communication; Precoding; Interference cancellation; Antennas; NOMA; Performance gain

Cache-aided non-orthogonal multiple access - Xiang, Lin; Ng, Derrick Wing Kwan; Ge, Xiaohu; Ding, Zhiguo; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2018)
In this paper, we propose a novel joint caching and non-orthogonal multiple access (NOMA) scheme to facilitate advanced downlink transmission for next generation cellular networks. In addition to reaping the conventional advantages of caching and NOMA transmission, the proposed cache-aided NOMA scheme also exploits cached data for interference cancellation which is not possible with separate caching and NOMA transmission designs. Furthermore, as caching can help to reduce the residual interference power, several decoding orders are feasible at the receivers, and these decoding orders can be flexibly selected for performance optimization. We characterize the achievable rate region of cache-aided NOMA and investigate its benefits for minimizing the time required to complete video file delivery. Our simulation results reveal that, compared to several baseline schemes, the proposed cache-aided NOMA scheme significantly expands the achievable rate region for downlink transmission, which translates into substantially reduced file delivery times.
CRIS-Team Scopus Importer:2020-01-31

Cache-Aided Non-Orthogonal Multiple Access: The Two-User Case - Xiang, Lin; Ng, Derrick Wing Kwan; Ge, Xiaohu; Ding, Zhiguo; Wong, Vincent W. S.; Schober, Robert (IEEE Journal of Selected Topics in Signal Processing, 2019)
In this paper, we propose a cache-aided non-orthogonal multiple access (NOMA) scheme for spectrally efficient downlink transmission. The proposed scheme not only reaps the benefits associated with NOMA and caching, but also exploits the data cached at the users for interference cancelation. As a consequence, caching can help to reduce the residual interference power, making multiple decoding orders at the users feasible. The resulting flexibility in decoding can be exploited for improved NOMA detection. We characterize the achievable rate region of cache-aided NOMA and derive the Pareto optimal rate tuples forming the boundary of the rate region. Moreover, we optimize cacheaided NOMA for minimization of the time required for completing file delivery. The optimal decoding order and the optimal transmit power and rate allocation are derived as functions of the cache status, the file sizes, and the channel conditions. Simulation results confirm that, compared to several baseline schemes, the proposed cache-aided NOMA scheme significantly expands the achievable rate region and increases the sum rate for downlink transmission, which translates into substantially reduced file delivery times.
CRIS-Team WoS Importer:2019-06-18

Cache-Aided Non-Orthogonal Multiple Access: The Two-User Case - Xiang, Lin; Ng, Derrick Wing Kwan; Ge, Xiaohu; Ding, Zhiguo; Wong, Vincent W.S.; Schober, Robert (IEEE Journal of Selected Topics in Signal Processing, 2019)
In this paper, we propose a cache-aided non-orthogonal multiple access (NOMA) scheme for spectrally efficient downlink transmission. The proposed scheme not only reaps the benefits associated with NOMA and caching, but also exploits the data cached at the users for interference cancelation. As a consequence, caching can help to reduce the residual interference power, making multiple decoding orders at the users feasible. The resulting flexibility in decoding can be exploited for improved NOMA detection. We characterize the achievable rate region of cache-aided NOMA and derive the Pareto optimal rate tuples forming the boundary of the rate region. Moreover, we optimize cache-aided NOMA for minimization of the time required for completing file delivery. The optimal decoding order and the optimal transmit power and rate allocation are derived as functions of the cache status, the file sizes, and the channel conditions. Simulation results confirm that, compared to several baseline schemes, the proposed cache-aided NOMA scheme significantly expands the achievable rate region and increases the sum rate for downlink transmission, which translates into substantially reduced file delivery times.<br
Keywords: NOMA; Decoding; Streaming media; Interference; Resource Management; Performance gain; Downlink

Cache-Enabled Physical Layer Security for Video Streaming in Backhaul-Limited Cellular Networks - Xiang, Lin; Ng, Derrick Wing Kwan; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Wireless Communications, 2017)
In this paper, we propose a novel wireless caching scheme to enhance the physical layer security of video streaming in cellular networks with limited backhaul capacity. By proactively sharing video data across a subset of base stations (BSs) through both caching and backhaul loading, secure cooperative joint transmission of several BSs can be dynamically enabled in accordance with the cache status, the channel conditions, and the backhaul capacity. Assuming imperfect channel state information (CSI) at the transmitters, we formulate a two-stage non-convex mixed-integer robust optimization problem for minimizing the total transmit power while providing the quality of service and guaranteeing communication secrecy during video delivery, where the caching and the cooperative transmission policy are optimized in an offline video caching stage and an online video delivery stage, respectively. Although the formulated optimization problem turns out to be NP-hard, low-complexity polynomial-time algorithms, whose solutions are globally optimal under certain conditions, are proposed for cache training and video delivery control. Caching is shown to be beneficial as it reduces the data sharing overhead imposed on the capacity-constrained backhaul links, introduces additional secure degrees of freedom, and enables a power-efficient communication system design. Simulation results confirm that the proposed caching scheme achieves simultaneously a low secrecy outage probability and a high power efficiency. Furthermore, due to the proposed robust optimization, the performance loss caused by imperfect CSI knowledge can be significantly reduced when the cache capacity becomes large.<br
Keywords: Streaming media; Wireless communication; Cellular networks; Communication system security; Quality of service; Robustness; Optimization

Can cooperation reduce the average transmitted power per participating user? - Michalopoulos, Diomidis S.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2013)
The answer is (in general) affirmative: For a given target bit error rate (BER), cooperation reduces the average transmitted power per user when partners are appropriately selected. The more cooperating users are available and the larger the propagation exponent, the larger the reduction on transmitted power per user. This conclusion is drawn from a preliminary study which considers a community of users located randomly along a straight line. The users communicate with a Base Station (BS) located at the end of this line, and the transmission is subject to path loss. The communication is established either directly (Direct Mode), or via another member of the community (Relaying Mode). We show that the total power needed to achieve a certain BER at the BS is on average lower for the Relaying Mode than for the Direct Mode, even without exploiting any receive diversity benefit. There exist cases, however, where the Relaying Mode is not beneficial. This is true for environments with a propagation exponent smaller than two (δ < 2). For δ = 2, the Relaying Mode performs identical to the Direct Mode. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Capacity complying MIMO channel models - Müller, Ralf; et al. (Conference Record of the Thirty-Seventh Asilomar Conference on Signals, Systems and Computers, 2003)
In [1], a unified framework for constructing MIMO models based on the principle of maximum entropy was provided. Several MIMO directional and double directional models were derived and in each case, the mutual information was shown to have asymptotically a Gaussian behavior. Interestingly, the results were shown to be accurate, through simulations, in the finite regime with an astonishing small number of antennas. In this paper, the models are analyzed and validated based on a wideband outdoor measurement campaign carried out in Oslo during summer 2002. The measurements were performed at a center frequency of 2.1 GHz with a bandwidth of 100 MHz in three different urban scenarios: a regular street grid scenario, an open city place and an indoor cell site.

Capacity of cellular CDMA systems applying interference cancellation and channel coding - Müller, Ralf; Huber, Johannes (Proceedings of the 1997 IEEE Global Telecommunications Mini-Conference, 1997)
Capacity of cellular CDMA applying interference cancellation is calculated for the uplink (reverse link) in the presence of AWGN. Both conventional demodulation and decorrelation are investigated as preprocessing unit to interference cancellation. Taking into account the path loss in a cellular system, CDMA applying interference cancellation shows a substantial difference in power efficiency, whether receive or transmit power is considered. This is in contrast to orthogonal multiple-access techniques, like TDMA and FDMA. If the comparison is based on transmit power, which is more reasonable, CDMA outperforms orthogonal multiple-access scheme

Capacity of the Gaussian Two-Hop Full-Duplex Relay Channel With Residual Self-Interference - Zlatanov, Nikola; Sippel, Erik; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we investigate the capacity of the Gaussian two-hop full-duplex (FD) relay channel with residual self-interference. This channel is comprised of a source, an FD relay, and a destination, where a direct source-destination link does not exist and the FD relay is impaired by residual self-interference. We adopt the worst case linear self-interference model with respect to the channel capacity, and model the residual self-interference as a Gaussian random variable whose variance depends on the amplitude of the transmit symbol of the relay. For this channel, we derive the capacity and propose an explicit capacity-achieving coding scheme. Thereby, we show that the optimal input distribution at the source is Gaussian and its variance depends on the amplitude of the transmit symbol of the relay. On the other hand, the optimal input distribution at the relay is discrete or Gaussian, where the latter case occurs only when the relay-destination link is the bottleneck link. The derived capacity converges to the capacity of the two-hop ideal FD relay channel without self-interference and to the capacity of the two-hop half-duplex (HD) relay channel in the limiting cases when the residual self-interference is zero and infinite, respectively. Our numerical results show that significant performance gains are achieved with the proposed capacity-achieving coding scheme compared with the achievable rates of conventional HD relaying and/or conventional FD relaying.

Capacity of the Gaussian Two-Hop Full-Duplex Relay Channel with Self-Interference - Zlatanov, Nikola; Sippel, Erik; Jamali, Vahid; Schober, Robert (2016 IEEE Global Communications Conference (GLOBECOM), 2016)
In this paper, we investigate the capacity of the Gaussian two-hop full-duplex (FD) relay channel with self-interference. This channel is comprised of a source, an FD relay, and a destination, where a direct source-destination link does not exist and the FD relay is impaired by self- interference. We model the self-interference as an additive Gaussian random variable whose variance is proportional to the amplitude of the transmit symbol at the relay. For this channel, we derive the capacity and propose an explicit capacity- achieving coding scheme. Thereby, we show that the optimal input distribution at the source is Gaussian and its variance depends on the amplitude of the transmit symbol at the relay. On the other hand, the optimal input distribution at the relay is discrete or Gaussian, where the latter case occurs only when the relay- destination link is the bottleneck link. The derived capacity converges to the capacity of the two-hop ideal FD relay channel without self- interference and to the capacity of the two-hop half-duplex (HD) relay channel in the limiting cases when the self-interference is zero and infinite, respectively. Our numerical results show that significant performance gains are achieved using the proposed capacity-achieving coding scheme compared to the achievable rates of conventional FD relaying and HD relayin
lhft_intern.bib::SipplE2016a

Capacity of the two-hop full-duplex relay channel with wireless power transfer from relay to battery-less source - Zlatanov, Nikola; Wing Kwan Ng, Derrick; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, we investigate a communication system comprised of a wireless sensor which harvests radio frequency (RF) energy from a full-duplex relay node and exploits this energy to transmit data to a destination node via the relay node. Thereby, the relay has two functions. Namely, it transfers RF energy to the sensor via wireless power transfer and relays the information received from the sensor to the destination. Moreover, we assume that the sensor is too small to be equipped with a battery. As a result, the energy of each symbol transmitted by the sensor is limited by the energy harvested during the previous symbol interval. For this system model, we derive the capacity for an average power constraint at the relay. Thereby, we show that in order to achieve the capacity, the sensor has to harvest the RF energy that reaches the sensor when the relay transmits information to the destination. As a result, the relay does not need to dedicate energy strictly for energy harvesting since the energy spent by the relay for information transfer can also be used by the sensor to harvest energy. In a numerical example, we compare the derived capacity to the rates of two benchmark schemes. Our results show that using the optimal input distributions at both the sensor and the relay is essential for high performance.<br
Keywords: Relays; Radio frequency; Wireless communication; Wireless sensor Networks; Batteries; AWGN channels; Sensors

Capacity of the Two-Hop Relay Channel With Wireless Energy Transfer From Relay to Source and Energy Transmission Cost - Zlatanov, Nikola; Wing Kwan Ng, Derrick; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we investigate a communication system comprised of an energy harvesting (EH) source, which harvests radio frequency (RF) energy from an out-of-band full-duplex relay node and exploits this energy to transmit data to a destination node via the relay node. We assume two scenarios for the battery of the EH source. In the first scenario, we assume that the EH source is not equipped with a battery and thereby cannot store energy. As a result, the RF energy harvested during one symbol interval can only be used in the following symbol interval. In the second scenario, we assume that the EH source is equipped with a battery having unlimited storage capacity in which it can store the harvested RF energy. As a result, the RF energy harvested during one symbol interval can be used in any of the following symbol intervals. For both system models, we derive the channel capacity subject to an average power constraint at the relay and an additional energy transmission cost at the EH source. We compare the derived capacities to the achievable rates of several benchmark schemes. Our results show that using the optimal input distributions at both the EH source and the relay is essential for high performance. Moreover, we demonstrate that neglecting the energy transmission cost at the source can result in a severe overestimation of the achievable performance.<br
Keywords: Relays; Batteries; Wireless communication; Radio frequency; AWGN channels; Channel models; Energy exchange

Capacity scaling in MIMO systems with general unitarily invariant random matrices - Çakmak, Burak; Müller, Ralf; Fleury, Bernard (IEEE Transactions on Information Theory, 2018)

CDMA systems with correlated spatial diversity: A generalized resource pooling result - Müller, Ralf; et al. (IEEE Transactions on Information Theory, 2007)
This correspondence analyzes the behavior of code-division multiple-access (CDMA) systems with correlated spatial diversity. The users transmit to one or more antenna arrays. The centralized receiver employs a linear multiuser detector. We derive the performance of a large system with random spreading sequences and weak assumptions on the flat-fading channel gains - the fading may be correlated and contain line-of-sight components. We show that, as the number of users and the spreading factor grow large with fixed ratio, the performance of the system is fully characterized by a square matrix with size equal to the number of receiving antennas and multiuser efficiencies are not identical for all users. Our general result includes the analysis of CDMA systems with spatial diversity discussed by Hanly and Tse ('01) for independent channel gains in case of both micro-diversity and macro-diversity and provides a rigorous proof for the macro-diversity case missing in their work. We also show that to any scenario with correlated Rayleigh fading, there exists a macro-diversity scenario with independent Rayleigh fading which is characterized by the same signal-to-interference-and-noise ratio (SINR). Furthermore, sufficient conditions are given which force the multiuser efficiencies of all users to become identical also in case of statistically dependent channel gains. © 2007 IEEE.
Keywords: Antenna array; Code-division multiple access (CDMA); Correlated channels; Large system analysis; Line-of-sight components; Multiuser detection; Random spreading; Resource pooling; Spatial diversity

CEPT SE7(18)102 Reference Values for RX Intermodulation - Gäde, Bernhard; Fischer, Georg (2018)
Keywords: Receiver Intermodulation; RX non-linearity; IIP3

CEPT SE7(18)103 Status of Seamcat IM plugin validation - Fischer, Georg; Gäde, Bernhard (2018)
Keywords: RX Intermodulation

CEPT SE7(18)105 Efficient frequency domain algorithms for calculation of RX Intermodulation - Gäde, Bernhard; Fischer, Georg (2018)
Keywords: RX Intermodulation; non-linear Circuit Technology; non-linear systems

CEPT SE7(18)106 Impact of LTE BS Activity Factor on TETRA RX Intermodulation - Gäde, Bernhard; Fischer, Georg (2018)
Keywords: RX Intermodulation; BS activity factor

Channel capacity and minimum probability of error in large dual antenna array systems with binary modulation - Müller, Ralf (IEEE Transactions on Signal Processing, 2003)
Uncoded bit error probability with maximum-likelihood detection and channel capacity is derived for binary signaling on the dual antenna array channel with constrained scattering in the large system limit making use of the replica method. Examples are discussed in case of equal power for all propagation paths. In case of poor scattering (or high load), a waterfall behavior of the uncoded bit error probability is observed.
Keywords: Channel capacity; Dual antenna arrays; Error probability; Limited scattering; MIMO systems; Replica method

Channel Capacity of Magnetic Induction Based Wireless Underground Sensor Networks under Practical Constraints - Kisseleff, Steven; Gerstacker, Wolfgang; Schober, Robert; Sun, Zhi; Akyildiz, Ian F. (IEEE Wireless Communications and Networking Conference (WCNC), 2013)

Channel Coding Rate for Finite Blocklength Faster-Than-Nyquist Signaling - Mohammadkarimi, Mostafa; Schober, Robert; Wong, Vincent W.S. (IEEE Communications Letters, 2021)
The fundamental tradeoff between low latency and high reliability makes the design of ultra-reliable low-latency communications (URLLC) wireless systems challenging. To support URLLC for a fixed bandwidth, faster-than-Nyquist (FTN) signaling is a promising approach since it increases the degrees of freedom (i.e., channel uses) per time interval, which can be exploited to improve reliability. In this letter, we derive analytical expressions for the approximate maximum channel coding rate (MCCR) for finite blocklength FTN signaling for water-filling and equal power allocations. We show that for practical non-sinc square-root Nyquist pulses, the penalty on the rate incurred due to the finite blocklength can be significantly reduced by non-orthogonal FTN transmission. Our results reveal that the MCCR for finite blocklength FTN signaling exceeds the Shannon capacity achieved for infinite blocklength and orthogonal transmission.
CRIS-Team Scopus Importer:2021-01-22
Keywords: channel dispersion; constrained channel capacity; Faster-than-Nyquist (FTN) signaling; finite blocklength

Channel Estimation and User Identification with Deep Learning for Massive Machine-Type Communications - Liu, Bryan; Wei, Zhiqiang; Yuan, Weijie; Yuan, Jinhong; Pajovic, Milutin (IEEE Transactions on Vehicular Technology, 2021)
In this paper, we investigate the detection problem for a massive machine-type communication (mMTC) system that has correlated user activities. Two deep learning assisted algorithms are proposed to exploit the user activity correlation to facilitate channel estimation and user identification. Due to the dependency among user activities, conventional element-wise minimum mean square error (MMSE) denoiser used in the orthogonal approximate message passing (OAMP) algorithm cannot achieve satisfying performance during the two-step iterative process. Therefore, we propose a deep learning modified OAMP (DL-mOAMP) algorithm, which iteratively modifies the user activity ratio via exploiting the user activity correlation in the MMSE denoiser based on the estimated sequence during each OAMP iteration. Moreover, given a specific false alarm probability, a constant threshold employed in the conventional user identification is not optimal in the presence of user activity correlation. Thus, we propose a neural network framework that is dedicated to the user identification (DL-mOAMP-UI algorithm), which minimizes the missed detection probability under a pre-determined false alarm probability. Numerical results show that the proposed DL-mOAMP algorithm provides a substantial mean squared error performance gain compared to the conventional OAMP algorithm and the DL-mOAMP-UI algorithm can further improve the user identification accuracy of an mMTC system.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Compressed sensing; deep learning; massive machine-type communications

Channel Estimation for Diffusive Molecular Communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Jardin, Christophe; Sticht, Heinrich; Schober, Robert (IEEE Transactions on Communications, 2016)
In molecular communication (MC) systems, the expected number of molecules observed at the receiver over time after the instantaneous release of molecules by the transmitter is referred to as the channel impulse response (CIR). Knowledge of the CIR is needed for the design of detection and equalization schemes. In this paper, we present a training-based CIR estimation framework for MC systems, which aims at estimating the CIR based on the observed number of molecules at the receiver due to emission of a sequence of known numbers of molecules by the transmitter. Thereby, we distinguish two scenarios depending on whether or not statistical channel knowledge is available. In particular, we derive maximum likelihood and least sum of square errors estimators, which do not require any knowledge of the channel statistics. For the case, when statistical channel knowledge is available, the corresponding maximum a posteriori and linear minimum mean square error estimators are provided. As performance bound, we derive the classical Cramer Rao (CR) lower bound, valid for any unbiased estimator, which does not exploit statistical channel knowledge, and the Bayesian CR lower bound, valid for any unbiased estimator, which exploits statistical channel knowledge. Finally, we propose the optimal and suboptimal training sequence designs for the considered MC system. Simulation results confirm the analysis and compare the performance of the proposed estimation techniques with the respective CR lower bounds.<br
Keywords: Channel estimation; Receivers; Transmitters; Channel models; Maximum likelihood estimation; Training

Channel Estimation for Intelligent Reflecting Surface-Assisted Millimeter Wave MIMO Systems - Lin, Tian; Yu, Xianghao; Zhu, Yu; Schober, Robert (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
Intelligent reflecting surfaces (IRSs) are regarded as promising enablers for future millimeter wave (mmWave) wireless communication, due to their ability to create favorable line-of-sight (LoS) propagation environments. In this paper, we investigate channel estimation in downlink IRS-assisted mmWave multiple-input multiple-output (MIMO) systems. By leveraging the sparsity of mmWave channels, we formulate the channel estimation problem as a fixed-rank constrained non-convex optimization problem. To tackle the non-convexity, an efficient algorithm is proposed by capitalizing on alternating minimization and manifold optimization (MO), which yields a locally optimal solution. Simulation results show that the proposed MObased estimation (MO-EST) algorithm significantly outperforms two benchmark schemes and demonstrate the robustness of the MO-EST algorithm with respect to imperfect knowledge of the sparsity level of the channels in practical implementations.
CRIS-Team Scopus Importer:2021-04-19

Channel Estimation for IRS-Assisted Millimeter-Wave MIMO Systems: Sparsity-Inspired Approaches - Lin, Tian; Yu, Xianghao; Zhu, Yu; Schober, Robert (IEEE Transactions on Communications, 2022)
Due to their ability to create favorable line-of-sight (LoS) propagation environments, intelligent reflecting surfaces (IRSs) are regarded as promising enablers for future millimeter-wave (mm-wave) wireless communication. In this paper, we investigate channel estimation for IRS-assisted mm-wave multiple-input multiple-output (MIMO) wireless systems. By leveraging the sparsity of mm-wave channels in the angular domain, we formulate the channel estimation problem as an ℓ1-norm regularized optimization problem with fixed-rank constraints. To tackle the non-convexity of the formulated problem, an efficient algorithm is proposed by capitalizing on alternating minimization and manifold optimization (MO), which yields a locally optimal solution. To further reduce the computational complexity of the estimation algorithm, we propose a compressive sensing- (CS-) based channel estimation approach. In particular, a three-stage estimation protocol is put forward where the subproblem in each stage can be solved via low-complexity CS methods. Furthermore, based on the acquired channel state information (CSI) of the cascaded channel, we design a passive beamforming algorithm for maximization of the spectral efficiency. Simulation results reveal that the proposed MO-based estimation (MO-EST) and beamforming algorithms significantly outperform two benchmark schemes while the CS-based estimation (CS-EST) algorithm strikes a balance between performance and complexity.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Array signal processing; Channel estimation; Channel estimation; compressive sensing; Estimation; fixed-rank manifold optimization; intelligent reflecting surface; MIMO; MIMO communication; Radio frequency; Receiving antennas; Wireless communication

Channel Estimation for RIS-Aided mmWave MIMO System from 1-Sparse Recovery Perspective - Peng, Zhendong; Zhou, Gui; Pan, Cunhua; Ren, Hong (2022 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM 2022), 2022)
CRIS-Team WoS Importer:2023-04-28

Channel Estimation for RIS-Aided Multi-User mmWave Systems with Uniform Planar Arrays - Peng, Zhendong; Zhou, Gui; Pan, Cunhua; Ren, Hong; Lee Swindlehurst, A.; Popovski, Petar; Wu, Gang (IEEE Transactions on Communications, 2022)
In this paper, we adopt a three-stage based uplink channel estimation protocol with reduced pilot overhead for an reconfigurable intelligent surface (RIS)-aided multi-user (MU) millimeter wave (mmWave) communication system, in which both the base station (BS) and the RIS are equipped with a uniform planar array (UPA). Specifically, in Stage I, the channel state information (CSI) of a typical user is estimated. To address the power leakage issue for the common angles-of-arrival (AoAs) estimation in this stage, we develop a low-complexity one-dimensional search method. In Stage II, a re-parameterized common BS-RIS channel is constructed with the estimated information from Stage I to estimate other users’ CSI. In Stage III, only the rapidly varying channel gains need to re-estimated. Furthermore, the proposed method can be extended to multi-antenna UPA-type users, by decomposing the estimation of a multi-antenna channel with J scatterers into estimating J single-scatterer channels for a virtual single-antenna user. An orthogonal matching pursuit (OMP)-based method is proposed to estimate the angles-of-departure (AoDs) at the users. Simulation results demonstrate that the proposed algorithm significantly achieves high channel estimation accuracy, which approaches the genie-aided upper bound in the high signal-to-noise ratio (SNR) regime.
CRIS-Team Scopus Importer:2022-11-04
Keywords: channel estimation; millimeter wave; Reconfigurable intelligent surface; uniform planar array

Channel estimation techniques for diffusion-based molecular communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Jardin, Christophe; Sticht, Heinrich; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
In molecular communication (MC) systems, the expected number of molecules observed at the receiver over time after the instantaneous release of molecules by the transmitter is referred to as the channel impulse response (CIR). Knowledge of the CIR is needed for the design of detection and equalization schemes. In this paper, we present a training-based CIR estimation framework for MC systems which aims at estimating the CIR based on the observed number of molecules at the receiver due to emission of a sequence of known numbers of molecules by the transmitter. In particular, we derive maximum likelihood (ML) and least sum of square errors (LSSE) estimators. We also study the Cramer Rao (CR) lower bound and training sequence design for the considered system. Simulation results confirm the analysis and compare the performance of the proposed estimation techniques with the CR lower bound.<br
Keywords: Receivers; Transmitters; Channel estimation; Channel models; Maximum likelihood estimation; Training

Channel Hardening of IRS-Aided Multi-Antenna Systems: How Should IRSs Scale? - Bereyhi, Ali; Asaad, Saba; Ouyang, Chongjun; Müller, Ralf; Schaefer, Rafael F.; Vincent Poor, H. (IEEE Journal on Selected Areas in Communications, 2023)
It is widely believed that large IRS-aided MIMO settings maintain the fundamental features of massive MIMO systems. This work gives a rigorous proof that confirms this belief. We show that using a large passive IRS, the end-to-end MIMO channel between the transmitter and the receiver always hardens, even if the IRS elements are strongly correlated. For fading direct and reflection links between the transmitter and the receiver, our derivations demonstrate that for a large number of reflecting elements on the IRS, the capacity of the end-to-end channel is accurately approximated by a real-valued Gaussian random variable whose variance goes to zero as the number of IRS elements grows unboundedly large. The order of this drop depends on how the physical dimensions of the IRS grow. We derive this order explicitly. Numerical experiments show that the closed-form approximation very closely matches the histogram of the capacity term, even in practical scenarios. As a sample application of the results, we characterize the dimensional trade-off between the transmitter and the IRS. The result is intuitive: For a target performance, the larger the IRS is, the fewer transmit antennas are required.
CRIS-Team Scopus Importer:2023-07-07
Keywords: asymptotic channel hardening; Channel capacity; ergodic capacity; Fading channels; large-system analysis; Massive MIMO; MIMO communication; MISO communication; outage probability; Reconfigurable intelligent surface; Transmitters; Transmitting antennas

Channel level crossing-based security for communications over fading channels - Karas, Dimitrios S.; Karagiannidis, George K.; Schober, Robert (IET Information Security, 2013)
Several key exchange methods for wireless channels have been proposed in the literature. They are referred to as physical-layer security techniques and are usually based on the channel's fading characteristics and the principle of channel reciprocity. In this study, the authors present key exchange algorithms for wireless fading channels whose operation is based on channel estimation. Specifically, the authors present a complete key exchange scheme that includes channel sampling, thresholding and error reconciliation. Two error reconciliation methods are proposed. The first one is based on neural networks and the second one is based on linear block coding. Simulations of the proposed methods' performances and levels of security are presented and conclusions are drawn regarding their overall utility. © The Institution of Engineering and Technology 2013.
CRIS-Team Scopus Importer:2020-02-03

Channel Modeling for Diffusive Molecular Communication - A Tutorial Review - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Wicke, Wayan; Noel, Adam; Schober, Robert (Proceedings of the IEEE, 2019)
Molecular communication (MC) is a new communication engineering paradigm where molecules are employed as information carriers. MC systems are expected to enable new revolutionary applications, such as sensing of target substances in biotechnology, smart drug delivery in medicine, and monitoring of oil pipelines or chemical reactors in industrial settings. As for any other kind of communication, simple yet sufficiently accurate channel models are needed for the design, analysis, and efficient operation of MC systems. In this paper, we provide a tutorial review on mathematical channel modeling for diffusive MC systems. The considered end-to-end MC channel models incorporate the effects of the release mechanism, the MC environment, and the reception mechanism on the observed information molecules. Thereby, the various existing models for the different components of an MC system are presented under a common framework and the underlying biological, chemical, and physical phenomena are discussed. Deterministic models characterizing the expected number of molecules observed at the receiver and statistical models characterizing the actual number of observed molecules are developed. In addition, we provide the channel models for time-varying MC systems with moving transmitters and receivers, which are relevant for advanced applications such as smart drug delivery with mobile nanomachines. For complex scenarios, where simple MC channel models cannot be obtained from first principles, we investigate the simulation- and experiment-driven channel models. Finally, we provide a detailed discussion of potential challenges, open research problems, and future directions in channel modeling for diffusive MC systems.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Diffusion; end-to-end channel impulse response (CIR); experiment-driven models; flow; molecular communications (MCs); reaction; simulation-driven models; statistical model

Channel Modeling for Drug Carrier Matrices - Schäfer, Maximilian; Salinas, Yolanda; Ruderer, Alexander; Enzenhofer, Franz; Brueggemann, Oliver; Schober, Robert; Haselmayr, Werner (2021 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2021)
CRIS-Team WoS Importer:2022-05-27

Channel Modeling for IRS -Assisted FSO Systems - Ajam, Hedieh; Najafi Kalyani, Marzieh; Jamali Kooshkghazi, Vahid; Schober, Robert (2021 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2021)
CRIS-Team WoS Importer:2021-10-29

Channel Modeling for Synaptic Molecular Communication With Re-uptake and Reversible Receptor Binding - Lotter, Sebastian; Ahmadzadeh, Arman; Schober, Robert (ICC 2020 - 2020 IEEE International Conference on Communications (ICC), 2020)
In Diffusive Molecular Communication (DMC), information is transmitted by diffusing molecules. Synaptic signaling is a natural implementation of this paradigm. It is responsible for relaying information from one neuron to another, but also provides support for complex functionalities, such as learning and memory. Many of its features are not yet understood, some are, however, known to be critical for robust, reliable neural communication. In particular, some synapses feature a re-uptake mechanism at the presynaptic neuron, which provides a means for removing neurotransmitters from the synaptic cleft and for recycling them for future reuse. In this paper, we develop a comprehensive channel model for synaptic DMC encompassing a spatial model of the synaptic cleft, molecule re-uptake at the presynaptic neuron, and reversible binding to individual receptors at the postsynaptic neuron. Based on this model, we derive an analytical time domain expression for the channel impulse response (CIR) of the synaptic DMC system. Our model explicitly incorporates macroscopic physical channel parameters and can be used to evaluate the impact of re-uptake, receptor density, and channel width on the CIR of the synaptic DMC system. Furthermore, we provide results from particlebased computer simulation, which validate the analytical model. The proposed comprehensive channel model for synaptic DMC systems can be exploited for the investigation of challenging problems, like the quantification of the inter-symbol interference between successive synaptic signals and the design of synthetic neural communication systems.<br
Keywords: Molecular Communications; Neurons; Monte Carlo methods; Adsorption; Neurotransmitters; Analytical models; Biomembranes; Synapses

Channel Modeling, Modulation and Detection for Terahertz Communications - Moldovan, Anamaria (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)

Channel modelling of MU-MIMO systems by quaternionic free probability - Müller, Ralf; Çakmak, Burak (2012 IEEE International Symposium on Information Theory, ISIT 2012, 2012)
This paper studies the asymptotic eigenvalue distribution (AED) and the mutual information of a multiuser (MU) multiple-input multiple output (MIMO) channel with a certain fraction of users experiencing line-of-sight. It shows that the AED of the channel matrix decomposes into two separate bulks for practically relevant parameter choices and differs very much from the common assumption of independent identically distributed (iid) entries which induces the quarter circle law. This happens even without antenna correlation at either side of the channel. In order to tackle this problem the paper makes use of recent developments in free probability theory which allow to deal with complex-valued eigenvalue distributions of non-Hermitian matrices by means of quaternions. © 2012 IEEE.
Keywords: antenna arrays; channel modeling; eigenvalue distribution; free probability; line of sight; multiple-input multiple output; quaternions; R-diagonal elements; random matrices; Rician fading; Stieltjes transform

Channel Models, Favorable Propagation and MultiStage Linear Detection in Cell-Free Massive MIMO - Gholami, Roya; Cottatellucci, Laura; Slock, Dirk (IEEE International Symposium on Information Theory - Proceedings, 2020)
We consider a cell-free MIMO system in uplink, comprising a massive number of distributed transmit and receive antennas. In our distributed antenna system (DAS), transmit and receive antennas are distributed according to homogeneous point processes (PP) and the received signals are processed jointly at a central processing unit (CPU). In centralized massive MIMO systems, the phenomenon of favorable propagation has been observed: when the number of receive antennas tends to infinity while the number of transmit antennas remains finite, the users' channels become almost orthogonal and low complexity detection via matched filtering is almost optimal. We analyze the properties of DASs in asymptotic conditions when the network dimensions go to infinity with given intensities of the transmit and receive antenna PPs. We study the analytical conditions of favorable propagation in DASs with two kinds of channels, namely, channels with path loss and transmit and receive antennas in line of sight (LoS) or in multipath Rayleigh fading. We show that the analytical conditions of favorable propagation are satisfied for channels impaired by path loss and Rayleigh fading while they do not hold in the case of LoS channels, motivating the use and analysis of multi-stage receivers. Simulation results of the favorable propagation conditions and the performance of multi-stage detectors for finite systems validate the asymptotic analytical results.
CRIS-Team Scopus Importer:2020-09-18

Channel Responses for the Molecule Release from Spherical Homogeneous Matrix Carriers - Schäfer, Maximilian; Salinas, Yolanda; Enzenhofer, Franz; Bruggemann, Oliver; Martinez-Manez, Ramon; Rabenstein, Rudolf; Schober, Robert; Haselmayr, Werner; Ruderer, Alexander (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2022)
Molecular communications is a promising framework for the design of controlled-release drug delivery systems. Under this framework, drug carriers, diseased cells, and the channel in between are modeled as transmitters, absorbing receivers, and diffusive channel, respectively. However, existing works on drug delivery systems consider only simple drug carrier models, which limits their practical applicability. In this paper, we investigate diffusion-based spherical matrix-type drug carriers, which are employed in medical applications. In a matrix carrier, the drug molecules are dispersed in the matrix core and diffuse from the inner to the outer layers of the carrier once immersed in a dissolution medium. We derive the channel response of the matrix carrier transmitter for an absorbing receiver. The results are validated by particle-based simulations and compared with commonly used point and transparent spherical transmitters to highlight the necessity of considering practical models. Moreover, we show that a transparent spherical transmitter, with the drug molecules uniformly distributed over the entire volume, is a special case of the considered matrix system. For this case, we provide an analytical expression for the channel response. Furthermore, we derive a criterion for evaluating whether the release process or the channel dynamics are more important for the overall characteristics of the channel response of a drug delivery system. For the limiting regimes, where only the release process or only the channel determine the behavior of the end-to-end system, we propose closed-form approximations for the channel response. Finally, as a scenario of practical relevance, we investigate the channel responses for the release of common therapeutic drugs, e.g., doxorubicin, from a diblock copolymer micelle acting as drug carrier.
Created from Fastlane, Scopus look-up
Keywords: Analytical models; Biological system modeling; Biology; Diseases; Drugs; Polymers; Transmitters

Characterization of an Inductance-based Detector in Molecular Communication Testbed Based on Superparamagnetic Iron Oxide Nanoparticles - Ahmed, Doaa; Unterweger, Harald; Fischer, Georg; Schober, Robert; Kirchner, Jens (IEEE SENSORS 2019, 2019)
Molecular communication (MC), using chemicals or particles, is a promising approach to bridge the gaps of conventional communication systems, e.g. in nano-scale or in pipelines. Our testbed depends on superparamagnetic iron oxide nanoparticles (SPIONs) as information carriers, which are detected using a susceptometer. In this paper, we study how the position and distribution of particles near the susceptometer, i.e., coil, affect its detected signal. When the particles move axially through the coil, an increment in the signal is detected. In addition, we observed a nonlinear additive behaviour of inductance in the same axial direction, i.e., changes in inductance due to partial volumes are not additive. An exponentially-like signal is detected when the particles move radially through the coil. Moreover, a linear additive behaviour of inductance is observed in this direction. Increasing the magnetic susceptibility has a significant effect on the detected signal. However, the susceptibility of SPIONs is relatively small in order to keep superparamagnetic properties. The coil inductance depends not only on the volume, or permeability of magnetic particles in its core, but also on how they are distributed inside. <br
Keywords: molecular communication; superparamagnetic nanoparticles; simulation; MC testbed; coils; magnetic fields

Charging Techniques for UAV-Assisted Data Collection: Is Laser Power Beaming the Answer? - Lahmeri, Mohamed Amine; Kishk, Mustafa A.; Alouini, Mohamed-Slim (IEEE Communications Magazine, 2022)
As COVID-19 has increased the need for connectivity around the world, researchers are targeting new technologies that could improve coverage and connect the unconnected in order to make progress toward the United Nations Sustainable Development Goals. In this context, drones are seen as one of the key features of 6G wireless networks that could extend the coverage of previous wireless network generations. That said, limited onboard energy seems to be the main drawback that hinders the use of drones for wireless coverage. Therefore, different wireless and wired charging techniques, such as laser beaming, charging stations, and tether stations, are proposed. In this article, we analyze and compare these different charging techniques by performing extensive simulations for the scenario of drone-assisted data collection from ground-based Internet of Things devices. We analyze the strengths and weaknesses of each charging technique, and finally show that laser-powered drones strongly compete with, and outperform in some scenarios, other charging techniques.
CRIS-Team WoS Importer:2022-06-03

Chemical Reactions-based Detection Mechanism for Molecular Communications - Cao, Trang Ngoc; Jamali, Vahid; Wicke, Wayan; Yeoh, Phee Lep; Zlatanov, Nikola; Evans, Jamie; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2020)
In molecular communications, the direct detection of signaling molecules may be challenging due to the lack of suitable sensors and interference from co-existing substances in the environment. Motivated by examples in nature, we investigate an indirect detection mechanism using chemical reactions between the signaling molecules and a molecular probe to produce an easy-to-measure product at the receiver. The underlying reaction-diffusion equations that describe the concentrations of the reactant and product molecules in the system are non-linear and coupled, and cannot be solved in closed-form. To analyze these molecule concentrations, we develop an efficient iterative algorithm by discretizing the time variable and solving for the space variables in each time step. We also derive insightful closed-form solutions for a special case. The accuracy of the proposed algorithm is verified by particle-based simulations. Our results show that the concentration of the product molecules has a similar characteristic over time as the concentration of the signaling molecules. We analyze the bit error rate (BER) for a threshold detector and highlight that significant improvements in the BER can be achieved by carefully choosing the molecular probe and optimizing the detection threshold.
CRIS-Team Scopus Importer:2020-07-10

Chemical Reactions-based Detection Mechanism for Molecular Communications - Cao, Trang Ngoc; Jamali, Vahid; Wicke, Wayan; Zlatanov, Nikola; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
In molecular communications, the direct detection of signaling molecules may be challenging due to a lack of suitable sensors and interference from co-existing substances in the environment. Motivated by research in molecular biology, we investigate an indirect detection mechanism using chemical reactions between the signaling molecules and a molecular probe to produce an easy-to-measure product at the receiver. We consider two implementations of the proposed detection mechanism, i.e., unrestricted probe movement and probes restricted to a volume around the receiver. In general, the resulting reaction-diffusion equations that describe the concentrations of the reactant and product molecules in the system are non-linear and coupled, and cannot be solved in closed form. To evaluate these molecule concentrations, we develop an efficient iterative algorithm by discretizing the time variable and solving for the space variables of the concentration equations in each time step. In the special case when the concentration of the unrestricted probes is high and not significantly changed by the chemical reaction, we obtain insightful closed-form solutions. Our results show that the concentrations of the product molecules and the signalling molecules have a similar characteristic over time, i.e., a single peak and a long tail. We highlight that by carefully choosing the molecular probe and optimizing the decision threshold, the BER can be improved significantly such that a direct detection system is outperformed. Moreover, when the molecular probes are kept in a small volume around the receiver, fewer resources are needed to achieve a lower BER and/or a higher data rate compared to the case of unrestricted molecular probes.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Calcium; Chemical and biological sensors; Chemical reactions; Chemicals; Mathematical models; Probes; Receivers

Codebook Based Two-Time Scale Resource Allocation Design for IRS-Assisted eMBB-URLLC Systems - Ghanem, Walid; Jamali, Vahid; Schellmann, Malte; Cao, Hanwen; Eichinger, Joseph; Schober, Robert (2022 IEEE GLOBECOM Workshops, GC Wkshps 2022 - Proceedings, 2022)
This paper investigates the resource allocation algorithm design for wireless systems assisted by large intelligent reflecting surfaces (IRSs) with coexisting enhanced mobile broadband (eMBB) and ultra reliable low-latency communication (URLLC) users. We consider a two-time scale resource allocation scheme, whereby the base station's precoders are optimized in each mini-slot to adapt to newly arriving URLLC traffic, whereas the IRS phase shifts are reconfigured only in each time slot to avoid excessive base station-IRS signaling. To facilitate efficient resource allocation design for large IRSs, we employ a codebook-based optimization framework, where the IRS is divided into several tiles and the phase-shift elements of each tile are selected from a pre-defined codebook. The resource allocation algorithm design is formulated as an optimization problem for the maximization of the average sum data rate of the eMBB users over a time slot while guaranteeing the quality-of-service (QoS) of each URLLC user in each mini-slot. An iterative algorithm based on alternating optimization (AO) is proposed to find a high-quality suboptimal solution. As a case study, the proposed algorithm is applied in an industrial indoor environment modelled via the Quadriga channel simulator. Our simulation results show that the proposed algorithm design enables the coexistence of eMBB and URLLC users and yields large performance gains compared to three baseline schemes. Furthermore, our simulation results reveal that the proposed two-time scale resource allocation design incurs only a small performance loss compared to the case when the IRSs are optimized in each mini-slot.
CRIS-Team Scopus Importer:2023-03-07

Codebook-Based User Tracking in IRS-Assisted mmWave Communication Networks - Garkisch, Moritz; Jamali, Vahid; Schober, Robert (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2023)
In this paper, we present a novel mobile user tracking (UT) scheme for codebook-based intelligent reflecting surface (IRS)-aided millimeter wave (mmWave) systems. The proposed UT scheme exploits the temporal correlation of the direction from the IRS to the mobile user for selecting IRS phase shifts that provide reflection towards the user. To this end, the user’s direction is periodically estimated based on a generalized likelihood ratio test (GLRT) and the user’s movement trajectory is extrapolated from several past direction estimates. The efficiency of the proposed UT scheme is evaluated in terms of the average effective rate, which accounts for both the required signaling overhead and the achieved signal-to-noise ratio (SNR). Our results show that for medium-to-high SNR, the proposed codebook-based UT scheme achieves a higher effective rate than two reference approaches based on full codebook search and optimization of the individual IRS unit cells, respectively.<br

Coexistence Analysis of Bluetooth and Cellular UMTS in the 2500-2690 MHz Band - Konrad, Markus; Koch, Wolfgang; Huschke, Jörg (Conference Proceedings, 2006)
One of the key issues of next generation mobile communications is compatibility with other wireless standards to further enhance ubiquity. The 2500-2690 MHz band has been identified as extension band for IMT-2000 systems such as UMTS (Universal Mobile Telecommunications System). The 2.4 GHz ISM (Industrial, Scientific, and Medical) band is available for all kinds of unlicensed technologies such as Bluetooth (BT) and Wireless LAN (WLAN). The combination of BT and GSM within one mobile phone has become widely accepted, and therefore the same combination will be required to work for UMTS mobile phones operating in the 2.5 GHz extension band as well. Radio network simulations are performed for a variety of scenarios in order to analyze the performance of the integrated BT receiver while the UMTS uplink signal for frequency division duplex (FDD) mode is present. The objective of this work is to analyze the performance of the BT receive mode in terms of user satisfaction and outage probabilities for indoor use as worst case scenario. © 2006 IEEE.
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.mobilk.coexis
Keywords: Bluetooth; 3G mobile communication; Wireless LAN; Mobile handsets; Performance Analysis; Mobile communication; Communication Standards; GSM; Radio Network; Analytical models

Colocated and Distributed Switch-and-Stay Combining: Optimality Under Switching Rate Constraints - Jataprolu, Manjunath Kashyap; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2013)
Switch-and-stay combining (SSC) is a low-complexity alternative to selection combining (SC) in dual diversity systems. These diversity systems can either be the conventional colocated diversity setups, where two antennas are available at the receiver, or the cooperative diversity systems, where two relays assist one transmitter-receiver pair. In SSC, a single diversity branch (i.e., a single antenna or a single relay) is activated and remains active as long as the corresponding channel is sufficiently strong, regardless of the quality of the other branch. Thereby, the switching threshold determines both the bit error rate (BER) and the switching rate, which are defined as the number of times per second a branch switching occurs. Since high switching rates are not preferred in practice, in this paper, we optimize the switching threshold of SSC to minimize the BER under a constraint on the switching rate. To this end, we derive approximate closed-form solutions for the optimization problem for both the colocated and the distributed antenna case. These solutions are shown to achieve close-to-optimal performance through computer simulations.<br
Keywords: cooperative communication; diversity reception; error statistics; optimisation; relay networks (telecommunication); telecommunication switching

Combined time-reversal space-time block coding and transmit beamforming for frequency-selective fading channels - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (IEEE International Conference on Communications, 2008)
Transmit beamforming (BF) with reliable channel state information at the transmitter (CSIT) can improve the system performance significantly. On the other hand, for unreliable CSIT pure space-time coding outperforms transmit BF. In this paper, the combination of time-reversal space-time block codes (TR-STBCs) and transmit BF for transmission over frequency-selective fading channels is considered. The proposed scheme takes the reliability of the CSIT into account in an optimum way. For unreliable CSIT, the proposed scheme yields the same diversity gains as a TR-STBC, whereas for reliable CSIT significant BF gains can be obtained in addition to the diversity gain of the TR-STBC. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Comparative Evaluation of a New Sensor for Superparamagnetic Iron Oxide Nanoparticles in a Molecular Communication Setting - Bartunik, Max; Unterweger, Harald; Alexiou, Christoph; Schober, Robert; Lübke, Maximilian; Fischer, Georg; Kirchner, Jens (EAI BICT 2020 - 12th EAI International Conference on Bio-inspired Information and Communications Technologies, 2020)
Testbeds are required to assess concepts and devices in the context of molecular communication. These allow the observation of real-life phenomena in a controlled environment and therefore present the basis of future work. A testbed using superparamagnetic iron oxide nanoparticles (SPIONs) as information carriers was constructed with regard to this context and requires a sensitive receiver for the detection of SPIONs. This paper focusses on the comparison between a newly presented device (inductance sensor), a previously constructed SPION sensor (resonance bridge), and a commercial susceptometer as reference. The new inductance sensor is intended to improve on a low sensitivity achieved with the previous device and restrictions with respect to sample rate and measurement aperture encountered with the susceptometer. The signal-to-noise ratio (SNR) for each device is assessed at a variety of SPION concentrations. Furthermore, the sensors bit error rates (BER) for a random bit sequence are determined. The results show the device based on an inductance sensor to be the most promising for further investigation as values both for BER and SNR exceed those of the resonance bridge while providing a suciently high sample rate. On average the SNR of the new device is 13 dB higher while the BER for the worst transmission scenario is 9% lower. The commercial susceptometer, although returning the highest SNR, lacks adaptability for the given use case.<br
Keywords: Molecular Communication; Superparamagnetic Iron Oxide; Nanoparticles; SPION; Testbed; Susceptometer; Resonance Bridge; Inductance Sensor; SNR; BER

Comparison of Convolutional and Block Codes for Low Structural Delay - Rachinger, Christoph; Huber, Johannes; Müller, Ralf (IEEE Transactions on Communications, 2015)
The performance of short block length low-density parity-check (LDPC) codes (both binary and nonbinary) and convolutional codes is compared under the constraint of tight structural delay constraints. Additionally, we use fundamental bounds on block codes and low rate turbo codes to evaluate our results in a broader context. It turns out that-depending on the code rate and given delay-convolutional codes are able to outperform fundamental lower bounds for block codes, yielding a definite result on the question, which codes are superior in this regime. From a break-even point onward, convolutional codes cannot compete with block codes anymore and nonbinary LDPC codes show the best performance. Turbo codes with a short interleaver length show competitive results.
Keywords: Low-density parity-check codes; convolutional codes; turbo codes; low latency decoding

Comparison of MOE and Blind LMS - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (IEEE Communications Letters, 2003)
In this letter, we provide a rigorous analytical comparison of two blind adaptive algorithms for adjustment of the minimum mean-squared error (MMSE) filter for multiple access interference (MAI) suppression for direct-square code-division multiple access (DS-CDMA). In particular, we compare the popular minimum-output-energy (MOE) algorithm and the blind least-mean-square algorithm (BLMS) in terms of complexity, transient behavior, convergence, stability, and steady-state performance. We show analytically that the MOE algorithm enjoys a faster speed of convergence and has a superior steady-state performance, while the BLMS algorithm is computationally less complex.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.mobilk.compar
Keywords: Blind adaptive algorithms; DS-CDMA; Multiuser interference suppression

Comparison of OFDM and Single-Carrier Transmission for Ultra-Low Delay Applications - Rachinger, Christoph; Huber, Johannes; Gerstacker, Wolfgang (2018 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2018)
CRIS-Team WoS Importer:2019-04-16

Comparison of Transmission Concepts for Indoor THz Communication Systems - Schram, Viktoria; Wu, Yifei; Kolleshi, Monika; Gerstacker, Wolfgang (2020 3rd International Workshop on Mobile Terahertz Systems, IWMTS 2020, 2020)
Continuous research progress in THz communications including communications and networking paradigms as well as devices and implementation aspects indicate that this technology has the potential to become a key component in future beyond 5G systems. Still, some research challenges have to tackled before, e.g. related to the peculiarities of the highly frequency-selective THz channel resulting in a much longer channel impulse response (CIR) compared to channels in the lower frequency bands. In this paper, first, various equalization techniques such as minimum mean-squared error (MMSE) linear equalization and decision-feedback equalization (DFE) are studied for single-carrier transmission in order to combat the frequency selectivity of a deterministic THz channel. Furthermore, orthogonal frequency-division multiplexing (OFDM) communication with zero-forcing (ZF) equalization is considered, and the performance of single-carrier and multi-carrier transmissions are compared. Secondly, the advantages of a stochastic channel model are pointed out for the analysis of a multiple-input multiple-output (MIMO) transmission, and ZF and MMSE linear frequency-domain equalization are investigated for a single-carrier frequency-division multiple access (SC-FDMA) transmission over a MIMO THz channel. We conclude that SC-FDMA along with MMSE linear equalization is promising for practical THz systems.
CRIS-Team Scopus Importer:2020-10-16
Keywords: equalization; indoor channels; OFDM; SC-FDMA; THz communications

Comprehensive reactive receiver modeling for diffusive molecular communication systems: Reversible binding, molecule degradation, and finite number of receptors - Ahmadzadeh, Arman; Arjmandi, Hamidreza; Burkovski, Andreas; Schober, Robert (IEEE Transactions on Nanobioscience, 2016)

Compressive Sensing Based Adaptive Active User Detection and Channel Estimation: Massive Access Meets Massive MIMO - Ke, Malong; Gao, Zhen; Wu, Yongpeng; Gao, Xiqi; Schober, Robert (IEEE Transactions on Signal Processing, 2020)
This paper considers massive access in massive multiple-input multiple-output (MIMO) systems and proposes an adaptive active user detection and channel estimation scheme based on compressive sensing. By exploiting the sporadic traffic of massive connected user equipments and the virtual angular domain sparsity of massive MIMO channels, the proposed scheme can support massive access with dramatically reduced access latency. Specifically, we design non-orthogonal pseudo-random pilots for uplink broadband massive access, and formulate the active user detection and channel estimation as a generalized multiple measurement vector compressive sensing problem. Furthermore, by leveraging the structured sparsity of the uplink channel matrix, we propose an efficient generalized multiple measurement vector approximate message passing (GMMV-AMP) algorithm to realize joint active user detection and channel estimation based on a spatial domain or an angular domain channel model. To jointly exploit the channel sparsity present in both the spatial and the angular domains for enhanced performance, a Turbo-GMMV-AMP algorithm is developed for detecting the active users and estimating their channels in an alternating manner. Finally, an adaptive access scheme is proposed, which adapts the access latency to guarantee reliable massive access for practical systems with unknown channel sparsity level. Additionally, the state evolution of the proposed GMMV-AMP algorithm is derived to predict its performance. Simulation results demonstrate the superiority of the proposed active user detection and channel estimation schemes compared to several baseline schemes.
CRIS-Team Scopus Importer:2020-02-04
Keywords: active user detection; approximate message passing; channel estimation; compressive sensing; Massive access; massive multiple-input multiple-output; structured sparsity

Compressive Sensing for Indoor THz Channel Estimation - Schram, Viktoria; Moldovan, Anamaria; Gerstacker, Wolfgang (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2019)
Terahertz (THz) communication is a new emerging technology which has the potential to satisfy the steadily growing demands for high data rates. However, transmission over the THz channel is a difficult task since perfect channel state information (CSI) is not available in real systems. Due to the high transmission rate and a high molecular absorption, spreading loss and reflection loss, the discrete-time channel impulse response (CIR) of the THz channel is very long and exhibits an approximately sparse characteristic. Conventional least-squares (LS) channel estimation does not incorporate the sparsity assumption into the estimation process. Therefore, in this work, sparse channel estimation for an indoor THz transmission example scenario using compressive sensing (CS) techniques is analyzed. A CS method based on solving a convex program by using the Dantzig selector (DS) and a CS approach using a greedy pursuit method called compressive sampling matching pursuit (CoSaMP) are investigated. All methods are analyzed with respect to mean squared error (MSE) performance, computational efficiency and numbers of observations needed. The numerical results show that significant advantages over LS estimation are achievable in all categories.
CRIS-Team Scopus Importer:2019-05-28

Conditional Capacity and Transmit Signal Design for SWIPT Systems with Multiple Nonlinear Energy Harvesting Receivers - Morsi, Rania; Jamali, Vahid; Hagelauer, Amelie Marietta; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2020)
In this paper, we study information-theoretic limits for simultaneous wireless information and power transfer (SWIPT) systems employing practical nonlinear radio frequency (RF) energy harvesting (EH) receivers (Rxs). In particular, we consider a SWIPT system with one transmitter that broadcasts a common signal to an information decoding (ID) Rx and multiple EH Rxs. Owing to the nonlinearity of the EH Rxs' circuitry, the efficiency of wireless power transfer depends on the waveform of the transmitted signal. We aim to answer the following fundamental question: What is the optimal input distribution of the transmit signal waveform that maximizes the information transfer rate at the ID Rx conditioned on individual minimum required direct-current (DC) powers to be harvested at the EH Rxs? Specifically, we study the conditional capacity problem of a SWIPT system impaired by additive white Gaussian noise subject to average-power (AP) and peak-power (PP) constraints at the transmitter and nonlinear EH constraints at the EH Rxs. To this end, we develop a novel nonlinear EH model that captures the saturation of the harvested DC power by taking into account not only the forward current of the rectifying diode but also the reverse breakdown current. Then, we derive a novel semi-closed-form expression for the harvested DC power, which simplifies to closed form for low input RF powers. The derived analytical expressions are shown to closely match circuit simulation results. We solve the conditional capacity problem for real- and complex-valued signalling and prove that the optimal input distribution that maximizes the rate-energy (R-E) region is unique and discrete with a finite number of mass points. Furthermore, we show that, for the considered nonlinear EH model and a given AP constraint, the boundary of the R-E region saturates for high PP constraints due to the saturation of the harvested DC power for high input RF powers. In addition, we devise a suboptimal input distribution whose R-E tradeoff performance is close to optimal. All theoretical findings are verified by numerical evaluations.
CRIS-Team Scopus Importer:2020-02-04
Keywords: channel capacity; energy harvesting (EH); matched filters; nonlinear circuit analysis; rectennas; rectifiers; Schottky diodes; semiconductor detectors; signal design; Wireless power transmission

Conference Report: IEEE BlackSeaCom 2017 - Ulema, Mehmet; Panayirci, Erdal; Erkucuk, Serhat; Schober, Robert (IEEE Communications Magazine, 2017)
CRIS-Team Scopus Importer:2020-01-31

Confirmation of random matrix model for the antenna array channel by indoor measurements - Müller, Ralf; et al. (2001 IEEE Antennas and Propagation Society International Symposium- Historical Overview of Development of Wireless-, 2001)
A random matrix model for communication via antenna arrays introduced recently in [1] characterizes the space-time nature of the channel in terms of the asymptotic eigenvalue distribution of its space time covarianco matrix as a function of the number of transmit antennas, receive antennas, and significantly scattering objects. This paper finds the theoretical predictions in [1] to accurately match data obtained in a recent measurement campaign. The number of significant scattering objects is found to strongly vary with frequency. The latter effect is described by the newly introduced richness spectrum.

Constant-Composition Codes for Maximum Likelihood Detection Without CSI in Diffusive Molecular Communications - Jamali, Vahid; Ahmadzadeh, Arman; Farsad, Nariman; Schober, Robert (IEEE Transactions on Communications, 2018)
Instantaneous or statistical channel state information (CSI) is needed for most detection schemes developed for molecular communication (MC) systems. Since the MC channel changes over time, e.g., due to variations in the velocity of flow, the temperature, or the distance between transmitter and receiver, CSI acquisition has to be conducted repeatedly to keep track of CSI variations. Frequent CSI acquisition may entail a large overhead whereas infrequent CSI acquisition may result in a low CSI estimation accuracy. To overcome these challenges, we design codes which enable maximum likelihood sequence detection at the receiver without instantaneous or statistical CSI. In particular, assuming concentration shift keying modulation, we show that a class of codes, known as constant-composition (CC) codes, enables optimal CSI-free sequence detection at the expense of a decrease in data rate. We analyze the code rate, the error rate, and the average number of released molecules for the adopted CC codes. In addition, we study the properties of binary CC codes and balanced CC codes in further detail. Simulation results verify our analytical derivations and reveal that CC codes with CSI-free detection outperform uncoded transmission with optimal coherent and noncoherent detection.<br
Keywords: Receivers; Transmitters; Modulation; Interference; Detectors; Maximum likelihood detection; Molecular communication

Constant False Alarm Rate Detection of Multicarrier Signals With Periodic Power Boosting - Karunakaran, Prasanth; Gerstacker, Wolfgang (IEEE Transactions on Cognitive Communications and Networking, 2018)
Given the prevalence of multicarrier waveforms in wireless systems, the sensing of such signals is of high importance for cognitive radio applications. In this paper, we exploit periodic power boosting of subcarriers in multicarrier signals which is applied, e.g., in LTE to improve the performance of sensing compared to state-of-the-art schemes under practical scenarios where noise uncertainties are present. First, we establish an analytical connection between the subcarrier power distribution and the autocorrelation function of a general multicarrier signal. Second, using this result, we demonstrate that periodic power boosting causes strong peaks in the magnitude of the autocorrelation function. The obtained analytical results match well with over-the-air measurement results corresponding to an orthogonal frequency division multiplexing (OFDM) signal of an LTE transmission. Here, the measurements indicate the presence of a boosting with a period of three subcarriers in the LTE signal which arises due to the cell-specific reference signals. Subsequently, algorithms for both sensing before transmission and simultaneous sensing and reception exploiting the special features of the autocorrelation function resulting from periodic power boosting are developed which outperform energy detection under realistic noise uncertainties as well as several state-of-the-art methods for detecting OFDM signal

(Continuous) phase modulation on the hypersphere - Sedaghat, Mohammad Ali; Müller, Ralf; Rachinger, Christoph (IEEE Transactions on Wireless Communications, 2016)

Controlled Signaling and Transmitter Replenishment for MC with Functionalized Nanoparticles - Schäfer, Maximilian; Brand, Lukas; Lotter, Sebastian; Büyükoglu, Atakan; Enzenhofer, Franz; Haselmayr, Werner; Castiglione, Kathrin; Appelhans, Dietmar; Schober, Robert (9th ACM International Conference on Nanoscale Computing and Communication, 2022)
In this paper, we propose novel Transmitter (Tx) models for Molecular Communication (MC) systems based on functionalized Nanoparticles (NPs). Current Tx models often rely on simplifying assumptions for the molecule release and replenishment mechanisms. In contrast, we propose a Tx model where the signaling molecule release is controlled by a switchable membrane driven by an external trigger. Moreover, we propose a reloading mechanism, where signaling molecules are harvested based on an enzymatic reaction. Hence, no repeated injection of signaling molecules is required. For the proposed Tx model, we develop a general mathematical description in terms of a discrete-time transfer function model. Furthermore, we investigate two realizations of the proposed Tx model, i.e., an idealized Tx relying on simplifying assumptions, and a realistic Tx employing practical components for the reloading and release mechanisms. Finally, we numerically evaluate the proposed model and compare our results to stochastic Particle Based Simulations (PBSs).<br

Convergence Behavior of LDPC decoding and application to early termination - Frenzel, Janik; Müller-Weinfurtner, Stefan; Huber, Johannes; Müller, Ralf (IEEE Personal Indoor and Mobile Radio Conference, 2018)

Convexity Analysis of Nonlinear Wireless Power Transfer with Multiple RF Sources - Yuan, Xiaopeng; Hu, Yulin; Schober, Robert; Schmeink, Anke (IEEE Transactions on Vehicular Technology, 2022)
In this paper, the performance of nonlinear wireless power transfer (WPT) enabled by multiple radio-frequency (RF) sources is characterized. The harvested power is modelled as a function of the RF powers received from multiple RF sources. Following the characterization, we prove the joint convexity of the harvested power under different sufficient conditions. In particular, based on these conditions, the joint convexity of the harvested power with respect to the reciprocals of the received powers is proved. Moreover, by providing an example design, we illustrate the benefits of exploiting the joint convexity for cooperative WPT enhancement.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Energy harvesting; energy harvesting; Integrated circuit modeling; jointly convex property; multiple RF sources; Nonlinear wireless power transfer; Radio frequency; RF signals; Synchronization; Wireless communication; Wireless power transfer

Convex precoding for vector channels in high dimensions - De Miguel, Rodrigo; Müller, Ralf (2008 International Zurich Seminar on Communications, IZS, 2008)
We analyze a non-linear vector precoding technique for MIMO channels in high dimensions. Channel inversion is carried out at the transmitter with the aim of minimizing signal processing at the receiver. In order to contain the transmission power, symbol constellations are extended onto the complex plane using convex alphabets. We compare the case where full channel inversion is possible at the transmitter (more transmitting elements than receiving elements), and the converse case where only partial channel inversion is possible and matched filter detection is required at the receiver. We show that, in some cases, it might be advantageous to turn off some receiving elements in order to contain the transmitted energy per bit. We also propose the use of two novel 8PSK modulation schemes. © 2008 IEEE.

Cooperative Abnormality Detection via Diffusive Molecular Communications - Mosayebi, Reza; Jamali Kooshkghazi, Vahid; Ghoroghchian, Nafiseh; Schober, Robert; Nasiri-Kenari, Masoumeh; Mehrabi, Mahdieh (IEEE Transactions on Nanobioscience, 2017)
In this paper, we consider abnormality detection via diffusive molecular communications (MCs) for a network consisting of several sensors and a fusion center (FC). If a sensor detects an abnormality, it injects a number of molecules into the medium which is proportional to its sensing output. Two transmission schemes for releasing molecules into the medium are considered. In the first scheme, each sensor releases a different type of molecule (DTM), whereas in the second scheme, all sensors release the same type of molecule (STM). The molecules released by the sensors propagate through the MC channel and some may reach the FC where the final decision regarding whether or not an abnormality has occurred is made. We derive the optimal decision rules for both DTM and STM. However, the optimal detectors entail high computational complexity as log-likelihood ratios (LLRs) have to be computed. To overcome this issue, we show that the optimal decision rule for STM can be transformed into an equivalent low-complexity decision rule. Since a similar transformation is not possible for DTM, we propose simple low-complexity sub-optimal detectors based on different approximations of the LLR. The proposed low-complexity detectors are more suitable for practical MC systems than the original complex optimal decision rule, particularly when the FC is a nano-machine with limited computational capabilities. Furthermore, we analyze the performance of the proposed detectors in terms of their false alarm and missed detection probabilities. Simulation results verify our analytical derivations and reveal interesting insights regarding the tradeoff between complexity and performance of the proposed detectors and the considered DTM and STM schemes.<br
Keywords: Detectors; Molecular communication; Computational complexity; Sensor fusion

Cooperative Internet of UAVs: Distributed Trajectory Design by Multi-Agent Deep Reinforcement Learning - Hu, Jingzhi; Zhang, Hongliang; Song, Lingyang; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Communications, 2020)
Due to the advantages of flexible deployment and extensive coverage, unmanned aerial vehicles (UAVs) have significant potential for sensing applications in the next generation of cellular networks, which will give rise to a cellular Internet of UAVs. In this article, we consider a cellular Internet of UAVs, where the UAVs execute sensing tasks through cooperative sensing and transmission to minimize the age of information (AoI). However, the cooperative sensing and transmission is tightly coupled with the UAVs' trajectories, which makes the trajectory design challenging. To tackle this challenge, we propose a distributed sense-and-send protocol, where the UAVs determine the trajectories by selecting from a discrete set of tasks and a continuous set of locations for sensing and transmission. Based on this protocol, we formulate the trajectory design problem for AoI minimization and propose a compound-action actor-critic (CA2C) algorithm to solve it based on deep reinforcement learning. The CA2C algorithm can learn the optimal policies for actions involving both continuous and discrete variables and is suited for the trajectory design. Our simulation results show that the CA2C algorithm outperforms four baseline algorithms. Also, we show that by dividing the tasks, cooperative UAVs can achieve a lower AoI compared to non-cooperative UAVs.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Cooperative Internet of UAVs; deep reinforcement learning; distributed trajectory design

Cooperative mobile-to-mobile file dissemination in cellular networks within a unified radio interface - Popova, Larissa; Herpel, Thomas; Gerstacker, Wolfgang; Koch, Wolfgang (Computer Networks, 2008)
In this paper, a data dissemination technique is introduced for cellular networks by embedding peer-to-peer data transfer into the hierarchical architecture of UMTS (Universal Mobile Telecommunication Systems) for cooperative sharing of data among mobile terminals. Our concept is based on the uplink/downlink traffic imbalance in 3G wireless networks and clearly confirms the social principle "real egoistic behavior is to cooperate". It boosts the spectral efficiency of UMTS by enabling direct mobile-to-mobile data transfer and by dynamically allocating users to temporarily unused uplink channels. The results indicate a substantial increase in service probability and overall system throughput, as well as a significant reduction of the expected file download time. © 2008 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.tech.IMMD.IMMD7.cooper
Keywords: Cooperative file dissemination; Spectral efficiency; Traffic imbalance; UMTS

Cooperative wireless backhauling - Jamali, Vahid; Zlatanov, Nikola; Schober, Robert (SCC 2017 - 11th International ITG Conference on Systems, Communications and Coding, 2019)
We consider wireless backhauling for a scenario where two small-cell base stations (SC-BSs) employ the same time and frequency resources for offloading their data to a common macro-cell base station (MC-BS). The two SC-BSs allocate a part of the shared resource to exchange data in order to be able to cooperate to boost the backhaul capacity. For this scenario, we develop the optimal transmission strategy which, based on the channel state information, determines whether the SC-BSs should exchange data and cooperate or transmit their data independently to the MC-BS. Our numerical results demonstrate the superiority of the proposed cooperative wireless backhauling protocol compared to existing protocols in the literature.
CRIS-Team Scopus Importer:2019-10-22

Coupled Phase-Shift STAR-RISs: A General Optimization Framework - Wang, Zhaolin; Mu, Xidong; Liu, Yuanwei; Schober, Robert (IEEE Wireless Communications Letters, 2022)
A general optimization framework is proposed for simultaneously transmitting and reflecting reconfigurable intelligent surfaces (STAR-RISs) with coupled phase shifts, which converges to the Karush– Kuhn–Tucker (KKT) optimal solution under some mild conditions. More particularly, the amplitude and phase-shift coefficients of STAR-RISs are optimized alternately in closed form. To demonstrate the effectiveness of the proposed optimization framework, the throughput maximization problem is considered in a case study. It is rigorously proved that the KKT optimal solution is obtained. Numerical results confirm the effectiveness of the proposed optimization framework compared to baseline schemes.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Coupled phase shifts; Karush–Kuhn–Tucker (KKT); Linear programming; Optimization; Reflection; Reflection coefficient; simultaneous transmission and reflection (STAR); Three-dimensional displays; Throughput; Upper bound

C-RAN with Hybrid RF/FSO Fronthaul Links: Joint Optimization of Fronthaul Compression and RF Time Allocation - Najafi, Marzieh; Jamali, Vahid; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2019)
This paper considers the uplink of a cloud radio access network (C-RAN) comprised of several multi-antenna remote radio units (RUs) which compress the signals that they receive from multiple mobile users (MUs) and forward them to a CU via wireless fronthaul links. To enable reliable high rate fronthaul links, we employ a hybrid radio frequency (RF)/free space optical (FSO) system for fronthauling. Moreover, to strike a balance between complexity and performance, we consider three different quantization schemes at the RUs, namely per-antenna vector quantization (AVQ), per-RU vector quantization (RVQ), and distributed source coding (DSC), two different RF fronthaul transmission modes, namely orthogonal transmission and non-orthogonal transmission, and two different detectors at the CU, namely the linear minimum mean square error detector and the optimal successive interference cancellation detector. For this network architecture, we investigate the joint optimization of the quantization noise covariance matrices at the RUs and the RF time allocation to the multiple-access and fronthaul links for rate region maximization. To this end, we formulate a unified weighted sum rate maximization problem valid for each possible combination of the considered quantization, RF fronthaul transmission, and detection schemes. To handle the non-convexity of the unified problem, we transform it into a bi-convex problem which facilitates the derivation of an efficient suboptimal solution using alternating convex optimization and golden section search. Moreover, by introducing a backoff parameter to reduce the probability of infeasibility, we generalize the proposed optimization framework to account for imperfect channel estimation. Our simulation results show that for each combination of the considered quantization, RF fronthaul transmission, and detection schemes, C-RAN with hybrid RF/FSO fronthauling can achieve a considerable sum rate gain compared to conventional systems employing pure FSO fronthauling, especially under unfavorable atmospheric conditions. In addition, employing a more sophisticated quantization scheme can significantly improve the system performance under adverse atmospheric conditions. In contrast, in clear weather conditions, when the FSO link capacity is high, the simple AVQ scheme performs close to the optimal DSC scheme. Furthermore, our simulation results suggest that the proposed algorithm can be adapted to the quality of the channel estimates by tuning the backoff parameter.
CRIS-Team Scopus Importer:2020-01-31
Keywords: C-RAN; complexity analysis; compression; hybrid RF/FSO; multi-user detection; optical wireless fronthauling

C-RAN with Hybrid RF/FSO Fronthaul Links: Joint Optimization of RF Time Allocation and Fronthaul Compression - Najafi Kalyani, Marzieh; Jamali, Vahid; Wing Kwan Ng, Derrick; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
This paper considers the uplink of a cloud radio access network (C-RAN) comprised of several multi-antenna remote radio units (RUs) which send the data that they received from multiple mobile users (MUs) to a central unit (CU) via a wireless fronthaul link. One of the fundamental challenges in implementing C-RAN is the huge data rate required for fronthauling. To address this issue, we employ hybrid radio frequency (RF)/free space optical (FSO) systems for the fronthaul links as they benefit from both the large data rates of FSO links and the reliability of RF links. To efficiently exploit the fronthaul capacity, the RUs employ vector quantization to jointly compress the signals received at their antennas. Moreover, due to the limited available RF spectrum, we assume that the RF multiple-access and fronthaul links employ the same RF resources. Thereby, we propose an adaptive protocol which allocates transmission time to the RF multiple-access and fronthaul links in a time division duplex (TDD) manner and optimizes the quantization noise covariance matrix at each RU such that the sum rate is maximized. Our simulation results reveal that a considerable gain in terms of sum rate can be achieved by the proposed protocol in comparison with benchmark schemes from the literature, especially when the FSO links experience unfavorable atmospheric conditions.<br
Keywords: Radio frequency; Protocols; Fading channels; Optical fiber communication; Bandwidth; Photodetectors; Uplink

Cross-Layer Optimization of Fast Video Delivery in Cache-Enabled Relaying Networks - Xiang, Lin; Wing Kwan Ng, Derrick; Islam, Toufiqul; Schober, Robert; Wong, Vincent W. S. (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
This paper investigates the cross-layer optimization of fast video delivery and caching for minimization of the overall video delivery time in a two-hop relaying network. The half-duplex relay nodes are equipped with both a cache and a buffer which facilitate joint scheduling of fetching and delivery to exploit the channel diversity for improving the overall delivery performance. The fast delivery control is formulated as a two-stage functional non-convex optimization problem. By exploiting the underlying convex and quasi-convex structures, the problem can be solved exactly and efficiently by the developed algorithm. Simulation results show that significant caching and buffering gains can be achieved with the proposed framework, which translates into a reduction of the overall video delivery time. Besides, a trade-off between caching and buffering gains is unveiled.<br
Keywords: Streaming media; Wireless communication; Resource management; Relays; Servers; Random access memory; Optimization

Data-Aided Channel Estimation for OTFS Systems with A Superimposed Pilot and Data Transmission Scheme - Yuan, Weijie; Li, Shuangyang; Wei, Zhiqiang; Yuan, Jinhong; Ng, Derrick Wing Kwan (IEEE Wireless Communications Letters, 2021)
The recently developed orthogonal time frequency space (OTFS) modulation has shown its capability of coping with the fast time-varying channels in high-mobility environments. In particular, OTFS modulation gives rise to the sparse representation of the delay-Doppler (DD) domain channel model. Hence, one can an enjoy accurate channel estimation by adopting only one pilot symbol. However, conventional OTFS channel estimation schemes require the deployment of guard space to avoid data-pilot interference, which inevitably sacrifices the spectral efficiency. In this paper, we develop a data-aided channel estimation algorithm for a superimposed pilot and data transmission scheme, which can improve the spectral efficiency. To accurately estimate the channel and detect the data symbols, we coarsely estimate the channel based on the pilot symbol, followed by an iterative process which detects the data symbols and refines the channel estimates. Simulation results show that the bit error rate (BER) performance based on the proposed method can approach the baseline scheme with perfect channel estimation.
CRIS-Team Scopus Importer:2021-08-20
Keywords: channel estimation; OTFS modulation; pilot-data superposition.

Data-Aided Secure Massive MIMO Transmission Under the Pilot Contamination Attack - Wu, Yongpeng; Wen, Chao-Kai; Chen, Wen; Jin, Shi; Schober, Robert; Caire, Giuseppe (IEEE Transactions on Communications, 2019)
In this paper, we study the design of secure communication for time-division duplex multi-cell multi-user massive multiple-input-multiple-output (MIMO) systems with active eavesdropping. We assume that the eavesdropper actively attacks the uplink pilot transmission and the uplink data transmission before eavesdropping the downlink data transmission of the users. We exploit both the received pilot’s and the received data signals for uplink channel estimation. We show analytically that when both the number of transmit antennas and the length of the data vector tend to infinity, the signals of the desired user and the eavesdropper lie in different eigenspaces of the received signal matrix at the base station, provided their signal powers are different. This finding reveals that decreasing (instead of increasing) the desired user’s signal power might be an effective approach to combat a strong active attack from an eavesdropper. Inspired by this observation, we propose a data-aided secure downlink transmission scheme and derive an asymptotic achievable secrecy sum-rate expression for the proposed design. For the special case of a single-cell single-user system with independent and identically distributed fading, the obtained expression reveals that the secrecy rate scales logarithmically with the number of transmit antennas. This is the same scaling law as for the achievable rate of a single-user massive MIMO system in the absence of eavesdroppers. The numerical results indicate that the proposed scheme achieves significant secrecy rate gains compared with alternative approaches based on matched filter precoding with artificial noise generation and null space transmission.<br
Keywords: Contamination; Uplink; MIMO communication; Downlink; Transmitting antennas; Channel estimation; Fading channels

Data-Aided Secure Massive MIMO Transmission with Active Eavesdropping - Wu, Yongpeng; Wen, Chao-Kai; Chen, Wen; Jin, Shi; Schober, Robert; Caire, Giuseppe (2018 IEEE International Conference on Communications (ICC), 2018)
In this paper, we study the design of secure communication for time division duplexing multi-cell multi-user massive multiple-input multiple-output (MIMO) systems with active eavesdropping. We assume that the eavesdropper actively attacks the uplink pilot transmission and the uplink data transmission before eavesdropping the downlink data transmission phase of the desired users. We exploit both the received pilots and data signals for uplink channel estimation. We show analytically that when the number of transmit antennas and the length of the data vector both tend to infinity, the signals of the desired user and the eavesdropper lie in different eigenspaces of the received signal matrix at the base station if their signal powers are different. This finding reveals that decreasing (instead of increasing) the desire user's signal power might be an effective approach to combat a strong active attack from an eavesdropper. Inspired by this result, we propose a data-aided secure downlink transmission scheme and derive an asymptotic achievable secrecy sum-rate expression for the proposed design. Numerical results indicate that under strong active attacks, the proposed design achieves significant secrecy rate gains compared to the conventional design employing matched filter precoding and artificial noise generation.<br
Keywords: Uplink; MIMO communication; Downlink; Data communication; Channel estimation; Contamination; Transmitting antennas

Data Rate Maximization for Terahertz Communication Systems using Finite Alphabets - Moldovan, Anamaria; Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE International Conference on Communications (ICC), 2016)

Decision-Feedback Sequence Estimation for Time-Reversal Space-Time Block Coded Transmission - Schober, Robert; Chen, Harry; Gerstacker, Wolfgang (IEEE Transactions on Vehicular Technology, 2004)
In this paper, we present three different decision-feedback sequence estimation (DFSE) schemes for time-reversal space-time block coding (TR-STBC). The first scheme is called unwhitened DFSE (U-DFSE) and performs reduced-state sequence estimation based on the output of the spatio-temporal matched filter (MF) typically employed in TR-STBC. The second approach improves upon U-DFSE by subtracting a bias term caused by anti-causal interference from the U-DFSE metric. In the third scheme, the noise component in the output of the spatio-temporal MF is first whitened using a prediction-error filter that can be efficiently computed using the Levinson-Durbin algorithm, and subsequently whitened DFSE (W-DFSE) is performed. As relevant example, all three DFSE schemes are compared for the GSM/EDGE system and typical channel profiles such as typical urban (TU) and hilly terrain (HT). Our results show that for binary modulation (as used in GSM) U-DFSE and its improved version can approach the performance of W-DFSE for the full range of delay spreads relevant for GSM and EDGE. On the other hand, for high-level modulation (as used in EDGE) only W-DFSE gives a satisfactory performance, if a low trellis complexity is desired.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.mobilk.decisi
Keywords: GSM; Interference; Additive white noise; Block codes; Matched filters; Filtering; Gaussian noise; Noise cancellation; Maximum likelihood estimation; Decision feedback equalizers

Deep Learning-based Resource Allocation For Device-to-Device Communication - Lee, Woongsup; Schober, Robert (IEEE Transactions on Wireless Communications, 2022)
In this paper, a deep learning (DL) framework for the optimization of the resource allocation in multi-channel cellular systems with device-to-device (D2D) communication is proposed. Thereby, the channel assignment and discrete transmit power levels of the D2D users, which are both integer variables, are optimized for maximization of the overall spectral efficiency whilst maintaining the quality-of-service (QoS) of the cellular users. Depending on the availability of channel state information (CSI), two different configurations are considered, namely 1) centralized operation with full CSI and 2) distributed operation with partial CSI, where in the latter case, the CSI is encoded according to the capacity of the feedback channel. Instead of solving the resulting resource allocation problem for each channel realization, a DL framework is proposed, where the optimal resource allocation strategy for arbitrary channel conditions is approximated by deep neural network (DNN) models. Furthermore, we propose a new training strategy that combines supervised and unsupervised learning methods and a local CSI sharing strategy to achieve near-optimal performance while enforcing the QoS constraints of the cellular users and efficiently handling the integer optimization variables based on a few ground-truth labels. Our simulation results confirm that near-optimal performance can be attained with low computation time, which underlines the real-time capability of the proposed scheme. Moreover, our results show that not only the resource allocation strategy but also the CSI encoding strategy can be efficiently determined using a DNN. Furthermore, we show that the proposed DL framework can be easily extended to communication systems with different design objectives.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Communication systems; CSI sharing; D2D transmission; deep learning; Device-to-device communication; distributed operation; interference channel; Multi-channel wireless communication systems; Optimization; Quality of service; resource allocation; Resource management; Training; Wireless communication

Deep Learning-Empowered Predictive Beamforming for IRS-Assisted Multi-User Communications - Liu, Chang; Liu, Xuemeng; Wei, Zhiqiang; Hu, Shaokang; Ng, Derrick Wing Kwan; Yuan, Jinhong (2021 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2021)
CRIS-Team WoS Importer:2022-05-27

Degrees of Freedom of the K-User Interference Channel Assisted by Active and Passive IRSs - Abdollahi Bafghi, Ali H.; Jamali, Vahid; Nasiri-Kenari, Masoumeh; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we study the degrees of freedom (DoF) region and sum DoF of the time-selective K-user interference channel in the presence of intelligent reflecting surfaces (IRSs). We consider both active and passive IRSs. While both types of IRS can attenuate the amplitude and change the phase of a reflected electromagnetic wave, active IRSs are also capable of amplifying the wave. We derive inner and outer bounds for the DoF region and lower and upper bounds for the sum DoF of the K-user interference channel in the presence of an active IRS and prove that the maximum value of K for the sum DoF can be achieved if the number of IRS elements exceeds a certain finite value. The analysis framework developed for active IRSs forms the basis for our analysis of passive IRS-assisted systems. In particular, we present probabilistic inner and outer bounds for the DoF region and probabilistic lower and upper bounds for the sum DoF of the K-user interference channel in the presence of a passive IRS and prove that the lower bound for the sum DoF asymptotically approaches K as the number of IRS elements grows large.
CRIS-Team Scopus Importer:2022-03-25
Keywords: active and passive intelligent reflecting surface; DoF region; Electromagnetic scattering; Interference; Interference channels; MIMO communication; Probabilistic logic; Relays; sum DoF; Time-selective K-user interference channel; Upper bound

Delay constrained buffer-aided relaying with outdated CSI - Islam, Toufiqul; Michalopoulos, Diomidis S.; Schober, Robert; Bhargava, Vijay K. (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
Recent studies have shown that buffer-aided relaying with adaptive link selection can provide significant performance gains compared to conventional relaying using a fixed transmission schedule. In this paper, we focus on error rate analysis of adaptive link selection for a three node decode-and-forward (DF) relay network with fixed-rate transmission. As in practice link selection may be performed based on outdated channel state information (CSI) because of a delay in the feedback link, we study the error rate performance for both perfect and outdated CSI. Since a packet transmission delay is unavoidable with opportunistic link selection, we provide a unified error-rate analysis in terms of a decision threshold β which can be adjusted to achieve buffer stability and a desired average system delay. We show that a diversity gain of two can be achieved for perfect CSI and the optimum BER can be approached even if only a small delay is tolerated.<br
Keywords: Delays; Relays; Bit error rate; Diversity methods; Throughput; Protocols

Delay Minimization for NOMA-MEC Offloading - Ding, Zhiguo; Wing Kwan Ng, Derrick; Schober, Robert; Poor, H. Vincent (IEEE Signal Processing Letters, 2018)
This letter considers the minimization of the offloading delay for nonorthogonal multiple access assisted mobile edge computing (NOMA-MEC). By transforming the delay minimization problem into a form of fractional programming, two iterative algorithms based on, respectively, Dinkelbach's method and Newton's method are proposed. The optimality of both methods is proved and their convergence is compared. Furthermore, criteria for choosing between three possible modes, namely orthogonal multiple access, pure NOMA, and hybrid NOMA, for MEC offloading are established.<br
Keywords: NOMA; Delays; Signal processing algorithms; Iterative Methods; Newton method

Detection of Spatially Modulated Signals via RLS: Theoretical Bounds and Applications - Bereyhi, Ali; Asaad, Saba; Gäde, Bernhard; Müller, Ralf; Poor, H. Vincent (IEEE Transactions on Wireless Communications, 2021)

Detection Schemes and Model Mismatch Analysis for 5G Configured-Grant Access for URLLC - Laue, Friedemann; Karunakaran, Prasanth; Schober, Robert (2019 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2019)
CRIS-Team WoS Importer:2020-08-21

Detector Nonlinearity in Six-Port Radar - Linz, Sarah; Will, Christoph; Lurz, Fabian; Lindner, Stefan; Mann, Sebastian; Schober, Robert; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2017)
This paper presents an in-situ detector characterization and calibration method for differential I/Q Sixport radar systems. A separate calibration of the nonlinear detectors and the linear Six-port front-end enables an independent analysis of errors caused by detector nonlinearity and by the measurement scenario. A linearity analysis of various detectors in Six-port radar systems shows the necessity of a detector calibration for accurate displacement measurements. The calibration is evaluated with three different Six-port front-ends at 24 GHz in divers measurement scenarios. An error reduction of up to 50% has been achieved.
elib2cris::1512001600,linz2017

Deterministic Identification for MC Binomial Channel - Salariseddigh, Mohammad Javad; Jamali, Vahid; Boche, Holger; Deppe, Christian; Schober, Robert (IEEE International Symposium on Information Theory - Proceedings, 2023)
The Binomial channel serves as a fundamental model for molecular communication (MC) systems employing molecule-counting receivers. Here, deterministic identification (DI) is addressed for the discrete-time Binomial channels (DTBC), subject to an average and a peak constraint on the molecule release rate. We establish that the number of different messages that can be reliably identified for the DTBC scales as 2(n log n)R, where n and R are the codeword length and coding rate, respectively. Lower and upper bounds on the DI capacity of the DTBC are developed.
CRIS-Team Scopus Importer:2023-09-29
Keywords: and Molecule-Counting Receivers; Binomial Channel; Deterministic Identification; Molecular Communications

Deterministic Identification for Molecular Communications Over the Poisson Channel - Salariseddigh, Mohammad Javad; Jamali, Vahid; Pereg, Uzi; Boche, Holger; Deppe, Christian; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
Various applications of molecular communications (MC) are event-triggered, and, as a consequence, the prevalent Shannon capacity may not be the right measure for performance assessment. Thus, in this paper, we motivate and establish the identification capacity as an alternative metric. In particular, we study deterministic identification (DI) for the discrete-time Poisson channel (DTPC), subject to an average and a peak molecule release rate constraint, which serves as a model for MC systems employing molecule counting receivers. It is established that the number of different messages that can be reliably identified for this channel scales as 2(nlogn)R, where n and R are the codeword length and coding rate, respectively. Lower and upper bounds on the DI capacity of the DTPC are developed. The obtained large capacity of the DI channel sheds light on the performance of natural DI systems such as natural olfaction, which are known for their extremely large chemical discriminatory power in biology. Furthermore, numerical results for the empirical miss-identification and false identification error rates are provided for finite length codes. This allows us to characterize the behaviour of the error rate for increasing codeword lengths, which complements our theoretically-derived scale for asymptotically large codeword lengths.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Channel Capacity; Channel coding; Codes; Deterministic Identification; Molecular Communication; Nanobioscience; Olfactory; Poisson Channel; Receivers; Task analysis; Upper bound

Deterministic Identification over Poisson Channels - Salariseddigh, Mohammad J.; Pereg, Uzi; Boche, Holger; Deppe, Christian; Schober, Robert (2021 IEEE Globecom Workshops, GC Wkshps 2021 - Proceedings, 2021)
Deterministic identification (DI) for the discrete-time Poisson channel, subject to an average and a peak power constraint, is considered. It is established that the code size scales as 2(nlogn)R, where n and R are the block length and coding rate, respectively. The authors have recently shown a similar property for Gaussian channels [1]. Lower and upper bounds on the DI capacity of the Poisson channel are developed in this scale. Those imply that the DI capacity is infinite in the exponential scale, regardless of the dark current, i.e., the channel noise parameter.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Channel capacity; deterministic codes; identification; Poisson channel

Deterministic K-Identification for MC Poisson Channel With Inter-Symbol Interference - Salariseddigh, Mohammad Javad; Jamali, Vahid; Pereg, Uzi; Boche, Holger; Deppe, Christian; Schober, Robert (IEEE Open Journal of the Communications Society, 2024)
Various applications of molecular communications (MCs) feature an alarm-prompt behavior for which the prevalent Shannon capacity may not be the appropriate performance metric. The identification capacity as an alternative measure for such systems has been motivated and established in the literature. In this paper, we study deterministic K-identification (DKI) for the discrete-time Poisson channel (DTPC) with inter-symbol interference (ISI), where the transmitter is restricted to an average and a peak molecule release rate constraint. Such a channel serves as a model for diffusive MC systems featuring long channel impulse responses and employing molecule-counting receivers. We derive lower and upper bounds on the DKI capacity of the DTPC with ISI when the size of the target message set K and the number of ISI channel taps L may grow with the codeword length n. As a key finding, we establish that for deterministic encoding, assuming that K and L both grow sub-linearly in n, i.e., K = 2κlogn and L = 2llogn with κ + 4l ϵ 0,1), where κ ϵ 0,1) is the identification target rate and l ϵ 0,1/4) is the ISI rate, then the number of different messages that can be reliably identified scales super-exponentially in n, i.e., 2(nlogn)R, where R is the DKI coding rate. Moreover, since l and κ must fulfill κ + 4l ϵ 0,1), we show that optimizing l (or equivalently the symbol rate) leads to an effective identification rate bits/s that scales sub-linearly with n. This result is in contrast to the typical transmission rate bits/s which is independent of n.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Channel capacity; deterministic identification; inter-symbol interference; Interference; molecular communication; Poisson channel; Receivers; Reliability; Symbols; Task analysis; Transmitters; Upper bound

Device Scheduling in Over-the-Air Federated Learning via Matching Pursuit - Bereyhi, Ali; Vagollari, Adela; Asaad, Saba; Müller, Ralf; Gerstacker, Wolfgang; Poor, H. Vincent (IEEE Transactions on Signal Processing, 2023)
This paper develops a class of low-complexity device scheduling algorithms for over-the-air federated learning via the method of matching pursuit. The proposed scheme tracks closely the close-to-optimal performance achieved by difference-of-convex programming, and outperforms significantly the well-known benchmark algorithms based on convex relaxation. Compared to the state-of-the-art, the proposed scheme imposes a drastically lower computational load on the system: for K devices and N antennas at the parameter server, the benchmark complexity scales with (N^2+K)^3 + N^6 while the complexity of the proposed scheme scales with K^p N^q for some 0 p,q ≤ 2 . The efficiency of the proposed scheme is confirmed through the convergence analysis and numerical experiments on CIFAR-10 dataset.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Computational modeling; Costs; Federated learning; Matching pursuit algorithms; Performance evaluation; Scheduling; Task analysis

Diffusive Mobile MC for Controlled-Release Drug Delivery with Absorbing Receiver - Cao, Trang Ngoc; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Wicke, Wayan; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (ICC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
Nanoparticle drug carriers play an important role in facilitating efficient targeted drug delivery, i.e., improving treatment success and reducing drug costs and side effects. However, the mobility of nanoparticle drug carriers poses a challenge in designing drug delivery systems. Moreover, healing results critically depend on the rate and time duration of drug absorption. Therefore, in this paper, we aim to design a controlled-release drug delivery system with a mobile drug carrier that minimizes the total amount of released drugs while ensuring a desired rate of drug absorption during a prescribed time period. We model the mobile drug carrier as a mobile transmitter, the targeted diseased cells as an absorbing receiver, and the channel between the transceivers as a time-variant channel since the carrier mobility results in a time-variant absorption rate of the drug molecules. Based on this, we develop a molecular communication (MC) framework to design the controlled-release drug delivery system. In particular, we develop new analytical expressions for the mean, variance, probability density function, and cumulative distribution function of the channel impulse response (CIR). Equipped with the statistical analysis of the CIR, we design and evaluate the performance of the controlled-release drug delivery system. Numerical results show significant savings in the amount of released drugs compared to a constant-release rate design and reveal the necessity of accounting for drug carrier mobility for reliable drug delivery.<br
Keywords: Drugs; Drug delivery; Absorption; Receivers; Diseases; Transmitters; Control systems

Diffusive Mobile MC With Absorbing Receivers: Stochastic Analysis and Applications - Cao, Trang Ngoc; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Wicke, Wayan; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2019)
This paper presents a stochastic analysis of the time-variant channel impulse response (CIR) of a three dimensional diffusive mobile molecular communication (MC) system where the transmitter, the absorbing receiver, and the molecules can freely diffuse. In our analysis, we derive the mean, variance, probability density function (PDF), and cumulative distribution function (CDF) of the CIR. We also derive the PDF and CDF of the probability p that a released molecule is absorbed at the receiver during a given time period. The obtained analytical results are employed for the design of drug delivery and MC systems with imperfect channel state information. For the first application, we exploit the mean and variance of the CIR to optimize a controlled-release drug delivery system employing a mobile drug carrier. We evaluate the performance of the proposed release design based on the PDF and CDF of the CIR. We demonstrate significant savings in the amount of released drugs compared to a constant-release scheme and reveal the necessity of accounting for the drug-carrier's mobility to ensure reliable drug delivery. For the second application, we exploit the PDF of the distance between the mobile transceivers and the CDF of p to optimize three design parameters of an MC system employing on-off keying modulation and threshold detection. Specifically, we optimize the detection threshold at the receiver, the release profile at the transmitter, and the time duration of a bit frame. We show that the proposed optimal designs can significantly improve the system performance in terms of the bit error rate and the efficiency of molecule usage.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Absorbing receivers; drug delivery; mobile molecular communications; stochastic channel modeling; time-varying channels

Diffusive Mobile Molecular Communications over Time-Variant Channels - Ahmadzadeh, Arman; Jamali, Vahid; Noel, Adam; Schober, Robert (IEEE Communications Letters, 2017)
This letter introduces a formalism for modeling time-variant channels for diffusive molecular communication systems. In particular, we consider a fluid environment where one transmitter nano-machine and one receiver nano-machine are subjected to Brownian motion in addition to the diffusive motion of the information molecules used for communication. Due to the stochastic movements of the transmitter and receiver nano-machines, the statistics of the channel impulse response change over time. We show that the time-variant behavior of the channel can be accurately captured by appropriately modifying the diffusion coefficient of the information molecules. Furthermore, we derive an analytical expression for evaluation of the expected error probability of a simple detector for the considered system. The accuracy of the proposed analytical expression is verified via particle-based simulation of the Brownian motion.
CRIS-Team Scopus Importer:2020-01-31
Keywords: mobile nano-machines; Molecular communication; time-variant channels

Diffusive Molecular Communications with Reactive Molecules: Channel Modeling and Signal Design - Jamali Kooshkghazi, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2018)
This paper focuses on molecular communication (MC) systems using two types of signaling molecules which may participate in a reversible bimolecular reaction in the channel. The motivation for studying these MC systems is that they can realize the concept of constructive and destructive signal superposition, which leads to favorable properties, such as inter-symbol interference (ISI) reduction and avoiding environmental contamination due to continuous release of signaling molecules into the channel. This paper first presents a general formulation for binary modulation schemes that employ two types of signaling molecules and proposes several modulation schemes as special cases. Moreover, two types of receivers are considered: 1) a receiver that is able to observe both types of signaling molecules (2TM) and 2) a simpler receiver that can observe only one type of signaling molecules (1TM). For both of these receivers, the maximum likelihood (ML) detector for general binary modulation is derived under the assumption that the detector has perfect knowledge of the ISI-causing sequence. The performance of this genie-aided ML detector yields an upper bound on the performance of any practical detector. In addition, two suboptimal detectors of different complexity are proposed, namely, an ML-based detector that employs an estimate of the ISI-causing sequence and a detector that neglects the effect of ISI. The proposed detectors, except for the detector that neglects ISI for the 2TM receiver, require knowledge of the channel response (CR) of the considered MC system. Moreover, the CR is needed for performance evaluation of all proposed detectors. However, deriving the CR of MC systems with reactive signaling molecules is challenging since the underlying partial differential equations that describe the reaction-diffusion mechanism are coupled and non-linear. Therefore, we develop an algorithm for efficient computation of the CR and validate its accuracy via particle-based simulation. Simulation results obtained using this CR computation algorithm confirm the effectiveness of the proposed modulation and detection schemes. Moreover, these results show that MC systems with reactive signaling have superior performance relative to those with non-reactive signaling due to the reduction of ISI enabled by the chemical reactions.
CRIS-Team Scopus Importer:2022-06-05
Keywords: and inter-symbol interference; channel modeling; detector design; Diffusive molecular communications; particle-based simulation; reactive signaling

Diffusive Molecular Communications with Reactive Signaling - Jamali Kooshkghazi, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea J. (2018 IEEE International Conference on Communications (ICC), 2018)
This paper focuses on molecular communication (MC) systems where the signaling molecules may participate in a reversible bimolecular reaction in the channel. The motivation for studying these MC systems is that they can realize the concept of constructive and destructive signal superposition, which leads to favorable properties such as inter-symbol interference (ISI) reduction and avoiding environmental contamination due to continuous release of molecules into the channel. This work first derives the maximum likelihood (ML) detector for a binary MC system with reactive signaling molecules under the assumption that the detector has perfect knowledge of the ISI. The performance of this genie-aided ML detector yields an upper bound on the performance of any practical detector. In addition, two suboptimal detectors of different complexity are proposed. The proposed ML detector as well as one of the suboptimal detectors require the channel response (CR) of the considered MC system. Moreover, the CR is needed for the performance evaluation of all proposed detectors. However, analyzing MC with reactive signaling is challenging since the underlying partial differential equations that describe the reaction-diffusion mechanism are coupled and non-linear. Therefore, an algorithm is developed in this paper for efficient computation of the CR to any arbitrary transmit symbol sequence. The accuracy of this algorithm is validated via particle-based simulation. Simulation results using the developed CR algorithm show that the performance of the proposed suboptimal detectors can approach that of the genie-aided ML detector. Moreover, these results show that MC systems with reactive signaling have superior performance relative to those with non-reactive signaling due to the reduction of ISI enabled by the chemical reactions.<br
Keywords: Detectors; Transmitters; Receivers; Biochemistry; Modulation; Computational modeling; Molecular communication

Diffusive molecular communication with disruptive flows - Noel, Adam; Cheung, Karen C.; Schober, Robert (2014 IEEE International Conference on Communications (ICC), 2014)
In this paper, we study the performance of detectors in a diffusive molecular communication environment where steady uniform flow is present. We derive the expected number of information molecules to be observed in a passive spherical receiver, and determine the impact of flow on the assumption that the concentration of molecules throughout the receiver is uniform. Simulation results show the impact of advection on detector performance as a function of the flow's magnitude and direction. We highlight that there are disruptive flows, i.e., flows that are not in the direction of information transmission, that lead to an improvement in detector performance as long as the disruptive flow does not dominate diffusion and sufficient samples are taken.<br
Keywords: Receivers; Detectors; Transmitters; Noise; Error probability; Accuracy; Molecular communication

Digital Signal Transmission in Magnetic Induction based Wireless Underground Sensor Networks - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2015)

Direct electricity trading in smart grid: A coalitional game analysis - Lee, Woongsup; Xiang, Lin; Schober, Robert; Wong, Vincent W. S. (IEEE Journal on Selected Areas in Communications, 2014)
Integration of distributed generation based on renewable energy sources into the power system has gained popularity in recent years. Many small-scale electricity suppliers (SESs) have recently entered the electricity market, which has been traditionally dominated by a few large-scale electricity suppliers. The emergence of SESs enables direct trading (DT) of electricity between SESs and end-users (EUs), without going through retailers, and promotes the possibility of improving the benefits to both parties. In this paper, the cooperation between SESs and EUs in DT is analyzed based on coalitional game theory. In particular, an electricity pricing scheme that achieves a fair division of revenue between SESs and EUs is analytically derived by using the asymptotic Shapley value. The asymptotic Shapley value is shown to be in the core of the coalitional game such that no group of SESs and EUs has an incentive to abandon the coalition, which implies the stable operation of DT for the proposed pricing scheme. Unlike the existing pricing schemes that typically require multiple stages of calculations and real time information about each participant, the electricity price for the proposed scheme can be determined instantaneously based on the number of participants in DT and statistical information about electricity supply and demand. Therefore, the proposed pricing scheme is suitable for practical implementation. Using computer simulations, the price of electricity for the proposed DT scheme is examined in various environments, and the numerical results validate the asymptotic analysis. Moreover, the revenues of the SESs and EUs are evaluated for various types of SESs and different numbers of participants in DT. The optimal ratio of different types of SESs is also investigated. © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: coalitional game; direct trading; electricity market; renewable energy; Shapley value; Smart grid

Disaster Detection in Magnetic Induction based Wireless Sensor Networks with Limited Feedback - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IFIP Wireless Days, 2014)

Discrete Load-Modulated Single-RF MIMO Transmitters - Sedaghat, Mohammad Ali; Müller, Ralf; Fischer, Georg; Ali, Arslan (20th Int’l ITG Workshop on Smart Antennas, 2016)

Distributed Beamforming for Magnetic Induction based Body Area Sensor Networks - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE Global Communications Conference (Globecom), 2016)

Distributed Multi-Antenna Frequency-Selective Energy Beamforming with Joint Total and Individual Power Constraints - Luo, Bing; Yeoh, Phee Lep; Schober, Robert; Krongold, Brian S. (IEEE Transactions on Green Communications and Networking, 2022)
We analyze distributed multi-antenna energy beamforming over frequency selective fading channels in wireless power transfer (WPT) systems with joint total and individual transmit power constraints. The constraints allow the WPT system to limit energy consumption for cost or environmental factors, and prevent individual coordinated energy transmitters (CETs) from overdriving their high-powered amplifiers due to hardware limitations. The harvested power at the energy receiver is modeled as an arbitrary non-linear, continuous, and non-decreasing function of the received radio frequency (RF) power. We show that the optimal frequency selective energy beamforming solution for K CETs with M antennas each is equivalent to maximizing the total RF power coherently combined at the energy receiver over N shared subchannels. We obtained the optimal frequency selective energy beamforming strategy with the following insightful properties: First, for any subchannel, either all antennas of all K CETs allocate zero power to this subchannel (i.e., inactive), or all antennas of all K CETs allocate non-zero power to this subchannel (i.e., active). Second, for the active subchannels, we show that the optimal power allocation obeys a proportionality principle for the powers from all antennas of all K CETs, which reveals that higher powers are not necessarily allocated to subchannels with higher channel gains. Third, we prove that optimally no more than T+1 subchannels are selected for energy beamforming, where T (less than K) is the number of CETs transmitting at their maximum individual powers due to the total power constraint. Based on the above properties, we show that the energy beamforming solution can be efficiently achieved via solving a low-complexity dual problem in simpler form with only K+1 variables compared to the original primal problem with NMK variables. Numerical examples verify our theoretical findings and show the impact of the joint total and individual power constraints on the average harvested power.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Antennas; Array signal processing; distributed energy beamforming; frequency-selective channels; KKT conditions.; optimal power allocation; Radio frequency; Radio transmitters; Receiving antennas; Resource management; total and individual power constraints; Transmitting antennas; Wireless power transfer

Distributed Optimization of Hierarchical Small Cell Networks: A GNEP Framework - Wang, Jiaheng; Guan, Wei; Huang, Yongming; Schober, Robert; You, Xiaohu (IEEE Journal on Selected Areas in Communications, 2017)
Deployment of small cell base stations (SBSs) overlaying the coverage area of a macrocell BS (MBS) results in a two-tier hierarchical small cell network. Cross-tier and inter-tier interference not only jeopardize primary macrocell communication but also limit the spectral efficiency of small cell communication. This paper focuses on distributed interference management for downlink small cell networks. We address the optimization of transmit strategies from both the game theoretical and the network utility maximization (NUM) perspectives and show that they can be unified in a generalized Nash equilibrium problem (GNEP) framework. Specifically, the small cell network design is first formulated as a GNEP, where the SBSs and MBS compete for the spectral resources by maximizing their own rates while satisfying global quality of service (QoS) constraints. We analyze the GNEP via variational inequality theory and propose distributed algorithms, which only require the broadcasting of some pricing information, to achieve a generalized Nash equilibrium (GNE). Then, we also consider a nonconvex NUM problem that aims to maximize the sum rate of all BSs subject to global QoS constraints. We establish the connection between the NUM problem and a penalized GNEP and show that its stationary solution can be obtained via a fixed point iteration of the GNE. We propose GNEP-based distributed algorithms that achieve a stationary solution of the NUM problem at the expense of additional signaling overhead and complexity. The convergence of the proposed algorithms is proved and guaranteed for properly chosen algorithm parameters. The proposed GNEP framework can scale from a QoS constrained game to an NUM design for small cell networks by trading off signaling overhead and complexity.<br
Keywords: Macrocell Networks; Interference; Computer Architecture; Microprocessors; Quality of Service; Games; Optimization

Distributed user-centric scheduling for visible light communication networks - Chen, Lingjiao; Wang, Jiaheng; Zhou, Jiantao; Ng, Derrick Wing Kwan; Schober, Robert; Zhao, Chunming (Optics Express, 2016)
Visible light communication (VLC) networks, consisting of multiple light-emitting diodes (LEDs) acting as optical access points (APs), can provide low-cost high-rate data transmission to multiple users simultaneously in indoor environments. However, the performance of VLC networks is severely limited by the interference between different users. In this paper, we establish a distributed user-centric scheduling framework based on stable marriage theory, and propose a novel decentralized scheduling method to manage interference by forming flexible amorphous cells for all users. The proposed scheduling method has provable low computational complexity and requires only the exchange of a few 1-bit messages between the APs and the users but not the feedback of the channel state information of the entire network. We further show that the proposed method can achieve both user-wise and system-wise optimality as well as a certain level of fairness. Simulation results indicate that our decentralized user-centric scheduling method outperforms existing centralized approaches in terms of throughput, fairness, and computational complexity.
CRIS-Team Scopus Importer:2020-01-31

Distribution of Modal Damping in Absorptive Shoebox Rooms - Schäfer, Maximilian; Prawda, Karolina; Rabenstein, Rudolf; Schlecht, Sebastian J. (IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2023)
The image-source method is widely applied to compute room impulse responses (RIRs) of shoebox rooms with arbitrary damping. However, with increasing RIR lengths, the number of image sources grows rapidly, leading to slow computation. We propose a method to estimate the damping density of a damped shoebox room, which in turn can provide the energy decay necessary to model the stochastic late reverberation. The damping density is derived from a modal decomposition that is compliant with the ISM solution. We show that the proposed method gives a more accurate estimate of the energy decay than previous methods and can be efficiently computed regardless of the RIR lengths. While we focus on the derivation and evaluation, the main practical applications of the proposed model include, e.g., the faster synthesis of late reverb and the analysis of multi-slope decays.
CRIS-Team Scopus Importer:2023-10-13
Keywords: Damping Density; Image Source Method; Modal Decomposition; Reverberation; Shoebox Rooms

Diversity and delay analysis of buffer-aided BICM-OFDM relaying - Islam, Toufiqul; Ikhlef, Aissa; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2013)
In this paper, we study a cooperative diversity scheme for wireless systems where the relay is equipped with a buffer. We consider practical frequency-selective channels and adopt the combination of bit interleaved coded modulation and orthogonal frequency division multiplexing (BICM-OFDM). We propose a novel link selection protocol for BICM-OFDM systems where the relay either transmits or receives in a given time slot depending on the quality of the links. We derive a closed-form upper bound for the asymptotic worst-case pairwise error probability (PEP) and the diversity gain of the considered buffer-aided relaying scheme for both infinite and finite buffer size. We show that significant diversity gains can be achieved with buffer-aided relaying compared to conventional relaying at the expense of larger packet delays. In fact, for buffers of infinite (or very large) size, the diversity gain is doubled for links with identical frequency diversity, and an even higher diversity gain advantage is possible for links with non-identical frequency diversities. Furthermore, we perform an exact closed-form average delay analysis for buffers of both finite and infinite size which provides important insight into the achieved delay-performance tradeoff. The derived analytical results and performance gains are corroborated by extensive simulation results. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM; Buffer-aided relaying; Cooperative diversity; OFDM

Downlink Massive MU-MIMO with Successively-Regularized Zero Forcing Precoding - Krishnamoorthy, Aravindh; Schober, Robert (IEEE Wireless Communications Letters, 2022)
In this letter, we consider linear precoding for downlink massive multi-user (MU) multiple-input multiple-output (MIMO) systems. We propose the novel successively-regularized zero forcing (SRZF) precoding, which exploits successive null spaces of the MIMO channels of the users, along with regularization, to control the inter-user interference (IUI) and to enhance performance and robustness to imperfect channel state information (CSI) at the base station (BS). We study the IUI characteristics of the proposed SRZF precoding for perfect and imperfect CSI at the BS. Furthermore, via computer simulations, we compare the sum rate of SRZF precoding with those of several baseline schemes including conventional and regularized zero forcing (ZF) precoding. Our simulation results reveal that, for massive MIMO systems with inter-user channel correlations, the proposed SRZF precoding significantly outperforms the considered baseline schemes for both perfect and imperfect CSI at the BS.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Decoding; Downlink; MIMO communication; Null space; Precoding; Robustness; Symmetric matrices

Downlink MIMO-RSMA with Successive Null-Space Precoding - Krishnamoorthy, Aravindh; Schober, Robert (IEEE Transactions on Wireless Communications, 2022)
In this paper, we consider the precoder design for an underloaded or critically loaded downlink multi-user multiple-input multiple-output (MIMO) communication system. We propose novel precoding and decoding schemes which enhance system performance based on rate splitting at the transmitter and single-stage successive interference cancellation at the receivers. The proposed successive null-space (SNS) precoding utilizes linear combinations of the null-space basis vectors of the successively augmented MIMO channel matrices of the users as precoding vectors to adjust the inter-user-interference experienced by the receivers. We formulate a non-convex weighted sum rate optimization problem for the precoding vectors and the associated power allocation for the proposed SNS-based MIMO-rate-splitting multiple access (RSMA) scheme. We obtain a suboptimal solution for this problem via successive convex approximation. Moreover, we study the robustness of the proposed precoding scheme to imperfect channel state information (CSI) at the base station via derivative-based sensitivity analysis. Our analysis and simulation results reveal the enhanced performance and robustness of the proposed SNS-based MIMO-RSMA scheme over several baseline multi-user MIMO schemes, especially for imperfect CSI.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Communication systems; Downlink; MIMO communication; Optimization; Precoding; Robustness; Symbols

Downlink Performance Improvements in (A)synchronous GPRS Networks using Single/Multiple Antenna Interference Cancellation Techniques - Popova, Larissa; Meyer, Raimund; Gerstacker, Wolfgang; Koch, Wolfgang (12th European Wireless Conference 2006 - Enabling Technologies for Wireless Multimedia Communications, 2011)
The aim of this paper is to assess GPRS data throughput of GSM networks for single and multiple antenna interference cancellation (SAIC/MAIC) receivers in the terminals. This is done by using a two-step top-down simulation methodology. Both synchronous and asynchronous networks with traditional European reuses of 1/3 and 3/9 are considered. It turns out that SAIC/MAIC receivers are very beneficial also for European network planning. The results indicate a substantial gain in data throughput in the order of 20-35% for SAIC compared to terminals with a conventional receiver. A further dramatic increase in throughput up to 120% can be achieved by terminals using an MAIC receiver. In spite of the widespread view that a maximum gain will be achieved for a synchronized network, where the amount of overlap between desired signal and interference can be controlled, our results show that the performance of both network types is very simila

Downlink Precoder Design for Two-User Power-Domain MIMO-NOMA with Excess Degrees of Freedom - Krishnamoorthy, Aravindh; Schober, Robert; Ding, Zhiguo (2019 IEEE International Conference on Communications Workshops (ICC Workshops), 2019)
In this paper, we consider downlink precoder design for two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) for the scenario where the receivers have fewer antennas than the transmitter. We propose a novel precoding scheme which takes advantage of the excess degrees of freedom (DoFs) at the transmitter to enhance MIMO-NOMA performance. The proposed precoder achieves simultaneous diagonalization of the MIMO channels of both users, assuming self-interference cancellation at one of the receivers, thereby lowering the overall decoding complexity. The performance of the proposed scheme is analyzed in terms of the ergodic rate using results from non-asymptotic random matrix theory. Our results show that the proposed scheme significantly outperforms orthogonal multiple access (OMA) and a benchmark precoder performing simultaneous diagonalization via generalized singular value decomposition (GSVD).<br

Downlink scheduling with transmission strategy selection for multi-cell MIMO systems - Niu, Binglai; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
In this paper, we study downlink scheduling with transmission strategy selection in multi-cell multiple-input multiple-output (MIMO) systems. Depending on the level of inter-cell interference experienced by a user, the scheduler can choose between two MIMO transmission strategies, namely, spatial multiplexing and interference alignment. We formulate an optimization problem which aims to jointly select a user and the corresponding transmission strategy for each base station in order to maximize the overall system utility while stabilizing all transmission queues. We first develop a centralized dynamic scheduling scheme with transmission strategy selection by using a stochastic network optimization approach. To reduce the communication overhead, we then propose a distributed scheduling algorithm which only requires limited message exchange between the base stations. We also consider the impact of imperfect channel state information on the scheduling schemes and propose an efficient rate adjustment method to improve the performance for this case. Simulation results show that the performance of the proposed distributed scheduling scheme is close to that of the centralized scheduling scheme, and both schemes achieve a better performance than schemes employing a single transmission strategy. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: interference alignment; Scheduling; spatial multiplexing; stochastic network optimization

Dynamic Sectorization in Multi-Panel Massive MIMO Systems - Antunovic, André; Amiri, Ebrahim; Biefel, Christian; Steinbock, Gerhard; Aulin, Jocelyn; Liers, Frauke; Gerstacker, Wolfgang (2021 IEEE 4th 5G World Forum, 2021)

Early cancer detection in blood vessels using mobile nanosensors - Mosayebi, Reza; Ahmadzadeh, Arman; Wicke, Wayan; Jamali, Vahid; Schober, Robert; Nasiri-Kenari, Masouhmeh (IEEE Transactions on Nanobioscience, 2019)
In this paper, we propose using mobile nanosensors (MNSs) for early stage anomaly detection. For concreteness, we focus on the detection of cancer cells located in a particular region of a blood vessel. These cancer cells produce and emit special molecules, so-called biomarkers, which are symptomatic for the presence of anomaly, into the cardiovascular system. Detection of cancer biomarkers with conventional blood tests is difficult in the early stages of a cancer due to the very low concentration of the biomarkers in the samples taken. However, close to the cancer cells, the concentration of the cancer biomarkers is high. Hence, detection is possible if a sensor with the ability to detect these biomarkers is placed in the vicinity of the cancer cells. Therefore, in this paper, we study the use of MNSs that are injected at a suitable injection site and can move through the blood vessels of the cardiovascular system, which potentially contain cancer cells. These MNSs can be activated by the biomarkers close to the cancer cells, where the biomarker concentration is sufficiently high. Eventually, the MNSs are collected by a fusion center (FC), where their activation levels are read and exploited to declare the presence of anomaly. We analytically derive the biomarker concentration in a network of interconnected blood vessels as well as the probability mass function of the MNSs' activation levels and validate the obtained results via particle-based simulations. Then, we derive the optimal decision rule for the FC regarding the presence of anomaly assuming that the entire network is known at the FC. Finally, for the FC, we propose a simple sum detector that does not require knowledge of the network topology. Our simulations reveal that while the optimal detector achieves a higher performance than the sum detector, both proposed detectors significantly outperform a benchmark scheme that uses fixed nanosensors at the FC.
CRIS-Team Scopus Importer:2019-05-14
Keywords: advection-diffusion; anomaly detection; cardiovascular system; mobile nanosensor; Molecular communication; optimal and suboptimal detectors

Effective capacity of communication systems over κ–μ shadowed fading channels - Zhang, Jiayi; Dai, Linglong; Gerstacker, Wolfgang; Wang, Zhaocheng (Electronics Letters, 2015)
The effective capacity of communication systems over generalised κ - μ shadowed fading channels is investigated. A novel and analytical expression for the exact effective capacity is derived in terms of the extended generalised bivariate Meijer's- G function. To intuitively reveal the impact of the system and channel parameters on the effective capacity, closed-form expressions are derived for the effective capacity in the asymptotically high signal-to-noise ratio regime. The results demonstrate that the effective capacity is a monotonically increasing function of channel fading parameters κ and μ as well as the shadowing parameter m , while it decays to zero when the delay constraint θ →

Efficient Charging of Access Limited Wireless Underground Sensor Networks - Kisseleff, Steven; Chen, Xiaoyang; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2016)

Efficient Detectors for Telegram Splitting-Based Transmission in Low Power Wide Area Networks With Bursty Interference - Kisseleff, Steven; Kneissl, Jakob; Kilian, Gerd; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2020)
Low Power Wide Area (LPWA) networks are known to be highly vulnerable to external in-band interference in terms of packet collisions which may substantially degrade the system performance. In order to enhance the performance in such cases, the telegram splitting (TS) method has been proposed recently. This approach exploits the typical burstiness of the interference via forward error correction (FEC) and offers a substantial performance improvement compared to other methods for packet transmissions in LPWA networks. While it has been already demonstrated that the TS method benefits from knowledge on the current interference state at the receiver side, corresponding practical receiver algorithms of high performance are still missing. The modeling of the bursty interference via Markov chains leads to the optimal detector in terms of a-posteriori symbol error probability. However, this solution requires a high computational complexity, assumes an a-priori knowledge on the interference characteristics and lacks flexibility. We propose a further developed scheme with increased flexibility and introduce an approach to reduce its complexity while maintaining a close-to-optimum performance. In particular, the proposed low-complexity solution substantially outperforms existing practical methods in terms of packet error rate and therefore is highly beneficial for practical LPWA network scenarios.
CRIS-Team WoS Importer:2021-01-08

Efficient Matrix Multiplication: The Sparse Power-of-2 Factorization - Müller, Ralf; Gäde, Bernhard; Bereyhi, Ali (2020 Information Theory and Applications Workshop, ITA 2020, 2020)
We present an algorithm to reduce the computational effort for the multiplication of a given matrix with an unknown column vector. The algorithm decomposes the given matrix into a product of matrices whose entries are either zero or integer powers of two utilizing the principles of sparse recovery. While classical low resolution quantization achieves an accuracy of 6 dB per bit, our method can achieve many times more than that for large matrices. Numerical and analytical evidence suggests that the improvement actually grows unboundedly with matrix size. Due to sparsity, the algorithm even allows for quantization levels below 1 bit per matrix entry while achieving highly accurate approximations for large matrices. Applications include, but are not limited to, neural networks, as well as fully digital beam-forming for massive MIMO and millimeter wave applications.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Quantization (signal); Neural networks; Millimeter wave technology; Massive MIMO; Sparse matrices; Matrix decomposition; Gain

Efficient receivers for GSM MUROS downlink transmission - Meyer, Raimund; Gerstacker, Wolfgang; Obernosterer, Frank; Ruder, Michael; Schober, Robert (2009 IEEE 20th International Symposium on Personal, Indoor and Mobile Radio Communications, 2010)
Currently, Multiple Users Reusing One Slot (MUROS) is discussed in 3GPP GERAN as an extension of the GSM standard. In MUROS, two overlaid GMSK signals are transmitted in the same time slot and at the same frequency resource. By this, capacity of existing GSM networks in principle can be doubled and up to four half rate voice users can share one time slot. In this paper, channel estimation and detection is investigated for the MUROS downlink. Two novel channel estimation algorithms are presented, taking into account the specifics of the MUROS downlink. For detection, a joint MLSE of both user signals can be applied in case of noise limited scenarios. For interference limited environments, it turns out that approaches based on the mono interference cancellation (MIC) algorithm for single antenna interference cancellation (SAIC) are more favorable. It is shown that the standard MIC algorithm performs sufficiently well and could be used for a fast introduction of MUROS in existing GSM networks. For enhanced performance, a novel algorithm based on MIC along with successive interference cancellation is proposed. The presented results demonstrate that an even better performance as the GSM reference performance before introduction of SAIC can be obtained for MUROS if well-designed receivers are use

Efficient supporting methods for adaptive pilot-aided channel estimation in OFDM systems - Rohde, Christian; Lipp, Stefan; Stadali, Holger; Gerstacker, Wolfgang; Koch, Wolfgang (18th International OFDM Workshop 2014, InOWo 2014, 2014)
Approaches for adaptive pilot-aided channel estimation in frequency domain are well established for orthogonal frequency-division multiplexing (OFDM) systems. To further enhance the performance of both the adaptive channel estimation and the entire receiver, three efficient supporting methods are discussed in this paper. First, the well-known concept of non-rectangular windowing is recalled due to its fundamental importance and benefits over the conventional rectangular windowing. Secondly, an approach is proposed to reduce the suboptimality of channel estimation algorithms applying real-valued filtering, which can even lead to convergence speed gains compared to complex-valued filtering in scenarios where real-valued filters are theoretically suboptimum. Third, a novel scheme treating continuous as scattered pilots (CASP) is introduced to solve the reference data problem of adaptive channel estimation algorithms. Simulation results for a scenario according to the hybrid satellite/terrestrial broadcasting system DVB-SH, show that these methods combine a low complexity with a noticeably increased receiver robustness.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Adaptive pilot-aided channel estimation; Block recursive least-squares (BRLS) algorithm; Enhanced real-valued filtering; Normalized block least-mean-square (NBLMS) algorithm; Orthogonal frequency-division multiplexing (OFDM); Treating continuous as scattered pilots (CASP)

Electric vehicle charging stations with renewable power generators: A game theoretical analysis - Lee, Woongsup; Xiang, Lin; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Smart Grid, 2015)
In this paper, we study the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). As electric vehicles (EVs) become more popular, a competition among EVCSs to attract EVs is inevitable. Thereby, each EVCS sets its electricity price to maximize its revenue by taking into account the competition with neighboring EVCSs. We analyze the competitive interactions between EVCSs using game theory, where relevant physical constraints such as the transmission line capacity, the distance between EV and EVCS, and the number of charging outlets at the EVCSs are taken into account. We show that the game played by EVCSs is a supermodular game and there exists a unique pure Nash equilibrium for best response algorithms with arbitrary initial policy. The electricity price and the revenue of EVCSs are evaluated via simulations, which reveal the benefits of having RPGs at the EVCSs.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Electric vehicle (EV); electric vehicle charging station (EVCS); game theory; pricing; renewable power generation

Electric vehicle charging stations with renewable power generators: A game theoretical analysis - Lee, Woongsup; Xiang, Lin; Schober, Robert; Wong, Vincent W. S. (2015 IEEE Power & Energy Society General Meeting, 2015)
Summary form only given. In this paper, we study the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). As electric vehicles (EVs) become more popular, a competition among EVCSs to attract EVs is inevitable. Thereby, each EVCS sets its electricity price to maximize its revenue by taking into account the competition with neighboring EVCSs. We analyze the competitive interactions between EVCSs using game theory, where relevant physical constraints such as the transmission line capacity, the distance between EV and EVCS, and the number of charging outlets at the EVCSs are taken into account. We show that the game played by EVCSs is a supermodular game and there exists a unique pure Nash equilibrium for best response algorithms with arbitrary initial policy. The electricity price and the revenue of EVCSs are evaluated via simulations, which reveal the benefits of having RPGs at the EVCS

Empfangsverfahren für den WLAN Standard IEEE 802.11b - Menden, Mirko (2003)

Empirical coordination in a triangular multiterminal network - Bereyhi, Ali; Bahrami, Mohsen; Mirmohseni, Mahtab; Aref, Mohammad Reza (IEEE International Symposium on Information Theory (ISIT), 2013)
In this paper, we investigate the problem of the empirical coordination in a triangular multiterminal network. A triangular multiterminal network consists of three terminals where two terminals observe two external i.i.d correlated sequences. The third terminal wishes to generate a sequence with desired empirical joint distribution. For this problem, we derive inner and outer bounds on the empirical coordination capacity region. It is shown that the capacity region of the degraded source network and the inner and outer bounds on the capacity region of the cascade multiterminal network can be directly obtained from our inner and outer bounds. For a cipher system, we establish key distribution over a network with a reliable terminal, using the results of the empirical coordination. As another example, the problem of rate distortion in the triangular multiterminal network is discussed in which a distributed doubly symmetric binary source is availabl

Enabling Secure Wireless Communications via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Enabling Wireless-Powered IoT through Incentive-based UAV Swarm Orchestration - Mekikis, Prodromos Vasileios; Bouzinis, Pavlos S.; Mitsiou, Nikos A.; Tegos, Sotiris A.; Tyrovolas, Dimitrios; Papanikolaou, Vasileios; Karagiannidis, George K. (IEEE Open Journal of the Communications Society, 2023)
The rapidly growing demand for vast numbers of Internet of Things (IoT), in both urban and rural areas, necessitates their ceaseless and automatic energy supply. This is particularly vital in cases where the IoT sensors are deployed in distant or dangerous locations outside human reach. In this direction, unmanned aerial vehicles (UAVs) with wireless power transfer (WPT) capabilities can address this issue, due to their flexible deployment. To this end, we devise an architecture in which a UAV swarm covers the energy demand of an IoT network, while concurrently, the UAVs fulfil their energy needs through a charging station (CS) infrastructure. A practical energy model is considered, which takes into account the UAVs’ battery level, energy consumption due to transition to different locations, hovering, and WPT. Also, to capture the UAV-CS interaction, an economic model is introduced. The UAVs aim to maximize their profit by transferring energy to the IoT, while the CSs aim to maximize their profit by recharging the UAVs. To ensure a profit-wise stable CS-UAV association, while providing energy coverage to the IoT, we formulate a many-to-one matching game. Due to inter-dependencies between UAVs’ utilities, i.e., externalities, a matching algorithm with two-sided exchange-stability is proposed. To further evaluate the considered system, we design an optimization scheme which performs the UAV-CS assignment towards maximizing the energy coverage of the IDs. Numerical results showcase the matching algorithm’s ability to provide near-optimal energy coverage to the IDs, while balancing fairness among the competing agents’ profit, compared to the optimization scheme.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Autonomous aerial vehicles; Batteries; charging stations; Games; Internet of Things; Internet of Things; Optimization; Resource management; Sensors; stable matching with externalities; UAV swarm; wireless power transfer

Energy-aware revenue optimization for cellular networks via device-to-device communication - Wu, Yuan; Wang, Jiaheng; Qian, Liping; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
In this paper, we investigate the revenue optimization of a cellular system, which intelligently provides access services to device-to-device users (DUs) by reusing the resource-blocks (RBs) of cellular users (CUs). While charging the DUs for services, the cellular system compensates for the additional power consumption costs of the CUs to meet their required quality of service (QoS), and hence aims at achieving the best tradeoff between charging the DUs and affording the CUs' costs to maximize its own revenue. We formulate this energy-aware revenue optimization problem as a joint RB-reuse and power control problem, which we further decompose into a power control problem for each individual CU-DU pair and a DU-selection problem for selecting appropriate DUs to reuse the CUs' RBs. For each CU-DU pair, we derive the optimal power allocation in closed form and the maximum gain of the cellular system from this pair. Based on the gains of all CU-DU pairs, we then consider the DU-selection problem as maximum weighted matching on a bipartite graph and solve it by using linear relaxation. Numerical results validate our analysis regarding the optimal power allocation for each CU-DU pair and the BS's optimal selection of the DUs to reuse the CUs' RBs such that the BS's revenue is maximized.<br
Keywords: Throughput; Resource management; Power demand; Optimization; Wireless communication; Power control; Copper

Energy-Efficient 5G Outdoor-to-Indoor Communication: SUDAS Over Licensed and Unlicensed Spectrum - Wing Kwan Ng, Derrick; Breiling, Marco; Rohde, Christian; Burkhardt, Frank; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we study the design of the user selection, the time allocation to uplink and downlink, and the transceiver processing matrix for uplink and downlink multicarrier transmission employing a shared user equipment (UE)-side distributed antenna system (SUDAS). The proposed SUDAS simultaneously utilizes licensed frequency bands and unlicensed frequency bands with large available bandwidths (e.g. the millimeter wave bands) to enable a spatial multiplexing gain for single-antenna UEs to improve the energy efficiency and throughput of 5th generation (5G) outdoor-to-indoor communication. The resource allocation algorithm design is formulated as a nonconvex optimization problem for the maximization of the end-to-end system energy efficiency (bits/Joule). The nonconvex matrix optimization problem is converted to an equivalent nonconvex scalar optimization problem for multiple parallel channels, which is solved by an asymptotically globally optimal iterative algorithm. Besides, we propose a suboptimal algorithm, which finds a locally optimal solution of the nonconvex optimization problem. Simulation results illustrate that the proposed resource allocation algorithms for SUDAS achieve a significant performance gain in terms of system energy efficiency and spectral efficiency compared to conventional baseline systems by offering multiple parallel data streams for single-antenna UEs.<br
Keywords: Resource management; OFDM; Wireless communication; Bandwidth; MIMO; Uplink; Downlink

Energy Efficient Cooperative Communications in Aggregated VLC/RF Networks with NOMA - Rallis, Konstantinos G.; Papanikolaou, Vasileios; Diamantoulakis, Panagiotis D.; Tegos, Sotiris A.; Dowhuszko, Alexis A.; Khalighi, Mohammad Ali; Karagiannidis, George K. (IEEE Transactions on Communications, 2023)
Optimizing the energy efficiency (EE) of wireless networks is one of the key priorities in the design of beyond 5G mobile technologies. In this pursuit, the use of new frequency bands, in combination with advanced multiple access protocols and cooperative communications strategies, has recently shown promising results. To this end, this paper investigates an indoor wireless network that aggregates communication resources in visible light and radio-frequency (RF) bands, taking advantage of the complementary aspects of the two technologies. More specifically, a non-orthogonal multiple access (NOMA) scheme is introduced for the visible light communication (VLC) downlink, such that cell-edge users experiencing a weak VLC signal enhance their aggregated data rate with the aid of cooperative communications over RF sidelinks (i.e., device-to-device links). The optimal resource allocation strategy over both VLC and RF bands is derived aiming at EE maximization based on the Dinkelbach’s algorithm and successive convex approximation. Additionally, for the sake of flexibility, a weighted EE metric is proposed for the characterization of the aggregated VLC/RF network performance. Simulation results are provided to validate the proposed analysis, revealing the impact of various design and system parameters, such as the weighting factors, quality of service requirements, and channel conditions.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Aggregated VLC/RF networks; Cooperative NOMA; Energy efficiency; Energy efficiency; Hybrid power systems; NOMA; Protocols; Radio frequency; Resource allocation; Resource management; Sidelink communications; Visible light communication; Visible light communications

Energy-Efficient Digital Beamforming by Means of Linear Computation Coding - Müller, Ralf (IEEE Workshop on Statistical Signal Processing Proceedings, 2021)
We utilize the new concept of linear computation coding to reduce the computational effort in digital beamforming. For that purpose the beamforming matrix is decomposed into the product of two or more matrices which are only composed of zeros and signed powers of two. As shown in [1], this allows for a multifold reduction of the required number of additions (multiplications are treated as multiple additions and bit-shifts) per entry of the beamforming matrix.We also provide an approximate analysis of the performance of linear computation coding for matrices with independent identically distributed matrices.For a typical implementation in beamforming, the proposed algorithm reduces the number of required addition units several times. To achieve the accuracy of 4-bit signed integer arithmetic for 1k-vectors, no multipliers and only half an adder per matrix entry is needed.
CRIS-Team Scopus Importer:2021-09-10
Keywords: digital beamforming; fixed-point arithmetic; quantization

Energy-efficient power allocation for M2M communications with energy harvesting transmitter - Ng, Derrick Wing Kwan; Schober, Robert (2012 IEEE Globecom Workshops, GC Wkshps 2012, 2012)
In this paper, power allocation for energy-efficient point-to-point machine-to-machine (M2M) communication systems with multiple energy harvesting sources is studied. Under a deterministic system setting, we formulate the power allocation problem as a non-convex optimization problem over a finite horizon taking into account the circuit energy consumption, finite battery storage capacities, and a minimum required data rate. The considered non-convex optimization problem is transformed into a convex optimization problem by exploiting the properties of fractional programming which results in an efficient optimal off-line iterative power allocation algorithm. In each iteration, the transformed problem is solved by using dual decomposition and a recursive power allocation solution is obtained for maximization of the energy efficiency of data transmission (bit/Joule delivered to the receiver). © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Energy-Efficient Resource Allocation and Antenna Selection for IRS-assisted Multi-Cell Downlink Networks - Rezaei, Atefeh; Khalilimahmoudabadi, Ataollah; Jalali, Jalal; Shafiei, Hossein; Wu, Qingqing (IEEE Wireless Communications Letters, 2022)
This letter considers a network-assisted intelligent reflecting surface (IRS) technology. We aim to adopt an energy-efficient strategy via an antenna selection (AS) framework that determines which base station (BS) antennas transmit the data to the user equipment. In particular, we select the best set of antennas to increase energy efficiency (EE) while reducing power consumption. Also, the network takes advantage of the IRS system to increase the coverage and overall throughput of the network. We first propose an efficient algorithm for the considered scenario based on the successive convex approximation (SCA). Then we employ the Dinkelbach method that jointly selects the best set of antennas and optimizes their beamforming. Second, by introducing the slack variable and SCA method, we propose a tight approximation to solve the passive beamforming at the IRS. Simulation results unveil the performance of the proposed method and its influence on the power consumption at each antenna’s RF chain.
CRIS-Team Scopus Importer:2022-04-08
Keywords: antenna selection (AS); Antennas; Array signal processing; energy efficiency (EE).; Intelligent reflecting surface (IRS); Interference; MISO communication; Optimization; Power demand; Transmitting antennas

Energy-Efficient Resource Allocation for Wireless Powered Communication Networks - Wu, Qingqing; Tao, Meixia; Ng, Derrick Wing Kwan; Chen, Wen; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
This paper considers a wireless powered communication network (WPCN), where multiple users harvest energy from a dedicated power station and then communicate with an information receiving station. Our goal is to investigate the maximum achievable energy efficiency (EE) of the network via joint time allocation and power control while taking into account the initial battery energy of each user. We first study the EE maximization problem in the WPCN without any system throughput requirement. We show that the EE maximization problem for the WPCN can be cast into EE maximization problems for two simplified networks via exploiting its special structure. For each problem, we derive the optimal solution and provide the corresponding physical interpretation, despite the nonconvexity of the problems. Subsequently, we study the EE maximization problem under a minimum system throughput constraint. Exploiting fractional programming theory, we transform the resulting nonconvex problem into a standard convex optimization problem. This allows us to characterize the optimal solution structure of joint time allocation and power control and to derive an efficient iterative algorithm for obtaining the optimal solution. Simulation results verify our theoretical findings and demonstrate the effectiveness of the proposed joint time and power optimization.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Energy efficiency; power control; time allocation; wireless powered networks

Energy-efficient resource allocation in multi-cell OFDMA systems with limited backhaul capacity - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2012)
We study resource allocation for energy-efficient communication in multi-cell orthogonal frequency division multiple access (OFDMA) downlink networks with cooperative base stations (BSs). We formulate the resource allocation problem for joint BS zero-forcing beamforming (ZFBF) transmission as a non-convex optimization problem which takes into account the circuit power consumption, the limited backhaul capacity, and the minimum required data rate. We transform the considered problem in fractional form into an equivalent optimization problem in subtractive form, which enables the derivation of an efficient iterative resource allocation algorithm. In each iteration, a low-complexity suboptimal semi-orthogonal user selection policy is computed. Besides, by using the concept of perturbation function, we show that in the considered systems under some general conditions, the duality gap with respect to the power optimization variables is zero despite the non-convexity of the primal problem. Thus, dual decomposition can be used in each iteration to derive an efficient closed-form power allocation solution for maximization of the energy efficiency of data transmission (bit/Joule delivered to the users). Simulation results illustrate that the proposed iterative resource allocation algorithm converges in a small number of iterations, and unveil the trade-off between energy efficiency, network capacity, and backhaul capacity: (1) In the low transmit power regime, an algorithm which achieves the maximum spectral efficiency may also achieve the maximum energy efficiency; (2) a high spectral efficiency does not necessarily result in a high energy efficiency; (3) spectral efficiency is always limited by the backhaul capacity; (4) energy efficiency increases with the backhaul capacity only until the maximum energy efficiency is achieved. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy efficiency; green communication; limited backhaul; network MIMO; non-convex optimization; resource allocation

Energy-efficient resource allocation in multiuser OFDM systems with wireless information and power transfer - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2013)
In this paper, we study the resource allocation algorithm design for multiuser orthogonal frequency division multiplexing (OFDM) downlink systems with simultaneous wireless information and power transfer. The algorithm design is formulated as a non-convex optimization problem for maximizing the energy efficiency of data transmission (bit/Joule delivered to the users). In particular, the problem formulation takes into account the minimum required system data rate, heterogeneous minimum required power transfers to the users, and the circuit power consumption. Subsequently, by exploiting the method of timesharing and the properties of nonlinear fractional programming, the considered non-convex optimization problem is solved using an efficient iterative resource allocation algorithm. For each iteration, the optimal power allocation and user selection solution are derived based on Lagrange dual decomposition. Simulation results illustrate that the proposed iterative resource allocation algorithm achieves the maximum energy efficiency of the system and reveal how energy efficiency, system capacity, and wireless power transfer benefit from the presence of multiple users in the system. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Energy-efficient resource allocation in OFDMA systems with hybrid energy harvesting base station - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
We study resource allocation algorithm design for energy-efficient communication in an orthogonal frequency division multiple access (OFDMA) downlink network with hybrid energy harvesting base station (BS). Specifically, an energy harvester and a constant energy source driven by a non-renewable resource are used for supplying the energy required for system operation. We first consider a deterministic offline system setting. In particular, assuming availability of non-causal knowledge about energy arrivals and channel gains, an offline resource allocation problem is formulated as a non-convex optimization problem over a finite horizon taking into account the circuit energy consumption, a finite energy storage capacity, and a minimum required data rate. We transform this non-convex optimization problem into a convex optimization problem by applying time-sharing and exploiting the properties of non-linear fractional programming which results in an efficient asymptotically optimal offline iterative resource allocation algorithm for a sufficiently large number of subcarriers. In each iteration, the transformed problem is solved by using Lagrange dual decomposition. The obtained resource allocation policy maximizes the weighted energy efficiency of data transmission (weighted bit/Joule delivered to the receiver). Subsequently, we focus on online algorithm design. A conventional stochastic dynamic programming approach is employed to obtain the optimal online resource allocation algorithm which entails a prohibitively high complexity. To strike a balance between system performance and computational complexity, we propose a low complexity suboptimal online iterative algorithm which is motivated by the offline algorithm. Simulation results illustrate that the proposed suboptimal online iterative resource allocation algorithm does not only converge in a small number of iterations, but also achieves a close-to-optimal system energy efficiency by utilizing only causal channel state and energy arrival information. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy harvesting; green communication; non-convex optimization; resource allocation

Energy-Efficient Transmission for Uplink NOMA in Wireless-Powered D2D Communications - Zhou, Qingjie; Zhang, Jing; Sun, Yan (2018 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2018)
CRIS-Team WoS Importer:2019-04-16

Energy-Efficient Transmission for Wireless Powered D2D Communication Networks - Zhang, Yanxia; Zhang, Jing; Sun, Yan; Ng, Derrick Wing Kwan (International Conference on Communications (ICC), 2017)
This paper studies resource allocation for energy-efficient device-to-device (D2D) communications in an overlay wireless cellular networks, where a D2D transmitter first harvests energy from a base station (BS) and then communicates with a D2D receiver. The resource allocation algorithm design is formulated as a non-convex optimization problem for the maximization of the energy efficiency (bits/Joule) of the D2D system. The proposed problem formulation takes into account the minimum required harvested energy, maximum duration of signal transmission, and minimum required system throughput. Exploiting fractional programming theory, we transform the non-convex problem into a standard convex optimization problem. This allows us to characterize the optimal solution structure of joint time, frequency, and power allocation and to derive an efficient iterative algorithm for obtaining the optimal solution. We reveal that the optimal energy-efficient D2D communication in this framework should occur if the D2D transmitter consumes all the harvested energy from the BS. Simulation results demonstrate the energy efficiency improvement brought by the proposed optimal resource allocation compared to two baseline schemes.
Keywords: Energy Transfer; Global optimization; Iterative Methods; Lagrange Multipliers; Mobile telecommunication systems; Resource allocation; Wireless networks

Energy-efficient transmission for wireless powered multiuser communication networks - Wu, Qingqing; Tao, Meixia; Ng, Derrick Wing Kwan; Chen, Wen; Schober, Robert (IEEE International Conference on Communications, 2015)
This paper considers wireless powered communication networks (WPCN). Our goal is to investigate the maximum network energy efficiency (EE) by joint time allocation and power control while taking account the initial battery energy level of each user. It is shown that the EE maximization problem for the WPCN can be cast into the EE maximization problems for two independent networks, i.e., purely wireless powered communication networks (PWPCN) or initial energy limited communication networks (IELCN). For the PWPCN, we find that: 1) in the wireless energy transfer (WET) stage, the power station always transmits with its maximum power; 2) it is not necessary for all users to transmit signals in the wireless information transmission (WIT) stage, but all scheduled users will deplete all of their energy; 3) the maximum system EE can always be achieved by exhausting all the available time. Based on these observations, we derive a closed-form expression for the system EE based on the user EE, which transforms the original problem into a user scheduling problem that can be solved efficiently. While for the IELCN, we reveal that the most energy-efficient transmission strategy is to only schedule the user who has the highest user EE. Simulation results validate our theoretical findings and demonstrate the effectiveness of the proposed scheme.
CRIS-Team Scopus Importer:2020-01-31

Energy Harvesting Receiver Modelling and Resource Allocation in SWIPT - Boshkovska, Elena (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Enhanced Downlink Capacity in UMTS supported by Mobile-to-Mobile Data Transfer - Popova, Larissa; Herpel, Thomas; Koch, Wolfgang (6th International IFIP-TC6 Networking Conference, 2007)
The goal of this work is first to analyze the feasibility of a peer-to-peer file sharing technique in mobile cellular environments, taking into account key characteristics and peculiarities of the UMTS Radio Access Network (UTRAN). The concept is referred here to as mobile-tomobile (m2m). Next, our research efforts explore the performance benefits of m2m file sharing applications in UMTS networks in terms of releasing overall downlink capacity, which can be used to provide better Quality of Service (QoS) for real-time services. To evaluate the performance of the proposed m2m concept we conducted extensive simulation studies with appropriately modified radio propagation models for low antenna heights for both, transmitter and receiver, as it is typical for m2m. Two alternative scenarios of serving user requests (m2m network mode and conventional UMTS mode) have been constructed and analyzed. The results indicate a dramatic increase in service probability and overall throughput gain of up to 85 % in a UMTS network, supported by the m2m data transmission mode. Furthermore, results show that by a well-designed m2m routing policy and proper utilization of currently not used uplink resources (due to asymmetric uplink/downlink traffic load) substantial reduction of the expected file download time can be achieved. © IFIP International Federation for Information Processing 2007.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD7.enhanc
Keywords: Asymmetric uplink/downlink traffic load; Data exchange policy; Direct mobile-to-mobile data transfer; Released downlink capacity; Unified radio interface; WCDMA

Enhanced GSM Broadcast Receiver using the Phase Output of a Sub-GHz Transceiver - Erhardt, Stefan; Gäde, Bernhard; Kölpin, Alexander; Weigel, Robert (2018 48th European Microwave Conference (EuMC), 2018)
With Sub-GHz transceivers it is possible to receive GSM broadcast messages, for example for implementing cell-ID based localization. In this publication the phase information output of an ultra-low power Sub-GHz transceiver is used for a software defined GSM receiver. For enhanced results channel estimation and equalization can be applie
Keywords: GSM; Receivers; Transceivers; Frequency modulation; Registers; Channel estimation; GSM; signal processing; channel estimation; equalizers

Enhancing LTE with Cloud-RAN and Load-Controlled Parasitic Antenna Arrays - Artuso, Matteo; Boviz, Dora; Checko, Aleksandra; Christiansen, Henrik; Clerckx, Bruno; Cottatellucci, Laura; Gesbert, David; Gizas, Bobby; Gopalasingham, Aravinthan; Khan, Faheem; Kelif, Jean-Marc; Müller, Ralf; et al. (IEEE Communications Magazine, 2016)

Entwicklung und Analyse eines Soft-Output CPFSK-Demodulators - Zarei, Shahram (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)

Equalization Concepts for EDGE - Gerstacker, Wolfgang; Schober, Robert (IEEE Transactions on Wireless Communications, 2002)
In this paper, an equalization concept for the novel radio access scheme Enhanced Data rates for GSM Evolution (EDGE) is proposed by which high performance can be obtained at moderate computational complexity. Because high-level modulation is employed in EDGE, optimum equalization as usually performed in Global System for Mobile Communications (GSM) receivers is too complex and suboptimum schemes have to be considered. It is shown that delayed decision-feedback sequence estimation (DDFSE) and reduced-state sequence estimation (RSSE) are promising candidates. For various channel profiles, approximations for the bit error rate of these suboptimum equalization techniques are given and compared with simulation results for DDFSE. It turns out that a discrete-time prefilter creating a minimum-phase overall impulse response is indispensible for a favorable tradeoff between performance and complexity. Additionally, the influence of channel estimation and of the receiver input filter is investigated and the reasons for performance degradation compared to the additive white Gaussian noise channel are indicated. Finally, the overall system performance attainable with the proposed equalization concept is determined for transmission with channel coding. © 2002 IEEE.
UnivIS-Import:2015-03-09:Pub.2002.tech.IE.mobilk.equali
Keywords: EDGE; Equalization; Mobile communications; Reduced-state trellis-based equalizers

Equalization for WLAN IEEE 802.11b - Gerstacker, Wolfgang; Jonietz, Christof; Schober, Robert (Conference Proceedings, 2004)
In this paper, complementary code keying (CCK) transmission over frequency-selective fading channels is investigated. Since CCK can be interpreted as a block code, an appropriate vector signal model is introduced. Based on pairwise error probabilities, we derive a performance approximation for optimum detection in general frequency-selective Ricean fading channels and compare the theoretical results with simulations. Because optimum maximum-likelihood sequence estimation (MLSE) is not practical for large channel delay spreads, minimum mean-squared error decision-feedback equalization (MMSE-DFE) is employed. Two different DFE approaches are considered here: (a) the conventional scalar DFE and (b) a block-based DFE optimized for the underlying vector signal model. Furthermore, a reduced-state sequence estimation (RSSE) algorithm is designed for CCK. Numerical results are given for fixed channels and common indoor fading channel profiles.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.equali
Keywords: Wireless LAN; Decision feedback Equalizers; Maximum likelihood estimation; Delay estimation; Frequency-selective fading channels; Block codes; Pairwise error probability; Frequency; Maximum likelihood detection; Algorithm design and analysis

Ergodic Sum Rate Analysis of UAV-Based Relay Networks With Mixed RF-FSO Channels - Ajam, Hedieh; Najafi, Marzieh; Jamali, Vahid; Schober, Robert (IEEE Open Journal of the Communications Society, 2020)
Unmanned aerial vehicle (UAV)-based communications is a promising new technology that can add a wide range of new capabilities to the current network infrastructure. Given the flexibility, cost-efficiency, and convenient use of UAVs, they can be deployed as temporary base stations (BSs) for on-demand situations like BS overloading or natural disasters. In this work, a UAV-based communication system with radio frequency (RF) access links to the mobile users (MUs) and a free-space optical (FSO) backhaul link to the ground station (GS) is considered. In particular, the RF and FSO channels in this network depend on the UAV's positioning and (in)stability. The relative position of the UAV with respect to the MUs impacts the likelihood of a line-of-sight (LOS) connection in the RF link and the instability of the hovering UAV affects the quality of the FSO channel. Thus, taking these effects into account, we analyze the end-to-end system performance of networks employing UAVs as buffer-aided (BA) and non-buffer-aided (non-BA) relays in terms of the ergodic sum rate. Simulation results validate the accuracy of the proposed analytical derivations and reveal the benefits of buffering for compensation of the random fluctuations caused by the UAV's instability. Our simulations also show that the ergodic sum rate of both BA and non-BA UAV-based relays can be enhanced considerably by optimizing the positioning of the UAV. We further study the impact of the MU density and the weather conditions on the end-to-end system performance.
CRIS-Team WoS Importer:2021-12-24

Erratum: Vector precoding for gaussian mimo broadcast channels: Impact of replica symmetry breaking (IEEE Transactions on Information Theory (2012) 58:3 (1413-1440)) - Zaidel, Benjamin M.; Müller, Ralf; Moustakas, Aris L.; De Miguel, Rodrigo (IEEE Transactions on Information Theory, 2012)

Error Propagation and Overhead Reduced Channel Estimation for RIS-Aided Multi-User mmWave Systems - Peng, Zhendong; Pan, Cunhua; Zhou, Gui; Ren, Hong (Proceedings of the International Symposium on Wireless Communication Systems, 2022)
In this paper, we propose a novel two-stage based uplink channel estimation strategy with reduced pilot overhead and error propagation for a reconfigurable intelligent surface (RIS)-aided multi-user (MU) millimeter wave (mmWave) system. Specifically, in Stage I, with the carefully designed RIS phase shift matrix and introduced matching matrices, all users jointly transmit the pilot signals for the estimation of the correlation factors between different paths of the common RIS-base station (BS) channel, which achieves significant multi-user diversity gain. Then, the inherent scaling ambiguity and angle ambiguity of the mmWave cascaded channel are utilized to construct an ambiguous common RIS-BS channel composed of the estimated correlation factors. In Stage II, with the constructed ambiguous common RIS-BS channel, each user independently sends reduced pilots for estimating their specific user-RIS channel so as to obtain the entire cascaded channel. The theoretical number of pilots required for the proposed method is analyzed and the simulation results are presented to validate the effectiveness of this strategy.
CRIS-Team Scopus Importer:2022-12-09
Keywords: channel estimation; millimeter wave; multi-user systems; Reconfigurable intelligent surface

Evolution of NOMA Toward Next Generation Multiple Access (NGMA) for 6G - Liu, Yuanwei; Zhang, Shuowen; Mu, Xidong; Ding, Zhiguo; Schober, Robert; Al-Dhahir, Naofal; Hossain, Ekram; Shen, Xuemin (IEEE Journal on Selected Areas in Communications, 2022)
Due to the explosive growth in the number of wireless devices and diverse wireless services, such as virtual/augmented reality and Internet-of-Everything, next generation wireless networks face unprecedented challenges caused by heterogeneous data traffic, massive connectivity, and ultra-high bandwidth efficiency and ultra-low latency requirements. To address these challenges, advanced multiple access schemes are expected to be developed, namely next generation multiple access (NGMA), which are capable of supporting massive numbers of users in a more resource- and complexity-efficient manner than existing multiple access schemes. As the research on NGMA is in a very early stage, in this paper, we explore the evolution of NGMA with a particular focus on non-orthogonal multiple access (NOMA), i.e., the transition from NOMA to NGMA. In particular, we first review the fundamental capacity limits of NOMA, elaborate on the new requirements for NGMA, and discuss several possible candidate techniques. Moreover, given the high compatibility and flexibility of NOMA, we provide an overview of current research efforts on multi-antenna techniques for NOMA, promising future application scenarios of NOMA, and the interplay between NOMA and other emerging physical layer techniques. Furthermore, we discuss advanced mathematical tools for facilitating the design of NOMA communication systems, including conventional optimization approaches and new machine learning techniques. Next, we propose a unified framework for NGMA based on multiple antennas and NOMA, where both downlink and uplink transmissions are considered, thus setting the foundation for this emerging research area. Finally, several practical implementation challenges for NGMA are highlighted as motivation for future work.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 6G; 6G mobile communication; Interference; machine learning; mathematical optimization; MIMO communication; multi-antenna techniques; next generation multiple access (NGMA); Next generation networking; NOMA; non-orthogonal multiple access (NOMA); Silicon carbide; Time division multiple access

Experimental Molecular Communication Testbed Based on Magnetic Nanoparticles in Duct Flow - Unterweger, Harald; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali Kooshkghazi, Vahid; Alexiou, Christoph; Fischer, Georg; Weigel, Robert; Schober, Robert (19th IEEE International Workshop on Signal Processing Advances in Wireless Communications, 2018)
Simple and easy to implement testbeds are needed to further advance molecular communication research. To this end, this paper presents an in-vessel molecular communication testbed using magnetic nanoparticles dispersed in an aqueous suspension as they are also used for drug targeting in biotechnology. The transmitter is realized by an electronic pump for injection via a Yconnector. A second pump provides a background flow for signal propagation. For signal reception, we employ a susceptometer, an electronic device including a coil, where the magnetic particles move through and generate an electrical signal. We present experimental results for the transmission of a binary sequence and the system response following a single injection. For this flowdriven particle transport, we propose a simple parameterized mathematical model for evaluating the system response. <br
Keywords: Molecular communication; magnetic nanoparticles

Experimental Molecular Communication Testbed Based on Magnetic Nanoparticles in Duct Flow - Unterweger, Harald; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Schober, Robert (2018 IEEE 19th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2018)
Simple and easy to implement testbeds are needed to further advance molecular communication research. To this end, this paper presents an in-vessel molecular communication testbed using magnetic nanoparticles dispersed in an aqueous suspension as they are also used for drug targeting in biotechnology. The transmitter is realized by an electronic pump for injection via a Y-connector. A second pump provides a background flow for signal propagation. For signal reception, we employ a susceptometer, an electronic device including a coil, where the magnetic particles move through and generate an electrical signal. We present experimental results for the transmission of a binary sequence and the system response following a single injection. For this flow-driven particle transport, we propose a simple parameterized mathematical model for evaluating the system Response.<br
Keywords: Electron tubes; Magnetic nanoparticles; Receivers; Molecular communication; Suspensions; Magnetic susceptibility; Transmitters

Experimental Research in Synthetic Molecular Communications - Part I - Lotter, Sebastian; Brand, Lukas; Jamali, Vahid; Schäfer, Maximilian; Loos, Helene; Unterweger, Harald; Greiner, Sandra; Kirchner, Jens; Alexiou, Christoph; Drummer, Dietmar; Fischer, Georg; Büttner, Andrea; et al. (IEEE Nanotechnology Magazine, 2023)
Since its emergence from the communication engineering community around one and a half decades ago, the field of Synthetic Molecular Communication (SMC) has experienced continued growth, both in the number of technical contributions from a vibrant community and in terms of research funding. Throughout this process, the vision of SMC as a novel, revolutionary communication paradigm has constantly evolved, driven by feedback from theoretical and experimental studies, respectively. It is believed that especially the latter ones will be crucial for the transition of SMC towards a higher technology readiness level in the near future. In this spirit, we present here a comprehensive survey of experimental research in SMC. In particular, this survey focuses on highlighting the major drivers behind different lines of experimental research in terms of the respective envisioned applications. This approach allows us to categorize existing works and identify current research gaps that still hinder the development of practical SMC-based applications. Our survey consists of two parts: this paper and a companion paper. While the companion paper focuses on SMC with relatively long communication ranges, this paper covers SMC over short distances of typically not more than a few millimeters.<br

Experimental Research in Synthetic Molecular Communications - Part II - Lotter, Sebastian; Brand, Lukas; Jamali, Vahid; Schäfer, Maximilian; Loos, Helene M.; Unterweger, Harald; Greiner, Sandra; Kirchner, Jens; Alexiou, Christoph; Drummer, Dietmar; Fischer, Georg; Buettner, Andrea; et al. (IEEE Nanotechnology Magazine, 2023)
In this second part of our survey on experimental research in Synthetic Molecular Communication (SMC), we review works on long-range SMC systems, i.e., systems with communication ranges of more than a few millimeters. Despite the importance of experimental research for the evolution of SMC towards a mature communication paradigm that will eventually support revolutionary applications beyond the reach of today’s prevalent communication paradigms, the existing body of literature is still comparatively sparse. Long-range SMC systems have been proposed in the literature for information transmission in two types of fluid media, liquid and air. While both types of SMC systems, i.e., liquid-based and air-based systems, rely on encoding and transmitting information using molecules, they differ substantially in terms of the physical system designs and in the type of applications they are intended for. In this article, we present a systematic characterization of experimental works on long-range SMC that reveals the major drivers of these works in terms of the respective target applications. Furthermore, the physical designs for long-range SMC proposed in the literature are comprehensively reviewed. In this way, our survey will contribute to making experimental research in this field more accessible and identifying novel directions for future research.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Copper; Detectors; Fluorescence; Ions; Liquids; Pipelines; Prototypes

Experimental System for Molecular Communication in Pipe Flow With Magnetic Nanoparticles - Wicke, Wayan; Unterweger, Harald; Kirchner, Jens; Brand, Lukas; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2021)
In the emerging field of molecular communication (MC), testbeds are needed to validate theoretical concepts, motivate applications, and guide further modeling efforts. To this end, this paper presents a flexible and extendable in-vessel testbed for flow-based macroscopic MC, abstractly modeling, e.g., a part of a chemical reactor or a blood vessel. Signaling is based on injecting non-reactive superparamagnetic iron oxide nanoparticles (SPIONs) dispersed in an aqueous suspension into a tube with background flow. A commercial magnetic susceptometer is used for non-intrusive downstream signal reception. To shed light on the operation of the testbed, we identify the physical mechanisms governing the transmission, propagation, and reception of the information-carrying SPIONs. Moreover, to facilitate system design, we propose a closed-form parametric expression for the end-to-end channel impulse response (CIR). The proposed CIR model is shown to consistently capture the experimentally observed distance-dependent impulse response peak heights and peak decays for transmission distances from 540. Moreover, to validate our testbed, reliable communication is demonstrated based on experimental data for model-agnostic and model-based detection methods.
Created from Fastlane, Scopus look-up
Keywords: Biology; Chemicals; Coatings; Electron tubes; Experimental system; fluid flow; injection; Iron; magnetic nanoparticles; Magnetic nanoparticles; Magnetic susceptibility; molecular communication; SPIONs; testbed.

Exploiting Tensor-Based Bayesian Learning for Massive Grant-Free Random Access in LEO Satellite Internet of Things - Ying, Ming; Chen, Xiaoming; Shao, Xiaodan (IEEE Transactions on Communications, 2023)
With the rapid development of Internet of Things (IoT), low earth orbit (LEO) satellite IoT is expected to provide low power, massive connectivity and wide coverage IoT applications. In this context, this paper provides a massive grant-free random access (GF-RA) scheme for LEO satellite IoT. This scheme does not need to change the transceiver, but transforms the received signal to a tensor decomposition form. By exploiting the characteristics of the tensor structure, a Bayesian learning algorithm for joint active device detection and channel estimation during massive GF-RA is designed. Theoretical analysis shows that the proposed algorithm has fast convergence and low complexity. Finally, extensive simulation results confirm its better performance in terms of error probability for active device detection and normalized mean square error for channel estimation over baseline algorithms in LEO satellite IoT. Especially, it is found that the proposed algorithm requires short preamble sequences and support massive connectivity with a low power, which is appealing to LEO satellite IoT.
CRIS-Team WoS Importer:2023-05-05

Fast Approximate AIG-Based Synthesis - Heil, Annika; Keszöcze, Oliver (International Workshop on Boolean Problems, 2022)
Approximate Computing is a design paradigm that trades off computational accuracy for gains in non-functional aspects such as smaller area, shorter delay, or less power consumption. Synthesizing approximate circuits is a difficult task due to the inherent complexity of evaluating error metrics used to indicate the quality of the approximated circuit. We present a novel and fast greedy, bucket-based Approximate Logic Synthesis technique working on AND-Inverter Graphs that iteratively performs XOR and constant replacements. It minimizes both, the area of the approximated circuit and, the error introduced by the approximations. We exploit properties of the replacement operations to speed up the computation of the weighted Hamming distance error metric, allowing the algorithm to have a very short execution time. The effectiveness of the presented method is evaluated in a set of experiments, including the state-of-the-art benchmark library EvoApproxLibLITE<br
Keywords: Approximate Computing; (XOR)-And-Inverter Graph; Logic Synthesis

Fast Approximate AIG-Based Synthesis - Heil, Annika; Keszöcze, Oliver (Advanced Boolean Techniques, 2023)
Approximate Computing is a design paradigm that trades off computational accuracy for gains in non-functional aspects such as smaller area, shorter delay, or less power consumption. Synthesizing approximate circuits is a difficult task due to the inherent complexity of evaluating error metrics used to indicate the quality of the approximated circuit. We present a novel and fast greedy, bucket-based Approximate Logic Synthesis technique working on AND-Inverter Graphs that iteratively performs XOR and constant replacements. It minimizes both, the area of the approximated circuit and, the error introduced by the approximations. We exploit properties of the replacement operations to speed up the computation of the weighted Hamming distance error metric, allowing the algorithm to have a very short execution time. The effectiveness of the presented method is evaluated in a set of experiments, including the state-of-the-art benchmark library EvoApproxLibLITE</sup

Faster-Than-Nyquist Asynchronous NOMA Outperforms Synchronous NOMA - Li, Shuangyang; Wei, Zhiqiang; Yuan, Weijie; Yuan, Jinhong; Bai, Baoming; Ng, Derrick Wing Kwan; Hanzo, Lajos (IEEE Journal on Selected Areas in Communications, 2022)
Faster-than-Nyquist (FTN) signaling aided non-orthogonal multiple access (NOMA) is conceived and its achievable rate is quantified in the presence of random link delays of the different users. We reveal that exploiting the link delays may potentially lead to a signal-to-interference-plus-noise ratio (SINR) gain, while transmitting the data symbols at FTN rates has the potential of increasing the degree-of-freedom (DoF). We then unveil the fundamental trade-off between the SINR and DoF. In particular, at a sufficiently high symbol rate, the SINR gain vanishes while the DoF gain achieves its maximum, where the achievable rate is almost (1 + beta) times higher than that of the conventional synchronous NOMA transmission in the high signal-to-noise ratio (SNR) regime, with beta being the roll-off factor of the signaling pulse. Our simulation results verify our analysis and demonstrate considerable rate improvements over the conventional power-domain NOMA scheme.
CRIS-Team WoS Importer:2022-04-01

Feedback-Aware Precoding for Millimeter Wave Massive MIMO Systems - Ghanaatian, Reza; Jamali, Vahid; Burg, Andreas; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2019)
Millimeter wave (mmWave) communication is a promising solution for coping with the ever-increasing mobile data traffic because of its large bandwidth. To enable a suffi-cient link margin, a large antenna array employing directional beamforming, which is enabled by the availability of channel state information at the transmitter (CSIT), is required. However, CSIT acquisition for mmWave channels introduces a huge feedback overhead due to the typically large number of transmit and receive antennas. Leveraging properties of mmWave channels, this paper proposes a precoding strategy which enables a flexible adjustment of the feedback overhead. In particular, the optimal unconstrained precoder is approximated by selecting a variable number of elements from a basis that is constructed as a function of the transmitter array response, where the number of selected basis elements can be chosen according to the feedback constraint. Simulation results show that the proposed precoding scheme can provide a near-optimal solution if a higher feedback overhead can be afforded. For a low overhead, it can still provide a good approximation of the optimal precoder.
CRIS-Team Scopus Importer:2020-01-31

Firefly Ultra Dense Networks with mmWave Fronthaul Links - Ackermann, Katharina; Jamali, Vahid; Gerstacker, Wolfgang; Wartenberg, Fredrik; Aulin, Jocelyn; Krishnan, Rajet; Schober, Robert (2018 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2018)
CRIS-Team WoS Importer:2019-04-16

Fractionally Spaced Equalization and Decision Feedback Sequence Detection for Diffusive MC - Cao, Trang Ngoc; Jamali, Vahid; Zlatanov, Nikola; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (IEEE Communications Letters, 2021)
In this letter, we consider diffusive molecular communication (MC) systems affected by signal-dependent diffusive noise, inter-symbol interference, and external noise. We design linear and nonlinear fractionally-spaced equalization schemes and a detection scheme which combines decision feedback and sequence detection (DFSD). In contrast to the symbol-rate equalization schemes in the MC literature, the proposed equalization and detection schemes exploit multiple samples of the received signal per symbol interval to achieve lower bit error rates (BERs) than existing schemes. The proposed DFSD scheme achieves a BER which is very close to that achieved by maximum likelihood sequence detection, but with lower computational complexity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: equalization; sequence detection; Signal-dependent noise

Full-Diversity Minimum Decoding Complexity Differential Quasi-Orthogonal STBC - Morsi, Rania; Linduska, Alexander; Lindner, Jurgen (IEEE Global Telecommunications Conference - GLOBECOM 2011, 2011)
In this paper, we introduce a low decoding complexity space-time modulation scheme that achieves full transmit diversity without the need of channel knowledge at the transmitter (Tx) nor at the receiver (Rx). The scheme is based on differential encoding of a low-complex quasi-orthogonal space-time block code (STBC). The idea of the differential encoding is based on mapping the original system to an equivalent system which is composed of two orthogonal subsystems. The differential encoding and decoding approach is described and the receiver metric is derived. The described technique is valid for any number of transmit antennas M for which a square orthogonal code of size M/2 exists, and is valid for any number of receive antennas. The proposed scheme is favourable in that it has single complex symbol decoding complexity while achieving a performance close to other differential quasi orthogonal codes of higher complexity and a remarkable performance advantage compared to differential orthogonal schemes especially at high data rates.<br
Keywords: decoding; diversity reception; space-time block codes; transmitting antennas; full-diversity minimum decoding complexity differential quasi-orthogonal STBC; low-complex quasi-orthogonal space- time block code; transmitting antennas; square orthogonal code; high data rates; Decoding; Encoding; Transmitting antennas; Complexity theory; Receiving antennas; Measurement

Fundamentals of Signal Design for WPT and SWIPT - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Standardized wireless communication systems based on radio frequency (RF) radiation are one of the important technologies in the modern societies. The emergence of low‐power autonomous wireless devices, such as ubiquitous sensing through wireless sensor networks (WSN) or an Internet‐of‐Things (IoT), has made the powering of such devices another challenge for the next generation 5G mobile networks. This chapter provides an overview of a wireless power transfer (WPT) architecture and the latest advances in the field of signal design for WPT and sequence wireless information power transfer (SWIPT). In order to demonstrate the feasibility of the proposed signal and system designs for WPT, prototyping and experimentation are required. Utilizing the WPT waveform designs shows that the rectifier nonlinearity has a significant impact on the performance of a SWIPT system.<br
Keywords: Wireless communication; Radio frequency; Rectennas; Wireless sensor Networks; Transmitters; Receivers; Signal design

Fundamentals of Wireless Information and Power Transfer: From RF Energy Harvester Models to Signal and System Designs - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Wing Kwan Ng, Derrick; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2018)
Radio waves carry both energy and information simultaneously. Nevertheless, radio-frequency (RF) transmissions of these quantities have traditionally been treated separately. Currently, the community is experiencing a paradigm shift in wireless network design, namely, unifying wireless transmission of information and power so as to make the best use of the RF spectrum and radiation as well as the network infrastructure for the dual purpose of communicating and energizing. In this paper, we review and discuss recent progress in laying the foundations of the envisioned dual purpose networks by establishing a signal theory and design for wireless information and power transmission (WIPT) and identifying the fundamental tradeoff between conveying information and power wirelessly. We start with an overview of WIPT challenges and technologies, namely, simultaneous WIPT (SWIPT), wirelessly powered communication networks (WPCNs), and wirelessly powered backscatter communication (WPBC). We then characterize energy harvesters and show how WIPT signal and system designs crucially revolve around the underlying energy harvester model. To that end, we highlight three different energy harvester models, namely, one linear model and two nonlinear models, and show how WIPT designs differ for each of them in single-user and multi-user deployments. Topics discussed include rate-energy region characterization, transmitter and receiver architectures, waveform design, modulation, beamforming and input distribution optimizations, resource allocation, and RF spectrum use. We discuss and check the validity of the different energy harvester models and the resulting signal theory and design based on circuit simulations, prototyping, and experimentation. We also point out numerous directions that are promising for future research.<br
Keywords: Radio frequency; System analysis and design; Receivers; Wireless Networks; Electronic mail; Backscatter

Gaussian multiple-access channels with weighted energy constraint - Müller, Ralf; et al. (1998 Information Theory Workshop, ITW 1998, 1998)
The Gaussian multiple-access channel with weighted energy constraint Esum = ∑k, Ek/(dk)2 models the situation in cellular multiuser communication more accurately than the standard approacb with dk = 1,∀k. The minimum weighted sum energy Esum is shown to be only achievable at a unique energy tupel (El, ..., Ek), if all weights differ in amplitude. Moreover, the theory is generalized to a multiple receiver system describing cellular communication systems with optimum multiple cell-site processing. While for single-receiver systems the optimum energy tupel is a vertex of the allowed energy region, i.e. successive cancellation is possible, for a multi-receiver system this does not hold in general.

Generalized Wireless-Powered Communications: When to Activate Wireless Power Transfer? - Wu, Qingqing; Zhang, Guangchi; Ng, Denick Wing Kwan; Chen, Wen; Schober, Robert (IEEE Transactions on Vehicular Technology, 2019)
Wireless-powered communication network (WPCN) is a key technology to power energy limited massive devices, such as on-board wireless sensors in autonomous vehicles, for Internet-of-Things applications. Conventional WPCNs rely only on dedicated downlink wireless power transfer (WPT), which is practically inefficient due to the significant energy loss in wireless signal propagation. Meanwhile, ambient energy harvesting is highly appealing as devices can scavenge energy from various existing energy sources (e.g., solar energy and cellular signals). Unfortunately, the randomness of the availability of these energy sources cannot guarantee stable communication services. Motivated by the above statements, we consider a generalized WPCN where the devices can not only harvest energy from a dedicated multiple-antenna power station (PS), but can also exploit stored energy stemming from ambient energy harvesting. Since the dedicated WPT consumes system resources, if the stored energy is sufficient, WPT may not be needed to maximize the weighted sum rate. To analytically characterize this phenomenon, we derive the condition for WPT activation and reveal how it is affected by the different system parameters. Subsequently, we further derive the optimal resource allocation policy for the cases that WPT is activated and deactivated, respectively. In particular, it is found that when WPT is activated, the optimal energy beamforming at the PS does not depend on the devices' stored energy, which is shown to lead to a new unfairness issue. Simulation results verify our theoretical findings and demonstrate the effectiveness of the proposed optimal resource allocation.
CRIS-Team WoS Importer:2019-09-10

Genetic Algorithm for Sparse Optimization of Mills Cross Array Used in Underwater Acoustic Imaging - Teng, Duo; Li, Yatian; Yang, Hu; Wei, Zhiqiang; Li, Yaan (Journal of Marine Science and Engineering, 2022)
Underwater acoustic imaging employs a special form of array which includes numerous transducer elements to achieve beamforming. Although a large-scale array can bring high imaging resolution, it will also cause difficulties in hardware complexity and real-time application. In this paper, in order to reduce the number of array elements, a sparse optimization for Mills cross is pro-posed, considering the elements’ distributions and weights design. The improved genetic algorithm is adopted to generate evolutions for sparse solution. In order to ensure effective convergence and successful evolution, relevant genetic operators are proposed, including appropriate population coding, correct fitness function, reasonable selection strategy and efficient two-point orthogonal crossover, among others. Essentially, a satisfied sparse solution is a result of mutual restraint between array elements’ survivals and their weights. The simulations reveal that our sparse cross array decreases the number of elements by 8.25% compared to the conventional Mills cross multiplicative array, while keeping the advantages of narrow main lobe width and low sidelobe level. Improved genetic algorithm is an effective method for the underwater acoustic imaging array to implement the sparse optimization.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Genetic algorithm; Mills cross multiplicative array; Sparse optimization; Underwater acoustic imaging

Geometric aspects of efficient cooperation - Michalopoulos, Diomidis S.; Schober, Robert (2015 IEEE International Conference on Communication Workshop (ICCW), 2015)
By appropriately selecting their relaying partners, wireless users are able to reduce their average transmit power without any performance cost. This important feature of cooperation is captured by the notion of relaying efficiency: A relaying partner is considered efficient for a given user if it can decrease the overall transmit power for achieving a certain signal-to-noise ratio (SNR) associated with that user. In this work, a two-dimensional geometric investigation of efficient cooperation is conducted. It is shown that the locus of efficient partner locations can be approximated by an ellipse, which is centred at the midpoint of the user and the base station, and has an eccentricity which depends on the path loss exponent. Moreover, the efficiency of the relaying partners is illustrated via contour graphs, which provide a graphical assessment of the energy efficiency potential of cooperation based on partner location. The cases of fading-free transmissions and transmission over Rayleigh fading channels are examined.<br
Keywords: Wireless communication; Integrated circuits

Globally Optimal Resource Allocation Design for IRS-Assisted Multiuser Networks with Discrete Phase Shifts - Wu, Yifei; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert; Gerstacker, Wolfgang (2023 IEEE International Conference on Communications Workshops: Sustainable Communications for Renaissance, ICC Workshops 2023, 2023)
Intelligent reflecting surfaces (IRSs) are envisioned as a low-cost solution to achieve high spectral and energy efficiency in future communication systems due to their ability to customize wireless propagation environments. Although resource allocation design for IRS-assisted multiuser wireless communication systems has been exhaustively investigated in the literature, the optimal design and performance of such systems are still not well understood. To fill this gap, in this paper, we study optimal resource allocation for IRS-assisted multiuser multiple-input single-output (MISO) systems. In particular, we jointly optimize the beamforming at the base station (BS) and the discrete IRS phase shifts to minimize the total transmit power. For attaining the globally optimal solution of the formulated non-convex combinatorial optimization problem, we develop a resource allocation algorithm with guaranteed convergence based on Schur's complement and the generalized Bender's decomposition. Our numerical results reveal that the proposed algorithm can significantly reduce the BS transmit power compared to the state-of-the-art suboptimal alternating optimization-based approach, especially for moderate-to-large numbers of IRS elements.
CRIS-Team Scopus Importer:2023-12-08

GLSE Precoders for Massive MIMO Systems: Analysis and Applications - Bereyhi, Ali; Sedaghat, Mohammad Ali; Müller, Ralf; Fischer, Georg (IEEE Transactions on Wireless Communications, 2018)
This paper proposes the class of Generalized Least-Square-Error (GLSE) precoders for multiuser massive MIMO systems. For a generic transmit constellation, GLSE precoders minimize the interference at user terminals assuring that given constraints on the transmit signals are satisfied. The general form of these precoders enables us to impose multiple restrictions at the transmit signal such as limited peak power and restricted number of active transmit antennas. Invoking the replica method from statistical mechanics, we study the performance of GLSE precoders in the large-system limit. We show that the output symbols of these precoders are identically distributed and their statistics are described with an equivalent scalar GLSE precoder. Using the asymptotic results, we further address some applications of the GLSE precoders; namely forming transmit signals over a restricted alphabet and transmit antenna selection. Our investigations demonstrate that a computationally efficient GLSE precoder requires 41% fewer active transmit antennas than conventional selection protocols in order to achieve a desired level of input-output distortion.

Graph-based Algorithms for Linear Computation Coding - Rosenberger, Hans; Bereyhi, Ali; Müller, Ralf (International Zurich Seminar on Information and Communication (IZS 2024). Proceedings, 2024)

Gridless Multidimensional Angle of Arrival Estimation for Arbitrary 3D Antenna Arrays - Sanchez-Fernandez, Matilde; Jamali, Vahid; Llorca, Jaime; Tulino, Antonia (IEEE Transactions on Wireless Communications, 2021)
A full multi–dimensional characterization of the angle of arrival (AoA) has immediate applications to the efficient operation of modern wireless communication systems. In this work, we develop a compressed sensing based method to extract multi-dimensional AoA information exploiting the sparse nature of the signal received by a sensor array. The proposed solution, based on the atomic ℓ0 norm, enables accurate gridless resolution of the AoA in systems with arbitrary 3D antenna arrays. Our approach allows characterizing the maximum number of distinct sources (or scatters) that can be identified for a given number of antennas and array geometry. Both noiseless and noisy measurement scenarios are addressed, deriving and evaluating the resolvability of the AoA propagation parameters through a multi–level Toeplitz matrix rank–minimization problem. To facilitate the implementation of the proposed solution, we also present a least squares approach regularized by a convex relaxation of the rank-minimization problem and characterize its conditions for resolvability.
CRIS-Team Scopus Importer:2021-03-19
Keywords: 3D antenna array; atomic norm; Multi–dimensional AoA; multi–level Vandermonde decomposition

GSM/EDGE: A mobile communications system determined to stay - Gerstacker, Wolfgang; Schober, Robert; Meyer, Raimund; Obernosterer, Frank; Ruder, Michael; Kalveram, Hans (AEÜ - International Journal of Electronics and Communications, 2011)
The Global System for Mobile Communications (GSM) is still the most successful mobile communications system worldwide. During the last decade, major steps have been taken towards an improvement of GSM with respect to performance and spectral efficiency. To serve the increasing demands of more and more users for higher data rates, significant efforts are made towards a further evolution of GSM. The standard extension Voice Services over Adaptive Multi-User Channels (VAMOS) has been specified in 3GPP Release 9. In VAMOS mode, two overlaid Gaussian minimum-shift keying (GMSK) signals are transmitted in the same time slot and frequency channel, potentially doubling the capacity of existing GSM networks in many cases. In this paper, we address channel estimation and detection techniques for the VAMOS downlink. In a new 3GPP work item called TIGHTER, it is also foreseen to tighten all downlink receiver performance requirements for all data and voice services by at least 2 dB through the application of more sophisticated processing techniques at the receiver. Furthermore, a 3GPP study on Signal Precoding Enhancements for EGPRS2 (SPEED) to further modify the modulation and coding for data services by introducing OFDM has been started recently. We present ideas for improved receivers to enable tighter performance requirements and for SPEED transmission concepts, which might merit further investigation. © 2011 Elsevier GmbH. All rights reserved.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Decoding; Equalization; GSM/EDGE; OFDM; SAIC; VAMOS

Guest Editorial - Dai, Linglong; Ding, Zhiguo; Al-Dhahir, Naofal; Chih-Lin, I.; Karagiannidis, George K.; Krikidis, Ioannis; Schober, Robert (IEEE Wireless Communications, 2018)
CRIS-Team Scopus Importer:2020-01-31

Guest Editorial Introduction to the Special Feature on the 6th Workshop on Molecular Communications - Arjmandi, Hamidreza; Awan, Hamdan; Tran, Huy; Schäfer, Maximilian; Haselmayr, Werner; Noel, Adam (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
CRIS-Team Scopus Importer:2023-04-14

Guest Editorial Massive Access for 5G and beyond - Part I - Chen, Xiaoming; Ng, Derrick Wing Kwan; Yu, Wei; Larsson, Erik G.; Al-Dhahir, Naofal; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2021)
CRIS-Team Scopus Importer:2021-03-19

Guest Editorial Special Issue on "Edge-Based Wireless Communications Technologies to Counter Communicable Infectious Diseases" - Balasubramaniam, Sasitharan; Schober, Robert; Pierobon, Massimiliano; Misra, Sudip; Thomas, Peter (IEEE Journal on Selected Areas in Communications, 2022)
CRIS-Team WoS Importer:2022-11-25

Guest Editorial Special Issue on Next Generation Multiple Access-Part II - Liu, Yuanwei; Zhang, Shuowen; Ding, Zhiguo; Schober, Robert; Al-Dhahir, Naofal; Hossain, Ekram; Shen, Xuemin (IEEE Journal on Selected Areas in Communications, 2022)
CRIS-Team WoS Importer:2022-04-29

Guest Editorial Special Issue on 'THz Communications and Networking' - Akyildiz, Ian F.; Kawanishi, Tetsuya; Gerstacker, Wolfgang; Dong, Xiaodai; Babakhani, Aydin (IEEE Journal on Selected Areas in Communications, 2021)
The Special Issue (SI) on ‘THz Communications and Networking’ of the IEEE Journal on Selected Areas In Communications targets presenting the most recent advances with respect to the theoretical foundations and practical implementation of THz wireless communications and networking. This includes approaches related to channel characterization and modeling, modulation, waveform design, and coding, information-theoretic analysis, channel estimation, detection, and equalization, (massive) multiple-input multiple-output (MIMO) communications, and beamforming, beamtracking, and precoding. The SI is aimed at compiling the latest and most significant research advances related to the modeling, design, analysis, and applications of THz wireless communications and networking as outlined above, and at fostering and envisioning new threads and directions in this still-emerging research area. The SI has attracted 49 high-quality submissions from authors based all around the world. All articles within the scope of the SI received at least three independent reviews, and the accepted articles went through at least one revision round.
CRIS-Team Scopus Importer:2021-06-11

Guest Editorial Special Issue on UAV Communications in 5G and beyond Networks - Part II - Wu, Qingqing; Xu, Jie; Zeng, Yong; Kwan Ng, Derrick Wing; Al-Dhahir, Naofal; Schober, Robert; Swindlehurst, A. Lee (IEEE Journal on Selected Areas in Communications, 2021)
CRIS-Team Scopus Importer:2021-10-29

Guest Editorial Wireless Transmission of Information and Power—Part I - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Ng, Derrick Wing Kwan; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2018)
Wireless transmission of information and power has received growing attention in the research community in the past few years. In two consecutive special issues, a total of thirty papers present state-of-the-art results in the broad area of wireless transmission of information and power.<br
Keywords: Special issues and sections; Wireless communication; Wireless power Transfer; Wireless Networks; Data transfer

Guest editorial wireless transmission of information and power - Part i - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Ng, Derrick Wing Kwan; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2019)
CRIS-Team Scopus Importer:2019-05-28

Guest Editorial Wireless Transmission of Information and Power—Part II - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Ng, Derrick Wing Kwan; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2019)
This second of the two issues on wireless transmission of information and power starts with some works on Simultaneous Wireless Information and Power Transfer (SWIPT), then switches to Wirelessly Powered Communication Networks (WPCNs), and finishes with a few works on Wirelessly Powered Backscatter Communication (WPBC).<br
Keywords: Special issues and sections; Wireless communication; Wireless power Transfer; Wireless sensor networks

Guest Editorial xURLLC in 6G: Next Generation Ultra-Reliable and Low-Latency Communications - She, Changyang; Pan, Cunhua; Duong, Trung Q.; Quek, Tony Q.S.; Schober, Robert; Simsek, Meryem; Zhu, Peiying (IEEE Journal on Selected Areas in Communications, 2023)
AS ONE of the new communication scenarios in 5th-generation (5G) mobile communication systems, ultra-reliable and low-latency communications (URLLC) have stringent requirements on latency (around 1 ms) and reliability (up to 99.99999%). Nevertheless, existing 5G URLLC alone cannot fulfill all the Key Performance Indicators (KPIs) in emerging mission-critical applications like industrial automation, intelligent transportation, telemedicine, Tactile Internet, and Virtual/Augmented Reality (VR/AR). The 6th generation (6G) communication systems need to meet additional requirements on some of the following KPIs in combination with URLLC: high spectrum efficiency (SE)/throughput/energy efficiency (EE)/network availability/security as well as low Age of Information (AoI)/jitter/round-trip delay. These new requirements pose unprecedented challenges in terms of design methodologies and enabling technologies in 6G. To fill the gap between 5G URLLC and the diverse KPI requirements of the neXt generation URLLC (xURLLC), novel methodologies and innovative technologies are much needed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Special issues and sections; 5G mobile communication; Low latency communication; 6G mobile communication; Performance evaluation; Ultra reliable low latency communication

Hard deadline constrained multiuser scheduling for random arrivals - Butt, M. Majid; Kansanen, Kimmo; Müller, Ralf (2011 IEEE Wireless Communications and Networking Conference, WCNC 2011, 2011)
In this work, an opportunistic scheduling scheme for a large multiuser system is proposed. A group of users with good channels are scheduled simultaneously for data transmission and separated by means of superposition coding. The proposed scheduling scheme is analyzed in the large system limit. Random packet arrivals are modeled as constant arrivals with random content size. Transmission thresholds are optimized in such a way that the system energy is minimized while obeying a strict upper bound on the packet delay. We find that the state space representations of systems with either constant or random arrivals are equivalent. Thus, the thresholds optimized for constant arrivals in earlier work are valid for systems with random arrivals as well. © 2011 IEEE.
Keywords: Furthermore; we address the option of intentional packet dropping and the trade-off between packet drop rate and required system energy

Hard fairness versus proportional fairness in wireless communications: The single-cell case - Caire, Giuseppe; Müller, Ralf; Knopp, Raymond (2006 IEEE International Symposium on Information Theory, ISIT 2006, 2006)
We consider the uplink and the downlink of a multiuser wireless system with one base station and K user terminals (single-cell case). Each user is affected by a position-dependent path loss, fixed in time, and by a slowly time-varying frequency-selective fading channel modeled as M parallel block-fading channels. We study the system throughput (sum rate) versus E /N under hard fairness and proportional fairness constraints. We obtain closed-form expressions for the throughput in the limit of a large number of users, as well as for the asymptotics in the low and high SNR regions. © 2006 IEEE.
Keywords: Wireless communication; Throughput; Base stations; Downlink; Fading; Closed-form solution; Resource Management; Scheduling algorithm; Delay effects; Delay systems

Hard fairness versus proportional fairness in wireless communications: The single-cell case - Müller, Ralf; et al. (IEEE Transactions on Information Theory, 2007)
We consider a wireless communication system formed by a single cell with one base station and K user terminals. User channels are characterized by frequency-selective fading due to small-scale effects, modeled as a set of M parallel block-fading channels, and a frequency-flat distance-dependent path loss. We compare delay-limited systems with variable-rate systems under fairness constraints, in terms of the achieved system spectral efficiency C (bit/s/Hz) versus E/ N. The considered delay-limited systems impose "hard-fairness": every user transmits at its desired rate on all blocks, independently of its fading conditions. The variable-rate system imposes proportional fairness via the popular Proportional Fair Scheduling (PFS) algorithm, currently implemented in 3G wireless for data (delay-tolerant) applications. We find simple iterative resource allocation algorithms that converge to the optimal delay-limited throughput for orthogonal (frequency-division multiple access (FDMA)/ time-division multiple access (TDMA)) and optimal (superposition/ interference cancellation) signaling. In the limit of large K and finite M we find closed-form expressions for C as a function of E/ N. We show that in this limit, the optimal allocation policy consists of letting each user transmit on its best subchannel only. Also, we find a simple closed-form expression for the throughput of PFS in a cellular environment, that holds for any K and M. Finally, we obtain closed-form expressions for C versus E/N in the low and high spectral efficiency regimes. The conclusions of ouranalysis in terms of system design guidelines are as follows: a) if hard fairness is a requirement, orthogonal access incurs a large throughput penalty with respect to the optimal (superposition coding) strategy, especially in the regime of high spectral efficiency; b) for high spectral efficiency, PFS does not provide any significant gain and may even perform worse than the optimal delay-limited system, despite the fact that the imposed fairness constraint is laxer; c) for low to moderate spectral efficiency, the stricter hard-fariness constraint incurs in a large throughput penalty with respect to PFS. © 2007 IEEE.
Keywords: Code-division multiple access (CDMA); Delay-limited capacity; Proportional fair scheduling; Uplink-downlink duality

Hierarchical Beam Alignment in Single-User MIMO Single-Carrier Frequency Division Multiple Access Terahertz Communication Systems - Wu, Yifei; Koch, Johannes; Vossiek, Martin; Gerstacker, Wolfgang (2021 IEEE International Conference on Communications Workshops, ICC Workshops 2021 - Proceedings, 2021)
Single-carrier frequency division multiple access (SC-FDMA) is a promising technique for high data rate Terahertz (THz) communications in future beyond 5G systems. Beam alignment (BA) is considered as a mandatory solution to establish a reliable communication link in SC-FDMA THz communication. However, existing BA methods introduce a large latency in searching for the optimal beam. In this paper, we propose a multi-armed bandit algorithm referred to as hierarchical beam alignment (HBA) for single-user SC-FDMA THz systems to reduce the beam alignment latency. HBA utilizes a hierarchical structure in the adopted codebook and the prior knowledge regarding the frequency-selective fading of the channel to speed up the BA process. Both theoretical analysis and simulation results illustrate that HBA converges to the optimal beam with high probability. The latency introduced by HBA is significantly lower compared to an exhaustive search method.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Beam alignment; indoor Terahertz communication; SC-FDMA

Hierarchical beam alignment in SU-MIMO terahertz communications - Wu, Yifei; Koch, Johannes; Vossiek, Martin; Gerstacker, Wolfgang (ITU Journal: ICT Discoveries, 2021)
Single-Carrier Frequency Division Multiple Access (SC-FDMA) is a promising technique for high data rate indoor Terahertz (THz) communications in future beyond 5G systems. In an indoor propagation scenario, the Line-Of-Sight (LOS) component may be blocked by the obstacles. Thus, efficient THz SC-FDMA communications require a fast and reliable Beam Alignment (BA) method for both LOS and Non-Line-Of-Sight (NLOS) scenarios. In this paper, we first adopt the hierarchical discrete Fourier transform codebook for LOS BA, and introduce the hierarchical k-means codebook for NLOS BA to improve the beamforming gain. Simulation results illustrate that the hierarchical DFT codebook and the hierarchical k-means codebook can achieve the beamforming gain close to that of the maximum ratio transmission in LOS and NLOS cases, respectively. Based on these two codebooks, we propose a Multi-Armed Bandit (MAB) algorithm named Hierarchical Beam Alignment (HBA) for single-user SC-FDMA THz systems to reduce the BA latency. HBA utilizes a hierarchical structure in the adopted codebook and prior knowledge regarding the noise power to speed up the BA process. Both theoretical analysis and simulation results indicate that the proposed BA method converges to the optimal beam with high probability for both the hierarchical DFT codebook and the hierarchical k-means codebook in the LOS and NLOS scenarios, respectively. The latency introduced by HBA is significantly lower when compared to an exhaustive search method and other MAB-based methods.
Keywords: Beam alignment; codebook design; SC-FDMA; SU-MIMO; terahertz communications

HoloFed: Environment-Adaptive Positioning via Multi-band Reconfigurable Holographic Surfaces and Federated Learning - Hu, Jingzhi; Chen, Zhe; Zheng, Tianyue; Schober, Robert; Luo, Jun (IEEE Journal on Selected Areas in Communications, 2023)
Positioning is an essential service for various applications and is expected to be integrated with existing communication infrastructures in 5G and 6G. Though current Wi-Fi and cellular base stations (BSs) can be used to support this integration, the resulting precision is unsatisfactory due to the lack of precise control of the wireless signals. Recently, BSs adopting reconfigurable holographic surfaces (RHSs) have been advocated for positioning as RHSs’ large number of antenna elements enable generation of arbitrary and highly-focused signal beam patterns. However, existing designs face two major challenges: i) RHSs only have limited operating bandwidth, and ii) the positioning methods cannot adapt to the diverse environments encountered in practice. To overcome these challenges, we present HoloFed, a system providing high-precision environment-adaptive user positioning services by exploiting multi-band (MB)-RHS and federated learning (FL). For improving the positioning performance, a lower bound on the error variance is obtained and utilized for guiding MB-RHS’s digital and analog beamforming design. For better adaptability while preserving privacy, an FL framework is proposed for users to collaboratively train a position estimator, where we exploit the transfer learning technique to handle the lack of position labels of the users. Moreover, a scheduling algorithm for the BS to select which users train the position estimator is designed, jointly considering the convergence and efficiency of FL. Our performance evaluation based on simulations confirms that HoloFed achieves a 57%lower positioning error variance compared to a beam-scanning baseline and can effectively adapt to diverse environments.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Array signal processing; Bandwidth; beamforming; federated learning; Federated learning; Global Positioning System; Optimization; Positioning; Privacy; Protocols; reconfigurable holographic surfaces

How Should IRSs Scale to Harden Multi-Antenna Channels? - Bereyhi, Ali; Asaad, Saba; Ouyang, Chongjun; Müller, Ralf; Schaefer, Rafael F.; Vincent Poor, H. (Proceedings of the IEEE Sensor Array and Multichannel Signal Processing Workshop, 2022)
This work extends the concept of channel hardening to multi-antenna systems that are aided by intelligent reflecting surfaces (IRSs). For fading links between a multi-antenna transmitter and a single-antenna receiver, we derive an accurate approximation for the distribution of the input-output mutual information when the number of reflecting elements grows large. The asymptotic results demonstrate that by increasing the number of elements on the IRS, the end-to-end channel hardens as long as the physical dimensions of the IRS grow as well. The growth rate however need not to be of a specific order and can be significantly sub-linear. The validity of the analytical result is confirmed by numerical experiments.
CRIS-Team Scopus Importer:2022-08-12
Keywords: channel hardening; Intelligent reflecting surfaces; large-system analysis

Hybrid Analogue Digital Outphasing Beamforming Architecture with Amplitude and Phase Control - Gäde, Bernhard; Sedaghat, Mohammad Ali; Müller, Ralf (2018)

Hybrid Beamforming for 5G and Beyond Millimeter-Wave Systems: A Holistic View - Zhang, Jun; Yu, Xianghao; Letaief, Khaled B. (IEEE Open Journal of the Communications Society, 2020)
Millimeter-wave (mm-wave) communication is a key technology for future wireless networks. To combat significant path loss and exploit the abundant mm-wave spectrum, effective beamforming is crucial. Nevertheless, conventional fully digital beamforming techniques are inapplicable, as they demand a separate radio frequency (RF) chain for each antenna element, which is costly and consumes too much energy. Hybrid beamforming is a cost-effective alternative, which can significantly reduce the hardware cost and power consumption by employing a small number of RF chains. This paper presents a holistic view on hybrid beamforming for 5G and beyond mm-wave systems, based on a new taxonomy for different hardware structures. We take a pragmatic approach and compare different proposals from three key aspects: 1) hardware efficiency, i.e., the required hardware components; 2) computational efficiency of the associated beamforming algorithm; and 3) achievable spectral efficiency, a main performance indicator. Through systematic comparisons, the interplay and trade-off among these three design aspects are demonstrated, and promising candidates for hybrid beamforming in future wireless networks are identified.
CRIS-Team WoS Importer:2021-12-24

Hybrid Digital-Analog codes for sending correlated Gaussian sources over an AWGN channel - Abolhassani, Melika; Javidbakht, Omid; Asaad, Saba; Behroozi, Hamid (6th International Symposium on Telecommunications (IST), 2012)

Hybrid MAP and PIC Detection for OTFS Modulation - Li, Shuangyang; Yuan, Weijie; Wei, Zhiqiang; Yuan, Jinhong; Bai, Baoming; Ng, Derrick Wing Kwan; Xie, Yixuan (IEEE Transactions on Vehicular Technology, 2021)
Orthogonal time frequency space (OTFS) modulation has attracted substantial attention recently due to its great potential of providing reliable communications in high-mobility scenarios. In this article, we propose a novel hybrid signal detection algorithm for OTFS modulation. Based on the system model, we first derive the near-optimal symbol-wise maximum a posteriori (MAP) detection algorithm for OTFS modulation. Then, in order to reduce the detection complexity, we propose a partitioning rule that separates the related received symbols into two subsets for detecting each transmitted symbol, according to the corresponding path gains. According to the partitioning rule, we design the hybrid detection algorithm to exploit the power discrepancy of each subset, where the MAP detection is applied to the subset with larger channel gains, while the parallel interference cancellation (PIC) detection is applied to the subset with smaller channel gains. We also provide the error performance analysis of the proposed hybrid detection algorithm. Simulation results show that the proposed hybrid detection algorithm can not only approach the performance of the near-optimal symbol-wise MAP algorithms, but also offer a substantial performance gain compared with existing algorithms.
CRIS-Team WoS Importer:2021-08-13

Hybrid NOMA Offloading in Multi-User MEC Networks - Ding, Zhiguo; Xu, Dongfang; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Wireless Communications, 2022)
Non-orthogonal multiple access (NOMA) assisted mobile edge computing (MEC) has recently attracted significant attention due to its superior capability to reduce the energy consumption and the latency of MEC offloading. In this paper, a general hybrid NOMA-MEC offloading strategy is proposed, which includes conventional orthogonal multiple access (OMA) and pure NOMA based offloading as special cases. A multi-objective optimization problem is formulated to minimize the energy consumption for MEC offloading, and a low-complexity resource allocation solution is derived and shown to be Pareto-optimal. Furthermore, by analyzing the properties of the obtained resource allocation solution, important insights regarding NOMA-MEC offloading are obtained. For example, it is proved that pure NOMA-MEC offloading cannot outperform hybrid NOMA-MEC. In addition, a precise condition under which NOMA-MEC outperforms OMA-MEC is established, and shown to match the one previously developed for the two-user special case. Furthermore, the developed analytical results also establish an interesting analogy between the proposed hybrid NOMA-MEC power allocation scheme and the well-known water-filling strategy.
CRIS-Team Scopus Importer:2022-02-04
Keywords: mobile edge computing (MEC); multi-objective optimization; Non-orthogonal multiple access (NOMA); Pareto optimality

Hybrid Precoder Design for Cache-Enabled Millimeter-Wave Radio Access Networks - He, Shiwen; Wu, Yongpeng; Ren, Ju; Huang, Yongming; Schober, Robert; Zhang, Yaoxue (IEEE Transactions on Wireless Communications, 2019)
In this paper, we study the design of a hybrid precoder, consisting of an analog and a digital precoder, for the delivery phase of downlink cache-enabled millimeter-wave (mm-wave) radio access networks (CeMm-RANs). In CeMm-RANs, enhanced remote radio heads (eRRHs), which are equipped with local cache and baseband signal processing capabilities in addition to the basic functionalities of conventional RRHs, are connected to the baseband processing unit via fronthaul links. Two different fronthaul information transfer strategies are considered, namely, hard fronthaul information transfer, where hard information of uncached requested files is transmitted via the fronthaul links to a subset of eRRHs, and soft fronthaul information transfer, where the fronthaul links are used to transmit quantized baseband signals of uncached requested files. The hybrid precoder is optimized for maximization of the minimum user rate under a fronthaul capacity constraint, an eRRH transmit power constraint, and a constant-modulus constraint on the analog precoder. The resulting optimization problem is non-convex, and hence, the global optimal solution is difficult to obtain. Therefore, convex approximation methods are employed to tackle the non-convexity of the achievable user rate, the fronthaul capacity constraint, and the constant modulus constraint on the analog precoder. Then, an effective algorithm with provable convergence is developed to solve the approximated optimization problem. The simulation results are provided to evaluate the performance of the proposed algorithms, where fully digital precoding is used as the benchmark. The results reveal that except for the case of a large fronthaul link capacity, soft fronthaul information transfer is preferable for CeMm-RANs. Furthermore, surprisingly, hybrid precoding outperforms fully digital precoding with soft fronthaul information transfer for medium-to-large file sizes and fronthaul capacity limited mm-wave cloud RANs<br
Keywords: Precoding; Optimization; Downlink; Wireless communication; Radio frequency; Radio access Networks; Baseband

Hybrid Precoder Design for Cache-Enabled Millimeter-Wave Radio Access Networks - He, Shiwen; Wu, Yongpeng; Ren, Ju; Huang, Yongming; Schober, Robert; Zhang, Yaoxue (IEEE Transactions on Wireless Communications, 2019)
In this paper, we study the design of a hybrid precoder, consisting of an analog and a digital precoder, for the delivery phase of downlink cache-enabled millimeter-wave (mm-wave) radio access networks (CeMm-RANs). In CeMm-RANs, enhanced remote radio heads (eRRHs), which are equipped with local cache and baseband signal processing capabilities in addition to the basic functionalities of conventional RRHs, are connected to the baseband processing unit via fronthaul links. Two different fronthaul information transfer strategies are considered, namely, hard fronthaul information transfer, where hard information of uncached requested files is transmitted via the fronthaul links to a subset of eRRHs, and soft fronthaul information transfer, where the fronthaul links are used to transmit quantized baseband signals of uncached requested files. The hybrid precoder is optimized for maximization of the minimum user rate under a fronthaul capacity constraint, an eRRH transmit power constraint, and a constant-modulus constraint on the analog precoder. The resulting optimization problem is non-convex, and hence, the global optimal solution is difficult to obtain. Therefore, convex approximation methods are employed to tackle the non-convexity of the achievable user rate, the fronthaul capacity constraint, and the constant modulus constraint on the analog precoder. Then, an effective algorithm with provable convergence is developed to solve the approximated optimization problem. The simulation results are provided to evaluate the performance of the proposed algorithms, where fully digital precoding is used as the benchmark. The results reveal that except for the case of a large fronthaul link capacity, soft fronthaul information transfer is preferable for CeMm-RANs. Furthermore, surprisingly, hybrid precoding outperforms fully digital precoding with soft fronthaul information transfer for medium-to-large file sizes and fronthaul capacity limited mm-wave cloud RANs.
CRIS-Team WoS Importer:2019-03-29

Hybrid Precoding for Secure Transmission in Reflect-Array-Assisted Massive MIMO Systems - Asaad, Saba; Schaefer, Rafael F.; Vincent Poor, H. (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2020)
Recently, a hybrid analog-digital architecture has been proposed for multiuser MIMO transmission in the millimeter-wave spectrum using reflect-arrays. The architecture exhibits scalability and high energy-efficiency while keeping the transmitter cost-efficient. Inspired by this architecture, we design a secure multiuser hybrid analog-digital precoding scheme. This scheme utilizes the method of regularized least-squares to shape the downlink beamformers, such that the signal received via malicious terminals is effectively suppressed. Numerical investigations depict high robustness of this scheme against the density of malicious terminals, as well as the quality of overhearing channels. Such properties along with high efficiency of the transmitter imply that the proposed scheme is an effective candidate for secure communication in multiuser millimeter-wave massive MIMO systems.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Hybrid analog-digital precoding; massive MIMO; reflect-arrays; regularized least-squares

Hybrid Puncturing and Superposition Scheme for Joint Scheduling of URLLC and eMBB Traffic - Darabi, Mostafa; Jamali, Vahid; Lampe, Lutz; Schober, Robert (IEEE Communications Letters, 2022)
Recent modifications to the air interface of 5G and beyond networks have improved the support for mixed enhanced mobile broadband (eMBB) and ultra-reliable and low-latency (URLLC) traffic. In particular, the concept of mini-slots has been introduced, and URLLC traffic is served at the mini-slot boundaries using superposition or puncturing of eMBB resources. This approach enables low latency for URLLC traffic, but it can incur a rate loss for eMBB traffic. To alleviate the latter, we propose a novel hybrid puncturing and superposition policy that jointly maximizes the minimum average throughput of eMBB traffic and the number of admitted URLLC users. Using sequential convex programming, a joint access technology selection, resource block, and power allocation problem is solved, where eMBB and URLLC user pairing and the decoding order in case of superposition are optimized based on channel state information. Our numerical results confirm that our proposed policy achieves a better trade-off between eMBB throughput and the number of admissible URLLC users when compared with existing solutions.
CRIS-Team Scopus Importer:2022-04-01
Keywords: 5G and beyond cellular networks; Decoding; Downlink; eMBB; hybrid puncturing and superposition; NOMA; Quality of service; Reliability; Resource management; Ultra reliable low latency communication; URLLC

IEEE fellow elevation for ComSoc members - Letaief, Khaled B.; Schober, Robert; Galli, Stefano (IEEE Communications Magazine, 2019)
CRIS-Team Scopus Importer:2020-01-31

Impact of Channel Models on Performance Characterization of RIS-Assisted Wireless Systems - Jamali, Vahid; Ghanem, Walid; Schober, Robert; Poor, H. Vincent (17th European Conference on Antennas and Propagation, EuCAP 2023, 2023)
The performance characterization of communication systems assisted by large reconfigurable intelligent surfaces (RISs) significantly depends on the adopted models for the underlying channels. Under unrealistic channel models, the system performance may be over- or under-estimated which yields inaccurate conclusions for the system design. In this paper, we review five channel models that are chosen to progressively improve the modeling accuracy for large RISs. For each channel model, we highlight the underlying assumptions, its advantages, and its limitations. We compare the system performance under the aforementioned channel models using RIS configuration algorithms from the literature and a new scalable algorithm proposed in this paper specifically for the configuration of extremely large RISs.
CRIS-Team Scopus Importer:2023-06-30

Impact of NOMA on Age of Information: A Grant-Free Transmission Perspective - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Wireless Communications, 2023)
The aim of this paper is to characterize the impact of non-orthogonal multiple access (NOMA) on the age of information (AoI) of grant-free transmission. In particular, a low-complexity form of NOMA, termed NOMA-assisted random access, is applied to grant-free transmission in order to illustrate the two benefits of NOMA for AoI reduction, namely increasing channel access and reducing user collisions. Closed-form analytical expressions for the time average AoI achieved by NOMA assisted grant-free transmission are obtained, and asymptotic studies are carried out to demonstrate that the use of the simplest form of NOMA is already sufficient to reduce the AoI of orthogonal multiple access (OMA) by more than 40%. In addition, the developed analytical expressions are also shown to be useful for optimizing the users’ transmission attempt probabilities, which are key parameters for grant-free transmission.
CRIS-Team Scopus Importer:2023-10-13
Keywords: age of information (AoI); Base stations; Complexity theory; grant-free transmission; Internet of Things; Markov processes; NOMA; Non-orthogonal multiple access (NOMA); Signal to noise ratio; Wireless communication

Impact of the power of the steering directions on the asymptotic capacity of MIMO channels - Debbah, Merouane; Müller, Ralf (3rd IEEE International Symposium on Signal Processing and Information Technology, ISSPIT 2003, 2003)
In this contribution, the double directional model derived within the maximum entropy framework in M. Debbah and R. Muller (2003) is studied. For a given power profile, an asymptotic analysis (in the number of antennas) is conducted on the achievable transmission limit using tools of random matrix theory. It is shown in particular that the optimal throughput is achieved when the scatterers have equally distributed powers. For special cases, the mutual information is proven to be asymptotically Gaussia
Keywords: Channel capacity; Eigenvalues and eigenfunctions; Entropy; Fourier transforms; Gaussian noise; MIMO; Mutual information; Receiving antennas; Scattering; Transmitting antennas

Improving and Bounding Asymptotic Approximations for Diversity Combiners in Correlated Generalized Rician Fading - Schlenker, Josh; Chen, Julian; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
Although relatively simple exact error rate expressions are available for selection combining (SC) and equal gain combining (EGC) with independent fading channels, results for correlated channels are highly complex, requiring multiple levels of integration when more than two branches are considered. Asymptotic analysis has been used to derive simple error expressions valid in the high signal-to-noise ratio (SNR) region. However, it is not clear at what SNR value the asymptotic results are an accurate approximation of the exact solution. In this paper, we derive asymptotic results for SC and EGC in correlated generalized Rician fading channels. Furthermore, the asymptotic results for SC are expanded into an exact infinite series. Although this series grows quickly in complexity as more terms are included, truncation to even two or three terms has much greater accuracy than the first (asymptotic) term alone. Finally, we derive asymptotically tight lower and upper bounds on the error rate for EGC. Using these bounds, we are able to show at what SNR value the asymptotic results are valid. <br
Keywords: Rician channels; Correlation; Signal to noise ratio; Fading; Error analysis; Diversity reception; Joints

Improving bandwidth efficiency in E-band communication systems - Mehrpouyan, Hani; Khanzadi, M. Reza; Matthaiou, Michail; Sayeed, Akbar M.; Schober, Robert; Hua, Yingbo (IEEE Communications Magazine, 2014)
The allocation of a large amount of bandwidth by regulating bodies in the 70/80 GHz band, that is, the E-band, has opened up new potentials and challenges for providing affordable and reliable gigabit-per-second wireless point-to-point links. This article first reviews the available bandwidth and licensing regulations in the E-band. Subsequently, different propagation models (e.g., the ITU-R and Cane models) are compared against measurement results, and it is concluded that to meet specific availability requirements, E-band wireless systems may need to be designed with larger fade margins compared to microwave systems. A similar comparison is carried out between measurements and models for oscillator phase noise. It is confirmed that phase noise characteristics, which are neglected by the models used for narrowband systems, need to be taken into account for the wideband systems deployed in the E-band. Next, a new MIMO transceiver design, termed continuous aperture phased (CAP)-MIMO, is presented. Simulations show that CAP-MIMO enables E-band systems to achieve fiber-optic-like throughputs. Finally, it is argued that full-duplex relaying can be used to greatly enhance the coverage of E-band systems without sacrificing throughput, thus facilitating their application in establishing the backhaul of heterogeneous Networks.<br
Keywords: Phase noise; MIMO; Wireless communicationtten; Attenuation; Bandwidth allocation; Transceivers

Improving Range of Molecular Communication with Relays - Ahmadzadeh, Arman (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)

Improving Receiver Performance of Diffusive Molecular Communication With Enzymes - Noel, Adam; Cheung, Karen; Schober, Robert (IEEE Transactions on Nanobioscience, 2014)
This paper studies the mitigation of intersymbol interference in a diffusive molecular communication system using enzymes that freely diffuse in the propagation environment. The enzymes form reaction intermediates with information molecules and then degrade them so that they cannot interfere with future transmissions. A lower bound expression on the expected number of molecules measured at the receiver is derived. A simple binary receiver detection scheme is proposed where the number of observed molecules is sampled at the time when the maximum number of molecules is expected. Insight is also provided into the selection of an appropriate bit interval. The expected bit error probability is derived as a function of the current and all previously transmitted bits. Simulation results show the accuracy of the bit error probability expression and the improvement in communication performance by having active enzymes present. <br
Keywords: Biochemistry; Receivers; Transmitters; Degradation; Nanobioscience; Molecular communication; Kinetic theory

Increasing the Capacity of Magnetic Induction Communications in RF-Challenged Environments - Sun, Zhi; Akyildiz, Ian F.; Kisseleff, Steven; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2013)

Individual packet deadline constrained opportunistic scheduling for a multiuser system - Butt, M. Majid; Kansanen, Kimmo; Müller, Ralf (2011 IEEE 73rd Vehicular Technology Conference, VTC2011-Spring, 2011)
In this work an opportunistic scheduling scheme is presented and analyzed for a multiuser system. The objective of the proposed scheme is to minimize the system transmit energy in the presence of a hard deadline delay constraint for the individual packets. In the large system limit, the scheme is modeled and analyzed in the scenario when arriving packets have associated deadlines which vary from packet to packet. We introduce transmission thresholds that depend on channel quality and number of time slots left before a packet reaches its hard deadline. These thresholds are optimized such that they reflect the interaction of deadline delay and channel variation, and result in a minimum system energy. The results demonstrate the saving in energy for a system where the applications have individual packet deadline delay constraints. © 2011 IEEE.
Keywords: Fading; Delay; Scheduling; Optimal scheduling; Numerical models; Analytical models

Individual packet deadline delay constrained opportunistic scheduling for large multiuser systems - Butt, Muhammad Majid; Müller, Ralf; Kansanen, Kimmo (EURASIP Journal on Wireless Communications and Networking, 2014)
This work addresses opportunistic distributed multiuser scheduling in the presence of a fixed packet deadline delay constraint. A threshold-based scheduling scheme is proposed which uses the instantaneous channel gain and buffering time of the individual packets to schedule a group of users simultaneously in order to minimize the average system energy consumption while fulfilling the deadline delay constraint for every packet. The multiuser environment is modeled as a continuum of interference such that the optimization can be performed for each buffered packet separately by using a Markov chain where the states represent the waiting time of each buffered packet. We analyze the proposed scheme in the large user limit and demonstrate the delay-energy trade-off exhibited by the scheme. We show that the multiuser scheduling can be broken into a packet-based scheduling problem in the large user limit and the packet scheduling decisions are independent of the deadline delay distribution of the packets. © 2014 Butt et al.; licensee Springer.
Keywords: Delay constrained data; Energy efficient communications; Large system analysis; Opportunistic scheduling

Indoor 3D Visible Light Positioning Analysis with Channel Estimation Errors - Bozanis, Dimitrios; Evgenidis, Nikos G.; Papanikolaou, Vasileios; Bouzinis, Pavlos S.; Tegos, Sotiris A.; Dowhuszko, Alexis A.; Diamantoulakis, Panagiotis D.; Karagiannidis, George K. (International Conference on Systems, Signals, and Image Processing, 2023)
Since radio-frequency signals are affected signifi-cantly by multipath fading, the localization accuracy they offer cannot meet the sixth generations (6G) demanding specifications. On the other hand, visible light positioning (VLP) has emerged as a low cost alternative that takes into account the highly deterministic channel characteristics of visible light communications to provide cm-level accuracy provided that the investigated spaces are adequately covered by LEDs. However, imperfect channel state information and modeling can lead to positioning errors. In this paper, localization accuracy is quantified in terms of channel estimation errors via low complexity lateration algorithm. The channel estimation errors can be caused by a variety of issues and the provided analysis is general so that it can be easily applied to a plethora of applications. Finally, Monte Carlo simulations validate the proposed method and offer valuable insights for the design and performance bounds of VLP systems.
CRIS-Team Scopus Importer:2023-08-11
Keywords: channel estimation errors; localization; visible light positioning (VLP)

Information and multiaccess interference in a complexity-constrained vector channel - Müller, Ralf; et al. (Journal of Physics A: Mathematical and Theoretical, 2007)
A noisy vector channel operating under a strict complexity constraint at the receiver is introduced. According to this constraint, detected bits, obtained by performing hard decisions directly on the channel's matched filter output, must be the same as the transmitted binary inputs. An asymptotic analysis is carried out using mathematical tools imported from the study of neural networks, and it is shown that, under a bounded noise assumption, such complexity-constrained channel exhibits a non-trivial Shannon-theoretic capacity. It is found that performance relies on rigorous interference-based multiuser cooperation at the transmitter and that this cooperation is best served when all transmitters use the same amplitude. © 2007 IOP Publishing Ltd.

Integrated Sensing and Communication-Assisted Orthogonal Time Frequency Space Transmission for Vehicular Networks - Yuan, Weijie; Wei, Zhiqiang; Li, Shuangyang; Yuan, Jinhong; Ng, Derrick Wing Kwan (IEEE Journal of Selected Topics in Signal Processing, 2021)
Orthogonal time frequency space (OTFS) modulation is a promising candidate for supporting reliable information transmission in high-mobility vehicular networks. In this paper, we consider the employment of the integrated (radar) sensing and communication (ISAC) technique for assisting OTFS transmission in both uplink and downlink vehicular communication systems. Benefiting from the OTFS-ISAC signals, the roadside unit (RSU) is capable of simultaneously transmitting downlink information to the vehicles and estimating the sensing parameters of vehicles, e.g., locations and speeds, based on the reflected echoes. Then, relying on the estimated kinematic parameters of vehicles, the RSU can construct the topology of the vehicular network that enables the prediction of the vehicle states in the following time instant. Consequently, the RSU can effectively formulate the transmit downlink beamformers according to the predicted parameters to counteract the channel adversity such that the vehicles can directly detect the information without the need of performing channel estimation. As for the uplink transmission, the RSU can infer the delays and Dopplers associated with different channel paths based on the aforementioned dynamic topology of the vehicular network. Thus, inserting guard space as in conventional methods are not needed for uplink channel estimation which removes the required training overhead. Finally, an efficient uplink detector is proposed by taking into account the channel estimation uncertainty. Through numerical simulations, we demonstrate the benefits of the proposed ISAC-assisted OTFS transmission scheme.
CRIS-Team WoS Importer:2021-12-17

Integrated Sensing and Communication in Distributed Antenna Networks - Xu, Dongfang; Khalili, Ata; Yu, Xianghao; Kwan Ng, Derrick Wing; Schober, Robert (2023 IEEE International Conference on Communications Workshops: Sustainable Communications for Renaissance, ICC Workshops 2023, 2023)
In this paper, we investigate the resource allocation design for integrated sensing and communication (ISAC) in distributed antenna networks (DANs). In particular, coordinated by a central processor (CP), a set of remote radio heads (RRHs) provide communication services to multiple users and sense several target locations within an ISAC frame. To avoid severe interference between the information transmission and the radar echo, we propose to divide the ISAC frame into a communication phase and a sensing phase. During the communication phase, the data signal is generated at the CP and then conveyed to the RRHs via fronthaul links. As for the sensing phase, based on pre-determined RRH-target pairings, each RRH senses a dedicated target location with a synthesized highly-directional beam and then transfers the samples of the received echo to the CP via its fronthaul link for further processing of the sensing information. Taking into account the limited fronthaul capacity and the quality-of-service requirements of both communication and sensing, we jointly optimize the durations of the two phases, the information beamforming, and the covariance matrix of the sensing signal for minimization of the total energy consumption over a given finite time horizon. To solve the formulated non-convex design problem, we develop a low-complexity alternating optimization algorithm which converges to a suboptimal solution. Simulation results show that the proposed scheme achieves significant energy savings compared to the two baseline schemes. Moreover, our results reveal that for efficient ISAC in wireless networks, energy-focused short-duration pulses are favorable for sensing while low-power long-duration signals are preferable for communication.
CRIS-Team Scopus Importer:2023-12-08

Integration of Molecular Communications into Future Generation Wireless Networks - Haselmayr, Werner; Springer, Andreas; Fischer, Georg; Alexiou, Christoph; Boche, Holger; Höher, Peter Adam; Dressler, Falko; Schober, Robert (6G Wireless Summit, 2019)

Intelligent Reflecting Surface Assisted Free-Space Optical Communications - Jamali, Vahid; Ajam, Hedieh; Najafi, Marzieh; Schmauß, Bernhard; Schober, Robert; Poor, H. Vincent (IEEE Communications Magazine, 2021)
Free-space optical (FSO) systems are able to offer the high data-rate, secure, and cost-efficient communication links required for applications such as wireless front- and backhauling for 5G and 6G communication networks. Despite the substantial advancement of FSO systems over the past decades, the requirement of a line-of-sight connection between transmitter and receiver remains a key limiting factor for their deployment. In this article, we discuss the potential role of intelligent reflecting surfaces (IRSs) as a solution to relax this requirement. We present an overview of existing optical IRS technologies; compare optical IRSs with radio frequency IRSs and optical relays; and identify various open problems for future research on IRS-assisted FSO communications.
CRIS-Team WoS Importer:2021-12-10

Intelligent Reflecting Surface Enabled Multi-Target Sensing - Meng, Kaitao; Wu, Qingqing; Schober, Robert; Chen, Wen (IEEE Transactions on Communications, 2022)
Besides improving communication performance, intelligent reflecting surfaces (IRSs) are also promising enablers for achieving larger sensing coverage and enhanced sensing quality. Nevertheless, in the absence of a direct path between the base station (BS) and the targets, multi-target sensing is generally very difficult, since IRSs are incapable of proactively transmitting sensing beams or analyzing target information. Moreover, the echoes of different targets reflected via the IRS-assisted virtual links arrive at the BS from the same direction. In this paper, we study a wireless system comprising a multi-antenna BS and an IRS for multi-target sensing, where the beamforming vector and the IRS phase shifts are jointly optimized to improve the sensing performance. To meet the different sensing requirements, such as a minimum received power and a minimum sensing frequency, we propose three novel IRS-assisted sensing schemes: Time division (TD) sensing, signature sequence (SS) sensing, and hybrid TD-SS sensing. For TD sensing, the sensing tasks are performed in sequence over time. In contrast, the novel SS sensing scheme senses all targets simultaneously and establishes a relationship between the target directions and SSs. To strike a flexible balance between the beam pattern gain and sensing efficiency, we also propose a general hybrid TD-SS sensing scheme with target grouping, where targets belonging to the same group are sensed simultaneously via SS sensing, while the targets in different groups are assigned to orthogonal time slots. By controlling the number of groups, hybrid TD-SS sensing can provide a more flexible balance between beam pattern gain and sensing frequency. Moreover, we propose a two-layer penalty-based algorithm to solve the challenging non-convex optimization problem for the joint design of the BS beamformers, IRS phase shifts, and target grouping. Simulation results demonstrate the effectiveness of the proposed hybrid scheme in achieving a flexible trade-off between beam pattern gain and sensing frequency. Our results also reveal that the power leakage in unintended directions is larger for tighter interference constraints.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Array signal processing; beamforming; Intelligent reflecting surface; multi-target sensing; non-line-of-sight (NLoS); Object detection; Optimization; Radar; Sensors; signature sequence; Task analysis; time division; Time-frequency analysis

Intelligent Reflecting Surface Enhanced Indoor Robot Path Planning: A Radio Map based Approach - Mu, Xidong; Liu, Yuanwei; Guo, Li; Lin, Jiaru; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
Integrating robots into cellular networks creating connected robotic users has emerged as a promising technology for future smart cities and smart factories due to their low cost and high maneuverability. However, the requirement of establishing stable and high-quality communication links to the robotic users greatly restricts their applicability, especially in indoor environments where obstacles may block the wireless link. To tackle this challenge, in this paper, an indoor robot navigation system is investigated, where an intelligent reflecting surface (IRS) is employed to enhance the connectivity between the access point (AP) and robotic users. Both single-user and multiple-user scenarios are considered. In the single-user scenario, one mobile robotic user (MRU) communicates with the AP. In the multiple-user scenario, the AP serves one MRU and one static robotic user (SRU) employing either non-orthogonal multiple access (NOMA) or orthogonal multiple access (OMA) transmission. The considered system is optimized for minimization of the travelling time/distance of the MRU from a given starting point to a predefined final location, while satisfying constraints on the communication quality of the robotic users. To this end, a radio map based approach is proposed to exploit location-dependent channel propagation knowledge. For the single-user scenario, a channel power gain map is constructed, which characterizes the spatial distribution of the maximum expected effective channel power gain of the MRU for the optimal IRS phase shifts. Based on the obtained channel power gain map, the communication-aware robot path planing problem is solved by exploiting graph theory. For the multiple-user scenario, a communication rate map is constructed, which characterizes the spatial distribution of the maximum expected rate of the MRU for the optimal power allocation at the AP and the optimal IRS phase shifts subject to a minimum rate requirement for the SRU. The joint optimization problem is efficiently solved by invoking bisection search and successive convex approximation methods. Then, a graph theory based solution for the robot path planning problem is derived by exploiting the obtained communication rate map. Our numerical results show that: 1) the required travelling distance of the MRU can be significantly reduced by deploying an IRS; 2) NOMA yields a higher communication rate for the MRU than OMA; 3) the IRS performance gain is significantly more pronounced for NOMA than for OMA.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Intelligent reflecting surfaces; non-orthogonal multiple access; radio maps; robot path planning

Intelligent Reflecting Surfaces for Free Space Optical Communications - Najafi, Marzieh; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Intelligent Reflecting Surfaces for Free Space Optical Communication Systems - Najafi, Marzieh; Schmauß, Bernhard; Schober, Robert (IEEE Transactions on Communications, 2021)
In this paper, we investigate the use of intelligent reflecting surfaces (IRSs) to relax the line-of-sight requirement of free space optical (FSO) systems. Considering a Gaussian laser beam, we first design a phase-shift distribution across the IRS that enables the reflection of the incident beam in any desired direction, i.e., realizing the generalized law of reflection. Moreover, for the designed phase-shift profile, we show that there exists an equivalent mirror-assisted FSO system that generates a reflected electric field on a mirror that is identical to that on the IRS in the original system. However, the location of the laser source and the properties of the emitted Gaussian laser beam are different in the original and the equivalent systems. This equivalence allows us to study the mirror-assisted system, employing the image method from geometric optics, instead of directly analyzing the original IRS-assisted system. Based on this analysis, we model the geometric and misalignment losses (GML) and characterize the impact of the physical parameters of the IRS, such as its size, position, and orientation, on the end-to-end FSO channel. Moreover, we develop a statistical model for the GML which accounts for the random movements of IRS, transmitter (Tx), and receiver (Rx) due to building sway. Furthermore, we analyze the outage probability of an IRS-assisted FSO link based on the derived channel model. Our simulation results validate the accuracy of the developed channel model and offer various insights for system design. For instance, both our simulations and theoretical analysis reveal that even if the variances of the fluctuations of the Tx, IRS, and Rx positions caused by building sway are identical, their impact on the end-to-end channel is not necessarily the same and depends on the relative positioning of these three nodes.
CRIS-Team Scopus Importer:2021-06-11
Keywords: anomalous reflection; Buildings; Channel models; free space optical systems; geometric and misalignment losses; Intelligent reflecting surfaces; Laser beams; Lenses; line-of-sight link; Mirrors; Optical surface waves; Optical transmitters; pointing error

Intelligent surface-Aided transmitter architectures for millimeter-wave ultra massive mimo systems - Jamali Kooshkghazi, Vahid; Tulino, Antonia M.; Fischer, Georg; Müller, Ralf; Schober, Robert (IEEE Open Journal of the Communications Society, 2021)
In this article, we study two novel massive multiple-input multiple-output (MIMO) transmitter architectures for millimeter wave (mmWave) communications which comprise few active antennas, each equipped with a dedicated radio frequency (RF) chain, that illuminate a nearby large intelligent reflecting/transmitting surface (IRS/ITS). The IRS (ITS) consists of a large number of low-cost and energy-efficient passive antenna elements which are able to reflect (transmit) a phase-shifted version of the incident electromagnetic field. Similar to lens array (LA) antennas, IRS/ITS-Aided antenna architectures are energy efficient due to the almost lossless over-The-Air connection between the active antennas and the intelligent surface. However, unlike for LA antennas, for which the number of active antennas has to linearly grow with the number of passive elements (i.e., the lens aperture) due to the non-reconfigurablility (i.e., non-intelligence) of the lens, for IRS/ITS-Aided antennas, the reconfigurablility of the IRS/ITS facilitates scaling up the number of radiating passive elements without increasing the number of costly and bulky active antennas. We show that the constraints that the precoders for IRS/ITS-Aided antennas have to meet differ from those of conventional MIMO architectures. Taking these constraints into account and exploiting the sparsity of mmWave channels, we design two efficient precoders; one based on maximizing the mutual information and one based on approximating the optimal unconstrained fully digital (FD) precoder via the orthogonal matching pursuit algorithm. Furthermore, we develop a power consumption model for IRS/ITS-Aided antennas that takes into account the impacts of the IRS/ITS imperfections, namely the spillover loss, taper loss, aperture loss, and phase shifter loss. Moreover, we study the effect that the various system parameters have on the achievable rate and show that a proper positioning of the active antennas with respect to the IRS/ITS leads to a considerable performance improvement. Our simulation results reveal that unlike conventional MIMO architectures, IRS/ITS-Aided antennas are both highly energy efficient and fully scalable in terms of the number of transmitting (passive) antennas. Therefore, IRS/ITS-Aided antennas are promising candidates for realizing the potential of mmWave ultra massive MIMO communications in practice.
CRIS-Team Scopus Importer:2022-06-05
Keywords: and energy efficiency; hybrid MIMO; Intelligent reflecting/transmitting surfaces; lens array; mmWave communications; reflect/transmit array; scalability

Interference Polarization in Magnetic Induction based Wireless Underground Sensor Networks - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications (SENSA Workshop), 2013)

Interferenzunterdrückung für Space-Time Codierte Signale - Rohde, Christian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)

Introduction to the Issue on Signal Processing Advances for Non-Orthogonal Multiple Access in Next Generation Wireless Networks - Liu, Yuanwei; Ding, Zhiguo; Al-Dhahir, Naofal; Schober, Robert; Dobre, Octavia A.; Karagiannidis, George K.; Fan, Pingzhi (IEEE Journal of Selected Topics in Signal Processing, 2019)
The papers in this special section focus on signal processing advances in non-orthogonal multiple access (NOMA) and network generation wireless networks. Recent years have witnessed the explosive growth ofmobile data traffic, which has led to ever-increasing demand for high system throughput, massive user access, heterogeneous data traffic, high bandwidth efficiency, and ultra-low latency. Non-orthogonal multiple access (NOMA) has received considerable attention in both industry and academia as an efficient multiple access scheme to meet this demand. The concept of NOMA is to encourage spectrum sharing and to accommodate multiple users in the same orthogonal resource block, such as a time slot, a frequency band, and a spatial direction. By doing so, high bandwidth efficiency and massive connectivity can be attained. Because of its superior performance, NOMA has already been included in the 3rd generation partnership project long-term evolution advanced (3GPP-LTE-A) standard and the next generation digital TV standard (ATSC 3.0), while new proposals for including NOMA in the 5G New Radio (NR) have been put forward. While the principle of NOMA has been wellaccepted by both academia and industry, there are still many open issues related to the required signal processing. The aim of this special issue is to present solutions for signal processing and practical implementation problems related to NOMA, in order to close the gap between theory and practice. In fact, this special issue presents innovative solutions to advanced signal processing designs for of NOMA systems.<br

Introduction to the Issue on Signal Processing Advances for Non-Orthogonal Multiple Access in Next Generation Wireless Networks - Liu, Yuanwei; Ding, Zhiguo; Al-Dhahir, Naofal; Schober, Robert; Dobre, Octavia A.; Karagiannidis, George K.; Fan, Pingzhi (IEEE Journal of Selected Topics in Signal Processing, 2019)
CRIS-Team WoS Importer:2019-06-18

Introduction to the Issue on Signal Processing for Exploiting Interference Toward Energy Efficient and Secure Wireless Communications - Krikidis, Ioannis; Masouros, Christos; Zheng, Gan; Zhang, Rui; Schober, Robert (IEEE Journal of Selected Topics in Signal Processing, 2016)
INTERFERENCE has been the central focus for meeting the ever increasing requirements on quality of service in modern and future wireless communication systems, and has long been considered as a deleterious factor that limits the system capacity. In conventional communications systems, the design objective is to allow users to share a medium with minimum or no interference. Thus, great efforts are made to avoid, mitigate, and cancel interference. For instance, to support multiple users, orthogonal access methods in time, frequency, code well as spatial domains have been used in different generations of cellular systems. In future-generation heterogeneous cellular networks, due to the increasing number of uncoordinated lowpower nodes such as femtocells to improve the coverage and pacity, interferences need to be mitigated in multiple domains, rendering their management a challenge. Interference mitigation/avoidance techniques provide convenient mechanisms allow multiple users to share the wireless medium. However, they lead to inefficient use of wireless resources.<br
Keywords: Special issues and sections; Interference; Energy efficiency; Wireless communication; Physical layer; Array signal processing; MIMO; Jamming

Introduction to the special section on energy-harvesting cognitive radio networks - Da Costa, Daniel Benevides; Karagiannidis, George K.; Dobre, Octavia A.; Upadhyay, Prabhat K.; Xia, Minghua; Ding, Haiyang; Schober, Robert (IEEE Transactions on Cognitive Communications and Networking, 2019)
We are delighted to introduce the readers to this special section of the IEEE Transactions on Cognitive Communications and Networking (TCCN), which has the purpose of addressing fundamental and practical challenges in the analysis and design of energy-harvesting cognitive radio networks (EH-CRNs). We received a total of 19 submissions, and after a rigorous review process, 9 articles have been selected for publication, which are briefly discussed next.<br
CRIS-Team Scopus Importer:2019-06-21

Investigations towards plausible blind upmixing of applause signals - Adami, Alexander; Brand, Lukas; Herre, Jürgen (142nd Audio Engineering Society International Convention 2017, AES 2017, 2017)
Vorträge und Veröffentlichungen auf Konferenzen_Applaus

Invited papers and timeliness of review process - Schober, Robert (IEEE Transactions on Communications, 2014)
CRIS-Team Scopus Importer:2020-02-03

Ion Channel Based Bio-Synthetic Modulator for Diffusive Molecular Communication - Arjmandi, Hamidreza; Ahmadzadeh, Arman; Schober, Robert; Nasiri-Kenari, Masoumeh (IEEE Transactions on Nanobioscience, 2016)
In diffusion-based molecular communication (DMC), a transmitter nanomachine is responsible for signal modulation. Thereby, the transmitter has to be able to control the release of the signaling molecules employed for representing the transmitted information. In nature, an important class of control mechanisms for releasing molecules from cells utilizes ion channels which are pore-forming proteins across the cell membrane. The opening and closing of the ion channels is controlled by a gating parameter. In this paper, an ion channel based modulator for DMC is proposed which controls the rate of molecule release from the transmitter by modulating a gating parameter signal. Exploiting the capabilities of the proposed modulator, an on-off keying modulation technique is introduced and the corresponding average modulated signal, i.e., the average release rate of the molecules from the transmitter, is analyzed. However, since the modulated signal is random in nature, it may deviate from its average. Therefore, the concept of modulator noise is introduced and the statistics of the modulated signal are investigated. Finally, by assuming a simple transparent receiver, the performance of the proposed on-off keying modulation format is studied. The derived analytical expressions for the average modulated signal are confirmed with particle based simulations. Our numerical results reveal that performance estimates of DMC systems obtained based on the assumption of instantaneous molecule release at the transmitter may substantially deviate from the performance achieved with practical modulators.<br
Keywords: Modulation; Logic gates; Biomembranes; Cells (biology); Nanobioscience; Optical transmitters

Ion pump based bio-synthetic modulator model for diffusive molecular communications - Arjmandi, Hamidreza; Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Burkovski, Andreas; Schober, Robert; Nasiri-Kenari, Masoumeh (2016 IEEE 17th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2016)
In diffusive molecular communication (DMC), the transmitter has to be able to control the release of signaling molecules for modulation of the information bits. In natural cells, pumping ions is an important control mechanism for releasing molecules which is carried out by ion pumps embedded in the membrane. The activity of the ion pumps is controlled by a driving parameter. In particular, light driven pumps are controlled by light intensity and enable a high degree of spatial and temporal control for modulation functionality. In this paper, a modulator based on ion pumps is proposed for DMC which controls the release rate of the molecules from the transmitter by modulating a light intensity signal. The pumping process of the ion pump is modeled by a Markov model based on which the stochastic nature of the modulated signal, i.e., the release rate of the ions from the transmitter is analyzed. A simple on-off keying modulation scheme is realized based on the proposed modulator. Our numerical results show that a realistic transmitter based on ion pumps can not release ions instantaneously nor deterministically.<br
Keywords: Ions; Photonics; Modulation; Absorption; Optical Transmitters; Proteins; Biomembranes

I/Q imbalance aware widely-linear channel estimation and detection for uplink massive MIMO systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2015 International Symposium on Wireless Communication Systems (ISWCS), 2016)
In this paper, we propose an in-phase/quadrature-phase imbalance (IQI) aware widely-linear minimum mean square error (IQA-WLMMSE) receiver for uplink single-cell massive multiple-input multiple-output (MIMO) systems with imperfect channel state information (CSI). In our system model, IQI is present at the base station and user terminals and affects both channel estimation and data detection. The proposed IQA-WLMMSE receiver processes the real and imaginary parts of the received signal separately and mitigates both multiple-access interference (MAI) and IQI. Our analytical and simulation results show that the proposed IQA-WLMMSE receiver performs significantly better than the conventional IQI unaware MMSE (IQU-MMSE) receiver, and its sum rate closely approaches the sum rate of the ideal system with no IQ

I/Q imbalance aware widely-linear precoding for downlink massive MIMO systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2014 IEEE Globecom Workshops (GC Wkshps), 2014)
In-phase/quadrature-phase (I/Q) imbalance is one of the most important hardware impairments in communication systems. It arises in the analog parts of direct conversion radio frequency (RF) transceivers and can cause large performance losses. In this paper, the impact of I/Q imbalance on the sum rate performance of downlink massive multiple-input multiple-output (MIMO) systems is analyzed and I/Q imbalance aware widely-linear precoding is considered. The proposed precoder is a widely-linear (WL) extension of the regularized zero-forcing (RZF) precoder and jointly mitigates multi-user interference and I/Q imbalance by processing the real and the imaginary parts of the transmit signal separately. Results from random matrix theory are used to derive analytical expressions for the achievable sum rate of the proposed precoder. Our analytical results show that if the number of base station antennas is much larger than the number of users, the proposed I/Q imbalance aware WL-RZF precoder achieves the same sum rate as the RZF precoder in an ideal system without I/Q imbalance. We also provide an analytical expression for the sum rate loss of the I/Q imbalance unaware RZF precoder compared to the ideal case without I/Q imbalance.<br
Keywords: MIMO; Base stations; Interference; Signal to noise ratio; Vectors; Downlink; Antennas

I/Q Imbalance Aware Widely-Linear Receiver for Uplink Multi-Cell Massive MIMO Systems: Design and Sum Rate Analysis - Zarei, Shahram; Gerstacker, Wolfgang; Aulin, Jocelyn; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In-phase/quadrature-phase imbalance (IQI) is one of the most important hardware impairments in communication systems. It arises in the analogue parts of direct conversion transceivers and can cause severe performance losses. In this paper, IQI aware widely-linear (WL) channel estimation and data detection schemes for uplink multicell massive multiple-input multiple-output (MIMO) systems are proposed. The resulting receiver is a WL extension of the minimum mean-square-error (MMSE) receiver and jointly mitigates multiuser interference and IQI by processing the real and the imaginary parts of the received signal separately. Thereby, the IQI arising at both the base station and the user terminals is taken into account. The considered channel state information acquisition model includes the effect of pilot contamination, which is caused by the reuse of the same training sequences in neighbouring cells. We apply results from random matrix theory to derive analytical expressions for the asymptotic achievable sum rates of the proposed IQI aware and conventional IQI unaware (IQU) receivers in the large system limit. Our simulation and analytical results show that the performance of the proposed IQI aware WLMMSE (IQA-WLMMSE) receiver in a system with IQI is close to that of the MMSE receiver in an ideal system without IQI.<br
Keywords: MIMO; Receivers; Uplink; Channel estimation; OFDM; Wireless communication; Interference

I/Q-Imbalance Self-Interference Coordination - Boulogeorgos, Alexandros-Apostolos A.; Kapinas, Vasileios M.; Schober, Robert; Karagiannidis, George K. (IEEE Transactions on Wireless Communications, 2016)
In this paper, we present a novel low-complexity technique, which improves the performance of single-antenna multi-carrier communication systems, suffering from in-phase and quadrature (I/Q)-imbalance (IQI) at the receiver. We refer to the proposed scheme as I/Q-imbalance self-interference coordination (IQSC). This technique not only mitigates the detrimental effects of IQI, but, through appropriate signal processing, also coordinates the self-interference terms produced by IQI in order to achieve second-order frequency diversity. However, these benefits come at the expense of a reduction in transmission rate. More specifically, IQSC is a simple transmit diversity scheme that improves the signal quality at the receiver by elementary signal processing operations across symmetric (mirror) pairs of subcarriers. Thereby, the proposed transmission protocol has a similar complexity as Alamouti's space-time block coding scheme and does not require extra transmit power nor any feedback. To evaluate the performance of IQSC, we derive closed-form expressions for the resulting outage probability and symbol-error rate. Interestingly, IQSC outperforms not only existing IQI compensation schemes but also the ideal system without IQI for the same spectral efficiency and practical target error rates, while it achieves almost the same performance as ideal (i.e., IQI-free) equal-rate repetition coding. Our findings reveal that IQSC is a promising low-complexity technique for significantly increasing the reliability of low-cost devices that suffer from high levels of IQI.<br
Keywords: Radio frequency; OFDM; Wireless communication; Interference; Receivers; Diversity reception

IRS-Assisted Active Device Detection - Laue, Friedemann; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2021)
This paper studies intelligent reflecting surface (IRS) assisted active device detection. Since the locations of the devices are a priori unknown, optimal IRS beam alignment is not possible and a worst-case design for a given coverage area is developed. To this end, we propose a generalized likelihood ratio test (GLRT) detection scheme and an IRS phase-shift design that minimizes the worst-case probability of misdetection. In addition to the proposed optimization-based phase-shift design, we consider two alternative suboptimal designs based on closed-form expressions for the IRS phase shifts. Our performance analysis establishes the superiority of the optimization-based design, especially for large coverage areas. Furthermore, we investigate the impact of scatterers on the proposed line-of-sight based design using simulations.
CRIS-Team Scopus Importer:2022-06-05

IRS-Assisted Green Communication Systems: Provable Convergence and Robust Optimization - Yu, Xianghao; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2021)
In this paper, we investigate resource allocation for IRS-assisted green multiuser multiple-input single-output (MISO) systems. To minimize the total transmit power, both the beamforming vectors at the access point (AP) and the phase shifts at multiple IRSs are jointly optimized, while taking into account the minimum required quality-of-service (QoS) of multiple users. First, two novel algorithms, namely a penalty-based alternating minimization (AltMin) algorithm and an inner approximation (IA) algorithm, are developed to tackle the non-convexity of the formulated optimization problem when perfect channel state information (CSI) is available. Existing designs employ semidefinite relaxation in AltMin-based algorithms, which, however, cannot ensure convergence. In contrast, the proposed penalty-based AltMin and IA algorithms are guaranteed to converge to a stationary point and a Karush-Kuhn-Tucker (KKT) solution of the design problem, respectively. Second, the impact of imperfect knowledge of the CSI of the channels between the AP and the users is investigated. To this end, a non-convex robust optimization problem is formulated and the penalty-based AltMin algorithm is extended to obtain a stationary solution. Simulation results reveal a key trade-off between the speed of convergence and the achievable total transmit power for the two proposed algorithms. In addition, we show that the proposed algorithms can significantly reduce the total transmit power at the AP compared to various baseline schemes and that the optimal numbers of transmit antennas and IRS reflecting elements, which maximize the system energy efficiency of the considered system, are finite.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Approximation algorithms; Array signal processing; Channel estimation; Convergence; Convergence; green communications; intelligent reflecting surface; MISO communication; Optimization; robust optimization; Wireless communication

IRS-Assisted Wireless Powered NOMA: Do We Really Need Different Phase Shifts in DL and UL? - Wu, Qingqing; Zhou, Xiaobo; Schober, Robert (IEEE Wireless Communications Letters, 2021)
Intelligent reflecting surface (IRS) is a promising technology to improve the performance of wireless powered communication networks (WPCNs) due to its capability to reconfigure signal propagation environments via smart reflection. In particular, the high passive beamforming gain promised by IRS can significantly enhance the efficiency of both downlink wireless power transfer (DL WPT) and uplink wireless information transmission (UL WIT) in WPCNs. Although adopting different IRS phase shifts for DL WPT and UL WIT, i.e., dynamic IRS beamforming, is in principle possible but incurs additional signaling overhead and computational complexity, it is an open problem whether it is actually beneficial. To answer this question, we consider an IRS-assisted WPCN where multiple devices employ a hybrid access point (HAP) to first harvest energy and then transmit information using non-orthogonal multiple access (NOMA). Specifically, we aim to maximize the sum throughput of all devices by jointly optimizing the IRS phase shifts and the resource allocation. To this end, we first prove that dynamic IRS beamforming is not needed for the considered system, which helps reduce the number of IRS phase shifts to be optimized. Then, we propose both joint and alternating optimization based algorithms to solve the resulting problem. Simulation results demonstrate the effectiveness of our proposed designs over benchmark schemes and also provide useful insights into the importance of IRS for realizing spectrum and energy efficient WPCNs.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Array signal processing; dynamic beamforming; Heuristic algorithms; IRS; NOMA; NOMA; Optimization; Throughput; time allocation.; Wireless communication; Wireless power transfer; wireless powered networks

IRS-Based Energy Efficiency and Admission Control Maximization for IoT Users with Short Packet Lengths - Jalali, Jalal; Khalili, Ata; Rezaei, Atefeh; Berkvens, Rafael; Weyn, Maarten; Famaey, Jeroen (IEEE Transactions on Vehicular Technology, 2023)
In this paper, we study a multiuser multiple-input single-output (MISO) machine type communication (MTC)-enabled intelligent reflecting surface (IRS) system, where a multi-antenna access point (AP) transmits information symbols to a set of Internet of Things (IoT) users with short packet transmission. In particular, the total energy efficiency (EE) and the number of IoT users that could be served fairly are maximized by jointly optimizing active and passive beamformers. An efficient algorithm based on alternating optimization (AO) is proposed to solve the main optimization problem iteratively. To this end, we adopt the difference of convex functions (DC) and successive convex approximation (SCA) to make a concave-convex function. Then, we employ the fractional programming based on the quadratic form to obtain a sub-optimal solution for the active beamformers at the AP and the number of admitted users. In the passive beamforming case, a penalty-based approach is utilized together with the SCA technique to handle the unit-modulus constraints at the IRS. Simulation results unveil an interesting tradeoff between EE and user admissibility performance. Besides, the results show the effectiveness of the IRS deployment in improving EE and successfully admitted users.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Admission control; alternating optimization (AO); energy efficiency (EE); intelligent reflecting surface (IRS); machine type communication (MTC); short packet transmission

Is NOMA Efficient in Multi-Antenna Networks? A Critical Look at Next Generation Multiple Access Techniques - Clerckx, Bruno; Mao, Yijie; Schober, Robert; Jorswieck, Eduard A.; Love, David J.; Yuan, Jinhong; Hanzo, Lajos; Li, Geoffrey Ye; Larsson, Erik G.; Caire, Giuseppe (IEEE Open Journal of the Communications Society, 2021)
In the past few years, a large body of literature has been created on downlink Non-Orthogonal Multiple Access (NOMA), employing superposition coding and Successive Interference Cancellation (SIC), in multi-antenna wireless networks. Furthermore, the benefits of NOMA over Orthogonal Multiple Access (OMA) have been highlighted. In this paper, we take a critical and fresh look at the downlink Next Generation Multiple Access (NGMA) literature. Instead of contrasting NOMA with OMA, we contrast NOMA with two other multiple access baselines. The first is conventional Multi-User Linear Precoding (MU-LP), as used in Space-Division Multiple Access (SDMA) and multi-user Multiple-Input Multiple-Output (MIMO) in 4G and 5G. The second, called Rate-Splitting Multiple Access (RSMA), is based on multi-antenna Rate-Splitting (RS). It is also a non-orthogonal transmission strategy relying on SIC developed in the past few years in parallel and independently from NOMA. We show that there is some confusion about the benefits of NOMA, and we dispel the associated misconceptions. First, we highlight why NOMA is inefficient in multi-antenna settings based on basic multiplexing gain analysis. We stress that the issue lies in how the NOMA literature, originally developed for single-antenna setups, has been hastily applied to multi-antenna setups, resulting in a misuse of spatial dimensions and therefore loss in multiplexing gains and rate. Second, we show that NOMA incurs a severe multiplexing gain loss despite an increased receiver complexity due to an inefficient use of SIC receivers. Third, we emphasize that much of the merits of NOMA are due to the constant comparison to OMA instead of comparing it to MU-LP and RS baselines. We then expose the pivotal design constraint that multi-antenna NOMA requires one user to fully decode the messages of the other users. This design constraint is responsible for the multiplexing gain erosion, rate and spectral efficiency loss, ineffectiveness to serve a large number of users, and inefficient use of SIC receivers in multi-antenna settings. Our analysis and simulation results confirm that NOMA should not be applied blindly to multi-antenna settings, highlight the scenarios where MU-LP outperforms NOMA and vice versa, and demonstrate the inefficiency, performance loss, and complexity disadvantages of NOMA compared to RSMA. The first takeaway message is that, while NOMA is suited for single-antenna settings (as originally intended), it is not efficient in most multi-antenna deployments. The second takeaway message is that another non-orthogonal transmission framework, based on RSMA, exists which fully exploits the multiplexing gain and the benefits of SIC to boost the rate and the number of users to serve in multi-antenna settings and outperforms both NOMA and MU-LP. Indeed, RSMA achieves higher multiplexing gains and rates, serves a larger number of users, is more robust to user deployments, network loads and inaccurate channel state information and has a lower receiver complexity than NOMA. Consequently, RSMA is a promising technology for NGMA and future networks such as 6G and beyond.
CRIS-Team WoS Importer:2021-07-16

Is RIS-Aided Massive MIMO Promising with ZF Detectors and Imperfect CSI? - Zhi, Kangda; Pan, Cunhua; Zhou, Gui; Ren, Hong; Elkashlan, Maged; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2022)
This paper provides a theoretical framework for understanding the performance of reconfigurable intelligent surface (RIS)-aided massive multiple-input multiple-output (MIMO) with zero-forcing (ZF) detectors under imperfect channel state information (CSI). We first introduce a low-overhead minimum mean square error (MMSE) channel estimator, and then derive and analyze closed-form expressions for the uplink achievable rate. Our analytical results demonstrate that: 1) regardless of the RIS phase shift design, the rate of all users scales at least on the order of O(log2 (MN)), where M and N are the numbers of antennas and reflecting elements, respectively; 2) by aligning the RIS phase shifts to one user, the rate of this user can at most scale on the order of O (log2 (MN2)); 3) either M or the transmit power can be reduced inversely proportional to N, while maintaining a given rate. Furthermore, we propose two low-complexity majorization-minimization (MM)-based algorithms to optimize the sum user rate and the minimum user rate, respectively, where closed-form solutions are obtained in each iteration. Finally, simulation results validate the accuracy of all derived analytical results. Our simulation results also show that the maximum sum rate can be closely approached by simply aligning the RIS phase shifts to an arbitrary user.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Channel estimation; Detectors; imperfect CSI; intelligent reflecting surface (IRS); majorization-minimization (MM); Manganese; massive MIMO; Massive MIMO; Optimization; Radio frequency; Reconfigurable intelligent surface (RIS); Signal to noise ratio; ZF

Iterative Antenna Selection for Secrecy Enhancement in Massive MIMO Wiretap Channels - Bereyhi, Ali; Asaad, Saba; Schaefer, Rafael F.; Müller, Ralf (IEEE International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2018)
The growth of interest in massive MIMO systems is accompanied with hardware cost and computational complexity. Antenna selection is an efficient approach to overcome this cost-plus-complexity issue which also enhances the secrecy performance in wiretap settings. Optimal antenna selection requires exhaustive search which is computationally infeasible for settings with large dimensions. This paper develops an iterative algorithm for antenna selection in massive multiuser MIMO wiretap settings. The algorithm takes a stepwise approach to find a suitable subset of transmit antennas. Numerical investigations depict a significant enhancement in the secrecy performance.

Iterative channel and data estimation: Framework and analysis via replica method - Vehkapera, Mikko; Takeuchi, Keigo; Müller, Ralf; Tanaka, Toshiyuki (2009 IEEE International Symposium on Information Theory, ISIT 2009, 2009)
The large system analysis of a randomly spread direct-sequence code-division multiple-access system operating over a frequency-selective fading channel is considered. Iterative multiuser detection and decoding based on generalized posterior mean estimation and interference cancellation is assumed. The channel is mismatched and provided by a linear estimator whose initial pilot-based decisions are iteratively refined by using a feedback from the single-user decoders. By an application of the replica method, a tool from statistical physics, and density evolution with Gaussian approximation, we show that the performance metrics of the considered multiuser system converge in distribution at the large system limit to that of a simple singleuser system operating over a flat fading channel. We also give the exact result of the hard decision feedback based channel estimator analyzed approximately by Li et al. (2007). © 2009 IEEE.
Keywords: Iterative Methods; Iterative Decoding; Feedback; Multiaccess communication; Frequency-selective fading channels; Multiuser detection; Interference cancellation; Physics; Gaussian Approximation; Measurement

Iterative channel estimation, detection, and decoding in large CDMA systems - Vehkaperä, Mikko; Takeuchi, Keigo; Müller, Ralf; Tanaka, Toshiyuki (6th International Symposium on Turbo Codes and Iterative Information Processing, ISTC 2010, 2010)
The large system analysis of randomly spread direct-sequence code-division multiple-access systems operating over frequency-selective fading channels is considered. Iterative multiuser detection and decoding (MUDD) based on generalized posterior mean estimation and single-user sum-product decoding is assumed to be used at the receiver. The channel state information (CSI) at the MUDD is mismatched and obtained by a linear channel estimator whose initial decisions are iteratively refined with the help of information feedback provided by the MUDD. Furthermore, a new training method by means of probability-biased signaling is proposed. The results indicate that in the large system limit and under certain threshold loads, a near single-user performance with perfect CSI can be achieved using a vanishing training overhead. It is also found that for the considered setups, the iterative linear minimum mean square error based channel estimator is near optimal for relatively slowly time-varying multipath fading channels. © 2010 IEEE.
Keywords: IP Networks; Channel estimation

Iterative Equalization with Soft Feedback with a Subsequent Stage Utilizing Hopfield Networks for Error Search and Correction - Rößler, Jürgen; Gerstacker, Wolfgang; Huber, Johannes (Conference Proceedings, 2004)
In this paper, a second stage for algorithms applying iterative soft decision interference cancellation (ISDIC), for channel equalization is proposed performing error search and correction. Analysis by simulations shows that a matched filter (MF) ISDIC with subsequent second stage can outperform a more complex minimum mean-squared error (MMSE) ISDIC. Furthermore, the latter can be improved by the proposed second stage by up to 2 dB. It is shown that the ISDIC scheme with following second stage can reach the matched filter bound up to a fraction of a dB for all analyzed channels and 4QAM transmission and up to 1 dB for 16QAM transmission. In [1] it has been reported that the MF ISDIC performs very well for highly dispersive channels, e.g. with 60 symbol-spaced paths, but for channels of moderate dispersion an error floor occurs. Utilizing performance bounds for delayed decision-feedback sequence estimation (DDFSE) we show that now already for channels of moderate length, e.g. 20 symbol-spaced taps, even the low-complexity MF ISDIC with the proposed subsequent second stage outperforms a DDFSE approach with about 109 states.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.iterat

Iterative joint channel estimation and multiuser detection for wireless MIMO-OFDM systems: Performance in a real indoor scenario - Salvo Rossi, Pierluigi; Pakniat, Parisa; Müller, Ralf; Edfors, Ove (4th IEEE International Symposium on Wireless Communication Systems 2007, ISWCS'07, 2007)
An iterative receiver for Multiple-Input Multiple-Output (MIMO) Orthogonal Frequency Division Multiplexing (OFDM) wireless systems is presented and tested on channel measurements from a real indoor scenario. The receiver jointly performs channel estimation and multiuser detection, with soft information iteratively provided by the singleuser decoders. Results for the performance are presented in terms of Bit Error Rate (BER) and relative Minimum Mean Square Error (MMSE) vs Signal-to-Noise Ratio (SNR). Comparison with the Single-User Bound (SUB) shows a loss in performance due to frequency correlation. © 2007 IEEE.

Iterative joint time-variant channel estimation and multi-user detection for MC-CDMA - Zemen, Thomas; Mecklenbräuker, Christoph F.; Wehinger, Joachim; Müller, Ralf (IEEE Transactions on Wireless Communications, 2006)
Joint time-variant channel estimation and multiuser detection are key building-blocks for wireless broadband communication for mobile users at vehicular speed. We propose an iterative receiver for a multi-carrier (MC) code division multiple access (CDMA) system in the uplink. Multi-user detection is implemented through iterative parallel interference cancelation and conditional linear minimum mean square error (MMSE) filtering. MC-CDMA is based on orthogonal frequency division multiplexing (OFDM), thus time-variant channel estimation can be performed for every subcarrier individually. The variation of a subcarrier over the duration of a data block is upper bounded by the maximum Doppler bandwidth which is determined by the maximum velocity of the users. We exploit results from the theory of time-concentrated and bandlimited sequences and apply a Slepian basis expansion for time-variant subcarrier estimation. This approach enables time-variant channel estimation without complete knowledge of the second-order statistics of the fading process. The square bias of the Slepian basis expansion is one order of magnitude smaller compared to the Fourier basis expansion. The square bias of the basis expansion is the determining factor for the performance of the iterative joint channel estimation and data detection. We present an iterative linear MMSE estimation algorithm for the basis expansion coefficients in a multi-user system. The consistent performance of the iterative receiver using the Slepian basis expansion is validated by simulations for a wide range of velocities. © 2006 IEE
Keywords: Discrete prolate spheroidal sequence; MC-CDMA; Multi-user detection; OFDM; Parallel interference cancelation; Slepian basis expansion; Time-variant channel estimation

Iterative LMMSE channel estimation and decoding based on probabilistic bias - Takeuchi, Keigo; Müller, Ralf; Vehkapera, Mikko (IEEE Transactions on Communications, 2013)
Iterative channel estimation and decoding based on probabilistic bias is investigated. In order to control the occurrence probability of transmitted symbols, biased convolutional codes (CCs) are proposed. A biased CC is obtained by puncturing the parity bit of a conventional (unbiased) CC and by inserting a fixed bit at the punctured position when the state is contained in a certain subset of all possible states. A priori information about the imposed bias is utilized for the initial linear minimum mean-squared error (LMMSE) channel estimation. This paper focuses on biased turbo codes that are constructed as the parallel concatenation of two biased CCs with interleaving, and proposes an iterative LMMSE channel estimation and decoding scheme based on approximate belief propagation. The convergence property of the iterative LMMSE channel estimation and decoding scheme is analyzed via density evolution (DE). The DE analysis allows one to design the magnitude of the bias according to the coherence time, in terms of the decoding threshold. The proposed scheme is numerically shown to outperform conventional pilot-based schemes in the moderate signal-to-noise ratio (SNR) regime, at the expense of a performance degradation in the high SNR regime. © 1972-2012 IEEE.
Keywords: Belief propagation; Biased convolutional codes; Density evolution; Iterative decoding; Linear minimum mean-squared error (LMMSE) channel estimation

Iterative multi-user decoding with time-variant channel estimation for MC-CDMA - Müller, Ralf; et al. (Fith IEE International Conference on 3G Mobile Communication Technologies 2004 - The Premier Technical Conference for 3G and Beyond, 2004)
We propose an iterative receiver for a multi-carrier (MC) code division multiple access (CDMA) system in the uplink for users moving at vehicular speed. MC-CDMA is based on orthogonal frequency division multiplexing (OFDM), thus time-variant channel estimation can be performed for every subcarrier independently. The variation of a subcarrier over the duration of a data block is upper bounded by a maximum Doppler bandwidth which is determined by the maximum velocity of the users and the carrier frequency. We exploit results from the theory of time-concentrated and bandlimited sequences and apply a Slepian basis expansion for time-variant subcarrier estimation. The Slepian basis functions are determined by two parameters; the block length and the maximum Doppler bandwidth. This approach enables time-variant channel estimation without complete knowledge of the second-order statistics of the fading process. The performance of the iterative receiver is validated for a wide range of velocities by simulations.
Keywords: Discrete prolate spheroidal sequence; Iterative time-variant channel estimation; MC-CDMA; OFDM; Slepian basis expansion

Iterative multiuser joint decoding: Optimal power allocation and low-complexity implementation - Caire, Giuseppe; Müller, Ralf; Tanaka, Toshiyuki (IEEE Transactions on Information Theory, 2004)
We consider a canonical model for coded code-division multiple access (CDMA) with random spreading, where the receiver makes use of iterative belief-propagation (BP) joint decoding. We provide simple density-evolution analysis in the large-system limit (large number of users) of the performance of the BP decoder and of some suboptimal approximations based on interference cancellation (IC). Based on this analysis, we optimize the received user signal-to-noise ratio (SNR) distribution in order to maximize the system spectral efficiency for given user channel codes, channel load (users per chip), and target user bit-error rate (BER). The optimization of the received SNR distribution is obtained by solving a simple linear program and can be easily incorporated into practical power control algorithms. Remarkably, under the optimized SNR assignment, the suboptimal minimum mean-square error (MMSE) IC-based decoder performs almost as well as the more complex BP decoder. Moreover, for a large class of commonly used convolutional codes, we observe that the optimized SNR distribution consists of a finite number of discrete SNR levels. Based on this observation, we provide a low-complexity approximation of the MMSE-IC decoder that suffers from very small performance degradation while attaining considerable savings in complexity. As by-products of this work, we obtain a closed-form expression of the multiuser efficiency (ME) of power-mismatched MMSE filters in the large-system limit, and we extend the analysis of the symbol-by-symbol maximum a posteriori probability (MAP) multiuser detector in the large-system limit to the case of nonconstant user powers and nonuniform symbol prior probabilities. © 2004 IEE

Jinghua Zhong Gemeinsame Kanalschätzung und Detektion für Ein- und Mehrantennen-Empfänger - Schmidt, Armin Christian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2006)

Joint Active and Passive Secure Precoding in IRS-Aided MIMO Systems - Asaad, Saba; Wu, Yifei; Bereyhi, Ali; Müller, Ralf; Schaefer, Rafael F.; Poor, H. Vincent (2021 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2021)
Using intelligent reflecting surfaces (IRSs), wireless propagation channels can be manipulated such that information leakage to eavesdropping terminals in a multiple-input multiple-output (MIMO) setting is significantly suppressed. This observation illustrates the potential secrecy gains of IRS-aided MIMO systems. This work develops a novel low-complexity algorithm by which these potential gains are exploited. Invoking methods from fractional programming, the algorithm iteratively designs the digital precoder at the transmitter and tunes the IRS elements, such that the weighted secrecy sum-rate is maximized. It is shown that as the algorithm iterates, the weighted secrecy sum-rate evolves in a non-decreasing way. Numerical investigations confirm the efficiency of the proposed algorithm.<br
CRIS-Team WoS Importer:2022-05-27
Keywords: Intelligent reflecting surfaces; physical-layer security; fractional programming; MIMO precoding

Joint antenna combining and multiuser detection - Müller, Ralf; Cottatellucci, Laura (Smart Antennas: State of the Art, 2005)

Joint Beamforming and Phase Shift Optimization for Multicell IRS-aided OFDMA-URLLC Systems - Ghanem, Walid; Jamali Kooshkghazi, Vahid; Schober, Robert (2021 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2021)
CRIS-Team WoS Importer:2021-10-29

Joint Data Compression and Computation Offloading in Hierarchical Fog-Cloud Systems - Ti Ti Nguyen,; Vu Nguyen Ha,; Long Bao Le,; Schober, Robert (IEEE Transactions on Wireless Communications, 2020)
Data compression (DC) has the potential to significantly improve the computation offloading performance in hierarchical fog-cloud systems. However, it remains unknown how to optimally determine the compression ratio jointly with the computation offloading decisions and the resource allocation. This optimization problem is studied in this paper where we aim to minimize the maximum weighted energy and service delay cost (WEDC) of all users. First, we consider a scenario where DC is performed only at the mobile users. We prove that the optimal offloading decisions have a threshold structure. Moreover, a novel three-step approach employing convexification techniques is developed to optimize the compression ratios and the resource allocation. Then, we address the more general design where DC is performed at both the mobile users and the fog server. We propose three algorithms to overcome the strong coupling between the offloading decisions and the resource allocation. Numerical results show that the proposed optimal algorithm for DC at only the mobile users can reduce the WEDC by up to 65% compared to computation offloading strategies that do not leverage DC or use sub-optimal optimization approaches. The proposed algorithms with additional DC at the fog server lead to a further reduction of the WEDC.
CRIS-Team Scopus Importer:2020-02-04
Keywords: computation offloading; data compression; energy saving; Fog computing; hierarchical fog/cloud; latency; mixed integer non-linear programming; resource allocation

Joint Deployment and Multiple Access Design for Intelligent Reflecting Surface Assisted Networks - Mu, Xidong; Liu, Yuanwei; Guo, Li; Lin, Jiaru; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
The fundamental intelligent reflecting surface (IRS) deployment problem is investigated for IRS-assisted networks, where one IRS is arranged to be deployed in a specific region for assisting the communication between an access point (AP) and multiple users. Specifically, three multiple access schemes are considered, namely non-orthogonal multiple access (NOMA), frequency division multiple access (FDMA), and time division multiple access (TDMA). The weighted sum rate maximization problem for joint optimization of the deployment location and the reflection coefficients of the IRS as well as the power allocation at the AP is formulated. The non-convex optimization problems obtained for NOMA and FDMA are solved by employing monotonic optimization and semidefinite relaxation to find a performance upper bound. The problem obtained for TDMA is optimally solved by leveraging the time-selective nature of the IRS. Furthermore, for all three multiple access schemes, low-complexity suboptimal algorithms are developed by exploiting alternating optimization and successive convex approximation techniques, where a local region optimization method is applied for optimizing the IRS deployment location. Numerical results are provided to show that: 1) near-optimal performance can be achieved by the proposed suboptimal algorithms; 2) asymmetric and symmetric IRS deployment strategies are preferable for NOMA and FDMA/TDMA, respectively; 3) the performance gain achieved with IRS can be significantly improved by optimizing the deployment location.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Channel estimation; Deployment design; Downlink; intelligent reflecting surface; MISO communication; monotonic optimization; NOMA; non-orthogonal multiple access; Resource management; Transmission line matrix methods; Wireless communication

Joint Detection and Classification of RF Signals Using Deep Learning - Vagollari, Adela; Schram, Viktoria; Wicke, Wayan; Hirschbeck, Martin; Gerstacker, Wolfgang (2021 IEEE 93RD VEHICULAR TECHNOLOGY CONFERENCE (VTC2021-SPRING), 2021)
CRIS-Team WoS Importer:2021-09-24

Joint Estimation of Channel Parameters in Massive MIMO Systems via PARAFAC Analysis - Wei, Xiao; Peng, Wei; Wing Kwan Ng, Derrick; Schober, Robert; Jiang, Tao (2018 International Conference on Computing, Networking and Communications (ICNC), 2018)
In this paper, we investigate channel parameter estimation for massive multiple-input multiple-output (MIMO) systems, where a large base station (BS) antenna array is used to provide multiplexing and diversity gains. We propose a Parallel Factor (PARAFAC)-based joint estimation scheme, which exploits the low-rank property of massive MIMO channels caused by the physical finite scattering environment. Specifically, we first parameterize the channel in terms of fading coefficients, directions of arrival (DOAs), and delays, thereby the channel is characterized via three equivalent PARAFAC models. Subsequently, we certify the identifiability of the three parameters of the PARAFAC models by exploiting the low-rank property. Then, we develop the proposed PARAFAC-based estimation scheme, which jointly estimates the three channel parameters using an alternating least squares (ALS) algorithm. Moreover, we analyze the computational complexity of the proposed scheme in terms of the required number of floating-point operations (FLOPs). Simulation results show that the proposed scheme achieves both a high performance and a low computational complexity.<br
Keywords: MIMO communication; Estimation; Channel estimation; Direction-of-arrival estimation; Delays; Fading channels; Computational modeling

Joint iterative time-variant channel estimation and multi-user detection for MIMO-OFDM systems - Salvo Rossi, Pierluigi; Müller, Ralf (50th Annual IEEE Global Telecommunications Conference, GLOBECOM 2007, 2007)
This paper presents an iterative receiver for Multiple-Input Multiple-Output (MIMO) Orthogonal Frequency Division Multiplexing (OFDM) systems. The receiver performs channel estimation and multi-user detection, with soft information iteratively provided by the single-user decoders. Time-variance is effectively taken into account exploiting the properties of the discrete prolate spheroidal (DPS) sequences. Simulation results for the performance are presented in terms of Bit Error Rate (BER) vs Signal-to-Noise Ratio (SNR), showing how the Single-User Bound (SUB) is approached in a few iterations. © 2007 IEEE.

Joint Optimal Pricing and Task Scheduling in Mobile Cloud Computing Systems - Shah-Mansouri, Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
The evolving mobile cloud computing (MCC) paradigm enables mobile users to offload their computing tasks to cloud servers. In this paper, we study the following problems in MCC systems: 1) which tasks should be offloaded to cloud servers? 2) and what is the optimal price of cloud services? We jointly address these issues by formulating two levels of optimization problems. On the mobile users side, we formulate a utility maximization problem that takes the energy consumption, delay, and price of cloud services into account and obtain the optimal scheduling for both delay-sensitive and delay-tolerant applications. On the cloud service provider (CSP) side, we determine the optimal pricing strategy by formulating a profit maximization problem, which is non-convex in general. We further propose an algorithm using convexification and primal-dual methods to mitigate the non-convexity. Through numerical studies, we investigate the mobile users' behavior and the CSP's pricing strategy. Our results reveal that the proposed scheduler effectively balances the tradeoff between the energy consumption and delay in comparison with different schedulers proposed in the literature. Furthermore, we show that with the proposed pricing algorithm, the CSP can improve its profit by up to 25% compared with static and dynamic pricing strategies.<br
Keywords: Cloud computing; Mobile communication; Pricing; Energy consumption; Mobile handsets; Servers; 5218 - 5232 Delays

Joint Power and Rate Control for Device-to-Device Communications in Cellular Systems - Song, Hojin; Ryu, Jong Yeol; Choi, Wan; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
This paper investigates device-to-device (D2D) communication nested in a cellular network, where a pair of D2D users directly exchanges their information using the uplink frequency band of the cellular network. When the D2D user treats the interference from the cellular user as noise, power control at the cellular user is optimal for maximizing the rate of the cellular user while controlling the interference to the D2D user. However, if the D2D user can perform successive interference cancelation (SIC), the cellular user needs to adjust both transmit power and rate to maximize its rate, because the decodability of the interfering signals at the D2D user depends not only on the signal power but also on the rate of the cellular user. To control the interference from the cellular user, we propose a joint transmit power and rate control scheme at the cellular user. Forcing the cellular user to transmit with a reduced data rate compared with the maximum possible rate, given its transmit power, the proposed joint power and rate control scheme efficiently enables SIC at the D2D user. To reduce the computational complexity, we also propose a near-optimal scheme that employs either power control or rate control depending on the channel conditions.<br
Keywords: Interference; Receivers; Silicon carbide; Power control; Quality of service; Transmitters; Uplink

JOINT POWER AND SUBCARRIER ALLOCATION FOR MULTI CARRIER FULL-DUPLEX SYSTEMS - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we investigate resource allocation for multicarrier communication systems employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. We study the joint power and subcarrier allocation design for the maximization of the weighted sum throughput of the system. The algorithm design is formulated as a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution may require prohibitively high computational complexity. Therefore, a low computational complexity suboptimal iterative algorithm exploiting successive convex approximation is proposed to obtain a locally optimal solution. Simulation results confirm that the proposed suboptimal algorithm obtains a substantial improvement in system throughput compared to various existing baseline schemes.

Joint Source-Relay Optimization for Fixed Receivers in Multi-Antenna Multi-Relay Networks - Ikhlef, Aissa; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
We jointly optimize the source and relay precoders for multi-antenna multi-relay networks employing a prefixed receiver. Prefixed receivers are of practical interest since they enable low complexity at the end-user's receiver as well as backward compatibility. To compute the source and relay precoders, we consider two different criteria. The objective of the first criterion is to maximize the worst stream signal-to-interference-plus-noise ratio (SINR) at the output of the receiver subject to source and relay transmit power constraints. Under the second criterion, we minimize the source and relay transmit powers subject to a certain quality-of-service constraint. Both optimization problems are non-convex. To solve them, we propose iterative alternating algorithms, where, in each iteration, we compute the precoders alternately, i.e., for each precoder optimization, we fix all the precoders except the one which is optimized. For both criteria, we formulate the optimization problem for the computation of the source precoder as a second order cone programming (SOCP) problem, for which the optimal solution can be found using interior point algorithms. For each relay precoder, we formulate the optimization problem as a semidefinite relaxation (SDR) problem for which ready-to-use solvers exist. If the solution to the SDR problem is not of rank one, matrix rank-one decomposition or randomization is applied. We also provide sufficient conditions for the convergence of the proposed iterative alternating algorithms to a fixed point. Simulation results show that the performance of the proposed algorithms is close to the performance achieved if the source, relay, and receiver filters are jointly optimized.<br
Keywords: Relays; Optimization; Receivers; Equalizers; Frequency modulation; Joints; Signal to noise ratio

Joint twofold-iterative channel estimation and multiuser detection for MIMO-OFDM systems - Rossi, Pierluigi Salvo; Müller, Ralf (IEEE Transactions on Wireless Communications, 2008)
This paper presents an iterative receiver for Multiple-Input Multiple-Output (MIMO) Orthogonal Frequency Division Multiplexing (OFDM) systems over time-variant wireless channels. The receiver performs joint decoding, channel estimation, and multiuser detection, with soft information iteratively provided by the single-user decoders. Time-variance is effectively taken into account exploiting the properties of the Discrete Prolate Spheroidal (DPS) sequences, being the bandlimited sequences with maximum energy concentration in time. Turbo codes are used for each transmit antenna, thus the receiver presents an iterative structure also in the single-user case. Simulation results for the performance are presented in terms of Bit Error Rate (BER) and Normalized Mean Square Error (NMSE) vs Signal-to-Noise Ratio (SNR). The effects of the number of external and internal iterations as well as the number of pilots on the performance of the system are investigated. © 2008 IEEE.
Keywords: Channel estimation; Discrete prolate spheroidal sequences; Iterative decoding; MIMO channels; Multiuser detection; OFDM systems; Turbo codes

Joint Uplink-Downlink Resource Allocation for OFDMA-URLLC MEC Systems - Ghanem, Walid; Jamali, Vahid; Zhang, Qiuyu; Schober, Robert (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
In this paper, we study resource allocation algorithm design for multiuser orthogonal frequency division multiple access (OFDMA) ultra-reliable low latency communication (URLLC) in mobile edge computing (MEC) systems. To achieve the stringent end-to-end delay and reliability requirements of URLLC MEC systems, we propose joint uplink-downlink resource allocation and finite blocklength transmission. Furthermore, we propose a partial time overlap between the uplink and downlink frames to minimize the end-to-end delay, which introduces new time causality constraints. Then, the proposed resource allocation algorithm is formulated as an optimization problem for minimization of the total weighted transmit power of the network under constraints on the minimum quality-of-service regarding the number of computed URLLC user bits within the maximum allowable computing time, i.e., the end-to-end delay of a computation task. Due to the non-convexity of the optimization problem, finding the globally optimal solution entails a high computational complexity which is not tolerable for real-time applications. Therefore, a low-complexity algorithm based on successive convex approximation is proposed to find a high-quality sub-optimal solution. Our simulation results show that the proposed resource allocation algorithm design facilitates the application of URLLC in MEC systems, and yields significant power savings compared to a benchmark scheme.
CRIS-Team Scopus Importer:2021-04-19

Joint user pairing, frequency allocation, and beamforming for MIMO SC-FDMA transmission with QoS requirements - Ruder, Michael; Gerstacker, Wolfgang (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
In this paper, we consider joint user pairing and frequency allocation with beamforming (BF) assuming per user Quality of Service (QoS) requirements. A single-carrier frequency-division multiple-access (SC-FDMA) transmission employing a zero-forcing (ZF) detector at the receiver is assumed. The BF filter coefficients are jointly optimized with the user pairing and frequency allocation of the users. The transmit power savings achievable by combining BF with user pairing and frequency allocation are compared to these of a constant power allocation over all subcarriers. To this end, BF filter coefficient optimization and constant power allocation are briefly revisited and novel BF filter solutions for single-input multiple-output (SIMO) and single-input single-output (SISO) transmission, respectively, are derived for SC-FDMA. Numerical results show that the transmit power can be significantly reduced with BF for suboptimum algorithms, but for optimal joint user pairing and frequency allocation the gain of BF compared to constant power allocation is negligibl

Joint User Selection and Precoding in Multiuser MIMO Systems via Group LASSO - Asaad, Saba; Bereyhi, Ali; Müller, Ralf; Schaefer, Rafael F. (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2019)
Joint user selection and precoding in multiuser MIMO settings can be interpreted as group sparse recovery in linear models. In this problem, a signal with group sparsity is to be reconstructed from an underdetermined system of equations. This paper utilizes this equivalent interpretation and develops a computationally tractable algorithm based on the method of group LASSO. Compared to the state of the art, the proposed scheme shows performance enhancements in two different respects: higher achievable sum-rate and lower interference at the non-selected user terminals.
CRIS-Team Scopus Importer:2019-12-13
Keywords: group LASSO; massive MIMO; precoding; User selection

Key Agreement Over A State-Dependent 3-Receiver Broadcast Channel - Bahrami, Mohsen; Bereyhi, Ali; Salehkalaibar, Sadaf; Aref, Mohammad Reza (Iran Workshop on Communication and Information Theory (IWCIT), 2013)
In this paper, we consider the problem of secret key agreement in state-dependent 3-receiver broadcast channels. In the proposed model, there are two legitimate receivers, an eavesdropper and a transmitter where the channel state information is non-causally available at the transmitter. We consider two setups. In the first setup, the transmitter tries to agree on a common key with the legitimate receivers while keeping it concealed from the eavesdropper. Simultaneously, the transmitter agrees on a private key with each of the legitimate receivers that needs to be kept secret from the other legitimate receiver and the eavesdropper. For this setup, we derive inner and outer bounds on the secret key capacity region. In the second setup, we assume that a backward public channel is available among the receivers and the transmitter. Each legitimate receiver wishes to share a private key with the transmitter. For this setup, an inner bound on the private key capacity region is found. Furthermore, the capacity region of the secret key in the state-dependent wiretap channel can be deduced from our inner and outer bounds.

Large-scale analysis of linear massive MIMO Precoders in the Presence of Phase Noise - Krishnan, R.; Khanzadi, M. R.; Krishnan, N.; Wu, Yongpeng; Graell I Amat, A.; Eriksson, T.; Schober, Robert (2015 IEEE International Conference on Communication Workshop, ICCW 2015, 2015)
We study the impact of phase noise on the downlink performance of a multi-user multiple-input multiple-output system, where the base station (BS) employs a large number of transmit antennas M. We consider a setup where the BS employs Mosc free-running oscillators, and M/Mosc antennas are connected to each oscillator. For this configuration, we analyze the impact of phase noise on the performance of regularized zero-forcing (RZF) precoding, when M and the number of users K are asymptotically large, while the ratio M/K = β is fixed. We analytically show that the impact of phase noise on the signal-to-interference-plus-noise ratio (SINR) can be quantified as an effective reduction in the quality of the channel state information available at the BS when compared to a system without phase noise. As a consequence, we observe that as Mosc increases, the SINR of the RZF precoder degrades as the interference power increases, and the desired signal power decreases. On the other hand, the variance of the random phase variations caused by the BS oscillators reduces with increasing Mosc. Through simulations, we verify our analytical results, and study the performance of the RZF precoder for different phase noise and channel noise variances.
CRIS-Team Scopus Importer:2020-01-31

Large-Scale MIMO Secure Transmission with Finite Alphabet Inputs - Wu, Yongpeng; Wang, Jun-Bo; Wang, Jue; Schober, Robert; Xiao, Chengshan (2017)
In this paper, we investigate secure transmission over the large-scale multiple-antenna wiretap channel with finite alphabet inputs. First, we show analytically that a generalized singular value decomposition (GSVD) based design, which is optimal for Gaussian inputs, may exhibit a severe performance loss for finite alphabet inputs in the high signal-to-noise ratio (SNR) regime. In light of this, we propose a novel Per-Group-GSVD (PG-GSVD) design which can effectively compensate the performance loss caused by the GSVD design. More importantly, the computational complexity of the PG-GSVD design is by orders of magnitude lower than that of the existing design for finite alphabet inputs in Wu2012TVT while the resulting performance loss is minimal. Numerical results indicate that the proposed PG-GSVD design can be efficiently implemented in large-scale multiple-antenna systems and achieves significant performance gains compared to the GSVD design.<br
Keywords: antenna arrays; computational complexity; MIMO communication; singular value decomposition; telecommunication security; wireless channels

Large system analysis of a binary low-cost MIMO transmitter - Sedaghat, Mohammad A.; Müller, Ralf (7th Int’l ITG Workshop on Smart Antennas, 2013)

Large-system analysis of joint channel and data estimation for MIMO DS-CDMA systems - Takeuchi, Keigo; Vehkaperä, Mikko; Tanaka, Toshiyuki; Müller, Ralf (IEEE Transactions on Information Theory, 2012)
This paper presents a large-system analysis of the performance of joint channel estimation, multiuser detection, and per-user decoding (CE-MUDD) for randomly spread multiple-input multiple-output (MIMO) direct-sequence code-division multiple-access (DS-CDMA) systems. A suboptimal receiver based on successive decoding in conjunction with linear minimum mean-squared error (LMMSE) channel estimation is investigated. The replica method, developed in statistical mechanics, is used to evaluate the performance in the large-system limit, where the number of users and the spreading factor tend to infinity while their ratio and the number of transmit and receive antennas are kept constant. Joint CE-MUDD based on LMMSE channel estimation is compared to several methods of one-shot channel estimation, i.e., methods that do not utilize decoded data symbols to refine the initial channel estimates, in terms of spectral efficiency. Joint CE-MUDD is found to significantly reduce the rate loss caused by transmission of pilot signals when compared to the receivers based on one-shot channel estimation. This holds particularly for multiple-antenna systems. As a result, joint CE-MUDD can provide significant performance gains compared to the receivers based on one-shot channel estimation. © 2011 IEEE.
Keywords: Channel estimation; direct-sequence code-division multiple-access (DS-CDMA) schemes; iterative receivers; large-system analysis; linear minimum mean-squared error (LMMSE) estimation; multiple-input multiple-output (MIMO) systems; multiuser detection (MUD); replica method; statistical mechanics; successive decoding

Large-system analysis of joint user selection and vector precoding with zero-forcing transmit beamforming for MIMO broadcast channels - Takeuchi, Keigo; Müller, Ralf; Kawabata, Tsutomu (2012 International Symposium on Information Theory and Its Applications, ISITA 2012, 2012)
Multiple-input multiple-output (MIMO) broadcast channels (BCs) (MIMO-BCs) with perfect channel state information (CSI) at the transmitter are considered. As joint user selection (US) and vector precoding (VP) (US-VP) with zero-forcing transmit beamforming (ZF-BF), US and continuous VP (CVP) (US-CVP) and data-dependent US (DD-US) are investigated. The replica method, developed in statistical physics, is used to analyze the energy penalties for the two US-VP schemes in the large-system limit, where the number of users, the number of selected users, and the number of transmit antennas tend to infinity with their ratios kept constant. Four observations are obtained in the large-system limit: First, the assumptions of replica symmetry (RS) and 1-step replica symmetry breaking (1RSB) for DD-US can provide acceptable approximations for low and moderate system loads, respectively. Secondly, DD-US outperforms CVP with random US in terms of the energy penalty for low-to-moderate system loads. Thirdly, the asymptotic energy penalty of DD-US is indistinguishable from that of US-CVP for low system loads. Finally, a greedy algorithm of DD-US proposed in authors' previous work can achieve nearly optimal performance for low-to-moderate system loads. © 2012 IEICE Institute of Electronics Informati.

Latency and Reliability of mmWave Multi-Hop V2V Communications Under Relay Selections - Li, Zipeng; Xiang, Lin; Ge, Xiaohu; Mao, Guoqiang; Chao, Han-Chieh (IEEE Transactions on Vehicular Technology, 2020)
Timely and reliable information sharing among autonomous vehicles (AVs) provides a promising approach for reducing traffic congestion and improving traffic efficiency in future intelligent transportation systems. In this paper, we consider millimeter-wave (mmWave) based multi-hop vehicle-to-vehicle (V2V) communications to facilitate ultra-reliable low-latency information sharing among AVs. We propose a novel framework for performance analysis and design of relay selection schemes in mmWave multi-hop V2V communications, while taking into account the mmWave signal propagation characteristics, road topology, and traffic conditions. In particular, considering the minimum tracking distance requirement of road traffic, the headway, i.e., the distance between adjacent AVs, is modeled as shifted-exponential distribution. Moreover, we model the communication path losses using the Manhattan distance metric in the taxicab geometry, which can more accurately capture the characteristics of mmWave signal propagation in urban grid roads than conventional Euclidean distance geometry. Based on the proposed model, we investigate the latency and reliability of mmWave multi-hop V2V communications for three widely adopted relay selection schemes, i.e., random with forward progress (RFP), most forward with fixed radius (MFR), and nearest with forward progress (NFP), respectively. Furthermore, we propose a novel relay selection scheme for joint optimization of the single-hop forward progress (FP) and single-hop latency according to the AVs' instantaneous locations and an estimate of the residual multi-hop latency. Simulation results show that, by balancing the current single-hop latency and the residual multi-hop latency for the multi-hop V2V network, the proposed relay selection scheme significantly outperforms the MFR, NFP and RFP in both multi-hop transmission latency and reliability of mmWave V2V communications.
CRIS-Team WoS Importer:2020-10-30

Lattice-reduction aided HNN for vector precoding - Gardasevic, Vesna; Müller, Ralf; Ryan, Daniel; Lundheim, Lars; Øien, Geir (2010 20th International Symposium on Information Theory and Its Applications, ISITA 2010 and the 2010 20th International Symposium on Spread Spectrum Techniques and Applications, ISSSTA 2010, 2010)
In this paper we propose a modification of the Hopfield neural networks for vector precoding, based on Lenstra, Lenstra, and Lovàsz lattice basis reduction. This precoding algorithm controls the energy penalty for system loads α = K/N close to 1, with N and K denoting the number of transmit and receive antennas, respectively. Simulation results for the average transmit energy as a function of α show that our algorithm improves performance within the range 0.9 ≤ α ≤ 1, between 0.4 dB and 2.6 dB in comparison to standard HNN precoding. The proposed algorithm performs close to the sphere encoder (SE) while requiring much lower complexity, and thus, can be applied as an efficient suboptimal precoding method. © 2010 IEEE.

Leader-Follower Dynamics for Diffusion-based Molecular Communication - Gomez, Jorge Torres; Wicke, Wayan; Toledo, Karel; Schober, Robert; Dressler, Falko (2021 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2021)
CRIS-Team WoS Importer:2022-05-27

Least Square Error Precoders for Massive MIMO With Signal Constraints: Fundamental Limits - Sedaghat, Mohammad Ali; Bereyhi, Ali; Müller, Ralf (IEEE Transactions on Wireless Communications, 2018)
This paper proposes nonlinear least square error (LSE) precoders for multiuser MIMO broadcast channels. The LSE precoders are designed such that the discrete output signals are from a predefined set. This predefined set allows us to model several signal constraints such as peak power constraint, constant envelope, and discrete constellations. We study the large-system performance of these precoders via the replica method from statistical physics, and derive a closed-form expression for the asymptotic distortion. Our results demonstrate that an LSE precoder with the output peak-to-average power ratio of 3 dB can perform similar to the regularized zero forcing (RZF) precoder. As the peak-to-average power ratio reduces to one, the constant envelope precoder is recovered. The investigations show that the performance of the RZF precoder is achieved by a constant envelope precoder with 20% additional transmit antennas. For M-phase shift keying constellations, our analysis gives a lower bound on the asymptotic distortion which is tight for moderate antenna-to-user ratios and deviates as the ratio grows. We improve this bound by deriving the replica solution under one-step of replica symmetry breaking. Our numerical investigations for this case show that the bound is tight for antenna-to-user ratios less than
Keywords: Massive MIMO; Precoding; Nonlinear distortion; Peak to average power ratio

Limited-Feedback Parity-Based Hybrid ARQ Using Spatially-Coupled LDPC Codes - Frenzel, Janik; Mueller-Weinfurtner, Stefan; Huber, Johannes; Müller, Ralf (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Linear Computation Coding: A Framework for Joint Quantization and Computing - Müller, Ralf; Gäde, Bernhard; Bereyhi, Ali (Algorithms, 2022)
Here we introduce the new concept of computation coding. Similar to how rate-distortion theory is concerned with the lossy compression of data, computation coding deals with the lossy computation of functions. Particularizing to linear functions, we present an algorithmic approach to reduce the computational cost of multiplying a constant matrix with a variable vector, which requires neither a matrix nor vector having any particular structure or statistical properties. The algorithm decomposes the constant matrix into the product of codebook and wiring matrices whose entries are either zero or signed integer powers of two. For a typical application like the implementation of a deep neural network, the proposed algorithm reduces the number of required addition units several times. To achieve the accuracy of 16-bit signed integer arithmetic for 4k-vectors, no multipliers and only 1.5 adders per matrix entry are needed.
CRIS-Team WoS Importer:2022-08-12

Linear computation coding - Müller, Ralf; Gäde, Bernhard; Bereyhi, Ali (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2021)
We introduce the new concept of computation coding. For linear functions, we present an algorithm to reduce the computational cost of multiplying an arbitrary given matrix with an unknown vector. It decomposes the given matrix into the product of codebook and wiring matrices whose entries are either zero or signed integer powers of two. For a typical implementation of deep neural networks, the proposed algorithm reduces the number of required addition units several times. To achieve the accuracy of 16-bit signed integer arithmetic for 4k-vectors, no multipliers and only 1.5 adders per matrix entry are needed.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Approximate computing; Fixed-point arithmetic; Neural networks; Quantization

Linear Computation Coding: Exponential Search and Reduced-State Algorithms - Rosenberger, Hans; Fröhlich, Johanna S.; Bereyhi, Ali; Müller, Ralf (Data Compression Conference Proceedings, 2023)
Linear computation coding is concerned with the compression of multidimensional linear functions, i.e. with reducing the computational effort of multiplying an arbitrary vector to an arbitrary, but known, constant matrix. This paper advances over the state-of-the art, that is based on a discrete matching pursuit (DMP) algorithm, by a step-wise optimal search. Offering significant performance gains over DMP, it is however computationally infeasible for large matrices and high accuracy. Therefore, a reduced-state algorithm is introduced that offers performance superior to DMP, while still being computationally feasible even for large matrices. Depending on the matrix size, the performance gain over DMP is on the order of at least 10%.
CRIS-Team Scopus Importer:2023-06-09

Linear Computation Coding for Convolutional Neural Networks - Müller, Ralf; Rosenberger, Hans; Reichenbach, Marc (2023)
Linear computation coding is a recent method aimed to reduce the computational effort for matrix-vector multiplications. Previous algorithms work especially well for large, dense matrices. These algorithms are adapted here for use in convolutional neural networks, where filter kernels typically consist of small, square matrices. For kernel matrices with a uniform element distribution, the number of additions (multiplications are counted as multiple additions) can be reduced compared to a standard implementation by a factor of two to five depending on the kernel size. For an implementation of LeNet5, the number of adders required is reduced by a factor of up to 2.74 compared to standard methods.<br
Keywords: Convolutional codes; Convolution; Conferences; Signal processing algorithms; Filtering algorithms; Encoding; Convolutional neural networks

Linear Computation Coding Inspired by the Lempel-Ziv Algorithm - Müller, Ralf (2022 IEEE INFORMATION THEORY WORKSHOP (ITW), 2022)
CRIS-Team WoS Importer:2023-02-10

Linear detectors for multi-user MIMO systems with correlated spatial diversity - Cottatellucci, Laura; Müller, Ralf; Debbah, Merouane (14th European Signal Processing Conference, EUSIPCO 2006, 2006)
A multiuser CDMA system with both the transmitting and the receiving sites equipped with multiple antenna elements is considered. The multiuser MIMO channel is correlated at the transmitting and the receiving sites. Multistage detectors achieving near-linear MMSE performance with a complexity order per bit linear in the number of users are proposed. The large system performance is analyzed in a general framework including any multiuser detector that admits a multistage representation. The performance of this large class of detectors is independent of the channel correlation at the transmitters. It depends on the direction of the channel gain vector of the user of interest if the channel gains are correlated.
Keywords: Detectors; Abstracts; 3G mobile communication; Fading; Legged locomotion; Information theory

Linear Massive MIMO Precoders in the Presence of Phase Noise - A Large-Scale Analysis - Krishnan, Rajet; Khanzadi, M. R.; Krishnan, N.; Wu, Yongpeng; Graell I Amat, Alexandre; Eriksson, Thomas; Schober, Robert (IEEE Transactions on Vehicular Technology, 2016)
We study the impact of phase noise on the downlink performance of a multiuser multiple-input-multiple-output (MIMO) system, where the base station (BS) employs a large number of transmit antennas M. We consider a setup where the BS employs Mosc free-running oscillators, and M/Mosc antennas are connected to each oscillator. For this configuration, we analyze the impact of phase noise on the performance of zero forcing (ZF), regularized ZF, and matched filter precoders when M and the number of users K are asymptotically large, whereas the ratio M/K = β is fixed. We analytically show that the impact of phase noise on the signal-to-interference-plus-noise ratio (SINR) can be quantified as an effective reduction in the quality of the channel state information (CSI) available at the BS when compared with a system without phase noise. As a consequence, we observe that as Mosc increases, the SINR performance of all considered precoders degrades. On the other hand, the variance of the random phase variations caused by the BS oscillators reduces with increasing Mosc. Through Monte Carlo simulations, we verify our analytical results and compare the performance of the precoders for different phase noise and channel noise variances. For all considered precoders, we show that when β is small, the performance of the setup where all BS antennas are connected to a single oscillator is superior to that of the setup where each BS antenna has its own oscillator. However, the opposite is true when β is large and the signal-to-noise ratio (SNR) at the users is low.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Broadcast channel (BC); linear precoding; massive multiple-input multiple-output (MIMO); multiuser (MU) MIMO; phase noise; random matrix theory (RMT)

Linear MIMO precoding in jointly-correlated fading multiple access channels with finite alphabet signaling - Wu, Yongpeng; Wen, Chao-Kai; Xiao, Chengshan; Gao, Xiqi; Schober, Robert (2014 IEEE International Conference on Communications (ICC), 2014)
In this paper, we investigate the design of linear precoders for multiple-input multiple-output (MIMO) multiple access channels (MAC). We assume that statistical channel state information (CSI) is available at the transmitters and consider the problem under the practical finite alphabet input assumption. First, we derive an asymptotic (in the large-system limit) weighted sum rate (WSR) expression for the MIMO MAC with finite alphabet inputs and general jointly-correlated fading. Subsequently, we obtain necessary conditions for linear precoders maximizing the asymptotic WSR and propose an iterative algorithm for determining the precoders of all users. In the proposed algorithm, the search space of each user for designing the precoding matrices is its own modulation set. This significantly reduces the dimension of the search space for finding the precoding matrices of all users compared to the conventional precoding design for the MIMO MAC with finite alphabet inputs, where the search space is the combination of the modulation sets of all users. As a result, the proposed algorithm decreases the computational complexity for MIMO MAC precoding design with finite alphabet inputs by several orders of magnitude. Simulation results for finite alphabet signalling indicate that the proposed iterative algorithm achieves significant performance gains over existing precoder designs, including the precoder design based on the Gaussian input assumption, in terms of both the sum rate and the coded bit error rate.<br
Keywords: MIMO; Algorithm design and analysis; Vectors; Transmitters; Fading; Mutual information; Modulation

Linear multiuser detection for asynchronous CDMA systems: Chip pulse design and time delay distribution - Cottatellucci, Laura; Debbah, Merouane; Müller, Ralf (2006 IEEE Information Theory Workshop, ITW 2006, 2006)
The large system performance analysis of linear multiuser detectors (e.g. MMSE, MSWF, multistage detectors) for asynchronous CDMA systems is provided. While the performance of synchronous systems with square-root waveforms is independent of the chip bandwidth, the performance of asynchronous systems depends on the pulse shape and the bandwidth. It increases as the bandwidth increases beyond half on the chip rate and, in such a case, asynchronous systems outperform the synchronous ones. © 2006 IEEE.
Keywords: Multiuser detection; Multiaccess communication; Delay effects; Detectors; Performance analysis; Bandwidth; Signal to noise Ratio; Low pass filters; Nonlinear filters; Matched filters

Linear Precoding for the MIMO Multiple Access Channel With Finite Alphabet Inputs and Statistical CSI - Wu, Yongpeng; Wen, Chao-Kai; Xiao, Chengshan; Gao, Xiqi; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
In this paper, we investigate the design of linear precoders for the multiple-input-multiple-output (MIMO) multiple access channel (MAC). We assume that statistical channel state information (CSI) is available at the transmitters and consider the problem under the practical finite alphabet input assumption. First, we derive an asymptotic (in the large system limit) expression for the weighted sum rate (WSR) of the MIMO MAC with finite alphabet inputs and Weichselberger's MIMO channel model. Subsequently, we obtain the optimal structures of the linear precoders of the users maximizing the asymptotic WSR and an iterative algorithm for determining the precoders. We show that the complexity of the proposed precoder design is significantly lower than that of MIMO MAC precoders designed for finite alphabet inputs and instantaneous CSI. Simulation results for finite alphabet signaling indicate that the proposed precoder achieves significant performance gains over existing precoder designs.<br
Keywords: MIMO; Transmitters; Vectors; Channel models; Fading; Mutual information; Iterative methods

Linear Precoding of Data and Artificial Noise in Secure Massive MIMO Systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2015)
n this paper, we consider secure downlink transmission in a multicell massive multiple-input multiple-output (MIMO) system where the numbers of base station (BS) antennas, mobile terminals, and eavesdropper antennas are asymptotically large. The channel state information of the eavesdropper is assumed to be unavailable at the BS and hence, linear precoding of data and artificial noise (AN) are employed for secrecy enhancement. Four different data precoders (i.e., selfish zero-forcing (ZF)/regularized channel inversion (RCI) and collaborative ZF/RCI precoders) and three different AN precoders (i.e., random, selfish/collaborative null-space-based precoders) are investigated and the corresponding achievable ergodic secrecy rates are analyzed. Our analysis includes the effects of uplink channel estimation, pilot contamination, multicell interference, and path-loss. Furthermore, to strike a balance between complexity and performance, linear precoders that are based on matrix polynomials are proposed for both data and AN precoding. The polynomial coefficients of the data and AN precoders are optimized, respectively, for minimization of the sum-mean-squared-error of and the AN leakage to the mobile terminals in the cell of interest using tools from free probability and random matrix theory. Our analytical and simulation results provide interesting insights for the design of secure multicell massive MIMO systems and reveal that the proposed polynomial data and AN precoders closely approach the performance of selfish RCI data and null-space-based AN precoders, respectively.<br
Keywords: MIMO; Interference; Polynomials; Collaboration; Contamination; Complexity theory; Downlink

Link Allocation for Multiuser Systems With Hybrid RF/FSO Backhaul: Delay-Limited and Delay-Tolerant Designs - Jamali Kooshkghazi, Vahid; Michalopoulos, Diomidis; Uysal, Murat; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we consider a cascaded radio frequency (RF) and hybrid RF/free space optical (FSO) system where several mobile users transmit their data over an RF link to a decode-and-forward relay node (e.g., a small cell base station) and the relay forwards the information to a destination (e.g., a macro-cell base station) over a hybrid RF/FSO backhaul link. The relay and the destination employ multiple antennas for transmission and reception over the RF links while each mobile user has a single antenna. The RF links are orthogonal to the FSO link but half-duplex with respect to each other, i.e., either the user-relay RF link or the relay-destination RF link is active. For this communication setup, we derive the optimal fixed and adaptive link allocation policies for sharing the transmission time between the RF links based on the statistical and instantaneous channel state information (CSI) of the RF and FSO links, respectively. Thereby, we consider the following two scenarios depending on the delay requirements: 1) delay-limited transmission where the relay has to immediately forward the packets received from the users to the destination, and 2) delay-tolerant transmission where the relay is allowed to store the packets received from the users in its buffer and forward them to the destination when the quality of the relay-destination RF link is favorable. Our numerical results illustrate the effectiveness of the proposed communication architecture and link allocation policies, and their superiority compared to existing schemes, which employ only one type of backhaul link.<br
Keywords: Radio frequency; Relays; Resource management; Delays; Antennas; Wireless communication; Mobile nodes

Link performance of an ESPAR-antenna array in rich scattering and clustered channels - Bains, R.; Müller, Ralf; Kalis, A. (Wireless Personal Communications, 2009)
This paper aims at evaluating the link performance of an electronically steerable passive array radiator (ESPAR) in both rich scattering and clustered channels. Previous work has shown that the performance of an ESPAR-antenna can be comparable to a 2 × 2 multiple-input-multiple-output (MIMO) system in a rich scattering environment. The design of the antenna patterns used for transmission was based on intuition, and therefore cannot be guaranteed to be optimal. In this paper, we design the antenna patterns by minimizing the average inner-product between signals that are transmitted with different antenna patterns. We also evaluate the performance of the ESPAR-antenna at higher spectral-efficiencies than previous literature has done. The performance in terms of spectral-efficiency is evaluated for both rich scattering environments and clustered channels, whereas the performance in terms of symbol error rate is evaluated for rich scattering channels only. © 2008 Springer Science+Business Media, LLC.
Keywords: Compact antenna arrays; ESPAR-antennas; MIMO; Passive antenna elements; Single RF-frontend; Spatial multiplexing

Link performance of an ESPAR-antenna array in rich scattering and clustered channels - Bains, Robert; Müller, Ralf; Kalis, Antonis (4th IEEE International Symposium on Wireless Communication Systems 2007, ISWCS'07, 2007)
This paper aims at evaluating the link performance of an Electronically Steerable Passive Array Radiator (ESPAR) in both rich scattering and clustered channels. Previous work has shown that the performance of an ESPAR-antenna can be comparable to a 2×2 Multiple-Input-Multiple-Output (MIMO) system in a rich scattering environment. The design of the antenna patterns used for transmission was based on intuition, and therefore cannot be guaranteed to be optimal. In this paper we follow a slightly different approach to the design of antenna patterns. We also evaluate the performance of the ESPAR antenna at higher spetral efficiencies than previous literaure has done. The performance in terms of spectral-efficiency is evaluated for both rich scattering environments and clustered channels. © 2007 IEEE.
Keywords: Impedance; Electromagnetic scattering; MIMO; Transmitting antennas; Voltage; Antenna Arrays; Equations; Receiving antennas; Information Technology; Electromagnetic induction

Load modulated arrays: A low complexity antenna - Sedaghat, Mohammad Ali; Barousis, Vlasis I.; Müller, Ralf; Papadias, Constantinos B. (IEEE Communications Magazine, 2016)

Load modulated massive MIMO - Müller, Ralf; Sedaghat, Mohammad Ali; Fischer, Georg (2014 IEEE Global Conference on Signal and Information Processing, GlobalSIP 2014, 2014)
We propose a new hardware architecture for cost-and size-effective implementation of massive MIMO transmitters based on load modulation that is fully compatible with standard receiver architectures. With load modulation, a massive MIMO transmitter can be driven by a single power amplifier operating at constant envelope. The various data streams are modulated onto the antennas elements by varying the complex impedances of the various antenna circuits at symbol rate. The law of large numbers ensures that the common power source is matched to the parallel concatenation of the various antenna circuits, if the number of antenna elements is very large. For 100 antenna elements that are supposed to transmit Gaussian-like signals, e.g. due to OFDM modulation and/or precoding, the crest factor is only 1.2 dB at a clipping probability of 0.1%. In that case, load modulation reduces the average consumed power and the amplifier peak power by 49% and 79%, respectively, as compared to classical distributed amplifiers with voltage modulation. Furthermore, one class F amplifier can be used to replace 100 class A/B amplifiers. Mutual antenna coupling need not be addressed by a physical matching network, but can be mitigated dynamically by digital signal processing in baseband without additional hardware. This allows for closer antenna spacing as in architectures with distributed amplifiers.
Keywords: Antenna coupling; Crest factor; Load modulation; Massive MIMO; Multi-antenna systems; Power amplifier

Load Scheduling and Power Trading in Systems With High Penetration of Renewable Energy Resources - Samadi, Pedram; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2015)
In this paper, we focus on the problems of load scheduling and power trading in systems with high penetration of renewable energy resources (RERs). We adopt approximate dynamic programming to schedule the operation of different types of appliances including must-run and controllable appliances. We assume that users can sell their excess power generation to other users or to the utility company. Since it is more profitable for users to trade energy with other users locally, users with excess generation compete with each other to sell their respective extra power to their neighbors. A game theoretic approach is adopted to model the interaction between users with excess generation. In our system model, each user aims to obtain a larger share of the market and to maximize its revenue by appropriately selecting its offered price and generation. In addition to yielding a higher revenue, consuming the excess generation locally reduces the reverse power flow, which impacts the stability of the system. Simulation results show that our proposed algorithm reduces the energy expenses of the users. The proposed algorithm also facilitates the utilization of RERs by encouraging users to consume excess generation locally rather than injecting it back into the power grid.<br
Keywords: Home appliances; Demand-side management; Power markets; Scheduling; Dynamic programming

Localization of a Silent Target Node in Magnetic Induction based Wireless Underground Sensor Networks - Kisseleff, Steven; Chen, Xiaoyang; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE International Conference on Communications (ICC), 2017)

LOS/NLOS Classification Using Scenario-Dependent Unsupervised Machine Learning - Kirmaz, Anil; Michalopoulos, Diomidis S.; Balan, Irina; Gerstacker, Wolfgang (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2021)
Location information is essential for a wide range of applications requiring, for example, highly accurate positioning information such as industrial automation, autonomous driving, inbound logistics and augmented reality. One of the major error sources in positioning is non-line-of-sight (NLOS) propagation while a line-of-sight (LOS) propagation is anticipated. Therefore, classifying positioning measurements as LOS or NLOS plays a key role to enable high accuracy positioning use cases.Existing solutions for the classification task either rely on availability of label or reference measurement data or do not consider effects of different scenarios or channel models. In this paper, we propose an unsupervised method for the classification task through a channel feature selection process to select only useful channel features to be used for the classification. Then, we show based on real-world data from several measurement campaigns that the proposed method outperforms the existing solutions both in classification performance and ranging accuracy.
CRIS-Team Scopus Importer:2021-11-12
Keywords: channel feature selection; channel impulse response; high accuracy positioning; line-of-sight classification; multipath identification; Unsupervised machine learning

Low-Complexity Hybrid Linear/Tomlinson-Harashima Precoding for Downlink Large-Scale MU-MIMO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2016 IEEE Globecom Workshops (GC Wkshps), 2016)
In this paper, we propose a novel low-complexity hybrid linear/Tomlinson-Harashima precoder (HL-THP) for downlink large-scale multiuser multiple-input multiple-output (MU-MIMO) systems. The proposed precoder comprises an inner linear precoder which is designed based on only the second order statistics of the channel state information (CSI) and outer THPs which exploit the instantaneous overall CSI of the cascade of the actual channel and the inner precoder. Thereby, the user terminals (UTs) are divided into groups, where for each group a THP successively mitigates the intra-group interference, whereas the inter-group interference is canceled by the inner linear precoder. Our analytical and simulation results show that the proposed HL-THP achieves a substantially higher average rate per UT and a considerably lower bit error rate (BER) than the linear regularized zero-forcing (RZF) precoder. Moreover, both the average achievable rate per UT and the BER of the proposed HL-THP are close to those of the conventional THP. In addition, we analyze the computational complexity of the proposed HL-THP in terms of the required number of floating-point operations. These results reveal that the proposed HL-THP has a much lower computational complexity than the conventional THP and RZF precoders, respectively. This and its high performance make the HL-THP an excellent candidate for practical systems.<br
Keywords: Computational complexity; Precoding; MIMO; Interference; Antennas; Benchmark testing; Downlink

Low-Complexity Linear Precoding for Downlink Large-Scale MIMO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Müller, Ralf; Schober, Robert (2013)
In this work, we present a low-complexity linear precoding scheme for downlink large-scale multiple-input multiple-output (MIMO) systems. The proposed scheme can achieve near minimum mean square error (MMSE) precoding performance in terms of the sum rate and is based on a matrix polynomial instead of matrix inversion. Simulation results show that matrix polynomials consisting of only a few terms are sufficient to closely approach the sum rate of the classical MMSE precoder and to perform orders of magnitude better than the simple conjugate beamforming (BF) precoder. We derive exact expressions for the computational complexity of the proposed scheme in terms of the number of additions and multiplications and compare it to the complexity of the BF and MMSE precoders. Our complexity analysis shows that for large number of base station antennas N compared to the number of generated transmit symbols tau per channel estimate and large number of users K, the proposed polynomial precoder has a lower complexity than the classical MMSE precoder.

Low-Complexity MIMO Precoding for Finite-Alphabet Signals - Wu, Yongpeng; Wing Kwan Ng, Derrick; Wen, Chao-Kai; Schober, Robert; Lozano, Angel (IEEE Transactions on Wireless Communications, 2017)
This paper investigates the design of precoders for single-user multiple-input multiple-output (MIMO) channels, and, in particular, for finite-alphabet signals. Based on an asymptotic expression for the mutual information of channels exhibiting line-of-sight components and rather general antenna correlations, precoding structures that decompose the general channel into a set of parallel subchannel pairs are proposed. Then, a low-complexity iterative algorithm is devised to maximize the sum mutual information of all pairs. The proposed algorithm significantly reduces the computational load of existing approaches with only minimal loss in performance. The complexity savings increase with the number of transmit antennas and with the cardinality of the signal alphabet, making it possible to support values thereof that were unmanageable with existing solutions. Most importantly, the proposed solution does not require instantaneous channel state information (CSI) at the transmitter, but only statistical CSI.<br
Keywords: MIMO; Mutual information; Channel models; Precoding; Complexity theory; Transmitting antennas

Low-complexity MIMO precoding with discrete signals and statistical CSI - Wu, Yongpeng; Wen, Chao-Kai; Wing Kwan Ng, Derrick; Schober, Robert; Lozano, Angel (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, we investigate the design of multiple-input multiple-output single-user precoders for finite-alphabet signals under the premise of statistical channel-state information at the transmitter. Based on an asymptotic expression for the mutual information of channels exhibiting antenna correlations, we propose a low-complexity iterative algorithm that radically reduces the computational load of existing approaches by orders of magnitude with only minimal losses in performance. The complexity savings increase with the number of transmit antennas and with the cardinality of the signal alphabet, making it possible to support values thereof that were unwieldy in existing solutions.<br
Keywords: Transmitters; MIMO; Mutual information; Channel models; Precoding; Receivers; Constellation diagram

Low complexity ML-detection of arbitrary spherical codes - Rachinger, Christoph; Huber, Johannes; Müller, Ralf (11th International ITG Conference on Systems, Communications & Coding, 2017)

Low-Complexity Widely-Linear Precoding for Downlink Large-Scale MU-MISO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (IEEE Communications Letters, 2015)
In this letter, we present a widely-linear minimum mean square error (WL-MMSE) precoding scheme employing real-valued transmit symbols for downlink large-scale multi-user multiple-input single-output (MU-MISO) systems. In contrast to the existing WL-MMSE transceivers for single-user multiple-input multiple-output (SU-MIMO) systems, which use both WL precoders and WL detectors, the proposed scheme uses WL precoding only and simple conventional detection at the user terminals (UTs). Moreover, to avoid the computational complexity associated with inversion of large matrices, we modify the WL-MMSE precoder using polynomial expansion (PE). Our simulation results show that in overloaded systems, where the number of UTs is larger than the number of base station antennas, the proposed PE WL-MMSE precoder with only a few terms in the matrix polynomial achieves a substantially higher sum rate than systems employing conventional MMSE precoding. Hence, more UTs sharing the same time/frequency resources can be served in a cell. We validate our simulation results with an analytical expression for the asymptotic sum rate which is obtained by using results from random matrix theory.<br
Keywords: Uplink; Downlink; Signal to noise ratio; Interference; Vectors; Detectors; MIMO

Low latency-constrained high rate coding: LDPC codes vs. convolutional codes - Rachinger, Christoph; Müller, Ralf; Huber, Johannes (2014 8th International Symposium on Turbo Codes and Iterative Information Processing, ISTC 2014, 2014)
This paper complements and generalizes the results in [1], [2] while taking new formulas from [3] into account. We compare convolutional and LDPC codes of different rates with respect to their structural delay. This property is intrinsic to the encoding and decoding process and gives a fundamental limit to the achievable latency for end-to-end communication, even when infinite processing speed is assumed. We show that in the case of very low delay convolutional codes perform better than LDPC codes and even break fundamental existence bounds for block codes for some rates. Furthermore, non-punctured convolutional codes can benefit from their shorter constraint length and reduce the delay further.

Low-to-Zero-Overhead IRS Reconfiguration: Decoupling Illumination and Channel Estimation - Jamali, Vahid; Alexandropoulos, George C.; Schober, Robert; Vincent Poor, H. (IEEE Communications Letters, 2022)
Most algorithms developed for the optimization of Intelligent Reflecting Surfaces (IRSs) so far require knowledge of full Channel State Information (CSI). However, the resulting acquisition overhead constitutes a major bottleneck for the realization of IRS-assisted wireless systems in practice. In contrast, in this paper, focusing on downlink transmissions from a Base Station (BS) to a Mobile User (MU) that is located in a blockage region, we propose to optimize the IRS for illumination of the area centered around the MU. Hence, the proposed design requires the estimation of the MU’s position and not the full CSI. For a given IRS phase-shift configuration, the end-to-end BS-IRS-MU channel can then be estimated using conventional channel estimation techniques. The IRS reconfiguration overhead for the proposed scheme depends on the MU mobility as well as on how wide the coverage of the IRS illumination is. Therefore, we develop a general IRS phase-shift design, which is valid for both the near- and far-field regimes and features a parameter for tuning the size of the illumination area. Moreover, we study a special case where the IRS illuminates the entire blockage area, which implies that the IRS phase shifts do not change over time leading to zero overhead for IRS reconfiguration.
CRIS-Team Scopus Importer:2022-03-18
Keywords: blockage area; channel estimation; Channel estimation; Downlink; Estimation; illumination area; Intelligent reflecting surfaces; Lighting; Location awareness; low-overhead design; Signal to noise ratio; Wireless communication

Magnetic Induction-Based Simultaneous Wireless Information and Power Transfer for Single Information and Multiple Power Receivers - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2016)
Magnetic induction (MI)-based communication systems have gained increased attention in recent years. Typical applications for these systems lie in the area of wireless power transfer, near-field communication (NFC), and wireless sensor networks in challenging environments. In this paper, a system for simultaneous wireless information and power transfer (SWIPT) using MI-based signal transmission is designed for supporting one data stream and multiple parallel power streams. One of the possible applications for this scheme is an NFC-based access point. The overall system is optimized to guarantee a certain quality-of-service for the data stream as well as a maximum sum receive power for all power receivers (max-sum problem) or a maximum receive power for the worst power receiver (max-min problem), respectively. Both optimization problems turn out to be non-convex, such that the optimum solution cannot be found with limited computational complexity. Hence, we provide efficient suboptimal solutions. In this context, a convex approximation of the transmit power constraint in MI-based multiple-input multiple-output systems turns out to be very useful. A very high achievable power efficiency renders the proposed MI-based SWIPT system very promisin

Magnetic Nanoparticle Based Interface for Molecular Communication Systems - Kisseleff, Steven; Schober, Robert; Gerstacker, Wolfgang (IEEE Communications Letters, 2017)

Magnetic nanoparticle based molecular communication in microfluidic environments - Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (IEEE Transactions on Nanobioscience, 2019)
The possibility to guide and control magnetic nanoparticles in a non-invasive manner has spawned various applications in biotechnology, such as targeted drug deliveryandsensingofbiologicalsubstances.Theseapplications are facilitated by the engineering of the size, selective chemical reactivity, and general chemical composition of the employed particles. Motivated by their widespread useandfavorableproperties,inthispaper,weprovideatheoreticalstudyofthepotentialbeneﬁtsofmagneticnanoparticles for the design of molecular communication systems. In particular, we consider a magnetic nanoparticle-based communication in a microﬂuidic channel where an external magnetic ﬁeld is employed to attract the informationcarrying particles to the receiver. We show that the particle transport affected by the Brownian motion, ﬂuid ﬂow, and an external magnetic ﬁeld can be mathematically modeled as diffusion with drift. Thereby, we reveal that the key parameters determining the magnetic force are the particle size and the magnetic ﬁeld gradient. Moreover, we derive an analyticalexpressionfor the channel impulse response, which is used to evaluatethe potentialgain in the expected number of observed nanoparticles due to the magnetic ﬁeld.Furthermore,adoptingthesymbolerrorrateasperformance metric, we show that using magnetic nanoparticles can enable a reliable communication in the presence of disruptive ﬂuid ﬂow. The numerical results obtained by the particle-based simulation validate the accuracy of the derived analyticalexpressions.<br

Magnetic nanoparticle-based molecular communication in microfluidic environments - Wicke, Wayan; Ahmadzadeh, Arman; Jamali, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (IEEE Transactions on Nanobioscience, 2019)
The possibility to guide and control magnetic nanoparticles in a non-invasive manner has spawned various applications in biotechnology, such as targeted drug delivery and sensing of biological substances. These applications are facilitated by the engineering of the size, selective chemical reactivity, and general chemical composition of the employed particles. Motivated by their widespread use and favorable properties, in this paper, we provide a theoretical study of the potential benefits of magnetic nanoparticles for the design of molecular communication systems. In particular, we consider a magnetic nanoparticle-based communication in a microfluidic channel where an external magnetic field is employed to attract the information-carrying particles to the receiver. We show that the particle transport affected by the Brownian motion, fluid flow, and an external magnetic field can be mathematically modeled as diffusion with drift. Thereby, we reveal that the key parameters determining the magnetic force are the particle size and the magnetic field gradient. Moreover, we derive an analytical expression for the channel impulse response, which is used to evaluate the potential gain in the expected number of observed nanoparticles due to the magnetic field. Furthermore, adopting the symbol error rate as performance metric, we show that using magnetic nanoparticles can enable a reliable communication in the presence of disruptive fluid flow. The numerical results obtained by the particle-based simulation validate the accuracy of the derived analytical expressions.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Analytical solution; diffusion; fluid flow; magnetic nanoparticles; microfluidic channel; molecular communication

Magnetic Steering of Superparamagnetic Nanoparticles in Duct Flow for Molecular Communication: A Feasibility Study - Schlechtweg, Niklas; Meyer, Sebastian; Unterweger, Harald; Bartunik, Max; Ahmed, Doaa; Wicke, Wayan; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Weigel, Robert; Schober, Robert; Kirchner, Jens (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST, 2019)
Molecular communication (MC) denotes information transmission by use of molecules and nanosized particles. For the realization of testbeds, superparamagnetic iron oxide nanoparticles (SPIONs) in duct flow have recently been proposed. Here, an experimental setup is provided to direct these particles at a branching of a tube into a specific direction by use of magnetic fields. For that purpose, gold-coated SPIONs suspended in water at constant flow rate are considered at a Y-shaped connector of tubes. The particles are attracted by use of a custom-made electromagnet, while change of particle concentration in either of the branches is measured by a commercial susceptometer. The approach is evaluated for different flow rates and with the electromagnet both at a fixed position and moving along the tube. Exemplary measurements show that an information transmission is feasible in both approaches and with all tested flow rates. The feasibility study hence shows that particle steering by use of magnetic fields is a viable approach, which is even robust against flow rate variations. It can thus be used in MC to address different transmission channels as well as to realize differential signal transmission. Furthermore, it might help to improve magnetic drug targeting in future applications.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Duct flow; Magnetic field; Molecular communication; Particle steering; Superparamagnetic nanoparticles

Markov Decision Process Based Design of SWIPT Systems: Non-Linear EH Circuits, Memory, and Impedance Mismatch - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2021)
In this paper, we study simultaneous wireless information and power transfer (SWIPT) systems employing practical non-linear energy harvester (EH) circuits. Since the voltage across the reactive elements of realistic EH circuits cannot drop or rise instantaneously, EHs have memory which we model with a Markov decision process (MDP). Moreover, since an analytical model that accurately models all non-linear effects and the unavoidable impedance mismatch of EHs is not tractable, we propose a learning based model for the EH circuit. We optimize the input signal distribution for maximization of the harvested power under a constraint on the minimum mutual information between transmitter (TX) and information receiver (IR). We distinguish the cases where the MDP state is known and not known at TX and IR. When the MDP state is known, the formulated optimization problem for the harvested power is convex. In contrast, if TX and IR do not know the MDP state, the resulting optimization problem is non-convex and solved via alternating optimization, which is shown to yield a limit point of the problem. Our simulation results reveal that the rate-power region of the considered SWIPT system depends on the symbol duration, the EH input power level, the EH impedance mismatch, and the type of EH circuit. In particular, a shorter symbol duration enables higher bit rates at the expense of a significant decrease in the average harvested power. Furthermore, whereas half-wave rectifiers outperform full-wave rectifiers in the low and medium input power regimes, full-wave rectifiers are preferable if the input power at the EH is high.
CRIS-Team Scopus Importer:2021-03-05
Keywords: energy harvesting; impedance matching; low-pass filters (LPF); Markov processes; non-linear circuits; rectennas; rectifiers; signal design; Wireless power transmission

Massive Access for 5G and Beyond - Chen, Xiaoming; Ng, Derrick Wing Kwan; Yu, Wei; Larsson, Erik G.; Al-Dhahir, Naofal; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2021)
Massive access, also known as massive connectivity or massive machine-type communication (mMTC), is one of the main use cases of the fifth-generation (5G) and beyond 5G (B5G) wireless networks. A typical application of massive access is the cellular Internet of Things (IoT). Different from conventional human-type communication, massive access aims at realizing efficient and reliable communications for a massive number of IoT devices. Hence, the main characteristics of massive access include low power, massive connectivity, and broad coverage, which require new concepts, theories, and paradigms for the design of next-generation cellular networks. This paper presents a comprehensive survey of massive access design for B5G wireless networks. Specifically, we provide a detailed review of massive access from the perspectives of theory, protocols, techniques, coverage, energy, and security. Furthermore, several future research directions and challenges are identified.
CRIS-Team WoS Importer:2021-03-26

Massive Access in Extra Large-Scale MIMO With Mixed-ADC Over Near-Field Channels - Mei, Yikun; Gao, Zhen; Mi, De; Zhou, Mingyu; Zheng, Dezhi; Matthaiou, Michail; Xiao, Pei; Schober, Robert (IEEE Transactions on Vehicular Technology, 2023)
Massive connectivity for extra large-scale multi-input multi-output (XL-MIMO) systems is a challenging issue due to the near-field access channels and the prohibitive cost. In this paper, we propose an uplink grant-free massive access scheme for XL-MIMO systems, in which a mixed-analog-to-digital converters (ADC) architecture is adopted to strike the right balance between access performance and power consumption. By exploiting the spatial-domain structured sparsity and the piecewise angular-domain cluster sparsity of massive access channels, a compressive sensing (CS)-based two-stage orthogonal approximate message passing algorithm is proposed to efficiently solve the joint activity detection and channel estimation problem. Particularly, high-precision quantized measurements are leveraged to perform accurate hyper-parameter estimation, thereby facilitating the activity detection. Moreover, we adopt a subarray-wise estimation strategy to overcome the severe angular-domain energy dispersion problem which is caused by the near-field effect in XL-MIMO channels. Simulation results verify the superiority of our proposed algorithm over state-of-the-art CS algorithms for massive access based on XL-MIMO with mixed-ADC architectures.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Channel estimation; Compressive sensing; massive access; Massive MIMO; Message passing; MIMO communication; mixed-ADC; orthogonal approximate message passing; Quantization (signal); Receiving antennas; Signal processing algorithms; XL-MIMO system

Massive Gaussian Multiple-Access by Random Coding With Soft Interference Cancellation - Müller, Ralf (IEEE INTERNATIONAL CONFERENCE ON COMMUNICATIONS (ICC 2021), 2021)
CRIS-Team WoS Importer:2021-12-17

Massive MIMO with antenna selection: Fundamental limits and applications - Asaad, Saba; Rabiei, Amir Masoud; Müller, Ralf (IEEE Transactions on Wireless Communications, 2018)

Maximum-A-Posteriori Signal Recovery with Prior Information: Applications to Compressive Sensing - Bereyhi, Ali; Müller, Ralf (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2018)
This paper studies the asymptotic performance of maximum-a-posteriori estimation in the presence of prior information. The problem arises in several applications such as recovery of signals with non-uniform sparsity pattern from underdetermined measurements. With prior information, the maximum-a-posteriori estimator might have asymmetric penalty. We consider a generic form of this estimator and study its performance via the replica method. Our analyses demonstrate an asymmetric form of the decoupling property in the large-system limit. Employing our results, we further investigate the performance of weighted zero-norm minimization for recovery of a non-uniform sparse signal. Our investigations illustrate that for a given distortion, the minimum number of required measurements can be significantly reduced by choosing weighting coefficients optimally.
Keywords: Maximum-a-posteriori estimation; Compressive sensing; Weighted norm minimization; Decoupling property; Replica method

Maximum SNR Transmit Filtering for Decision-Feedback Equalization in Physical Layer Network Coding - Schmidt, Armin Christian; Gerstacker, Wolfgang; Schober, Robert (SCC 2013; 9th International ITG Conference on Systems, Communication and Coding, 2013)
We consider a two-way relaying system employing physical layer network coding (PNC) in channels suffering from frequency-selective fading. In order to mitigate the distortions introduced by the channel, decision-feedback equalization (DFE) is used at the relay node. We introduce transmit filters that generate identical overall channel impulse responses for the links from both source nodes to the relay node, while achieving the maximum signal-to-noise ratio (SNR) for zero-forcing DFE and minimum mean-squared error DFE at the relay node. The performance gain of our novel approach is compared against a benchmark filtering scheme which also creates identical channel impulse responses to enable decision-feedback equalization at the rela

Maximum SNR transmit filtering for linear equalization in physical layer network coding - Schmidt, Armin Christian; Gerstacker, Wolfgang; Schober, Robert (2012 IEEE Globecom Workshops, 2013)
We consider a two-way relaying system employing physical layer network coding (PNC) in channels suffering from frequency-selective fading. In order to mitigate the distortions introduced by the channel, a linear equalizer is used at the relay node. We introduce transmit filters that generate identical overall channel impulse responses for both source nodes, while achieving the maximum signal-to-noise ratio (SNR) for linear zero-forcing (ZF) and minimum mean-squared error (MMSE) equalization at the relay node. The performance gain of our novel approach is compared against a benchmark filtering scheme which also creates identical channel impulse responses to enable linear equalization at the rela

Max-Min Fair Beamforming for SWIPT Systems with Non-Linear EH Model - Boshkovska, Elena; Chen, Xiaoming; Dai, Linglong; Wing Kwan Ng, Derrick; Schober, Robert (2017 IEEE 86th Vehicular Technology Conference (VTC-Fall), 2017)
We study the beamforming design for multiuser systems with simultaneous wireless information and power transfer (SWIPT). Employing a practical non-linear energy harvesting (EH) model, the design is formulated as a non-convex optimization problem for the maximization of the minimum harvested power across several energy harvesting receivers. The proposed problem formulation takes into account imperfect channel state information (CSI) and a minimum required signal-to-interference-plus-noise ratio (SINR). The globally optimal solution of the design problem is obtained via the semidefinite programming (SDP) relaxation approach. Interestingly, we can show that at most one dedicated energy beam is needed to achieve optimality. Numerical results demonstrate that with the proposed design a significant performance gain and improved fairness can be provided to the users compared to two baseline schemes.<br
Keywords: Erbium; Integrated circuit modeling; Receivers; Array signal processing; Wireless communication; Radio frequency; Mathematical model

Max-min fair wireless energy transfer for secure multiuser communication systems - Wing Kwan Ng, Derrick; Schober, Robert (2014 IEEE Information Theory Workshop (ITW 2014), 2014)
This paper considers max-min fairness for wireless energy transfer in a downlink multiuser communication system. Our resource allocation design maximizes the minimum harvested energy among multiple multiple-antenna energy harvesting receivers (potential eavesdroppers) while providing quality of service (QoS) for secure communication to multiple single-antenna information receivers. In particular, the algorithm design is formulated as a non-convex optimization problem which takes into account a minimum required signal-to-interference-plus-noise ratio (SINR) constraint at the information receivers and a constraint on the maximum tolerable channel capacity achieved by the energy harvesting receivers for a given transmit power budget. The proposed problem formulation exploits the dual use of artificial noise generation for facilitating efficient wireless energy transfer and secure communication. A semidefinite programming (SDP) relaxation approach is exploited to obtain a global optimal solution of the considered problem. Simulation results demonstrate the significant performance gain in harvested energy that is achieved by the proposed optimal scheme compared to two simple baseline schemes.<br
Keywords: Receivers; Energy harvesting; Resource management; Noise; Wireless communication; Interference; Optimization

Max–Min Multicell-Aware Precoding and Power Allocation for Downlink Massive MIMO Systems - Zarei, Shahram; Aulin, Jocelyn; Gerstacker, Wolfgang; Schober, Robert (IEEE Signal Processing Letters, 2017)
We propose a max-min multicell-aware regularized zero-forcing (MCA-RZF) precoding and power allocation scheme for downlink multicell massive multiple-input multiple-output systems. A general correlated channel model is considered, and the adopted channel state information (CSI) acquisition model includes the effects of estimation errors and pilot contamination. We use results from random matrix theory to derive deterministic equivalents for the proposed max-min power allocation in the large system limit, which solely depend on statistical CSI, but not on individual channel realizations. Our numerical results show that the proposed max-min MCA-RZF precoder achieves a substantially higher network-wide minimum rate than the MCA-RZF and the conventional RZF precoders with uniform power allocation, respectively, as well as the conventional RZF precoder with max-min power allocation.<br
Keywords: Resource management; Precoding; MIMO; Interference; Signal to noise ratio; Optimization; Channel estimation

Media Modulation based Molecular Communication - Brand, Lukas; Garkisch, Moritz; Lotter, Sebastian; Schäfer, Maximilian; Burkovski, Andreas; Sticht, Heinrich; Castiglione, Kathrin; Schober, Robert (IEEE Transactions on Communications, 2022)
In conventional molecular communication (MC) systems, the signaling molecules used for information transmission are stored, released, and then replenished by a transmitter (TX). However, the replenishment of signaling molecules at the TX is challenging in practice. Furthermore, in most envisioned MC applications, e.g., in the medical field, it is not desirable to insert the TX into the MC system, as this might impair natural biological processes. In this paper, we propose the concept of media modulation based MC where the TX is placed outside the channel and utilizes signaling molecules already present inside the system. The signaling molecules can assume different states which can be switched by external stimuli. Hence, in media modulation based MC, the TX modulates information into the state of the signaling molecules. In particular, we exploit the group of photochromic molecules, which undergo light-induced reversible state transitions, for media modulation. We study the usage of these molecules for information transmission in a three-dimensional duct system, which contains an eraser, a TX, and a receiver for erasing, writing, and reading of information via external light, respectively. We develop a statistical model for the received signal which accounts for the distribution of the signaling molecules in the system, the initial states of the signaling molecules, the reliability of the state control mechanism, the randomness of irrepressible, spontaneous state switching, and the randomness of molecule propagation. We adopt a maximum likelihood detector and show that it can be reduced to a threshold based detector. Furthermore, we derive analytical expressions for the optimal threshold value and the resulting bit error rate (BER), respectively. Both the statistical model and BER results are verified by computer simulations. Our results reveal that media modulation enables reliable information transmission, validating it as a promising alternative to MC based on molecule emitting TXs.<br

Media Modulation in Molecular Communications - Brand, Lukas; Garkisch, Moritz; Lotter, Sebastian; Schäfer, Maximilian; Castiglione, Kathrin; Schober, Robert (IEEE International Conference on Communications, 2022)
In conventional molecular communication (MC) systems, the signaling molecules used for information transmission are stored, released, and then replenished by a transmitter (TX). However, the replenishment of signaling molecules at the TX is challenging in practice. Furthermore, in most envisioned MC applications, e.g., in the medical field, it is not desirable to insert the TX into the MC system, as this might impair natural biological processes. In this paper, we propose the concept of media modulation based MC where the TX is placed outside the channel and utilizes signaling molecules already existing inside the system. We consider signaling molecules that can be in different states which can be switched by external stimuli. Hence, in media modulation based MC, for information transmission, the TX stimulates the signaling molecules to encode information into their state. In particular, we elaborate media modulation for the group of photochromic molecules, which undergo light-induced reversible transformations, and study the usage of these molecules for information transmission in a three-dimensional duct system. We develop a statistical model for the received signal which depends on the distribution of the signaling molecules in the system, the reliability of the state control mechanism, and the randomness of molecule propagation. Furthermore, we analyze the performance of media modulation based MC in terms of the bit error rate (BER). We show that media modulation enables reliable information transmission, which renders a TX inside the channel unnecessary.
CRIS-Team Scopus Importer:2022-09-16

ME-SSA: An advanced random access for the satellite return channel - Gallinaro, G.; Alagha, N.; De Gaudenzi, R.; Kansanen, K.; Müller, Ralf; Rossi, P. Salvo (IEEE International Conference on Communications, ICC 2015, 2015)
The paper analyzes the performance of an advanced random access scheme for the return channel of a satellite communication link. The scheme is an evolution of the E-SSA scheme proposed in [1], [2] that couples an asynchronous Spread Spectrum Aloha access with Successive Interference Cancellation (SIC) at the central Gateway (GW) receiver to increase the channel throughput. Main feature of the proposed scheme is the exploitation of an approximate linear Minimum Mean Square Error (MMSE) detector in place of the conventional Single User Matched Filter (SUMF) detector used in E-SSA. A gain of 50% in terms of spectral efficiency is achieved over E-SSA in most typical scenarios.
Keywords: CDMA; Multiple Access; Random Access; Satellite Communications; Spread Spectrum; Up Link

Millimeter-Wave Full-Duplex UAV Relay: Joint Positioning, Beamforming, and Power Control - Zhu, Lipeng; Zhang, Jun; Xiao, Zhenyu; Cao, Xianbin; Xia, Xiang Gen; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2020)
In this paper, a full-duplex unmanned aerial vehicle (FD-UAV) relay is employed to increase the communication capacity of millimeter-wave (mmWave) networks. Large antenna arrays are equipped at the source node (SN), destination node (DN), and FD-UAV relay to overcome the high path loss of mmWave channels and to help mitigate the self-interference at the FD-UAV relay. Specifically, we formulate a problem for maximization of the achievable rate from the SN to the DN, where the UAV position, analog beamforming, and power control are jointly optimized. Since the problem is highly non-convex and involves high-dimensional, highly coupled variable vectors, we first obtain the conditional optimal position of the FDUAV relay for maximization of an approximate upper bound on the achievable rate in closed form, under the assumption of a line-of-sight (LoS) environment and ideal beamforming. Then, the UAV is deployed to the position which is closest to the conditional optimal position and yields LoS paths for both air-to-ground links. Subsequently, we propose an alternating interference suppression (AIS) algorithm for the joint design of the beamforming vectors and the power control variables. In each iteration, the beamforming vectors are optimized for maximization of the beamforming gains of the target signals and the successive reduction of the interference, where the optimal power control variables are obtained in closed form. Our simulation results confirm the superiority of the proposed positioning, beamforming, and power control method compared to three benchmark schemes. Furthermore, our results show that the proposed solution closely approaches a performance upper bound for mmWave FD-UAV systems.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Antenna arrays; Array signal processing; beamforming; full-duplex relay; Interference; Millimeter wave communication; mmWave communications; positioning; power control; Power control; Relays; UAV communications; Unmanned aerial vehicles

MIMO channel modeling and the principle of maximum entropy - Debbah, Merouane; Müller, Ralf (IEEE Transactions on Information Theory, 2005)
We devise theoretical grounds for constructing channel models for multiple-input multiple-output (MIMO) systems based on information-theoretic tools. The paper provides a general method to derive a channel model which is consistent with one's state of knowledge. The framework we give here has already been fruitfully explored with success in the context of Bayesian spectrum analysis and parameter estimation. For each channel model, we conduct an asymptotic analysis (in the number of antennas) of the achievable transmission rate using tools from random matrix theory. A central limit theorem is provided on the asymptotic behavior of the mutual information and validated in the finite case by simulations. The results are useful both in terms of designing a system based on criteria such as quality of service and in optimizing transmissions in multiuser networks. © 2005 IEE
Keywords: Antenna arrays; Bayesian probability theory; Channel modeling; Entropy; Multiple-input multiple-output (MIMO); Random matrices

MIMO wiretap channels: Secure transmission using Transmit antenna selection and receive generalized selection combining - Yang, Nan; Yeoh, Phee Lep; Elkashlan, Maged; Schober, Robert; Yuan, Jinhong (IEEE Communications Letters, 2013)
We propose and analyze transmit antenna selection with receive generalized selection combining (TAS/GSC) for physical layer security enhancement in multiple-input multiple-output wiretap channels. In this protocol, a single antenna out of NA antennas is selected at the transmitter and L B antennas out of NB antennas are combined at the legitimate receiver. We characterize the physical layer secrecy of TAS/GSC via our new closed-form expressions for the exact and the asymptotic secrecy outage probability. We demonstrate that the maximum secrecy outage diversity gain of NA NB is achieved. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: generalized selection combining; Multiple-input multiple-output wiretap channel; transmit antenna selection

Minimum BER transmit beamforming for MIMO-OFDM systems with finite rate feedback - Liang, Yang-Wen; Schober, Robert; Gerstacker, Wolfgang (IEEE International Conference on Communications, 2008)
In this paper, we consider minimum bit error rate (BER) beamforming (BF) for multiple-input multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) systems. In particular, assuming perfect channel state information (CSI) at the transmitter we optimize cyclic BF filters (C-BFFs) for minimization of the average BER and the maximum sub-carrier BER, respectively. If the C-BFF length Lg is equal to the number of sub-carriers Nc, closed-form solutions to both optimization problems exist. For the practically relevant case L g < Nc we present numerical methods for calculation of the optimum C-BFFs. For finite-rate feedback channels we provide a global vector quantization (GVQ) scheme for codebook design. Simulation results for typical IEEE 802.11n channels confirm the excellent performance of the proposed minimum BER BF schemes for both uncoded and coded MIMO-OFDM systems. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Minimum bit error probability of large randomly spread MC-CDMA systems in multipath rayleigh fading - Müller, Ralf; et al. (2004 IEEE International Symposium on Spread Spectrum Techniques and Applications, ISSSTA 2004, 2004)
We address bit error probability of the optimum multiuser detector for multi-carrier code-division multiple-access in frequency-selective fading channels. We use the replica method, a tool from statistical physics, to calculate the bit error probability in the large system limit for randomly assigned spreading sequences. The analysis allows for binary input symbols with biased probabilities and, therefore, can be used to analyze iterative multiuser decoders. © 2004 IEEE.

Minimum probability of error and channel capacity in large dual antenna array systems - Müller, Ralf; Weichselberger, Werner (10th International Conference on Telecommunications, ICT 2003, 2003)
Uncoded bit error probability with maximum-likelihood detection and channel capacity is derived analytically for binary signaling on the dual antenna array channel with correlated fading in the large system limit. The example of fading correlation due to poor scattering is analyzed in greater detail. In case of poor scattering (or high load), a waterfall behavior of the uncoded bit error probability is observe
Keywords: Antenna arrays; Channel capacity; Error probability; Fading; Matrix decomposition; Maximum likelihood detection; Receiving antennas; Scattering; Signal analysis; Tail

MISO wireless communication systems via intelligent reflecting surfaces - Yu, Xianghao; Xu, Dongfang; Schober, Robert (2019 IEEE/CIC International Conference on Communications in China, ICCC 2019, 2019)
Intelligent reflecting surfaces (IRSs) have received considerable attention from the wireless communications research community recently. In particular, as low-cost passive devices, IRSs enable the control of the wireless propagation environment, which is not possible in conventional wireless networks. To take full advantage of such IRS-assisted communication systems, both the beamformer at the access point (AP) and the phase shifts at the IRS need to be optimally designed. However, thus far, the optimal design is not well understood. In this paper, a point-to-point IRS-assisted multiple-input single-output (MISO) communication system is investigated. The beamformer at the AP and the IRS phase shifts are jointly optimized to maximize the spectral efficiency. Two efficient algorithms exploiting fixed point iteration and manifold optimization techniques, respectively, are developed for solving the resulting non-convex optimization problem. The proposed algorithms not only achieve a higher spectral efficiency but also lead to a lower computational complexity than the state-of-the-art approach. Simulation results reveal that deploying large-scale IRSs in wireless systems is more efficient than increasing the antenna array size at the AP for enhancing both the spectral and the energy efficiency.
CRIS-Team Scopus Importer:2019-11-05

Mixed RF and Hybrid RF/FSO Relaying - Jamali Kooshkghazi, Vahid; Michalopoulos, Diomidis S.; Uysal, Murat; Schober, Robert (2015 IEEE Globecom Workshops (GC Wkshps), 2015)
In this paper, we consider a mixed RF and hybrid RF/FSO system where several mobile users transmit their data over an RF link to a relay node (e.g. a small cell base station) and the relay forwards the information to a destination (e.g. a macro cell base station) over a hybrid RF/FSO backhaul link. The relay and the destination employ multiple antennas for transmission and reception over the RF links while each mobile user has a single antenna. The RF links are orthogonal with respect to the FSO link and half-duplex with respect to each other, i.e., either the user-relay RF link or the relay-destination RF link is active. For this communication setup, we derive the optimal policy for sharing the RF transmission time between the RF links. Our numerical results show the effectiveness of the proposed communication architecture and link allocation policy, and their superiority compared to existing schemes which employ only one type of backhaul link.<br
Keywords: Radio frequency; Relays; Antennas; Bandwidth; Mobile nodes; Receivers

ML Detection without CSI for Constant-Weight Codes in THz Communications with Strong Phase Noise - Wu, Yifei; Koch, Johannes; Vossiek, Martin; Schober, Robert; Gerstacker, Wolfgang (2022 IEEE Global Communications Conference, GLOBECOM 2022 - Proceedings, 2022)
To meet the ever-increasing requirements of high-rate data transmission, the significant amount of spectrum available in the TeraHertz (THz) band is considered for future wireless communications. However, the performance of THz communications is limited by strong phase noise (PN) introduced by oscillators and the complexity added by channel state information (CSI) acquisition. To overcome such impediments, we propose a new transmission concept based on constant-weight (CW) codes which enable low-complexity maximum-likelihood (ML) sequence detection at the receiver side in the presence of strong PN without requiring statistical or instantaneous CSI knowledge. In addition, the error rate of the ML receiver for the proposed CW codes is analyzed. Simulation results verify the analytical derivations and illustrate that the proposed transmission scheme outperforms transmission with on-off keying modulation and coherent detection.
CRIS-Team Scopus Importer:2023-03-07

MMSE beamforming for SC-FDMA transmission over MIMO ISI channels - Dang, Uyen Ly; Ruder, Michael; Schober, Robert; Gerstacker, Wolfgang (EURASIP Journal on Advances in Signal Processing, 2011)
We consider transmit beamforming for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filters are optimized for minimization of the sum of the mean-squared errors (MSEs) of the transmitted data streams after MIMO minimum mean-squared error linear equalization (MMSE-LE), and for minimization of the product of the MSEs after MIMO MMSE decision-feedback equalization (MMSE-DFE), respectively. We prove that for SC-FDMA transmission in both cases eigenbeamforming, diagonalizing the overall channel, together with a nonuniform power distribution is the optimum beamforming strategy. The optimum power allocation derived for MMSE-LE is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Berger/Tufts and Yang/Roy, whereas for MMSE-DFE the capacity achieving waterfilling strategy well known from conventional single-carrier transmission schemes is obtained. Moreover, we present a modification of the beamformer design to mitigate an increase of the peak-to-average power ratio (PAPR) which is in general associated with beamforming. Simulation results demonstrate the high performance of the proposed beamforming algorithms. Copyright © 2011 Uyen Ly Dang et al.
CRIS-Team Scopus Importer:2020-02-03

MMSE Beamforming for SC-FDMA Transmission over MIMO ISI Channels with Linear Equalization - Dang, Thi Uyen Ly; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2011)
We consider transmit beamforming for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filter is optimized for minimization of the sum of the mean-squared errors (MMSEs) of the transmitted data streams after equalization. Here, MIMO minimum mean-squared error linear equalization (MMSE-LE) is considered. We prove that for SC-FDMA transmission eigen-beamforming diagonalizing the overall channel together with a nonuniform power distribution is the optimum beamforming strategy in the MMSE sense. The derived optimum power allocation is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Berger/Tufts and Yang/Roy. Moreover, we present a modification of the beamformer design to mitigate an increase of the peak-to-average power ratio (PAPR) which is in general associated with beamforming. Simulation results demonstrate the excellent performance of the proposed beamforming algorith

Mobile Network Traffic Forecasting Using Artificial Neural Networks - Kirmaz, Anil; Michalopoulos, DIomidis S.; Balan, Irina; Gerstacker, Wolfgang (Proceedings - IEEE Computer Society's Annual International Symposium on Modeling, Analysis, and Simulation of Computer and Telecommunications Systems, MASCOTS, 2020)
Mobile communication systems need to adapt to temporally and spatially changing mobile network traffic, due to dynamic characteristics of mobile users, in order to provide high quality of service. Since these changes are not purely random, one can extract the deterministic portion and patterns from the observed network traffic to predict the future network traffic status. Such prediction can be utilized for a series of proactive network management procedures including coordinated beam management, beam activation/deactivation and load balancing. To this end, in this paper, an intelligent predictor using artificial neural networks is proposed and compared with a baseline scheme that uses linear prediction. It is shown that the neural network scheme outperforms the baseline scheme for relatively balanced data traffic between highly random and deterministic mobility patterns. For highly random or deterministic mobility patterns, the performance of the two considered schemes is similar to each other.
CRIS-Team Scopus Importer:2021-04-19
Keywords: artificial neural networks; joint beam configuration; mobility prediction; network load balancing; Network traffic forecasting

Modeling and Analysis of Synaptic Communication as Molecular Communication System - Lotter, Sebastian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)

Modeling and Design of IRS-Assisted Multi-Link FSO Systems - Ajam, Hedieh; Najafi, Marzieh; Jamali Kooshkghazi, Vahid; Schmauß, Bernhard; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we investigate the modeling and design of intelligent reflecting surface (IRS)-assisted optical communication systems, which can circumvent the line-of-sight (LOS) requirement in multi-link free space optical (FSO) systems. The FSO laser beams incident on the optical IRSs have a Gaussian power intensity profile and a nonlinear phase profile, whereas the plane waves in radio frequency (RF) systems have a uniform power intensity profile and a linear phase profile. Given these substantial differences, the results available for IRS-assisted RF systems are not applicable to IRS-assisted FSO systems. Therefore, we develop a new analytical channel model for point-to-point IRS-assisted FSO systems based on the Huygens-Fresnel principle. Our analytical model captures the impact of the size, position, and orientation of the IRS as well as its phase shift profile on the end-to-end channel. To allow the sharing of the optical IRS by multiple FSO links, we propose three different protocols, namely the time division (TD), IRS-division (IRSD), and IRS homogenization (IRSH) protocols. The proposed protocols address the specific characteristics of FSO systems including the non-uniformity and possible misalignment of the laser beams. Furthermore, to compare the proposed IRS sharing protocols, we analyze the bit error rate (BER) and the outage probability of IRS-assisted multi-link FSO systems in the presence of inter-link interference. Our simulation results validate the accuracy of the proposed analytical channel model for IRS-assisted FSO systems and confirm that this model is applicable for both large and intermediate IRS-receiver lens distances. Furthermore, we show that for the proposed IRSD and IRSH protocols, inter-link interference becomes negligible if the laser beams are properly centered on the IRS and the transceivers are carefully positioned, respectively. Moreover, in the absence of misalignment errors, the IRSD protocol outperforms the other protocols, whereas in the presence of misalignment errors, the IRSH protocol performs significantly better than the IRSD protocol.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Analytical models

Modeling an Experimental Biological Modulator for Molecular Communications by Electrical Circuits - Schäfer, Maximilian; Wicke, Wayan; Grebenstein, Laura; Strobl, Christian; Stavracakis Peixoto, Renata; Kirchner, Jens; Burkovski, Andreas; Fischer, Georg; Weigel, Robert; Rabenstein, Rudolf; Schober, Robert (4th Workshop on Molecular Communications, 2019)
Experimental systems are necessary to validate and improve theoretical molecular communication models. We propose an analytical model for a biological modulator based on genetically modified Escherichia coli (E. coli) bacteria which convert an electrically-controlled light signal into a chemical response. Techniques from system identification and electrical networks synthesis are used to model the complex biological system. Compared to a simple reference model, a better fit to the observed dynamics in the experimental data is obtaine

Modeling Duct Flow for Molecular Communication - Wicke, Wayan; Schwering, Tobias; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Noel, Adam; Schober, Robert (2018 IEEE Global Communications Conference (GLOBECOM), 2018)
Active transport such as fluid flow is sought in molecular communication to extend coverage, improve reliability, and mitigate interference. Flow models are often over-simplified, assuming one-dimensional diffusion with constant drift. However, diffusion and flow are usually encountered in three-dimensional bounded environments where the flow is highly non-uniform such as in blood vessels or microfluidic channels. For a qualitative understanding of the relevant physical effects inherent to these channels, based on the Peclet number and the transmitter-receiver distance, we study when simplified models of uniform flow and advection-only transport are applicable. For these two regimes, analytical expressions for the channel impulse response are derived and validated by particle-based simulation. Furthermore, as advection-only transport is typically overlooked and hence not analyzed in the molecular communication literature, we evaluate the symbol error rate for exemplary on-off keying as performance metri

Modeling Duct Flow for Molecular Communication - Wicke, Wayan; Schwering, Tobias; Ahmadzadeh, Arman; Jamali, Vahid; Noel, Adam; Schober, Robert (2018 IEEE Global Communications Conference, GLOBECOM 2018 - Proceedings, 2019)
Active transport such as fluid flow is sought in molecular communication to extend coverage, improve reliability, and mitigate interference. Flow models are often over-simplified, assuming one-dimensional diffusion with constant drift. However, diffusion and flow are usually encountered in three-dimensional bounded environments where the flow is highly non-uniform such as in blood vessels or microfluidic channels. For a qualitative understanding of the relevant physical effects inherent to these channels, based on the Péclet number and the transmitter-receiver distance, we study when simplified models of uniform flow and advection-only transport are applicable. For these two regimes, analytical expressions for the channel impulse response are derived and validated by particle-based simulation. Furthermore, as advection-only transport is typically overlooked and hence not analyzed in the molecular communication literature, we evaluate the symbol error rate for exemplary on-off keying as performance metric.
CRIS-Team Scopus Importer:2019-05-02

Molecular Communication in Blood Vessel: A Stochastic Channel Modeling Approach - Schwering, Tobias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)

Molecular communication using magnetic nanoparticles - Wang, Jiaheng; Huang, Yongming; Jin, Shi; Schober, Robert; You, Xiaohu; Zhao, Chunming (IEEE Journal on Selected Areas in Communications, 2018)
As a promising technology for 5G networks, device-to-device (D2D) communication can improve spectrum utilization by sharing the resources of cellular users (CUs). However, this is at the cost of generating interference to the CUs. While most existing works focused on eliminating or suppressing the interference between the D2D links and the CUs, such interference could in fact be beneficial for improving the security of cellular communication. Specifically, D2D links may, in return for reusing cellular resources to achieve high spectral efficiency, act as friendly jammers and help the CUs against malicious wiretapping. To reach this win-win situation, D2D resource management has to be designed from a physical layer security perspective. In this paper, we consider the joint optimization of power allocation and channel assignment of the D2D links and the CUs with the aim to provide security to the CUs and improve the spectral efficiency of the D2D links simultaneously. We focus on the challenging downlink resource sharing problem and investigate both single-channel and multi-channel D2D communications. The resulting resource management design problems turn out to be difficult nonlinear mixed integer problems. Nevertheless, by exploiting the inherent properties of the formulated optimization problems, we are able to analytically characterize the optimal power allocation of the CUs and D2D links, and develop efficient methods for joint optimization of their channel assignments. Simulation results show that the proposed resource management policies outperform several baseline schemes and can indeed achieve the desired twofold objective.<br
Keywords: Device-to-device communication; Resource Management; Copper; Security; Interference; Channel allocation; Downlink

Molecular communication using magnetic nanoparticles - Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (Proceedings of IEEE Wireless Communications and Networking Conference (WCNC), 2018)

Molecular Communication with Magnetic Nano-Particles - Wicke, Wayan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)

Molecular Noise In Synaptic Communication - Lotter, Sebastian; Schäfer, Maximilian; Schober, Robert (IEEE Transactions on Nanobioscience, 2022)
In synaptic molecular communication (MC), the activation of postsynaptic receptors by neurotransmitters (NTs) is governed by a stochastic reaction-diffusion process. This randomness of synaptic MC contributes to the randomness of the electrochemical downstream signal in the postsynaptic cell, called postsynaptic membrane potential (PSP). Since the randomness of the PSP is relevant for neural computation and learning, characterizing the statistics of the PSP is critical. However, the statistical characterization of the synaptic reaction-diffusion process is difficult because the reversible bi-molecular reaction of NTs with receptors renders the system nonlinear. Consequently, there is currently no model available which characterizes the impact of the statistics of postsynaptic receptor activation on the PSP. In this work, we propose a novel statistical model for the synaptic reaction-diffusion process in terms of the chemical master equation (CME). We further propose a novel numerical method which allows to compute the CME efficiently and we use this method to characterize the statistics of the PSP. Finally, we present results from stochastic particle-based computer simulations which validate the proposed models. We show that the biophysical parameters governing synaptic transmission shape the autocovariance of the receptor activation and, ultimately, the statistics of the PSP. Our results suggest that the processing of the synaptic signal by the postsynaptic cell effectively mitigates synaptic noise while the statistical characteristics of the synaptic signal are preserved. The results presented in this paper contribute to a better understanding of the impact of the randomness of synaptic signal transmission on neuronal information processing.
Created from Fastlane, Scopus look-up
Keywords: Adaptation models; Biological system modeling; Computational modeling; Degradation; Ions; Monte Carlo methods; Synapses

Molecule Harvesting Transmitter Model for Molecular Communication Systems - Ahmadzadeh, Arman; Jamali, Vahid; Schober, Robert (IEEE Open Journal of the Communications Society, 2022)
This paper develops mathematical models for molecule harvesting transmitters in diffusive molecular communication (MC) systems. In particular, we consider a communication link consisting of a spherical transmitter nano-machine and a spherical receiver nano-machine suspended in a fluid environment. The transmitter and the receiver exchange information via signaling molecules. The transmitter is equipped with molecule harvesting units on its surface. Signaling molecules which come into contact with the harvesting units may be re-captured by the transmitter. For this system, we derive closed-form expressions for the channel impulse response and harvesting impulse response. Furthermore, we extend the harvesting transmitter model to the case of continuous signaling molecule release. In particular, we derive closed-form expressions for the average received signal at the receiver and the average harvested signal at the transmitter for different temporal release rates namely, constant, linearly increasing, and linearly decreasing release rates. Finally, we validate the accuracy of the derived mathematical expressions via particle-based simulations.
CRIS-Team WoS Importer:2022-03-25

More Efficient CMMs on FPGAs: Instantiated Ternary Adders for Computation Coding - Lehnert, Alexander; Rosenberger, Hans; Müller, Ralf; Reichenbach, Marc (Applied Reconfigurable Computing. Architectures, Tools, and Applications, 2023)
With the ever increasing complexity of modern algorithms, especially Artificial Neural Networks, the acceleration of linear operations becomes highly beneficial. Computation Coding (CC) matrix decomposition methods promise great reductions in operational cost of Constant Matrix Multiplication. Implementations of such decompositions rely on shifts followed by additions only. Recent FPGAs enable efficient addition of three operands by using multiple-output Lookup-Tables (LUTs) and CC decompositions naturally enable fine control over operand counts in each addition. However, synthesis does not always infer these efficient adder structures. To better utilize the resources present on FPGAs, we use primitive instantiation via a Python-based hardware generation framework allowing for fine control over implemented logic. We show, that designs based on instantiated primitive ternary-input adders reduce hardware cost in LUTs by up to 1.8× compared to inferred designs and decompositions based on binary input adders only, but also perform well with regards to pipelining and timing restriction

Most Resource Efficient Matrix Vector Multiplication on FPGAs - Lehnert, Alexander; Holzinger, Philipp; Pfenning, Simon; Müller, Ralf; Reichenbach, Marc (IEEE Access, 2023)
Fast and resource-efficient inference in artificial neural networks (ANNs) is of utmost importance and drives many new developments in the area of new hardware architectures, e.g., by means of systolic arrays or algorithmic optimization such as pruning. In this paper, we present a novel method for lowering the computation effort for ANN inference utilizing ideas from information theory.Weight matrices are sliced into submatrices of logarithmic aspect ratios. These slices are then factorized. This reduces the number of required computations without compromising on fully parallel processing. We create a new hardware architecture for this dedicated purpose. We also provide a tool to map these sliced and factorized matrices efficiently to reconfigurable hardware. By comparing to the state of the art FPGA implementations, we can prove our claim by lowering hardware resources measured in look-up-tables (LUTs) by a factor of three to six. Our method does not rely on any particular property of the weight matrices of the ANN. It works for the general task of multiplying an input vector with a constant matrix and is also suitable for digital signal processing beyond ANNs.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Computational Efficiency; Computer Architecture; Computer architecture; Constant Matrix Multiplication; Encoding; Field programmable gate arrays; Hardware; Matrix decomposition; Neural Networks; Reconfigurable Architectures; Signal processing algorithms; Sparse matrices

Multi‐antenna Energy Beamforming for SWIPT - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Energy‐constrained wireless networks, such as sensor networks, are typically powered by batteries that have limited operation time. This chapter focuses on the downlink case with simultaneous wireless information and power transfer (SWIPT) from the access point (AP) to user terminals (UTs). It considers simplified scenarios with only one or two active UTs in the network. The chapter analyzes the multi‐antenna design for rate‐energy region characterization in a two‐user SWIPT system with separated information decoding (ID) receiver and energy harvesting (EH) receivers, by assuming perfect channel state information (CSI) at the transmitter. It reveals fundamental trade‐offs in designing wireless MIMO systems for maximizing the efficiency of simultaneous information and energy transmission and discusses some extensions of such a SWIPT design to different setups by considering various practical considerations.<br
Keywords: Receivers; Wireless communication; Transmitters; Covariance matrices; Wireless sensor networks; Baseband; Radio frequency

Multi-Cell Massive MIMO Systems With Hardware Impairments: Uplink-Downlink Duality and Downlink Precoding - Zarei, Shahram; Gerstacker, Wolfgang; Aulin, Jocelyn; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
In this paper, we propose a new framework for uplink-downlink duality in multi-cell multi-user multiple-input multiple-output systems suffering from residual hardware impairments (HWIs) at the base stations and the user terminals. We apply the proposed uplink-downlink duality framework to derive a multi-cell interference and HWI aware minimum mean square error (MCHA-MMSE) precoder which also takes channel state information estimation errors into account. We use results from random matrix theory to derive an analytical expression for the downlink power allocation for the proposed MCHA-MMSE precoder in the large system limit, which only depends on the channel's second order statistics. In contrast to the conventional MMSE precoder, the proposed MCHA-MMSE precoder takes inter-cell interference, pilot contamination, and residual HWIs into account and therefore achieves substantially higher sum rates. The proposed MCHA-MMSE precoder exploits statistical channel knowledge, but does not require data exchange between base stations via backhaul links. In order to reduce the computational complexity, the matrix inversion required for the computation of the MCHA-MMSE precoder is approximated by a matrix polynomial leading to a new polynomial-expansion MCHA-MMSE precoder. Using results from the random matrix theory, we derive closed-form expressions for the asymptotically optimal coefficients of the matrix polynomial, which only depend on the channel's second order statistics.<br
Keywords: MIMO; Training; Interference; Resource Management; Signal to noise Ratio; Covariance Matrices; Wireless communication

Multi-dimensional continuous phase modulation in the uplink of massive MIMO - Sedaghat, Mohammad Ali; Müller, Ralf (Euro- pean Signal Processing Conference, 2015)

Multi-objective beamforming for energy-efficient SWIPT systems - Leng, Shiyang; Wing Kwan Ng, Derrick; Zlatanov, Nikola; Schober, Robert (2016 International Conference on Computing, Networking and Communications (ICNC), 2016)
In this paper, we study the resource allocation algorithm design for energy-efficient simultaneous wireless information and power transfer (SWIPT) systems. The considered system comprises a transmitter, an information receiver, and multiple energy harvesting receivers equipped with multiple antennas. We propose a multi-objective optimization framework to study the trade-off between the maximization of the energy efficiency of information transmission and the maximization of wireless power transfer efficiency. The proposed problem formulation takes into account the per antenna circuit power consumption of the transmitter and the imperfect channel state information of the energy harvesting receivers. The adopted non-convex multi-objective optimization problem is transformed into an equivalent rank-constrained semidefinite program (SDP) and optimally solved by SDP relaxation. Numerical results unveil an interesting trade-off between the considered conflicting system design objectives and reveal the benefits of multiple transmit antennas for improving system energy efficiency.<br
Keywords: Receivers; Transmitters; System analysis and design; Resource Management; Energy harvesting; Optimization; Erbium

Multi-objective beamforming for secure communication in systems with wireless information and power transfer - Ng, Derrick Wing Kwan; Xiang, Lin; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2013)
In this paper, we study power allocation for secure communication in a multiuser multiple-input single-output (MIS-O) downlink system with simultaneous wireless information and power transfer. The receivers are able to harvest energy from the radio frequency when they are idle. We propose a multi-objective optimization problem for power allocation algorithm design which incorporates two conflicting system objectives: total transmit power minimization and energy harvesting efficiency maximization. The proposed problem formulation takes into account a quality of service (QoS) requirement for the system secrecy capacity. Our designs advocate the dual use of artificial noise in providing secure communication and facilitating efficient energy harvesting. The multi-objective optimization problem is non-convex and is solved by a semidefinite programming (SDP) relaxation approach which results in an approximate of solution. A sufficient condition for the global optimal solution is revealed and the accuracy of the approximation is examined. To strike a balance between computational complexity and system performance, we propose two suboptimal power allocation schemes. Numerical results not only demonstrate the excellent performance of the proposed suboptimal schemes compared to baseline schemes, but also unveil an interesting trade-off between energy harvesting efficiency and total transmit power. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Multi-Objective Optimization for Active IRS-Assisted Communication Systems - Xu, Dongfang; Yu, Xianghao; Song, Shenghui; Kwan Ng, Derrick Wing; Schober, Robert (2023 IEEE International Mediterranean Conference on Communications and Networking, MeditCom 2023, 2023)
In this paper, we study the resource allocation algorithm design for a multiuser communication system assisted by an active intelligent reflecting surface (IRS). In particular, supported by a power source, each active IRS element can adjust the phase and amplify the magnitude of the incident signal. To realize power-efficient communication, the proposed design incorporates two conflicting yet desirable objectives, i.e., access point (AP) transmit power minimization and active IRS amplification power minimization, via a multi-objective optimization problem (MOOP). In the literature, systematic algorithms that can efficiently tackle such a non-convex MOOP while preserving joint optimality are not available. To this end, we propose a state-of-the-art optimization framework by capitalizing on bilinear transformation, ϵ-constraint, and inner approximation methods. Simulation results not only reveal the power consumption tradeoff between the AP and the active IRS, but also confirm that the proposed scheme is more power-efficient than four baseline schemes.
CRIS-Team Scopus Importer:2023-11-10

Multi-Objective Optimization for Power Efficient Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (Global Communications Conference (GLOBECOM), 2015)
In this paper, we investigate power efficient resource allocation algorithm design for multiuser wireless communication systems employing a full-duplex (FD) radio base station for serving multiple half-duplex (HD) downlink and uplink users simultaneously. We propose a multi-objective optimization framework for achieving two conflicting yet desirable system design objectives, i.e., total downlink transmit power minimization and total uplink transmit power minimization, while guaranteeing the quality-of-service of all users. To this end, the weighted Tchebycheff method is adopted to formulate a multi-objective optimization problem (MOOP). Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming relaxation. Simulation results not only unveil the trade-off between the total downlink and the total uplink transmit power, but also confirm that the proposed FD system provides substantial power savings over traditional HD systems.
Keywords: Downlink; Uplink; Optimization; Resource Management; MIMO; Wireless communication; High definition video

Multi-Objective Optimization for Robust Power Efficient and Secure Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zhu, Jun; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we investigate the power efficient resource allocation algorithm design for secure multiuser wireless communication systems employing a full-duplex (FD) base station (BS) for serving multiple half-duplex (HD) downlink (DL) and uplink (UL) users simultaneously. We propose a multi-objective optimization framework to study two conflicting yet desirable design objectives, i.e., total DL transmit power minimization and total UL transmit power minimization. To this end, the weighed Tchebycheff method is adopted to formulate the resource allocation algorithm design as a multi-objective optimization problem (MOOP). The considered MOOP takes into account the quality-of-service requirements of all legitimate users for guaranteeing secure DL and UL transmission in the presence of potential eavesdroppers. Thereby, secure UL transmission is enabled by the FD BS and would not be possible with an HD BS. The imperfectness of the channel state information of the eavesdropping channels and the inter-user interference channels is incorporated for robust resource allocation algorithm design. Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming relaxation. Simulation results not only unveil the trade-off between the total DL transmit power and the total UL transmit power, but also confirm the robustness of the proposed algorithm against potential eavesdroppers.
Keywords: Full-duplex radio; physical layer security; multi-objective optimization; non-convex optimization

Multi-objective optimization for secure full-duplex wireless communication systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (Full-Duplex Communications for Future Wireless Networks, 2020)
In traditional half-duplex (HD) communication systems, the HD base station (BS) can transmit artificial noise (AN) to jam the eavesdroppers for securing the downlink (DL) communication. However, guaranteeing uplink (UL) transmission is not possible with an HD BS because HD BSs cannot jam the eavesdroppers during UL transmission. In this chapter, we investigate the resource allocation algorithm design for secure multiuser systems employing a full-duplex (FD) BS for serving multiple HD DL and UL users simultaneously. In particular, the FD BS transmits AN to guarantee the concurrent DL and UL communication security. We propose a multi-objective optimization framework to study two conflicting yet desirable design objectives, namely total DL transmit power minimization and total UL transmit power minimization. To this end, the weighted Tchebycheff method is adopted to formulate the resource allocation algorithm design as a multi-objective optimization problem (MOOP). The considered MOOP takes into account the quality-of-service (QoS) requirements of all legitimate users for guaranteeing secure DL and UL transmission in the presence of potential eavesdroppers. Thereby, secure UL transmission is enabled by the FD BS, which would not be possible with an HD BS. Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming (SDP) relaxation. Simulation results not only unveil the trade-off between the total DL transmit power and the total UL transmit power, but also confirm that the proposed secure FD system can guarantee concurrent secure DL and UL transmission and provide substantial power savings over a baseline system.
CRIS-Team Scopus Importer:2020-08-07

Multi-Objective Power Allocation for Energy Efficient Wireless Information and Power Transfer Systems - Leng, Shiyang (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Multiobjective Resource Allocation for Secure Communication in Cognitive Radio Networks With Wireless Information and Power Transfer - Wing Kwan Ng, Derrick; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2015)
In this paper, we study resource allocation for multiuser multiple-input-single-output secondary communication systems with multiple system design objectives. We consider cognitive radio (CR) networks where the secondary receivers are able to harvest energy from the radio frequency when they are idle. The secondary system provides simultaneous wireless power and secure information transfer to the secondary receivers. We propose a multiobjective optimization framework for the design of a Pareto-optimal resource allocation algorithm based on the weighted Tchebycheff approach. In particular, the algorithm design incorporates three important system design objectives: total transmit power minimization, energy harvesting efficiency maximization, and interference-power-leakage-to-transmit-power ratio minimization. The proposed framework takes into account a quality-of-service (QoS) requirement regarding communication secrecy in the secondary system and the imperfection of the channel state information (CSI) of potential eavesdroppers (idle secondary receivers and primary receivers) at the secondary transmitter. The proposed framework includes total harvested power maximization and interference power leakage minimization as special cases. The adopted multiobjective optimization problem is nonconvex and is recast as a convex optimization problem via semidefinite programming (SDP) relaxation. It is shown that the global optimal solution of the original problem can be constructed by exploiting both the primal and the dual optimal solutions of the SDP-relaxed problem. Moreover, two suboptimal resource allocation schemes for the case when the solution of the dual problem is unavailable for constructing the optimal solution are proposed. Numerical results not only demonstrate the close-to-optimal performance of the proposed suboptimal schemes but unveil an interesting tradeoff among the considered conflicting system design objectives as well.<br
Keywords: Receivers; Resource management; Energy harvesting; Interference; Wireless communication; Radio transmitters

Multiple-Access Fading Channel With Wireless Power Transfer and Energy Harvesting - Hadzi-Velkov, Zoran; Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2014)
We consider the achievable average rates of a multiple-access system, which consists of N energy-harvesting users (EHUs) that transmit information over a block fading multiple-access channel (MAC) and a base station (BS) that broadcasts radio frequency (RF) energy to the EHUs for wireless power transfer. The information (over the uplink) and power (over the downlink) can be transmitted either in time division duplex or frequency division duplex. For the case when the EHUs' battery capacities and the number of transmission slots are both infinite, we determine the optimal power allocation for the BS and the optimal rates and power allocations for the EHUs that maximize the achievable rate region of the MAC. The resulting online solution is asymptotically optimal and also applicable for a finite number of transmission slots and finite battery capacities.<br
Keywords: Wireless communication; Fading; Uplink; Downlink; Batteries; Resource management; Energy harvesting

Multiple-antenna techniques for wireless communications - a comprehensive literature survey - Mietzner, Jan; Schober, Robert; Lampe, Lutz; Gerstacker, Wolfgang; Höher, Peter (IEEE Communications Surveys & Tutorials, 2009)
The use of multiple antennas for wireless communication systems has gained overwhelming interest during the last decade - both in academia and industry. Multiple antennas can be utilized in order to accomplish a multiplexing gain, a diversity gain, or an antenna gain, thus enhancing the bit rate, the error performance, or the signal-to-noise-plus-interference ratio of wireless systems, respectively. With an enormous amount of yearly publications, the field of multiple-antenna systems, often called multiple-input multiple-output (MIMO) systems, has evolved rapidly. To date, there are numerous papers on the performance limits of MIMO systems, and an abundance of transmitter and receiver concepts has been proposed. The objective of this literature survey is to provide non-specialists working in the general area of digital communications with a comprehensive overview of this exciting research field. To this end, the last ten years of research efforts are recapitulated, with focus on spatial multiplexing and spatial diversity techniques. In particular, topics such as transmitter and receiver structures, channel coding, MIMO techniques for frequency-selective fading channels, diversity reception and space-time coding techniques, differential and non-coherent schemes, beamforming techniques and closed-loop MIMO techniques, cooperative diversity schemes, as well as practical aspects influencing the performance of multiple-antenna systems are addressed. Although the list of references is certainly not intended to be exhaustive, the publications cited will serve as a good starting point for further readin

Multiple Target Measurements: Bayesian Framework for Moving Object Detection in Mimo Radar - Eisele, Bastian; Bereyhi, Ali; Müller, Ralf (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2023)
Utilizing compressive sensing (CS), one can significantly reduce the number of required antenna elements in MIMO radar systems, while preserving a high spatial resolution. Most CS-based studies focus on individual processing of a single set of measurements collected from an stationary scene. In this paper, we propose a new scheme called multiple target measurements (MTM). This scheme uses the target movement to collect multiple sets of measurements from jointly sparse stationary scenes. Invoking approximate message passing, we develop a Bayesian-like iterative algorithm to recover the sparse scenes jointly. Our analytical and numerical investigations demonstrate that MTM can further reduce the array size required to achieve a desired spatial resolutio
Keywords: Compressive Sensing; MIMO Radar; Approximate Message Passing

Multi-scale stochastic simulation for diffusive molecular communication - Noel, Adam; Cheung, Karen; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
Recently, hybrid models have emerged that combine microscopic and mesoscopic regimes in a single stochastic reaction-diffusion simulation. Microscopic simulations track every individual molecule and are generally more accurate. Mesoscopic simulations partition the environment into subvolumes, track when molecules move between adjacent subvolumes, and are generally more computationally efficient. In this paper, we present the foundation of a multi-scale stochastic simulator from the perspective of molecular communication, for both mesoscopic and hybrid models, where we emphasize simulation accuracy at the receiver and efficiency in regions that are far from the communication link. Our multi-scale models use subvolumes of different sizes, between which we derive the diffusion event transition rate. Simulation results compare the accuracy and efficiency of traditional approaches with that of a regular hybrid method and with those of our proposed multi-scale methods.<br
Keywords: Computational modeling; Microscopy; Silicon; Accuracy; Receivers; Stochastic processes; Nanoscale devices

Multiuser detection for continuous phase CDMA - Müller, Ralf (2011 1st IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, APWC'11, 2011)
This paper studies linear multiuser detection for code-division multiple-access (CDMA) with continuous-time constant envelope and continuous phase. The restriction to continuous phase is found to cause negligible degradation of multiuser efficiency when detected by means of linear multiuser detectors. This holds for both classical linear multiuser detection as well as for multistage detection based on universal weight design. © 2011 IEEE.
Keywords: Multiaccess communication; Signal to noise Ratio; Bandwidth; Interference; Multiuser detection; Detectors; Degradation

Multiuser diversity in channels with limited scatterers - Kansanen, Kimmo; Müller, Ralf (2008 IEEE 19th International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2008, 2008)
Multiuser diversity scheduling is studied in a single cell system with a limited scatterers channel. The scheduler implements the proportional fairness algorithm with infinite time constant, serving at each scheduling instant the user with the maximum short term fading coefficient. The limits of multiuser diversity gains due to the bounded support of the limited scatterers channel are explored by evaluating the average system capacity and the corresponding required transmitted energy per transmitted bit. The bounded support of the limited scatterers channel results in a capacity saturation as user population size grows even though the number of channel scatterers - the channel richness - is assumed to grow proportionally with the number of users. © 2008 IEEE.

Multiuser diversity in delay-limited cellular wideband systems - Müller, Ralf; et al. (IEEE 2006 International Zurich Seminar on Digital Communications, 2006)
We consider the uplink and the downlink of a multiuser wireless system with one base station and K user terminals. Each user is affected by a propagation path loss, fixed in time, and by a slowly time-varying frequency-selective fading channel, modeled as M parallel block-fading channels. We investigate "multiuser diversity", i.e., the gain achieved by a multiuser system over a single-user system. In particular, we compare "delay-limited" systems with "delay-tolerant" systems based on Proportional Fair Scheduling. Our analysis allows us to quantify the loss incurred by a strict delay constraint in a cellular environment, for given M, K and channel statistics. © 2006 IEEE.

Multiuser diversity in delay-limited cellular wideband systems - Müller, Ralf; Caire, Giuseppe; Knopp, Raymond (IEEE ITSOC Information Theory Workshop 2005 on Coding and Complexity, ITW2005, 2005)
We consider the uplink and the downlink of a multiuser wireless system with one base station and K user terminals. We model wideband transmission by considering M parallel subchannels, each of which is affected by fading. The fading processes in each subchannel are slowly time-varying with respect to the coding block length. Hence, in order to maintain given rate requirements for each user and each channel state, power control is used. We study the delay-limited achievable sum rate (throughput) versus the system E /N, under orthogonal and optimal signaling. We show that for both the orthogonal and the optimal schemes, in the limit of large K and finite M, the optimal allocation strategy consists of allocating each user to its best subchannel only. Hence, we are able to quantify the multiuser diversity gain by comparing the case K → ∞ with the single-user delay-limited case. Finally, we show that the limits of optimal signaling can be approached by relatively simple convolutional codes and iterative joint multiuser decoding with appropriate power control. The proposed scheme can be regarded as a practical version of the optimal successive decoding approach, that mitigates the error propagation due to the suboptimality of the user channel codes. © 2005 IEEE.
Keywords: Delay Systems; Wideband; Fading; Power Control; Iterative Decoding; Downlink; Base stations; Power system modeling; Throughput; Diversity methods

Multiuser MISO UAV Communications in Uncertain Environments with No-Fly Zones: Robust Trajectory and Resource Allocation Design - Xu, Dongfang; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2020)
In this paper, we investigate robust resource allocation algorithm design for multiuser downlink multiple-input single-output (MISO) unmanned aerial vehicle (UAV) communication systems, where we account for the various uncertainties that are unavoidable in such systems and, if left unattended, may severely degrade system performance. We jointly optimize the two-dimensional (2-D) trajectory and the transmit beamforming vector of the UAV for minimization of the total power consumption. The algorithm design is formulated as a non-convex optimization problem taking into account the imperfect knowledge of the angle of departure (AoD) caused by UAV jittering, user location uncertainty, wind speed uncertainty, and polygonal no-fly zones (NFZs). Despite the non-convexity of the optimization problem, we solve it optimally by employing monotonic optimization theory and semidefinite programming relaxation which yields the optimal 2-D trajectory and beamforming policy. Since the developed optimal resource allocation algorithm entails a high computational complexity, we also propose a suboptimal iterative low-complexity scheme based on successive convex approximation to strike a balance between optimality and computational complexity. Our simulation results reveal not only the significant power savings enabled by the proposed algorithms compared to two baseline schemes, but also confirm their robustness with respect to UAV jittering, wind speed uncertainty, and user location uncertainty. Moreover, our results unveil that the joint presence of wind speed uncertainty and NFZs has a considerable impact on the UAV trajectory. Nevertheless, by counteracting the wind speed uncertainty with the proposed robust design, we can simultaneously minimize the total UAV power consumption and ensure a secure trajectory that does not trespass any NFZ.
CRIS-Team Scopus Importer:2020-06-02
Keywords: aerodynamic power consumption; disjunctive programming; monotonic optimization; multi-antenna UAV; no-fly zones; Robust trajectory design; UAV communication systems

Multiuser opportunistic scheduling for hard delay constrained systems - Butt, M. Majid; Kansanen, Kimmo; Müller, Ralf (2008 IEEE Sarnoff Symposium, SARNOFF, 2008)
In this work, an opportunistic group scheduling scheme is proposed which schedules a group of users based upon the instantaneous channel conditions. The users empty the buffer partially corresponding to short term fast fading. The task is to provide a maximum hard delay guarantee to each user and minimize the consumption of the overall system energy. The scheme performs well for large networks because all the users perform scheduling independent of each other and no state information is required about the other users for the scheduling task, making the task simpler. The hard delay constraint is proposed as a system parameter to control the maximum delayenergy tradeoff and the results demonstrate the energy efficiency of the scheme for the multiuser environment.
Keywords: Delay Systems; Fading; Scheduling; Delay effects; Jitter; Wireless sensor Networks; Control Systems; Energy Efficiency; Bandwidth; Statistics

Multi-user Scheduling Schemes for Simultaneous Wireless Information and Power Transfer - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (International Conference on Communications (ICC), 2014)
In this paper, the downlink multi-user scheduling problem is studied for a time-slotted system with simultaneous wireless information and power transfer. In particular, in each time slot, a single user is scheduled to receive information, while the remaining users opportunistically harvest the ambient radio frequency (RF) energy. We devise novel scheduling schemes in which the tradeoff between the users' ergodic capacities and their average amount of harvested energy can be controlled. To this end, two fair scheduling schemes used in information-only transfer systems are modified. First, proportionally fair maximum normalized signal-to-noise ratio (N-SNR) scheduling is modified by scheduling the user having the jth ascendingly ordered (rather than the maximum) N-SNR. We refer to this scheme as order-based N-SNR scheduling. Second, conventional equal-throughput (ET) fair scheduling is modified by scheduling the user having the minimum moving average throughput among the set of users whose N-SNR orders fall into a certain set of allowed orders Sa (rather than the set of all users). We refer to this scheme as order-based ET scheduling. The feasibility conditions required for the users to achieve ET with this scheme are also derived. It is shown that the smaller the selection order j for the order-based N-SNR scheme, and the lower the orders in Sa for the order-based ET scheme, the higher the average amount of energy harvested by the users at the expense of a reduction in their ergodic capacities. The performance of the considered scheduling schemes is analyzed for independent and non-identically distributed (i.n.d.) Ricean fading channels, and closed-form results for the special case of i.n.d. Rayleigh fading are provided.

Multiuser Scheduling Schemes for Simultaneous Wireless Information and Power Transfer Over Fading Channels - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
Radio-frequency (RF) energy harvesting presents a viable solution to prolong the lifetime of wireless communication devices. In this paper, we study downlink multiuser scheduling for a time-slotted system with simultaneous wireless information and power transfer. In particular, in each time slot, a single user is scheduled to receive information, whereas the remaining users opportunistically harvest the ambient RF energy. We devise novel online scheduling schemes in which the tradeoff between the users' ergodic rates and their average amount of harvested energy can be controlled. In particular, we modify the well-known maximum signal-to-noise ratio (SNR) and maximum normalized-SNR (N-SNR) schedulers by scheduling the user whose SNR/N-SNR has a certain ascending order (selection order) rather than the maximum one. We refer to these new schemes as order-based SNR/N-SNR scheduling and show that the lower the selection order, the higher the average amount of harvested energy in the system at the expense of a reduced ergodic sum rate. The order-based N-SNR scheduling scheme provides proportional fairness among the users in terms of both the ergodic achievable rate and the average harvested energy. Furthermore, we propose an order-based equal throughput (ET) fair scheduler, which schedules the user having the minimum moving average throughput out of the users whose N-SNR orders fall into a given set of allowed orders. We show that this scheme provides the users with proportionally fair average harvested energy values. In this context, we also derive feasibility conditions for achieving ET with the order-based ET scheduler. Using the theory of order statistics, the average per-user harvested energy and ergodic achievable rate of all proposed scheduling schemes are analyzed and obtained in closed form for independent and nonidentically distributed Rayleigh, Rician, Nakagami-m, and Weibull fading channels. Our closed-form analytical results are corroborated by simulations.
Keywords: Wireless information and power transfer; RF energy harvesting; multi-user scheduling; fairness

NANO-NETWORKING FOR NANO-, MICRO-, MACRO-SCALE APPLICATIONS - Demirkol, Ilker; Mitra, Urbashi; Schober, Robert; Yilmaz, H. Birkan (IEEE Communications Magazine, 2021)
CRIS-Team WoS Importer:2021-06-18

Near-Field Communications: A Tutorial Review - Liu, Yuanwei; Wang, Zhaolin; Xu, Jiaqi; Ouyang, Chongjun; Mu, Xidong; Schober, Robert (IEEE Open Journal of the Communications Society, 2023)
Extremely large-scale antenna arrays, tremendously high frequencies, and new types of antennas are three clear trends in multi-antenna technology for supporting the sixth-generation (6G) networks. To properly account for the new characteristics introduced by these three trends in communication system design, the near-field spherical-wave propagation model needs to be used, which differs from the classical far-field planar-wave one. As such, near-field communication (NFC) will become essential in 6G networks. In this tutorial, we cover three key aspects of NFC. 1) Channel Modelling: We commence by reviewing near-field spherical-wave-based channel models for spatially-discrete (SPD) antennas. Then, uniform spherical wave (USW) and non-uniform spherical wave (NUSW) models are discussed. Subsequently, we introduce a general near-field channel model for SPD antennas and a Green’s function-based channel model for continuous-aperture (CAP) antennas. 2) Beamfocusing and Antenna Architectures: We highlight the properties of near-field beamfocusing and discuss NFC antenna architectures for both SPD and CAP antennas. Moreover, the basic principles of near-field beam training are introduced. 3) Performance Analysis: Finally, we provide a comprehensive performance analysis framework for NFC. For near-field line-of-sight channels, the received signal-to-noise ratio and power-scaling law are derived. For statistical near-field multipath channels, a general analytical framework is proposed, based on which analytical expressions for the outage probability, ergodic channel capacity, and ergodic mutual information are obtained. Finally, for each aspect, topics for future research are discussed.
CRIS-Team Scopus Importer:2023-09-08
Keywords: 6G mobile communication; Antenna architecture; Antenna arrays; Antennas; beamforcusing; channel modelling; Channel models; near-field communications; performance analysis; Transmitting antennas; Tutorials; Wireless networks

Near-Field Hierarchical Beam Management for RIS-Enabled Millimeter Wave Multi-Antenna Systems - Alexandropoulos, George C.; Jamali, Vahid; Schober, Robert; Vincent Poor, H. (Proceedings of the IEEE Sensor Array and Multichannel Signal Processing Workshop, 2022)
In this paper, we present a low overhead beam management approach for near-field millimeter-wave multi-antenna communication systems enabled by Reconfigurable Intelligent Surfaces (RISs). We devise a novel variable-width hierarchical phase-shift codebook suitable for both the near- and far-field of the RIS, and present a fast alignment algorithm for the RIS phase shifts and the transceiver beamformers. Indicative performance evaluation results are shown, verifying the effectiveness of the proposed approach in comparison with various benchmark schemes.
CRIS-Team Scopus Importer:2022-08-12
Keywords: beam management; hierarchical codebook; millimeter wave; near-field regime; Reconfigurable intelligent surfaces

Network coding assisted mobile-to-mobile file transfer - Popova, Larissa; Schmidt, Armin; Gerstacker, Wolfgang; Koch, Wolfgang (2007 Australasian Telecommunication Networks and Applications Conference, 2008)
This paper is a sequel of previous work, in which we have studied the problem of congestions on the typically overloaded downlink channels in UMTS (Universal Mobile Telecommunication System) networks. Our concept is based on the uplink/downlink traffic imbalance in 3G wireless networks and is realized by organizing seamless cooperation between peer-to-peer and cellular networks using a unified radio interface for both systems. The primary goal is to improve the spectral efficiency of cellular networks by enabling direct mobile-to-mobile (m2m) communication on temporarily unused uplink channels for the distribution of a large popular content in a non-real time multicast manner. The aim of this work is to further improve the interaction between cellular and peer-to-peer networks by generalizing the traditional scheduling paradigm. A network coding technique is embedded as a solution to the scheduling problem in the distributed dynamic environment of wireless large-scale networks. We investigate the performance of the system in terms of dependability of information distribution among m2m users. Simulations demonstrate the enhanced performance of the file distribution in terms of file download time. Furthermore, the obtained results highlight that network coding based m2m data transfer allows distribution of popular files to a large number of users while placing minimal bandwidth requirements on the central serve

Network Simulation for Powerline Protocols with Direct Code Execution Applied to DLC (R)-3000 SFN - Deutschmann, Jörg; Lehmann, Andreas; Hampel, Johannes; Huber, Johannes (2014)
The simulation of powerline communication (PLC) networks with larger numbers of nodes and with different channel conditions is essential for the development of the respective protocols, especially regarding medium access and network layer strategies. However, creating realistic models for network simulations is a complex process and demands high resources. Therefore, emulation and testbeds have been a necessary addition for testing and verification. In this paper, we propose a solution that brings both approaches closer together. Via the direct code execution (DCE) framework of the network simulator 3 (ns-3) project, we show how the machine code from real devices can be run within the network simulator, thus making it unnecessary to model the PLC protocol in another instance, namely the simulator. We will show results for the DLC (R)-3000 Single Frequency Network (SFN) PLC protocol and a proof of concept, that the same code performs on real PLC devices as well as within the simulator.

NOMA-Assisted Grant-Free Transmission: How to Design Pre-Configured SNR Levels? - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Wireless Communications Letters, 2024)
The key idea of non-orthogonal multiple access (NOMA) assisted grant-free transmission is to create pre-configured receive signal-to-noise ratio (SNR) levels that can be used to serve users in a way similar to conventional bandwidth resources, such as time slots and subcarriers. In the literature, there exist two different SNR-level designs, and the aim of this letter is to investigate their impact on the performance of grant-free transmission, where age-of-information is adopted as the performance metric as it captures not only failures at the physical layer, such as outages and bit errors, but also errors caused by user collisions. The presented analytical and simulation results illustrate the performance gain achieved by NOMA over orthogonal multiple access, and also reveal the relative merits of the considered designs for pre-configured SNR levels.
CRIS-Team Scopus Importer:2024-02-23
Keywords: age of information (AoI); Grant-free transmission; non-orthogonal multiple access (NOMA)

NOMA Assisted Wireless Caching: Strategies and Performance Analysis - Ding, Zhiguo; Fan, Pingzhi; Karagiannidis, George K.; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Communications, 2018)
Conventional wireless caching assumes that content can be pushed to local caching infrastructure during off-peak hours in an error-free manner; however, this assumption is not applicable if local caches need to be frequently updated via wireless transmission. This paper investigates a new approach to wireless caching for situations in which the cache content has to be updated during on-peak hours. Two non-orthogonal multiple access (NOMA)-assisted caching strategies are developed, namely, the push-then-deliver strategy and the push-and-deliver strategy. In the push-then-deliver strategy, the NOMA principle is applied to push more content files to the content servers during a short time interval reserved for content pushing during on-peak hours and to provide more connectivity for content delivery, compared with the conventional orthogonal multiple access (OMA) strategy. The push-and-deliver strategy is motivated by the fact that some users' requests cannot be accommodated locally and the base station has to serve them directly. These events during the content delivery phase are exploited as opportunities for content pushing, which further facilitates the frequent update of the files cached at the content servers. It is also shown that this strategy can be straightforwardly extended to device-to-device caching, and various analytical results are developed to illustrate the superiority of the proposed caching strategies compared with OMA based schemes.<br
Keywords: NOMA; Servers; Device-to-device communication; Bandwidth; Wireless networks; Electronic mail

NOMA-Based Coexistence of Near-Field and Far-Field Massive MIMO Communications - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Wireless Communications Letters, 2023)
This letter considers a legacy massive multiple-input multiple-output (MIMO) network, in which spatial beams have been preconfigured for near-field users, and proposes to use the non-orthogonal multiple access (NOMA) principle to serve additional far-field users by exploiting the spatial beams preconfigured for the legacy near-field users. Our results reveal that the coexistence between near-field and far-field communications can be effectively supported via NOMA, and that the performance of NOMA-assisted massive MIMO can be efficiently improved by increasing the number of antennas at the base station.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Antenna arrays; Array signal processing; Base stations; beamforming; Multiaccess communication; near-field communications; Noise measurement; NOMA; Non-orthogonal multiple access (NOMA); Resource management

NOMA Meets Finite Resolution Analog Beamforming in Massive MIMO and Millimeter-Wave Networks - Ding, Zhiguo; Dai, Linglong; Schober, Robert; Poor, H. Vincent (IEEE Communications Letters, 2017)
Finite resolution analog beamforming (FRAB) has been recognized as an effective approach to reduce hardware costs in massive multiple-input multiple-output and millimeter-wave networks. However, the use of FRAB means that the beamformers are not perfectly aligned with the users' channels and multiple users may be assigned similar or even identifical beamformers. This letter shows how non-orthogonal multiple access (NOMA) can be used to exploit this feature of FRAB, in which a single FRAB-based beamformer is shared by multiple users. Both analytical and simulation results are provided to demonstrate the excellent performance achieved by this new NOMA transmission scheme.<br
Keywords: NOMA; Array signal processing; MIMO; Diversity Methods; Base stations; Fading channels; Signal to noise ratio

Non-Coherent Detection for Diffusive Molecular Communication Systems - Jamali Kooshkghazi, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea J. (IEEE Transactions on Communications, 2018)
We study non-coherent detection schemes for molecular communication (MC) systems with negligible inter-symbol interference that do not require knowledge of the channel state information (CSI). In particular, we first derive the optimal maximum likelihood (ML) multiple-symbol (MS) detector for MC systems. As a special case of the optimal MS detector, we show that the optimal ML symbol-by-symbol (SS) detector can be equivalently written in the form of a threshold-based detector, where the optimal decision threshold is constant and depends only on the statistics of the MC channel. The main challenge of the MS detector is the complexity associated with the calculation of the optimal detection metric. To overcome this issue, we propose an approximate MS detection metric that can be expressed in closed form. In addition, we develop a non-coherent decision-feedback detector, which introduces a lower detection delay compared with the optimal MS detector, and a suboptimal blind detector, which has a significantly lower complexity than the optimal MS detector. Finally, we derive analytical expressions for the bit error rate (BER) of the optimal SS detector, as well as upper and lower bounds for the BER of the optimal MS detector. Simulation results confirm the analysis and reveal the effectiveness of the proposed optimal and suboptimal detection schemes compared with the benchmark scheme that assumes perfect CSI knowledge, particularly, when the number of observations used for detection is sufficiently large. Simulation results are also presented that show the performance of the proposed detectors, when inter-symbol interference is non-negligible.<br
Keywords: Detectors; Receivers; Transmitters; Channel models; Bit error rate; Interference; Measurement

Non-coherent multiple-symbol detection for diffusive molecular communications - Jamali, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea (Proceedings of the 3rd ACM International Conference on Nanoscale Computing and Communication, ACM NANOCOM 2016, 2016)
Most of the available works on molecular communication (MC) assume that the channel state information (CSI) is perfectly known at the receiver for data detection. In contrast, in this paper, we study non-coherent multiple-symbol detection schemes which do not require knowledge of the CSI. In particular, we derive the optimal maximum likelihood (ML) multiple-symbol (MLMS) detector. Moreover, we propose an approximated detection metric and a suboptimal detector to cope with the high complexity of the optimal MLMS detector. Numerical results reveal the effectiveness of the proposed optimal and suboptimal detection schemes with respect to a baseline scheme which assumes perfect CSI knowledge, particularly when the number of observations used for detection is sufficiently large.
CRIS-Team Scopus Importer:2020-01-31

Nonlinear Equalization Approaches for Physical Layer Network Coding - Schmidt, Armin; Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Wireless Communications, 2016)
We consider a two-way relaying system employing physical layer network coding in channels suffering from frequency-selective fading. We study decision-feedback equalization (DFE), a technique based on delayed decision-feedback sequence estimation (DDFSE), and Tomlinson-Harashima precoding (THP) approaches for mitigating the distortions introduced by the channel. For DFE, we introduce transmit filtering schemes that generate identical overall source-to-relay channel impulse responses for both source nodes, while achieving the maximum signal-to-noise ratio after equalization for the zero-forcing and the minimum mean-squared error criterion, respectively. The advocated DDFSE approach also relies on transmit filtering at the source nodes. For the THP scheme, we derive the optimal precoding filters that guarantee an intersymbol interference free source-to-relay transmission. In order to obtain a two-way relaying system, which uses the same equalization techniques in both transmission directions, we design a THP-based compromise precoding scheme for the relay-to-destination transmission. The performance of the proposed techniques is compared with that of benchmark schemes with simpler filtering/precoding, where identical overall source-to-relay channel impulse responses are enforced by straightforward but suboptimum choices for the transmit filters. Our results reveal that the developed schemes enable significant gains compared with the benchmark schemes.<br
Keywords: Relays; Decision feedback equalizers; Uplink; OFDM; Fading channels; Precoding; Wireless communication

Nonlinear Forwarding Strategy for Firefly Ultra Dense Networks with mmWave Fronthaul Links - Ackermann, Katharina; Jamali Kooshkghazi, Vahid; Gerstacker, Wolfgang; Aulin, Jocelyn; Schober, Robert (IEEE Access, 2021)
We consider the uplink of firefly ultra dense networks which combine the promising features of ultra dense deployment and centralized processing. In these networks, a large number of remote radio units which we denote as firefly nodes (FNs) are spatially distributed over an area. The mobile devices (MDs) in the coverage area are simultaneously connected via sub-6 GHz radio frequency links to all FNs. Unlike the cloud radio access network (C-RAN) architecture, in firefly ultra dense networks, the FNs forward the MDs’ data through multi-hop millimeter-wave (mmWave) links to one or multiple root nodes since the coverage radius of each mmWave link is limited. These root nodes then forward the data via optical fiber links further to a central unit (CU), where the MDs’ signals are decoded. The amount of data that is received at each FN is potentially huge, and hence, efficient signal processing is needed at each FN before the received signals can be forwarded to other FNs. Therefore, we propose a nonlinear processing strategy, which quantizes the received signals at each FN. In particular, we formulate an optimization problem for a local design strategy for the nonlinear forwarding at the FNs, and present an optimal solution by exploiting strong duality and using the Lagrangian method to convert the optimization problem into an unconstrained problem via its dual formulation. A closed-form solution for the primal variables and a bisection algorithm for finding the optimal dual variables are presented. Moreover, based on the cut-set bound, we develop an upper bound on the achievable sum rate of the considered firefly network. The proposed nonlinear forwarding strategy is shown to outperform a benchmark linear forwarding strategy and to approach the performance upper bound in relevant transmit power regimes at the expense of a higher computational complexity. Our results reveal that having more root nodes in the topology improves the performance of linear and nonlinear forwarding but requires additional optical fiber links to the CU.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Cloud radio access network (C-RAN); millimeter wave (mmWave); multi-hop system; nonlinear forwarding; Optical fiber communication; Optical network units; Optimization; Radio frequency; Receiving antennas; Topology; ultra dense network (UDN); Upper bound

Nonlinear Precoders for Massive MIMO Systems with General Constraints - Bereyhi, Ali; Sedaghat, Mohammad Ali; Asaad, Saba; Müller, Ralf (Proceedings of 21st International ITG Workshop on Smart Antennas (WSA), 2017)
We introduce a class of nonlinear least square error precoders with a general penalty function for multiuser massive MIMO systems. The generality of the penalty function allows us to consider several hardware limitations including transmitters with a predefined constellation and restricted number of active antennas. The large-system performance is then investigated via the replica method under the assumption of replica symmetry. It is shown that the least square precoders exhibit the “marginal decoupling property” meaning that the marginal distributions of all precoded symbols converge to a deterministic distribution. As a result, the asymptotic performance of the precoders is described by an equivalent single-user system. To address some applications of the results, we further study the asymptotic performance of the precoders when both the peak-to-average power ratio and number of active transmit antennas are constrained. Our numerical investigations show that for a desired distortion at the receiver side, proposed forms of the least square precoders need to employ around 35% fewer number of active antennas compared to cases with random transmit antenna selectio
Keywords: MIMO precoding; Massive MIMO; Antenna selection; PAPR restriction

Non-orthogonal multiple access: Common myths and critical questions - Vaezi, Mojtaba; Schober, Robert; Ding, Zhiguo; Vincent Poor, H. (IEEE Wireless Communications, 2019)
Non-orthogonal multiple access (NOMA) has received tremendous attention for the design of radio access techniques for fifth generation (5G) wireless networks and beyond. The basic concept behind NOMA is to serve more than one user in the same resource block, for example, a time slot, subcarrier, spreading code, or space. With this, NOMA promotes massive connectivity, lowers latency, improves user fairness and spectral efficiency, and increases reliability compared to orthogonal multiple access (OMA) techniques. While NOMA has gained significant attention from the communications community, it has also been subject to several widespread misunderstandings, such as "NOMA is based on allocating higher power to users with worse channel conditions. As such, cell-edge users receive more power in NOMA and due to this biased power allocation toward celledge users inter-cell interference is more severe in NOMA compared to OMA. NOMA also compromises security for spectral efficiency." The above statements are actually false, and this article aims at identifying such common myths about NOMA and clarifying why they are not true. We also pose critical questions that are important for the effective adoption of NOMA in 5G and beyond and identify promising research directions for NOMA, which will require intense investigation in the future.
CRIS-Team Scopus Importer:2019-11-12

No-Pain No-Gain: DRL Assisted Optimization in Energy-Constrained CR-NOMA Networks - Ding, Zhiguo; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2021)
This paper applies machine learning to optimize the transmission policy of cognitive radio inspired non-orthogonal multiple access (CR-NOMA) networks, where time-division multiple access (TDMA) is used to serve multiple primary users and an energy-constrained secondary user is admitted to the primary users’ time slots via NOMA. During each time slot, the secondary user performs the two tasks: data transmission and energy harvesting based on the signals received from the primary users. The goal of the paper is to maximize the secondary user’s long-term throughput, by optimizing its transmit power and the time-sharing coefficient for its two tasks. The long-term throughput maximization problem is challenging due to the need for making decisions that yield long-term gains but might result in short-term losses. For example, when in a given time slot, a primary user with large channel gains transmits, intuition suggests that the secondary user should not carry out data transmission due to the strong interference from the primary user but perform energy harvesting only, which results in zero data rate for this time slot but yields potential long-term benefits. In this paper, a deep reinforcement learning (DRL) approach is applied to emulate this intuition, where the deep deterministic policy gradient (DDPG) algorithm is employed together with convex optimization. Our simulation results demonstrate that the proposed DRL assisted NOMA transmission scheme can yield significant performance gains over two benchmark schemes.
CRIS-Team Scopus Importer:2021-08-06
Keywords: and energy harvesting; cognitive radio communications; deep reinforcement learning; Non-orthogonal multiple access

Novel protocol with improved outage probability performance for the fading two-hop half-duplex relay channel - Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Wing Kwan Ng, Derrick; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
Based on the coding scheme recently introduced in [1], we propose new communication protocols with improved outage probability performance for the fading two-hop half-duplex (HD) relay channel. This channel is comprised of a source, a HD relay, and a destination, where a direct source-destination link does not exist. For this channel, we assume that the transmitting nodes do not have transmitter-side channel state information and therefore have to transmit with fixed rate. As a result, outages may occur. We propose protocols for the cases when feedback from receiving to transmitting nodes is not possible and restricted to one bit of feedback information per time slot, respectively. In the proposed protocols, the relay's silent symbol intervals, when the relay receives, carry information which improves the reliability of both the source-relay and relay-destination links. In contrast, in existing protocols, the relay's silent symbol intervals, when the relay receives, are a priori known to the destination and thereby cannot carry information. Our numerical results show that the proposed protocols achieve significant performance gains in terms of outage probability compared to existing protocols in the literature. These gains are only the result of using a different coding scheme and not of utilizing more resources than existing protocols.<br
Keywords: Relays; Protocols; High definition Video; Fading channels; Encoding; Time-frequency Analysis; Buffer storage

Novel Radar-based Calibration Techniques for Massive MIMO Arrays - Carlowitz, Christian; Gröschel, Patrick; Schober, Robert; Vossiek, Martin (IMS 2017 Workshop on Massive MIMO and its 5G Related Applications, 2017)

Novel Receiver for Superparamagnetic Iron Oxide Nanoparticles in a Molecular Communication Setting - Bartunik, Max; Lübke, Maximilian; Unterweger, Harald; Alexiou, Christoph; Meyer, Sebastian; Ahmed, Doaa; Fischer, Georg; Wicke, Wayan; Jamali Kooshkghazi, Vahid; Schober, Robert; Kirchner, Jens (Proceedings of the 6th ACM International Conference on Nanoscale Computing and Communication, NANOCOM 2019, 2019)
Superparamagnetic iron oxide nanoparticles (SPIONs) have recently been introduced as information carriers in a testbed for molecular communication (MC) in duct flow. Here, a new receiver for this testbed is presented, based on the concept of a Wheatstone bridge. The capability for a reliable transmission using the testbed and detection of the proposed receiver was evaluated by sending a text message and a 80 bit random sequence at a bit rate of 1/s, which resulted in a bit error rate of 0 %. Furthermore, the sensitivity of the device was assessed by a dilution series, which gave a limit of detectability of peaks between 0:1 to 0:5 mg/mL. Compared to the commercial susceptometer that was previously used as receiver, the new detector provides an increased sampling rate of 100 samples/s and flexibility in the dimensions of the propagation channel. Furthermore, it allows to implement both single-ended and differential signaling in SPION-bases MC testbeds <br
CRIS-Team Scopus Importer:2019-10-29
Keywords: Molecular communication; superparamagnetic iron oxide nanoparticles; SPION; differtial signaling; receiver

OFDM transmission with single antenna interference cancellation - Konrad, Markus; Gerstacker, Wolfgang (2008 IEEE 9th Workshop on Signal Processing Advances in Wireless Communications, 2008)
Future mobile communications radio networks, e.g. 3GPP long term evolution (LTE), will typically use an orthogonal frequency division multiplexing (OFDM) based air interface in the downlink. Furthermore, in order to avoid frequency planning, a frequency reuse factor of one is desirable. In this case, system capacity is limited by interference, which is particularly crucial for mobile terminals with a single receive antenna. For a high throughput, interference cancellation algorithms are required in the receiver. In this paper, a single antenna interference cancellation (SAIC) algorithm is introduced for amplitude-shift keying (ASK) modulation schemes used in coded OFDM transmission which achieves high gains in comparison to a conventional coded OFDM transmission employing quadrature amplitude modulation (QAM) in an interference limited scenario. Furthermore, an adaptive least-mean-square (LMS) and a recursive least-squares (RLS) SAIC receiver, respectively, are presented. We show that in particular the RLS solution enables a good tradeoff between performance and complexity and is robust even to multiple interferers and frequency synchronization error

Olfaction-inspired MCs: Molecule Mixture Shift Keying and Cross-Reactive Receptor Arrays - Jamali, Vahid; Loos, Helene; Büttner, Andrea; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2023)
In this paper, we propose a novel concept for engineered molecular communication (MC) systems inspired by animal olfaction. We focus on a multi-user scenario where several transmitters wish to communicate with a central receiver. We assume that each transmitter employs a unique mixture of different types of signaling molecules to represent its message and the receiver is equipped with an array comprising R different types of receptors in order to detect the emitted molecule mixtures. The design of an MC system based on orthogonal molecule-receptor pairs implies that the hardware complexity of the receiver linearly scales with the number of signaling molecule types Q (i.e., R = Q). Natural olfaction systems avoid such high complexity by employing arrays of cross-reactive receptors, where each type of molecule activates multiple types of receptors and each type of receptor is predominantly activated by multiple types of molecules albeit with different activation strengths. For instance, the human olfactory system is believed to discriminate several thousands of chemicals using only a few hundred receptor types, i.e., Q ≫ R. Motivated by this observation, we first develop an end-to-end MC channel model that accounts for the key properties of olfaction. Subsequently, we present the proposed transmitter and receiver designs. In particular, given a set of signaling molecules, we develop algorithms that allocate molecules to different transmitters and optimize the mixture alphabet for communication. Moreover, we formulate the molecule mixture recovery as a convex compressive sensing problem which can be efficiently solved via available numerical solvers. Finally, we present a comprehensive set of simulation results to evaluate the performance of the proposed MC designs revealing interesting insights regarding the design parameters. For instance, we show that mixtures comprising few types of molecules are best suited for communication since they can be more reliably detected by the cross-reactive array than one type of molecule or mixtures of many molecule types.
CRIS-Team Scopus Importer:2023-03-03
Keywords: compressive sensing; Engineered molecular communication; generalist receptors; molecule mixture modulation; odor; pheromone; transmitter and receiver design

On Adjacent Channel Interference Mitigation for Rotating MIMO Receivers - Zaidel, Benjamin; Müller, Ralf (IEEE Transactions on Wireless Communications, 2015)
Virtually rotating antennas, which rotate once or several times during a symbol interval, have been considered in recent years as a compact (in volume) alternative for achieving additional degrees of freedom compared to standard multiple antenna receivers. Antenna rotation effectively induces bandwidth expansion at the receiver, which in turn increases the effective dimensionality, and may potentially allow for spatial multiplexing. However, in a licensed spectrum such bandwidth expansion also introduces interference from signals transmitted in adjacent frequency bands. This paper investigates to what extent such adjacent channel interference can be mitigated by appropriate signal processing. The potentially achievable throughput of systems employing multiple virtually rotating antennas is examined analytically in a multiuser setting, while considering the large system limit, and employing random matrix theory tools. The analysis focuses on the linear minimum mean-square error (MMSE) receiver, and a receiver that optimally decodes the transmissions of desired users, while being unaware of the codebooks of interferers. The achievable throughput is compared to the corresponding throughputs of standard multiple antenna receivers employing the same number of physical active antenna elements. Conditions for virtually rotating antennas to be beneficial are identified, which when met are shown to lead to significant performance enhancement over standard multiple antenna receivers.
Keywords: Rotating antennas; multiuser receivers; interference mitigation; multiple-input multiple-output; random matrix theory

On an achievable rate of large rayleigh block-fading MIMO channels with no CSI - Takeuchi, Keigo; Müller, Ralf; Vehkapera, Mikko; Tanaka, Toshiyuki (IEEE Transactions on Information Theory, 2013)
Training-based transmission over Rayleigh block-fading multiple-input multiple-output (MIMO) channels is investigated. As a training method a combination of a pilot-assisted scheme and a biased signaling scheme is considered. The achievable rates of successive decoding (SD) receivers based on the linear minimum mean-squared error (LMMSE) channel estimation are analyzed in the large-system limit, by using the replica method under the assumption of replica symmetry. It is shown that negligible pilot information is best in terms of the achievable rates of the SD receivers in the large-system limit. The obtained analytical formulas of the achievable rates can improve the existing lower bound on the capacity of the MIMO channel with no channel state information (CSI), derived by Hassibi and Hochwald, for all SNRs. The comparison between the obtained bound and a high-SNR approximation of the channel capacity, derived by Zheng and Tse, implies that the high-SNR approximation is unreliable unless quite high SNR is considered. Energy efficiency in the low-SNR regime is also investigated in terms of the power per information bit required for reliable communication. The required minimum power is shown to be achieved at a positive rate for the SD receiver with no CSI, whereas it is achieved in the zero-rate limit for the case of perfect CSI available at the receiver. Moreover, numerical simulations imply that the presented large-system analysis can provide a good approximation for not so large systems. The results in this paper imply that SD schemes can provide a significant performance gain in the low-to-moderate SNR regimes, compared to conventional receivers based on one-shot channel estimation. © 1963-2012 IEEE.
Keywords: Biased signaling; large-system analysis; linear minimum mean-squared error (LMMSE) channel estimation; multiple-input multiple-output (MIMO) systems; noncoherent capacity; Rayleigh block-fading channels; replica method; successive decoding (SD); training-based transmission

On Approximation, Bounding & Exact Calculation of Average Block Error Probability for Random Code Ensembles - Müller, Ralf (IEEE Transactions on Communications, 2021)
This paper presents a method to calculate the exact average block error probability of some random code ensembles under maximum-likelihood decoding. The proposed method is applicable to various channels and ensembles. The focus is on both spherical and Gaussian random codes on the additive white Gaussian noise channel as well as binary random codes on both the binary symmetric channel and the binary erasure channel. While for the uniform spherical ensemble Shannon, in 1959, argued with solid angles in N-dimensional space, the presented approach projects the problem into two dimensions and applies standard trigonometry. This simplifies the derivation and also allows for the analysis of the independent identically distributed (i.i.d.) Gaussian ensemble which turns out to perform better for short blocklengths and high rates. Moreover, a new lower bound on the average block error probability of the uniform spherical ensemble is found. For codes with more than three codewords, it is tighter than the sphere packing bound, but requires exactly the same computing effort. Furthermore, tight approximations are proposed to simplify the computation of both the exact average error probability and the two bounds. For the binary symmetric channel and the binary erasure channel, bounds on the average block error probability for i.i.d. random coding are derived and compared to the exact calculations.
CRIS-Team Scopus Importer:2021-04-09
Keywords: AWGN; AWGN channels; binary symmetric channel; block error probability; Channel coding; Error probability; finite blocklength; low-latency communications; Maximum likelihood decoding; maximum-likelihood decoding; Measurement; random coding; sphere packing; Standards; Tools

On Approximation, Bounding Exact Calculation of Block Error Probability for Random Codes - Müller, Ralf (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
This paper presents a method to calculate the exact average block error probability of some random code ensembles under maximum-likelihood decoding. Deviating from Shannon's 1959 solid angle argument, we project the problem into two dimensions and apply standard trigonometry. This enables us to also analyze Gaussian random codes in additive white Gaussian noise and binary random codes for the binary symmetric channel. We find that the Voronoi regions harden doubly-exponential in the blocklength and utilize that to propose the new median bound that outperforms Shannon's 1959 sphere packing bound for the uniform spherical ensemble, whenever the code contains more than three codewords. Furthermore, we propose a very tight approximation to simplify computation of both exact error probability and the two bounds.
CRIS-Team Scopus Importer:2021-04-19

On Capacity of Active Relaying in Magnetic Induction based Wireless Underground Sensor Networks - Kisseleff, Steven; Sackenreuter, Benjamin; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE International Conference on Communications (ICC), 2015)

On channel capacity of communication via antenna arrays with receiver noise matching - Müller, Ralf; Godana, Bruhtesfa E.; Sedaghat, Mohammad A.; Huber, Johannes (2012 IEEE Information Theory Workshop, ITW 2012, 2012)
We consider the total capacity of a Gaussian multiple-access MIMO channel with a linear array of R receive antennas and T distributed transmit antennas. If the spatial distribution of transmit antennas weighed by their path loss and marginalized to a sphere around the receive array is proportional to the ratio of receive antenna directivity to transmit antenna directivity, the capacity is shown to approach Rlog(1 + SNR) as T → ∞, irrespective of the inter-element distance at the receiver.We further show that the capacity for other distributions of transmit antennas can be even greater, as the inter-element distance approaches zero. © 2012 IEEE.
Keywords: antenna arrays; canonical minimum scattering antenna; channel capacity; channel modeling; Gaussian channel; Hertzian dipole; isotropic antennas; multiple-input multiple output; noise matching

On channel estimators for iterative CDMA multiuser receivers in flat Rayleigh fading - Müller, Ralf; et al. (2004 IEEE International Conference on Communications, 2004)
In this work we compare channel estimation algorithms for use in an iterative CDMA receiver in a block fading environment. The receiver consists of a soft multiuser data estimator, a bank of single user decoders, and a multiuser channel estimator. The multiuser data estimator is implemented as parallel interference canceler with unconditional post-MMSE filtering (PIC-MMSE) and the decoder is a soft-in soft-out MAP decoder. In the channel estimator we make use of dedicated pilot symbols and fed back soft-code symbols which are exploited as additional soft pilot symbols when the iterations proceed. We show that using extrinsic information increases the receiver performance significantly compared to using a posteriori information in the feedback for channel estimation. We introduce a linear MMSE (LMMSE) estimator which takes into account the variances of fed back code symbols and compare it to approximations of the least-squares (ALS) estimator and the linear minimum-mean-square-error (ALMMSE) estimator. Performance results are illustrated in terms of bit error rate (BER) and average normalized square error (ANSE) of the channel estimators. They show that the newly proposed LMMSE algorithm outperforms the ALS and ALMMSE algorithms.

On convex vector precoding for multiuser MIMO broadcast channels - De Miguel, Rodrigo; Müller, Ralf (IEEE Transactions on Signal Processing, 2009)
We propose different convex alphabet relaxation schemes for vector precoding in MIMO broadcast channels using binary, quaternary and octonary modulation. Expressions are presented for the probability of the different precoding schemes to achieve interference-free communication over singular channels. The energy of transmission is evaluated in the many user limit using the replica method from statistical physics. An alternative channel inversion technique is proposed which makes purely real binary alphabets perform as well as their complex extensions, resulting in reduced complexity in the optimization process. The relevance of the asymptotic analysis is confirmed by finite size simulations. © 2009 IEEE.
Keywords: Asymptotic analysis; Channel inversion; Multiple antennas; Multiple-input multiple-output (MIMO) systems; Nonlinear vector precoding; R-transform; Random matrices; Replica method; Singular channels; Zero-forcing

Online resource allocation for energy harvesting downlink MIMO systems with finite-alphabet inputs - Zeng, Weiliang; Zheng, Yahong Rosa; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
This paper proposes an online resource allocation algorithm for weighted sum rate maximization in energy harvesting downlink multiuser multiple-input multiple-output (MIMO) systems. Taking into account the discrete nature of the modulation and coding rates (MCRs) used in practice, we formulate a stochastic dynamic programming (SDP) problem to jointly design the MIMO precoders, select the MCRs, assign the subchannels, and optimize the energy consumption over multiple time slots with causal and statistical energy arrival information and statistical channel state information. Solving this high-dimensional SDP entails several difficulties: the SDP has a nonconcave objective function, the optimization variables are of mixed binary and continuous types, and the number of optimization variables is on the order of thousands. We propose a new method to solve this NP-hard SDP by decomposing the high-dimensional SDP into an equivalent three-layer optimization problem and show that efficient algorithms can be used to solve each layer separately. The decomposition reduces the computational burden and breaks the curse of dimensionality.<br
Keywords: MIMO; Energy consumption; Transmitters; Optimization; Wireless communication; Downlink; Joints

Online Resource Allocation for Energy Harvesting Downlink Multiuser Systems: Precoding With Modulation, Coding Rate, and Subchannel Selection - Zeng, Weiliang; Zheng, Yahong Rosa; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
This paper proposes an online resource allocation algorithm for weighted sum rate maximization in energy harvesting downlink multiuser multiple-input-multiple-output (MIMO) systems, where the base station transmitter is powered by both a regular energy source and an energy buffer that is connected to an energy harvester. Taking into account the discrete nature of the modulation and coding rates (MCRs) used in practice, we formulate a stochastic dynamic programming (SDP) problem to jointly design the MIMO precoders, select the MCRs, assign the subchannels, and optimize the energy consumption over multiple time slots with causal and statistical energy arrival information and statistical channel state information. Solving this high-dimensional SDP entails several difficulties: the SDP has a nonconcave objective function, the optimization variables are of mixed binary and continuous types, and the number of optimization variables is on the order of thousands. We propose a new method to solve this NP-hard SDP by decomposing the high-dimensional SDP into an equivalent three-layer optimization problem and develop efficient algorithms to solve each layer separately. The decomposition reduces the computational burden and breaks the curse of dimensionality successfully. We analyze the complexity of the proposed algorithm and demonstrate the performance gains based on numerical examples.<br
Keywords: MIMO; Resource management; Energy consumption; Wireless communication; Transmitters; Joints; Optimization

On Modulation for Magnetic Induction based Transmission in Wireless Underground Sensor Networks - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE International Conference on Communications (ICC), 2014)

On near-far gain in multiuser diversity systems - Kansanen, Kimmo; Müller, Ralf (6th Intl. Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks, Wiopt 2008, 2008)
Multiuser diversity scheduling in a single-cell system is studied. The scheduler chooses a constant size subset of users with best short term fading gains and coordinates transmissions using superposition coding. Rate allocation is performed according to users' channel states assuming equal power allocation over users. Asymptotic analysis of system capacity is applied to study system behavior at low and high spectral efficiencies. It is found that if users have non-symmetric channel distributions, i.e. path loss is present, with large enough user population it becomes beneficial in the sum rate sense to schedule more than one user at a time.
Keywords: Optimal scheduling; Fading; Random variables; Statistical distributions; Wireless communication; Propagation losses; Throughput; Power Control; Statistics; Measurement

On-Off Transmission Policy for Wireless Powered Communication with Energy Storage - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (2014)
In this paper, we consider an energy harvesting (EH) node which harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We consider a simple transmission policy, which accounts for the fact that, in practice, the EH node may not have knowledge of the EH profile nor of the UL channel state information. In particular, in each time slot, the EH node transmits with either a constant desired power or remains silent if not enough energy is available in its energy buffer. For this simple policy, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite-and infinitesize energy buffers. Moreover, we take into account imperfections of the energy buffer and the circuit power consumption of the EH node. For a Rayleigh fading DL channel, we provide the limiting distribution of the energy buffer content in closed form. In addition, we analyze the average error rate and the outage probability of a Rayleigh faded UL channel and show that the diversity order is not affected by the finite capacity of the energy buffer. Our results reveal that, for medium to high signal-to-noise ratio (SNRs), the optimal target transmit power of the EH node is less than the average harvested power and increases with the capacity of the energy buffer.
Keywords: data communication; energy harvesting; energy storage; Markov processes; probability; radio networks; Rayleigh channels; telecommunication network reliability; telecommunication power management; on-off transmission policy; wireless powered communication; energy storage; energy harvesting; EH; radio frequency signal; RF signal; access point; AP; downlink; data transmission; uplink; UL channel state information; discrete-time continuous-state Markov chain; circuit power consumption; Rayleigh fading DL channel; energy buffer distribution; average error rate; outage probability; Rayleigh fading UL channel; signal-to-noise ratio; SNR; Limiting; Buffer storage; Energy storage; Rayleigh channels; Probability density function; Approximation methods

On-off transmission policy for wireless powered communication with energy storage - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2015)
In this paper, we consider an energy harvesting (EH) node which harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We consider a simple transmission policy, which accounts for the fact that, in practice, the EH node may not have knowledge of the EH profile nor of the UL channel state information. In particular, in each time slot, the EH node transmits with either a constant desired power or remains silent if not enough energy is available in its energy buffer. For this simple policy, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite- and infinite-size energy buffers. Moreover, we take into account imperfections of the energy buffer and the circuit power consumption of the EH node. For a Rayleigh fading DL channel, we provide the limiting distribution of the energy buffer content in closed form. In addition, we analyze the average error rate and the outage probability of a Rayleigh faded UL channel and show that the diversity order is not affected by the finite capacity of the energy buffer. Our results reveal that, for medium to high signal-to-noise ratio (SNRs), the optimal target transmit power of the EH node is less than the average harvested power and increases with the capacity of the energy buffer.
CRIS-Team Scopus Importer:2020-01-31

On Optimum Asymptotic Multiuser Efficiency of Randomly Spread CDMA - Sedaghat, Mohammad A.; Müller, Ralf; Marvasti, Farokh (IEEE Transactions on Information Theory, 2015)
We extend the result by Tse and Verdu on the optimum asymptotic multiuser efficiency of randomly spread code division multiple access (CDMA) with binary phase shift keying input. Random Gaussian and random binary antipodal spreading are considered. We obtain the optimum asymptotic multiuser efficiency of a K-user system with spreading gain N when K and N -> infinity and the loading factor, (K/N), grows logarithmically with K under some conditions. It is shown that the optimum detector in a Gaussian randomly spread CDMA system has a performance close to the single user system at high signal-to-noise ratio when K and N. 8 and the loading factor, (K/N), is kept less than (log(3) K/2). Random binary antipodal matrices are also studied and a lower bound for the optimum asymptotic multiuser efficiency is obtained. Furthermore, we investigate the connection between detecting matrices in the coin weighing problem and optimum asymptotic multiuser efficiency. We obtain a condition such that for any binary input, an N x K random matrix, whose entries are chosen randomly from a finite set, is a detecting matrix as K and N -> infinity.
Keywords: Code division multiple access (CDMA); random spreading; multiuser detection; optimum asymptotic multiuser efficiency; detecting matrices; compressive sensing

On overloaded vector precoding for single-user MIMO channels - De Miguel, Rodrigo; Gardasevic, Vesna; Müller, Ralf; Knudsen, Finn F. (IEEE Transactions on Wireless Communications, 2010)
We address the possibility of overloaded vector precoding in single user MIMO channels, i.e. the number of data streams is larger than the minimum of the number of antennas at transmitter and receiver side.We find that the convex vector precoding introduced in [1] allows for overloading while, with a certain probability, keeping the received signal free of interference. We find that the probability that overloading is not possible decays exponentially with the size of the system as long as the number of data streams is less than twice the minimum number of antennas. We give an explicit formula to calculate this probability for any antenna configuration in presence of correlated Rayleigh fading. Although overloading comes with the need for increased transmitted power, we show by means of the replica method that overloading up to 22% yields better spectral and power efficiency than without overload and spatial matched filter processing at the receiver. © 2010 IEEE.
Keywords: Asymptotic analysis; Channel inversion; MIMO; Nonlinear vector precoding; Replica method; Singular channels; Zero-forcing

On PLC Channel Emulation via Transmission Line Theory - Gruber, Florian; Lampe, Lutz (Proceedings of 2015 IEEE International Symposium on Power Line Communications and Its Applications (ISPLC), 2015)
The emulation of power line communication (PLC) channels is an important tool for the analysis and development of PLC systems. Especially for the study of PLC networks, the so-called bottom-up channel emulation using transmission-line theory (TLT) is the proper method. The underlying assumption of this approach is that the power line propagation characteristics are known. That is, the per-unit length (PUL) parameters of the power lines need to be computed. However, especially for multi-conductor lines this can be theoretically and computationally challenging. In this paper, we present a compact overview of the computation of PUL parameters. We briefly discuss the assumptions associated with different solution methods and develop a numerical solver applicable to general multi-conductor transmission lines. Considering a sample set of different cable types, we demonstrate the effects of simplifying assumptions on the accuracy of computed PUL parameters and channel frequency response
Keywords: carrier transmission on power lines; electromagnetic wave propagation; frequency response; multiconductor transmission lines; telecommunication channels; transmission line theory; PLC channel emulation; power line communication channel emulation; transmission line theory; PLC networks; TLT; bottom-up channel emulation; power line propagation characteristics; per-unit length parameter computation; general multiconductor transmission lines; numerical solver; channel frequency response computation; Conductors; Cable shielding; Cable insulation; Capacitance; Permittivity; Closed-form solutions

On Prefilter Computation for Reduced-State Equalization - Gerstacker, Wolfgang; Obernosterer, Frank; Meyer, Raimund; Huber, Johannes (IEEE Transactions on Wireless Communications, 2002)
In advanced time-division multiple-access (TDMA) mobile communications systems, reduced-state equalization algorithms have to be employed because high-level modulation is used in order to improve spectral efficiency. Reduced-state equalizers yield only high performance, if the overall discrete-time system to be equalized is minimum-phase. Therefore, in general, a discrete-time prefllter has to be inserted in front of equalization. For prefllter computation, several approaches are investigated in this paper. For the finite impulse response (FIR) prefilter case, which seems to be more relevant for practical applications than the infinite impulse response case, we discuss a method based on minimum mean-squared error decision-feedback equalization and a novel approach based on linear prediction (LP). The LP method seems to be very robust and requires an only moderate amount of computational complexity. Here, the prefilter consists of the cascade of a channel-matched filter and a prediction-error filter, which may be viewed as a finite-length approximation to the noise whitening part of the ideal prefilter transfer function. A key observation of the paper is that the proposed cascaded structure enables a very efficient prefilter computation because a prediction-error filter can be calculated via the Levinson-Durbin algorithm. Simulation results are given, which demonstrate that the performance of reduced-state equalization with proper FIR prefiltering is close to that of equalization combined with ideal all-pass prefiltering. Furthermore, it is shown that high performance can be obtained for TDMA mobile communications systems, if the LP scheme is employed for prefiltering. © 2002 IEEE.
UnivIS-Import:2015-03-09:Pub.2002.tech.IE.mobilk.onpref
Keywords: EDGE; Minimum-phase systems; Preflltering; Reduced-state equalization; Time-division multiple-access mobile communications

On Prefiltering for Reduced-State Equalization of MIMO Channels - Gerstacker, Wolfgang; Taylor, Desmond (Conference Proceedings, 2004)
In this paper, we consider prefiltering for reduced-state equalization of frequency-selective multiple-input multiple-output (MIMO) channels. We introduce the minimum- and maximum-phase equivalent MIMO system transfer functions, respectively, and show their relation to zero-forcing decision-feedback equalization (ZF-DFE). Furthermore, energy concentration properties of the minimum- and maximum-phase equivalent are established which are generalizations of their well-known SISO counterparts and suggest to insert a MIMO prefilter in front of any trellis-based reduced-state equalization algorithm. Finally, a MIMO prefilter computation algorithm with lower complexity than state-of-the-art schemes is given.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.onpref

On random CDMA with constant envelope - Müller, Ralf (2011 IEEE International Symposium on Information Theory Proceedings, ISIT 2011, 2011)
This paper studies the design of random code-division multiple-access (CDMA) with continuous-time constant envelope. The proposed scheme is compatible with linear CDMA and allows for standard methods of linear multiuser detection while avoiding phase jumps at all times. The proposed algorithm finds a set of spreading waveforms with approximately rectangular power spectral density and stop-band attenuation of more than 60 dB at exactly constant envelope. Alternatively, the algorithm can provide perfect stop-band attenuation at a peak-to-average power ratio of 0.04 dB at spreading factor 512. © 2011 IEEE.

On replica symmetry breaking in vector precoding for the Gaussian MIMO broadcast channel - Zaidel, Benjamin M.; Müller, Ralf; De Miguel, Rodrigo; Moustakas, Aris L. (46th Annual Allerton Conference on Communication, Control, and Computing, 2008)
The so-called "replica method" of statistical physics is employed for the large system analysis of vector precoding for the Gaussian multiple-input multiple-output (MIMO) broadcast channel. Focusing on discrete complex input alphabets, the transmitter is assumed to comprise a linear front-end combined with nonlinear precoding, that minimizes the front-end imposed transmit energy penalty. The energy penalty is minimized by relaxing the input alphabet to a larger alphabet set prior to precoding. The limiting empirical distribution of the precoder's output, as well as the limiting energy penalty, are derived while harnessing what is referred to as the first order replica symmetry breaking (1RSB) ansatz. Particularizing to a "zero-forcing" (ZF) linear front-end, and non-cooperative users, a decoupling result is derived according to which the channel observed by each of the individual receivers can be effectively characterized by the Markov chain u-x-y, where u is the channel input, × is the equivalent precoder output, and y is the channel output. An illustrative example is considered, based on discrete-lattice alphabet relaxation, for which the impact of replica symmetry breaking is demonstrated. A comparative spectral efficiency analysis reveals significant performance gains compared to linear ZF precoding in the medium to high E/N region. The performance vs. Complexity tradeoff of the nonlinear precoding scheme is also shortly discussed. © 2008 IEEE.

On Robustness of Massive MIMO Systems Against Passive Eavesdropping under Antenna Selection - Bereyhi, Ali; Asaad, Saba; Müller, Ralf; Schaefer, Rafael F.; Rabiei, Amir Masoud (IEEE Global Communications Conference (GLOBECOM), 2018)
In massive MIMO wiretap settings, the base station can significantly suppress eavesdroppers by narrow beamforming toward legitimate terminals. Numerical investigations show that by this approach, secrecy is obtained at no significant cost. We call this property of massive MIMO systems `secrecy for free' and show that it not only holds when all the transmit antennas at the base station are employed, but also when only a single antenna is set active. Using linear precoding, the information leakage to the eavesdroppers can be sufficiently diminished, when the total number of available transmit antennas at the base station grows large, even when only a fixed number of them are selected. This result indicates that passive eavesdropping has no significant impact on massive MIMO systems, regardless of the number of active transmit antennas.

On spectral efficiency of vector precoding for Gaussian MIMO broadcast channels - Zaidel, Benjamin; Müller, Ralf; De Miguel, Rodrigo; Moustakas, Aris L. (2008 IEEE 10th International Symposium on Spread Spectrum Techniques and Applications, ISSSTA2008, 2008)
The spectral efficiency of practically oriented vector precoding schemes for the Gaussian multiple-input multiple-output (MIMO) broadcast channel is analyzed in the large system limit. Considering discrete complex input alphabets, the transmitter is assumed to comprise a linear front-end combined with nonlinear precoding, that minimizes the transmit energy penalty imposed by the linear front-end. The energy penalty is minimized by relaxing the input alphabet to a larger alphabet set prior to precoding. The so-called "replica method" of statistical physics is employed to derive the limiting empirical distribution of the precoder's output, as well as the limiting energy penalty. Particularizing to a "zero-forcing" (ZFJ linear front-end, and non- cooperative users, a decoupling result is derived according to which the channel observed by each of the individual receivers can be characterized by the Markov chain u-x-y, where u is the channel input, x is the equivalent precoder output, and y is the channel output. A comparative spectral efficiency analysis of two illustrative examples reveals significant performance gains compared to linear ZF precoding in the medium to high E /N region. In particular, we demonstrate that convex extended alphabets, amenable to efficient energy minimization algorithms, provide an attractive alternative to alphabets based on the discrete Gaussian integer lattice, for which the energy minimization problem is NP-hard. © 2008 IEEE.
Keywords: MIMO; Limiting; Transmitters; Vectors; Receivers; Physics; Signal to noise ratio

On the Application of NOMA to Wireless Caching - Ding, Zhiguo; Fan, Pingzhi; Karagiannidis, George K.; Schober, Robert; Poor, H. Vincent (2018 IEEE International Conference on Communications (ICC), 2018)
This paper investigates the impact of non-orthogonal multiple access (NOMA) on wireless caching. Two NOMA caching strategies are developed, namely the push-then- deliver strategy and the push-and-deliver strategy, with the objective to improve the spectral efficiency of the two caching phases, content pushing and content delivery, compared to the conventional orthogonal multiple-access (OMA) based strategy. Both analytical and computer simulation results are provided to demonstrate the performance of the proposed caching strategies and verify the accuracy of the developed analytical results.<br
Keywords: NOMA; Servers; Wireless communication; Resource management; Reliability; Power system reliability; Probability

On the asymptotic eigenvalue distribution of concatenated vector-valued fading channels - Müller, Ralf (2001 IEEE International Symposium on Information Theory (ISIT 2001), 2001)
The linear vector-valued channel x → Π Mx+z is analyzed in the asymptotic regime as the dimensions of the matrices and vectors involved become large. The eigenvalue distribution of the channel's covariance matrix is given in terms of its Stieltjes transform. The channel gets more and more ill-conditioned the more factors appear in the product.

On the asymptotic eigenvalue distribution of concatenated vector-valued fading channels - Müller, Ralf (IEEE Transactions on Information Theory, 2002)
The linear vector-valued channel x → ∏ M x + z with z and M denoting additive white Gaussian noise and independent random matrices, respectively, is analyzed in the asymptotic regime as the dimensions of the matrices and vectors involved become large. The asymptotic eigenvalue distribution of the channel's covarianee matrix is given in terms of an implicit equation for its Stieltjes transform as well as an explicit expression for its moments. Additionally, almost all eigenvalues are shown to converge toward zero as the number of factors grows over all bounds. This effect cumulates the total energy in a vanishing number of dimensions. The channel model addressed generalizes the model introduced in [1] for communication via large antenna arrays to N-fold scattering per propagation path. As a byproduct, the multiplicative free convolution is shown to extend to a certain class of asymptotically large non-Gaussian random covariance matrice
Keywords: Antenna arrays; Catalan numbers; Channel models; Fading channels; Multiplicative free convolution; Random matrices; S-transform; Stieltjes transform

On the Capacity Loss due to Separation of Detection and Decoding - Gerstacker, Wolfgang; Müller, Ralf (IEEE Transactions on Information Theory, 2004)
The performance loss due to separation of detection and decoding on the binary-input additive white Gaussian noise (AWGN) channel is quantified in terms of mutual information. Results are reported for both the code-division multiple-access (CDMA) channel in the large system limit and the intersymbol interference (ISI) channel. The results for CDMA rely on the replica method developed in statistical mechanics. It is shown that a previous result of Shamai and Verdú found for Gaussian input alphabet holds also for binary input alphabets. For the ISI channel, the performance loss is calculated via the Bahl-Cocke-Jelinek-Raviv (BCJR) algorithm. Comparisons are made to the capacity of separate detection and decoding using suboptimum detectors such as a decision-feedback equalizer. © 2004 IEEE.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.mobilk.onthec

On the Capacity Loss due to Separation of Detection and Decoding for ISI Channels - Gerstacker, Wolfgang; Müller, Ralf (IEEE Transactions on Information Theory, 2002)
The performance loss due to separation of detection and decoding on the binary-input additive white Gaussian noise (AWGN) channel is quantified in terms of mutual information. Results are reported for both the code-division multiple-access (CDMA) channel in the large system limit and the intersymbol interference (ISI) channel. The results for CDMA rely on the replica method developed in statistical mechanics. It is shown that a previous result of Shamai and Verdú found for Gaussian input alphabet holds also for binary input alphabets. For the ISI channel, the performance loss is calculated via the Bahl-Cocke-Jelinek-Raviv (BCJR) algorithm. Comparisons are made to the capacity of separate detection and decoding using suboptimum detectors such as a decision-feedback equalizer. <br
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.mobilk.onthec_8
Keywords: Channel capacity loss; Fading channels; Maximum detection; Replica method

On the Capacity Loss due to Separation of Detection and Decoding in Large CDMA Systems - Müller, Ralf; Gerstacker, Wolfgang (Conference Proceedings, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.mobilk.onthec

On the capacity of asynchronous CDMA systems - Cottatellucci, Laura; Müller, Ralf; Debbah, Merouane (41st Asilomar Conference on Signals, Systems and Computers, ACSSC, 2007)
The total capacity per chip constrained to a given chip pulse waveform of asynchronous code division multiple access (CDMA) channels with random spreading and subject to frequency-flat fading is investigated in the large system limit. The analysis in terms of signal to interference and noise ratio (SINR) is extended to CDMA systems with linear minimum mean square error (MMSE) detectors. The system behaviour is completely described by a positive function n(f) that can be interpreted as the spectrum of the multiuser efficiency. Both total capacity per chip and SINR of linear MMSE detectors can be expressed in terms of the spectrum of the multiuser efficiency. A simple relation between the total capacities per chip of asynchronous CDMA systems with modulation based on sinc pulse waveforms and of synchronous CDMA systems is derived. © 2007 IEEE.
Keywords: Multiaccess communication; Signal to noise Ratio; Detectors; Pulse Modulation; Interference constraints; Frequency conversion; Fading; Signal Analysis; Mean square error Methods; Code division multiplexing

On the Capacity of SWIPT Systems with a Nonlinear Energy Harvesting Circuit - Morsi, Rania; Jamali Kooshkghazi, Vahid; Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications (ICC), 2018)
In this paper, we study information-theoretic limits for simultaneous wireless information and power transfer (SWIPT) systems employing a practical nonlinear radio frequency (RF) energy harvesting (EH) receiver. In particular, we consider a three-node system with one transmitter that broadcasts a common signal to separated information decoding (ID) and EH receivers. Owing to the nonlinearity of the EH receiver circuit, the efficiency of wireless power transfer depends significantly on the waveform of the transmitted signal. In this paper, we aim to answer the following fundamental question: What is the optimal input distribution of the transmit waveform that maximizes the rate of the ID receiver for a given required harvested power at the EH receiver? In particular, we study the capacity of a SWIPT system impaired by additive white Gaussian noise (AWGN) under average-power (AP) and peak-power (PP) constraints at the transmitter and an EH constraint at the EH receiver. Using Hermite polynomial bases, we prove that the optimal capacity-achieving input distribution that maximizes the rate-energy region is unique and discrete with a finite number of mass points. Our numerical results show that the rate-energy region is enlarged for a larger PP constraint and that the rate loss of the considered SWIPT system compared to the AWGN channel without EH receiver is reduced by increasing the AP budge
Keywords: AWGN channels; channel capacity; decoding; energy harvesting; optimisation; polynomials; radio receivers; radiofrequency power transmission; telecommunication power supplies; rate-energy region; nonlinear energy harvesting circuit; information-theoretic limits; wireless power transfer; SWIPT system; nonlinear radio frequency energy harvesting receiver; information decoding; additive white Gaussian noise; average-power constraint; peak-power constraint; Hermite polynomial; simultaneous wireless information and power transfer; Receivers; Radio frequency; Integrated circuit modeling; Rectennas; Transmitters; RF signals; AWGN channels

On the Capacity of the Two-Hop Half-Duplex Relay Channel - Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
Although extensively investigated, the capacity of the two-hop half-duplex (HD) relay channel is not fully understood. In particular, a capacity expression which can be evaluated straightforwardly is not available and an explicit coding scheme which achieves the capacity is not known either. In this paper, we derive a new expression for the capacity of the two-hop HD relay channel based on a simplified converse. Compared to previous results, this capacity expression can be easily evaluated. Moreover, we propose an explicit coding scheme which achieves the capacity. To achieve the capacity, the relay does not only send information to the destination by transmitting information-carrying symbols but also with the zero symbols resulting from the relay's silence during reception. As examples, we compute the capacities of the two-hop HD relay channel for the cases when the source-relay and relay-destination links are both binary-symmetric channels (BSCs) and additive white Gaussian noise (AWGN) channels, respectively, and numerically compare the capacities with the rates achieved by conventional relaying where the relay receives and transmits in a codeword-by-codeword fashion and switches between reception and transmission in a strictly alternating manner. Our numerical results show that the capacities of the two-hop HD relay channel for BSC and AWGN links are significantly larger than the rates achieved with conventional relaying.<br
Keywords: Relays; High definition video; Encoding; Entropy; AWGN channels; Mutual information; Switches

On the delay-energy tradeoff in multiuser fading channels - Chaporkar, Prasanna; Kansanen, Kimmo; Müller, Ralf (EURASIP Journal on Wireless Communications and Networking, 2009)
We consider the delay-energy tradeoff on a fading channel with multiuser diversity. For fixed arbitrary rates of the users, the total transmitted energy is minimized subject to a delay constraint. To achieve this goal we propose a scheme which schedules a subset of all users simultaneously. The scheduled users are allocated power to guarantee successful separation at the detector by successive decoding. In this way, we can benefit from both multiuser diversity and the near-far situation via scheduling and simultaneous transmission, respectively. We analytically show that when the number of users goes to infinity the energy required to guarantee the required user rates can be made as small as required at the cost of a higher delay delay-energy tradeoff. We explicitly compute the delay under the proposed scheduling policy and discuss how delay differentiation can be achieved. We extend the results to multiband multiaccess channel. Finally, all the results can be generalized in a straightforward fashion to broadcast channel due to the Gaussian multiaccess-broadcast channel duality.

On the Design and Security of a Lattice-Based Threshold Secret Sharing Scheme - Amini Khorasgani, Hamidreza; Asaad, Saba; Pilaram, Hossein; Eghlidos, Taraneh; Aref, Mohammad Reza (International Journal of Information Security, 2016)

On the Design of Matched Filters for Molecule Counting Receivers - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert (IEEE Communications Letters, 2017)
In this letter, we design matched filters for diffusive molecular communication systems taking into account the following impairments: signal-dependent diffusion noise, inter-symbol interference (ISI), and external interfering molecules. The receiver counts the number of observed molecules several times within one symbol interval and employs linear filtering to detect the transmitted data. We derive the optimal matched filter by maximizing the expected signal-to-interference-plus-noise ratio of the decision variable. Moreover, we show that for the special case of an ISI-free channel, the matched filter reduces to a simple sum detector and a correlator for the channel impulse response for the diffusion noise-limited and (external) interference-limited regimes, respectively. Our simulation results reveal that the proposed matched filter considerably outperforms the benchmark schemes available in literature, especially when ISI is severe.<br
Keywords: Interference; Receivers; Signal to noise ratio; Optimal matching; Correlators; Transmitters; Detectors

On the design of MIMO-NOMA downlink and uplink transmission - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, a novel MIMO-NOMA framework for downlink and uplink transmission is proposed by applying the concept of signal alignment. By using stochastic geometry, closed-form analytical results are developed to facilitate the performance evaluation of the proposed framework for randomly deployed users and interferers. The impact of different power allocation strategies, such as fixed power allocation and cognitive radio inspired power allocation, on the performance of MIMO-NOMA is also investigated. Computer simulation results are provided to demonstrate the performance of the proposed framework and the accuracy of the developed analytical results.<br
Keywords: Base stations; NOMA; Interference; Uplink; Resource management; Downlink; Signal to noise ratio

On the Ergodic Mutual Information of Keyhole MIMO Channels with Finite-Alphabet Inputs - Ouyang, Chongjun; Bereyhi, Ali; Asaad, Saba; Müller, Ralf; Cheng, Julian; Yang, Hongwen (IEEE Communications Letters, 2023)
This letter studies the ergodic mutual information (EMI) of keyhole multiple-input multiple-output channels having finite-alphabet input signals. The EMI is first investigated for single-stream transmission considering both cases with and without the channel state information at the transmitter. Then, the derived results are extended to the scenario of multi-stream transmission. Asymptotic analyses are performed in the regime of high signal-to-noise ratio (SNR). The high-SNR EMI is shown to converge to a constant with its rate of convergence determined by the diversity order. On this basis, the influence of the keyhole effect on the EMI is discussed. The analytical results are validated by numerical simulations.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Ergodic mutual information; finite-alphabet inputs; keyhole channel; multiple-input multiple-output

On the evaluation of blind pilot decontamination in finite dimensions - Amiri, Ebrahim; Müller, Ralf; Gerstacker, Wolfgang (ITG Workshop on Smart Antennas, 2017)

On the Feasibility of UMTS-based Traffic Information Systems - Sommer, Christoph; Schmidt, Armin Christian; German, Reinhard; Dressler, Falko; Koch, Wolfgang; et al. (Ad Hoc Networks, 2010)
Intelligent Transportation Systems (ITS) are a hot topic in the communications society. Currently, research is primarily focusing on setting up Vehicular Ad Hoc Networks (VANETs) based on WLAN technology. However, VANETs are heavily dependent on high market penetration or infrastructure support. Third-generation (3G) networks might complement these efforts. They are already widely deployed and can serve as the basis for Car-to-Infrastructure (C2I) applications. We developed a simulation framework for holistic analysis of complex UMTS-based ITS. This framework couples simulation models with corresponding protocols of the UMTS link level, of higher network layers, and of road traffic. Based on our simulation framework and real-world 3G network coverage data, we evaluated a UMTS-based Traffic Information Systems (TIS) in a typical highway scenario in which information about traffic jams needed to be communicated to other cars for optimized route planning. The evaluation clearly outlines the capabilities of the simulation framework and evaluation results are consistent with all expectations. For example, we show that the availability of UMTS multicast distribution services are demanded for an efficient operation of the TIS application. © 2010 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2010.tech.IMMD.IMMD7.onthef
Keywords: Car-to-Infrastructure; Intelligent Transportation Systems; Performance modeling; UMTS

On the finite-SNR diversity-multiplexing tradeoff in Rayleigh product channels - Zheng, Zhong; Müller, Ralf; Speicher, Roland; Hämäläinen, Jyri; Corander, Jukka; Wei, Lu (IEEE Int’l Symp. Inform. Theory, 2015)

On the fluctuation of mutual information in double scattering channel. - Zheng, Zhong; Wei, Lu; Speicher, Roland; Müller, Ralf; Hämäläinen, Jyri; Corander, Jukka (Int’l Zurich Seminar on Commun, 2014)

On the impact of phase shifting designs on IRS-NOMA - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Wireless Communications Letters, 2020)
In this letter, the impact of two phase shifting designs, namely coherent phase shifting and random discrete phase shifting, on the performance of intelligent reflecting surface (IRS) assisted non-orthogonal multiple access (NOMA) is studied. Analytical and simulation results are provided to show that the two designs achieve different tradeoffs between reliability and complexity. To further improve the reception reliability of the random phase shifting design, a low-complexity phase selection scheme is also proposed in this letter.
CRIS-Team Scopus Importer:2020-10-30
Keywords: intelligent reflecting surface (IRS); Non-orthogonal multiple access (NOMA); phase shifting designs

On the link performance of a proposed compact antenna system - Bains, Robert; Kalis, Antonis; Müller, Ralf (IEEE Communications Letters, 2008)
In this paper we consider an antenna system, that consists of one active and one parasitic antenna element. Different antenna patterns may be created by loading the parasitic element with appropriate reactive impedances on each symbol period. We demonstrate the performance of a communication link that uses the proposed antenna system at the transmitter and two omnidirectional antennas at the receiver. The Arimoto-Blahut algorithm is used to find the capacity achieving distribution on the channel symbols. The capacity of the antenna system is compared to the capacity obtained by a single transmitter antenna. © 2008 IEEE.
Keywords: Antenna array mutual coupling; MIMO systems; Parasitic antennas

On the Outage Performance of Non-Orthogonal Multiple Access With 1-bit Feedback - Xu, Peng; Yuan, Yi; Ding, Zhiguo; Dai, Xuchu; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, the outage performance of downlink non-orthogonal multiple access (NOMA) is investigated for the case where each user feeds back only one bit of its channel state information (CSI) to the base station. Conventionally, opportunistic one-bit feedback has been used in fading broadcast channels to select only one user for transmission. In contrast, the considered NOMA scheme adopts superposition coding to serve all users simultaneously in order to improve user fairness. A closed-form expression for the common outage probability (COP) is derived, along with the optimal diversity gains under two types of power constraints. Particularly, it is demonstrated that the diversity gain under a long-term power constraint is twice as large as that under a short-term power constraint. Furthermore, we study dynamic power allocation optimization for minimizing the COP, based on one-bit CSI feedback. This problem is challenging, since the objective function is non-convex; however, under the short-term power constraint, we demonstrate that the original problem can be transformed into a set of convex problems. Under the long-term power constraint, an asymptotically optimal solution is obtained for high signal-to-noise ratio.<br
Keywords: NOMA; Fading channels; Base stations; Resource management; Encoding; Downlink; Transmitters

On the performance of iterative receivers for interfering MIMO-OFDM systems in measured channels - Hammarberg, P.; Rossi, P. Salvo; Tufvesson, F.; Edfors, O.; Kolmonen, V. -M.; Almers, P.; Müller, Ralf; Molisch, A. F. (2008 42nd Asilomar Conference on Signals, Systems and Computers, ASILOMAR 2008, 2008)
This paper investigates the gains harvested through base station cooperation in the up-link for a multi-user (MU) Multiple-Input Multiple-Output Orthogonal Frequency Division Multiplexing (MIMO-OFDM) system, operating in a real indoor environment. The base stations perform joint detection using an iterative receiver that carries out multi-user detection and channel estimation via soft information from the single-user decoders. Performance evaluation is carried out using real channels from an indoor dynamic dual MIMO link measurement campaign. The measured scenario represent a real life situation where two users communicate with two base stations, each with two antennas, in an environment resembling a shopping mall or an airport terminal. System performance is evaluated in terms of both Bit- Error Rate (BER) vs. Signal-to-Interference Ratio (SIR) and Cumulative Distribution Functions (CDF) for the instantaneous BER. Also, the impact of using soft information in the channel estimation is analyzed. © 2008 IEEE.

On the Performance of LTE/Wi-Fi Dual-Mode Uplink Transmission: Connection Probability Versus Energy Efficiency - Zhang, Jing; Han, Jing; Xiang, Lin; Ng, Derrick Wing Kwan; Chen, Min; Jo, Minho (IEEE Transactions on Vehicular Technology, 2020)
This paper evaluates the performance of uplink transmission in an LTE/Wi-Fi coexisting heterogeneous network (HetNet), where user equipments (UEs) capable of jointly performing LTE/Wi-Fi dual access and dual power control have a higher preference in connecting the Wi-Fi access points (WAPs) than the LTE base stations (LBSs). Thereby, each UE competes for Wi-Fi connection using carrier-sense multiple access with collision avoidance (CSMA/CA) and, only if unsuccessful, employs cellular communication. During uplink transmission, the UEs employ truncated channel inversion power control with receiving thresholds adjusted according to the occupied communication modes. Based on the stochastic geometry theory, we derive the analytical expressions for the successful connection probability and the average energy efficiency (EE) of Wi-Fi communications. We show that there exists a maximal successful connection probability for Wi-Fi communications, where the optimal receiving signal and energy thresholds of WAPs depend critically on the density of WAPs. Moreover, the average EE of UEs successfully accessing WAPs saturates in the large receiving signal threshold regime, independent of the density of WAPs. These findings significantly differ from those in cellular communications, where maintaining stable service connection is more emphasized than other operation goals, and reveal that deploying Wi-Fi communication has a potential for improving the EE of the considered HetNet. Both simulation and experiment results validate the analytical derivations. These results together show that, compared with single-mode uplink transmission, the considered dual-mode transmission can achieve higher connection probability and EE simultaneously in LTE/Wi-Fi coexisting HetNets.
CRIS-Team WoS Importer:2020-12-25

On the Performance of Wireless Powered Communication With Non-linear Energy Harvesting - Morsi, Rania; Boshkovska, Elena; Ramadan, Esmat; Ng, Derrick Wing Kwan; Schober, Robert (International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2017)
In this paper, we analyze the performance of a time-slotted multi-antenna wireless powered communication (WPC) system, where a wireless device first harvests radio frequency (RF) energy from a power station (PS) in the downlink to facilitate information transfer to an information receiving station (IRS) in the uplink. The main goal of this paper is to provide insights and guidelines for the design of practical WPC systems. To this end, we adopt a recently proposed parametric non-linear RF energy harvesting (EH) model, which has been shown to accurately model the end-to-end non-linearity of practical RF EH circuits. In order to enhance the RF power transfer efficiency, maximum ratio transmission is adopted at the PS to focus the energy signals on the wireless device. Furthermore, at the IRS, maximum ratio combining is used. We analyze the outage probability and the average throughput of information transfer, assuming Nakagamim fading uplink and downlink channels. Moreover, we study the system performance as a function of the number of PS transmit antennas, the number of IRS receive antennas, the transmit power of the PS, the fading severity, the transmission rate of the wireless device, and the EH time duration. In addition, we obtain a fixed point equation for the optimal transmission rate and the optimal EH time duration that maximize the asymptotic throughput for high PS transmit powers. All analytical results are corroborated by simulations.

On the spectral efficiency of MMSE vector precoding - Gardasevic, Vesna; Müller, Ralf; Zaidel, Benjamin M.; Geir Egil Oien, Geir Egil Oien; Lundheim, Lars (2011 IEEE Wireless Communications and Networking Conference, WCNC 2011, 2011)
In this paper, we investigate the spectral efficiency of vector precoding with minimum mean square error (MMSE) linear preprocessing. We restrict the discussion to the spectral efficiency of MMSE vector precoding with quadrature phase-shift keying (QPSK) signaling. Spectral efficiency is investigated by numerical simulations, and plotted as a function of the energy per bit divided by the noise spectral density E/N. The optimum system load , given as the ratio of the number of transmit and receive antennas, that maximizes spectral efficiency is obtained. Previously obtained spectral efficiency results for: Dirty paper coding (DPC), linear zero forcing (ZF), ZF vector precoding, and linear MMSE precoding are provided for comparison. We quantify the performance enhancement that MMSE vector precoding obtains in comparison to vector precoding with ZF linear preprocessing, in the low to medium E/N region. We also find that MMSE vector precoding does not significantly outperform its linear counterpart. © 2011 IEEE.
Keywords: Vectors; Phase shift keying; Receiving antennas; Noise; Forward error correction; MIMO; Transmitting antennas

On the statistics of reaction-diffusion simulations for molecular communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (Proceedings of the 2nd ACM International Conference on Nanoscale Computing and Communication, ACM NANOCOM 2015, 2015)
A molecule traveling in a realistic propagation environment can experience stochastic interactions with other molecules and the environment boundary. The statistical behavior of some isolated phenomena, such as dilute unbounded molecular diffusion, are well understood. However, the coupling of multiple interactions can impede closed-form analysis, such that simulations are required to determine the statistics. This paper compares the statistics of molecular reactiondiff usion simulation models from the perspective of molecular communication systems. Microscopic methods track the location and state of every molecule, whereas mesoscopic methods partition the environment into virtual containers that hold molecules. The properties of each model are described and compared with a hybrid of both models. Simulation results also assess the accuracy of Poisson and Gaussian approximations of the underlying Binomial statistics.
CRIS-Team Scopus Importer:2020-01-31

On the Throughput of Wireless Underground Sensor Networks using Magneto-Inductive Waveguides - Kisseleff, Steven; Gerstacker, Wolfgang; Sun, Zhi; Akyildiz, Ian F. (IEEE Global Communications Conference (GLOBECOM), 2013)

On the transport capacity of a multiple access Gaussian channel - Müller, Ralf; et al. (2004 International Workshop on Wireless Ad-Hoc Networks, 2005)
We address the problem of maximizing the transport capacity of a wireless network, defined as the sum, over all transmitters, of the products of the transmission rate with a reward r(x), which is a function of the distance x separating the transmitter and its receiver. When r(x) = x, this product is measured in bps × meters, and is the natural measure of the usefulness of a transmission in a multihop wireless ad hoc network. We first consider a single transmitter-receiver pair, and determine the optimal distance between the two that maximizes the rate-reward product, for reward functions of the form r(x) = x and when the signal power decays with distance according to a power law. We then calculate the scheme that maximizes the transport capacity in a multiple access network consisting of a single receiver and a number of transmitters, each placed at a fixed distance from the receiver, and each with a fixed power constraint. We conclude by showing that when the per-transmitter power constraints are substituted with a single constraint on the sum of the powers, the maximum transport capacity and the power allocation scheme that achieves it can be found by solving a convex optimization problem. © 2004 IEEE.

On the transport capacity of Gaussian multiple access and broadcast channels - Gupta, G. A.; Toumpis, S.; Sayir, J.; Müller, Ralf (Wireless Networks, 2008)
We study the transport capacity of the Gaussian multiple access channel (MAC), which consists of multiple transmitters and a single receiver, and the Gaussian broadcast channel (BC), which consists of a single transmitter and multiple receivers. The transport capacity is defined as the sum, over all transmitters (for the MAC) or receivers (for the BC), of the product of the data rate with a reward r(x) which is a function of the distance x that the data travels. In the case of the MAC, assuming that the sum of the transmit powers is upper bounded, we calculate in closed form the optimal power allocation among the transmitters, that maximizes the transport capacity, using Karush-Kuhn-Tucker (KKT) conditions. We also derive asymptotic expressions for the optimal power allocation, that hold as the number of transmitters approaches infinity, using the most-rapid-approach method of the calculus of variations. In the case of the BC, we calculate in closed form the optimal allocation of the transmit power among the signals to the different receivers, both for a finite number of receivers and for the case of asymptotically many receivers, using our results for the MAC together with duality arguments. Our results can be used to gain intuition and develop good design principles in a variety of settings. For example, they apply to the uplink and downlink channel of cellular networks, and also to sensor networks which consist of multiple sensors that communicate with a single central station. © 2006 Springer Science+Business Media, LLC.
Keywords: Broadcast channel; Multiple access channel; Power allocation; Transport capacity; Wireless networks

On uncoded high rate transmission over synchronous Gaussian multiple-access channels - Müller, Ralf; et al. (1998 IEEE International Symposium on Information Theory, ISIT 1998, 1998)
On Gaussian multiple-access channels a penalty in power efficiency is to be paid if total transmission rate is higher than 1 bit/s/Hz per dimension. This usually results from the need for higher order modulation schemes required to maintain orthogonality of all users' signal waveforms. In this paper, we show that keeping binary modulation and accepting some multiple-access interference, is a more power efficient strategy by presenting simulation results of transmission systems outperforming orthogonal schemes for rates between 1.25 and 1.75 bit/s/Hz, per dimension. © 1998 IEEE.

On user pairing in NOMA uplink - Sedaghat, Mohammad Ali; Müller, Ralf (IEEE Transactions on Wireless Communications, 2018)

Optical IRSs: Power Scaling Law, Optimal Deployment, and Comparison with Relays - Ajam, Hedieh; Najafi, Marzieh; Jamali, Vahid; Schober, Robert (IEEE Transactions on Communications, 2023)
The line-of-sight (LOS) requirement of free-space optical (FSO) systems can be relaxed by employing optical relays or optical intelligent reflecting surfaces (IRSs). In this paper, we show that the power reflected from FSO IRSs and collected at the receiver (Rx) lens may scale quadratically or linearly with the IRS size or may saturate at a constant value. We analyze the power scaling law for optical IRSs and unveil its dependence on the wavelength, transmitter (Tx)-to-IRS and IRS-to-Rx distances, beam waist, and Rx lens size. We also consider the impact of linear, quadratic, and focusing phase shift profiles across the IRS on the power collected at the Rx lens for different IRS sizes. Our results reveal that surprisingly the powers received for the different phase shift profiles are identical, unless the IRS operates in the saturation regime. Moreover, IRSs employing the focusing (linear) phase shift profile require the largest (smallest) size to reach the saturation regime. We also compare optical IRSs in different power scaling regimes with optical relays in terms of the outage probability, diversity and coding gains, and optimal placement. Our results show that, at the expense of a higher hardware complexity, relay-assisted FSO links yield a better outage performance at high signal-to-noise-ratios (SNRs), but optical IRSs can achieve a higher performance at low SNRs. Moreover, while it is optimal to place relays equidistant from Tx and Rx, the optimal location of optical IRSs depends on the phase shift profile and the power scaling regime they operate in.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Laser beams; Lenses; Optical network units; Optical receivers; Optical saturation; Optical transmitters; Relays

Optimal 3D-Trajectory Design and Resource Allocation for Solar-Powered UAV Communication Systems - Sun, Yan; Xu, Dongfang; Ng, Derrick Wing Kwan; Dai, Linglong; Schober, Robert (IEEE Transactions on Communications, 2019)
n this paper, we investigate the resource allocation algorithm design for multicarrier solar-powered unmanned aerial vehicle (UAV) communication systems. In particular, the UAV is powered by the solar energy enabling sustainable communication services to multiple ground users. We study the joint design of the 3D aerial trajectory and the wireless resource allocation for maximization of the system sum throughput over a given time period. As a performance benchmark, we first consider an off-line resource allocation design assuming non-causal knowledge of the channel gains. The algorithm design is formulated as a mixed-integer non-convex optimization problem taking into account the aerodynamic power consumption, solar energy harvesting, a finite energy storage capacity, and the quality-of-service requirements of the users. Despite the non-convexity of the optimization problem, we solve it optimally by applying monotonic optimization to obtain the optimal 3D-trajectory and the optimal power and subcarrier allocation policy. Subsequently, we focus on the online algorithm design that only requires real-time and statistical knowledge of the channel gains. The optimal online resource allocation algorithm is motivated by the off-line scheme and entails a high computational complexity. Hence, we also propose a low-complexity iterative suboptimal online scheme based on the successive convex approximation. Our simulation results reveal that both the proposed online schemes closely approach the performance of the benchmark off-line scheme and substantially outperform two baseline schemes. Furthermore, our results unveil the tradeoff between solar energy harvesting and power-efficient communication. In particular, the solar-powered UAV first climbs up to a high altitude to harvest a sufficient amount of solar energy and then descends again to a lower altitude to reduce the path loss of the communication links to the users it serves.<br
Keywords: Resource management; Communication systems; Trajectory; Solar energy; Unmanned aerial vehicles; Optimization; Aerodynamics

Optimal 3D-Trajectory Design and Resource Allocation for Solar-Powered UAV Communication Systems - Sun, Yan; Xu, Dongfang; Ng, Derrick Wing Kwan; Dai, Linglong; Schober, Robert (IEEE Transactions on Communications, 2019)
In this paper, we investigate the resource allocation algorithm design for multicarrier solar-powered unmanned aerial vehicle (UAV) communication systems. In particular, the UAV is powered by the solar energy enabling sustainable communication services to multiple ground users. We study the joint design of the 3D aerial trajectory and the wireless resource allocation for maximization of the system sum throughput over a given time period. As a performance benchmark, we first consider an off-line resource allocation design assuming non-causal knowledge of the channel gains. The algorithm design is formulated as a mixed-integer non-convex optimization problem taking into account the aerodynamic power consumption, solar energy harvesting, a finite energy storage capacity, and the quality-of-service requirements of the users. Despite the non-convexity of the optimization problem, we solve it optimally by applying monotonic optimization to obtain the optimal 3D-trajectory and the optimal power and subcarrier allocation policy. Subsequently, we focus on the online algorithm design that only requires real-time and statistical knowledge of the channel gains. The optimal online resource allocation algorithm is motivated by the off-line scheme and entails a high computational complexity. Hence, we also propose a low-complexity iterative suboptimal online scheme based on the successive convex approximation. Our simulation results reveal that both the proposed online schemes closely approach the performance of the benchmark off-line scheme and substantially outperform two baseline schemes. Furthermore, our results unveil the tradeoff between solar energy harvesting and power-efficient communication. In particular, the solar-powered UAV first climbs up to a high altitude to harvest a sufficient amount of solar energy and then descends again to a lower altitude to reduce the path loss of the communication links to the users it serves.
CRIS-Team Scopus Importer:2019-07-02
Keywords: 3D-trajectory planning; monotonic optimization; power and subcarrier allocation; solar energy harvesting; UAV communication systems

Optimal Antenna Placement for Two-Antenna Near-Field Wireless Power Transfer - Mayer, Kenneth; Cottatellucci, Laura; Schober, Robert (IEEE International Conference on Communications, ICC 2023, 2023)
Current trends in communication system design precipitate a change in the operating regime from the traditional far-field to the radiating near-field (Fresnel) region. We investigate the optimal transmit antenna placement for a multiple-input single-output (MISO) wireless power transfer (WPT) system designed for a three-dimensional cuboid room under line-of-sight (LoS) conditions in the Fresnel region. We formulate an optimisation problem for maximising the received power at the worst possible receiver location by considering the spherical nature of the electromagnetic (EM) wavefronts in the Fresnel region while assuming perfect knowledge of the channel at the transmitter. For the case of two transmit antennas, we derive a closed-form expression for the optimal positioning of the antennas which is purely determined by the geometry of the environment. If the room contains locations where the far-field approximation holds, the proposed positioning is shown to reduce to the far-field solution. The analytical solution is validated through simulation. Furthermore, the maximum received power at the locations yielding the worst performance is quantified and the power gain over the optimal far-field solution is presented. For the considered cuboid environment, we show that a distributed antenna system is optimal in the Fresnel region, whereas a co-located antenna architecture is ideal for the far-field.<br
Keywords: Geometry; Transmitting antennas; Receiving antennas; Wireless power transfer; MISO communication; Pulse width modulation; Market research

Optimal Beamforming for MISO Communications via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2020)
Wireless communications via intelligent reflecting surfaces (IRSs) has received considerable attention from both academia and industry. In particular, IRSs are able to create favorable wireless propagation environments with typically low-cost passive devices. While various IRS-Aided wireless communication systems have been investigated in the literature, thus far, the optimal design of such systems is not well understood. In this paper, IRS-Assisted single-user multiple-input single-output (MISO) communication is investigated. To maximize the spectral efficiency, a branch-And-bound (BnB) algorithm is proposed to obtain globally optimal solutions for both the active and passive beamformers at the access point (AP) and the IRS, respectively. Simulation results confirm the effectiveness of deploying IRSs in wireless systems. Furthermore, by taking the proposed optimal BnB algorithm as the performance benchmark, the optimality of existing design algorithms is investigated.
CRIS-Team Scopus Importer:2020-09-18

Optimal Buffer-Aided Relaying With Imperfect CSI - Jamali Kooshkghazi, Vahid; Waly, Noha; Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2016)
In this letter, we consider a two-hop relay channel that consists of a source, a half-duplex decode-and-forward relay, and a destination. We derive the optimal buffer-aided relaying policy based on imperfect channel state information (CSI) and under long-term per-node power constraints for the source and the relay. In particular, the proposed protocol determines the optimal state of the relay node, namely, the transmit, receive, or silent state, based on the imperfect CSI of the involved links, the quality of the CSI, and the required acquisition overhead. Our simulation results verify the analysis and reveal that there is an optimal tradeoff between the required acquisition overhead and the quality of the CSI that maximizes the throughput.<br
Keywords: Relays; Throughput; Protocols; Channel estimation; Fading channels; Simulation; Indexes

Optimal Detection of Multiple Symbol-Slotted Random Access based Packet Transmissions - Kisseleff, Steven; Gerstacker, Wolfgang (IEEE Wireless Communications Letters, 2021)
Random access (RA) protocols are suitable for the support of massive connectivity especially in machine-type communications, such as the Internet of Things (IoT). In this context, ALOHA protocols (both slotted and unslotted) have been re-introduced as promising enablers due to a potentially high throughput when enhanced via successive interference cancellation (SIC). Meanwhile, SIC has become the most popular solution for RA detection problems. In this work, we first point out the weaknesses of SIC and then propose a novel method based on joint detection of all randomly scheduled data packets. The proposed method is based on the joint computation of a-posteriori probabilities for all data symbols and packet localizations, such that optimal detection for RA is obtained.
CRIS-Team Scopus Importer:2021-02-19
Keywords: ALOHA.; joint detection; Location awareness; MAP; Markov processes; Modulation; Protocols; Random access; Receivers; Silicon carbide; Synchronization

Optimal Energy Beamforming for Distributed Wireless Power Transfer Over Frequency-Selective Channels - Luo, Bing; Yeoh, Phee Lep; Schober, Robert; Krongold, Brian S. (CC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
This paper analyzes the optimal transmission strategy and power allocation for a distributed wireless power transfer (WPT) system operating over frequency-selective fading channels. We consider K coordinated energy transmitters (CETs) coherently transmitting energy to a single user over N > K subchannels with individual power constraints. To maximize the total harvested energy, we derive the optimal co-phasing power allocation rule which has the following properties: 1) For any given subchannel, if the optimal power allocation of one CET is zero, then the power allocated by all the other K − 1 CETs to that subchannel is also zero (i.e., the subchannel is inactive); 2) For the non-zero power subchannels, the optimal power allocation obeys a proportionality principle that establishes a relationship between the powers allocated by all K CETs to all active subchannels. Based on this property, we prove that the optimal distributed WPT strategy is for all CETs to select no more than K subchannels. This is in sharp contrast to wireless information transmission where more than K subchannels may be used for capacity maximization. Numerical examples verify our theoretical results and show the performance gains of our proposed scheme compared to two benchmark schemes.<br
Keywords: Resource Management; Array signal processing; Frequency-selective fading channels; Receivers; Linear programming; Wireless power Transfer; Transmitters

Optimal Energy Signal Design for Multi-user MISO WPCNs with Non-linear Energy Harvesting Circuits - Shanin, Nikita; Hagelauer, Amelie; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2023)
The optimal energy signal design for wireless powered communication networks (WPCNs) enabling energy-sustainable communication for a large number of low-power devices is still an open problem in practical systems. In this work, we study a multi-user WPCN, where a multi-antenna base station (BS) sends an energy signal to multiple single-antenna users, which, in turn, harvest energy from the received signal and utilize it for information transmission in the uplink. In contrast to the existing works on multiple-input single-output (MISO) WPCN design, in this paper, we jointly optimize the energy signal waveform and downlink beamforming at the BS for energy harvesting (EH) devices described by non-linear circuit-based models. To this end, we assume that the BS broadcasts a pulse-modulated signal employing multiple energy signal vectors and we formulate an optimization problem for the joint design of the downlink transmit energy signal vectors, their number, the durations of the transmit pulses, and the time allocation policy for minimization of the average transmit power at the BS. We show that for single-user WPCNs, a single energy signal vector, which is collinear with the maximum ratio transmission (MRT) vector and drives the EH circuit at the user device into saturation, is optimal. Next, for the general multi-user case, we show that the optimal signal design requires a maximum number of energy signal vectors that exceeds the number of users by one and propose an algorithm to obtain the optimal energy signal vectors. Since the complexity of the optimal design is high, we also propose two suboptimal schemes for WPCN design. First, for asymptotic massive WPCNs, where the ratio of the number of users to the number of BS antennas, i.e., the system load, tends to zero, we show that the optimal downlink transmit signal can be obtained in closed-form and comprises a sequence of weighted sums of MRT vectors. Next, based on this result, for general WPCNs with finite system loads, we propose a suboptimal closed-form MRT-based design and a suboptimal semidefinite relaxation (SDR)-based scheme. Our simulation results reveal that the proposed optimal scheme and suboptimal SDR-based design achieve nearly identical performance and outperform two baseline schemes, which are based on linear and sigmoidal EH models. Furthermore, we show that, if the system load of the WPCN is low, the performance gap between the proposed suboptimal solutions is small and becomes negligible as the number of BS antennas tends to infinity.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Downlink; Integrated circuit modeling; MISO communication; Multiple-input multiple-output (MIMO); Non-linear energy harvesting; Radio frequency; Signal design; Signal design; Uplink; Wireless communication; Wireless powered communication

Optimal Frequency-Selective Energy Beamforming with Joint Total and Individual Power Constraints - Luo, Bing; Yeoh, Phee Lep; Schober, Robert; Krongold, Brian S. (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Optimal joint power and subcarrier allocation for full-duplex multicarrier non-orthogonal multiple access systems - Sun, Yan; Ng, Derrick Wing Kwan; Ding, Zhiguo; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we investigate resource allocation algorithm design for multicarrier non-orthogonal multiple access (MC-NOMA) systems employing a full-duplex (FD) base station for serving multiple half-duplex (HD) downlink and uplink users simultaneously. The proposed algorithm is obtained from the solution of a non-convex optimization problem for the maximization of the weighted sum system throughput. We apply monotonic optimization to develop an optimal joint power and subcarrier allocation policy. The optimal resource allocation policy serves as a system performance benchmark due to its high computational complexity. Furthermore, a suboptimal iterative scheme based on successive convex approximation is proposed to strike a balance between computational complexity and optimality. Our simulation results reveal that the proposed suboptimal algorithm achieves a close-to-optimal performance. In addition, FD MC-NOMA systems employing the proposed resource allocation algorithms provide a substantial system throughput improvement compared with conventional HD multicarrier orthogonal multiple access (MC-OMA) systems and other baseline schemes. In addition, our results unveil that FD MC-NOMA systems enable a fairer resource allocation compared with traditional HD MC-OMA systems.<br
Keywords: monotonic optimization; full-duplex radio; non-convex optimization; multicarrier systems; Non-orthogonal multiple access

Optimal Joint Power and Subcarrier Allocation for MC-NOMA Systems - Sun, Yan; Ng, Derrick Wing Kwan; Ding, Zhiguo; Schober, Robert (2016)
In this paper, we investigate the resource allocation algorithm design for multicarrier non-orthogonal multiple access (MC-NOMA) systems. The proposed algorithm is obtained from the solution of a non-convex optimization problem for the maximization of the weighted system throughput. We employ monotonic optimization to develop the optimal joint power and subcarrier allocation policy. The optimal resource allocation policy serves as a performance benchmark due to its high complexity. Furthermore, to strike a balance between computational complexity and optimality, a suboptimal scheme with low computational complexity is proposed. Our simulation results reveal that the suboptimal algorithm achieves a close-tooptimal performance and MC-NOMA employing the proposed resource allocation algorithm provides a substantial system throughput improvement compared to conventional multicarrier orthogonal multiple access (MC-OMA).

Optimal MAP Detection in Presence of Burst Interference for Low Power Wide Area Networks - Kisseleff, Steven; Kneissl, J.; Killian, G.; Gerstacker, Wolfgang (2018 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2018)
CRIS-Team WoS Importer:2019-06-07

OPTIMAL MULTIUSER SCHEDULING SCHEMES FOR SIMULTANEOUS WIRELESS INFORMATION AND POWER TRANSFER - Chynonova, Maryna; Morsi, Rania; Ng, Derrick Wing Kwan; Schober, Robert (EUSIPCO, 2015)
In this paper, we study the downlink multiuser scheduling problem for systems with simultaneous wireless information and power transfer (SWIPT). We design optimal scheduling algorithms that maximize the long-term average system throughput under different fairness requirements, such as proportional fairness and equal throughput fairness. In particular, the algorithm designs are formulated as non-convex optimization problems which take into account the minimum required average sum harvested energy in the system. The problems are solved by using convex optimization techniques and the proposed optimization framework reveals the tradeoff between the long-term average system throughput and the sum harvested energy in multiuser systems with fairness constraints. Simulation results demonstrate that substantial performance gains can be achieved by the proposed optimization framework compared to existing suboptimal scheduling algorithms from the literature.
Keywords: RF energy harvesting; wireless information and power transfer; optimal multiuser scheduling

Optimal Number of Transmit Antennas for Secrecy Enhancement in Massive MIMOME Channels - Asaad, Saba; Bereyhi, Ali; Müller, Ralf; Schaefer, Rafael F.; Rabiei, Amir Masoud (IEEE Global Communications Conference (GLOBECOM), 2017)
This paper studies the impact of transmit antenna selection on the secrecy performance of massive MIMO wiretap channels. We consider a scenario in which a multi-antenna transmitter selects a subset of transmit antennas with the strongest channel gains. Confidential messages are then transmitted to a multi-antenna legitimate receiver while the channel is being overheard by a multi-antenna eavesdropper. For this setup, we approximate the distribution of the instantaneous secrecy rate in the large-system limit. The approximation enables us to investigate the optimal number of selected antennas which maximizes the asymptotic secrecy throughput of the system. We show that increasing the number of selected antennas enhances the secrecy performance of the system up to some optimal value, and that further growth in the number of selected antennas has a destructive effect. Using the large-system approximation, we obtain the optimal number of selected antennas analytically for various scenarios. Our numerical investigations show an accurate match between simulations and the analytic results even for not so large dimensions.
Keywords: Antenna selection; Massive MIMO wiretap channel

Optimal power allocation for a hybrid energy harvesting transmitter - Ahmed, Imtiaz; Ikhled, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications, 2013)
In this work, we consider a point-to-point link where the transmitter has a hybrid supply of energy, i.e., the energy is supplied by a constant energy source and an energy harvester, which harvests energy from its surrounding environment. Our goal is to jointly minimize the power consumed by the constant energy source and any possible waste of the harvested energy to ensure their optimum utilization for transmission of a given amount of data in a given number of time intervals. Two scenarios are considered for packet arrival. In the first scenario, we assume that all data packets have arrived before the transmission begins, whereas in the second scenario, we assume that data packets are arriving during the course of data transmission. For both scenarios, we propose optimal offline transmit power allocation schemes which provide insight on how to efficiently consume the energy supplied by the constant energy source and the energy harvester. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal power allocation for three-phase bidirectional DF relaying with fixed rates - Hadzi-Velkov, Zoran; Zlatanov, Nikola; Schober, Robert (Proceedings of the International Symposium on Wireless Communication Systems, 2013)
Wireless systems that carry delay-sensitive information (such as speech and/or video signals) typically transmit with fixed data rates, but may occasionally suffer from transmission outages caused by the random nature of the fading channels. If the transmitter has instantaneous channel state information (CSI) available, it can compensate for a significant portion of these outages by utilizing power allocation. In this paper, we consider optimal power allocation for a conventional dual-hop bidirectional decode-and-forward (DF) relaying system with a threephase transmission protocol. The proposed strategy minimizes the average power consumed by the end nodes and the relay, subject to some maximum allowable system outage probability (OP), or equivalently, minimizes the system OP while meeting average power constraints at the end nodes and the relay. We show that in the proposed power allocation scheme, the end nodes and the relay adjust their output powers to the minimum level required to avoid outages, but will sometimes be silent, in order to conserve power and prolong their lifetimes. For the proposed scheme, the end nodes use the instantaneous CSI of their respective sourcerelay links and the relay uses the instantaneous CSI of both links. © VDE Verlag GMBH.
CRIS-Team Scopus Importer:2020-02-03

Optimal Power and Time Allocation for WPCNs With Piece-Wise Linear EH Model - Pejoski, Slavche; Hadzi-Velkov, Zoran; Schober, Robert (IEEE Wireless Communications Letters, 2017)
We propose a novel transmission protocol for harvest-then-transmit wireless powered communication networks, which takes into account the non-linearity of the energy harvesting (EH) process at the EH users and maximizes the sum rate in the uplink. We assume a piece-wise linear EH model and provide expressions for the optimal transmit power of the base station (BS), the duration of the EH phase, and the duration of the uplink information transmission phases of the users. The obtained solution provides insight regarding the significance of the non-linear EH model on the optimal resource allocation. Simulations unveil the growing impact of the saturation effect, which occurs for high received radio frequency powers, as the average and the maximum instantaneous transmit powers of the BS increase.<br
Keywords: Resource management; Integrated circuit modeling; Wireless communication; Uplink; Pins; Batteries; Time division multiple access

Optimal power control for analog bidirectional relaying with long-term relay power constraint - Hadzi-Velkov, Zoran; Zlatanov, Nikola; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2013)
Wireless systems that carry delay-sensitive information (such as speech and/or video signals) typically transmit with fixed data rates, but may occasionally suffer from transmission outages caused by the random nature of the fading channels. If the transmitter has instantaneous channel state information (CSI) available, it can compensate for a significant portion of these outages by utilizing power allocation. In a conventional dual-hop bidirectional amplify-and-forward (AF) relaying system, the relay already has instantaneous CSI of both links available, as this is required for relay gain adjustment. We therefore develop an optimal power allocation strategy for the relay, which adjusts its instantaneous output power to the minimum level required to avoid outages, but only if the required output power is below some cutoff level; otherwise, the relay is silent in order to conserve power and prolong its lifetime. The proposed scheme is proven to minimize the system outage probability, subject to an average power constraint at the relay and fixed output powers at the end nodes. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Power Control for Energy Efficient D2D Communication and Its Distributed Implementation - Wu, Yuan; Wang, Jiaheng; Qian, Liping; Schober, Robert (IEEE Communications Letters, 2015)
In this letter, we propose an energy efficient power control scheme for resource sharing between cellular and device-to-device (D2D) users in cellular network assisted D2D communication. We take into account the circuit power consumption of the device-to-device user (DU) and aim at maximizing the DU's energy efficiency while guaranteeing the required throughputs of both the DU and the cellular user. Specifically, we define three different regions for the circuit power consumption of the DU and derive the optimal power control scheme for each region. Moreover, a distributed algorithm is proposed for implementation of the optimal power control scheme.<br
Keywords: Power control; Throughput; Power demand; Interference; Educational institutions; Convergence; Distributed algorithms

Optimal receiver design for diffusive molecular communication with flow and additive noise - Noel, Adam; Cheung, Karen C.; Schober, Robert (IEEE Transactions on Nanobioscience, 2014)
In this paper, we perform receiver design for a diffusive molecular communication environment. Our model includes flow in any direction, sources of information molecules in addition to the transmitter, and enzymes in the propagation environment to mitigate intersymbol interference. We characterize the mutual information between receiver observations to show how often independent observations can be made. We derive the maximum likelihood sequence detector to provide a lower bound on the bit error probability. We propose the family of weighted sum detectors for more practical implementation and derive their expected bit error probability. Under certain conditions, the performance of the optimal weighted sum detector is shown to be equivalent to a matched filter. Receiver simulation results show the tradeoff in detector complexity versus achievable bit error probability, and that a slow flow in any direction can improve the performance of a weighted sum detector.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Diffusion; matched filter; molecular communication; sequence detection; weighted sum detector

Optimal Relay Selection for Outdated CSI - Michalopoulos, Diomidis; Ng, Jonathan; Schober, Robert (IEEE Communications Letters, 2013)
Consider the scenario of relay selection in an environment where the channel estimates are outdated, yet their reliability is known. For this scenario, we propose the optimal relay selection policy, in a minimum outage probability sense. We show that, if the reliabilities of the channel estimates are dissimilar across the relays, this policy offers a noteworthy improvement in terms of array gain, when compared to conventional selection policies. Analytical outage probability expressions are provided, which are corroborated by simulation

Optimal Relay Selection for the Parallel Hybrid RF/FSO Relay Channel: Non-Buffer-Aided and Buffer-Aided Designs - Najafi Kalyani, Marzieh; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Communications, 2017)
Hybrid radio frequency (RF)/free space optical (FSO) systems are among the candidate enabling technologies for the next generation of wireless networks, since they benefit from both the high data rates of the FSO subsystem and the high reliability of the RF subsystem. In this paper, we focus on the problem of throughput maximization in the parallel hybrid RF/FSO relay channel. In the parallel hybrid RF/FSO relay channel, a source node sends its data to a destination node with the help of multiple relay nodes. Thereby, for a given relay, the source-relay and the relay-destination FSO links are orthogonal with respect to each other due to the narrow beam employed for FSO transmission, whereas due to the broadcast nature of the RF channel, half-duplex operation is required for the RF links if self-interference is to be avoided. Moreover, we consider the two cases where the relays are and are not equipped with buffers. For both cases, we derive the optimal relay selection policies for the RF and FSO links and the optimal time allocation policy for transmission and reception for the RF links. The proposed optimal protocols provide important insights for an optimal system design. Since the optimal buffer-aided policy introduces an unbounded delay, we also propose a suboptimal buffer-aided policy, which ensures certain target average delays. Moreover, we present distributed implementations for both the proposed optimal protocols. Simulation results demonstrate that a considerable gain can be achieved by the proposed adaptive protocols in comparison with benchmark schemes from the literature.<br
Keywords: Relays; Radio frequency; Protocols; Throughput; Wireless communication; Optical transmitters; Delays

Optimal Relay Selection in case of Imperfect Channel Estimation - Ng, Jonathan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)

Optimal Resource Allocation and Beamforming for Two-User MISO WPCNs for a Non-linear Circuit-Based EH Model - Shanin, Nikita; Garkisch, Moritz; Hagelauer, Amelie; Schober, Robert; Cottatellucci, Laura (Proceedings of ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2022)
In this paper, we study multi-user multi-antenna wireless power transfer (WPT) systems, where each antenna at the energy harvesting (EH) nodes is connected to a dedicated non-linear rectifier. We propose optimal transmit strategies which maximize a weighted sum of the average harvested powers at the EH nodes subject to a constraint on the power budget of the transmitter. First, for multiple-input single-output (MISO) WPT systems, we prove that the optimal strategy employs maximum ratio transmission (MRT) beamforming and scalar symbols with arbitrary phases and discrete amplitudes following a probability density function (pdf) with at most two mass points. Then, we prove that for single-input multiple-output (SIMO) WPT systems, the optimal transmit symbol amplitudes are discrete random variables, whose pdf also has no more than two mass points. For general multi-user MIMO WPT, we show that the optimal transmit strategy employs scalar unit-norm symbols with arbitrary phases and at most two beamforming vectors. To determine these vectors, we formulate a non-convex optimization problem and obtain an optimal solution based on monotonic optimization. Since the computational complexity of the optimal solution is high, we propose a low-complexity iterative algorithm to obtain a suboptimal solution, which achieves near-optimal performance. Our simulation results reveal that the proposed transmit strategy for multi-user MIMO WPT systems outperforms baseline schemes based on a linear EH model and a single beamforming vector. For a given transmit power budget, we show that the harvested power saturates when increasing the number of transmit antennas. Finally, we observe that the harvested power region spanned by multiple EH nodes is convex and the power harvested at one EH node can be traded for a higher harvested power at the other node

OPTIMAL RESOURCE ALLOCATION AND BEAMFORMING FOR TWO-USER MISO WPCNs FOR A NON-LINEAR CIRCUIT-BASED EH MODEL (Invited Paper) - Shanin, Nikita; Garkisch, Moritz; Hagelauer, Amelie; Schober, Robert; Cottatellucci, Laura (2022 IEEE INTERNATIONAL CONFERENCE ON ACOUSTICS, SPEECH AND SIGNAL PROCESSING (ICASSP), 2022)
CRIS-Team WoS Importer:2023-01-13

Optimal Resource Allocation Design for Large IRS-Assisted SWIPT Systems: A Scalable Optimization Framework - Xu, Dongfang; Jamali, Vahid; Yu, Xianghao; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we study the optimal resource allocation algorithm design for large intelligent reflecting surface (IRS)-assisted simultaneous wireless information and power transfer (SWIPT) systems. To facilitate efficient system design for large IRSs, instead of jointly optimizing all the IRS elements, we partition the IRS into several tiles and employ a scalable optimization framework comprising an offline design stage and an online optimization stage. In the offline stage, the IRS elements of each tile are jointly designed to support a set of different phase shift configurations, referred to as transmission modes, while the best transmission mode is selected from the set for each tile in the online stage. Given a transmission mode set, we aim to minimize the total base station (BS) transmit power by jointly optimizing the beamforming and the transmission mode selection policy taking into account the quality-of-service requirements of information decoding and non-linear energy harvesting receivers, respectively. Although the resource allocation algorithm design is formulated as a non-convex combinatorial optimization problem, we solve it optimally by applying the branch-and-bound (BnB) approach which entails a high computational complexity. To strike a balance between optimality and computational complexity, we also develop an efficient suboptimal algorithm capitalizing on the penalty method and successive convex approximation. Our simulation results show that the proposed designs enable considerable power savings compared to several baseline schemes. Moreover, our results reveal that by properly adjusting the numbers of tiles and transmission modes, the proposed scalable optimization framework indeed facilitates online design for large IRSs. Besides, our results confirm that the advocated physics-based model and scalable optimization framework enable a flexible trade-off between performance and complexity, which is vital for realizing the performance gains promised by large IRS-assisted communication systems in practice.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Array signal processing; Branch and bound approach; Computational complexity; intelligent reflecting surface; optimal resource allocation; Optimization; Radio frequency; Receivers; Resource management; scalable optimization; Wireless communication

Optimal resource allocation for energy harvesting two-way relay systems with channel uncertainty - Ahmed, Imtiaz; Ikhlef, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (2013 IEEE Global Conference on Signal and Information Processing, GlobalSIP 2013 - Proceedings, 2013)
In this paper, we consider two-way decode-and-forward (DF) multiple access and time division broadcasting relaying protocols with energy harvesting (EH) nodes. We propose optimal offline joint energy and transmission time allocation schemes for the considered relaying protocols taking into account channel state uncertainty. The proposed joint energy and transmission time allocation schemes are obtained based on convex optimization problems and maximize the aggregate system throughput over a finite number of transmission intervals.We compare the optimal throughputs obtained for the multiple access and time division broadcasting protocols via simulations. Our results reveal that the proposed schemes are robust to imperfect channel state information and that multiple access broadcasting is less affected by low harvesting rate at the relay than time division broadcasting. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Resource Allocation for Multicarrier MISO-NOMA Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we investigate optimal resource allocation for multicarrier (MC) multiple-input single-output non-orthogonal multiple access (MISO-NOMA) downlink systems. The resource allocation design for the maximization of the weighted system throughput is formulated as a non-convex optimization problem taking into account the quality-of-service requirements of the downlink receivers. We employ monotonic optimization to solve the formulated problem and to obtain the optimal joint precoding and subcarrier allocation policy. The optimal resource allocation policy serves as a performance benchmark due to its high computational complexity. Furthermore, a low-complexity suboptimal resource allocation algorithm is developed and shown to find a locally optimal solution. Our simulation results reveal that the suboptimal algorithm closely approaches the optimal performance. Besides, our results show that MC MISO-NOMA significantly improves the system throughput compared to conventional MC MISO orthogonal multiple access.

Optimal Resource Allocation for Multi-User OFDMA-URLLC MEC Systems - Ghanem, Walid; Jamali, Vahid; Schober, Robert (IEEE Open Journal of the Communications Society, 2022)
In this paper, we study resource allocation algorithm design for multi-user orthogonal frequency division multiple access (OFDMA) ultra-reliable low latency communication (URLLC) in mobile edge computing (MEC) systems. To meet the stringent end-to-end delay and reliability requirements of URLLC MEC systems, we employ joint uplink-downlink resource allocation and finite blocklength transmission. Furthermore, we propose a partial time overlap between the uplink and downlink frames to minimize the end-to-end delay, which introduces a new time causality constraint. The proposed resource allocation algorithm is formulated as an optimization problem for minimization of the total weighted power consumption of the network under a constraint on the number of URLLC user bits computed within the maximum allowable computation time, i.e., the end-to-end delay of a computation task of each user. Despite the non-convexity and the complicated structure of the formulated optimization problem, we develop a globally optimal solution using a branch-and-bound approach based on discrete monotonic optimization theory. The branch-and-bound algorithm minimizes an upper bound on the total power consumption until convergence to the globally optimal value. Furthermore, to strike a balance between computational complexity and performance, we propose two efficient suboptimal algorithms. For the first suboptimal scheme, the optimization problem is reformulated in the canonical form of difference of convex programming. Then, successive convex approximation (SCA) is used to determine a locally optimal solution. For the second suboptimal scheme, we use a high signal-to-noise ratio approximation for the channel dispersion. Then, via novel transformations, we convert the non-convex quality-of-service constraints of the original problem into equivalent second-order-cone constraints. Our simulation results reveal that the proposed resource allocation algorithm design facilitates URLLC in MEC systems, and yields significant power savings compared to three baseline schemes. Moreover, our simulation results show that the proposed suboptimal algorithms offer different trade-offs between performance and complexity and attain an excellent performance at comparatively low complexity.
CRIS-Team WoS Importer:2022-11-25

Optimal storage-aided wind generation integration considering ramping requirements - Xiang, Lin; Ng, Derrick Wing Kwan; Lee, William; Schober, Robert (2013 IEEE International Conference on Smart Grid Communications, SmartGridComm 2013, 2013)
Large-scale integration of intermittent wind energy can put a large burden on the utility company in balancing system demand and supply. As more and more dispersed wind energy suppliers connect to the system for electricity supply, the power system suffers from increased operation cost and risk caused by the discrepant interests of energy suppliers and the utility company. Energy suppliers may only concern about maximizing their own profits by pushing as much energy into the grid as possible, while neglecting the risk of steep ramps in wind generation. In this paper, exploiting the two-way communication capability in smart grid, we propose interactive ramp control of wind energy integration by aligning the individual pursuits of the energy suppliers and the utility company for social welfare maximization. The optimal wind energy integration and generator ramp control are investigated in an offline social welfare optimization problem assuming full knowledge of future wind energy and load demand. Moreover, the benefits of storage are exploited in our proposed storage-aided generation range adaption scheme to reduce the potential risk caused by inaccurate wind energy forecasts and the ramping latency of slow generators. Furthermore, a suboptimal storage-aided generation range adaption scheme with low computational complexity is presented for online control of wind integration when wind energy forecasts are unavailable. Our simulation results show that interactive ramp control is necessary to achieve efficient and secure wind energy integration and with the aid of storage, the power system's ramping capability can be improved at lower operation cost. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Large-scale integration; Ramp control; Smart grid

Optimal Tomlinson-Harashima precoding for physical layer network coding - Schmidt, Armin Christian; Schober, Robert; Gerstacker, Wolfgang (2013 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2013)
We consider a two-way relaying system employing physical layer network coding in channels suffering from frequency-selective fading. In order to mitigate the distortions introduced by the channel, Tomlinson-Harashima precoding is applied at the source nodes. We introduce an optimal precoding scheme that provides intersymbol interference free source-to-relay transmission without requiring identical overall channel impulse responses, which is in contrast to previously proposed equalization approaches. The performance of our novel approach is compared against that of a benchmark precoding scheme, motivated by the optimal decision-feedback equalization for physical layer network coding, which creates identical overall channel impulse responses in order to be able to use identical feedback filters for precoding at both source node

Optimal Transmit Antenna Selection for Massive MIMO Wiretap Channels - Asaad, Saba; Bereyhi, Ali; Rabiei, Amir Masoud; Müller, Ralf; Schaefer, Rafael F. (IEEE Journal on Selected Areas in Communications, 2018)
In this paper, we study the impacts of transmit antenna selection on the secrecy performance of massive MIMO systems. We consider a wiretap setting in which a fixed number of transmit antennas are selected and then confidential messages are transmitted over them to a multi-antenna legitimate receiver while being overheard by a multi-antenna eavesdropper. For this setup, we derive an accurate approximation of the instantaneous secrecy rate. Using this approximation, it is shown that in some wiretap settings under antenna selection the growth in the number of active antennas enhances the secrecy performance of the system up to some optimal number and degrades it when this optimal number is surpassed. This observation demonstrates that antenna selection in some massive MIMO settings not only reduces the RF-complexity, but also enhances the secrecy performance. We then consider various scenarios and derive the optimal number of active antennas analytically using our large-system approximation. Numerical investigations show an accurate match between simulations and the analytic results.
Keywords: Massive MIMO wiretap channel; Physical layer security; Transmit antenna selection

Optimal Transmit Strategy for MIMO WPT Systems with Non-linear Energy Harvesting - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (Proceedings - 17th Annual International Conference on Distributed Computing in Sensor Systems, DCOS 2021, 2021)
In this paper, we study multiple-input multiple-output (MIMO) wireless power transfer (WPT) systems, where the energy harvesting (EH) node is equipped with multiple nonlinear rectennas. We characterize the optimal transmit strategy by the optimal distribution of the transmit symbol vector that maximizes the average harvested power at the EH node subject to a constraint on the power budget of the transmitter. We show that the optimal transmit strategy employs scalar unit-norm input symbols with arbitrary phase and two beamforming vectors, which are determined as solutions of a non-convex optimization problem. To solve this problem, we propose an iterative algorithm based on a two-dimensional grid search, semi-definite relaxation, and successive convex approximation. Our simulation results reveal that the proposed MIMO WPT design significantly outperforms two baseline schemes based on a linear EH model and a single beamforming vector, respectively. Finally, we show that the average harvested power grows linearly with the number of rectennas at the EH node and saturates for a large number of TX antennas.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Energy harvesting; Information Theory; Power Transfer

Optimal Transmit Strategy for Multi-User MIMO WPT Systems With Non-Linear Energy Harvesters - Shanin, Nikita; Schober, Robert; Cottatellucci, Laura (IEEE Transactions on Communications, 2022)
In this paper, we study multi-user multi-antenna wireless power transfer (WPT) systems, where each antenna at the energy harvesting (EH) nodes is connected to a dedicated non-linear rectifier. We propose optimal transmit strategies which maximize a weighted sum of the average harvested powers at the EH nodes subject to a constraint on the power budget of the transmitter. First, for multiple-input single-output (MISO) WPT systems, we prove that the optimal strategy employs maximum ratio transmission (MRT) beamforming and scalar symbols with arbitrary phases and discrete amplitudes following a probability density function (pdf) with at most two mass points. Then, we prove that for single-input multiple-output (SIMO) WPT systems, the optimal transmit symbol amplitudes are discrete random variables, whose pdf also has no more than two mass points. For general multi-user MIMO WPT, we show that the optimal transmit strategy employs scalar unit-norm symbols with arbitrary phases and at most two beamforming vectors. To determine these vectors, we formulate a non-convex optimization problem and obtain an optimal solution based on monotonic optimization. Since the computational complexity of the optimal solution is high, we propose a low-complexity iterative algorithm to obtain a suboptimal solution, which achieves near-optimal performance. Our simulation results reveal that the proposed transmit strategy for multi-user MIMO WPT systems outperforms baseline schemes based on a linear EH model and a single beamforming vector. For a given transmit power budget, we show that the harvested power saturates when increasing the number of transmit antennas. Finally, we observe that the harvested power region spanned by multiple EH nodes is convex and the power harvested at one EH node can be traded for a higher harvested power at the other node

Optimal Tx-BF for MIMO SC-FDE Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay Kishore (IEEE Communications Letters, 2013)
Transmit beamforming (Tx-BF) for multiple-input multiple-output (MIMO) channels is an effective means to improve system performance. In frequency-selective channels, Tx-BF can be implemented in combination with single-carrier frequency-domain equalization (SC-FDE) to combat inter-symbol interference. In this paper, we consider the optimal design of the Tx-BF matrix for a MIMO SC-FDE system employing a linear minimum mean square error (MSE) receiver. We formulate the Tx-BF optimization problem as the minimization of a general function of the stream MSEs, subject to a transmit power constraint. The optimal structure of the Tx-BF matrix is obtained in closed form and an efficient algorithm is proposed for computing the optimal power allocation. Our simulation results validate the excellent performance of the proposed scheme in terms of uncoded bit-error rate and achievable bit rat

Optimization-Based Phase-Shift Codebook Design for Large IRSs - Ghanem, Walid; Jamali, Vahid; Schellmann, Malte; Cao, Hanwen; Eichinger, Joseph; Schober, Robert (IEEE Communications Letters, 2023)
In this letter, we focus on large intelligent reflecting surfaces (IRSs) and propose a new codebook construction method to obtain a set of pre-designed phase-shift configurations for the IRS unit cells. Since the complexity of online optimization and the overhead for channel estimation scale with the size of the phase-shift codebook, the design of small codebooks is of high importance. We consider both continuous and discrete phase-shift designs and formulate the codebook construction as optimization problems. To solve the optimization problems, we propose an optimal algorithm for the discrete phase-shift design and a locally optimal solution for the continuous design. Simulation results show that the proposed algorithms facilitate the construction of codebooks of different sizes and with different beamwidths. Moreover, the performance of the discrete phase-shift design with 2-bit quantization is shown to approach that of the continuous phase-shift design. Finally, our simulation results show that the proposed designs enable large transmit power savings compared to the existing linear and quadratic codebook designs.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Intelligent reflecting surfaces (IRSs); optimization problem; phase-shift codebook

Optimization of Aggregate Capacity of PEVs for Frequency Regulation Service in Day-Ahead Market - Yao, Enxin; Wong, Vincent W.S.; Schober, Robert (IEEE Transactions on Smart Grid, 2016)
An aggregator can coordinate plug-in electric vehicles (PEVs) to provide frequency regulation service to an independent system operator (ISO). The aggregator can participate in the electricity markets of ISOs which provide economic incentives for PEV frequency regulation service. While the ISOs typically use forward market [e.g., day-ahead market (DAM)] to trade frequency regulation service, the available regulation capacity of an aggregator is subject to the random arrival and departure of the PEVs. In the DAM, the aggregator submits a bid to indicate its available capacity on the next day. This motivates us to study the problem of how an aggregator determines its bid in the DAM, given the uncertainty of the available regulation capacity of the PEVs. The DAM is used to trade the frequency regulation capacity in California ISO (CAISO) and New York ISO (NYISO). We consider two types of DAMs based on the market rules of CAISO and NYISO. For the first type, the exact amount of regulation capacity submitted in the DAM needs to be fulfilled on the next day. For the second type, a market participant can settle a shortage of capacity by paying a penalty to the ISO. In both cases, the aggregator can participate in the real-time market to sell extra capacity on the next day. We formulate the problem for determining the bid using stochastic programming. As PEVs have uncertain arrival and departure times, our problem formulation incorporates risk management using the conditional value at risk. Efficient algorithms are proposed for solving the formulated problem. PEV charging data collected in Vancouver, BC, Canada, is used in our simulations. We compare the profit of the aggregator when it participates in the markets of CAISO and NYISO. Our simulation results show that the uncertainty of the PEVs' available capacity has less effect on the profit and financial risk as the number of PEVs increases.<br
Keywords: Frequency control; ISO; Power grids; Uncertainty; Contracts; Batteries; Stochastic processes

Optimization of Delay Diversity for Fading ISI Channels - Schober, Robert; Hehn, Thorsten; Gerstacker, Wolfgang (Conference Proceedings, 2004)
In this paper, we propose an optimized delay diversity (ODD) scheme for fading intersymbol interference (ISI) channels. We derive a cost function for optimization of the ODD transmit filters and we provide a steepest descent algorithm for iterative calculation of the filter coefficients. In addition, an upper bound on the cost function is derived and employed to prove the asymptotic optimality of the generalized DD (ODD) scheme in [1] for very high signal-to-noise (SNR) ratios and transmit filters of maximum length. However, for SNRs of practical interest and reasonable filter lengths the novel ODD scheme significantly outperforms GDD for both optimum and suboptimum equalization.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.optimi

Optimization of Multi-UAV-BS Aided Millimeter-Wave Massive MIMO Networks - Zhu, Lipeng; Zhang, Jun; Xiao, Zhenyu; Schober, Robert (2020 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2020)
CRIS-Team WoS Importer:2021-10-29

Optimized Delay Diversity for Frequency-Selective Fading Channels - Hehn, Thorsten; Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Wireless Communications, 2005)
This paper proposes an optimized delay diversity (ODD) scheme for frequency-selective fading channels. The novel scheme requires knowledge of the channel impulse response (CIR) autocorrelation matrix at the transmitter, but the CIRs themselves have to be available only at the receiver side. A cost function for optimization of the ODD transmit filters is derived and a steepest descent algorithm for iterative calculation of the filter coefficients is provided. In addition, an upper bound on the cost function is derived and employed to prove the asymptotic optimally of the generalized DD (GDD) scheme in [Proc. IEEE Int. Conf. Communications (ICC), (2002) p. 1949] for very high signal-to-noise ratios (SNRs) and transmit filters of maximum length. However, for SNRs of practical interest and reasonable filter lengths, the novel ODD scheme significantly outperforms GDD for both optimum and suboptimum equalizations. It is also shown that, in contrast to the frequency-nonselective case, for frequency-selective channels, transmit diversity schemes designed under the high SNR assumption may perform poorly for practically relevant SNRs. © 2005 IEEE.
UnivIS-Import:2015-03-09:Pub.2005.tech.IE.mobilk.optimi_7
Keywords: Delay diversity (DD); Equalization; Frequency-selective channels; Transmit diversity (TD)

Optimized of Delay Diversity for Linear Equalization - Yiu, Simon; Schober, Robert; Gerstacker, Wolfgang (Conference Proceedings, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.mobilk.optimi

Orthogonal Time Frequency Space Modulation – Part I: Fundamentals and Challenges Ahead - Wei, Zhiqiang; Li, Shuangyang; Yuan, Weijie; Schober, Robert; Caire, Giuseppe (IEEE Communications Letters, 2022)
This letter is the first part of a three-part tutorial on orthogonal time frequency space (OTFS) modulation, which is a promising candidate waveform for future wireless networks. This letter introduces and compares two popular implementations of OTFS modulation, namely the symplectic finite Fourier transform (SFFT)-and discrete Zak transform (DZT)-based architectures. Based on these transceiver architectures, fundamental concepts of OTFS modulation, including the delay-Doppler (DD) domain, DD domain information multiplexing, and its potential benefits, are discussed. Finally, the challenges ahead for OTFS modulation are highlighted. Parts II and III of this tutorial on OTFS modulation focus on transceiver designs and integrated sensing and communication (ISAC), respectively.
CRIS-Team Scopus Importer:2022-10-21
Keywords: delay-Doppler domain; Delays; Demodulation; DZT; Indexes; Modulation; OTFS; SFFT; Symbols; Time-frequency analysis; Transceivers

Orthogonal Time Frequency Space Modulation – Part III: ISAC and Potential Applications - Yuan, Weijie; Wei, Zhiqiang; Li, Shuangyang; Schober, Robert; Caire, Giuseppe (IEEE Communications Letters, 2022)
The first two parts of this tutorial on orthogonal time frequency space (OTFS) modulation have discussed the fundamentals of delay-Doppler (DD) domain communications as well as some advanced technologies for transceiver design. In this letter, we will present an OTFS-based integrated sensing and communications (ISAC) system, which is regarded as an enabling technology in next generation wireless communications. In particular, we illustrate the sensing as well as the communication models for OTFS-ISAC systems. Next, we show that benefiting from time-invariant DD channels, the sensing parameters can be used for inferring the communication channels, leading to an efficient transmission scheme. As both functionalities are realized in the same DD domain, we briefly discuss several promising benefits of OTFS-based ISAC systems, which have not been completely unveiled yet. Finally, a range of potential applications of OTFS for the future wireless networks will be highlighted.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Array signal processing; delay-Doppler domain; Delays; Doppler effect; integrated sensing and communications (ISAC); Linear antenna arrays; OTFS; Receiving antennas; Sensors; Time-frequency analysis

Orthogonal Time Frequency Space Modulation – Part II: Transceiver Designs - Li, Shuangyang; Yuan, Weijie; Wei, Zhiqiang; Schober, Robert; Caire, Giuseppe (IEEE Communications Letters, 2022)
The fundamental concepts and challenges of orthogonal time frequency space (OTFS) modulation have been reviewed in Part I of this three-part tutorial. In this second part, we provide an overview of the state-of-the-art transceiver designs for OTFS systems, with a particular focus on the cyclic prefix (CP) design, window design, pulse shaping, channel estimation, and signal detection. Furthermore, we analyze the performance of OTFS modulation, including the diversity gain and the achievable rate. Specifically, comparative simulations are presented to evaluate the error performance of different OTFS detection schemes, and the advantages of coded OTFS systems over coded orthogonal frequency-division multiplexing (OFDM) systems are investigated.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Channel estimation; Delays; Modulation; OFDM; OTFS; performance analysis; Pulse shaping methods; Shape; transceiver designs; Transceivers

OTFS-NOMA: An Efficient Approach for Exploiting Heterogenous User Mobility Profiles - Ding, Zhiguo; Schober, Robert; Fan, Pingzhi; Vincent Poor, H. (IEEE Transactions on Communications, 2019)
This paper considers a challenging communication scenario, in which users have heterogenous mobility profiles, e.g., some users are moving at high speeds and some users are static. A new non-orthogonal multiple-access (NOMA) transmission protocol that incorporates orthogonal time frequency space (OTFS) modulation is proposed. Thereby, users with different mobility profiles are grouped together for the implementation of NOMA. The proposed OTFS-NOMA protocol is shown to be applicable to both uplink and downlink transmission, where sophisticated transmit and receive strategies are developed to remove inter-symbol interference and harvest both multi-path and multi-user diversity. Analytical results demonstrate that both the high-mobility and the low-mobility users benefit from the application of OTFS-NOMA. In particular, the use of NOMA allows the spreading of the high-mobility users' signals over a large amount of time-frequency resources, which enhances the OTFS resolution and improves the detection reliability. In addition, OTFS-NOMA ensures that low-mobility users have access to bandwidth resources which in conventional OTFS-orthogonal multiple access (OTFS-OMA) would be solely occupied by the high-mobility users. Thus, OTFS-NOMA improves the spectral efficiency and reduces latency.
CRIS-Team Scopus Importer:2019-12-10
Keywords: dual plane multiple access; non-orthogonal multiple access (NOMA); Orthogonal time frequency space (OTFS); uplink and downlink transmission

Outage analysis of q-duplex RF/FSO relaying - Jamali Kooshkghazi, Vahid; Michalopoulos, Diomidis; Uysal, Murat; Schober, Robert (2015 International Symposium on Wireless Communication Systems (ISWCS), 2015)
In this paper, we propose and analyze a novel q-duplex radio frequency/free space optical (RF/FSO) relaying protocol for a mixed RF and hybrid RF/FSO communication system. In our scheme, several mobile users transmit their data over an RF link to a relay node (e.g. a small cell base station) and the relay forwards the information to a destination (e.g. a macro cell base station) over a hybrid RF/FSO backhaul link. The RF links are full-duplex with respect to the FSO link and half-duplex with respect to each other, i.e., either the user-relay RF link or the relay-destination RF link is active. Depending on the channel statistics, the q-duplex relaying protocol may reduce to full-duplex relaying, when the quality of the FSO link is sufficiently high, or to half-duplex relaying, when the FSO link becomes unavailable due to severe atmospheric conditions. We derive an analytical expression for the end-to-end outage probability of the proposed protocol when the fading for the user-relay RF link, the relay-destination RF link, and the relay-destination FSO link are modelled as Rayleigh, Ricean, and Gamma-Gamma distributed, respectively. Our simulation results confirm the analytical derivations and reveal the effectiveness of the proposed q-duplex protocol and its superiority compared to existing schemes.<br
Keywords: Radio frequency; Relays; Mixers; Optical fiber communication; Encoding

Outage capacity of Rayleigh product channels: a free probability approach - Zheng, Zhong; Wei, Lu; Speicher, Roland; Müller, Ralf; Hämäläinen, Jyri; Corander, Jukka (IEEE Transactions on Information Theory, 2017)

Outage Constrained Robust Transmission Design for IRS-aided Secure Communications with Direct Communication Links - Hong, Sheng; Pan, Cunhua; Zhou, Gui; Ren, Hong; Wang, Kezhi (IEEE Transactions on Communications, 2023)
This paper considers an intelligent reflecting surface (IRS) aided secure communication with direct communication links where a legitimate receiver (Bob) served by a base station (BS) is overheard by multiple eavesdroppers (Eves), meanwhile the artificial noise (AN) is incorporated to confuse Eves. Since Eves are not legitimate users, their channels cannot be estimated perfectly. We investigate two scenarios with partial channel state information (CSI) error of only cascaded BS-IRS-Eve channel and full CSI errors of both cascaded BS-IRS-Eve channel and direct BS-Eve channel under the statistical CSI error model. To ensure the security performance under CSI errors, the transmit beamforming, AN spatial distribution at the BS, and phase shifts at IRS are jointly optimized to minimize the transmit power constrained by the minimum data rate requirement of Bob and the outage probability of maximum data rate limitation of Eves. In contrast to existing works, the direct link considered in our work makes the optimization of phase shifts at IRS much more challenging, thus we propose a series of novel and artful mathematical manipulations to tackle this issue. Moreover, the proposed algorithm can be applied for both uncorrelated and correlated CSI errors. Simulations confirm the superiority of our proposed algorithm.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Array signal processing; Channel estimation; Covariance matrices; CSI errors; direct communication link; Intelligent Reflecting Surface (IRS); Minimization; MISO communication; Optimization; outage probability; Receivers; robust transmission design; secure communication

Outphasing Elements for Hybrid Analogue Digital Beamforming and Single-RF MIMO - Gäde, Bernhard; Amon, Michael; Bereyhi, Ali; Fischer, Georg; Müller, Ralf (2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2019)
In conventional Multiple-Input Multiple Output (MIMO) systems, each antenna requires its own Radio Frequency (RF) chain. Since each RF-chain includes several active components that have to be synchronised, costs and complexity become restrictive. The outphasing MIMO and the outphasing precoder architectures are possible approaches to mitigate this problem. The core of both architectures are Outphasing Elements (OEs), which are used to form a electronically controllable, passive antenna feed network. In this paper, these OEs are analysed with respect to component tolerances. The feasibility of the outphasing concept is demonstrated by the implementation of a hardware prototype OE. The performance of this prototype is measured and compared to theoretical predictions with good agreemen
Keywords: outphasing; MIMO; hybrid analog digital precoding; beamforming; sensitivity

Overcoming noise and multiuser interference in diffusive molecular communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (Proceedings of the 1st ACM International Conference on Nanoscale Computing and Communication, NANOCOM 2014, 2014)
In this paper, weighted sum detectors in Diffusion molecu- lar communication are assessed for their performance in the presence of multiuser interference and continuously-emitting noise sources that release molecules over finite time intervals. Weighted sum decision feedback detectors are proposed to address the limitations imposed by intersymbol and mul- Tiuser interference. Weighted sum detectors with matched filter weights are shown to be more robust to noise and in- Terference than equal weight detectors, and adding decision feedback enables additional improvements in performance.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Diffusion channel; Matched filter; Molecular communication; Multiuser interference; Weighted sum detector

Oversampled Adaptive Sensing - Müller, Ralf; Bereyhi, Ali; Mecklenbräuker, Christoph F. (Information Theory and Applications Workshop (ITA), 2018)
We develop a Bayesian framework for sensing which adapts the sensing time and/or basis functions to the instantaneous sensing quality measured in terms of the expected posterior mean-squared error. For sparse Gaussian sources a significant reduction in average sensing time and/or mean-squared error is achieved in comparison to non-adaptive sensing. For compression ratio 3, a sparse 10% Gaussian source and equal average sensing times, the proposed method gains about 2 dB over the performance bound of optimum compressive sensing, about 3 dB over non-adaptive 3-fold oversampled orthogonal sensing and about 6 to 7 dB to LASSO-based recovery schemes while enjoying polynomial time complexity. We utilize that in the presence of Gaussian noise the mean-squared error conditioned on the current observation is proportional to the derivative of the conditional mean estimate with respect to this observation.
Keywords: Adaptive sensing; Bayesian estimation

Oversampled Adaptive Sensing via a Predefined Codebook - Bereyhi, Ali; Asaad, Saba; Müller, Ralf (2021 1st IEEE International Online Symposium on Joint Communications and Sensing, JC and S 2021, 2021)
Oversampled adaptive sensing (OAS) is a Bayesian framework recently proposed for effective sensing of structured signals in a time-limited setting. In contrast to the conventional blind oversampling, OAS uses the prior information on the signal to construct posterior beliefs sequentially. These beliefs help in constructive oversampling which iteratively evolves through a sequence of time sub-frames. The initial studies of OAS consider the idealistic assumption of full control on sensing coefficients which is not feasible in many applications. In this work, we extend the initial investigations on OAS to more realistic settings in which the sensing coefficients are selected from a predefined set of possible choices, referred to as the codebook. We extend the OAS framework to these settings and compare its performance with classical non-adaptive approaches.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Bayesian inference; Oversampled adaptive sensing; sparse recovery; stepwise regression

Oversampled adaptive sensing with random projections: Analysis and algorithmic approaches - Müller, Ralf; Bereyhi, Ali; Mecklenbräuker, Christoph F. (IEEE International Symposium on Signal Processing and Information Technology, 2018)

PAPR-Limited Precoding in Massive MIMO Systems with Reflect- and Transmit-Array Antennas - Bereyhi, Ali; Jamali, Vahid; Müller, Ralf; Fischer, Georg; Schober, Robert; Tulino, Antonia M. (CONFERENCE RECORD OF THE 2019 FIFTY-THIRD ASILOMAR CONFERENCE ON SIGNALS, SYSTEMS & COMPUTERS, 2019)
CRIS-Team WoS Importer:2020-07-31

PAPR of Variable-Gain and Fixed-Gain Amplify and Forward Relaying - Michalopoulos, Diomidis; Hadzi-Velkov, Zoran; Karagiannidis, George K.; Schober, Robert (SCC 2013; 9th International ITG Conference on Systems, Communication and Coding, 2013)
Most works on amplify and forward (AF) relaying assume that the relay obtains perfect channel state information (CSI) of the source-relay channel. This renders variable-gain relaying (VGR) an attractive technique, as the relay can ideally invert the channel at its input and thus ensure constant output power. What happens to the output power, however, if the CSI at the input is outdated? As an attempt to answer this question, we introduce a study of AF relaying under a novel perspective. This involves the use of the well-known peak-to-average-powerratio (PAPR) for capturing the negative effects of imperfect channel inversion at the relay. The imperfect channel inversion, caused by imperfect CSI at the relay, results in using the power amplifier in its non-linear region, which induces signal distortion. In this regard, expressions for the complementary cumulative distribution function (CCDF) of the PAPR at the relay's output are derived. The analysis involves VGR with outdated CSI at its input, as well as its simpler counterpart which uses only statistical CSI, namely fixed-gain relaying (FGR). Our results manifest that there exists a threshold on the reliability of the CSI at the relay, below which VGR looses its advantage over FGR in being more efficient in terms of the potential signal distortion at the relay, caused by amplification in the non-linear regio

Performance Analysis and Design of STBC's for Fading ISI Channels - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (Conference Proceedings, 2002)
In this paper, space-time block-coded transmission over fading intersymbol interference (ISI) channels is investigated. A lower bound on the pairwise error probability for optimum detection is given. Also an approximation for the bit error rate is derived and compared with simulation results for maximum-likelihood sequence estimation (MLSE) for the GSM/EDGE (Enhanced Data Rates for GSM Evolution) system. Furthermore, a novel design rule for space-time block codes (STBC's) with arbitrary rate for fading ISI channels is provided. A corresponding full-rate code is designed and shown to yield higher performance than Alamouti's code. It is demonstrated that for fading channels with L independent impulse response coefficients, full-rate STBC's designed for the flat fading channel can achieve at most a diversity order of (NT + L - 1)NR if NT transmit antennas and NR receive antennas are used. On the other hand, the maximum diversity order employing the proposed code design rule is LNT NR.
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.mobilk.perfor
Keywords: Approximation Theory; Bit error rate; Block codes; Computer simulation; Error analysis; Fading (radio); Global system for mobile communication; Intersymbol interference; Maximum likelihood estimation; Receiving antennas; Transceivers

Performance Analysis and Design of STBC's for Frequency-Selective Fading Channels - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (IEEE Transactions on Wireless Communications, 2004)
In this paper, space-time block-coded transmission over frequency-selective fading channels is investigated. A lower bound for the pairwise error probability for optimum detection is given. Also, an approximation for the bit-error rate is derived and compared with simulation results for maximum-likelihood sequence estimation (MLSE) for the GSM/EDGE (Enhanced Data Rates for GSM Evolution) system. Furthermore, a novel design rule for space-time block codes (STBCs) for frequency-selective fading channels is provided. A corresponding code is designed and shown to yield higher performance than Alamouti's code. It is demonstrated that for fading channels with L independent impulse response coefficients, STBCs designed for the flat fading channel can achieve at most a diversity order of (NT + L - 1) NR if NT transmit antennas and NR receive antennas are used. On the other hand, the maximum diversity order employing the proposed code design rule is LNTNR. <br
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.mobilk.perfor
Keywords: Bit-error rate (BER) analysis; Equalization; Frequency-selective fading channels; Space-time codes

Performance Analysis of 1-Bit Quantization with Oversampling for Higher-Order Constellations - Forsch, Christian; Zillmann, Peter; Alrabadi, Osama; Brueck, Stefan; Gerstacker, Wolfgang (Latin-American Conference on Communications (LATINCOM), 2022)
In this work, we consider a real additive white Gaussian noise (AWGN) channel with 1-bit quantization and oversampling at the receiver side for transmission with higher-order amplitude-shift keying (ASK) constellations. We analytically compute the statistics of the detection variable for arbitrary real inputs and present an optimal as well as a suboptimal detection scheme. Furthermore, we evaluate the symbol error rate (SER) for a 4-ary ASK constellation and different detection schemes as well as oversampling factors. The SER curves show that a reliable communication can be established for higher-order ASK constellations when the oversampling factor is sufficiently high. Then, we optimize the 4-ASK constellation with respect to the SER. The results show that the minimum SER can be decreased significantly by increasing the distance between the inner and outer points of the input constellation. Finally, the results are extended to complex-valued constellations.<br

Performance analysis of a multi-hop power line communication system over log-normal fading in presence of impulsive noise - Dubey, Ankit; Mallik, Ranjan K.; Schober, Robert (IET Communications, 2015)
The authors present a study on the end-to-end average bit error rate (BER), the average channel capacity and the outage performance of a multi-hop power line communication (PLC) system equipped with decode-and-forward (DF) relays. To combat the issue of distance dependent signal attenuation, multi-hop data transmission has recently been introduced for PLC systems. However, apart from the distance dependent signal attenuation, PLC systems also suffer from (i) the variation in signal amplitude (fading) because of reflections and (ii) impulsive noise. Thus, in this study, the channel for each hop of the multi-hop PLC system is modelled by a log-normal fading amplitude, which is clubbed to a distance dependent signal attenuation factor. To consider the effect of the impulsive noise along with the background noise, the additive noise at each node is modelled by a Bernoulli-Gaussian process. Analytical expressions for the end-to-end average BER for binary phase-shift keying, the average channel capacity and the outage probability are obtained. The merit of the multi-hop PLC system over a conventional direct transmission PLC system for fixed transmission power is shown through numerical results. The authors' results show that with increasing number of DF relays, the end-to-end average BER, the average channel capacity and the outage performance improve.<br

Performance analysis of a power line communication system employing selection combining in correlated log-normal channels and impulsive noise - Dubey, Ankit; Mallik, Ranjan K.; Schober, Robert (IET Communications, 2014)
The authors analyse an L -channel selection combining (SC) scheme for a power line communication (PLC) system with binary phase-shift keying. The focus is on improving the reliability in data transfer of the system instead of improving the data rate. To enhance the reliability in data transfer, multiple PLC channels are used to send the same information-bearing signal to the receiver. The L PLC channels are subject to log-normal fading, which is modelled by a multivariate log-normal distribution with an exponential correlation. The channels are also corrupted by additive impulsive noise as well as thermal noise. To consider the effect of both types of noises, they adopt a Gaussian mixture noise model, in which the additive noise samples are taken from a Bernoulli-Gaussian process. The system performance is evaluated in terms of the average bit error rate and the average channel capacity, for which approximate closed form expressions are derived. Numerical results showing the impact of the number of PLC channels, the amount of correlation, the noise scenarios, and the fading environments on the performance are presented. The authors' results show that the performance improves with increasing number of PLC channels; however, the amount of improvement reduces with increasing channel correlation.<br

Performance analysis of asynchronous optical code division multiple access with spectral-amplitudecoding - Sedaghat, Mohammad Ali; Müller, Ralf; Marvasti, Farokh (IET Communications, 2014)
In this study, the performance of a spectral-amplitude-coding optical code division multiple access (SAC-OCDMA) system in the asynchronous regime is evaluated using a Gaussian approximation of the decision variable for codes with fixed cross-correlation used in SAC-OCDMA systems. The authors consider the effect of phase-induced intensity noise (PIIN), thermal noise and shot noise. Moreover, the validity of the Gaussian approximation is confirmed by a Kolmogorov-Smirnov fitness test. For sake of comparison, the bit error rate (BER) of the asynchronous SAC-OCDMA system is also plotted numerically in comparison with the BER of the synchronous SAC-OCDMA. They show that a SAC-OCDMA system without any time management for the users, that is, the asynchronous regime, has a better performance than the synchronous SAC-OCDMA when PIIN effect exists. © The Institution of Engineering and Technology 2014.

Performance Analysis of Coded OTFS Systems over High-Mobility Channels - Li, Shuangyang; Yuan, Jinhong; Yuan, Weijie; Wei, Zhiqiang; Bai, Baoming; Ng, Derrick Wing Kwan (IEEE Transactions on Wireless Communications, 2021)
Orthogonal time frequency space (OTFS) modulation is a recently developed multi-carrier multi-slot transmission scheme for wireless communications in high-mobility environments. In this paper, the error performance of coded OTFS modulation over high-mobility channels is investigated. We start from the study of conditional pairwise-error probability (PEP) of the OTFS scheme, based on which its performance upper bound of the coded OTFS system is derived. Then, we show that the coding improvement for OTFS systems depends on the squared Euclidean distance among codeword pairs and the number of independent resolvable paths of the channel. More importantly, we show that there exists a fundamental trade-off between the coding gain and the diversity gain for OTFS systems, i.e., the diversity gain of OTFS systems improves with the number of resolvable paths, while the coding gain declines. Furthermore, based on our analysis, the impact of channel coding parameters on the performance of the coded OTFS systems is unveiled. The error performance of various coded OTFS systems over high-mobility channels is then evaluated. Simulation results demonstrate a significant performance improvement for OTFS modulation over the conventional orthogonal frequency division multiplexing (OFDM) modulation over high-mobility channels. Analytical results and the effectiveness of the proposed code design are also verified by simulations with the application of both classical and modern codes for OTFS systems.
CRIS-Team Scopus Importer:2021-06-11
Keywords: code design; diversity analysis; fading channels; high-mobility; OTFS modulation

Performance Analysis of Cooperative NOMA with Dynamic Decode-and-Forward Relaying - Zhou, Yong; Wong, Vincent W. S.; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
Non-orthogonal multiple access (NOMA) is a promising multiple access technique, which exploits the power domain to enhance the spectral efficiency of the fifth generation (5G) wireless networks. In this paper, we propose a dynamic decode-and-forward (DDF) based cooperative NOMA scheme for downlink transmission to enhance the reception reliability of spatially random users. In DDF-based cooperative NOMA, the user closer to the base station decodes the superimposed mixture of the users' signals received from the base station based on partial reception, and then forwards the signal intended for the far user. To avoid the need for instantaneous channel state information at the base station, we consider random user pairing, where the users are randomly paired for NOMA transmission. Tools from point process theory are utilized to derive the outage probability of the proposed DDF-based cooperative NOMA scheme. Simulation results validate the performance analysis and demonstrate the performance gains of the proposed DDF-based cooperative NOMA scheme over conventional NOMA and cooperative NOMA.<br
Keywords: NOMA; Base stations; Relays; Downlink; Power system reliability; Probability; Signal to noise ratio

Performance analysis of large dual antenna array systems with binary modulation - Müller, Ralf (Proceedings 2003 IEEE International Symposium on Information Theory (ISIT), 2003)
Channel capacity and minimum probability of error for communication via large dual antenna arrays is calculated for binary modulation taking into account statistical dependencies among channel coefficients using the correlation model introduced in [1]. Calculations rely upon the replica method developed in statistical physics [2

Performance Analysis of Near-Optimal Energy Buffer Aided Wireless Powered Communication - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
In this paper, we consider a wireless powered communication system, where an energy harvesting (EH) node harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We investigate two simple online transmission policies for the EH node, namely a best-effort policy and an on-off policy, which do not require knowledge of the EH profile nor channel knowledge. In particular, for both policies, the EH node transmits in each time slot with a constant desired power if sufficient energy is available in its energy buffer. Otherwise, the node transmits with the maximumpossible power in the best-effort policy and remains silent in the on-off policy. For both policies, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite-and infinite-size energy buffers. We provide this limiting distribution in closed form for a Nakagami-m fading DL channel and analyze the outage probability for a Nakagami-m fading UL channel. All derived analytical results are not limited to EH via RF WPT but are applicable for any independent and identically distributed EH process from e.g. solar and wind energy. Our results reveal that, for low-to-medium outage probabilities, the best-effort policy is superior to the on-off policy and the optimal UL transmit power of the EH node that minimizes the outage probability is always less than the average harvested power. The opposite behaviour is observed for high outage probabilities. Furthermore, we show that the minimum outage probability of the two proposed policies is near-optimal.
Keywords: Energy harvesting; energy storage; Markov processes; wireless power transmission

Performance analysis of optimal channel estimation and multiuser detection in a randomly-spread CDMA channel - Takeuchi, Keigo; Vehkapera, Mikko; Tanaka, Toshiyuki; Müller, Ralf (Journal of Systems Science & Complexity, 2010)
This paper analyzes performance of optimal channel estimation and multiuser detection (MUD) in a block-fading code-division multiple-access (CDMA) channel on the assumptions of random spreading and large-system limit, by using the replica method developed in statistical mechanics. The authors find that the asymptotic spectral efficiency of the linear minimum mean-squared error (LMMSE) MUD which was proposed and analyzed by Evans and Tse in 2000 is indistinguishable from that of the optimal MUD for small system loads. Our results imply that performance of MUD scarcely improves even if one spends more computational cost than that of the LMMSE MUD, i. e., at most the cube of the number of users, on the above-described conditions. © 2010 Institute of Systems Science, Academy of Mathematics and Systems Science, CAS and Springer-Verlag Berlin Heidelberg.
Keywords: Channel estimation; Code-division multiple-access (CDMA) systems; Multiuser detection; Replica method; Spectral efficiency

Performance Analysis of OSTBC Relaying in AF MIMO Relay Systems With Imperfect CSI - Arti, M. K.; Mallik, Ranjan K.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2014)
In this paper, the transmission of orthogonal space-time block codes (OSTBCs) in amplify-and-forward (AF) multiple-input-multiple-output (MIMO) relay networks, with imperfect channel state information (CSI), is considered. Individual channel estimation and time-efficient cascaded (for estimating the product of channel matrices) channel estimation protocols are used for estimating the channel matrices required for decoding of OSTBC data at the destination. We derive tight approximations for the moment-generating function (m.g.f.) of the received signal-to-noise ratio at the destination node with imperfect CSI, by ignoring higher order noise terms, in Rayleigh fading. Using the derived m.g.f. expression, we obtain the analytical symbol error rate (SER) of the AF MIMO relay system for general OSTBCs with M-ary phase-shift keying constellation. The diversity order of the MIMO OSTBC relay system is also derived for some special cases by using the SER expression.<br
Keywords: Relays; MIMO; Channel estimation; Decoding; Noise; Protocols; Approximation methods

Performance Analysis of Wireless Powered Communication with Finite/Infinite Energy Storage - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (International Conference on Communications ICC, 2015)
In this paper, we consider an energy harvesting (EH) node which harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We consider a simple transmission policy, which accounts for the fact that in practice the EH node may not have knowledge of the EH profile nor of the UL channel state information. In particular, in each time slot, the EH node transmits with either a constant desired power or a lower power if not enough energy is available in its energy buffer. For this simple policy, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite-and infinitesize energy buffers. Moreover, we take into account imperfections of the energy buffer and the circuit power consumption of the EH node. For a Rayleigh fading DL channel, we provide the limiting distribution of the energy buffer content in closed form. In addition, we analyze the average error rate (AER) and the outage probability of a Rayleigh faded UL channel and show that the diversity order is not affected by the finite capacity of the energy buffer. Our results reveal that, except for high outage probabilities and high AERs, the optimal transmit power by the EH node is less than the average harvested power and increases with the capacity of the energy buffer.
Keywords: Buffer storage; Limiting; Energy storage; Fading; Probability density function; Approximation methods; Wireless communication

Performance limits of massive MIMO systems based on Bayes-optimal inference - Wen, Chao-Kai; Wu, Yongpeng; Wong, Kai-Kit; Schober, Robert; Ting, Pangan (2015 IEEE International Conference on Communications (ICC), 2015)
This paper gives a replica analysis for the minimum mean square error (MSE) of a massive multiple-input multipleoutput (MIMO) system by using Bayesian inference. The Bayesoptimal estimator is adopted to estimate the data symbols and the channels from a block of received signals in the spatial-temporal domain. We show that using the Bayes-optimal estimator, the interfering signals from adjacent cells can be separated from the received signals without pilot information of the interfering signals. In addition, the MSEs with respect to the data symbols and the channels of the desired users decrease with the number of receive antennas and the number of data symbols, respectively. There are no residual interference terms that remain bounded away from zero as the numbers of receive antennas and data symbols approach infinity.<br
Keywords: Estimation; Channel estimation; MIMO; Interference; Antennas; Wireless communication; Receivers

Performance of an iterative multi-user receiver for MIMO-OFDM systems in a real indoor scenario - Rossi, P. Salvo; Hammarberg, P.; Tufvesson, F.; Edfors, O.; Almers, P.; Kolmonen, V. -M.; Koivunen, J.; Haneda, K.; Müller, Ralf (2008 IEEE Global Telecommunications Conference, GLOBECOM 2008, 2008)
This paper aims at validation of an iterative receiver for Multiple-Input Multiple-Output with Orthogonal Frequency Division Multiplexing (MIMO-OFDM) systems using real-measurement channel data from an indoor scenario. The receiver performs iterative Multi-User Detection (MUD) and Channel Estimation (CE) via soft information from the single- user decoders. The Channel measurements were performed for a dynamic dual MIMO link scenario. The case with two users with multiple antennas interfering each other is considered. CE at the receiver exploits the frequency correlation of the MIMO link. Simulation results for the performance are shown in terms of Bit- Error Rate (BER) vs. Signal-to-Noise Ratio (SNR). Performance for the whole system are provided and compared with respect to the case of Perfect Channel-State Information (PCSI) at the receiver, as well as for the single user. We also provide an analysis of BER with respect to Signal-to-Interference Ratio (SIR). CE performance are evaluated in terms of Normalized Mean Square Error (NMSE). © 2008 IEEE.

Phase Noise Robust Terahertz Communications - Forsch, Christian; Alrabadi, Osama; Brueck, Stefan; Gerstacker, Wolfgang (2022 IEEE 95th Vehicular Technology Conference: (VTC2022-Spring), 2022)
Terahertz (THz) communications is envisaged as one of the key enablers for beyond fifth-generation (5G) wireless networks because of its massive bandwidth opportunities. However, wireless transmission at such high frequencies comes with its own challenges, including the increased power consumption and hardware complexity, the challenging task of channel estimation, as well as the strong impact of phase noise (PN). In this work, we consider coherent and noncoherent transmission techniques based on spatial modulation (SM) for the THz channel with PN impairments. SM schemes carry part of the information by the baseband modulated symbols and part by the used antenna or subarray index. Our investigations show that the index detection in the SM chain remains robust against the strong PN impairment, unlike the symbol detection which deteriorates as the modulation order increases. The robustness of index detection under PN coupled with low modulation order renders SM an attractive candidate for THz communications. Under strong PN, space-shift keying (SSK) schemes, i.e., SM schemes which solely transmit index information, are preferable<br

Physical layer security for massive MIMO systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (Institution of Engineering and Technology, 2017)
The chapter is organised as follows. In Sections 5.1 and 5.2, we briefly review the fundamentals of massive MIMO and physical layer security, respectively. In Section 5.3, we motivate the chapter by illustrating why we consider physical layer security for massive MIMO systems. The considered model and the performance evaluation metrics for secure massive MIMO systems are introduced in Sections 5.4 and 5.5, respectively. Section 5.6 studies linear precoding for downlink secure massive MIMO transmission. In Section 5.7, we conclude with abrief summary of this chapter.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Alamouti coding; Antenna arrays; Antenna selection strategies; Correlation; Full-duplex wiretap channels; Imperfect feedback; Low feedback overhead; Low hardware complexity; MIMO communication; Multiple-input multiple-output wiretap channels; Physical layer security; Secrecy performance; Secure transmissions; Space-time block codes; TAS; Telecommunication security; Transmit antenna selection; Transmitting antennas

Physical layer security for massive MIMO systems impaired by phase noise - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (2016 IEEE 17th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2016)
In this paper, we investigate the impact of phase noise on the secrecy performance of downlink massive MIMO systems in the presence of a passive multiple-antenna eavesdropper. Thereby, for the base station (BS) and the legitimate users, the effect of multiplicative phase noise is taken into account, whereas the eavesdropper is assumed to employ ideal hardware. We derive a lower bound for the ergodic secrecy rate of a given user when matched filter data precoding and artificial noise transmission are employed at the BS. Based on the derived analytical expression, we investigate the impact of the various system parameters on the secrecy rate. Our analytical and simulation results reveal that distributively deployed local oscillators (LOs) can achieve a better performance than one common LO for all BS antennas as long as a sufficient amount of power is assigned for data transmission.<br
Keywords: Phase noise; MIMO; Hardware; Downlink; Precoding; Channel estimation; Data communication

Physical layer security in SWIPT systems with nonlinear energy harvesting circuits - Su, Yuqing; Ng, Derrick Wing Kwan; Schober, Robert (wiley, 2018)
The discrepancy between the properties of practical nonlinear harvesting circuits and the linear harvesting model conventionally assumed in the literature may cause a severe mismatch for resource allocation, leading to insecure simultaneous wireless information and power transfer (SWIPT) systems. This chapter presents novel beamforming designs enabling secure SWIPT based on a practical nonlinear energy harvesting model. It introduces the adopted channel model and a practical nonlinear RF-based energy harvesting model. The chapter studies the beamforming design for secure communication in SWIPT systems taking into account the impact of imperfect channel state information (CSI). Simulation results are presented to illustrate the performance of proposed resource allocation algorithm. The chapter aims to maximize the system achievable secrecy rate while guaranteeing a required minimum harvested power at the energy harvesting receivers (ERs).
CRIS-Team Scopus Importer:2022-06-05
Keywords: Energy harvesting receivers; Imperfect channel state information; Resource allocation; RF-based energy harvesting model; Simulation results; SWIPT systems

Physical Modeling using Recurrent Neural Networks with Fast Convolutional Layers - Parker, Julian; Schlecht, Sebastian J.; Rabenstein, Rudolf; Schäfer, Maximilian (25th International Conference on Digital Audio Effects (DaFX22), 2022)

Physics-based Modeling and Scalable Optimization of Large Intelligent Reflecting Surfaces - Najafi, Marzieh; Jamali, Vahid; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2020)
Intelligent reflecting surfaces (IRSs) have the potential to transform wireless communication channels into smart reconfigurable propagation environments. To realize this new paradigm, the passive IRSs have to be large, especially for communication in far-field scenarios, so that they can compensate for the large end-to-end path-loss, which is caused by the multiplication of the individual path-losses of the transmitter-to-IRS and IRS-to-receiver channels. However, optimizing a large number of sub-wavelength IRS elements imposes a significant challenge for online transmission. To address this issue, in this paper, we develop a physics-based model and a scalable optimization framework for large IRSs. The basic idea is to partition the IRS unit cells into several subsets, referred to as tiles, model the impact of each tile on the wireless channel, and then optimize each tile in two stages, namely an offline design stage and an online optimization stage. For physics-based modeling, we borrow concepts from the radar literature, model each tile as an anomalous reflector, and derive its impact on the wireless channel for a given phase shift by solving the corresponding integral equations for the electric and magnetic vector fields. In the offline design stage, the IRS unit cells of each tile are jointly designed for the support of different transmission modes, where each transmission mode effectively corresponds to a given configuration of the phase shifts that the unit cells of the tile apply to an impinging electromagnetic wave. In the online optimization stage, the best transmission mode of each tile is selected such that a desired quality-of-service (QoS) criterion is maximized. We consider an exemplary downlink system and study the minimization of the base station (BS) transmit power subject to QoS constraints for the users. Since the resulting mixed-integer programming problem for joint optimization of the BS beamforming vectors and the tile transmission modes is non-convex, we derive two efficient suboptimal solutions, which are based on alternating optimization and a greedy approach, respectively. We show that the proposed modeling and optimization framework can be used to efficiently optimize large IRSs comprising thousands of unit cells.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Optimization; Quality of service; Radar cross-sections; Receivers; Solid modeling; Surface waves; Wireless communication

Physics-based Modeling of Large Intelligent Reflecting Surfaces for Scalable Optimization - Najafi Kalyani, Marzieh; Jamali, Vahid; Schober, Robert; Poor, H. Vincent (2020 54TH ASILOMAR CONFERENCE ON SIGNALS, SYSTEMS, AND COMPUTERS, 2020)
CRIS-Team WoS Importer:2021-09-03

pi/2-shifted phase shift keying on the hypersphere: Transmitter and receiver algorithms - Rachinger, Christoph; Sedaghat, Mohammad Ali; Müller, Ralf; Huber, Johannes (IEEE International Conference on Communications, 2017)

Pilot decontamination using combined angular and amplitude based projections in massive MIMO systems - Yin, Haifan; Cottatellucci, Laura; Gesbert, David; Müller, Ralf; He, Gaoning (16th IEEE International Workshop on Signal Processing Advances in Wireless Communications, SPAWC 2015, 2015)
We address the problem of noise and interference corrupted channel estimation in massive MIMO systems. Interference, which originates from pilot reuse (or contamination), can in principle be discriminated from the desired channels upon observing the distributions of path angles and amplitudes. In this paper we propose novel robust channel estimation algorithms exploiting path diversity in both angle and amplitude domains, relying on a suitable combination of a subspace projection and MMSE estimation. The proposed estimator improves on past methods in a wide range of system and topology scenarios.
Keywords: Antennas; Base stations; Channel estimation; Discrete Fourier transforms; Interference; MIMO; Wireless communication

Pilot Spoofing Attack by Multiple Eavesdroppers - Huang, Ke-Wen; Wang, Hui-Ming; Wu, Yongpeng; Schober, Robert (IEEE Transactions on Wireless Communications, 2018)
In this paper, we investigate the design of a pilot spoofing attack (PSA) carried out by multiple single-antenna eavesdroppers (Eves) in a downlink time-division duplex system, where a multiple antenna base station (BS) transmits confidential information to a single-antenna legitimate user. During the uplink channel training phase, multiple Eves collaboratively impair the channel acquisition of the legitimate link, aimed at maximizing the wiretapping signal-to-noise ratio (SNR) in the subsequent downlink data transmission phase. Two different scenarios are investigated: 1) the BS is unaware of the PSA and 2) the BS attempts to detect the presence of the PSA. For both scenarios, we formulate wiretapping SNR maximization problems. For the second scenario, we also investigate the probability of successful detection and constrain it to remain below a pre-designed threshold. The two resulting optimization problems can be unified into a more general non-convex optimization problem, and we propose an efficient algorithm based on the minorization-maximization (MM) method and the alternating direction method of multipliers (ADMM) to solve it. The proposed MM-ADMM algorithm is shown to converge to a stationary point of the general problem. In addition, we propose a semi-definite relaxation (SDR) method as a benchmark to evaluate the efficiency of the MM-ADMM algorithm. Numerical results show that the MM-ADMM algorithm achieves near-optimal performance and is computationally more efficient than the SDR-based method.<br
Keywords: Training; Channel estimation; Uplink; Signal to noise Ratio; Optimization; Downlink; MIMO communication

Pilot symbol assisted BPSK on rayleigh fading channels with diversity: Performance analysis and parameter optimization - Müller, Ralf; et al. (IEEE Transactions on Communications, 1998)
In this letter, the loss due to imperfect channel estimation is derived for pilot symbol assisted binary phaseshift keying (BPSK) on fading channels with diversity. The presented approach, which holds for both narrow-band and spread spectrum communication, further provides an analytical optimization of pilot symbol spacing. The loss due to channel estimation is demonstrated to be low if the maximum Doppler frequency is significantly less than the bit rate. © 1998 IEEE.
Keywords: Channel estimation; Code-division multiple access; Convolutional coding; Phase-shift keying; Rayleigh fading channel; Spread spectrum

Polar Quantisation of Uniformly Distributed Signals on the Hypersphere for OMA - Gäde, Bernhard; Bereyhi, Ali; Müller, Ralf (24th International ITG Workshop on Smart Antennas (WSA 2020), 2020)

Polynomial-Expansion Multi-Cell Aware Detector for Uplink Massive MIMO Systems with Imperfect CSI - Zarei, Shahram; Aulin, Jocelyn; Gerstacker, Wolfgang; Schober, Robert (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
In this paper, we propose a multi-cell aware (MCA) detector for uplink multi-cell massive multiple-input multiple-output (MIMO) systems. The proposed detector exploits knowledge of the channel statistics but data exchange between different base stations over backhaul links is not required. A correlated channel model is considered and the adopted channel state information (CSI) acquisition model includes the effects of estimation errors and pilot contamination. In contrast to the conventional minimum mean square error (MMSE) detector, which mitigates only the multiple-access interference (MAI) in the target cell, the proposed detector takes the interference from neighboring cells and pilot contamination into account and therefore achieves substantially higher sum rates. Moreover, in order to reduce the computational complexity, the matrix inversion required for the MCA detector is approximated by a matrix polynomial leading to a new polynomial-expansion MCA (PEMCA) detector. Using results from random matrix theory, we derive closed-form expressions for the optimal coefficients of the matrix polynomial, which only depend on the channel statistics but not on the channel realizations. Our simulation results show that the PEMCA detector with only a few terms in the matrix polynomial achieves a considerably higher sum rate than the conventional MMSE detector while having a lower computational complexity.<br
Keywords: Detectors; MIMO; Channel estimation; Interference; Uplink; Contamination; Complexity theory

Power Allocation and Scheduling for SWIPT Systems with Non-linear Energy Harvesting Model - Boshkovska, Elena; Morsi, Rania; Ng, Derrick Wing Kwan; Schober, Robert (International Conference on Communications ICC, 2016)
In this paper, we design a resource allocation algorithm for multiuser simultaneous wireless information and power transfer systems for a realistic non-linear energy harvesting (EH) model. In particular, the algorithm design is formulated as a non-convex optimization problem for the maximization of the long-term average total harvested power at EH receivers subject to quality of service requirements for information decoding receivers. To obtain a tractable solution, we transform the corresponding non-convex sum-of-ratios objective function into an equivalent objective function in parametric subtractive form. This leads to a computationally efficient iterative resource allocation algorithm. Numerical results reveal a significant performance gain that can be achieved if the resource allocation algorithm design is based on the non-linear EH model instead of the traditional linear model.

Power allocation for a hybrid energy harvesting relay system with imperfect channel and energy state information - Ahmed, I. Zakir; Ikhlef, Aissa; Wing Kwan Ng, Derrick; Schober, Robert (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
In this paper, we consider both channel state uncertainty and harvested energy state uncertainty for a source-relay-destination communication link where the source and the relay are equipped with hybrid energy sources. Taking into account these uncertainties is of important for practical energy harvesting (EH) communication. While channel state uncertainties also affect conventional communication systems and have been widely studied, harvested energy state uncertainties are specific to energy harvesting systems and have not been considered in the literature before. The considered hybrid energy sources include a constant energy source and an energy harvester. Our objective is to maximize the worst case system throughput over a finite number of transmission intervals. We propose robust optimal offline, optimal online, and suboptimal online power allocation schemes. The offline power allocation design is formulated as an optimization problem which can be solved optimally. For the online case, we propose a dynamic programming (DP) approach to compute the optimal transmit power. To alleviate the prohibitively high complexity inherent to DP, we also propose several suboptimal low-complexity online power allocation schemes. Simulation results confirm the robustness of the proposed power allocation schemes to channel and energy state uncertainties.<br
Keywords: Resource management; Optimized production technology; Uncertainty; Batteries; Channel estimation; Relays

Power allocation for an energy harvesting transmitter with hybrid energy sources - Ahmed, Imtiaz; Ikhlef, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
In this work, we consider a point - to - point communication link where the transmitter has a hybrid supply of energy. Specifically, the hybrid energy is supplied by a constant energy source and an energy harvester, which harvests energy from its surrounding environment and stores it in a battery which suffers from energy leakage. Our goal is to minimize the power consumed by the constant energy source for transmission of a given amount of data in a given number of time intervals. Two scenarios are considered for packet arrival. In the first scenario, we assume that all data packets have arrived before transmission begins, whereas in the second scenario, we assume that data packets are arriving during the course of data transmission. For both scenarios, we propose an optimal offline transmit power allocation scheme which provides insight into how to efficiently consume the energy supplied by the constant energy source and the energy harvester. For offline power allocation, we assume that causal and non - causal information regarding the channel and the amount of harvested energy is available a priori. For optimal online power allocation, we adopt a stochastic dynamic programming (DP) approach for both considered scenarios. For online power allocation, only causal information regarding the channel and the amount of harvested energy is assumed available. Due to the inherent high complexity of DP, we propose suboptimal online algorithms which are appealing because of their low complexity. Simulation results reveal that the offline scheme performs best among all considered schemes and the suboptimal online scheme provides a good performance - complexity tradeoff. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: convex optimization; dynamic programming; Energy harvesting; hybrid energy supply; power allocation

Power Allocation for Conventional and Buffer-Aided Link Adaptive Relaying Systems with Energy Harvesting Nodes - Ahmed, Imtiaz; Ikhlef, Aissa; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Wireless Communications, 2014)
In this paper, we consider optimal power allocation for conventional and buffer-aided link adaptive energy harvesting (EH) relay systems, where an EH source communicates with the destination via an EH decode-and-forward relay over fading channels. In conventional relaying, source and relay transmit signals in consecutive time slots whereas in buffer-aided link adaptive relaying, the state of the source-relay and relay-destination channels as well as the amounts of energy available at source and relay determine whether the source or the relay is selected for transmission. Our objective is to maximize the system throughput over a finite number of transmission time slots for both relaying protocols. In case of conventional relaying, we propose an offline and several online joint source and relay transmit power allocation schemes. For offline power allocation, we formulate a convex optimization problem whereas for the online case, we propose a dynamic programming (DP) approach to compute the optimal online transmit power. To alleviate the complexity inherent to DP, we also propose several suboptimal online power allocation schemes. For buffer-aided link adaptive relaying, we show that the joint offline optimization of the source and relay transmit powers along with the link selection results in a mixed integer non-linear program which we solve optimally using the spatial branch-and-bound method. We also propose efficient online power allocation schemes for buffer-aided link adaptive relaying. Simulation results show that buffer-aided link adaptive relaying provides significant performance gains compared to conventional relaying but requires a higher complexity for computation of the power allocation solution. We also show that buffer-aided link adaptive relaying is more robust to changes in the EH rate than conventional relaying.<br
Keywords: Resource management; Relays; Batteries; Protocols; Optimization; Throughput; Fading

Power Allocation for SC-FDE-Based CR Systems Under Explicit Primary User Protection - Wu, Peiran; Schober, Robert; Bhargava, Vijay Kishore (IEEE Communications Letters, 2016)
In this letter, we consider the power allocation for a single-carrier (SC)-based secondary user (SU) transmitter (Tx), which transmits concurrently with an SC or multicarrier (MC) primary user (PU) over the same frequency band. A rate maximization problem for the SU system is formulated subject to an SU-Tx power constraint and an explicit rate loss constraint for the PU system. Due to the nonconvexity of the resulting problem, we propose a successive convex approximation approach to solve the problem where in each iteration closed-form solutions are derived for the power allocation variables of the SU-Tx. We further prove that the proposed algorithm is guaranteed to converge to a local optimum of the original nonconvex problem. Simulation results are provided to show the efficacy of the proposed approach.<br
Keywords: OFDM; Interference; Signal to noise Ratio; Resource Management; Frequency-domain Analysis; Approximation algorithms; Decision support systems

Power dispatch and load control with generation uncertainty - Samadi, Pedram; Bahrami, Shahab; Wong, Vincent W.S.; Schober, Robert (2015 IEEE Global Conference on Signal and Information Processing (GlobalSIP), 2015)
In this paper, we focus on the problem of joint load scheduling and generation management to better match supply and demand. We formulate an optimization problem to jointly minimize the generation cost and discomfort cost of the users subject to the voltage and power balance equations for the equivalent circuit of the power system. The optimal power flow (OPF) equations are solved using semidefinite programming (SDP) relaxation technique. In our system model, we assume that users can exploit renewable energy resources (RERs). RERs are random in nature and may cause voltage variations in different nodes of the system. To minimize the risk of having high voltage values, a barrier term is added to the objective function. This term is calculated based on the concept of conditional value-at-risk (CVaR). Simulation results show that compared to the case where there is no control over the load, our proposed algorithm reduces the generation cost by better matching the generation and demand. Moreover, the proposed algorithm reduces the voltage variations at different nodes of the system.<br
Keywords: Reactive power; Power generation; Power demand; Cost function; Supply and demand; Mathematical model; Admittance

Power Efficiency, Overhead, and Complexity Tradeoff of IRS Codebook Design – Quadratic Phase-Shift Profile - Jamali, Vahid; Najafi, Marzieh; Schober, Robert; Vincent Poor, H. (IEEE Communications Letters, 2021)
In this paper, we focus on large intelligent reflecting surfaces (IRSs) and propose a new codebook construction method to obtain a set of predesigned phase-shift configurations for the IRS unit cells. Since the overhead for channel estimation and the complexity of online optimization for IRS-assisted communications scale with the size of the phase-shift codebook, the design of small codebooks is of high importance. We show that there exists a fundamental tradeoff between power efficiency and the size of the codebook. We first analyze this tradeoff for baseline designs that employ a linear phase-shift across the IRS. Subsequently, we show that an efficient design for small codebooks mandates higher-order phase-shift variations across the IRS. Consequently, we propose a quadratic phase-shift design, derive its coefficients as a function of the codebook size, and analyze its performance. Our simulation results show that the proposed design yields a higher power efficiency for small codebooks than the linear baseline designs.
CRIS-Team Scopus Importer:2021-04-09
Keywords: and power efficiency; Channel estimation; channel estimation overhead; complexity; Complexity theory; Discrete Fourier transforms; Downlink; Intelligent reflecting surfaces; Millimeter wave communication; Optimization; phase-shift design; Transmission line matrix methods

Power Efficient and Secure Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (Power Efficient and Secure Full-Duplex Wireless Communication Systems, 2015)
In this paper, we study resource allocation for a full-duplex (FD) radio base station serving multiple half-duplex (HD) downlink and uplink users simultaneously. The considered resource allocation algorithm design is formulated as a non-convex optimization problem taking into account minimum required receive signal-to-interference-plus-noise ratios (SINRs) for downlink and uplink communication and maximum tolerable SINRs at potential eavesdroppers. The proposed optimization framework enables secure downlink and uplink communication via artificial noise generation in the downlink for interfering the potential eavesdroppers. We minimize the weighted sum of the total downlink and uplink transmit power by jointly optimizing the downlink beamformer, the artificial noise covariance matrix, and the uplink transmit power. We adopt a semidefinite programming (SDP) relaxation approach to obtain a tractable solution for the considered problem. The tightness of the SDP relaxation is revealed by examining a sufficient condition for the global optimality of the solution. Simulation results demonstrate the excellent performance achieved by the proposed scheme and the significant transmit power savings enabled optimization of the artificial noise covariance matrix.

Power efficient and secure multiuser communication systems with wireless information and power transfer - Leng, Shiyang; Ng, Derrick Wing Kwan; Schober, Robert (2014 IEEE International Conference on Communications Workshops, ICC 2014, 2014)
In this paper, we study resource allocation algorithm design for power efficient secure communication with simultaneous wireless information and power transfer (WIPT) in multiuser communication systems. In particular, we focus on power splitting receivers which are able to harvest energy and decode information from the received signals. The considered problem is modeled as an optimization problem which takes into account a minimum required signal-to-interference-plus-noise ratio (SINR) at multiple desired receivers, a maximum tolerable data rate at multiple multi-antenna potential eavesdroppers, and a minimum required power delivered to the receivers. The proposed problem formulation facilitates the dual use of artificial noise in providing efficient energy transfer and guaranteeing secure communication. We aim at minimizing the total transmit power by jointly optimizing transmit beamforming vectors, power splitting ratios at the desired receivers, and the covariance of the artificial noise. The resulting non-convex optimization problem is transformed into a semidefinite programming (SDP) and solved by SDP relaxation. We show that the adopted SDP relaxation is tight and achieves the global optimum of the original problem. Simulation results illustrate the significant power saving obtained by the proposed optimal algorithm compared to suboptimal baseline schemes. © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Power-Efficient and Secure WPCNs With Hardware Impairments and Non-Linear EH Circuit - Boshkovska, Elena; Wing Kwan Ng, Derrick; Dai, Linglong; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we design a robust resource allocation algorithm for a wireless-powered communication network (WPCN) taking into account residual hardware impairments (HWIs) at the transceivers, the imperfectness of the channel state information, and the non-linearity of practical radio frequency energy harvesting circuits. In order to ensure power-efficient secure communication, physical layer security techniques are exploited to deliberately degrade the channel quality of a multiple-antenna eavesdropper. The resource allocation algorithm design is formulated as a non-convex optimization problem for minimization of the total power consumption in the network, while guaranteeing the quality of service of the information receivers in terms of secrecy rate. The globally optimal solution of the optimization problem is obtained via a 2-D search and semidefinite programming relaxation. To strike a balance between computational complexity and system performance, a low-complexity iterative suboptimal resource allocation algorithm is also proposed. Numerical results demonstrate that both the proposed optimal and suboptimal schemes can significantly reduce the total system power consumption required for guaranteeing secure communication, and unveil the impact of HWIs on the system performance: 1) residual HWIs create a system performance bottleneck in WPCN in the high transmit/receive power regimes; 2) increasing the number of transmit antennas can effectively reduce the power consumption of wireless power transfer and alleviate the performance degradation due to residual HWIs; and 3) imperfect CSI exacerbates the impact of residual HWIs, which increases the power consumption of both wireless power and wireless information transfer.<br
Keywords: Wireless communication; Algorithm design and Analysis; Communication system security; Resource Management; Hardware; Energy harvesting; Security

Power-Efficient and Secure WPCNs with Residual Hardware Impairments and a Non-Linear EH Model - Boshkovska, Elena; Ng, Derrick Wing Kwan; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
In this paper, we design a resource allocation algorithm for a wireless-powered communication network (WPCN) taking into account residual hardware impairments (HWIs) at the transceivers and the non-linearity of radio frequency (RF) energy harvesting (EH) circuits. In order to ensure communication secrecy, physical layer (PHY) security techniques are exploited to deliberately degrade the channel quality of a multiple-antenna eavesdropper. The resource allocation algorithm design is formulated as a non-convex optimization problem for the minimization of the total consumed power in the network, while guaranteeing the quality of service (QoS) of the information receivers (IRs). The globally optimal solution of the optimization problem is obtained via a one-dimensional search and semidefinite programming (SDP) relaxation. Numerical results demonstrate that the proposed scheme can significantly reduce the power consumption of the system compared to a baseline scheme, which assumes ideal hardware.<br
Keywords: Hardware; Wireless communication; Communication system security; Resource management; Algorithm design and analysis; Distortion; Security

Power-Efficient Beam Designs for Millimeter Wave Communication Systems - Zhang, Jianjun; Huang, Yongming; Wang, Jiaheng; Schober, Robert; Yang, Luxi (IEEE Transactions on Wireless Communications, 2020)
The use of the millimeter wave (mmwave) spectrum for next generation mobile communication systems has gained significant attention recently. Large antenna arrays along with beamforming techniques are required to combat the large path-loss at mmwave frequencies. However, the existing beam designs often cause a large peak to average power ratio, and thus require power-inefficient power amplifiers (PAs). In this paper, we propose power-efficient beam design methods that facilitate the use of power-efficient PAs. Specifically, we design digital and hybrid analog-digital mmwave beams that possess a per-antenna constant envelope (PACE) and thus are highly power-efficient. Meanwhile, we also minimize the ripples in the mainlobe and sidelobe of the beams and consider both infinite and finite resolution phase shifters. To this end, we first propose an efficient feasible point search method to provide a feasible solution for the considered difficult beam design problem. Then, a novel hybrid analog-digital mapping algorithm is developed to map a designed digital beam to a hybrid analog-digital beam. To achieve better performance, we propose an improved hybrid analog-digital beam design method employing further optimization based on the feasible point. The proposed method is applicable to both infinite-resolution and finite-resolution phase shifters. Comprehensive simulation results are provided to demonstrate the effectiveness and superiority of the proposed beam designs.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Beam design; beam optimization; low PAPR; millimeter wave communication; power-efficient

Power efficient MISO beamforming for secure layered transmission - Wing Kwan Ng, Derrick; Schober, Robert; Alnuweiri, Hussein (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
This paper studies secure layered video transmission in a multiuser multiple-input single-output (MISO) beamforming downlink communication system. The power allocation algorithm design is formulated as a non-convex optimization problem for minimizing the total transmit power while guaranteeing a minimum received signal-to-interference-plus-noise ratio (SINR) at the desired receiver. In particular, the proposed problem formulation takes into account the self-protecting architecture of layered transmission and artificial noise generation to prevent potential information eavesdropping. A semi-definite programming (SDP) relaxation based power allocation algorithm is proposed to obtain an upper bound solution. A sufficient condition for the global optimal solution is examined to reveal the tightness of the upper bound solution. Subsequently, two suboptimal power allocation schemes with low computational complexity are proposed for enabling secure layered video transmission. Simulation results demonstrate significant transmit power savings achieved by the proposed algorithms and layered transmission compared to the baseline schemes.<br
Keywords: Receivers; Resource management; Transmitters; Noise; Vectors; Streaming media; Optimization

Power Efficient Resource Allocation for Full-Duplex Radio Distributed Antenna Networks - Wing Kwan Ng, Derrick; Wu, Yongpeng; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we study the resource allocation algorithm design for distributed antenna multiuser networks with full-duplex (FD) radio base stations (BSs), which enable simultaneous uplink and downlink communications. The considered resource allocation algorithm design is formulated as an optimization problem taking into account the antenna circuit power consumption of the BSs and the quality of service (QoS) requirements of both uplink and downlink users. We minimize the total network power consumption by jointly optimizing the downlink beamformer, the uplink transmit power, and the antenna selection. To overcome the intractability of the resulting problem, we reformulate it as an optimization problem with decoupled binary selection variables and nonconvex constraints. The reformulated problem facilitates the design of an iterative resource allocation algorithm, which obtains an optimal solution based on the generalized Bender's decomposition (GBD). For this algorithm, we also propose a simple technique to improve the speed of convergence. Furthermore, to strike a balance between computational complexity and system performance, a suboptimal resource allocation algorithm with polynomial time complexity is proposed. Simulation results illustrate that the proposed GBD-based iterative algorithm converges to the globally optimal solution and the suboptimal algorithm achieves a close-to-optimal performance. Our results also demonstrate the tradeoff between power efficiency and the number of active transmit antennas when the circuit power consumption is taken into account. In particular, activating an exceedingly large number of antennas may not be an efficient approach for reducing the total system power consumption. In addition, our results reveal that FD systems facilitate significant power savings compared to traditional half-duplex systems, despite the nonnegligible self-interference.<br
Keywords: Downlink; Uplink; Resource management; Antenna arrays; Algorithm design and analysis; Power demand

Power-Efficient Resource Allocation for Multiuser MISO Systems via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
Intelligent reflecting surfaces (IRSs) are regarded as key enablers of next-generation wireless communications, due to their capability of customizing the wireless propagation environment. In this paper, we investigate power-efficient resource allocation for IRS-assisted multiuser multiple-input single-output (MISO) systems. To minimize the transmit power, both the beamforming vectors at the access point (AP) and phase shifts at the IRS are jointly optimized while taking into account the minimum required quality-of-service (QoS) of the users. To tackle the non-convexity of the formulated optimization problem, an inner approximation (IA) algorithm is developed. Unlike existing designs, which cannot guarantee local optimality, the proposed algorithm is guaranteed to converge to a Karush-Kuhn-Tucker (KKT) solution. Our simulation results show the effectiveness of the proposed algorithm compared to baseline schemes and reveal that deploying IRSs is more promising than leveraging multiple antennas at the AP in terms of energy efficiency.
CRIS-Team Scopus Importer:2021-04-19

Power optimal scheduling for guaranteed throughput in multi-access fading channels - Chaporkar, Prasanna; Kansanen, Kimmo; Müller, Ralf (2007 IEEE International Symposium on Information Theory, ISIT 2007, 2007)
A power optimal scheduling algorithm that guarantees desired throughput and bounded delay to each user is developed for fading multi-access multi-band channels that can model many important practical systems including OFDM system and flat and frequency selective multi-access channels. The optimization is over the joint space of all rate allocation and coding strategies. The proposed scheduling assigns rates on each band based only on the current system state, and subsequently uses optimal multi-user signaling to achieve these rates. The scheduling is computationally simple, and hence scalable. Due to uplink-downlink duality, all the results extend in straightforward fashion to the broadcast channels. ©2007 IEEE.
Keywords: Convex optimization; Power minimization; Scheduling; Stability; Super-position encoding and successive decoding

Power Randomization for Iterative Detection Over Random-Access Fading Channels - Salvo Rossi, Pierluigi; Kansanen, Kimmo; Müller, Ralf; Rachinger, Christoph (IEEE Transactions on Wireless Communications, 2015)
In this paper, we focus on throughput performance of multiuser communications systems over fading channels. More specifically, we consider the uplink where multiuser detection under asynchronous transmissions is exploited for random-access management and iterative receivers are considered for practical issues. Normalized throughput is evaluated through a semi-analytic procedure in order to avoid time-consuming simulations. Power randomization is explored as a means for improving performance through system asymmetries. It is found beneficial, particularly in case of overloaded systems operating at low-to-medium signal-to-noise ratio, where it allows reducing significantly the number of iterations at the receive
Keywords: Code-division multiple access (CDMA); fading channels; iterative decoding; multiuser detection; power randomization; random-access communications; throughput evaluation

Power saving potential of cooperative communication: A two-dimensional approach - Korn, Clemens; Michalopoulos, Diomidis; Schober, Robert (SCC 2015 - 10th International ITG Conference on Systems, Communications and Coding, 2019)
We assess the power saving potential of cooperative communication for a two-dimensional user distribution scenario. In particular, we compare the average total transmit power of cooperative transmission (i.e., the sum of the user and the relay transmit power, averaged over the distribution of the users) with the average transmit power of conventional (direct) communication. The comparison is performed on the basis of achieving the same signal-to-noise ratio (SNR) at the base station in both cases. In this regard, a circular shaped radio cell with circularly uniformly distributed users is considered. A theoretical investigation of the savings in transmit power offered by cooperation is conducted for the case where the path-loss exponent equals four. The theoretical analysis is verified by simulations, which also consider a wider range of path loss exponent values for the evaluation of the power savings achieved by cooperation. Our results demonstrate that the power savings per user increase with increasing path loss exponent and with increasing number of users within the circular cell.
CRIS-Team Scopus Importer:2019-10-22

Power Scaling Law for Optical IRSs and Comparison with Optical Relays - Ajam, Hedieh; Najafi Kalyani, Marzieh; Jamali, Vahid; Schober, Robert (2022 IEEE Global Communications Conference, GLOBECOM 2022 - Proceedings, 2022)
The line-of-sight (LOS) requirement of free-space optical (FSO) systems can be relaxed by employing optical relays and optical intelligent reflecting surfaces (IRSs). Unlike radio frequency (RF) IRSs, which typically exhibit a quadratic power scaling law, the power reflected from FSO IRSs and collected at the receiver lens may scale quadratically or linearly with the IRS size or may even saturate at a constant value. We analyze the power scaling law for optical IRSs and unveil its dependence on the wavelength, transmitter (Tx)-to-IRS and IRS-to-receiver (Rx) distances, beam waist, and lens size. We compare optical IRSs in different power scaling regimes with optical relays in terms of the outage probability, diversity and coding gains, and optimal placement. Our results show that, at the expense of a higher hardware complexity, relay-assisted FSO links yield a better outage performance at high signal-to-noise-ratios (SNRs), but optical IRSs can achieve a higher performance at low SNRs. Moreover, while it is optimal to place relays equidistant from Tx and Rx, the optimal location of IRSs depends on the power scaling regime they operate in.
CRIS-Team Scopus Importer:2023-03-07

Practical Non-Linear Energy Harvesting Model and Resource Allocation for SWIPT Systems - Boshkovska, Elena; Wing Kwan Ng, Derrick; Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2015)
In this letter, we propose a practical non-linear energy harvesting model and design a resource allocation algorithm for simultaneous wireless information and power transfer (SWIPT) systems. The algorithm design is formulated as a non-convex optimization problem for the maximization of the total harvested power at energy harvesting receivers subject to minimum required signal-to-interference-plus-noise ratios (SINRs) at multiple information receivers. We transform the considered non-convex objective function from sum-of-ratios form into an equivalent objective function in subtractive form, which enables the derivation of an efficient iterative resource allocation algorithm. In each iteration, a rank-constrained semidefinite program (SDP) is solved optimally by SDP relaxation. Numerical results unveil a substantial performance gain that can be achieved if the resource allocation design is based on the proposed non-linear energy harvesting model instead of the traditional linear model.<br
Keywords: Resource management; Wireless communication; Integrated circuit modeling; Receivers; Optimization; Wireless sensor networks

Practical signaling with vanishing pilot-energy for large noncoherent block-fading MIMO channels - Takeuchi, Keigo; Müller, Ralf; Vehkapera, Mikko; Tanaka, Toshiyuki (2009 IEEE International Symposium on Information Theory, ISIT 2009, 2009)
We propose a randomly-biased quadrature phase shift keying (QPSK) signaling scheme for a noncoherent Rayleigh block-fading multiple-input multiple-output (MIMO) channel. Inorder to optimize a prior of bias, we evaluate a lower bound of the spectral efficiency of the noncoherent MIMO channel withrandomly-biased QPSK signaling in the large-system limit, by using the replica method. Our main result is that randomlybiased QPSK signaling with vanishing bias is optimal in thelarge-system limit for any signal-to-noise ratio. © 2009 IEEE.

Precoder Design and Power Allocation for Downlink MIMO-NOMA via Simultaneous Triangularization - Krishnamoorthy, Aravindh; Huang, Meng; Schober, Robert (2021 IEEE Wireless Communications and Networking Conference (WCNC), 2021)

Precoder Design and Statistical Power Allocation for MIMO-NOMA via User-Assisted Simultaneous Diagonalization - Krishnamoorthy, Aravindh; Ding, Zhiguo; Schober, Robert (IEEE Transactions on Communications, 2020)
Keywords: Symmetric matrices; Decoding; Covariance matrices; NOMA; MIMO communication; Resource management; Precoding

Precoder Design for Two-User Uplink MIMO-NOMA with Simultaneous Triangularization - Krishnamoorthy, Aravindh; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
In this paper, we consider the uplink precoder design for two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) systems. We propose a novel precoding scheme which utilizes simultaneous tri-angularization to decompose the MIMO-NOMA channels of the two users into multiple single-input single-output (SISO)-NOMA channels assuming low-complexity self-interference cancellation at the base station, thereby reducing the decoding complexity. The proposed scheme takes advantage of the available excess degrees of freedom at the base station to enhance the ergodic achievable rate. The ergodic achievable rate region of the proposed scheme is characterized using finite-size random matrix theory (RMT). Our results illustrate that the proposed scheme significantly outperforms traditional MIMO-OMA and zero forcing based MIMO-NOMA schemes, and has a small performance gap to the achievable rate region of MIMO-NOMA.
CRIS-Team WoS Importer:2020-08-14

Precoding and Decoding Schemes for Downlink MIMO-RSMA with Simultaneous Diagonalization and User Exclusion - Diab, Rouaa; Krishnamoorthy, Aravindh; Schober, Robert (2022 IEEE International Conference on Communications Workshops, ICC Workshops 2022, 2022)
In this paper, we consider the precoder design for downlink multiple-input multiple-output (MIMO) rate-splitting multiple access (RSMA) systems. The proposed scheme with simultaneous diagonalization (SD) decomposes the MIMO channel matrices of the users into scalar channels via higher-order generalized singular value decomposition for the common message (CM) and block diagonalization (BD) for the private messages, thereby enabling low-complexity element-by-element successive interference cancellation (SIC) and decoding at the receivers. Furthermore, the proposed SD MIMO-RSMA overcomes a critical limitation in RSMA systems, whereby the achievable rate of the CM is restricted by the users with weak effective MIMO channel for the CM, by excluding a subset of users from decoding the CM. We formulate a non-convex weighted sum rate (WSR) optimization problem for SD MIMO-RSMA and solve it via successive convex approximation to obtain a locally optimal solution. Our simulation results reveal that, for both perfect and imperfect CSI, the proposed SD MIMO-RSMA with user exclusion outperforms baseline MIMO-RSMA schemes and linear BD precoding.
CRIS-Team Scopus Importer:2022-08-05

Precoding via Approximate Message Passing with Instantaneous Signal Constraints - Bereyhi, Ali; Sedaghat, Mohammad Ali; Müller, Ralf (International Zurich Seminar on Information and Communication (IZS), 2018)
This paper proposes a low complexity precoding algorithm based on the recently proposed Generalized Least Square Error (GLSE) scheme with generic penalty and support. The algorithm iteratively constructs the transmit vector via Approximate Message Passing (AMP). Using the asymptotic decoupling property of GLSE precoders, we derive closed form fixed point equations to tune the parameters in the proposed algorithm for a general set of instantaneous signal constraints. The tuning strategy is then utilized to construct transmit vectors with restricted peak-to-average power ratios and to efficiently select a subset of transmit antennas. The numerical investigations show that the proposed algorithm tracks the large-system performance of GLSE precoders even for a moderate number of antennas.

Pricing Mobile Data Offloading: A Distributed Market Framework - Wang, Kehao; Lau, Francis C. M.; Chen, Lin; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
Mobile data offloading is an emerging technology to avoid congestion in cellular networks and improve the level of user satisfaction. In this paper, we develop a distributed market framework to price the offloading service, and conduct a detailed analysis of the incentives for offloading service providers and conflicts arising from the interactions of different participators. Specifically, we formulate a multileader multifollower Stackelberg game (MLMF-SG) to model the interactions between the offloading service providers and the offloading service consumers in the considered market framework, and investigate the cases where the offloading capacity of APs is unlimited and limited, respectively. For the case without capacity limit, we decompose the followers' game of the MLMF-SG (FG-MLMF-SG) into a number of simple follower games (FGs), and prove the existence and uniqueness of the equilibrium of the FGs from which the existence and uniqueness of the FG-MLMF-SG also follows. For the leaders' game of the MLMF-SG, we also prove the existence and uniqueness of the equilibrium. For the case with capacity limit, by considering a symmetric strategy profile, we establish the existence and uniqueness of the equilibrium of the corresponding MLMF-SG, and present a distributed algorithm that allows the leaders to achieve the equilibrium. Finally, extensive numerical experiments demonstrate that the Stackelberg equilibrium is very close to the corresponding social optimum for both considered cases.<br
Keywords: Games; Mobile communication; IEEE 802.11 Standard; Radio frequency; Pricing; Mobile computing; Femtocells

Proactive Resource Allocation for Aggregated VLC/RF Networks With Outdated CSI - Bozanis, Dimitrios; Evgenidis, Nikos G.; Papanikolaou, Vasileios; Dowhuszko, Alexis A.; Tegos, Sotiris A.; Diamantoulakis, Panagiotis D.; Karagiannidis, George K. (IEEE Wireless Communications Letters, 2024)
In this paper, the case of an aggregated VLC/RF network is presented, where the users can be served simultaneously by both a visible light communication (VLC) carrier and a radio-frequency (RF) carrier to increase their achievable data rate. The optimal resource allocation in the network is dependent on always having accurate channel state information (CSI), otherwise, in the case of outdated CSI, the system is prone to sub-optimally allocating resources and, due to the limited coverage of VLC, users may also experience outage. A closed-form expression for the coverage probability is presented for a user moving randomly in the cell. Using this, a proactive resource allocation algorithm is proposed that takes into account outdated CSI which can occur due to user movement, and ensures the outage probability is low in the network without diminishing the average achievable data rate of users. Finally, simulation results validate the proposed analysis and showcase the effectiveness of this approach.
CRIS-Team Scopus Importer:2024-02-02
Keywords: aggregated VLC/RF networks; Optical receivers; Optical sensors; Optimization; outdated CSI; proactive resource allocation; Radio frequency; Resource management; Visible light communication; Wireless communication

Proportional Fairness in ALOHA Networks With RF Energy Harvesting - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola; Schober, Robert (IEEE Wireless Communications Letters, 2018)
In this letter, we study wireless powered communication networks that employ the slotted ALOHA protocol, which is the preferred protocol for simple and uncoordinated networks. In the energy harvesting (EH) phase, the base station broadcasts radio frequency energy to the EH users (EHUs). The EHUs harvest the broadcasted energy and use it to transmit information back to the base station by contending for access to the uplink channel in the random access (RA) phase. In order to ensure fairness among the users, we propose a proportionally fair resource allocation scheme that exploits the RA nature of slotted ALOHA. Specifically, assuming statistical channel state information, we determine the optimal transmit power at the base station, the optimal durations of the EH and RA phases, the channel access probability, and the rate of each EHU.<br
Keywords: Fading channels; Resource Management; Wireless Networks; Batteries; Power Generation; Throughput

Proportional Fairness in ALOHA Networks With RF Energy Harvesting - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola; Schober, Robert (IEEE Wireless Communications Letters, 2019)
In this letter, we study wireless powered communication networks that employ the slotted ALOHA protocol, which is the preferred protocol for simple and uncoordinated networks. In the energy harvesting (EH) phase, the base station broadcasts radio frequency energy to the EH users (EHUs). The EHUs harvest the broadcasted energy and use it to transmit information back to the base station by contending for access to the uplink channel in the random access (RA) phase. In order to ensure fairness among the users, we propose a proportionally fair resource allocation scheme that exploits the RA nature of slotted ALOHA. Specifically, assuming statistical channel state information, we determine the optimal transmit power at the base station, the optimal durations of the EH and RA phases, the channel access probability, and the rate of each EHU.
CRIS-Team WoS Importer:2019-03-06

Pulse Shaping for MC via Particle Size - Wicke, Wayan; Felsheim, Rebecca; Brand, Lukas; Jamali, Vahid; Loos, Helene; Büttner, Andrea; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
In molecular communication (MC), combining different types of particles at the transmitter is a degree of freedom which can be utilized to improve performance. In this paper, we address the problem of pulse shaping to simplify time synchronization requirements by exploiting and combining the received signal characteristics of particles of different sizes. In particular, we optimize the mixture of particles of different sizes used for transmission in order to support a prescribed detection time period for on-off keying, guaranteeing on average 1) a sufficiently large received signal if a binary one is transmitted, and 2) a low enough received signal if a binary zero is transmitted even in the presence of inter-symbol interference. For illustration, we consider an optimization problem based on a free space diffusion channel model. It is shown that there is a tradeoff between the maximum feasible detection duration and the for different particle sizes from the smallest particle size enabling the largest detection duration to the largest particle size minimizing the at the expense of a limited detection duration.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Pulse shaping methods; Receivers; Robustness; Shape; Symbols; Synchronization; Transmitters

Quasi-Coherent Phase-Based Localization and Tracking of Incoherently Transmitting Radio Beacons - Sippel, Erik; Hehn, Markus; Kögel, Tobias; Gröschel, Patrick; Hofmann, Andreas; Brückner, Stefan; Geiß, Johanna; Schober, Robert; Vossiek, Martin (IEEE Access, 2021)
The direct measurement of distance-dependent information between wireless units represents a challenge for wireless locating systems, because it requires the exact time synchronization of separate wireless units. To avoid these synchronization efforts, many wireless locating systems only evaluate phase difference of arrival (PDOA) measurements. While simple PDOA localization techniques rely on multiangulation, advanced PDOA concepts like the holographic extended Kalman filter (HEKF) directly evaluate the measured phases without non-linear preprocessing. However, these differential phase measurement approaches are less sensitive than systems that can measure absolute phase variations, which allow the tracking of much smaller position changes than the signal’s carrier wavelength. This paper proposes to extend the HEKF by the evaluation of absolute phases in an incoherent measurement setup, which consists of a continuous wave (CW) beacon and several receivers. The developed quasi-coherent holographic extended Kalman filter (QCHEKF) uses the overdetermined PDOA measurements to estimate the phase–frequency relation between each beacon–receiver pair. Then, the established phase–frequency relations allow the evaluation of absolute phase measurements and, thus, the accurate localization and tracking of a simple, unsynchronized, narrowband CW beacon, even under severe multipath conditions. This novel concept is experimentally validated via 3D localization results in a challenging indoor scenario using a 24 GHz CW measurement setup. Here, the QCHEKF improves the achieved localization accuracy in comparison to the HEKF by 35% from 0.78 cm to 0.51 cm, while the maximum deviation from the trajectory reduces by 68% from 5 cm to 1.6 cm. Furthermore, the QCHEKF enables the exact tracking of fast changes in direction, which is usually a significant challenge for standard wireless target tracking systems.
Keywords: Phase measurement; Location awareness; Antenna measurements; Time-frequency analysis; Receiving antennas; Time measurement; Wireless sensor networks

Quasi constant envelope CDMA for VHF maritime communications via satellite - Gallinaro, Gennaro; Alagha, Nader; Müller, Ralf; Titomanlio, S. (Ka and Broadband Communications Conference (Ka), 2017)

RACE: QoI-Aware Strategic Resource Allocation for Provisioning Se-aaS - Misra, Sudip; Schober, Robert; Chakraborty, Aishwariya (IEEE Transactions on Services Computing, 2022)
In this paper, the problem of ensuring profitability for multiple sensor-owners in sensor-cloud, while satisfying the service requirements of end-users, is studied. In traditional sensor-cloud, Sensor-Cloud Service Provider (SCSP) solely dictates the service provisioning process. However, the SCSP cannot always ensure high profits for sensor-owners, who incur significant maintenance costs for their sensor-nodes. Contrarily, it is highly essential to meet the Quality-of-Information (QoI) requirements of end-users to ensure their service satisfaction. Existing works proposed a few node allocation schemes which neither consider the cost incurred by sensor-owners nor the QoI of sensed-data in sensor-cloud. To address this problem, a strategic resource allocation scheme, named RACE, is proposed, which introduces the participation of sensor-owners in the node allocation process. First, utility theory is used to calculate the optimum number of nodes to be allocated for a service. Thereafter, single leader multiple followers Stackelberg game is formulated to decide the number of nodes to be contributed by each sensor-owner and the price to be charged. Simulation-based experimental results reveal that, using RACE, the profits of the sensor-owners and those of the SCSP increase by 86.11-89.26 percent and 41.95-80.82 percent, respectively, as compared to the existing benchmark schemes, while considering that each sensor-node is capable of serving multiple applications simultaneously. Moreover, service availability in sensor-cloud increases by 31.70-96.96 percent using RACE.
CRIS-Team WoS Importer:2022-07-08

Random matrix methods for design of multiuser communication systems - Müller, Ralf (Conference on Applications of Random Matrices to Economy and Other Complex Systems, 2005)
A short review on multiuser communication systems is given. System design for iterative multiuser decoding is improved by means of large system results from statistical physics and random matrix theory. With the application of multiuser detection for wireless communications in mind, it is shown how a system of linear equations with random coefficients can be solved efficiently exploiting the asymptotic convergence of its eigenvalue spectrum. In addition, the conditional convergence of the diagonal elements of a power of a random matrix drawn from a Marchenko-Pastur ensemble is established.

Rate Optimization for Hybrid SC-FDE/OFDM Decode-and-Forward MIMO Relay Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (IEEE Communications Letters, 2014)
In this paper, we consider the rate-optimal transceiver design for a hybrid single-carrier frequency-domain equalization and orthogonal frequency-division multiplexing decode-and-forward (DF) multiple-input-multiple-output (MIMO) relay system. Such hybrid systems can provide a high end-to-end bit rate and a low peak-to-average power ratio at one of the transmitting nodes. Assuming minimum mean-squared-error equalization at the receiving nodes, we optimize the transmit precoding matrices for maximization of the achievable bit rate (ABR) of the system subject to a joint node transmit power constraint. We provide a unified solution for the precoding matrices, which subsumes the solutions for pure single-carrier and pure multicarrier MIMO DF relay systems as special cases. Specifically, the optimal structure of the precoding matrices is obtained by exploiting the relation between our design and conventional point-to-point MIMO transceiver designs. With the optimal precoding structure, the optimization problem reduces to a convex power allocation problem, for which an efficient closed-form solution is derived. Numerical results are provided to confirm the excellent ABR performance of the proposed relaying schemes.<br
Keywords: Relays; OFDM; MIMO; Optimization; Transceivers; Wireless communication; Vectors

Rate-Power Region of SWIPT Systems Employing Nonlinear Energy Harvester Circuits with Memory - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (IEEE International Conference on Communications, 2020)
In this paper, we study the rate-power region of a simultaneous wireless information and power transfer (SWIPT) system where a transmitter (TX) broadcasts a common signal to an information receiver (IR) and an energy harvester (EH). Since practical EH circuits include a reactive element as part of their signal rectifier and the voltage on this element cannot drop or rise instantaneously, the EH circuit has memory. We model the memory effect of the EH by a Markov reward chain. Furthermore, since an analytical model that includes all nonlinear and memory effects of the EH circuit is not available, we employ a deep neural network (DNN) to model the Markov chain. We formulate an optimization problem to determine the rate-power region of the considered SWIPT system and propose an iterative algorithm based on sequential quadratic programming (SQP) to solve it. Our numerical results show that the optimal input distribution and the rate-power region depend on both the input power level at the EH and the symbol duration.
CRIS-Team Scopus Importer:2020-08-28

Rate-Splitting for Intelligent Reflecting Surface-Aided Multiuser VR Streaming - Huang, Rui; Wong, Vincent W.S.; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2023)
The growing demand for virtual reality (VR) applications requires wireless systems to provide a high transmission rate to support 360-degree video streaming to multiple users simultaneously. In this paper, we propose an intelligent reflecting surface (IRS)-aided rate-splitting (RS) VR streaming system. In the proposed system, RS facilitates the exploitation of the shared interests of the users in VR streaming, and IRS creates additional propagation channels to support the transmission of high-resolution 360-degree videos. IRS also enhances the capability to mitigate the performance bottleneck caused by the requirement that all RS users have to be able to decode the common message. We formulate an optimization problem for maximization of the achievable bitrate of the 360-degree video subject to the quality-of-service (QoS) constraints of the users. We propose a deep deterministic policy gradient with imitation learning (Deep-GRAIL) algorithm, in which we leverage deep reinforcement learning (DRL) and the hidden convexity of the formulated problem to optimize the IRS phase shifts, RS parameters, beamforming vectors, and bitrate selection of the 360-degree video tiles. We also propose RavNet, which is a deep neural network customized for the policy learning in our Deep-GRAIL algorithm. Performance evaluation based on a real-world VR streaming dataset shows that the proposed IRS-aided RS VR streaming system outperforms several baseline schemes in terms of system sum-rate, achievable bitrate of the 360-degree videos, and online execution runtime. Our results also reveal the respective performance gains obtained from RS and IRS for improving the QoS in multiuser VR streaming systems.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Array signal processing; Base stations; Bit rate; deep reinforcement learning; imitation learning; intelligent reflecting surface; Quality of service; Rate-splitting; Signal to noise ratio; Streaming media; virtual reality; Wireless communication

Rate-Splitting for IRS-Aided Multiuser VR Streaming: An Imitation Learning-Based Approach - Huang, Rui; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2023)
Virtual reality (VR) applications require wireless systems to provide a high transmission rate to support 360-degree video streaming to multiple users simultaneously. In this paper, we propose an intelligent reflecting surface (IRS)-aided rate-splitting (RS) VR streaming system. In the proposed system, RS exploits the shared interests of the users in VR streaming, and the IRS creates reflected channels to facilitate a high transmission rate. The IRS also mitigates the performance bottleneck caused by the requirement that all RS users have to be able to decode the common message. We formulate an optimization problem for maximization of the achievable bitrate of the streamed 360-degree video subject to the quality-of-service (QoS) constraints of the users. We propose a deep reinforcement learning (DRL)-based algorithm, in which we leverage imitation learning and the hidden convexity of the formulated problem to optimize the IRS phase shifts, RS parameters, beamforming vectors, and bitrate selection of the 360-degree video tiles. Simulations based on a real-world dataset show that the proposed IRS-aided RS VR streaming system outperforms two baseline schemes in terms of system sum-rate and average runtime.
CRIS-Team Scopus Importer:2023-12-15

Rate-Splitting Multiple Access: Fundamentals, Survey, and Future Research Trends - Mao, Yijie; Dizdar, Onur; Clerckx, Bruno; Schober, Robert; Popovski, Petar; Poor, H. Vincent (IEEE Communications Surveys & Tutorials, 2022)
Rate-splitting multiple access (RSMA) has emerged as a novel, general, and powerful framework for the design and optimization of non-orthogonal transmission, multiple access (MA), and interference management strategies for future wireless networks. By exploiting splitting of user messages as well as non-orthogonal transmission of common messages decoded by multiple users and private messages decoded by their corresponding users, RSMA can softly bridge and therefore reconcile the two extreme interference management strategies of fully decoding interference and treating interference as noise. RSMA has been shown to generalize and subsume as special cases four existing MA schemes, namely, orthogonal multiple access (OMA), physical-layer multicasting, space division multiple access (SDMA) based on linear precoding (currently used in the fifth generation wireless network–5G), and non-orthogonal multiple access (NOMA) based on linearly precoded superposition coding with successive interference cancellation (SIC). Through information and communication theoretic analysis, RSMA has been shown to be optimal (from a Degrees-of-Freedom region perspective) in several transmission scenarios. Compared to the conventional MA strategies used in 5G, RSMA enables spectral efficiency (SE), energy efficiency (EE), coverage, user fairness, reliability, and quality of service (QoS) enhancements for a wide range of network loads (including both underloaded and overloaded regimes) and user channel conditions. Furthermore, it enjoys a higher robustness against imperfect channel state information at the transmitter (CSIT) and entails lower feedback overhead and complexity. Despite its great potential to fundamentally change the physical (PHY) layer and media access control (MAC) layer of wireless communication networks, RSMA is still confronted with many challenges on the road towards standardization. In this paper, we present the first comprehensive tutorial on RSMA by providing a survey of the pertinent state-of-the-art research, detailing its architecture, taxonomy, and various appealing applications, as well as comparing with existing MA schemes in terms of their overall frameworks, performance, and complexities. An in-depth discussion of future RSMA research challenges is also provided to inspire future research on RSMA-aided wireless communication for beyond 5G systems.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 5G mobile communication; beyond 5G (B5G); Interference; interference management; Multiaccess communication; multiple-input multiple-output (MIMO); next generation multiple access; NOMA; non-orthogonal transmission; Radio transmitters; Rate-splitting (RS); rate-splitting multiple access (RSMA); Time-frequency analysis; Wireless communication

Rate-Splitting Unifying SDMA, OMA, NOMA, and Multicasting in MISO Broadcast Channel: A Simple Two-User Rate Analysis - Clerckx, Bruno; Mao, Yijie; Schober, Robert; Poor, H. Vincent (IEEE Wireless Communications Letters, 2020)
Considering a two-user multi-antenna Broadcast Channel, this letter shows that linearly precoded Rate-Splitting (RS) with Successive Interference Cancellation (SIC) receivers is a flexible framework for non-orthogonal transmission that generalizes, and subsumes as special cases, four seemingly different strategies, namely Space Division Multiple Access (SDMA) based on linear precoding, Orthogonal Multiple Access (OMA), Non-Orthogonal Multiple Access (NOMA) based on linearly precoded superposition coding with SIC, and physical-layer multicasting. This letter studies the sum-rate and shows analytically how RS unifies, outperforms, and specializes to SDMA, OMA, NOMA, and multicasting as a function of the disparity of the channel strengths and the angle between the user channel directions.
CRIS-Team Scopus Importer:2020-03-27
Keywords: multi-antenna broadcast channel; multicasting; NOMA; OMA; rate analysis; Rate-splitting; SDMA

Reactive receiver modeling for diffusive molecular communication systems with molecule degradation - Ahmadzadeh, Arman; Arjmandi, Hamidreza; Burkovski, Andreas; Schober, Robert (2016 IEEE International Conference on Communications, ICC 2016, 2016)
In this paper, we consider the diffusive molecular communication channel between a transmitter nano-machine and a receiver nano-machine in a fluid environment. The information molecules released by the transmitter nano-machine into the environment can degrade in the channel via a first-order degradation reaction and those that reach the receiver nano-machine can participate in a reversible bimolecular-reaction with receiver receptor proteins. We derive a closed-form analytical expression for the expected received signal at the receiver, i.e., the expected number of activated receptors on the surface of the receiver. The accuracy of the derived analytical result is verified with a Brownian motion particle-based simulation of the environment.
CRIS-Team Scopus Importer:2020-01-31

Real-Time Pricing for Demand Response Based on Stochastic Approximation - Samadi, Pedram; Mohsenian-Rad, Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2014)
In this paper, we propose a new pricing algorithm to minimize the peak-to-average ratio (PAR) in aggregate load demand. The key challenge that we seek to address is the energy provider's uncertainty about the impact of prices on users' load profiles, in particular when users are equipped with automated energy consumption scheduling (ECS) devices. We use an iterative stochastic approximation approach to design two real-time pricing algorithms based on finite-difference and simultaneous perturbation methods, respectively. We also propose the use of a system simulator unit (SSU) that employs approximate dynamic programming to simulate the operation of the ECS devices and users' price-responsiveness. Simulation results show that our proposed real-time pricing algorithms reduce the PAR in aggregate load and help the users to reduce their energy expenses.<br
Keywords: Approximation algorithms; Pricing; Linear programming; Approximation methods; Home appliances; Vectors; Peak to average power ratio

Real vs. complex bpsk precoding for mimo broadcast channels - De Miguel, Rodrigo; Müller, Ralf (2008 IEEE 19th International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2008, 2008)
Recently MülIer et ale (IEEE J. Select. Areas Commun. 2008) used asymptotic methods from statistical physics to analyze non-linear vector precoding for MIMO broadcast channels. They proposed to extend BPSK input alphabets onto both real and complex supersets of the original constellation points. They showed that, as the optimization space is greater. lower energies are achieved when the extended alphabets a"; complex. In this work we use similar asymptotic methods and propose an alternative channel inversion technique which makes purely real alphabets perform as well as their complex extensions which results in reduced complexity in the optimization process. © 2008 IEEE.

Receiver Concepts for WLAN IEEE 802.11b - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (Conference Proceedings, 2004)
In this paper, complementary code keying (CCK) transmission over frequency-selective fading channels is investigated. A vector signal model is introduced since CCK can be interpreted as a block code. Based on pairwise error probabilities we derive a performance approximation for optimum detection obtained for given channel statistics, and compare the theoretical results with simulations. Because optimum maximum-likelihood sequence estimation (MLSE) is not practical for large channel delay spreads, minimum mean-squared error decision-feedback equalization (MMSE-DFE) is employed. Two different DFE approaches are considered here: (a) the conventional scalar DFE and (b) a block-based DFE, which is well suited for the underlying vector signal model. For various common indoor channel profiles, numerical results are given for MLSE, scalar DFE and block DFE in terms of bit error rates (BERs) and packet error rates (PERs).
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.receiv

Receivers with Widely Linear Processing for Frequency-Selective Channels - Gerstacker, Wolfgang; Schober, Robert; Lampe, Alexander (IEEE Transactions on Communications, 2003)
In this paper, we propose several equalization schemes based on widely linear processing (WLP). The received signal and its complex conjugate are separately filtered and the results are linearly combined. It is shown that WLP yields a gain in performance if the (noiseless) received signal can be interpreted as the convolution of a real-valued data sequence and an equivalent complex-valued intersymbol interference channel impulse response. Such a model applies to, e.g., amplitude-shift keying, offset quadrature amplitude modulation, and binary minimum-shift keying-type modulation. We consider receivers without and with decision feedback. Finite impulse response filters are derived for these structures, which are optimum with respect to the zero-forcing and minimum mean-squared error (MMSE) criterion, respectively. In the MMSE case, adaptive algorithms for filter adjustment are given. Infinite filter orders are investigated in order to obtain analytical performance results. Furthermore, suboptimum trellis-based detection with widely linear preprocessing is briefly discussed. It is demonstrated analytically and by numerical examples that widely linear schemes may outperform conventional schemes significantly, depending on the considered application.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.mobilk.receiv
Keywords: Equalization; Global system for mobile communication (GSM); Intersymbol interference (ISI); Widely linear processing (WLP)

Receiver techniques - Bains, Robert; Müller, Ralf (Springer New York, 2014)
This chapter explores a concept for deploying parasitic elements at the receiver site to achieve a multiplexing gain in MIMO systems. The concept is based on a virtually fast rotating directional receiver antenna, which rotates once or several times per symbol interval. The antenna rotation is obtained by using a single active antenna element and multiple parasitic elements. The antenna rotation results in the same spatial multiplexing, which is also obtained by conventional MIMO receivers with multiple active elements. It is shown that the rotating receiver antenna provides a much higher capacity than a single receiver antenna. It is also shown that the virtual rotation idea can suffer from problems due to adjacent channel interferenc

Receptor Saturation Modeling for Synaptic DMC - Lotter, Sebastian; Schäfer, Maximilian; Zeitler, Johannes; Schober, Robert (ICC 2021 - IEEE International Conference on Communications, 2021)
Synaptic communication is a natural Molecular Communication (MC) system which may serve as a blueprint for the design of synthetic MC systems. In particular, it features highly specialized mechanisms to enable inter-symbol interference (ISI)-free and energy efficient communication. The understanding of synaptic MC is furthermore critical for disruptive innovations in the context of brain-machine interfaces. However, the physical modeling of synaptic MC is complicated by the possible saturation of the molecular receiver arising from the competition of postsynaptic receptors for neurotransmitters. Saturation renders the system behavior nonlinear and is commonly neglected in existing analytical models. In this work, we propose a novel model for receptor saturation in terms of a nonlinear, state-dependent boundary condition for Fick’s diffusion equation. We solve the resulting boundary-value problem using an eigenfunction expansion of the Laplace operator and the incorporation of the receiver memory as feedback system into the corresponding state-space description. The presented solution is numerically stable and computationally efficient. Furthermore, the proposed model is validated with particle-based stochastic computer simulations.
Keywords: Degradation; Neurotransmitters; Computational modeling; Biological system modeling; Stochastic processes; Receivers; Brain modeling

Reconfigurable Intelligent Surface-Aided Multi-User Networks: Interplay Between NOMA and RIS - Liu, Yuanwei; Mu, Xidong; Liu, Xiao; Di Renzo, Marco; Ding, Zhiguo; Schober, Robert (IEEE Wireless Communications, 2022)
This article focuses on the exploitation of reconfigurable intelligent surfaces (RISs) in multiuser networks employing orthogonal multiple access (OMA) or non-orthogonal multiple access (NOMA), with an emphasis on investigating the interplay between NOMA and RIS. Depending on whether the RIS reflection coefficients can be adjusted only once or multiple times during one transmission, we distinguish between static and dynamic RIS configurations. In particular, the capacity region of RIS-aided single-antenna NOMA networks is discussed and compared with the OMA rate region from an information-theoretic perspective, revealing that the dynamic RIS configuration is capacity-achieving. Then, the impact of the RIS deployment location on the performance of different multiple access schemes is investigated, which reveals that asymmetric and symmetric deployment strategies are preferable for NOMA and OMA, respectively. Furthermore, for RIS-aided multiple-antenna NOMA networks, three novel joint active and passive beamformer designs are proposed based on both beamformer-based and cluster-based strategies. Finally, open research problems for RIS-NOMA networks are highlighted.
CRIS-Team WoS Importer:2022-07-08

Reconfigurable Intelligent Surface-Assisted NOMA With Coordinate Reflector Interleaving Under Rician Fading Channel - Asmoro, Krisma; Ramatryana, I Nyoman Apraz; Shin, Soo Young (IEEE Access, 2024)
The concept of reconfigurable intelligent surface-assisted (RIS) for assisting non-orthogonal multiple access (NOMA) transmission, where the phases can be adjusted to decrease error rates and increase capacity, has been gaining popularity as a promising candidate for 6G communication and beyond. This paper considers RIS-NOMA downlink transmission under the Rician fading channel. A coordinate reflector interleaving (CRI) is proposed, where two groups of reflector elements are introduced, such as in-phase element and quadrature element groups. Therefore, it can reduce system complexity because of a reduced number of successive interference cancellations (SIC) among users. As a result, a computer simulation shows that CRI-RIS-NOMA preserves a lower BER compared to conventional RIS-NOMA. Moreover, the superiority of CRI-RIS-NOMA over RIS-NOMA is that it can work at any power allocation for 2 users. This paper comprehensively studies theoretical derivation for 2 and 4 users to verify the computer-simulated BER. An upper-bound analysis of CRI-RIS-NOMA was also studied to observe the impact of RIS elements with respect to transmitting power from a base station.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Bit error rates (BER); coordinate reflector interleaving (CRI); non-orthogonal multiple access (NOMA); reconfigurable intelligent surfaces (RIS); rician fading

Reduced-State Sequence Estimation for Complementary Code Keying - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (Conference Proceedings, 2004)
In this paper, reduced-state sequence estimation (RSSE) designed for complementary code keying (CCK) transmission over frequency-selective fading channels is investigated. An Ungerboeck-like set partitioning of the multidimensional CCK symbol constellation is given. For the proposed RSSE algorithm based on this partitioning, numerical results are provided for a typical indoor wireless channel. A comparison is made with optimum detection and suboptimum decision-feedback equalization (DFE), respectively.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.reduce
Keywords: Complementary code keying; Reduced-state sequence estimation; Set partitioning; WLAN IEEE 802.11b

Relay Selection for Simultaneous Information Transmission and Wireless Energy Transfer: A Tradeoff Perspective - Michalopoulos, Diomidis S.; Suraweera, Himal A.; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2014)
In certain applications, relay terminals can be employed to simultaneously deliver information and energy to a designated receiver and a set of radio frequency (RF) energy harvesters, respectively. In such scenarios, the relay that is preferable for information transmission does not necessarily coincide with the relay that is preferable for energy transfer, since the corresponding channels fade independently. Relay selection thus entails a tradeoff between the efficiency of the information transmission to the receiver and the amount of energy transferred to the energy harvesters. The study of this tradeoff is the subject on which this work mainly focuses. Specifically, we investigate the dependence of the ergodic capacity and the outage probability of the information transmission to the receiver on the amount of energy transferred to the RF energy harvesters. We propose a relay selection policy that yields the optimal tradeoff in a maximum capacity/minimum outage probability sense, for a given energy transfer constraint. We also propose two suboptimal relay selection methods that apply to scenarios with limited availability of channel state information. Additionally, we propose a suboptimal scheme which approximates the optimal scheme for the special case of two relays and facilitates performance analysis. Interesting insights on the aforementioned tradeoffs are unveiled.<br
Keywords: Relays; Energy exchange; Information processing; Signal to noise ratio; Radio frequency; Energy harvesting; Measurement

Rényi Entropy Bounds on the Active Learning Cost-Performance Tradeoff - Jamali, Vahid; Tulino, Antonia; Llorca, Jaime; Erkip, Elza (IEEE International Symposium on Information Theory - Proceedings, 2020)
Semi-supervised classification, one of the most prominent fields in machine learning, studies how to combine the statistical knowledge of the often abundant unlabeled data with the often limited labeled data in order to maximize overall classification accuracy. In this context, the process of actively choosing the data to be labeled is referred to as active learning. In this paper, we initiate the non-asymptotic analysis of the optimal policy for semi-supervised classification with actively obtained labeled data. Considering a general Bayesian classification model, we provide the first characterization of the jointly optimal active learning and semi-supervised classification policy, in terms of the cost-performance tradeoff driven by the label query budget (number of data items to be labeled) and overall classification accuracy. Leveraging recent results on the Rényi Entropy, we derive tight information-theoretic bounds on such active learning cost-performance tradeoff.
CRIS-Team Scopus Importer:2020-09-18

Repeated Intersession Network Coding Games: Efficiency and Min-Max Bargaining Solution - Mohsenian-Rad, Hamed; Huang, Jianwei; Wong, Vincent W.S.; Schober, Robert (IEEE-ACM Transactions on Networking, 2013)
Recent results have shown that selfish users do not have an incentive to participate in intersession network coding in a static noncooperative game setting. Because of this, the worst-case network efficiency (i.e., the price-of-anarchy) can be as low as 20%. In this paper, we show that if the same game is played repeatedly, then the price-of-anarchy can be improved to 36%. We design a grim-trigger strategy that encourages users to cooperate and participate in the intersession network coding. A key challenge is to determine a common cooperative coding rate that the users should mutually agree on. We resolve the conflict of interest among the users through a bargaining process and obtain tight upper bounds for the price-of-anarchy that are valid for any possible bargaining scheme. Moreover, we propose a simple and efficient min-max bargaining solution that can achieve these upper bounds, as confirmed through simulation studies. The coexistence of multiple selfish network coding sessions as well as the coexistence of selfish network coding and routing sessions are also investigated. Our results represent a first step toward designing practical intersession network coding schemes that achieve reasonable performance for selfish users.<br
Keywords: Network coding; Games; Encoding; Routing; Nash equilibrium; Resource management; History

Replica analysis of general multiuser detection in MIMO DS-CDMA channels with imperfect CSI - Takeuchi, Keigo; Vehkaperä, Mikko; Tanaka, Toshiyuki; Müller, Ralf (2008 IEEE International Symposium on Information Theory, ISIT 2008, 2008)
We consider impacts of channel estimation errors on performance of general multiuser detectors in MIMO DS-CDMA channels. We evaluate their performance in terms of asymptotic spectral efficiency, which is obtained via decoupling structure, by using the replica method. Numerical results imply that the performance of LMMSE detection is very close to that of MMSE detection for small system loads. Furthermore, we find that the spectral efficiency of MMSE detection grows discontinuously with the length of pilot sequences for large system loads, and that the critical length is close to the optimal length. While it is indistinguishable from that of LMMSE detection for short pilot sequences, the gap between the two is significantly large if the length of pilot sequences is longer than the critical length. © 2008 IEEE.

Replica Symmetry Breaking in Compressive Sensing - Bereyhi, Ali; Schulz-Baldes, Hermann; Müller, Ralf (Information Theory and Applications Workshop (ITA), 2017)
For noisy compressive sensing systems, the asymptotic distortion with respect to an arbitrary distortion function is determined when a general class of least-square based reconstruction schemes is employed. The sampling matrix is considered to belong to a large ensemble of random matrices including i.i.d. and projector matrices, and the source vector is assumed to be i.i.d. with a desired distribution. We take a statistical mechanical approach by representing the asymptotic distortion as a macroscopic parameter of a spin glass and employing the replica method for the large-system analysis. In contrast to earlier studies, we evaluate the general replica ansatz which includes the RS ansatz as well as RSB. The generality of the solution enables us to study the impact of symmetry breaking. Our numerical investigations depict that for the reconstruction scheme with the "zero-norm" penalty function, the RS fails to predict the asymptotic distortion for relatively large compression rates; however, the one-step RSB ansatz gives a valid prediction of the performance within a larger regime of compression rates.
Keywords: STATISTICAL-MECHANICS; SPIN-GLASSES; CODES

Residential Demand Side Management Under High Penetration of Rooftop Photovoltaic Units - Yao, Enxin; Samadi, Pedram; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2015)
In a residential area where many households have installed rooftop photovoltaic (PV) units, there is a reverse power flow from the households to the substation when the power generation from PV units is larger than the aggregate load of the households. This reverse power flow causes the voltage rise problem. In this paper, we study the use of demand side management to mitigate the voltage rise problem. We propose an autonomous energy consumption scheduling algorithm, which schedules the operation of deferrable loads to jointly shave the peak load and reduce the reverse power flow. The proposed algorithm shifts the operation of deferrable loads from peak consumption hours to hours with high-power generation from the PV units. We use stochastic programming to formulate an energy consumption scheduling problem, which takes into account the uncertainty related to the amount of power generation from PV units. The formulated cost function comprises a monetary cost for energy consumption, the revenue from energy export, and an external cost for the voltage rise. Numerical results show that our proposed algorithm can mitigate the voltage rise problem in areas with high penetration of PV units and reduce the peak-to-average ratio of the aggregate load.<br
Keywords: Energy consumption; Cost function; Companies; Pricing; System-on-chip; Solar power generation

Resource Allocation and 3D Trajectory Design for Power-Efficient IRS-Assisted UAV-NOMA Communications - Cai, Yuanxin; Wei, Zhiqiang; Hu, Shaokang; Liu, Chang; Ng, Derrick Wing Kwan; Yuan, Jinhong (IEEE Transactions on Wireless Communications, 2022)
In this paper, an intelligent reflecting surface (IRS) is introduced to assist an unmanned aerial vehicle (UAV) communication system based on non-orthogonal multiple access (NOMA) for serving multiple ground users. We aim to minimize the average total system energy consumption by jointly designing the resource allocation strategy, the three dimensional (3D) trajectory of the UAV, as well as the phase control at the IRS. The design is formulated as a non-convex optimization problem taking into account the maximum tolerable outage probability constraint and the individual minimum data rate requirement. To circumvent the intractability of the design problem due to the altitude-dependent Rician fading in UAV-to-user links, we adopt the deep neural network (DNN) approach to accurately approximate the corresponding effective channel gains, which facilitates the development of a low-complexity suboptimal iterative algorithm via dividing the formulated problem into two subproblems and address them alternatingly. Numerical results demonstrate that the proposed algorithm can converge to an effective solution within a small number of iterations and illustrate some interesting insights: (1) IRS enables a highly flexible UAV's 3D trajectory design via recycling the dissipated radio signal for improving the achievable system data rate and reducing the flight power consumption of the UAV; (2) IRS provides a rich array gain through passive beamforming in the reflection link, which can substantially reduce the required communication power for guaranteeing the required quality-of-service (QoS); (3) Optimizing the altitude of UAV's trajectory can effectively exploit the outage-guaranteed effective channel gain to save the total required communication power enabling power-efficient UAV communications; (4) NOMA communications offer higher degrees of freedom (DoF) than that of the conventional orthogonal multiple access (OMA) scheme to minimize the average power consumption via optimizing the UAV's trajectory.
CRIS-Team WoS Importer:2023-02-24

Resource Allocation for Active IRS-Assisted Multiuser Communication Systems - Xu, Dongfang; Yu, Xianghao; Kwan Ng, Derrick Wing; Schober, Robert (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2021)
Intelligent reflecting surfaces (IRSs) are emerging as promising enablers for the next generation of wireless communication systems, because of their ability to customize favorable radio propagation environments. However, with the conventional passive architecture, IRSs can only adjust the phase of the incident signals limiting the achievable beamforming gain. To fully unleash the potential of IRSs, in this paper, we consider a more general IRS architecture, i.e., active IRSs, which can adapt the phase and amplify the magnitude of the reflected incident signal simultaneously with the support of an additional power source. To realize green communication in active IRS-assisted multiuser systems, we jointly optimize the reflection matrix at the IRS and the beamforming vector at the base station (BS) for the minimization of the BS transmit power. The resource allocation algorithm design is formulated as an optimization problem taking into account the maximum power budget of the active IRS and the quality-of-service (QoS) requirements of the users. To handle the non-convex design problem, we develop a novel and computationally efficient algorithm based on the bilinear transformation and inner approximation methods. The proposed algorithm is guaranteed to converge to a locally optimal solution of the considered problem. Simulation results illustrate the effectiveness of the proposed scheme compared to two baseline schemes. Moreover, the results unveil that deploying active IRSs is a promising approach to enhance the system performance compared to conventional passive IRSs, especially when strong direct links exist.
CRIS-Team Scopus Importer:2022-06-05

Resource allocation for coordinated multipoint networks with wireless information and power transfer - Ng, Derrick Wing Kwan; Schober, Robert (2014 IEEE Global Communications Conference, GLOBECOM 2014, 2014)
This paper studies the resource allocation algorithm design for multiuser coordinated multipoint (CoMP) networks with simultaneous wireless information and power transfer (SWIPT). In particular, remote radio heads (RRHs) are connected to a central processor (CP) via capacity-limited backhaul links to facilitate CoMP joint transmission. Besides, the CP transfers energy to the RRHs for more efficient network operation. The considered resource allocation algorithm design is formulated as a non-convex optimization problem with a minimum required signal-to-interference-plus-noise ratio (SINR) constraint at multiple information receivers and a minimum required power transfer constraint at the energy harvesting receivers. By optimizing the transmit beamforming vectors at the CP and energy sharing between the CP and the RRHs, we aim at jointly minimizing the total network transmit power and the maximum capacity consumption per backhaul link. The resulting non-convex optimization problem is NP-hard. In light of the intractability of the problem, we reformulate it by replacing the non-convex objective function with its convex hull, which enables the derivation of an efficient iterative resource allocation algorithm. In each iteration, a non-convex optimization problem is solved by semi-definite programming (SDP) relaxation and the proposed iterative algorithm converges to a local optimal solution of the original problem. Simulation results illustrate that our proposed algorithm achieves a close-to-optimal performance and provides a significant reduction in backhaul capacity consumption compared to full cooperation. Besides, the considered CoMP network is shown to provide superior system performance as far as power consumption is concerned compared to a traditional system with multiple antennas co-located.
CRIS-Team Scopus Importer:2020-02-03

Resource Allocation for GSM MUROS/VAMOS - Gerstacker, Wolfgang (Electrical and Electronic Engineering for Communication Workshop - Entwicklerforum - Fachmesse, 2012)
elib2cris::1512001600,gerstacked2012

Resource Allocation for Intelligent Reflecting Surface-Assisted Cognitive Radio Networks - Xu, Dongfang; Yu, Xianghao; Schober, Robert (PROCEEDINGS OF THE 21ST IEEE INTERNATIONAL WORKSHOP ON SIGNAL PROCESSING ADVANCES IN WIRELESS COMMUNICATIONS (IEEE SPAWC2020), 2020)
CRIS-Team WoS Importer:2021-03-05

Resource Allocation for Intelligent Reflecting Surface-Assisted Cognitive Radio Networks - Xu, Dongfang; Yu, Xianghao; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2020)
In this paper, we investigate resource allocation algorithm design for intelligent reflecting surface (IRS)-Assisted multiuser cognitive radio (CR) systems. In particular, an IRS is deployed to mitigate the interference caused by the secondary network to the primary users. The beamforming vectors at the base station (BS) and the phase shift matrix at the IRS are jointly optimized for maximization of the sum rate of the secondary system. The algorithm design is formulated as a non-convex optimization problem taking into account the maximum interference tolerance of the primary users. To tackle the resulting non-convex optimization problem, we propose an alternating optimization-based suboptimal algorithm exploiting semidefinite relaxation, the penalty method, and successive convex approximation. Our simulation results show that the system sum rate is dramatically improved by our proposed scheme compared to two baseline schemes. Moreover, our results also illustrate the benefits of deploying IRSs in CR networks.
CRIS-Team Scopus Importer:2020-09-18

Resource Allocation for IRS-Assisted Full-Duplex Cognitive Radio Systems - Xu, Dongfang; Yu, Xianghao; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2020)
In this article, we investigate the resource allocation design for intelligent reflecting surface (IRS)-assisted full-duplex (FD) cognitive radio systems. In particular, a secondary network employs an FD base station (BS) for serving multiple half-duplex downlink (DL) and uplink (UL) users simultaneously. An IRS is deployed to enhance the performance of the secondary network while helping to mitigate the interference caused to the primary users (PUs). The DL transmit beamforming vectors and the UL receive beamforming vectors at the FD BS, the transmit power of the UL users, and the phase shift matrix at the IRS are jointly optimized for maximization of the total spectral efficiency of the secondary system. The design task is formulated as a non-convex optimization problem taking into account the imperfect knowledge of the PUs' channel state information (CSI) and their maximum interference tolerance. Since the maximum interference tolerance constraint is intractable, we apply a safe approximation to transform it into a convex constraint. To efficiently handle the resulting approximated optimization problem, which is still non-convex, we develop an iterative block coordinate descent (BCD)-based algorithm. This algorithm exploits semidefinite relaxation, a penalty method, and successive convex approximation and is guaranteed to converge to a stationary point of the approximated optimization problem. Our simulation results do not only reveal that the proposed scheme yields a substantially higher system spectral efficiency for the secondary system than several baseline schemes, but also confirm its robustness against CSI uncertainty. Besides, our results illustrate the tremendous potential of IRS for managing the various types of interference arising in FD cognitive radio networks.
CRIS-Team WoS Importer:2021-01-08

Resource Allocation for Large IRS-Assisted SWIPT Systems with Non-linear Energy Harvesting Model - Xu, Dongfang; Yu, Xianghao; Jamali Kooshkghazi, Vahid; Ng, Derrick Wing Kwan; Schober, Robert (2021 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2021)
CRIS-Team WoS Importer:2021-10-29

Resource Allocation for MC-NOMA Systems with Cognitive Relaying - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we investigate the resource allocation algorithm design for cooperative cognitive relaying multicarrier non-orthogonal multiple access (MC-NOMA) systems. In particular, the secondary base station serves multiple secondary users and simultaneously acts as a relay assisting the information transmission in the primary network. The resource allocation aims to maximize the weighted system throughput by jointly optimizing the power and subcarrier allocation for both the primary and the secondary networks while satisfying the quality-of-service requirements of the primary users. The algorithm design is formulated as a mixed combinatorial non-convex optimization problem. We apply monotonic optimization theory to solve the problem leading to an optimal resource allocation policy. Besides, we develop a low-complexity scheme to find a suboptimal solution. Our simulation results reveal that the performance of the proposed suboptimal algorithm closely approaches that of the optimal one. Besides, the combination of MC-NOMA and cognitive relaying improves the system throughput considerably compared to conventional multicarrier cognitive relaying systems.

Resource Allocation for Multi-User Downlink MISO OFDMA-URLLC Systems - Ghanem, Walid; Jamali, Vahid; Sun, Yan; Schober, Robert (IEEE Transactions on Communications, 2020)
This article considers the resource allocation algorithm design for downlink multiple-input single-output (MISO) orthogonal frequency division multiple access (OFDMA) ultra-reliable low latency communication (URLLC) systems. To meet the stringent delay requirements of URLLC, short packet transmission is adopted and taken into account for resource allocation algorithm design. The resource allocation is optimized for maximization of the weighted system sum throughput subject to quality-of-service (QoS) constraints regarding the URLLC users' number of transmitted bits, packet error probability, and delay. Despite the non-convexity of the resulting optimization problem, the optimal solution is found via monotonic optimization. The corresponding optimal resource allocation policy can serve as a performance upper bound for sub-optimal low-complexity solutions. We develop such a low-complexity sub-optimal resource allocation algorithm based on successive convex approximation and difference of convex programming. Our simulation results reveal the importance of using multiple antennas for reducing the latency and improving the reliability of URLLC systems. Moreover, the proposed sub-optimal algorithm is shown to closely approach the performance of the proposed optimal algorithm and outperforms two baseline schemes by a considerable margin, especially when the users have heterogeneous delay requirements. Finally, conventional resource allocation designs based on Shannon's capacity formula are shown to be not applicable in MISO OFDMA-URLLC systems as they are not able to guarantee the users' delay constraints.
CRIS-Team Scopus Importer:2020-12-04
Keywords: monotonic optimization; orthogonal frequency division multiple access (OFDMA); Resource allocation; short packet transmission; ultra-reliable low latency communication (URLLC)

Resource Allocation for Multi-User Downlink URLLC-OFDMA Systems - Ghanem, Walid; Jamali Kooshkghazi, Vahid; Sun, Yan; Schober, Robert (2019 IEEE International Conference on Communications Workshops (ICC Workshops), 2019)
In this paper, we study resource allocation for downlink orthogonal frequency division multiple access (OFDMA) systems with the objective to enable ultra-reliable low latency communication (URLLC). To meet the stringent delay requirements of URLLC, the impact of short packet communication is taken into account for resource allocation algorithm design. In particular, the resource allocation design is formulated as a weighted system sum throughput maximization problem with quality-of-service (QoS) constraints for the URLLC users. The formulated problem is non-convex, and hence, finding the global optimum solution entails a high computational complexity. Thus, an algorithm based on successive convex optimization is proposed to find a sub-optimal solution with polynomial time complexity. Simulation results confirm that the proposed algorithm facilities URLLC and significantly improves the system sum throughput compared to two benchmark schemes.<br

Resource Allocation for Outdoor-to-Indoor Amplify-and-Forward SUDAS with Independent Relay Processing - Goodarzi, Meysam; Krishnamoorthy, Aravindh; Schober, Robert; Breiling, Marco (SCC 2019; 12th International ITG Conference on Systems, Communications and Coding, 2019)
In this work, we study resource allocation for a downlink multicarrier outdoor-to-indoor transmission system employing a shared user equipment (UE)-side distributed antenna system (SUDAS) with independently operating amplifyand-forward (AF) relays which utilize both licensed and unlicensed frequency bands to enhance indoor data throughput and coverage. We formulate a non-convex matrix-valued resource allocation problem for maximization of the sum rate. The nonconvex problem is simplified to a scalar optimization problem using an approximation in order to obtain a low-complexity algorithm based on alternating optimization (AO). Simulation results illustrate that despite the simplification, the proposed algorithm achieves excellent performance in terms of the sum rate and closely approaches the max-flow min-cut upper bound. The proposed SUDAS scheme facilitates low-complexity outdoor-to-indoor communication for next-generation wireless systems.<br

Resource Allocation for Outdoor-to-Indoor Compress-and-Forward SUDAS with Independent Relay Processing - Krishnamoorthy, Aravindh; Schober, Robert; Breiling, Marco (Vehicular Technology Conference (VTC-Fall), 2017)
In this paper, we consider resource allocation for an outdoor-to-indoor shared user-equipment (UE)-side distributed antenna system (SUDAS) employing multiple independently operating compress-and-forward (CF) relays which utilize both licensed and unlicensed frequency bands to enhance indoor data throughput. First, a non-convex matrix-valued resource allocation problem for maximization of the weighted sum rate is formulated. Next, the non-convex problem is simplified to obtain a low-complexity suboptimal resource allocation algorithm based on sequential quadratic programming (SQP). The proposed algorithm is shown to provide excellent performance in practical scenarios. Furthermore, the algorithm has a low channel state information (CSI) feedback requirement and can accommodate arbitrary communication bands and technologies for indoor relaying. Therefore, the proposed CF-SUDAS scheme can help achieve high outdoor-to-indoor data throughput at low complexity, a crucial requirement for next generation wireless communication systems.
Keywords: Relays; Resource Management; MIMO communication; Quantization (signal); Antennas; Covariance matrices; Bandwidth

Resource Allocation for Outdoor-to-Indoor Multicarrier Transmission with Shared UE-Side Distributed Antenna Systems - Breiling, Marco; Ng, Derrick Wing Kwan; Rohde, Christian; Burkhardt, Frank; Schober, Robert (2015 IEEE 81st Vehicular Technology Conference (VTC Spring), 2015)
In this paper, we study the resource allocation algorithm design for downlink multicarrier transmission with a shared user equipment (UE)-side distributed antenna system (SUDAS) which utilizes both licensed and unlicensed frequency bands for improving the system throughput. The joint UE selection and transceiver processing matrix design is formulated as a non-convex optimization problem for the maximization of the end-to-end system throughput (bits/s). In order to obtain a tractable resource allocation algorithm, we first show that the optimal transmitter precoding and receiver post-processing matrices jointly diagonalize the end-to-end communication channel. Subsequently, the optimization problem is converted to a scalar optimization problem for multiple parallel channels, which is solved by using an asymptotically optimal iterative algorithm. Simulation results illustrate that the proposed resource allocation algorithm for the SUDAS achieves an excellent system performance and provides a spatial multiplexing gain for single-antenna UEs.<br
Keywords: Resource management; Optimization; OFDM; MIMO; Downlink; Bandwidth; Algorithm design and analysis

Resource Allocation for Secure Full-Duplex OFDMA Radio Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we study the resource allocation for an orthogonal frequency division multiple access (OFDMA) radio system employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. The resource allocation design objective is the maximization of the weighted system throughput while limiting the information leakage to guarantee secure simultaneous downlink and uplink transmission in the presence of potential eavesdroppers. The algorithm design leads to a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution entails a prohibitively high computational complexity. Therefore, an efficient successive convex approximation based suboptimal iterative algorithm is proposed. Our simulation results confirm that the proposed suboptimal algorithm achieves a significant performance gain compared to two baseline schemes.

Resource Allocation for Secure Full-Duplex OFDMA Radio Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we study the resource allocation for an orthogonal frequency division multiple access (OFDMA) radio system employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. The resource allocation design objective is the maximization of the weighted system throughput while limiting the information leakage to guarantee secure simultaneous downlink and uplink transmission in the presence of potential eavesdroppers. The algorithm design leads to a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution entails a prohibitively high computational complexity. Therefore, an efficient successive convex approximation based suboptimal iterative algorithm is proposed. Our simulation results confirm that the proposed suboptimal algorithm achieves a significant performance gain compared to two baseline schemes.

Resource allocation for secure full-duplex OFDMA radio systems : (Invited paper) - Sun, Yan; Wing Kwan Ng, Derrick; Schober, Robert (2017 IEEE 18th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2017)
In this paper, we study the resource allocation for an orthogonal frequency division multiple access (OFDMA) radio system employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. The resource allocation design objective is the maximization of the weighted system throughput while limiting the information leakage to guarantee secure simultaneous downlink and uplink transmission in the presence of potential eavesdroppers. The algorithm design leads to a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution entails a prohibitively high computational complexity. Therefore, an efficient successive convex approximation based suboptimal iterative algorithm is proposed. Our simulation results confirm that the proposed suboptimal algorithm achieves a significant performance gain compared to two baseline schemes.<br
Keywords: Resource management; Silicon; Optimization; Wireless communication; Covariance matrices; High definition video; Throughput

Resource Allocation for Secure IRS-assisted Multiuser MISO Systems - Xu, Dongfang; Yu, Xianghao; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2019 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2019)
CRIS-Team WoS Importer:2020-08-21

Resource Allocation for Secure Multi-User Downlink MISO-URLLC Systems - Ghanem, Walid; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE International Conference on Communications, 2020)
In this paper, we study resource allocation algorithm design for secure multi-user downlink ultra-reliable low latency communication (URLLC). To enhance physical layer security (PLS), the base station (BS) is equipped with multiple antennas and artificial noise (AN) is injected by the BS to impair the eavesdroppers' channels. To meet the stringent delay requirements in secure URLLC systems, short packet transmission (SPT) is adopted and taken into consideration for resource allocation design. The resource allocation algorithm design is formulated as an optimization problem for minimization of the total transmit power, while guaranteeing qualityof-service (QoS) constraints regarding the URLLC users' number of transmitted bits, packet error probability, information leakage, and delay. Due to the non-convexity of the optimization problem, finding a global solution entails a high computational complexity. Thus, we propose a low-complexity algorithm based successive convex approximation (SCA) to find a sub-optimal solution. Our simulation results show that the proposed resource allocation algorithm design ensures the secrecy of the URLLC users' transmissions, and yields significant power savings compared to a baseline scheme.
CRIS-Team Scopus Importer:2020-08-28

Resource Allocation for Simultaneous Wireless Information and Power Transfer Systems: A Tutorial Overview - Wei, Zhiqiang; Yu, Xianghao; Ng, Derrick Wing Kwan; Schober, Robert (Proceedings of the IEEE, 2021)
Over the last decade, simultaneous wireless information and power transfer (SWIPT) has become a practical and promising solution for connecting and recharging battery-limited devices due to significant advances in low-power electronics technology and wireless communications techniques. To realize the promised potentials, advanced resource allocation design plays a decisive role in revealing, understanding, and exploiting the intrinsic rate-energy tradeoff capitalizing on the dual use of radio frequency (RF) signals for wireless charging and communication. In this article, we provide a comprehensive tutorial overview of SWIPT from the perspective of resource allocation design. The fundamental concepts, system architectures, and RF energy harvesting (EH) models are introduced. In particular, three commonly adopted EH models, namely, the linear EH model, the nonlinear saturation EH model, and the nonlinear circuit-based EH model, are characterized and discussed. Then, for a typical wireless system setup, we establish a generalized resource allocation design framework that subsumes conventional resource allocation design problems as special cases. Subsequently, we elaborate on relevant tools from optimization theory and exploit them for solving representative resource allocation design problems for SWIPT systems with and without perfect channel state information (CSI) available at the transmitter, respectively. The associated technical challenges and insights are also highlighted. Furthermore, we discuss several promising and exciting future research directions for resource allocation design for SWIPT systems intertwined with cutting-edge communication technologies, such as intelligent reflecting surfaces, unmanned aerial vehicles, mobile edge computing, federated learning, and machine learning.
Keywords: Wireless communication; Resource management; Wireless sensor networks; Integrated circuit modeling; Radio frequency; Systems architecture; RF signals; optimization; resource allocation; simultaneous wireless information and power transfer (SWIPT); wireless pwoer transfer (WPT)

Resource Allocation for Solar Powered UAV Communication Systems - Sun, Yan; Wing Kwan Ng, Derrick; Xu, Dongfang; Dai, Linglong; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2018)
In this paper, we investigate the resource allocation design for multicarrier (MC) systems employing a solar powered unmanned aerial vehicle (UAV) for providing communication services to multiple downlink users. We study the joint design of the three-dimensional positioning of the UAV and the power and subcarrier allocation for maximization of the system sum throughput. The algorithm design is formulated as a mixed-integer non-convex optimization problem, which requires a prohibitive computational complexity for obtaining the globally optimal solution. Therefore, a low-complexity suboptimal iterative solution based on successive convex approximation is proposed. Simulation results confirm that the proposed suboptimal algorithm achieves a substantially higher system sum throughput compared to several baseline schemes.
CRIS-Team Scopus Importer:2020-01-31

Resource allocation for wireless communication networks with RF energy harvesting - Boshkovska, Elena; Ng, Derrick Wing Kwan; Schober, Robert (From Internet of Things to Smart Cities: Enabling Technologies, 2017)
The successful development of wireless communication networks and technologies has triggered an exponential growth in the number of wireless communication devices worldwide. In the near future, devices embedded with multifunctional sensors and communication chip sets will be able to collect and exchange information via the Internet. Specifically, these smart devices will be connected to computationally powerful central computing systems to provide intelligent services for the daily life such as environmental monitoring, e-health, automated control, energy management, logistics, and safety management. This new concept of interconnecting a massive number of communication and sensing devices is known as the Internet of Things (IoT).
CRIS-Team Scopus Importer:2020-01-31

RIS-Assisted Device Activity Detection with Statistical Channel State Information - Laue, Friedemann; Jamali, Vahid; Schober, Robert (IEEE Transactions on Wireless Communications, 2023)
This paper studies reconfigurable intelligent surface (RIS)-assisted device activity detection for grant-free (GF) uplink transmission in wireless communication networks. In particular, we consider mobile devices located in an area where the direct link to an access point (AP) is blocked. Thus, the devices try to connect to the AP via a reflected link provided by an RIS. Therefore, for the RIS, a phase-shift design is desired that covers the entire blocked area with a wide reflection beam because the exact locations and times of activity of the devices are unknown in GF transmission. In order to study the impact of the phase-shift design on the device activity detection at the AP, we derive a generalized likelihood ratio test (GLRT) based detector and present an analytical expression for the probability of detection, which is a function of the channel statistics and the phase-shift design. Assuming knowledge of statistical channel state information (CSI), we formulate an optimization problem for the phase-shift design for maximization of the guaranteed probability of detection for all locations within a given coverage area. To tackle the non-convexity of the problem, we propose two different approximations of the objective function and an algorithm based on the majorization-minimization (MM) principle. The first approximation leads to a design that aims to reduce the variations of the end-to-end channel while taking system parameters such as transmit power, noise power, and probability of false alarm into account. The second approximation can be adopted for versatile RIS deployments because it only depends on the line-of-sight (LoS) component of the end-to-end channel and is not affected by system parameters. For comparison, we also consider a phase-shift design maximizing the average channel gain and a baseline analytical phase-shift design for large blocked areas. Our performance evaluation shows that the proposed approximations result in phase-shift designs that guarantee a high probability of detection across the coverage area and outperform the baseline designs.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Channel models; coverage extension; Detectors; Device activity detection; grant-free uplink; Mobile handsets; Optimization; Performance evaluation; phase-shift design; Probability; reconfigurable intelligent surface; Reflection; statistical channel state information

Risk-averse forward contract for electric vehicle frequency regulation service - Yao, Enxin; Wong, Vincent W. S.; Schober, Robert (2015 IEEE International Conference on Smart Grid Communications (SmartGridComm, 2015)
Electric vehicles (EVs) can be coordinated by an aggregator to participate in the electricity day-ahead market (DAM) and provide frequency regulation service. In the DAM, a short-term forward contract is made between the aggregator and an independent system operator (ISO). The contract specifies the contract size, which is the amount of regulation capacity provided by the aggregator for each hour of the next day. However, since the capacity of the aggregator is provided by many EVs instead of a single source, the challenge is how to efficiently aggregate the small and uncertain individual capacity and determine the optimal size of the forward contract. We consider two cases for the contract between the aggregator and the ISO. In the first case, the aggregator needs to ensure that the capacity provided by the EVs on the next day will meet the amount specified in the contract. In contrast, in the second case, the ISO allows an update of the contract size. A stochastic program is formulated to determine the contract size for both cases. Our problem formulation incorporates risk management using the conditional value at risk (CVaR). Chance constraints are embedded when the contract size is fixed. We tackle the chance constraints using the Markov inequality and propose an efficient algorithm. The EV charging data collected in the province of British Columbia, Canada, is used to evaluate the performance of the proposed algorithm. Simulation results show that the proposed algorithm improves the revenue of the aggregator compared to an existing algorithm from the literature.<br
Keywords: Forward contracts; ISO; Frequency control; Smart grids; Microgrids; Real-time systems

RISMA: Reconfigurable Intelligent Surfaces Enabling Beamforming for IoT Massive Access - Mursia, Placido; Sciancalepore, Vincenzo; Garcia-Saavedra, Andres; Cottatellucci, Laura; Costa-Perez, Xavier; Gesbert, David (IEEE Journal on Selected Areas in Communications, 2020)
Massive access for Internet-of-Things (IoT) in beyond 5G networks represents a daunting challenge for conventional bandwidth-limited technologies. Millimeter-wave technologies (mmWave)— which provide large chunks of bandwidth at the cost of more complex wireless processors in harsher radio environments— is a promising alternative to accommodate massive IoT but its cost and power requirements are an obstacle for wide adoption in practice. In this context, meta-materials arise as a key innovation enabler to address this challenge by Re-configurable Intelligent Surfaces (RISs). In this paper we take on the challenge and study a beyond 5G scenario consisting of a multi-antenna base station (BS) serving a large set of single-antenna user equipments (UEs) with the aid of RISs to cope with non-line-of-sight paths. Specifically, we build a mathematical framework to jointly optimize the precoding strategy of the BS and the RIS parameters in order to minimize the system sum mean squared error (SMSE). This novel approach reveals convenient properties used to design two algorithms, RISMA and Lo-RISMA, which are able to either find simple and efficient solutions to our problem (the former) or accommodate practical constraints with low-resolution RISs (the latter). Numerical results show that our algorithms outperform conventional benchmarks that do not employ RIS (even with low-resolution meta-surfaces) with gains that span from 20% to 120& in sum rate performance.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 6G; Beamforming; Beyond-5G; IoT; Massive access; mmWave; Re-configurable intelligent surfaces; RISs

RLS-Based Detection for Massive Spatial Modulation MIMO - Bereyhi, Ali; Asaad, Saba; Gäde, Bernhard; Müller, Ralf (IEEE International Symposium on Information Theory - Proceedings, 2019)
Most detection algorithms in spatial modulation (SM) are formulated as linear regression via the regularized least-squares (RLS) method. In this method, the transmit signal is estimated by minimizing the residual sum of squares penalized with some regularization. This paper studies the asymptotic performance of a generic RLS-based detection algorithm employed for recovery of SM signals. We derive analytically the asymptotic average mean squared error and the error rate for the class of bi-unitarily invariant channel matrices.The analytic results are employed to study the performance of SM detection via the box-LASSO. The analysis demonstrates that the performance characterization for i.i.d. Gaussian channel matrices is valid for matrices with non-Gaussian entries, as well. This justifies the partially approved conjecture given in [1]. The derivations further extend the former studies to scenarios with non-i.i.d. channel matrices. Numerical investigations validate the analysis, even for practical system dimensions.
CRIS-Team Scopus Importer:2019-10-22

RLS Precoding for Massive MIMO Systems with Nonlinear Front-End - Bereyhi, Ali; Asaad, Saba; Müller, Ralf; Chatzinotas, Symeon (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2019)
To keep massive MIMO systems cost-efficient, power amplifiers with rather small output dynamic ranges are employed. They may distort the transmit signal and degrade the performance. This paper proposes a distortion aware precoding scheme for realistic scenarios in which RF chains have nonlinear characteristics. The proposed scheme utilizes the method of regularized least-squares (RLS) to jointly compensate the channel impacts and the distortion imposed by the RF chains. To construct the designed transmit waveform with low computational complexity, an iterative algorithm based on approximate message passing is developed. This algorithm is shown to track the achievable average signal distortion of the proposed scheme tightly, even for practical system dimensions. The results demonstrate considerable enhancement compared to the state of the art.
CRIS-Team Scopus Importer:2019-09-27
Keywords: approximate message passing; massive MIMO; nonlinear power amplifiers; Precoding; regularized least-squares

RLS Recovery with Asymmetric Penalty: Fundamental Limits and Algorithmic Approaches - Bereyhi, Ali; Sedaghat, Mohammad Ali; Müller, Ralf (International Balkan Conference on Communications and Networking (BalkanCom), 2018)
This paper studies regularized least square recovery of signals whose samples' prior distributions are nonidentical, e.g., signals with time-variant sparsity. For this model, Bayesian framework suggests to regularize the least squares term with an asymmetric penalty. We investigate this problem in two respects: First, we characterize the asymptotic performance via the replica method and then discuss algorithmic approaches to the problem. Invoking the asymptotic characterization of the performance, we propose a tuning strategy to optimally tune the algorithmic approaches for recovery. To demonstrate applications of the results, the particular example of BPSK recovery is investigated and the efficiency of the proposed strategy is depicted in the shadow of results available in the literature.
Keywords: RLS regression method; Replica method; Approximate message passing

Robust and Secure Resource Allocation for Full-Duplex MISO Multicarrier NOMA Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zhu, Jun; Schober, Robert (IEEE Transactions on Communications, 2018)
In this paper, we study the resource allocation algorithm design for multiple-input single-output (MISO) multicarrier non-orthogonal multiple access (MC-NOMA) systems, in which a full-duplex base station serves multiple half-duplex uplink and downlink users on the same subcarrier simultaneously. The resource allocation is optimized for maximization of the weighted system throughput while the information leakage is constrained and artificial noise is injected to guarantee secure communication in the presence of multiple potential eavesdroppers. To this end, we formulate a robust non-convex optimization problem taking into account the imperfect channel state information of the eavesdropping channels and the quality-of-service requirements of the legitimate users. Despite the non-convexity of the optimization problem, we solve it optimally by applying monotonic optimization which yields the optimal beamforming, artificial noise design, subcarrier allocation, and power allocation policy. The optimal resource allocation policy serves as a performance benchmark since the corresponding monotonic optimization-based algorithm entails a high computational complexity. Hence, we also develop a low-complexity suboptimal resource allocation algorithm which converges to a locally optimal solution. Our simulation results reveal that the performance of the suboptimal algorithm closely approaches that of the optimal algorithm. Besides, the proposed optimal MISO NOMA system can not only ensure downlink and uplink communication security simultaneously but also provides a significant system secrecy rate improvement compared with the traditional MISO orthogonal multiple access systems and two other baseline schemes.<br
Keywords: physical layer security; full-duplex radio; multicarrier systems; imperfect channel state information; Non-orthogonal multiple access (NOMA); non-convex and combinatorial optimization

Robust and Secure Resource Allocation for ISAC Systems: A Novel Optimization Framework for Variable-Length Snapshots - Xu, Dongfang; Yu, Xianghao; Ng, Derrick Wing Kwan; Schmeink, Anke; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we investigate the robust resource allocation design for secure communication in an integrated sensing and communication (ISAC) system. A multi-antenna dual-functional radar-communication (DFRC) base station (BS) serves multiple single-antenna legitimate users and senses for targets simultaneously, where already identified targets are treated as potential single-antenna eavesdroppers. The DFRC BS scans a sector with a sequence of dedicated beams, and the ISAC system takes a snapshot of the environment during the transmission of each beam. Based on the sensing information, the DFRC BS can acquire the channel state information (CSI) of the potential eavesdroppers. Different from existing works that focused on the resource allocation design for a single snapshot, in this paper, we propose a novel optimization framework that jointly optimizes the communication and sensing resources over a sequence of snapshots with adjustable durations. Besides, artificial noise (AN) is exploited by the BS for joint sensing and physical layer security provisioning. To this end, we jointly optimize the duration of each snapshot, the beamforming vector, and the covariance matrix of the AN for maximization of the system sum secrecy rate over a sequence of snapshots while guaranteeing a minimum required average achievable rate and a maximum information leakage constraint for each legitimate user. The resource allocation algorithm design is formulated as a non-convex optimization problem, where we account for the imperfect CSI of both the legitimate users and the potential eavesdroppers. To make the problem tractable, we derive a bound for the uncertainty region of the potential eavesdroppers’ small-scale fading based on a safe approximation, which facilitates the development of a block coordinate descent-based iterative algorithm for obtaining an efficient suboptimal solution. Simulation results illustrate that the proposed scheme can significantly enhance the physical layer security of ISAC systems compared to three baseline schemes. Moreover, compared to the conventional multi-stage approach for ISAC system design, the proposed approach based on variable-length snapshots not only facilitates a highly-directional offline sensing beam design but also allows us to flexibly prioritize communication or sensing depending on the application scenario.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Array signal processing; beamforming design; imperfect channel state information; Integrated sensing and communication; Optimization; Radar; Resource management; secure communication; Sensors; Uncertainty; Wireless communication

Robust and Secure Sum-Rate Maximization for Multiuser MISO Downlink Systems with Self-sustainable IRS - Hua, Shaokang; Wei, Zhiqiang; Cai, Yuanxin; Liu, Chang; Ng, Derrick Wing Kwan; Yuan, Jinhong (IEEE Transactions on Communications, 2021)
This paper investigates robust and secure multiuser multiple-input single-output (MISO) downlink communications assisted by a self-sustainable intelligent reflection surface (IRS), which can simultaneously reflect and harvest energy from the received signals. We study the joint design of beamformers at an access point (AP) and the phase shifts as well as the energy harvesting schedule at the IRS for maximizing the system sum-rate. The design is formulated as a non-convex optimization problem taking into account the wireless energy harvesting capability of IRS elements, secure communications, and the robustness against the impact of channel state information (CSI) imperfection. Subsequently, we propose a computationally-efficient iterative algorithm to obtain a suboptimal solution to the design problem. In each iteration, S-procedure and the successive convex approximation are adopted to handle the intermediate optimization problem. Our simulation results unveil that: 1) there is a non-trivial trade-off between the system sum-rate and the self-sustainability of the IRS; 2) the performance gain achieved by the proposed scheme is saturated with a large number of energy harvesting IRS elements; 3) an IRS equipped with small bit-resolution discrete phase shifters is sufficient to achieve a considerable system sum-rate of the ideal case with continuous phase shifts.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Array signal processing; Communication system security; Energy harvesting; Optimization; Phase shifters; Resource management; Wireless networks

Robust and Secure Wireless Communications via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Sun, Ying; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2020)
In this paper, intelligent reflecting surfaces (IRSs) are employed to enhance the physical layer security in a challenging radio environment. In particular, a multi-antenna access point (AP) has to serve multiple single-antenna legitimate users, which do not have line-of-sight communication links, in the presence of multiple multi-antenna potential eavesdroppers whose channel state information (CSI) is not perfectly known. Artificial noise (AN) is transmitted from the AP to deliberately impair the eavesdropping channels for security provisioning. We investigate the joint design of the beamformers and AN covariance matrix at the AP and the phase shifters at the IRSs for maximization of the system sum-rate while limiting the maximum information leakage to the potential eavesdroppers. To this end, we formulate a robust non-convex optimization problem taking into account the impact of the imperfect CSI of the eavesdropping channels. To address the non-convexity of the optimization problem, an efficient algorithm is developed by capitalizing on alternating optimization, a penalty-based approach, successive convex approximation, and semidefinite relaxation. Simulation results show that IRSs can significantly improve the system secrecy performance compared to conventional architectures without IRS. Furthermore, our results unveil that, for physical layer security, uniformly distributing the reflecting elements among multiple IRSs is preferable over deploying them at a single IRS.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Alternating optimization; imperfect channel state information; intelligent reflecting surface; physical layer security

Robust Beamforming Design in C-RAN With Sigmoidal Utility and Capacity-Limited Backhaul - Wang, Zehua; Wing Kwan Ng, Derrick; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
In this paper, we study the robust beamforming design in cloud radio access networks, where remote radio heads (RRHs) are connected to a cloud server that performs signal processing and resource allocation in a centralized manner. Different from traditional approaches adopting a concave increasing function to model the utility of a user, we model the utility by a sigmoidal function of the signal-to-interference-plus-noise ratio (SINR) to capture the diminishing utility returns for very small and very large SINRs in real-time applications (e.g., video streaming). Our objective is to maximize the aggregate utility of the users while considering the imperfection of channel state information (CSI), limited backhaul capacity, and minimum quality of service requirements. Because of the sigmoidal utility function and some of the constraints, the formulated problem is non-convex. To efficiently solve the problem, we introduce a maximum interference constraint, transform the CSI uncertainty constraints into linear matrix inequalities, employ convex relaxation to handle the backhaul capacity constraints, and exploit the sum-of-ratios form of the objective function. This leads to an efficient resource allocation algorithm, which outperforms several baseline schemes, and closely approaches a performance upper bound for large CSI uncertainty or large number of RRHs.<br
Keywords: Array signal processing; Interference; Signal to noise ratio; Servers; Downlink; Data communication; Mobile communication

Robust Beamforming for Secure Communication in Systems With Wireless Information and Power Transfer - Wing Kwan Ng, Derrick; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
This paper considers a multiuser multiple-input single-output (MISO) downlink system with simultaneous wireless information and power transfer. In particular, we focus on secure communication in the presence of passive eavesdroppers and potential eavesdroppers (idle legitimate receivers). We study the design of a resource allocation algorithm minimizing the total transmit power for the case when the legitimate receivers are able to harvest energy from radio frequency signals. Our design advocates the dual use of both artificial noise and energy signals in providing secure communication and facilitating efficient wireless energy transfer. The algorithm design is formulated as a non-convex optimization problem. The problem formulation takes into account artificial noise and energy signal generation for protecting the transmitted information against both considered types of eavesdroppers when imperfect channel state information (CSI) of the potential eavesdroppers and no CSI of the passive eavesdroppers are available at the transmitter. Besides, the problem formulation also takes into account different quality of service (QoS) requirements: a minimum required signal-to-interference-plus-noise ratio (SINR) at the desired receiver; maximum tolerable SINRs at the potential eavesdroppers; a minimum required outage probability at the passive eavesdroppers; and minimum required heterogeneous amounts of power transferred to the idle legitimate receivers. In light of the intractability of the problem, we reformulate the considered problem by replacing a non-convex probabilistic constraint with a convex deterministic constraint. Then, a semi-definite programming (SDP) relaxation approach is adopted to obtain the optimal solution for the reformulated problem. Furthermore, we propose a suboptimal resource allocation scheme with low computational complexity for providing communication secrecy and facilitating efficient energy transfer. Simulation results demonstrate the close-to-optimal performance of the proposed schemes and significant transmit power savings by optimization of the artificial noise and energy signal generation.<br
Keywords: Receivers; Transmitters; Noise; Energy harvesting; Wireless communication; Resource management; Algorithm design and analysis

Robust Beamforming for SWIPT Systems with Non-linear Energy Harvesting Model - Boshkovska, Elena; Kölpin, Alexander; Kwan Ng, Derrick Wing; Zlatanov, Nikola; Schober, Robert (IEEE 17th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2016)
This paper investigates resource allocation for simultaneous wireless information and power transfer (SWIPT) downlink systems based on a non-linear energy harvesting model. The resource allocation algorithm design is formulated as a non-convex optimization problem for the maximization of the total harvested power. The proposed problem formulation not only takes into account imperfect channel state information (CSI) but also guarantees the quality-of-service (QoS) of information transfer. A novel iterative algorithm is proposed to obtain the globally optimal solution of the considered non-convex optimization problem. In each iteration, a rank-constrained semidefinite program (SDP) is solved optimally by SDP relaxation. Simulation results demonstrate the significant gains in harvested power and the robustness against CSI imperfection for the proposed optimal resource allocation, compared to a baseline scheme designed for perfect CSI and the conventional linear energy harvesting model.
elib2cris::1512001600,boshkovska2016
Keywords: Energy Harvesting; Diode Detector

Robust cooperative beamforming for SC-FDMA based multi-relay networks - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (2014 IEEE International Conference on Communications (ICC), 2014)
In this work, we propose a robust cooperative relay beamforming (rBF) design for single-carrier frequency-division multiple access (SC-FDMA) based multiuser multi-relay systems with imperfect channel state information. We maximize a lower bound on the achievable bit rate (ABR) of the network, subject to an aggregate relay transmit power constraint. Employing the primal decomposition technique, we decompose the problem into two subproblems: the rBF coefficient optimization and the relay power allocation. For a given power allocation across the frequency tones, a closed-form solution for the rBF matrices is obtained first. Subsequently, the convexity of the remaining power allocation problem is then proved, and efficient convex optimization methods are employed to find the global optimum. Simulation results validate the excellent performance of the proposed rBF schemes and show their superiority compared to conventional non-robust designs.<br
Keywords: Relays; Channel estimation; Optimization; Vectors; Resource management; Noise; Matrix decomposition

Robust cyclic space-frequency filtering for BICM-OFDM with outdated CSIT - Chen, Harry Z.B.; Schober, Robert; Gerstacker, Wolfgang (IEEE International Conference on Communications, 2009)
In this paper, we introduce robust cyclic space-frequency (CSF) filtering for systems combining bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). The proposed robust CSF filtering scheme exploits outdated channel state information at the transmitter (CSIT) and takes into account the reliability of the CSIT via a Bayesian model. Based on an upper bound on the worst-case pairwise error probability we formulate the optimization problem for the robust CSF filters which can be solved exactly for certain special cases. For the general case, we obtain an approximate solution by solving a related problem with additional constraints. This approximate solution can be further improved with a gradient algorithm for the original problem. Simulation results confirm the excellent performance of BICM-OFDM with robust CSF filtering. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Robust Energy-Efficient Transmission for Wireless-Powered D2D Communication Networks - Zhang, Jing; Zhang, Yanxia; Xiang, Lin; Sun, Yan; Ng, Derrick Wing Kwan; Jo, Minho (IEEE Transactions on Vehicular Technology, 2021)
This paper considers optimal joint time, frequency, and power allocation for energy-efficient device-to-device (D2D) communications in an overlay cellular network, where multiple D2D transmitters communicate with their corresponding D2D receivers while utilizing the energy harvested from a cellular base station (BS). Due to channel estimation error and feedback delays, the channel state information (CSI) available at the transmitters is usually imperfect, which can significantly deteriorate the energy efficiency (EE) of the considered system. To mitigate the impact of imperfect CSI, we formulate a non-convex robust optimization problem for the maximization of the EE (in bits/Joule) of the system while ensuring quality of service (QoS) requirements on the minimum data rata and the minimum amount of harvested energy for cellular and D2D users, respectively. We reveal that the optimal energy-efficient D2D transmission should exhaust all the harvested energy of each D2D transmitter. Exploiting this fact, we propose an efficient iterative algorithm for obtaining the optimal solution. To strike a balance between performance and computational complexity, we further propose a low-complexity suboptimal algorithm. Simulation results show that compared with several baseline schemes, both the proposed optimal and suboptimal algorithms can significantly improve the EE of wireless-powered D2D communications under imperfect CSI. Moreover, the proposed suboptimal algorithm is close-to-optimal when the number of cellular users are small or the channel estimation error is large.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Convex optimization; D2D communication; energy efficiency; wireless power transfer

Robust Frequency Regulation Capacity Scheduling Algorithm for Electric Vehicles - Yao, Enxin; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2016)
Electric vehicles (EVs) have the potential to provide frequency regulation service to an independent system operator (ISO) by changing their real-time charging or discharging power according to an automatic generation control (AGC) signal. Recently, the Federal Energy Regulatory Commission has issued Order 755 to ISOs to introduce a performance-based compensation scheme in the frequency regulation market. The goal is to provide economic incentives for fast ramping resources such as EVs to participate in the market. In this paper, we model the EV frequency regulation service under the performance-based compensation scheme. Thereby, a robust optimization framework is adopted for the formulation of a frequency regulation capacity scheduling problem. Our problem formulation takes into account the performance-based compensation scheme, the random AGC signal, and the dynamic arrival and departure times of the EVs. We propose an efficient algorithm to solve the formulated problem. Simulation results show that the proposed algorithm improves the revenue under the performance-based compensation scheme compared with a benchmark algorithm.<br
Keywords: Frequency control; Automatic generation control; ISO; Robustness; Real-time systems; Optimization; Heuristic algorithms

Robust MBSFN transmission using the Golden code - Konrad, Markus; Gerstacker, Wolfgang; Koch, Wolfgang (2009 International Conference on Ultra Modern Telecommunications & Workshops, 2009)
Multimedia broadcast over a single frequency network (MBSFN) has attracted a lot of interest recently. This paper is on Golden coded spatial multiplexing MBSFN transmission using a soft-output sphere decoder (SOSD) and the impact of such a transceiver on the block error rate (BLER) system performance. In total, we consider three transceiver types and evaluate their performance in cellular orthogonal frequency division multiplexing (OFDM) based MBSFN scenarios with urban characteristic taking into account single-cell broadcast and multi-cell broadcast with and without guard interval (GI) excess. In addition to the Golden coded system, we consider horizontal BLAST (H-BLAST) with decoded-feedback minimum mean-squared error (MMSE) successive interference cancelation (SIC) detector as a low complexity reference system, and a pure spatial multiplexing system with SOSD. The Golden coded transmission shows an increased overall robustness in an MBSFN network in comparison to the H-BLAST MMSE SIC reference system and in comparison to spatial multiplexing with SOSD, particularly in scenarios with high spectral efficiencies, i.e., high rates of the channel code. We demonstrate that this also applies for the critical case of an exceeded G

Robust MMSE design for full-duplex decode-and-forward SC-FDE relay Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (2015 IEEE International Conference on Communications (ICC), 2015)
In this paper, we consider the robust transceiver design for a two-hop full-duplex decode-and-forward relay system employing single-carrier transmission with frequency-domain equalization (SC-FDE). The design problem for the transmit precoding and receive equalization is formulated as an optimization problem with the objective to minimize the sum mean-squared error (MSE) of the two hops subject to separate node transmit power constraints. We show that the equalization filters can be optimized individually at the receiving nodes and take the form of robust Wiener filters. However, due to the loopback interference, the transmissions in the two hops are coupled and the transmit precoding problem boils down to a non-convex power allocation problem in the frequency domain. An alternating optimization approach is proposed to obtain the power allocation where convex programming problems and difference of convex programming problems are solved in an alternating manner. Numerical results are provided to validate the MSE and the achievable rate of the proposed robust schemes, showing that significant performance gains can be achieved compared to conventional half-duplex systems and non-robust full-duplex designs.<br
Keywords: Relays; Channel estimation; Optimization; Resource Management; Robustness; Interference; Linear programming

Robust MSE-Balancing Hierarchical Linear/Tomlinson-Harashima Precoding for Downlink Massive MU-MIMO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Weigel, Robert; Vossiek, Martin; Schober, Robert (IEEE Transactions on Wireless Communications, 2018)
In this paper, we propose a robust minimum maximum mean square error Tomlinson-Harashima precoding (Min-Max-MSE THP) scheme and a low-complexity robust Min-Max-MSE hierarchical linear/THP (HL-THP) scheme for downlink massive multiuser multiple-input-multiple-output (MU-MIMO) systems with imperfect channel state information (CSI) at the transmitter. The proposed robust Min-Max-MSE HL-THP scheme comprises an inner linear beamformer (BF), which is designed based on second-order CSI statistics, and outer THP modules, which exploit the instantaneous overall CSI of the cascade of the actual channel and the inner BF. Thereby, the user terminals are divided into groups, where for each group a THP module successively mitigates the intra-group interference, whereas the inter-group interference is canceled by the inner BF. To ensure fairness, we adopt the maximization of the asymptotic signal-to-leakage-plus-noise ratio in the large system limit and the Min-Max-MSE as an optimization criterion for designing the inner BF and the per-group THP modules, respectively. Our analytical and simulation results show that the proposed robust Min-Max-MSE HL-THP scheme achieves a substantially improved performance in terms of the Max-MSE, maximum bit error rate, and minimum rate compared to linear regularized zero-forcing precoding. Moreover, the performance loss of the proposed robust Min-Max-MSE HL-THP scheme compared to the robust Min-Max-MSE THP scheme is small. In addition, our complexity analysis reveals that the proposed robust Min-Max-MSE HL-THP scheme has a much lower computational complexity than the Min-Max-MSE THP scheme. Hence, the robust Min-Max-MSE HL-THP scheme provides a favorable tradeoff between complexity and performanc
lhft_intern.bib::Zarei2018a
Keywords: Precoding; Robustness; Interference; Computational complexity; Optimization; Wireless communication

Robust pilot decontamination based on koint angle and power domain discrimination - Yin, Haifan; Cottatellucci, Laura; Gesbert, David; Müller, Ralf; He, Gaoning (IEEE Transactions on Signal Processing, 2016)

Robust Resource Allocation for Full-Duplex Cognitive Radio Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zlatanov, Nikola; Schober, Robert (2016)
In this paper, we investigate resource allocation algorithm design for full-duplex (FD) cognitive radio systems. The secondary network employs a FD base station for serving multiple half-duplex downlink and uplink users simultaneously. We study the resource allocation design for minimizing the maximum interference leakage to primary users while providing quality of service for secondary users. The imperfectness of the channel state information of the primary users is taken into account for robust resource allocation algorithm design. The algorithm design is formulated as a non-convex optimization problem and solved optimally by applying semidefinite programming (SDP) relaxation. Simulation results not only show the significant reduction in interference leakage compared to baseline schemes, but also confirm the robustness of the proposed algorithm.

Robust Resource Allocation for MIMO Wireless Powered Communication Networks Based on a Non-Linear EH Model - Boshkovska, Elena; Wing Kwan Ng, Derrick; Zlatanov, Nikola; Kölpin, Alexander; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we consider a multiple-input multiple-output wireless powered communication network, where multiple users harvest energy from a dedicated power station in order to be able to transmit their information signals to an information receiving station. Employing a practical non-linear energy harvesting (EH) model, we propose a joint time allocation and power control scheme, which takes into account the uncertainty regarding the channel state information (CSI) and provides robustness against imperfect CSI knowledge. In particular, we formulate two non-convex optimization problems for different objectives, namely system sum throughput maximization and the maximization of the minimum individual throughput across all wireless powered users. To overcome the non-convexity, we apply several transformations along with a one-dimensional search to obtain an efficient resource allocation algorithm. Numerical results reveal that a significant performance gain can be achieved when the resource allocation is designed based on the adopted non-linear EH model instead of the conventional linear EH model. Besides, unlike a non-robust baseline scheme designed for perfect CSI, the proposed resource allocation schemes are shown to be robust against imperfect CSI knowledge.<br
Keywords: Resource management; Wireless communication; Algorithm design and analysis; Robustness; Power generation; Throughput; Radio frequency

Robust Resource Allocation for UAV Systems with UAV Jittering and User Location Uncertainty - Xu, Dongfang; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2018 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2018)
CRIS-Team WoS Importer:2019-04-16

Robust Transceiver Design for Broadband Multiuser Multi-Relay Networks - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2015)
In this paper, we study the robust design of the relay beamforming (rBF) and destination equalization (dEQ) filters for broadband multiuser multi-relay networks employing single-carrier frequency-division multiple access (SC-FDMA) and orthogonal frequency-division multiple access (OFDMA). Thereby, we consider the realistic case where only imperfect channel state information is available for rBF and dEQ filter optimization. Our goal is to maximize a lower bound for the weighted achievable bit rate (ABR) of the network, subject to either individual relay power constraints (Ind-PCs) or an aggregate relay power constraint (Agg-PC). We first derive the optimal dEQ filters and the phases of the optimal rBF filter coefficients, which are independent of the power constraints. For the Agg-PC, the amplitude optimization of the rBF filter coefficients is decomposed into two subproblems, which correspond to the optimization of the power allocation across the relays and the power allocation across the users and subcarriers, respectively. We obtain a closed-form structural solution for the first subproblem by fixing the powers across users and subcarriers, and the global optimal solution for the second subproblem. For the Ind-PCs, the corresponding optimization problem is formulated as a reverse-convex problem with convex constraints. Subsequently, the constrained convex concave procedure is applied to approximate the original non-convex problem with a sequence of convex problems, which can be efficiently solved using convex optimization techniques. Simulation results validate the excellent performance of the proposed robust rBF and dEQ filter designs and show their superiority compared to conventional non-robust and naive relaying schemes.<br
Keywords: Relays; Optimization; OFDM; Channel estimation; Robustness; Broadband communication; Signal to noise ratio

Robust Transceiver Design for SC-FDE Multi-hop Full-Duplex Decode-and-Forward Relaying Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay Kishore (IEEE Transactions on Wireless Communications, 2015)
In this paper, we consider the robust transceiver design for a multi-hop full-duplex decode-and-forward (DF) relay system employing single-carrier transmission with frequency-domain equalization (SC-FDE). We take into account the effect of imperfect channel state information (CSI) where the CSI errors are modeled as Gaussian random variables with known statistics. The design of the precoding at the transmitter and the equalization at the receiver is formulated as an optimization problem with the objective to minimize two relevant performance metrics, namely, the sum mean-square error (MSE) and the maximum MSE across the different hops, subject to separate transmit power constraints for the nodes. We show that the equalization filters can be optimized individually at the receiving nodes and take the form of robust Wiener filters. However, due to the loopback/backward interference, the transmit signals in the different hops are coupled and the transmit precoding problem leads to a nonconvex power allocation problem in the frequency domain. To find the optimal power allocation, we first employ a sequential geometric programming (sGP) approach, which uses the condensation technique to transform the objective function into a posynomial and then solves a sequence of standard GP problems. The sGP approach requires global channel knowledge at a central node and the involved subproblems admit only numerical solutions. To gain further insight into the structure of the problem, we also consider an alternating optimization (AO) approach for power allocation where convex programming problems and difference of convex programming problems are solved in an alternating manner. The resulting AO algorithm admits closed-form solutions in each iteration step and requires less signaling overhead compared to the centralized sGP scheme. Numerical results for the MSEs and achievable rates of the proposed robust schemes are provided, showing that the proposed sGP and AO algorithms yield significant performance gains compared to conventional half-duplex relay systems and nonrobust full-duplex designs.<br
Keywords: Relays; Resource Management; Channel estimation; Optimization; Robustness; Interference; Transceivers

Robust Transmission Design for RIS-assisted Secure Multiuser Communication Systems in the Presence of Hardware Impairments - Peng, Zhangjie; Weng, Ruisong; Pan, Cunhua; Zhou, Gui; Di Renzo, Marco; Lee Swindlehurst, A. (IEEE Transactions on Wireless Communications, 2023)
This paper investigates reconfigurable intelligent surface (RIS)-assisted secure multiuser communication systems in the presence of hardware impairments (HIs) at the RIS and the transceivers. We jointly optimize the beamforming vectors at the base station (BS) and the phase shifts of the reflecting elements at the RIS so as to maximize the weighted minimum approximate ergodic secrecy rate (WMAESR), subject to the transmission power constraints at the BS and unit-modulus constraints at the RIS. To solve the formulated optimization problem, we first decouple it into two tractable subproblems and then use the block coordinate descent (BCD) method to alternately optimize the subproblems. Two different methods are proposed to solve the two obtained subproblems. The first method transforms each subproblem into a second order cone programming (SOCP) problem by invoking the penalty convexconcave procedure (CCP) method and the closed-form fractional programming (FP) criterion, and then directly solves them by using CVX. The second method leverages the minorization-maximization (MM) algorithm. Specifically, we first derive a concave approximation function, which is a lower bound of the original objective function, and then the two subproblems are transformed into two simple surrogate problems that admit closed-form solutions. Simulation results verify the performance gains of the proposed robust transmission methods over existing non-robust designs. In addition, the MM algorithm is shown to have much lower complexity than the SOCP-based algorithm.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Approximation algorithms; Distortion; Hardware; hardware impairments (HIs); Intelligent reflecting surface (IRS); MISO communication; physical layer security (PLS); reconfigurable intelligent surface (RIS); Security; Transceivers; Wireless communication

Robust transmit processing for frequency-selective fading channels with imperfect channel feedback - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (IEEE Transactions on Wireless Communications, 2008)
Reliable channel state information at the transmitter (CSIT) can improve the throughput of wireless networks significantly. In a realistic scenario, there is a mismatch between the CSIT and the true channel. The CSIT may be outdated due to channel variations or could be erroneous due to quantization effects. In this paper, robust transmit beamforming (rBF) and the combination of time-reversal space-time block codes (TR-STBCs) with rBF, both optimized for transmission over frequency-selective fading channels with decision-feedback equalization (DFE), are considered. The reliability of the CSIT is taken into account for the design of channel state dependent transmit signal processing algorithms to achieve robustness against imperfect CSIT. Noisy (quantized) CSIT, outdated CSIT, and the combination of both cases are considered. We show that the performance of the rBF scheme is upper and lower bounded by that of transmit BF with perfect CSIT and optimized delay diversity (ODD) without instantaneous CSIT, respectively. The combination of a TR-STBC with rBF yields significant BF gains in addition to the diversity gains of the TR-STBC for reliable CSIT, whereas for unreliable CSIT, the performance is identical to that of the TR-STB

RSB decoupling property of MAP estimators - Bereyhi, Ali; Müller, Ralf; Schulz-Baldes, Hermann (2016 IEEE Information Theory Workshop (ITW), 2016)
The large-system decoupling property of a MAP estimator is studied when it estimates the i.i.d. vector x from the observation y=Ax+z with A being chosen from a wide range of matrix ensembles, and the noise vector z being i.i.d. and Gaussian. Using the replica method, we show that the marginal joint distribution of any two corresponding input and output symbols converges to a deterministic distribution which describes the input-output distribution of a single user system followed by a MAP estimator. Under the bRSB assumption, the single user system is a scalar channel with additive noise where the noise term is given by the sum of an independent Gaussian random variable and b correlated interference terms. As the bRSB assumption reduces to RS, the interference terms vanish which results in the formerly studied RS decoupling principle.

Safeguarding 5G-and-Beyond Networks with Physical Layer Security - Wu, Yongpeng; Duong, Trung Q.; Swindlehurst, A. Lee (IEEE Wireless Communications, 2019)
CRIS-Team WoS Importer:2019-11-22

SAFEGUARDING UAV NETWORKS THROUGH INTEGRATED SENSING, JAMMING, AND COMMUNICATIONS - Wei, Zhiqiang; Liu, Fan; Ng, Derrick Wing Kwan; Schober, Robert (2022 IEEE INTERNATIONAL CONFERENCE ON ACOUSTICS, SPEECH AND SIGNAL PROCESSING (ICASSP), 2022)
CRIS-Team WoS Importer:2023-01-13

Saturating Receiver and Receptor Competition in Synaptic DMC: Deterministic and Statistical Signal Models - Lotter, Sebastian; Schäfer, Maximilian; Zeitler, Johannes; Schober, Robert (IEEE Transactions on Nanobioscience, 2021)
Synaptic communication is based on a biological Molecular Communication (MC) system which may serve as a blueprint for the design of synthetic MC systems. However, the physical modeling of synaptic MC is complicated by the possible saturation of the molecular receiver caused by the competition of neurotransmitters (NTs) for postsynaptic receptors. Receiver saturation renders the system behavior nonlinear in the number of released NTs and is commonly neglected in existing analytical models. Furthermore, due to the ligands’ competition for receptors (and vice versa), the individual binding events at the molecular receiver are in general not statistically independent and the commonly used binomial model for the statistics of the received signal does not apply. Hence, in this work, we propose a novel deterministic model for receptor saturation in terms of a state-space description based on an eigenfunction expansion of Fick’s diffusion equation. The presented solution is numerically stable and computationally efficient. Employing the proposed deterministic model, we show that saturation at the molecular receiver effectively reduces the peak-value of the expected received signal and accelerates the clearance of NTs as compared to the case when receptor occupancy is neglected. We further derive a statistical model for the received signal in terms of the hypergeometric distribution which accounts for the competition of NTs for receptors and the competition of receptors for NTs. The proposed statistical model reveals how the signal statistics are shaped by the number of released NTs, the number of receptors, and the binding kinetics of the receptors, respectively, in the presence of competition. In particular, we show that the impact of these parameters on the signal variance is qualitatively different depending on the relative numbers of NTs and receptors. Finally, the accuracy of the proposed deterministic and statistical models is verified by particle-based computer simulations.
Keywords: Receivers; Mathematical model; Analytical models; Computational modeling; Numerical models; Monte Carlo methods; Degradation

Scalable and Energy-Efficient Millimeter Massive MIMO Architectures: Reflect-Array and Transmit-Array Antennas - Jamali, Vahid; Tulino, Antonia M.; Fischer, Georg; Muller, Ralf; Schober, Robert (ICC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
Hybrid analog-digital architectures are considered as promising candidates for implementing millimeter wave (mmWave) massive multiple-input multiple-output (MIMO) systems since they enable a considerable reduction of the required number of costly radio frequency (RF) chains by moving some of the signal processing operations into the analog domain. However, the analog feed network, comprising RF dividers, combiners, phase shifters, and line connections, of hybrid MIMO architectures is not scalable due to its prohibitively high power consumption for large numbers of transmit antennas. Motivated by this limitation, in this paper, we study novel massive MIMO architectures, namely reflect-array (RA) and transmit-array (TA) antennas. We show that the precoders for RA and TA antennas have to meet different constraints compared to those for conventional MIMO architectures. Taking these constraints into account and exploiting the sparsity of mmWave channels, we design an efficient precoder for RA and TA antennas based on the orthogonal matching pursuit algorithm. Furthermore, in order to fairly compare the performance of RA and TA antennas with conventional fully-digital and hybrid MIMO architectures, we develop a unified power consumption model. Our simulation results show that unlike conventional MIMO architectures, RA and TA antennas are highly energy efficient and fully scalable in terms of the number of transmit antennas.<br
Keywords: Vehicular ad hoc networks; Taxonomy; Vehicle-to-infrastructure; Databases; Real-time systems

SCW codes for optimal CSI-free detection in diffusive molecular communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Farsad, Nariman; Schober, Robert (2017 IEEE International Symposium on Information Theory (ISIT), 2017)
Instantaneous or statistical channel state information (CSI) is needed for most detection schemes developed in the molecular communication (MC) literature. Since the MC channel changes, e.g., due to variations in the velocity of flow, the temperature, or the distance between transmitter and receiver, CSI acquisition has to be conducted repeatedly to keep track of CSI variations. Frequent CSI acquisition may entail a large overhead whereas infrequent CSI acquisition may result in a low CSI estimation quality. To cope with these issues, we design codes which facilitate maximum likelihood sequence detection at the receiver without instantaneous or statistical CSI. In particular, assuming concentration shift keying modulation, we show that a class of codes, referred to as strongly constant-weight (SCW) codes, enables optimal CSI-free sequence detection at the cost of decreasing the data rate. For the proposed SCW codes, we analyze the code rate and the error rate. Simulation results verify our analytical derivations and reveal that the proposed CSI-free detector for SCW codes outperforms the baseline coherent and non-coherent detectors for uncoded transmission.<br
Keywords: Receivers; Transmitters; Modulation; Detectors; Complexity theory; Information theory; Molecular communication

Secrecy analysis of multi-cell massive MIMO systems with RCI precoding and artificial noise transmission - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (2014 6th International Symposium on Communications, Control and Signal Processing (ISCCSP), 2014)
In this paper, we study linear precoding for a secure multi-cell massive multiple-input multiple-output (MIMO) downlink system employing artificial noise generation. We consider the large system limit where the number of base station antennas, the number of mobile users, and the number of eavesdropper antennas are all growing without bound but with fixed ratio. The proposed precoder is based on regularized channel inversion (RCI) with regularization parameter κ. The optimal κ is derived such that the ergodic secrecy rate is maximized in the case of imperfect channel state information at the transmitter due to pilot contamination. Our analytical results show that the proposed RCI precoder outperforms other linear precoders.<br
Keywords: Antennas

Secrecy outage of TAS/GSC in Nakagami-m fading channels - Wang, Lifeng; Elkashlan, Maged; Huang, Jing; Schober, Robert; Mallik, Ranjan K. (2014 IEEE International Conference on Communications (ICC), 2014)
This paper considers transmit antenna selection (TAS) and receive generalized selection combining (GSC) for secure communication in MIMO wiretap channel, where confidential messages transmitted from an N A -antenna transmitter to an N B -antenna legitimate receiver are overheard by an N E -antenna eavesdropper. We assume that the main channel and the eavesdropper's channel undergo Nakagami-m fading with fading parameters m B and m E , respectively. In an effort to assess the secrecy performance, we present a closed-form expression for the secrecy outage probability. We then derive closed-form expressions for the secrecy outage probability at high signal-to-noise ratio (SNR) for two realistic scenarios: 1) the legitimate receiver is located close to the transmitter, and 2) the legitimate receiver and the eavesdropper are located close to the transmitter. In the first scenario, we confirm that the secrecy diversity order is m B N B N A . In the second scenario, we confirm that the secrecy diversity order collapses to zero. While this may appear discouraging at a first glance, we show that low secrecy outage probability can still be achieved.<br
Keywords: Receiving antennas; Transmitting antennas; Niobium; Signal to noise ratio; Fading

Secure Active and Passive Beamforming in IRS-Aided MIMO Systems - Asaad, Saba; Wu, Yifei; Bereyhi, Ali; Müller, Ralf; Schaefer, Rafael F.; Vincent Poor, H. (IEEE Transactions on Information Forensics and Security, 2022)
In intelligent reflecting surface (IRS)-aided multiple-input multiple-output (MIMO) systems, the IRS can be utilized to suppress the information leakage towards malicious terminals. This can lead to significant secrecy gains. This work exploits these gains via a tractable joint design of downlink beamformers and IRS phase-shifts. In this respect, we consider a generic IRS-aided MIMO wiretap setting and invoke fractional programming and alternating optimization to iteratively find the beamformers and phase-shifts that maximize the achievable weighted secrecy sum-rate. Our design concludes two low-complexity algorithms. Performance of the proposed algorithms are numerically evaluated and compared to the benchmark. The results reveal that integrating IRSs into MIMO systems not only boosts the secrecy performance, but also improves the robustness against passive eavesdropping.
CRIS-Team Scopus Importer:2022-03-25
Keywords: alternating optimization; Array signal processing; Downlink; Eavesdropping; fractional programming; intelligent reflecting surfaces; majorization-maximization method; Massive MIMO; MISO communication; Optimization; Physical layer security; Programming

Secure and Green SWIPT in Distributed Antenna Networks With Limited Backhaul Capacity - Wing Kwan Ng, Derrick; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
This paper studies the resource allocation algorithm design for secure information and renewable green energy transfer to mobile receivers in distributed antenna communication systems. In particular, distributed remote radio heads (RRHs/antennas) are connected to a central processor (CP) via capacity-limited backhaul links to facilitate joint transmission. The RRHs and the CP are equipped with renewable energy harvesters and share their energies via a lossy micropower grid for improving the efficiency in conveying information and green energy to mobile receivers via radio frequency signals. The considered resource allocation algorithm design is formulated as a mixed nonconvex and combinatorial optimization problem taking into account the limited backhaul capacity and the quality-of-service requirements for simultaneous wireless information and power transfer (SWIPT). We aim at minimizing the total network transmit power when only imperfect channel state information of the wireless energy harvesting receivers, which have to be powered by the wireless network, is available at the CP. In light of the intractability of the problem, we reformulate it as an optimization problem with binary selection, which facilitates the design of an iterative resource allocation algorithm to solve the problem optimally using the generalized Bender's decomposition (GBD). Furthermore, a suboptimal algorithm is proposed to strike a balance between computational complexity and system performance. Simulation results illustrate that the proposed GBD-based algorithm obtains the global optimal solution and the suboptimal algorithm achieves a close-to-optimal performance. In addition, the distributed antenna network for SWIPT with renewable energy sharing is shown to require a lower transmit power compared with a traditional system with multiple colocated antennas.<br
Keywords: Receivers; Wireless communication; Antenna arrays; Noise; Resource management; Erbium; Communication system security

Secure Coding via Gaussian Random Fields - Bereyhi, Ali; Loureiro, Bruno; Krzakala, Florent; Müller, Ralf; Schulz-Baldes, Hermann (IEEE International Symposium on Information Theory - Proceedings, 2022)
Inverse probability problems whose generative models are given by strictly nonlinear Gaussian random fields show the all-or-nothing behavior: There exists a critical rate at which Bayesian inference exhibits a phase transition. Below this rate, the optimal Bayesian estimator recovers the data perfectly, and above it the recovered data becomes uncorrelated. This study uses the replica method from the theory of spin glasses to show that this critical rate is the channel capacity. This interesting finding has a particular application to the problem of secure transmission: A strictly nonlinear Gaussian random field along with random binning can be used to securely encode a confidential message in a wiretap channel. Our large-system characterization demonstrates that this secure coding scheme asymptotically achieves the secrecy capacity of the Gaussian wiretap channel.
CRIS-Team Scopus Importer:2022-09-02
Keywords: decoupling principle; information-theoretic secrecy; Nonlinear Gaussian random fields; replica method

Secure Downlink Transmission in Massive MIMO System with Zero-Forcing Precoding - Zhu, Jun; Bhargava, Vijay K.; Schober, Robert (European Wireless 2014; 20th European Wireless Conference, 2014)
We analyze the ergodic secrecy rate of multi-cell downlink systems assuming that the number of base station (BS) antennas per cell, the number of mobile users, and the number of eavesdropper antennas are all growing without bound. Our analysis includes the effect of uplink channel estimation, pilot contamination, and path-loss. The BS employs zero-forcing (ZF) precoding and artificial noise (AN) generation for secrecy enhancement. Our analytical results reveal that in a secure massive multiple-input multiple-output (MIMO) system employing AN, ZF precoding outperforms matched-filter (MF) precoding, unless the signal power is very small, inter-cell interference is severe, or the effect of pilot contamination is dominant.<br

Secure layered transmission in multicast systems with wireless information and power transfer - Wing Kwan Ng, Derrick; Schober, Robert; Alnuweiri, Hussein (2014 IEEE International Conference on Communications (ICC), 2014)
This paper considers downlink multicast transmit beamforming for secure layered transmission systems with wireless simultaneous information and power transfer. We study the power allocation algorithm design for minimizing the total transmit power in the presence of passive eavesdroppers and energy harvesting receivers. The algorithm design is formulated as a non-convex optimization problem. Our problem formulation promotes the dual use of energy signals in providing secure communication and facilitating efficient energy transfer. Besides, we take into account a minimum required power for energy harvesting at the idle receivers and heterogeneous quality of service (QoS) requirements for the multicast video receivers. In light of the intractability of the problem, we reformulate the considered problem by replacing a non-convex probabilistic constraint with a convex deterministic constraint which leads to a smaller feasible solution set. Then, a semidefinite programming relaxation (SDR) approach is adopted to obtain an upper bound solution for the reformulated problem. Subsequently, sufficient conditions for the global optimal solution of the reformulated problem are revealed. Furthermore, we propose two suboptimal power allocation schemes based on the upper bound solution. Simulation results demonstrate the excellent performance and significant transmit power savings achieved by the proposed schemes compared to isotropic energy signal generation.<br
Keywords: Receivers; Resource management; Transmitters; Energy harvesting; Wireless communication; Vectors; Interference

Secure Massive MIMO transmission in the presence of an active eavesdropper - Wu, Yongpeng; Schober, Robert; Wing Kwan Ng, Derrick; Xiao, Chengshan; Caire, Giuseppe (2015 IEEE International Conference on Communications (ICC), 2015)
In this paper, we investigate secure and reliable transmission strategies for multi-cell multi-user massive multipleinput multiple-output (MIMO) systems in the presence of an active eavesdropper. We consider a time-division duplex system where uplink training is required and an active eavesdropper can attack the training phase to cause pilot contamination at the transmitter. This forces the precoder used in the subsequent downlink transmission phase to implicitly beamform towards the eavesdropper, thus increasing its received signal power. We derive an asymptotic achievable secrecy rate for matched filter precoding and artificial noise (AN) generation at the transmitter when the number of transmit antennas goes to infinity. For the achievability scheme at hand, we obtain the optimal power allocation policy for the transmit signal and the AN in closed form. For the case of correlated fading channels, we show that the impact of the active eavesdropper can be completely removed if the transmit correlation matrices of the users and the eavesdropper are orthogonal. Inspired by this result, we propose a precoder null space design exploiting the low rank property of the transmit correlation matrices of massive MIMO channels, which can significantly degrade the eavesdropping capabilities of the active eavesdropper.<br
Keywords: MIMO; Correlation; Training; Transmitters; Null space; Fading; Uplink

Secure Regularized Zero Forcing for Multiuser MIMOME Channels - Asaad, Saba; Bereyhi, Ali; Müller, Rainer; Schaefer, Rafael F. (CONFERENCE RECORD OF THE 2019 FIFTY-THIRD ASILOMAR CONFERENCE ON SIGNALS, SYSTEMS & COMPUTERS, 2019)
CRIS-Team WoS Importer:2020-07-31

Secure SWIPT Networks Based on a Non-Linear Energy Harvesting Model - Boshkovska, Elena; Zlatanov, Nikola; Dai, Linglong; Wing Kwan Ng, Derrick; Schober, Robert (2017 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2017)
We optimize resource allocation to enable com- munication security in simultaneous wireless information and power transfer (SWIPT) for internet-of-things (IoT) networks. The resource allocation algorithm design is formulated as a non-convex optimization problem. We aim at maximizing the total harvested power at energy harvesting (EH) receivers via the joint optimization of transmit beamforming vectors and the covariance matrix of the artificial noise injected to facilitate secrecy provisioning. The proposed problem formulation takes into account the non-linearity of energy harvesting circuits and the quality of service requirements for secure communication. To obtain a globally optimal solution of the resource allocation problem, we first transform the resulting non-convex sum-of- ratios objective function into an equivalent objective function in parametric subtractive form, which facilitates the design of a novel iterative resource allocation algorithm. In each iteration, the semidefinite programming (SDP) relaxation approach is adopted to solve a rank-constrained optimization problem optimally. Nu- merical results reveal that the proposed algorithm can guarantee communication security and provide a significant performance gain in terms of the harvested energy compared to existing designs which are based on the traditional linear EH model.<br
Keywords: Erbium; Wireless communication; Resource management; Receivers; Radio frequency; Energy harvesting; Security

Secure Transmission in IRS-Assisted MIMO Systems with Active Eavesdroppers - Bereyhi, Ali; Asaad, Saba; Müller, Ralf; Schaefer, Rafael F.; Poor, H. Vincent (2020 54TH ASILOMAR CONFERENCE ON SIGNALS, SYSTEMS, AND COMPUTERS, 2020)
CRIS-Team WoS Importer:2021-09-03

Secure Transmission in Multicell Massive MIMO Systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2014)
In this paper, we consider physical layer security provisioning in multicell massive multiple-input-multiple-output (MIMO) systems. Specifically, we consider secure downlink transmission in a multicell massive MIMO system with matched-filter precoding and artificial noise (AN) generation at the base station (BS) in the presence of a passive multiantenna eavesdropper. We investigate the resulting achievable ergodic secrecy rate and the secrecy outage probability for the cases of perfect training and pilot contamination. Thereby, we consider two different AN shaping matrices, namely, the conventional AN shaping matrix, where the AN is transmitted in the null space of the matrix formed by all user channels, and a random AN shaping matrix, which avoids the complexity associated with finding the null space of a large matrix. Our analytical and numerical results reveal the following, in multicell massive MIMO systems employing matched-filter precoding: 1) AN generation is required to achieve a positive ergodic secrecy rate if the user and the eavesdropper experience the same path loss; 2) even with AN generation, secure transmission may not be possible if the number of eavesdropper antennas is too large and not enough power is allocated to channel estimation; 3) for a given fraction of power allocated to AN and a given number of users, in case of pilot contamination, the ergodic secrecy rate is not a monotonically increasing function of the number of BS antennas; and 4) random AN shaping matrices provide a favorable performance/complexity tradeoff and are an attractive alternative to conventional AN shaping matrices.<br
Keywords: MIMO; Channel estimation; Training; Vectors; Contamination; Transmitting antennas; Interference

Secure transmission via transmit antenna selection in MIMO wiretap channels - Yang, Nan; Yeoh, Phee Lep; Elkashlan, Maged; Schober, Robert; Collings, Iain B. (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
We propose and analyze transmit antenna selection (TAS) to enhance physical layer security in a wiretap channel with multiple antennas at the transmitter, the receiver, and the eavesdropper. We consider the practical scenario of passive eavesdropping, where the transmitter does not have any channel state information (CSI) of the eavesdropper's channel. In the main channel between the transmitter and the receiver, we select a single antenna at the transmitter that maximizes the instantaneous signal-to-noise ratio (SNR) at the receiver. At the receiver and the eavesdropper, we consider two combining techniques: 1) maximal-ratio combining (MRC) and 2) selection combining (SC). For non-identical Rayleigh fading between the main channel and the eavesdropper's channel, we first derive new closed-form expressions for the exact and asymptotic secrecy outage probabilities. The asymptotic results accurately reveal the secrecy diversity order and the secrecy array gain. Next, we derive new closed-form expressions for the probability of positive secrecy and characterize the ε-outage secrecy capacity. We show that, under TAS/MRC and TAS/SC protocols, the secrecy outage probability approaches zero and the ε-outage secrecy capacity increases with increasing number of transmitter antennas. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Secure Transmission With Antenna Selection in MIMO Nakagami- m Fading Channels - Wang, Lifeng; Elkashlan, Maged; Huang, Jing; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Wireless Communications, 2014)
This paper considers transmit antenna selection (TAS) and receive generalized selection combining (GSC) for secure communication in the multiple-input-multiple-output wiretap channel, where confidential messages transmitted from an NA-antenna transmitter to an NB-antenna legitimate receiver are overheard by an NE-antenna eavesdropper. We assume that the main channel and the eavesdropper's channel undergo Nakagami-m fading with fading parameters mB and mE, respectively. In order to assess the secrecy performance, we present a new unifying framework for the average secrecy rate and the secrecy outage probability. We first derive expressions for the probability density function and the cumulative distribution function of the signal-to-noise ratio with TAS/GSC, from which we derive exact expressions for the average secrecy rate and the secrecy outage probability. We then derive compact expressions for the asymptotic average secrecy rate and the asymptotic secrecy outage probability for two distinct scenarios: 1) the legitimate receiver is located close to the transmitter, and 2) the legitimate receiver and the eavesdropper are located close to the transmitter. For these scenarios, we present new closed-form expressions for several key performance indicators: 1) the capacity slope and the power offset of the asymptotic average secrecy rate, and 2) the secrecy diversity order and the secrecy array gain of the asymptotic secrecy outage probability. For the first scenario, we confirm that the capacity slope is one and the secrecy diversity order is mBNBNA. For the second scenario, we confirm that the capacity slope and the secrecy diversity order collapse to zero.<br
Keywords: Signal to noise ratio; Receiving antennas; Fading; Transmitting antennas; Niobium

Secure Transmission With Large Numbers of Antennas and Finite Alphabet Inputs - Wu, Yongpeng; Wang, Jun-Bo; Wang, Jue; Schober, Robert; Xiao, Chengshan (IEEE Transactions on Communications, 2017)
In this paper, we investigate secure transmission over the large-scale multiple-antenna wiretap channel with finite alphabet inputs. First, we investigate the case where instantaneous channel state information (CSI) of the eavesdropper is known at the transmitter. We show analytically that a generalized singular value decomposition (GSVD)-based design, which is optimal for Gaussian inputs, may exhibit a severe performance loss for finite alphabet inputs in the high signal-to-noise ratio regime. In light of this, we propose a novel Per-Group-GSVD (PG-GSVD) design, which can effectively compensate the performance loss caused by the GSVD design. More importantly, the computational complexity of the PG-GSVD design is by orders of magnitude lower than that of the existing design for finite alphabet inputs while the resulting performance loss is minimal. Then, we extend the PG-GSVD design to the case where only statistical CSI of the eavesdropper is available at the transmitter. Numerical results indicate that the proposed PG-GSVD design can be efficiently implemented in large-scale multiple-antenna systems and achieves significant performance gains compared with the GSVD design.<br
Keywords: Receivers; Signal to noise Ratio; Transmitting antennas; Covariance Matrices; Precoding; MIMO

Secure Video Streaming in Heterogeneous Small Cell Networks with Untrusted Cache Helpers - Xiang, Lin; Ng, Derrick Wing Kwan; Schober, Robert; Wong, Vincent W.S. (2017 IEEE Global Communications Conference, GLOBECOM 2017 - Proceedings, 2017)
This paper studies secure video streaming in cache-enabled small cell networks, where some of the cache-enabled small cell base stations (BSs) helping in video delivery are untrusted. Unfavorably, caching improves the eavesdropping capability of these untrusted helpers as they may intercept both the cached and the delivered video files. To address this issue, we propose joint caching and scalable video coding (SVC) of video files to enable secure cooperative multiple-input multiple-output (MIMO) transmission and exploit the cache memory of all BSs for improving system performance. The caching and delivery design is formulated as a non-convex mixed-integer optimization problem to minimize the total BS transmit power required for secure video streaming. We develop an algorithm based on the modified generalized Benders decomposition (GBD) to solve the problem optimally. Inspired by the optimal algorithm, a low-complexity suboptimal algorithm is also proposed. Simulation results show that the proposed schemes achieve significant gains in power efficiency and secrecy performance compared to three baseline schemes.
CRIS-Team Scopus Importer:2020-01-31

Secure Video Streaming in Heterogeneous Small Cell Networks With Untrusted Cache Helpers - Xiang, Lin; Wing Kwan Ng, Derrick; Schober, Robert; Wong, Vincent W.S. (IEEE Transactions on Wireless Communications, 2018)
This paper studies secure video streaming in cache-enabled small cell networks, where some of the cache-enabled small cell base stations (BSs) helping in video delivery are untrusted. Unfavorably, caching improves the eavesdropping capability of these untrusted helpers as they may intercept both the cached and the delivered video files. To address this issue, we propose joint caching and scalable video coding of video files to enable secure cooperative multiple-input multiple-output transmission and, at the same time, exploit the cache memory of both the trusted and untrusted BSs for improving the system performance. Considering imperfect channel state information at the transmitters, we formulate a two-timescale non-convex mixed-integer robust optimization problem to minimize the total transmit power required for guaranteeing the quality of service and secrecy during video streaming. We develop an iterative algorithm based on a modified generalized Benders decomposition to solve the problem optimally, where the caching and the cooperative transmission policies are determined via offline (long-timescale) and online (short-timescale) optimization, respectively. Furthermore, inspired by the optimal algorithm, a low-complexity suboptimal algorithm based on a greedy heuristic is proposed. Simulation results show that the proposed schemes achieve significant gains in power efficiency and secrecy performance compared to several baseline schemes.<br
Keywords: Streaming media; Wireless communication; Communication system security; Microcell networks; Eavesdropping; MIMO communication; Computer architecture

Securing Massive MIMO Systems: Secrecy for Free with Low-Complexity Architectures - Bereyhi, Ali; Asaad, Saba; Müller, Ralf; Schaefer, Rafael F.; Fischer, Georg; Vincent Poor, H. (IEEE Transactions on Wireless Communications, 2021)
Passively overheard massive multiple-input multiple-output (MIMO) settings are capable of suppressing eavesdroppers via narrow beamforming towards legitimate receivers. This implies that secrecy is obtained almost for free in these settings. This study shows that this is a valid property for a large class of low-complexity massive MIMO transmitters. The investigations consider two dominant approaches for complexity reduction, namely antenna selection and hybrid analog-digital precoding. It is shown that using either approach, the information leakage per achievable sum-rate vanishes as the number of transmit antennas grows large. The results demonstrate that, as the transmit array size grows large, the normalized information leakage obtained by antenna selection and hybrid analog-digital precoding converges to zero double-logarithmically and logarithmically, respectively. The analytical results are confirmed for various benchmark architectures via numerical simulations.
CRIS-Team Scopus Importer:2021-04-23
Keywords: antenna selection; hybrid analog-digital precoding; massive MIMO systems; Physical layer security

Security Enhancement via Device-to-Device Communication in Cellular Networks - Wang, Jiaheng; Tang, Qi; Yang, Chungang; Schober, Robert; Li, Jing (IEEE Signal Processing Letters, 2016)
Device-to-device (D2D) communication underlaying cellular networks improves spectral efficiency but causes interference to cellular users (CUs). Such interference can be utilized to help CUs prevent wiretapping. This paper aims to achieve the twofold goal of security provisioning for CUs and spectral efficiency enhancement for D2D links by optimizing the resource sharing of CUs and D2D links. We first provide the necessary and sufficient conditions for the accessibility of a CU channel by a D2D link. Then, we derive the jointly optimal resource sharing strategy, including the closed-form power control and the optimal channel pairing of CUs and D2D links. Numerical results show that the proposed strategy can improve both the CUs' security and D2D spectral efficiency.<br
Keywords: Device-to-device communication; Copper; Security; Power Control; Quality of Service; Interference; Resource management

Semi-blind channel estimation for massive MIMO systems exploiting low-rank matrix reconstruction - Amiri, Ebrahim; Müller, Ralf; Gerstacker, Wolfgang (International Symposium on Wireless Personal Multimedia Communications, WPMC, 2020)
In order to improve channel estimation for massive multiple-input multiple-output (MIMO) systems, we propose a novel method to mitigate the effect of additive Gaussian noise on the received signal utilizing the fundamental assumption for massive MIMO systems that the number of antennas at the base station (BS) is much larger than the number of several users. We use the asymptotic singular value distribution of a low-rank matrix plus Gaussian noise matrix to reconstruct the signal via the singular value decomposition (SVD) of the received signal. We refer to this new method as low-rank SVD (LRSVD). Simulation results confirm that applying LRSVD can improve the channel estimation and data detection performance significantly for low-to-moderate signal-to-noise ratios, in particular for the semi-blind methods using independent component analysis (ICA) which are sensitive to noise and require significantly noise suppression.
CRIS-Team Scopus Importer:2021-04-19

Semi-blind channel estimation in massive MIMO by mutual information rate as contrast function - Amiri, Ebrahim; Müller, Ralf; Gerstacker, Wolfgang (ITG Workshop on Smart Antennas, 2018)

Sensing Algorithms and Protocol for Simultaneous Sensing and Reception-Based Cognitive D2D Communications in LTE-A Systems - Karunakaran, Prasanth; Gerstacker, Wolfgang (IEEE Transactions on Cognitive Communications and Networking, 2017)
We explore the application of simultaneous sensing and reception (SSR) for cognitive communication in orthogonal frequency division multiplexing (OFDM)-based wireless systems such as 3GPP LTE-A which may find application in multi-tier spectrum sharing paradigms such as the spectrum access system. In such a system, a cognitive radio (CR) synchronized to the macro base station (BS) is assumed to exploit the spectral holes in the OFDMA time-frequency grid. We analyze the impact of timing alignment in such a system and show that power control and guard bands are essential to support such an operation. Practical algorithms for SSR with the constant false alarm rate property are developed using the generalized likelihood ratio test principle to protect macro BS users occupying the same transmission resources as the CRs. Subsequently, we propose a transmission-reception protocol with SSR for bidirectional communication between two time-division duplex CRs and compare it to a protocol with only sensing before transmission (SBT). The simulation results show that the sensing overhead in traditional SBT protocols can be much reduced with the use of SSR when the BS activity in adjacent slots is highly correlate

Sensitivity Analysis of Outphasing Elements for Hybrid Analogue Digital Beamforming and Single-RF MIMO - Gäde, Bernhard; Amon, Michael; Fischer, Georg; Müller, Ralf (KleinheubacherTagung 2018, 2018)

Shearlet analysis of confocal laser-scanning microscopy images to extract morphological features of neurons - Suendermann, Frederik; Lotter, Sebastian; Lim, Wang-Q; Golovyashkina, Nataliya; Brandt, Roland; Kutyniok, Gitta (Laser Scanning Microscopy and Quantitative Image Analysis of Neuronal Tissue, 2014)
Due to the progress in laser scanning microscopy techniques computational image analysis methods increasingly have come in the focus of biology. Methods of image analysis can broadly be divided into two groups: The first group deals with segmentation and noise reduction problems, while the second group focuses on the statistical and morphological analysis of structures. Structure analysis strongly depends on the quality of the output of segmentation approaches, which aim to separate the digital image in undesirable (background) and desirable (foreground) information. The progress in microscopy techniques has led to a large amount of highly detailed images containing fine structures. Unfortunately, such images cannot be separated in an automated way without loss of considerable detail and information. In this chapter, we present an approach that is based on compressed sensing methods to separate biologically relevant information, in this case the structure of dendrites, from an image background. The approach has the advantage that it allows separating even fine structural details in large images without the common disadvantages of intensity based algorithms. We have written a freely downloadable software suite and present a detailed protocol of its use to determine morphological features of dendritic trees from fluorescence stained 3D image stacks. © 2014 Springer Science+Business Media New York.
Created from Fastlane, Scopus look-up
Keywords: Compressed sensing; Image analysis; Image processing; Image reconstruction; Image separation; Neuron thickness; Neuronal morphology

Signal Reception With Generic Three-State Receptors in Synaptic MC - Lotter, Sebastian; Barros, Michael Taynnan; Schober, Robert; Schäfer, Maximilian (IEEE Global Communications Conference, 2022)
Synaptic communication is studied by communication engineers for two main reasons. One is to enable novel neuroengineering applications that require interfacing with neurons. The other reason is to draw inspiration for the design of synthetic molecular communication systems. Both of these goals require understanding of how the chemical synaptic signal is sensed and transduced at the synaptic receiver (Rx). While signal reception in synaptic molecular communication (SMC) depends heavily on the kinetics of the receptors employed by the synaptic Rxs, existing channel models for SMC either oversimplify the receptor kinetics or employ complex, high-dimensional kinetic schemes limited to specific types of receptors. Both approaches do not facilitate a comparative analysis of different types of natural synapses. In this paper, we propose a novel deterministic channel model for SMC which employs a generic three-state receptor model that captures the characteristics of the most important receptor types in SMC. The model is based on a transfer function expansion of Fick's diffusion equation and accounts for release, diffusion, and degradation of neurotransmitters as well as their reversible binding to finitely many generic postsynaptic receptors. The proposed SMC model is the first that allows studying the impact of the characteristic dynamics of the main postsynaptic receptor types on synaptic signal transmission. Numerical results indicate that the proposed model indeed exhibits a wide range of biologically plausible dynamics when specialized to specific natural receptor types.<br

Simple Semi-Grant-Free Transmission Strategies Assisted by Non-Orthogonal Multiple Access - Ding, Zhiguo; Schober, Robert; Fan, Pingzhi; Poor, H. Vincent (IEEE Transactions on Communications, 2019)
Grant-free transmission is an important feature to be supported by future wireless networks since it reduces the signaling overhead caused by conventional grant-based schemes. However, for grant-free transmission, the number of users admitted to the same channel is not capped, which can lead to a failure of multi-user detection. This paper proposes non-orthogonal multiple-access (NOMA) assisted semi-grant-free (SGF) transmission, which is a compromise between grant-free and grant-based schemes. In particular, instead of reserving channels either for grant-based users or grant-free users, the focus here is on an SGF communication scenario, where users are admitted to the same channel via a combination of grant-based and grant-free protocols. As a result, a channel reserved by a grantbased user can be shared by grant-free users, which improves both connectivity and spectral efficiency. Two NOMA assisted SGF contention control mechanisms are developed to ensure that, with a small amount of signaling overhead, the number of admitted grant-free users is carefully controlled and the interference from the grant-free users to the grant-based users is effectively suppressed. Analytical results are provided to demonstrate that the two proposed SGF mechanisms employing different successive interference cancelation decoding orders are applicable to different practical network scenarios.
CRIS-Team WoS Importer:2019-07-09

Simple Semi-Grant-Free Transmission Strategies Assisted by Non-Orthogonal Multiple Access - Ding, Zhiguo; Schober, Robert; Fan, Pingzhi; Poor, H. Vincent (IEEE Transactions on Communications, 2019)
Grant-free transmission is an important feature to be supported by future wireless networks since it reduces the signaling overhead caused by conventional grant-based schemes. However, for grant-free transmission, the number of users admitted to the same channel is not capped, which can lead to a failure of multi-user detection. This paper proposes non-orthogonal multiple-access (NOMA) assisted semi-grant-free (SGF) transmission, which is a compromise between grant-free and grant-based schemes. In particular, instead of reserving channels either for grant-based users or grant-free users, the focus here is on an SGF communication scenario, where users are admitted to the same channel via a combination of grant-based and grant-free protocols. As a result, a channel reserved by a grant-based user can be shared by grant-free users, which improves both connectivity and spectral efficiency. Two NOMA assisted SGF contention control mechanisms are developed to ensure that, with a small amount of signaling overhead, the number of admitted grant-free users is carefully controlled and the interference from the grant-free users to the grant-based users is effectively suppressed. Analytical results are provided to demonstrate that the two proposed SGF mechanisms employing different successive interference cancelation decoding orders are applicable to different practical network scenarios.<br
Keywords: Base stations; Protocols; NOMA; Silicon Carbide; Decoding; Multiuser detection; Fans

Simulating with AcCoRD: Actor-based Communication via Reaction–Diffusion - Noel, Adam; Cheung, Karen C.; Schober, Robert; Makrakis, Dimitrios; Hafid, Abdelhakim (Nano Communication Networks, 2017)
This paper introduces AcCoRD (Actor-based Communication via Reaction–Diffusion)version 1.0. AcCoRD is a sandbox reaction–diffusion solver designed for the study of molecular communication systems. It uses a hybrid of microscopic and mesoscopic simulation models that enables scalability via user control of local accuracy. AcCoRD is developed in C as an open source command line tool and includes utilities to process simulation output in MATLAB. The latest code and links to user documentation can be found at https://github.com/adamjgnoel/AcCoRD/. This paper provides an overview of AcCoRD's design, including the motivation for developing a specialized reaction–diffusion solver. The corresponding algorithms are presented in detail, including the computational complexity of the microscopic and mesoscopic models. Other novel derivations include the transition rates between adjacent mesoscopic subvolumes of different sizes. Simulation results demonstrate the use of AcCoRD as both an accurate reaction–diffusion solver and one that is catered to the analysis of molecular communication systems. Videos in the supplementary materials demonstrate many of the simulated scenarios. Additional insights from the simulation results include the selection of suitable hybrid model parameters, the impact of reactive surfaces that are in the proximity of a hybrid interface, and the size of a bounded environment that is necessary to assume that it is unbounded. The development of AcCoRD is ongoing, so its future direction is also discussed in order to highlight improvements that will expand its potential areas of application. New features that are being planned at the time of writing include a fluid flow model and more complex actor behavior.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Mesoscopic simulation; Microscopic simulation; Molecular communication; Reaction–diffusion

Simultaneous information transmission and wireless energy transfer via selecting one out of two relays - Michalopoulos, Diomidis; Suraweera, Himal A.; Schober, Robert (2014 6th International Symposium on Communications, Control and Signal Processing (ISCCSP), 2014)
In certain applications, relay terminals can be employed to simultaneously deliver information and energy to a designated receiver and a radio frequency (RF) energy harvester, respectively. The relays are efficiently deployed when one out of the set of available relays is activated, as multiple relay activation reduces the overall spectral efficiency. In this regard, since the relays that are preferable for information and energy delivery do not necessarily coincide with one another, relay selection entails a tradeoff between information transmission and energy transfer. Assuming that two relays are available, we investigate the behavior of the ergodic capacity of the information transmission to the receiver, for a given amount of energy transferred to the RF energy harvester. We propose the optimal relay selection method for a given energy transfer constraint (in a maximum achievable capacity sense), as well as three suboptimal schemes which apply to scenarios with limited channel state information.<br
Keywords: Relays; Energy exchange; Information processing; Wireless sensor networks; Wireless communication; Radio frequency; Receivers

Simultaneously Transmitting And Reflecting (STAR) RIS Aided Wireless Communications - Mu, Xidong; Liu, Yuanwei; Guo, Li; Lin, Jiaru; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
The novel concept of simultaneously transmitting and reflecting (STAR) reconfigurable intelligent surfaces (RISs) is investigated, where the incident wireless signal is divided into transmitted and reflected signals passing into both sides of the space surrounding the surface, thus facilitating a full-space manipulation of signal propagation. Based on the introduced basic signal model of ‘STAR’, three practical operating protocols for STAR-RISs are proposed, namely energy splitting (ES), mode switching (MS), and time switching (TS). Moreover, a STAR-RIS aided downlink communication system is considered for both unicast and multicast transmission, where a multi-antenna base station (BS) sends information to two users, i.e., one on each side of the STAR-RIS. A power consumption minimization problem for the joint optimization of the active beamforming at the BS and the passive transmission and reflection beamforming at the STAR-RIS is formulated for each of the proposed operating protocols, subject to communication rate constraints of the users. For ES, the resulting highly-coupled non-convex optimization problem is solved by an iterative algorithm, which exploits the penalty method and successive convex approximation. Then, the proposed penalty-based iterative algorithm is extended to solve the mixed-integer non-convex optimization problem for MS. For TS, the optimization problem is decomposed into two subproblems, which can be consecutively solved using state-of-the-art algorithms and convex optimization techniques. Finally, our numerical results reveal that: 1) the TS and ES operating protocols are generally preferable for unicast and multicast transmission, respectively; and 2) the required power consumption for both scenarios is significantly reduced by employing the proposed STAR-RIS instead of conventional reflecting/transmiting-only RISs.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Array signal processing; Multicast communication; Operating protocols; Optimization; Power demand; Protocols; reconfigurable intelligent surfaces; simultaneous transmission and reflection; Unicast; unicast and multicast communication; Wireless communication

Simultaneously Transmitting and Reflecting (STAR)-RISs: A Coupled Phase-Shift Model - Liu, Yuanwei; Mu, Xidong; Schober, Robert; Poor, H. Vincent (IEEE International Conference on Communications, 2022)
A simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) aided communication system is investigated, where an access point sends information to two users located on each side of the STAR-RIS. Different from current works assuming that the phase-shift coefficients for transmission and reflection can be independently adjusted, which is non-trivial to realize for purely passive STAR-RISs, a coupled transmission and reflection phase-shift model is considered. Based on this model, a power consumption minimization problem is formulated for both non-orthogonal multiple access (NOMA) and orthogonal multiple access (OMA). In particular, the amplitude and phase-shift coefficients for transmission and reflection are jointly optimized, subject to the rate constraints of the users. To solve this non-convex problem, an efficient element-wise alternating optimization algorithm is developed to find a high-quality suboptimal solution, whose complexity scales only linearly with the number of STAR elements. Finally, numerical results are provided for both NOMA and OMA to validate the effectiveness of the proposed algorithm by comparing its performance with that of STAR-RISs using the independent phase-shift model and conventional reflecting/transmitting-only RISs.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Coefficient design; coupled phase-shift model; reconfigurable intelligent surfaces; simultaneous transmission and reflection

Simultaneous Wireless Information and Power Transfer in modern communication systems - Krikidis, Ioannis; Timotheou, Stelios; Nikolaou, Symeon; Zheng, Gan; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Communications Magazine, 2014)
Energy harvesting for wireless communication networks is a new paradigm that allows terminals to recharge their batteries from external energy sources in the surrounding environment. A promising energy harvesting technology is wireless power transfer where terminals harvest energy from electromagnetic radiation. Thereby, the energy may be harvested opportunistically from ambient electromagnetic sources or from sources that intentionally transmit electromagnetic energy for energy harvesting purposes. A particularly interesting and challenging scenario arises when sources perform simultaneous wireless information and power transfer (SWIPT), as strong signals not only increase power transfer but also interference. This article provides an overview of SWIPT systems with a particular focus on the hardware realization of rectenna circuits and practical techniques that achieve SWIPT in the domains of time, power, antennas, and space. The article also discusses the benefits of a potential integration of SWIPT technologies in modern communication networks in the context of resource allocation and cooperative cognitive radio networks.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Decoding; Energy harvesting; Green products; Radio frequency; Receiving antennas; Telecommunication services; Wireless communication

Single-antenna interference cancellation for complex-valued signal constellations with applications to GSM/EDGE - Lehmann, Andreas; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications, 2012)
Different approaches for single antenna interference cancellation (SAIC) in GSM/EDGE have been proposed. Most of them work best in synchronous interference environments. We propose three different modifications of the conventional EDGE receiver, which target the harmful effects of asynchronous co-channel interference (ACCI). All modifications are applicable to all linear modulation alphabets and do not require any modification of the GSM/EDGE air interface. We model the effect of ACCI as impulsive Generalized Gaussian noise. The proposed methods include a modification of the conventional path metrics for the reduced-state equalizer and the decoder, respectively, as well as a Viterbi algorithm, which performs erasure decoding. Based on simulation results, the performances of the proposed schemes are compared with that of a standard GSM/EDGE receiver. We show that all three proposed schemes outperform the standard receiver in ACCI environments and discuss their complexit

Single Antenna Interference Cancellation for GSM/VAMOS/EDGE Using Lp-Norm Detection and Decoding - Ruder, Michael; Lehmann, Andreas; Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Wireless Communications, 2015)
Different schemes for single antenna interference cancellation (SAIC) in the Global System for Mobile Communications (GSM) have been proposed so far. Most of these schemes work best in synchronous interference environments and are limited to Gaussian minimum-shift keying (GMSK) modulation. In this paper, we propose several modifications of the conventional GSM receiver, which target the harmful effects of asynchronous co-channel interference (ACCI). Based on the observation that the impairment caused by ACCI cannot be modeled as additive Gaussian noise, which was assumed for the derivation of the metric used in state-of-the-art receivers, we propose modeling the impairment as Generalized Gaussian noise (GGN). This leads to modifications of the conventional branch metrics of the reduced-state equalizer and the decoder employed at the receiver. Both proposed modifications are applicable to any linear modulation alphabet and do not require any modification of the GSM air interface. Hence, the proposed novel branch metrics are also applicable in Enhanced Data Rates for GSM Evolution (EDGE) systems which employ 8-ary phase-shift keying (8-PSK) modulation and where the SAIC algorithms tailored for GMSK cannot be used. Furthermore, we show that the proposed branch metric modifications also improve the performance of the new Voice Services over Adaptive Multiuser channels on One Slot (VAMOS) extension of GSM in ACCI environments. Based on simulation results, the performance of the proposed schemes is compared with that of an unmodified receiver employing the conventional Gaussian metric. We show that the proposed receivers outperform the unmodified receiver in ACCI environments and discuss the complexity entailed by the proposed branch metric modifications.<br
Keywords: Measurement; GSM; Receivers; Decoding; Equalizers; Interference; Modulation

Slepian-based two-dimensional estimation of time-frequency variant MIMO-OFDM channels - Rossi, Pierluigi Salvo; Müller, Ralf (IEEE Signal Processing Letters, 2008)
A linear channel estimator for multiple-input multiple-output orthogonal frequency-division multiplexing (MIMO-OFDM) systems, based on a two-dimensional Slepian expansion, is presented. The estimator is meant to be part of an iterative receiver. We consider both estimation based on pilots only and on pilots and data, the latter considered as a reference for the case when feedback from decoders is exploited. Performances are analyzed via computer simulations comparing the relative minimum square error (RMMSE) of an analogous one-dimensional estimator and the proposed extension. © 2007 IEEE.
Keywords: Channel estimation; Discrete prolate spheroidal sequences; Iterative receivers; Multiple-input multiple-output (MIMO) channels; Orthogonal frequency-division multiplexing (OFDM) systems

SLNC for multi-source multi-relay BICM-OFDM systems - Islam, Toufiqul; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay (IEEE Transactions on Wireless Communications, 2014)
In this paper, we study the application of bit - interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM) to reap the benefits of wireless multiuser network coding in practical frequency - selective fading channels. We propose a mapping based symbol level network coding (SLNC) scheme for a cooperative diversity system comprising multiple sources, multiple relays, and one common destination. A simple cooperative maximum - ratio combining scheme is used at the destination and is shown to successfully exploit both the full spatial and the full frequency diversity offered by the channel for arbitrary numbers of sources, arbitrary numbers of relays, and arbitrary linear modulation schemes. To gain analytical insight for system design, we derive a closed - form upper bound for the asymptotic worst - case pairwise error probability (PEP) and obtain the diversity gain of the considered SLNC scheme for BICM - OFDM systems. These analytical results reveal the influence of the various system parameters, such as the number of sources, the free distance of the code, and the frequency diversity of the involved links, on performance. Furthermore, we propose two different relay selection schemes for the considered system: a) bulk selection, i.e., a single best relay is selected to transmit on all sub - carriers, and b) per - subcarrier selection, where a best relay is selected on each sub - carrier. Last but not least, we exploit the derived PEP expression for selecting a subset of sources from the set of active sources when the number of active sources is larger than the number of available orthogonal relay channels. We study the achievable diversity gain for the proposed relay and source subset selection schemes. Numerical results corroborate the derived diversity gain expressions and confirm the performance gains. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM - OFDM; Cooperative diversity; network coding; relay selection; source subset selection

Smart and Reconfigurable Wireless Communications: From IRS Modeling to Algorithm Design - Yu, Xianghao; Jamali, Vahid; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Wireless Communications, 2021)
Intelligent reflecting surfaces (IRSs) have been introduced into wireless communications systems due to their great potential to smartly customize and reconfigure radio propagation environments in a cost-effective manner. Despite the promising advantages of IRSs, academic research on IRSs is still in its infancy. In particular, the design and analysis of IRS-assisted wireless communication systems critically depend on accurate and tractable modeling of the IRS. In this article, we first present and compare three IRS models, namely the conventional independent diffusive scatterer-based model, physics-based model, and impedance network-based model, in terms of their accuracy, tractability, and implementation simplicity. Furthermore, a new framework based on partitioning the IRS into tiles and employing codebooks of transmission modes is introduced to enable scalable IRS optimization. Then we investigate the impact of the three considered IRS models on system design, where several crucial technical challenges for the efficient design of IRS-assisted wireless systems are identified and the corresponding solutions are unraveled. Furthermore, to illustrate the properties of the considered models and the efficiency of the proposed solution concepts, IRS-assisted secure wireless systems and simultaneous wireless information and power transfer systems are studied in more detail. Finally, several promising future research directions for IRS-assisted wireless systems are highlighted.
CRIS-Team WoS Importer:2022-02-04

Smart Resource Allocation Model via Artificial Intelligence in Software Defined 6G Networks - Nouruzi, Ali; Rezaei, Atefeh; Khalili, Ata; Mokari, Nader; Javan, Mohammad Reza; Jorswieck, Eduard A.; Yanikomeroglu, Halim (IEEE International Conference on Communications, 2023)
In this paper, we design a new flexible smart software-defined radio access network (Soft-RAN) architecture with traffic awareness for sixth generation (6G) wireless networks. In particular, we consider a hierarchical resource allocation model for the proposed smart soft-RAN model where the software-defined network (SDN) controller is the first and foremost layer of the framework. This unit dynamically monitors the network to select a network operation type on the basis of distributed or centralized resource allocation procedures to intelligently perform decision-making. In this paper, our aim is to make the network more scalable and more flexible in terms of conflicting performance indicators such as achievable data rate, overhead, and complexity indicators. To this end, we introduce a new metric, i.e, throughput-overhead-complexity (TOC), for the proposed machine learning-based algorithm, which supports a trade-off between these performance indicators. In particular, the decision making based on TOC is solved via deep reinforcement learning (DRL) which determines an appropriate resource allocation policy. Furthermore, for the selected algorithm, we employ the soft actor-critic (SAC) method which is more accurate, scalable, and robust than other learning methods. Simulation results demonstrate that the proposed smart network achieves better performance in terms of TOC compared to fixed centralized or distributed resource management schemes that lack dynamism. Moreover, our proposed algorithm outperforms conventional learning methods employed in recent state-of-the-art network designs.
CRIS-Team Scopus Importer:2023-12-15

Soft interference cancellation for random coding in massive gaussian multiple-access† - Müller, Ralf (Entropy, 2021)
In 2017, Polyanskiy showed that the trade-off between power and bandwidth efficiency for massive Gaussian random access is governed by two fundamentally different regimes: low power and high power. For both regimes, tight performance bounds were found by Zadik et al., in 2019. This work utilizes recent results on the exact block error probability of Gaussian random codes in additive white Gaussian noise to propose practical methods based on iterative soft decoding to closely approach these bounds. In the low power regime, this work finds that orthogonal random codes can be applied directly. In the high power regime, a more sophisticated effort is needed. This work shows that power-profile optimization by means of linear programming, as pioneered by Caire et al. in 2001, is a promising strategy to apply. The proposed combination of orthogonal random coding and iterative soft decoding even outperforms the existence bounds of Zadik et al. in the low power regime and is very close to the non-existence bounds for message lengths around 100 and above. Finally, the approach of power optimization by linear programming proposed for the high power regime is found to benefit from power imbalances due to fading which makes it even more attractive for typical mobile radio channels.
CRIS-Team Scopus Importer:2021-06-04
Keywords: AWGN; Block error probability; Finite blocklength; Iterative decoding; Low-latency communications; Multiple-access; Non-othogonal multiple-access; Random coding; Spectral efficiency; Successive cancellation

Space-Time Block Coding and Receive Diversity for WLAN IEEE 802.11b - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (Conference Proceedings, 2005)
In this paper, we investigate time-reversal space-time block codes (TR-STBCs) and receive diversity for complementary code keying (CCK) modulation, which is employed in the wireless local area network (WLAN) standard IEEE 802.11b. The construction of TR-STBCs from orthogonal space-time block codes designed for flat fading channels for an arbitrary number of transmit antennas is discussed. Furthermore, an equivalent single-input single-output (SISO) transmission model for CCK is derived, which combines the effects of space-time coding and multiple receive antennas. For indoor multipath fading channels numerical results are provided for TR-STBCs with two and three transmit antennas, which demonstrate that significant gains can be obtained compared to a SISO transmission. For detection, decision-feedback equalization (DFE) and reduced-state sequence estimation (RSSE) especially tailored for CCK transmission are considered. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.mobilk.spacet
Keywords: Block codes; Wireless LAN; Diversity reception; Decision feedback Equalizers; Fading; Diversity methods; Modulation coding; Transmitting antennas; Frequency diversity; Decoding

Special Issue-Advances in Molecular Communications: Theory, Experiment, and Application - Haselmayr, Werner; Hyttinen, Jari; Schäfer, Maximilian; Femminella, Mauro; Morris, Richard J.; Lenk, Kerstin; Noel, Adam; Barros, Michael Taynnan (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2021)
Molecular communications (MC) broadly defines information exchange using (bio-)chemical signals over multiple scales. The research in this area addresses various fields where MC plays an important role. Notable examples include 1) the modeling of living systems, which aims to gain new insights into biological systems; 2) their interface with the outer world, aiming to develop techniques to control biological systems; and 3) synthetic MC, focusing on the design, analysis, and implementation of human-made MC systems at different scales.
CRIS-Team WoS Importer:2021-07-23

Special Issue on Intelligent Reflecting Surface for Green Communication, Computing, and Sensing - You, Changsheng; Wu, Qingqing; Liu, Yuanwei; Schober, Robert; Swindlehurst, A. Lee (IEEE Transactions on Green Communications and Networking, 2022)
CRIS-Team WoS Importer:2022-03-11

Special Issue on Next Generation Multiple Access-Part I - Liu, Yuanwei; Zhang, Shuowen; Ding, Zhiguo; Schober, Robert; Al-Dhahir, Naofal; Hossain, Ekram; Shen, Xuemin (IEEE Journal on Selected Areas in Communications, 2022)
As the long-term evolution (LTE) system is reaching maturity and the fifth-generation (5G) systems are being commercially deployed, researchers have turned their attention to the development of next-generation wireless networks. Compared to current wireless networks, on the one hand, next-generation wireless networks are expected to achieve significantly higher capacity, extremely low latency, ultra-high reliability, as well as massive and ubiquitous connectivity for supporting diverse disruptive applications (e.g., virtual reality (VR), augmented reality (AR), and industry 4.0). On the other hand, the evolution toward next-generation wireless networks requires a paradigm shift from the communication-oriented design to a multi-functional design, including communication, sensing, imaging, computing, and localization. Looking back at the history of wireless communication systems, multiple access (MA) techniques have been key enablers. From the first generation (1G) to the fifth generation (5G), orthogonal multiple access (OMA) schemes are mainly employed, where multiple users are allotted in orthogonal frequency/time/code resources, and the uplink transmission of the code code-division multiple-access (CDMA) uses non-orthogonal code resources. However, given the enormous challenges and diverse services of next-generation wireless networks, which significantly differ from that in current and previous wireless networks, existing MA schemes may not be applicable. As a result, a fundamental issue is the design of next-generation multiple access (NGMA) techniques. The key concept of NGMA is to enable a very large number of users/devices to be efficiently, flexibly, and intelligently connected with the network over the given wireless radio resources to not only satisfy stringent communication requirements but also realize heterogeneous functions. The investigation of NGMA is still in the infancy stage, and extensive research efforts have to be devoted to areas, including but not limited to 1) the development of new MA schemes, such as non-orthogonal multiple access (NOMA) and space division multiple access (SDMA), which are capable of achieving higher bandwidth efficiency and higher connectivity compared with conventional MA schemes; 2) the development of innovative techniques, such as reconfigurable metasurfaces, random access, advanced modulation, and channel coding, which are beneficial to the overall design of NGMA; and 3) the exploitation of advanced machine learning (ML) tools and big data techniques for providing effective solutions to address newly emerging NGMA problems.
CRIS-Team WoS Importer:2022-04-01

Special Issue on UAV Communications in 5G and Beyond Networks-Part I - Wu, Qingqing; Xu, Jie; Zeng, Yong; Ng, Derrick Wing Kwan; Al-Dhahir, Naofal; Schober, Robert; Swindlehurst, A. Lee (IEEE Journal on Selected Areas in Communications, 2021)
CRIS-Team WoS Importer:2021-09-24

Special Section on Full-Duplex Transceivers for Future Networks: Theory and Techniques - Tran, Nghi H.; Suraweera, Himal A.; Riihonen, Taneli; Reiskarimian, Negar; Jain, Hardik; Schober, Robert (IEEE Open Journal of the Communications Society, 2021)
Conventional wireless communication systems operate in a half-duplex mode, i.e., current radios cannot transmit and receive at the same time and on the same frequency. Full-duplex wireless operation was generally assumed to be impossible due to the great difference in transmit and receive signal power levels. However, recent advances in antenna, hardware, and signal processing techniques have shown that full-duplex operation is practically feasible. Thanks to novel combinations of antenna, analog, and digital cancellation techniques, self-interference suppression of 80-110 dB can be made possible. The feasibility in building a practical full-duplex radio using off-the-shelf hardware and software-defined radios therefore alleviates many problems in wireless network design.
CRIS-Team WoS Importer:2021-11-26

Spectral and Energy-Efficient Wireless Powered IoT Networks: NOMA or TDMA? - Wu, Qingqing; Chen, Wen; Wing Kwan Ng, Derrick; Schober, Robert (IEEE Transactions on Vehicular Technology, 2018)
Wireless powered communication networks (WPCNs), where multiple energy-limited devices first harvest energy in the downlink and then transmit information in the uplink, have been envisioned as a promising solution for the future Internet-of-Things (IoT). Meanwhile, nonorthogonal multiple access (NOMA) has been proposed to improve the system spectral efficiency (SE) of the fifth-generation (5G) networks by allowing concurrent transmissions of multiple users in the same spectrum. As such, NOMA has been recently considered for the uplink of WPCNs based IoT networks with a massive number of devices. However, simultaneous transmissions in NOMA may also incur more transmit energy consumption as well as circuit energy consumption in practice which is critical for energy constrained IoT devices. As a result, compared to orthogonal multiple access schemes such as time-division multiple access (TDMA), whether the SE can be improved and/or the total energy consumption can be reduced with NOMA in such a scenario still remains unknown. To answer this question, we first derive the optimal time allocations for maximizing the SE of a TDMA-based WPCN (T-WPCN) and a NOMA-based WPCN (N-WPCN), respectively. Subsequently, we analyze the total energy consumption as well as the maximum SE achieved by these two networks. Surprisingly, it is found that N-WPCN not only consumes more energy, but also is less spectral efficient than T-WPCN. Simulation results verify our theoretical findings and unveil the fundamental performance bottleneck, i.e., “worst user bottleneck problem”, in multiuser NOMA systems.<br
Keywords: NOMA; Energy consumption; Wireless communication; Time division multiple Access; Throughput; Resource Management; IEEE transactions

Spectral efficiency in large-scale MIMO-OFDM systems with per-antenna power cost - Ng, Derrick Wing Kwan; Schober, Robert (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2012)
In this paper, resource allocation for multipleinput multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) downlink networks with large numbers of base station antennas is studied. Assuming perfect channel state information at the transmitter, the resource allocation algorithm design is modeled as a non-convex optimization problem which takes into account the joint power consumption of the power amplifiers, antenna unit, and signal processing circuit unit. Subsequently, by exploiting the law of large numbers and dual decomposition, an efficient suboptimal iterative resource allocation algorithm is proposed for maximization of the system capacity (bit/s). In particular, closed-form power allocation and antenna allocation policies are derived in each iteration. Simulation results illustrate that the proposed iterative resource allocation algorithm achieves a close-to-optimal performance in a small number of iterations and unveil a trade-off between system capacity and the number of activated antennas: Activating all antennas may not be a good solution for system capacity maximization when a system with a per antenna power cost is considered. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Spectral efficiency of CDMA systems with linear MMSE interference suppression - Müller, Ralf; et al. (IEEE Transactions on Communications, 1999)
Code-division multiple-access is a promising technique for communication systems. Recently, many demodulation schemes have been proposed which take account of inherent multiple-access interference. In this paper, linear interference suppression as proposed in, e.g, [1], is compared with conventional demodulation based on power-bandwidth plane. This approach is much more general than the comparison of error rates for specific scenarios as used to be done before. In case of interference suppression, spectral efficiency is calculated by a combination of analysis and simulation. The coding and modulation scheme used is characterized within power-bandwidth plane for a single-call scenario as well as for a cellular system. In the latter case, some statements which are valid for the single-cell scenario have to be revised.

Spectral efficiency of random CDMA with constant envelope modulation - Müller, Ralf; Lampe, Alexander (AEÜ - International Journal of Electronics and Communications, 2011)
This paper studies the spectral efficiency of code-division multiple access with constant envelope modulation in the large system limit. Despite the fact that continuous phase modulation is hit by a severe drawback in spectral efficiency as compared to quadrature amplitude modulation on a single user communication link, the gap in terms of spectral efficiency is found to be negligible when employed on a multiple access channel with the CDMA protocol. Accounting for the efficiency of the transmit amplifier, the latter comparison becomes even favorable for constant envelope modulation. © 2011 Elsevier GmbH. All rights reserved.
Keywords: Amplifier efficiency; Code-division multiple-access; Continuous phase modulation; Large-system analysis; Multiuser detection; Random spreading; Spectral efficiency

Spectral efficient optimization in OFDM systems with wireless information and power transfer - Ng, Derrick Wing Kwan; Schober, Robert (European Signal Processing Conference, 2013)
This paper considers an orthogonal frequency division multiplexing (OFDM) point-to-point wireless communication system with simultaneous wireless information and power transfer. We study a receiver which is able to harvest energy from the desired signal, noise, and interference. In particular, we consider a power splitting receiver which dynamically splits the received power into two power streams for information decoding and energy harvesting. We design power allocation algorithms maximizing the spectral efficiency (bit/s/Hz) of data transmission. In particular, the algorithm design is formulated as a nonconvex optimization problem which takes into account the constraint on the minimum power delivered to the receiver. The problem is solved by using convex optimization techniques and a one-dimensional search. The optimal power allocation algorithm serves as a system benchmark scheme due to its high complexity. To strike a balance between system performance and computational complexity, we also propose two suboptimal algorithms which require a low computational complexity. Simulation results demonstrate the excellent performance of the proposed suboptimal algorithms. © 2013 EURASIP.
CRIS-Team Scopus Importer:2020-02-03

Sphere Constrained Block RSSE with Per-Survivor Intra-Block Processing for CCK Transmission - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (2008 IEEE 10th International Symposium on Spread Spectrum Techniques and Applications, 2008)
In the wireless local area network (WLAN) standard IEEE 802.11b, complementary code keying (CCK) modulation has been adopted for the high data rate transmission mode, which can be considered as a special type of spread spectrum modulation with data-dependent spreading. In this paper, complexity reduction for block reduced-state sequence estimation (bRSSE), tailored for CCK transmission over frequency-selective channels, is considered. A trellis diagram for the chip phases of the codewords fully describes the CCK code properties. Subset trellises are derived from the full CCK trellis diagram based on set partitioning of the multidimensional CCK code set. The CCK subset trellises connect consecutive bRSSE states in order to form a compound trellis. The Viterbi algorithm (VA) with per-survivor processing is applied to the compound trellis to take the inter-chip interference into account. Inter-codeword interference is also accounted for by state-dependent decision feedback. The resulting scheme is denoted as bRSSE-pS and has a significantly lower complexity than bRSSE with brute-force search. By introducing a sphere constraint on the overall decoding trellis (SC-bRSSE-pS), the complexity of bRSSE-pS can be further reduced. Omitting states in the CCK subset trellises that violate the sphere constraint, edges that emanate from such states can be pruned, and the average number of metric calculations per CCK trellis segment can be reduced. Simulation results show that the performance of bRSSE-pS and SC-bRSSE-pS, respectively, is essentially equivalent to that of bRSSE with brute-force search, while complexity is significantly reduce

Spherical Diffusion Model with Semi-Permeable Boundary: A Transfer Function Approach - Schäfer, Maximilian; Wicke, Wayan; Haselmayr, Werner; Rabenstein, Rudolf; Schober, Robert (IEEE International Conference on Communications (ICC), 2020)
The derivation of suitable analytical models is an important step for the design and analysis of molecular commu- nication systems. However, many existing models have limited applicability in practical scenarios due to various simplifications (e.g., assumption of an unbounded environment). In this paper, we develop a realistic model for particle diffusion in a bounded sphere and particle transport through a semi-permeable bound- ary. This model can be used for various applications, such as modeling of inter-/intra-cell communication or the release process of drug carriers. The proposed analytical model is based on a transfer function approach, which allows for fast numerical evaluation and provides insights into the impact of the relevant molecular communication system parameters. The proposed solution of the bounded spherical diffusion problem is formulated in terms of a state-space description and the semi-permeable boundary is accounted for by a feedback loop. Particle-based simulations verify the proposed modeling approach.

STAR-RISs: A Correlated T&R Phase-Shift Model and Practical Phase-Shift Configuration Strategies - Xu, Jiaqi; Liu, Yuanwei; Mu, Xidong; Schober, Robert; Poor, H. Vincent (IEEE Journal of Selected Topics in Signal Processing, 2022)
A correlated transmission and reflection (T&R) phase-shift model is proposed for passive lossless simultaneously transmitting and reflecting reconfigurable intelligent surfaces (STAR-RISs). A STAR-RIS-aided two-user downlink communication system is investigated for both orthogonal multiple access (OMA) and non-orthogonal multiple access (NOMA). To evaluate the impact of the correlated T&R phase-shift model on the communication performance, three phase-shift configuration strategies are developed, namely the primary-secondary phase-shift configuration (PS-PSC), the diversity preserving phase-shift configuration (DP-PSC), and the T/R-group phase-shift configuration (TR-PSC) strategies. Furthermore, we derive the outage probabilities for the three proposed phase-shift configuration strategies as well as for those for the random phase-shift configuration and the independent phase-shift model, which constitute performance lower and upper bounds, respectively. Then, the diversity order of each strategy is investigated based on the obtained analytical results. It is shown that the proposed DP-PSC strategy achieves full diversity order simultaneously for users located on both sides of the STAR-RIS. Moreover, power scaling laws are derived for the three proposed strategies and for the random phase-shift configuration. Numerical simulations reveal a performance gain if the users on both sides of the STAR-RIS are served by NOMA instead of OMA. Moreover, it is shown that the proposed DP-PSC strategy yields the same diversity order as achieved by STAR-RISs under the independent phase-shift model and a comparable power scaling law with only 4 dB reduction in received power.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Analytical models; Electromagnetics; Hardware; hardware modelling; NOMA; Numerical models; performance analysis; Probability; reconfigurable intelligent surfaces (RISs); Reflection; simultaneous transmission and reflection; Wireless networks

STAR: SIMULTANEOUS TRANSMISSION AND REFLECTION FOR 360 degrees COVERAGE BY INTELLIGENT SURFACES - Liu, Yuanwei; Mu, Xidong; Xu, Jiaqi; Schober, Robert; Hao, Yang; Poor, H. Vincent; Hanzo, Lajos (IEEE Wireless Communications, 2021)
A novel simultaneous transmitting and reflecting (STAR) system design relying on reconfigurable intelligent surfaces (RISs) is conceived. First, an existing prototype is reviewed, and the potential benefits of STAR-RISs are discussed. Then the key differences between conventional reflecting-only RISs and STAR-RISs are identified from the perspectives of hardware design, physical principles, and communication system design. Furthermore, the basic signal model of STAR-RISs is introduced, and three practical protocols are proposed for their operation, namely energy splitting, mode switching, and time switching. Based on the proposed protocols, a range of promising application scenarios are put forward for integrating STAR-RISs into next-generation wireless networks. By considering the downlink of a typical RIS-aided multiple-input single-output system, numerical case studies are provided for revealing the superiority of STAR-RISs over other baselines when employing the proposed protocols. Finally, several open research problems are discussed.
CRIS-Team WoS Importer:2022-02-04

Static Layered Schedules and Core-Only Parity Check for the 5G New Radio LDPC Codes - Frenzel, Janik; Muller-Weinfurtner, Stefan; Huber, Johannes; Müller, Ralf (SCC 2019 - 12th International ITG Conference on Systems, Communications and Coding, 2019)
We analyze static update schedules for high-speed decoding of the Low-Density Parity-Check (LDPC) codes used in 5G New Radio (NR). Motivated by the fact that updates of Check Nodes (CNs) with smaller degrees result in larger mutualinformation (MI) gains, we propose a schedule based on the ascending order of CN degrees. Furthermore, we examine the individual bit-error rates throughout the codeword and present a Core-Only Parity Check (COPC) strategy to accelerate the decoder convergence. These two simple concepts reduce the number of iterations until convergence by up to 15% compared to a Top-to-Bottom (TtB) schedule with the full parity check.
CRIS-Team Scopus Importer:2021-04-20

Statistical Analysis of Time-Variant Channels in Diffusive Mobile Molecular Communications - Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
In this paper, we consider a diffusive mobile molecular communication (MC) system consisting of a pair of mobile transmitter and receiver nano- machines suspended in a fluid medium, where we model the mobility of the nano-machines by Brownian motion. The transmitter and receiver nano-machines exchange information via diffusive signaling molecules. Due to the random movements of the transmitter and receiver nano-machines, the statistics of the channel impulse response (CIR) change over time. We introduce a statistical framework for characterization of the impulse response of time-variant MC channels. In particular, we derive closed-form analytical expressions for the mean and the autocorrelation function of the impulse response of the channel. Given the autocorrelation function, we define the coherence time of the time-variant MC channel as a metric that characterizes the variations of the impulse response. Furthermore, we derive an analytical expression for evaluation of the expected error probability of a simple detector for the considered system. In order to investigate the impact of CIR decorrelation over time, we compare the performances of a detector with perfect channel state information (CSI) knowledge and a detector with outdated CSI knowledge. The accuracy of the proposed analytical expression is verified via particle-based simulation of the Brownian motion.<br
Keywords: Receivers; Transmitters; Mobile communication; Nanobioscience; Stochastic processes; Correlation; Detectors

Statistical-CSI-Based Antenna Selection and Precoding in Uplink MIMO - Ouyang, Chongjun; Bereyhi, Ali; Asaad, Saba; Müller, Ralf; Yang, Hongwen (WSA and SCC 2023 - 26th International ITG Workshop on Smart Antennas and 13th Conference on Systems, Communications, and Coding, 2023)
Classical antenna selection schemes require instantaneous channel state information (CSI). This leads to high signaling overhead in the system. This work proposes a novel joint receive antenna selection and precoding scheme for multiuser multiple-input multiple-output uplink transmission that relies only on the long-term statistics of the CSI. The proposed scheme designs the switching network and the uplink precoders, such that the expected throughput of the system in the long term is maximized. Invoking results from the random matrix theory, we derive a closed-form expression for the expected throughput of the system. We then develop a tractable iterative algorithm to tackle the throughput maximization problem, capitalizing on the alternating optimization and majorization-maximization (MM) techniques. Numerical results substantiate the efficiency of the proposed approach and its superior performance as compared with the baseline.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Antenna selection; multiuser multiple-input multiple-output; statistical channel state information

Statistical Mechanics of MAP Estimation: General Replica Ansatz - Bereyhi, Ali; Müller, Ralf; Schulz-Baldes, Hermann (IEEE Transactions on Information Theory, 2019)
The large-system performance of maximum-a-poste-rior estimation is studied considering a general distortion function when the observation vector is received through a linear system with additive white Gaussian noise. The analysis considers the system matrix to be chosen from the large class of rotationally invariant random matrices. We take a statistical mechanical approach by introducing a spin glass corresponding to the estimator, and employing the replica method for the large-system analysis. In contrast to earlier replica based studies, our analysis evaluates the general replica ansatz of the corresponding spin glass and determines the asymptotic distortion of the estimator for any structure of the replica correlation matrix. Consequently, the replica symmetric as well as the replica symmetry breaking ansatz with b steps of breaking is deduced from the given general replica ansatz. The generality of our distortion function lets us derive a more general form of the maximum-a-posterior decoupling principle. Based on the general replica ansatz, we show that for any structure of the replica correlation matrix, the vector-valued system decouples into a bank of equivalent decoupled scalar systems followed by maximum-a-posterior estimators. The structure of the decoupled system is further studied under both the replica symmetry and the replica symmetry breaking assumptions. For b steps of symmetry breaking, the decoupled system is found to be an additive system with a non-Gaussian noise term given as the sum of an independent Gaussian random variable with b non-Gaussian impairment terms which depend on the input symbol. The general decoupling property of the maximum-a-posterior estimator leads to the idea of a replica simulator which represents the replica ansatz through the state evolution of a transition system described by its corresponding decoupled system. As an application of our study, we investigate large compressive sensing systems by considering the ℓp norm minimization recovery schemes. Our numerical investigations show that the replica symmetric ansatz for ℓ0 norm recovery fails to give an accurate approximation of the mean square error as the compression rate grows, and therefore, the replica symmetry breaking ansätze are needed in order to assess the performance precisely.
CRIS-Team Scopus Importer:2020-02-21
Keywords: compressive sensing; decoupling principle; equivalent single-user system; linear vector channel; Maximum-a-posterior estimation; replica method; replica simulator; replica symmetry breaking; statistical physics; zero norm

Statistical Modeling of Airborne Virus Transmission Through Imperfectly Fitted Face Masks - Lotter, Sebastian; Brand, Lukas; Schäfer, Maximilian; Schober, Robert (NANOCOM '21, Eight Annual ACM International Conference on Nanoscale Computing and Communication, 2021)
The rapid emergence and the disastrous impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic on public health, societies, and economies around the world has created an urgent need for understanding the pathways critical for virus transmission and counteracting the spread of SARS-CoV-2 efficiently. Airborne virus transmission by asymptomatic SARS-CoV-2-infected individuals is considered to be a major contributor to the fast spread of SARS-CoV-2 and social distancing and wearing of face masks in public have been implemented as countermeasures in many countries. Concerted research efforts in diverse scientific fields have meanwhile advanced the understanding of the physical principles of the manifold processes involved in airborne transmission of SARS-CoV-2. As part of these efforts, the physics and dynamics of aerosol filtration by various types of face masks have been studied. However, a comprehensive risk assessment framework for the airborne transmission of SARS-CoV-2 incorporating realistic assumptions on the filtration of infectious aerosols (IAs) by face masks is not available yet. In particular, in most end-to-end models for airborne virus transmission, it is neglected that the stochastic spread of IAs through imperfectly fitted face masks depends on the dynamics of the breathing of the wearer. In this paper, we consider airborne virus transmission from an infected but asymptomatic individual to a healthy individual, both wearing imperfectly fitted face masks, in an indoor environment. By framing the end-to-end virus transmission as a Molecular Communications (MC) system, we obtain a statistical description of the number of IAs inhaled by the healthy person subject to the respective configurations of the face masks of both persons. We demonstrate that the exhalation and inhalation air flow dynamics have a significant impact on the stochastic filtering of IAs by the imperfectly fitted face masks. Furthermore, we are able to show that the fit of the face mask of the infected person can highly impact the infection probability if the infectious dose for virus transmission to the healthy person is in a critical range. We conclude that the proposed MC model may contribute a valuable assessment tool to fight the spread of SARS-CoV-2 as it naturally encompasses the randomness of the transmission process and thus enables comprehensive risk analysis beyond statistical averages.

Statistical Modeling of FSO Fronthaul Channel for Drone-Based Networks - Najafi Kalyani, Marzieh; Ajam, Hedieh; Jamali Kooshkghazi, Vahid; Diamantoulakis, Panagiotis D.; Karagiannidis, George K.; Schober, Robert (2018 IEEE International Conference on Communications (ICC), 2018)
We consider a drone-based communication network, where several drones hover above an area and serve as mobile remote radio heads for a large number of mobile users. We assume that the drones employ free space optical (FSO) links for fronthauling of the users' data to a central unit. The main focus of this paper is to quantify the geometric loss of the FSO channel arising from random fluctuation of the position and orientation of the drones. In particular, we derive upper and lower bounds, corresponding approximate expressions, and a closed-form statistical model for the geometric loss. Simulation results validate our derivations and quantify the FSO channel quality as a function of the drone's instability, i.e., the variation of its position and orientation.<br
Keywords: Laser beams; Drones; Optical beams; Optical losses; Laser modes; Buildings; Atmospheric modeling

Statistical Modeling of the FSO Fronthaul Channel for UAV-Based Communications - Najafi, Marzieh; Ajam, Hedieh; Jamali, Vahid; DIamantoulakis, Panagiotis D.; Karagiannidis, George K.; Schober, Robert (IEEE Transactions on Communications, 2020)
In this paper, we investigate the statistics of the free space optics (FSO) communication channel between a hovering unmanned aerial vehicle (UAV) and a central unit. Two unique characteristics make UAV-based FSO systems significantly different from conventional FSO systems with static transceivers. First, for UAV-based FSO systems, the incident laser beam is not always orthogonal to the receiver lens plane. Second, both position and orientation of the UAV fluctuate over time due to dynamic wind load, inherent random air fluctuations in the atmosphere around the UAV, and internal vibrations of the UAV. On the contrary, for conventional FSO systems, the laser beam is always perpendicular to the receiver lens plane and the relative movement of the transceivers is limited. In this paper, we develop a novel channel model for UAV-based FSO systems by quantifying the corresponding geometric and misalignment losses (GML), while taking into account the non-orthogonality of the laser beam and the random fluctuations of the position and orientation of the UAV. In particular, for diverse weather conditions, we propose different fluctuation models for the position and orientation of the UAV and derive corresponding statistical models for the GML. We further analyze the performance of a UAV-based FSO link in terms of outage probability and ergodic rate and simplify the resulting analytical expressions for the high signal-to-noise ratio (SNR) regime. Finally, simulations validate the accuracy of the presented analysis and provide important insights for system design. For instance, we show that for a given variance of the fluctuations, the beam width should be properly adjusted to minimize the outage probability.
CRIS-Team Scopus Importer:2020-07-03
Keywords: channel modeling; free space optics (FSO) backhauling; geometric loss; pointing error; random UAV fluctuations; Unmanned aerial vehicle (UAV) communications

Statistical power allocation for downlink two-user power-domain MIMO-NOMA with excess degrees of freedom - Krishnamoorthy, Aravindh; Schober, Robert (WSA 2020 - 24th International ITG Workshop on Smart Antennas, 2020)
In this paper, we investigate statistical power allocation (SPA) for downlink two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) to enhance the ergodic rate performance. We utilize a modified generalized singular value decomposition (M-GSVD) based precoding scheme which simultaneously diagonalizes the MIMO-NOMA channels of the users into multiple single-input single-output (SISO) NOMA channels, thereby reducing the decoding complexity. The M-GSVD precoding scheme is also able to exploit excess degrees of freedom at the base station to improve MIMO-NOMA performance. Based on finite-size random matrix theory, we derive novel expressions for the ergodic achievable rate of MIMO-NOMA with M-GSVD precoding and non-equal power allocation, which are then used for SPA and for obtaining the ergodic achievable rate region. The derived expressions are validated with Monte-Carlo simulations. Our results show that the proposed scheme outperforms M-GSVD precoding with equal power allocation and orthogonal multiple access, thereby demonstrating the benefits of SPA.
CRIS-Team Scopus Importer:2020-12-04

Statistics and chip pulse design for efficient multiuser detection in asynchronous CDMA - Cottatellucci, Laura; Debbah, Merouane; Müller, Ralf (2007 IEEE Wireless Communications and Networking Conference, WCNC 2007, 2007)
The design and analysis of multistage detectors with universal weights for asynchronous CDMA systems is presented. The use of a front-end that enables joint detection and provides sufficient statistics is proposed. With such a front end the proposed multistage detector has the same complexity order per bit as the matched filter. The proposed approach can also take into account other suboptimum statistics and the non-ideality of the chip pulse waveforms. In such a way, the universal weights can be designed and the performance can be computed for very realistic scenarios. © 2007 IEE

Stepwise Transmit Antenna Selection in Downlink Massive Multiuser MIMO - Bereyhi, Ali; Asaad, Saba; Müller, Ralf (22nd International ITG Workshop on Smart Antennas (WSA), 2018)
Due to the large power consumption in RF-circuitry of massive MIMO systems, practically relevant performance measures such as energy efficiency or bandwidth efficiency are neither necessarily monotonous functions of the total transmit power nor the number of active antennas. Optimal antenna selection is however computationally infeasible in these systems. In this paper, we propose an iterative algorithm to optimize the transmit power and the subset of selected antennas subject to non-monotonous performance measures in massive multiuser MIMO settings. Numerical results are given for energy efficiency and demonstrate that for several settings the optimal number of selected antennas reported by the proposed algorithm is significantly smaller than the total number of transmit antennas. This fact indicates that antenna selection in several massive MIMO scenarios not only reduces the hardware complexity and RF-costs, but also enhances the energy efficiency of the syste

Stochastic Channel Modeling for Diffusive Mobile Molecular Communication Systems - Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Communications, 2018)
In this paper, we consider mobile molecular communication (MC) systems which are expected to find application in several fields including targeted drug delivery and health monitoring. We develop a mathematical framework for modeling the time-variant stochastic channels of diffusive mobile MC systems. In particular, we consider a diffusive mobile MC system consisting of a pair of transmitter and receiver nano-machines suspended in a fluid medium with a uniform bulk flow, where we assume that either the transmitter or the receiver or both are mobile, and we model the mobility by Brownian motion. The transmitter and receiver nano-machines exchange information via diffusive signaling molecules. Due to the random movements of the transmitter and receiver nano-machines, the statistics of the channel impulse response (CIR) change over time. We derive closed-form expressions for the mean, the autocorrelation function (ACF), the cumulative distribution function (CDF), and the probability density function (PDF) of the time-variant CIR. Exploiting the ACF, we define the coherence time of the time-variant MC channel as a metric for characterization of the variations of the CIR. The derived CDF is employed for calculation of the outage probability of the system. We also show that under certain conditions, the PDF of the CIR can be accurately approximated by a Log-normal distribution. Based on this approximation, we derive a simple model for outdated channel state information (CSI). Moreover, we derive an analytical expression for the evaluation of the expected error probability of a simple detector for the considered MC system. In order to investigate the impact of CIR decorrelation over time, we compare the performances of a detector with perfect CSI knowledge and a detector with outdated CSI knowledge. The accuracy of the proposed analytical expressions is verified via particle-based simulation of the Brownian motion.<br
Keywords: Receivers; Transmitters; Stochastic processes; Nanobioscience; Probability density function; Mathematical model; Closed-form solutions

Stochastic Chemical Reaction Networks for MAP Detection in Cellular Receivers - Heinlein, Bastian; Brand, Lukas; Egan, Malcolm; Schäfer, Maximilian; Schober, Robert; Lotter, Sebastian (NanoCom 2023 - Proceedings of the 10th ACM International Conference on Nanoscale Computing and Communication, 2023)
In order to fully exploit the potential of molecular communication (MC) for intra-body communication, practically implementable cellular receivers are an important long-term goal. A variety of receiver architectures based on chemical reaction networks (CRNs) and gene-regulatory networks (GRNs) has been introduced in the literature, because cells use these concepts to perform computations in nature. However, practical feasibility is still limited by stochastic fluctuations of chemical reactions and long computation times in GRNs. Therefore, in this paper, we propose two receiver designs based on stochastic CRNs, i.e., CRNs that perform computations by exploiting the intrinsic fluctuations of chemical reactions with very low molecule counts. The first CRN builds on a recent result from chemistry that showed how Boltzmann machines (BMs), a commonly used machine learning model, can be implemented with CRNs. We show that BMs with optimal parameter values and their CRN implementations can act as maximum-a-posteriori (MAP) detectors. Furthermore, we show that BMs can be efficiently trained from simulation data to achieve close-to-MAP performance. While this approach yields a fixed CRN once deployed, our second approach based on a manually designed CRN can be trained with pilot symbols even within the cell and thus adapt to changing channel conditions. We extend the literature by showing that practical robust detectors can achieve close-to-MAP performance even without explicit channel knowledge.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Boltzmann machine; chemical reaction network; machine learning; maximum-a-posteriori detection; Molecular communication

Storage Constrained Linear Computation Coding - Karataev, Alexander; Rosenberger, Hans; Bereyhi, Ali; Müller, Ralf (Data Compression Conference Proceedings, 2023)
Linear computation coding (LCC) has been developed in [1] as a new framework for the computation of linear functions. LCC significantly reduces the complexity of matrix-vector multiplication [1]. In basic LCC, storage is not restricted i.e. the wiring exponents are arbitrary integer exponents of 2.
CRIS-Team Scopus Importer:2023-06-09
Keywords: approximate computing; computational complexity; fixed point arithmetic; function compression; linear systems; quantization

Subspace projection and noncoherent equalization in multi-user massive MIMO systems - Fischer, Robert; Stierstorfer, Clemens; Müller, Ralf (10th Int’l ITG Conf. Syst., Commun. & Coding, 2015)

Successive Null-Space Precoder Design for Downlink MU-MIMO with Rate Splitting and Single-Stage SIC - Krishnamoorthy, Aravindh; Schober, Robert (2021 IEEE International Conference on Communications Workshops, ICC Workshops 2021 - Proceedings, 2021)
In this paper, we consider the precoder design for an under-loaded or critically loaded downlink multi-user multiple-input multiple-output (MU-MIMO) communication system. We propose novel precoding and decoding schemes which enhance system performance based on rate splitting at the transmitter and single-stage successive interference cancellation at the receivers. The proposed successive null-space (SNS) precoding scheme utilizes linear combinations of the null-space basis vectors of the successively augmented MIMO channel matrices of the users as precoding vectors to adjust the inter-user-interference experienced by the receivers. We formulate a non-convex weighted sum rate (WSR) optimization problem, and solve it via successive convex approximation to obtain a suboptimal solution for the precoding vectors and the associated power allocation. Our simulation results reveal that the proposed SNS precoders outperform block diagonalization based linear and rate splitting designs, and in many cases, have a relatively small gap to the maximum sum rate achieved by dirty paper coding.
CRIS-Team Scopus Importer:2021-08-27

SUDAS: mmWave relaying for 5G outdoor-to-indoor communications - Breiling, Marco; Ng, Derrick Wing Kwan; Rohde, Christian; Burkhardt, Frank; Schober, Robert (Advanced Relay Technologies in Next Generation Wireless Communications, 2016)
In this chapter, we have proposed a novel SUDAS with the objective of achieving the 10 Gbit/s data rate goal set by 5G for indoor UEs. The proposed SUDAS exploits the benefits of the licensed and unlicensed frequency bands simultaneously. In particular, it translates the spatial multiplexing in the licensed bands into frequency multiplexing in the unlicensed bands for boosting the end-to-end data rate via VMIMO. It is expected that the proposed SUDAS can further enhance the system performance when advanced resource allocation technique is employed. Besides, we have also discussed some potential application scenarios where deployment of SUDAS appears to be beneficial. Also, we have investigated different potential realizations of SUDAS and the corresponding implementation challenges. It is expected that the proposed SUDAS is able to bridge the gap between the current technology and the high data rate requirement of the next generation communication systems.
CRIS-Team Scopus Importer:2020-01-31
Keywords: 5G mobile communication; 5G outdoor-to-indoor communications; Advanced resource allocation technique; Data communication; Data rate; End-to-end data rate; Frequency multiplexing; Indoor UE; MIMO communication; Mmwave relaying; Next generation communication systems; Next generation networks; Resource allocation; Space division multiplexing; Spatial multiplexing; SUDAS; VMIMO

Sum Rate Analysis of the Downlink of a Massive MIMO System with Linear Precoders and Advance User Terminals - Ackermann, Katharina (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Sweet Streams are Made of This: The System Engineer’s View on Energy Efficiency in Video Communications (Preprint) - Herglotz, Christian; Kränzler, Matthias; Schober, Robert; Kaup, André (Ieee Circuits and Systems Magazine, 2023)

SW-Implementation of Selected MIMO Receiver Algorithms on Intel Xeon Server - Ega, Vandith (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)

Switchable Signaling Molecules for Media Modulation: Fundamentals, Applications, and Research Directions - Brand, Lukas; Scherer, Maike; Lotter, Sebastian; tom Dieck, Teena; Schaufer, Maximilian; Burkovski, Andreas; Sticht, Heinrich; Castiglione, Kathrin; Schober, Robert (IEEE Communications Magazine, 2023)
Although visionary applications of molecular communication (MC), such as long-term continuous health monitoring by cooperative in-body nanomachines, have been proposed, MC is still in its infancy when it comes to practical implementation. In particular, long-term experiments and applications face issues such as depletion of signaling molecules (SMs) at the transmitter (TX) and inter-symbol interference (ISI) at the receiver (RX). To overcome these practical challenges, a new class of SMs with switchable states seems to be promising for future MC applications. In this work, we provide an overview of existing switchable SMs, and classify them according to their properties. Furthermore, we highlight how switchable SMs can be utilized as information carriers for media modulation. In addition, we present theoretical and experimental results for an end-toend MC system employing the green fluorescent protein variant "Dreiklang" (GFPD) as switchable SM. Our experimental results show, for the first time, successful information transmission in a closed-loop pipe system using media modulation. Finally, we discuss media modulation specific challenges and opportunities.
Created from Fastlane, Scopus look-up
Keywords: Information processing; Media; Modulation; Monitoring; Optical switches; Optical transmitters; Proteins

Symbol-by-Symbol and Trellis-Based Equalization with Widely Linear Processing for Space-Time Block-Coded Transmission over Frequency-Selective Fading Channels - Gerstacker, Wolfgang; Obernosterer, Frank; Schober, Robert; Lehmann, Alexander; Lampe, Alexander; Gunreben, Peter (Conference Proceedings, 2002)
In this paper, we develop receiver concepts for transmission with space-time block codes (STBC's) over frequency-selective fading channels. The focus lies on Alamouti's STBC, but the results may be generalized to related STBC's. We show that a straightforward combination of conventional equalizers and a space-time block decoder is only possible if at least as many receive antennas as transmit antennas are employed, but not for the practically interesting case of pure transmit diversity. This restriction is circumvented by our approach. Equalizers with widely linear (WL) processing are designed, utilizing the structural properties of the transmit signal of space-time block coding, which is shown to be improper (rotationally variant). These schemes are especially suited for equalization of high-level modulated signals, which are used in third-generation time-division multiple access mobile communications standards such as EDGE (Enhanced Data Rates for GSM Evolution).
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.mobilk.symbol
Keywords: Frequency-selective fading channels; Block codes; Equalizers; Receiving antennas; Decoding; Transmitting antennas; Process design; Signal design; Signal processing; Mobile communication

Symbol Level Precoding in the RF Domain for Low Hardware Complexity RIS-Assisted MU-MISO Systems - Tsinos, Christos G.; Tsiftsis, Theodoros A.; Schober, Robert (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2023)
In this paper, a radio-frequency (RF) domain symbol level precoding technique is developed for reconfigurable intelligent surface (RIS)-assisted downlink multiuser multiple-input single-output (MU-MISO) systems. We study a system with a base station (BS) employing an analog architecture formed by a phase shifting network which serves a number of single antenna users with the help of a RIS. Such an architecture facilitates significant reductions in power consumption and hardware complexity. The objective of this paper is to jointly derive the optimal RF precoder, RIS reflection matrix and receive processing coefficients, subject to constraints on the BS analog architecture, the total transmit power, and the structure of the RIS reflection matrix. To that end, a difficult nonconvex optimization problem is formulated and solved. An efficient algorithmic solution is developed for the considered problem. Numerical results show that the derived solution offers significant energy efficiency gains when compared to non-RIS-assisted approaches.
CRIS-Team Scopus Importer:2023-12-01

Symbol Synchronization for Diffusion-Based Molecular Communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert (IEEE Transactions on Nanobioscience, 2018)
Symbol synchronization refers to the estimation of the start of a symbol interval and is needed for reliable detection. In this paper, we develop several symbol synchronization schemes for molecular communication (MC) systems where we consider some practical challenges, which have not been addressed in the literature yet. In particular, we take into account that in MC systems, the transmitter may not be equipped with an internal clock and may not be able to emit molecules with a fixed release frequency. Such restrictions hold for practical nanotransmitters, e.g., modified cells, where the lengths of the symbol intervals may vary due to the inherent randomness in the availability of food and energy for molecule generation, the process for molecule production, and the release process. To address this issue, we develop two synchronization-detection frameworks which both employ two types of molecule. In the first framework, one type of molecule is used for symbol synchronization and the other one is used for data detection, whereas in the second framework, both types of molecule are used for joint symbol synchronization and data detection. For both frameworks, we first derive the optimal maximum likelihood (ML) symbol synchronization schemes as performance upper bounds. Since ML synchronization entails high complexity, for each framework, we also propose three low-complexity suboptimal schemes, namely a linear filter-based scheme, a peak observation-based scheme, and a threshold-trigger scheme, which are suitable for MC systems with limited computational capabilities. Furthermore, we study the relative complexity and the constraints associated with the proposed schemes and the impact of the insertion and deletion errors that arise due to imperfect synchronization. Our simulation results reveal the effectiveness of the proposed synchronization schemes and suggest that the end-to-end performance of MC systems significantly depends on the accuracy of the symbol synchronization.<br
Keywords: Synchronization; Computational complexity; Molecular communication

Symbol synchronization for diffusive molecular communication systems - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert (2017 IEEE International Conference on Communications (ICC), 2017)
Symbol synchronization refers to the estimation of the start of a symbol interval and is needed for reliable detection. In this paper, we develop a symbol synchronization framework for molecular communication (MC) systems where we consider some practical challenges which have not been addressed in the literature yet. In particular, we take into account that in MC systems, the transmitter may not be equipped with an internal clock and may not be able to emit molecules with a fixed release frequency. Such restrictions hold for practical nanotransmitters, e.g. modified cells, where the lengths of the symbol intervals may vary due to the inherent randomness in the availability of food and energy for molecule generation, the process for molecule production, and the release process. To address this issue, we propose to employ two types of molecules, one for synchronization and one for data transmission. We derive the optimal maximum likelihood (ML) symbol synchronization scheme as a performance upper bound. Since ML synchronization entails high complexity, we also propose two low-complexity synchronization schemes, namely a peak observation-based scheme and a threshold-trigger scheme, which are suitable for MC systems with limited computational capabilities. Our simulation results reveal the effectiveness of the proposed synchronization schemes and suggest that the end-to-end performance of MC systems significantly depends on the accuracy of symbol synchronization.<br
Keywords: Synchronization; Receivers; Optical transmitters; Clocks; Molecular communication

Synaptic Channel Modeling for DMC: Neurotransmitter Uptake and Spillover in the Tripartite Synapse - Lotter, Sebastian; Ahmadzadeh, Arman; Schober, Robert (IEEE Transactions on Communications, 2020)
In Diffusive Molecular Communication (DMC), information is transmitted by diffusing molecules. Synaptic signaling, as a natural implementation of this paradigm, encompasses functional components that, once understood, can facilitate the development of synthetic DMC systems. To unleash this potential, however, a thorough understanding of the synaptic communication channel based on biophysical principles is needed. Since synaptic transmission critically depends also on non-neural cells, such understanding requires the consideration of the so-called tripartite synapse. In this paper, we develop a comprehensive channel model of the tripartite synapse encompassing a three-dimensional, finite-size spatial model of the synaptic cleft, molecule uptake at the presynaptic neuron and at glial cells, reversible binding to individual receptors at the postsynaptic neuron, and spillover to the extrasynaptic space. Based on this model, we derive analytical time domain expressions for the channel impulse response (CIR) of the synaptic DMC system and for the number of molecules taken up at the presynaptic neuron and at glial cells, respectively. These expressions provide insight into the impact of macroscopic physical channel parameters on the decay rate of the CIR and the reuptake rate, and reveal fundamental limits for synaptic signal transmission induced by chemical reaction kinetics and the channel geometry. Adapted to realistic parameters, our model produces plausible results when compared to previous experimental and simulation studies and we provide results from particle-based computer simulations to further validate the analytical model. The proposed comprehensive channel model admits a wide range of synaptic configurations making it suitable for the investigation of many practically relevant questions, such as the impact of glial cell uptake and spillover on signal transmission in the tripartite synapse.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Analytical models; Glial cells; Mathematical model; Monte Carlo methods; Neurons; Solid modeling; Synapses

Target-Mounted Intelligent Reflecting Surface for Secure Wireless Sensing - Shao, Xiaodan; Zhang, Rui (IEEE Transactions on Wireless Communications, 2024)
In this paper, we consider a challenging secure wireless sensing scenario where a legitimate radar station (LRS) intends to detect a target at unknown location in the presence of an unauthorized radar station (URS). We aim to enhance the sensing performance of the LRS and in the meanwhile prevent the detection of the same target by the URS. Under this setup, conventional stealth-based approaches such as wrapping the target with electromagnetic wave absorbing materials are not applicable, since they will disable the target detection by not only the URS, but the LRS as well. To tackle this challenge, we propose in this paper a new target-mounted IRS approach, where intelligent reflecting surface (IRS) is mounted on the outer/echo surface of the target and by tuning the IRS reflection, the strength of its reflected radar signal in any angle of departure (AoD) can be adjusted based on the signal’s angle of arrival (AoA), thereby enhancing/suppressing the signal power towards the LRS/URS, respectively. To this end, we propose a practical protocol for the target-mounted IRS to estimate the LRS/URS channel and waveform parameters based on its sensed signals and control the IRS reflection for/against the LRS/URS accordingly. Specifically, we formulate new optimization problems to design the reflecting phase shifts at IRS for maximizing the received signal power at the LRS while keeping that at the URS below a certain level, for both the cases of short-term and long-term IRS operations with different dynamic reflection capabilities. To solve these non-convex problems, we apply the penalty dual decomposition method to obtain high-quality suboptimal solutions for them efficiently. Finally, simulation results are presented that verify the effectiveness of the proposed protocol and algorithms for the target-mounted IRS to achieve secure wireless sensing, as compared with various benchmark schemes.
CRIS-Team Scopus Importer:2024-03-08
Keywords: passive beamforming; sensing security; Target-mounted IRS; wireless sensing

The Era of Wireless Information and Power Transfer - Ng, Derrick Wing Kwan; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Wireless power transfer (WPT) offers a viable solution for facilitating efficient and sustainable communication networks serving energy‐limited communication devices. WPT technology enables simultaneous wireless information and power transfer (WIPT). The existing WPT technologies can be categorized into three classes: inductive coupling, magnetic resonant coupling, and RF‐based WPT. RF‐based energy harvesting technology enables the possibility of simultaneous WIPT (SWIPT), wireless‐powered communication (WPC), and wireless‐powered backscatter communication (WPBC).This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book addresses the challenges incurred by the nature of WPT and provides a comprehensive reference for various solutions for realizing efficient WIPT in practice. It also provides some background information on WPT and discusses exciting research directions. The book helps to study the fundamental problems in WIPT networks, including communication security in WIPT systems, energy transfer efficiency, and interference management in WIPT systems.<br
Keywords: Wireless communication; Wireless sensor networks; Energy harvesting; Communication Networks; Receivers; Radio frequency; RF signals

The First Cell Phone in Molecular Communications: A Pilot Model of a Biological Transmitter - Grebenstein, Laura; Kirchner, Jens; Stavracakis Peixoto, Renata; Fischer, Georg; Weigel, Robert; Schober, Robert; Burkovski, Andreas (3rd Workshop on Molecular Comunications, 2018)
In the past years, Molecular Communications were studied mainly from a communication engineering and theoretical point of view. To design nano- to micro-sized signaling networks, reliable communication-theoretical models and experimental testbeds are still missing. Inspired by microbial cells we established an organic, molecular signal converter as a modulator for MC signals. The transmitter is a bacterial cell expressing the light-driven proton pump gloeorhodopsin. In recent test runs, we were able to send short messages encoded in a light signal and converted to pH variation with a rate of 2 bits/min with the help of living bacteria.<br

The impact of relay selection on the tradeoff between information transmission and wireless energy transfer - Michalopoulos, Diomidis; Suraweera, Himal A.; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
In certain applications, relay terminals can be employed to simultaneously deliver information and energy to a designated receiver and a radio frequency (RF) energy harvester, respectively. In such scenarios, the relay that is preferable for information transmission does not necessarily coincide with the relay with the strongest channel to the energy harvester, since the corresponding channels fade independently. Relay selection thus entails a tradeoff between the efficiency of the information transfer to the receiver and the amount of energy transferred to the energy harvester. The study of this tradeoff is the subject on which this work mainly focuses. We propose a relay selection policy that optimizes the quality of information transmission for a given energy transfer constraint. Additionally, we propose two suboptimal relay selection methods that apply to scenarios with limited availability of channel state information and facilitate closed-form analytical results. We conduct a performance analysis that sheds some light on the tradeoff between ergodic capacity and wireless energy transfer, and we prove that the optimal relay selection policy optimizes also other performance metrics for a given energy transfer, such as the outage probability and the error probability.<br
Keywords: Relays; Energy exchange; Information processing; Wireless communication; Signal to noise ratio; Radio frequency; Pareto optimization

The impact of transceiver distortions on the spectral properties of random CDMA with constant envelope - Lampe, Alexander; Müller, Ralf (9th International Multi-Conference on Systems, Signals and Devices, SSD 2012, 2012)
This paper studies the robustness of spreading sequences designed for random code-division multiple-access (CDMA) schemes with continuous-time constant envelope (CE) against transmitter impairments. It is shown that by taking into account the impairments of a real implementation the investigated design algorithm finds a set of spreading waveforms with exactly constant envelope which would even satisfy the transmit signal spectrum requirements of the 3rd generation Universal Mobile Telecommunications System (UMTS) standard. This shows that CE CDMA is compatible with linear CDMA while achieving higher power efficiency and supporting the usage of standard linear multiuser detection algorithms. © 2012 IEEE.

The Internet of Bio-Nano Things in Blood Vessels: System Design and Prototypes - Lee, Changmin; Koo, Bon Hong; Chae, Chan Byoung; Schober, Robert (Journal of Communications and Networks, 2023)
In this paper, we investigate the Internet of bionano things (IoBNT) which pertains to networks formed by molecular communications. By providing a means of communication through the ubiquitously connected blood vessels (arteries, veins, and capillaries), molecular communication-based IoBNT enables a host of new eHealth applications. For example, an organ monitoring sensor can transfer internal body signals through the IoBNT to health-monitoring applications. We empirically show that blood vessel channels introduce a new set of challenges in the design of molecular communication systems in comparison to free-space channels. Then, we propose cylindrical duct channel models and discuss the corresponding system designs conforming to the channel characteristics. Furthermore, based on prototype implementations, we confirm that molecular communication techniques can be utilized for composing the IoBNT. We believe that the promising results presented in this work, together with the rich research challenges that lie ahead, are strong indicators that IoBNT with molecular communications can drive novel applications for emerging eHealth systems.
CRIS-Team Scopus Importer:2023-06-30
Keywords: health monitoring; Internet of bionano things (IoBNT); molecular communications; prototypes; Terms-Blood vessel

Theoretical Bounds on MAP Estimation in Distributed Sensing Networks - Bereyhi, Ali; Haghoghatshoar, Saeid; Müller, Ralf (IEEE, 2018)
The typical approach for recovery of spatially correlated signals is regularized least squares with a coupled regularization term. In the Bayesian framework, this algorithm is seen as a maximum-a-posterior estimator whose postulated prior is proportional to the regularization term. In this paper, we study distributed sensing networks in which a set of spatially correlated signals are measured individually at separate terminals, but recovered jointly via a generic maximum-a-posterior estimator. Using the replica method, it is shown that the setting exhibits the decoupling property. For the case with jointly sparse signals, we invoke Bayesian inference and propose the "multi-dimensional soft thresholding" algorithm which is posed as a linear programming. Our investigations depict that the proposed algorithm outperforms the conventional ℓ2,1-norm regularized least squares scheme while enjoying a feasible computational complexity.
Keywords: Distributed compressive sensing; Maximum-a-posterior estimation; Decoupling property; Replica method

The Zeros of Random Polynomials: Further Results and Applications - Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2002)
In this letter, we consider the density of the zeros of random polynomials with nonzero mean correlated Gaussian coefficients. We show that for most communication problems the original result by Hammersley can be expressed in a simpler form. In order to illustrate the usefulness of the presented theory, two applications are considered. First, the zeros of frequency-selective Ricean fading channels are investigated. Second, the zeros of the transfer function corresponding to channel impulse response estimates obtained by a least-squares approach are calculated. For both applications implications for equalizer design are discussed.
UnivIS-Import:2015-03-09:Pub.2002.tech.IE.mobilk.thezer
Keywords: Channel estimation; Equalization; Random polynomials; Wireless channels

Three-Dimensional Placement and Transmit Power Design for UAV Covert Communications - Zhou, Xiaobo; Yan, Shihao; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Vehicular Technology, 2021)
This work tackles the joint optimization of a unmanned aerial vehicle's (UAV's) three-dimensional (3D) placement and transmit power for covert communications with the objective to maximize the communication covertness subject to a constraint on communication quality. We analytically prove that the optimal horizontal location of the UAV must be on the straight line connecting the legitimate receiver and the warden, while its optimal height is the minimum allowable flying altitude. Subsequently, we derive closed-form expressions to characterize the UAV's optimal 3D location and its optimal transmit power, taking into account the impact of finite blocklength coding. Our numerical results show that the developed optimal design can achieve a better covertness performance compared with an optimal two-dimensional (2D) UAV deployment, especially when the warden is close to the receiver. Besides, we show that, for a given requirement on the communication quality, communication covertness does not always improve as the number of channel uses increases.
CRIS-Team Scopus Importer:2021-11-12
Keywords: 3D UAV deployment; Covert communications; Error probability; finite blocklength; Receivers; Security; Signal to noise ratio; Three-dimensional displays; Throughput; transmit power design; Unmanned aerial vehicles

Throughput-Efficient Scheduling and Interference Alignment for MIMO Wireless Systems - Ronasi, Keivan; Niu, Binglai; Wong, Vincent W.S.; Gopalakrishnan, Sathish; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
Multiple-input multiple-output (MIMO) wireless communication systems can achieve higher throughput through interference alignment. For a small number of users, determining the maximum possible degrees of freedom as well as the feasibility of interference alignment in MIMO systems is well studied. However, the issues of scheduling in systems employing interference alignment and serving a large number of users have received little attention so far. In this paper, we study the problem of joint scheduling, interference alignment, and packet admission control in MIMO wireless systems with the goal of maximizing system throughput subject to stability constraints. We formulate a stochastic network optimization problem and propose a scheduling and interference alignment (SIA) algorithm. In each time slot, SIA schedules some users among many competing ones to transmit data, and determines encoding and decoding matrices for the selected users. Packet admission control is performed in each time slot. In addition, we propose a heuristic semi-distributed algorithm (SDSIA), which has a lower computational complexity than the SIA algorithm. Via simulation, we evaluate the performance of SIA and SDSIA for different algorithm parameters and different numbers of users. We also compare the performance of SDSIA with other approaches which do not simultaneously exploit interference alignment and scheduling and find that the combination of these two techniques increases the achievable data rate dramatically.<br
Keywords: Interference; Receivers; Throughput; Transmitters; Scheduling; MIMO; Vectors

Throughput of the Magnetic Induction based Wireless Underground Sensor Networks: Key Optimization Techniques - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2014)

Throughput Optimization for Grant-Free Multiple Access with Multiagent Deep Reinforcement Learning - Huang, Rui; Wong, Vincent W.S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
Grant-free multiple access (GFMA) is a promising paradigm to efficiently support uplink access of Internet of Things (IoT) devices. In this paper, we propose a deep reinforcement learning (DRL)-based pilot sequence selection scheme for GFMA systems to mitigate potential pilot sequence collisions. We formulate a pilot sequence selection problem for aggregate throughput maximization in GFMA systems with specific throughput constraints as a Markov decision process (MDP). By exploiting multiagent DRL, we train deep neural networks (DNNs) to learn near-optimal pilot sequence selection policies from the transition history of the underlying MDP without requiring information exchange between the users. While the training process takes advantage of global information, we leverage the technique of factorization to ensure that the policies learned by the DNNs can be executed in a distributed manner. Simulation results show that the proposed scheme can achieve an average aggregate throughput that is within 85% of the optimum, and is 31%, 128%, and 162% higher than that of acknowledgement-based GFMA, dynamic access class barring, and random selection GFMA, respectively. Our results also demonstrate the capability of the proposed scheme to support IoT devices with specific throughput requirements.
CRIS-Team Scopus Importer:2021-01-29
Keywords: deep reinforcement learning (DRL); Grant-free multiple access (GFMA); Internet of Things (IoT); medium access control (MAC) protocols

Throughput Optimization in Grant-Free NOMA with Deep Reinforcement Learning - Huang, Rui; Wong, Vincent W. S.; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Time of Arrival Error Estimation for Positioning Using Convolutional Neural Networks - Kirmaz, Anil; Şahin, Taylan; Michalopoulos, Diomidis S.; Ashraf, Muhammad Ikram; Gerstacker, Wolfgang (IEEE Wireless Communications and Networking Conference, WCNC, 2023)
Wireless high-accuracy positioning has recently attracted growing research interest due to diversified nature of applications such as industrial asset tracking, autonomous driving, process automation, and many more. However, obtaining a highly accurate location information is hampered by challenges due to the radio environment. A major source of error for time-based positioning methods is inaccurate time-of-arrival (ToA) or range estimation. Machine leaning (ML) techniques emerged as potential solutions to mitigate ToA-related errors. However, existing ML-based solutions either employ a set of features representing channel measurements only to a limited extent, or account for only device-specific proprietary methods of ToA estimation. In this paper, we propose a convolutional neural network (CNN) to estimate and mitigate the errors of a variety of ToA estimation methods utilizing channel impulse responses (CIRs). Based on real-world measurements from two independent campaigns, the proposed method yields significant improvements in ranging accuracy (up to 37%) of conventional ToA estimators, often eliminating the need of optimizing the underlying conventional methods.
CRIS-Team Scopus Importer:2023-06-02
Keywords: convolutional neural networks; high accuracy positioning; Time-of-arrival estimation

ToA and TDoA Estimation Using Artificial Neural Networks for High-Accuracy Ranging - Kirmaz, Anil; Sahin, Taylan; Michalopoulos, Diomidis S.; Gerstacker, Wolfgang (IEEE Journal on Selected Areas in Communications, 2023)
High-accuracy positioning enables various applications such as industrial asset tracking, autonomous driving and process automation. Accurate location information relies on accurate time-of-arrival (ToA) or time-difference-of-arrival (TDoA) estimation in widely utilized time-based ranging. In this paper, we propose artificial neural network (ANN) based methods either to estimate T(D)oA directly or to mitigate the error of the conventional estimators. Based on real-world channel measurements, we show that the proposed direct ANN estimator outperforms the conventional estimators at least by approximately 37% and 24% in the 90th percentile ranging error, derived from ToA and TDoA estimations, respectively. Additionally, the proposed T(D)oA error-mitigating ANNs outperform the benchmark error mitigation methods with a gain varying between 17-43% in the 90th percentile ranging error, depending on the underlying conventional estimator. The ranging accuracy delivered by the direct estimation and error mitigation methods using ANNs are similar. Furthermore, the ANN estimators yield a more robust performance than the conventional estimators when the carrier frequency of the positioning signal is varied. ANN-based ToA estimation yields a marginally better ranging accuracy than ANN-based TDoA estimation. This advantage comes at the expense of a larger communication latency, while avoiding the need for synchronization among the positioning anchors.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Artificial neural networks; Artificial neural networks; Distance measurement; Estimation; Fingerprint recognition; indoor positioning systems; Measurement uncertainty; Position measurement; ranging; Receivers; time difference of arrival; time of arrival estimation

Toward Interdisciplinary Synergies in Molecular Communications: Perspectives from Synthetic Biology, Nanotechnology, Communications Engineering and Philosophy of Science - Egan, Malcolm; Kuscu, Murat; Barros, Michael Taynnan; Booth, Michael; Llopis-Lorente, Antoni; Magarini, Maurizio; Martins, Daniel; Schäfer, Maximilian; Stano, Pasquale (Life, 2023)

Towards Power-Efficient Aerial Communications via Dynamic Multi-UAV Cooperation - Xiang, Lin; Lei, Lei; Chatzinotas, Symeon; Ottersten, Bjorn; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2020)
Aerial base stations (BSs) attached to unmanned aerial vehicles (UAVs) constitute a new paradigm for next-generation cellular communications. However, the flight range and communication capacity of aerial BSs are usually limited due to the UAVs' size, weight, and power (SWAP) constraints. To address this challenge, in this paper, we consider dynamic cooperative transmission among multiple aerial BSs for power-efficient aerial communications. Thereby, a central controller intelligently selects the aerial BSs navigating in the air for cooperation. Consequently, the large virtual array of moving antennas formed by the cooperating aerial BSs can be exploited for low-power information transmission and navigation, taking into account the channel conditions, energy availability, and user demands. Considering both the fronthauling and the data transmission links, we jointly optimize the trajectories, cooperation decisions, and transmit beamformers of the aerial BSs for minimization of the weighted sum of the power consumptions required by all BSs. Since obtaining the global optimal solution of the formulated problem is difficult, we propose a low-complexity iterative algorithm that can efficiently find a Karush-Kuhn-Tucker (KKT) solution to the problem. Simulation results show that, compared with several baseline schemes, dynamic multi-UAV cooperation can significantly reduce the communication and navigation powers of the UAVs to overcome the SWAP limitations, while requiring only a small increase of the transmit power over the fronthauling links.
CRIS-Team Scopus Importer:2020-07-10

Trajectory and Resource Optimization for UAV Synthetic Aperture Radar - Lahmeri, Mohamed Amine; Ghanem, Walid; Knill, Christina; Schober, Robert (2022 IEEE GLOBECOM Workshops, GC Wkshps 2022 - Proceedings, 2022)
In this paper, we study the trajectory and resource optimization for lightweight rotary-wing unmanned aerial vehicles (UAVs) equipped with a synthetic aperture radar (SAR) system. The UAV's mission is to perform SAR imaging of a given area of interest (AoI). In this setup, real-time communication with a base station (BS) is required to facilitate live mission planning for the drone. For this purpose, a non-convex mixed-integer non-linear program (MINLP) is formulated such that the UAV resources and three-dimensional (3D) trajectory are jointly optimized for maximization of the drone radar ground coverage. We present a low-complexity sub-optimal algorithm based on successive convex approximation (SCA) for solving the problem, and perform a finite search to optimize the total distance traversed by the UAV for maximal coverage. We show that the proposed 3D trajectory planning achieves at least 70% improvement in radar ground coverage compared to benchmark schemes employing constant powers for communication or radar imaging. We also show that positioning the BS near the AoI can significantly improve the radar coverage of the UAV.
CRIS-Team Scopus Importer:2023-03-07

Trajectory Design and Resource Allocation for UAV-Enabled Data Collection in Wireless Sensor Networks with 3D Blockages - Cai, Yuanxin; Yuan, Weijie; Wei, Zhiqiang; Liu, Chang; Hu, Shaokang; Kwan Ng, Derrick Wing (2022 1st International Conference on 6G Networking, 6GNet 2022, 2022)
In this paper, we study the trajectory design and resource allocation for the unmanned aerial vehicle (UAV)-enabled data collection in wireless sensor networks (WSNs) considering the potential blockages caused by multiple three-dimensional (3D) buildings. We aim to maximize the average data collection rate via jointly designing the sensor node (SN) scheduling for data collection, the transmit power, and the UAV's trajectory. To this end, the design is formulated as a non-convex optimization problem taking into account the existence of blockages and the potential of data buffer overflow at SNs. Since the formulated problem is intractable, we propose an iterative algorithm to obtain an efficient suboptimal solution. Numerical results demonstrate that the proposed algorithm can achieve substainal performance gain in terms of data collection for different number of SNs over other baseline schemes.
CRIS-Team Scopus Importer:2022-09-02

Transceiver design for SC-FDE based MIMO relay systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2013)
In this paper, we propose a joint transceiver design for single-carrier frequency-domain equalization (SC-FDE) based multiple-input multiple-output (MIMO) relay systems. To this end, we first derive the optimal minimum mean-squared error linear and decision-feedback frequency-domain equalization filters at the destination along with the corresponding error covariance matrices at the output of the equalizer. Subsequently, we formulate the source and relay precoding matrix design problem as the minimization of a family of Schur-convex and Schur-concave functions of the mean-squared errors at the output of the equalizer under separate power constraints for the source and the relay. By exploiting properties of the error covariance matrix and results from majorization theory, we derive the optimal structures of the source and relay precoding matrices, which allows us to transform the matrix optimization problem into a scalar power optimization problem. Adopting a high signal-to-noise ratio approximation for the objective function, we obtain the global optimal solution for the power allocation variables. We illustrate the excellent performance of the proposed system and compare it to that of conventional orthogonal frequency-division multiplexing MIMO relay systems based on computer simulations. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: MIMO Relay; Single-carrier frequency-domain equalization; Transceiver design

Transfer Function Models for Cylindrical MC Channels with Diffusion and Laminar Flow - Schäfer, Maximilian; Wicke, Wayan; Brand, Lukas; Rabenstein, Rudolf; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2021)
The analysis and design of advection-diffusion based molecular communication (MC) systems in cylindrical environments is of particular interest for applications such as micro-fluidics and targeted drug delivery in blood vessels. Therefore, the accurate modeling of the corresponding MC channel is of high importance. The propagation of particles in these systems is caused by a combination of diffusion and flow with a parabolic velocity profile, i.e., laminar flow. The propagation characteristics of the particles can be categorized into three different regimes: The flow dominant regime where the influence of diffusion on the particle transport is negligible, the dispersive regime where diffusion has a much stronger impact than flow, and the mixed regime where both effects are important. For the limiting regimes, i.e., the flow dominant and dispersive regimes, well-known solutions and approximations for particle transport exist. For the mixed regime, approximations, numerical techniques, and particle based simulations are employed. However, the few analytical models that are applicable in all three regimes impose significant constraints on the possible transmitter locations and particle release profiles. In this paper, we develop a more general analytical model for the advection-diffusion problem in cylindrical environments, which is applicable in all three regimes and accounts for general particle release models. The proposed model exhibits a higher accuracy than existing models and is based on a transfer function approach, where the main challenge is the incorporation of laminar flow. The properties of the proposed model are analyzed by numerical evaluation for different scenarios including the uniform and point release of particles. We provide a comparison with particle based simulations and existing analytical models from the literature to demonstrate the validity of the proposed analytical model.<br
Keywords: Analytical models; Mathematical model; Numerical models; Dispersion; Biology; Transfer functions; Plugs

Transfer function models for particle diffusion in a horizontal cylindrical shape with a vertical force component - Schäfer, Maximilian; Wicke, Wayan; Rabenstein, Rudolf; Schober, Robert (2018)

Transmission and Reception Concepts for WLAN IEEE 802.11b - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (IEEE Transactions on Wireless Communications, 2006)
State-of-the-art wireless local area network (WLAN) IEEE 802.11b terminals employ complementary code keying (CCK) as modulation format. In this paper, receiver concepts tailored for CCK transmission over frequency-selective fading channels are presented in a unified and systematic framework. First, optimum maximum-likelihood (ML) detection for CCK signaling is considered. Second, for complexity reduction, minimum mean-squared error block decision-feedback equalization (MMSE-DFE) is investigated and reduced-state sequence estimation (RSSE) is considered on the basis of an Ungerböck-like set partitioning of the multidimensional CCK code word set. In order to improve the reliability of CCK transmission over fading channels, time-reversal space-time block codes (TR-STBCs) combined with receive diversity are applied. Simulation results of the considered suboptimum receivers are compared with a performance approximation for optimum detection. Our results demonstrate the excellent performance of the advocated equalization schemes and the significant gains that can be achieved with TR-STBCs and receive diversity in typical WLAN environments. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.mobilk.transm
Keywords: (time-reversal) space-time block codes; Complementary code keying; Decision feedback equalization; Diversity; Equalization; Reduced-state sequence estimation; WLAN IEEE 802.11b

Transmit antenna selection for security enhancement in MIMO wiretap channels - Yang, Nan; Yeoh, Phee Lep; Elkashlan, Maged; Schober, Robert; Collings, Iain B. (IEEE Transactions on Communications, 2013)
We propose and analyze transmit antenna selection (TAS) to enhance physical layer security in a wiretap channel with NA antennas at the transmitter, NB antennas at the receiver, and NE antennas at the eavesdropper. We focus on the practical scenario where the transmitter does not have any channel state information (CSI) of the eavesdropper's channel. The transmitter selects a single antenna that maximizes the instantaneous signal-to-noise ratio (SNR) at the receiver. The receiver and the eavesdropper employ either maximal-ratio combining (MRC) or selection combining (SC) to combine the received signals. For the proposed protocols, we derive new closed-form expressions for the probability of non-zero secrecy capacity. We consider Nakagami-m fading with non-identical fading parameters of the main channel, mB, and of the eavesdropper's channel, mE. Next, we derive new closed-form expressions for the exact secrecy outage probability, based on which the ε-outage secrecy capacity is characterized. Based on the exact expressions, we derive the asymptotic secrecy outage probability which accurately reveals the secrecy diversity order and the secrecy array gain. We confirm that the proposed protocols achieve identical secrecy diversity orders of NANBmB. An interesting conclusion is reached that this diversity order is independent of NE and m E. Furthermore, we prove that under the proposed protocols, the secrecy outage probability and the ε-outage secrecy capacity improve with increasing NA. © 1972-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: MIMO; Nakagami-m fading; physical layer security; transmit antenna selection

Transmit beamforming for QoE improvement in C-RAN with mobile virtual network operators - Wang, Zehua; Wing Kwan Ng, Derrick; Wong, Vincent W. S.; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
Network slicing enables mobile virtual network operators (MVNOs) to lease network resources from a mobile network operator (MNO). The cloud radio access network (CRAN) architecture reduces the capital and operational expenditures for the MNO and also facilitates MVNOs running virtual machines on the cloud server. In this paper, we propose a beamforming scheme that coordinates multiple remote radio heads (RRHs) in C-RAN to improve the quality of experience (QoE) of users by maximizing their aggregate weighted quality of service (QoS). We model the QoS of each mobile user by a sigmoidal function and formulate the beamforming design as a non-convex optimization problem. By introducing an interference threshold, we first develop an iterative algorithm to determine a suboptimal solution of the original problem. Based on simulation results, we then show that a suitable interference threshold can be obtained in an off-line manner such that the suboptimal solution is a close-to-optimal solution of the original non-convex problem. Simulation results also show that the proposed scheme can significantly improve the aggregate weighted QoS of the mobile users compared to the traditional design where the weighted system sum rate is maximized.<br
Keywords: Mobile communication; Quality of service; Interference; Array signal processing; Mobile computing; Servers; Cloud computing

Transmitter-Side Channel Estimation in Magnetic Induction based Communication Systems - Kisseleff, Steven; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE International Black Sea Conferance on Comunications (BlackSeaCom), 2014)

Transport capacity of gaussian multiple access and broadcast channels with a large number of nodes - Müller, Ralf; et al. (2005 IEEE International Symposium on Information Theory, ISIT 05, 2005)
We determine the maximum transport capacity of a Gaussian broadcast channel and of a Gaussian multiple access channel. Transport capacity is denned as the sum, over all simultaneous transmissions, of the product of the transmission rate with a reward r(x), where x is the distance between the receiver and the transmitter. In the case of the broadcast channel, the optimization is performed over all allocations of the transmitter power to the signals intended for the different receivers. In the case of the multiple access channel, the optimization is performed over all allocations of power at the transmitters that satisfy a sum constraint. Our approach is to assume a large number of receivers (or transmitters) and formulate the problem within the framework of the calculus of variations.

Trellis-based equalization schemes for physical layer network coding - Schmidt, Armin Christian; Gerstacker, Wolfgang (2012 IEEE International Conference on Communications (ICC), 2012)
In this paper, we consider two-way relaying in a physical layer network coded system in a scenario where transmissions are subject to frequency-selective fading. Physical Layer Network Coding (PNC) enabled single-carrier transmission systems operating in flat fading environments have been subjected to scrutiny extensively, yet approaches for tackling the problem of extending them to environments causing multi-path fading are quite limited. We present three equalization schemes that can be used at the relay nodes to retrieve the data to be relayed in the presence of intersymbol interference (ISI). The most basic scheme jointly estimates both data streams and combines them afterwards. Furthermore, a scheme that already combines state and transition probabilities inside the trellis diagram is devised. Finally, we present a complexity-reduced algorithm where state combinations that yield the same bit to be relayed can be combined into a single state. All of the three algorithms can be regarded as different types of a decode-and-forward (DF) schem

TTD Configurations for Near-Field Beamforming: Parallel, Serial, or Hybrid? - Wang, Zhaolin; Mu, Xidong; Liu, Yuanwei; Schober, Robert (IEEE Transactions on Communications, 2024)
True-time delayers (TTDs) are popular components for hybrid beamforming architectures to combat the spatial-wideband effect in wideband near-field communications. In this paper, a serial and a hybrid serial-parallel TTD configuration are investigated for hybrid beamforming architectures. Compared to the conventional parallel configuration, the serial configuration exhibits a cumulative time delay caused by multiple TTDs, which potentially alleviates the maximum delay requirements on the individual TTDs. However, independent control of individual TTDs becomes impossible in the serial configuration. Therefore, a hybrid TTD configuration is proposed as a compromise solution. Furthermore, a power equalization approach is proposed to address the cumulative insertion loss of the serial and hybrid TTD configurations. Moreover, the wideband near-field beamforming design for different configurations is studied to maximize the spectral efficiency in both single-user and multiple-user systems. 1) For single-user systems, a closed-form solution for the beamforming design is derived. The preferred user locations and the required maximum time delay of each TTD configuration are characterized. 2) For multi-user systems, a penalty-based iterative algorithm is developed to obtain a stationary point of the spectral efficiency maximization problem for the considered TTD configurations. In addition, a hybrid-forward-and-backward (HFB) implementation is proposed to enhance the performance of the serial configuration. Our numerical results confirm the effectiveness of the proposed designs and unveil that i) compared to the conventional parallel configuration, both the serial and hybrid configurations can significantly reduce the maximum time delays required for the individual TTDs and ii) the hybrid configuration excels in single-user systems, while the HFB serial configuration is preferred in multi-user systems.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Array signal processing; Beamfocusing; Delay effects; Delays; Hybrid power systems; near-field communications; OFDM; Radio frequency; spatial wideband effect; true-time delayers; Wideband

Two-Phase Channel Estimation for UPA-Type RIS-Aided Multi-User mmWave Systems with Reduced Pilot Overhead and Error Propagation - Peng, Zhendong; Pan, Cunhua; Zhou, Gui; Ren, Hong (IEEE International Conference on Communications, 2023)
In this paper, an efficient two-phase channel estimation scheme with reduced pilot overhead and error propagation is proposed for a uniform planar array (UPA)-type reconfigurable intelligent surface (RIS)-aided multi-user (MU) millimeter wave (mmWave) system. In Phase I, based on the carefully designed RIS phase shift matrix, all users jointly transmit the pilot signals to estimate the correlation factors between different propagation paths of the common RIS-base station (BS) channel, which facilitates a significant MU diversity gain. Then, in Phase II, with the constructed ambiguous RIS-BS channel composed of the correlation factors obtained in the previous phase, each user independently sends a few pilots to estimate their own ambiguous user-RIS channel so as to obtain the entire cascaded channel. Simulation results validate that the proposed algorithm outperforms the existing algorithms in terms of both pilot overhead and estimation accuracy, and that its estimation performance improves as the number of users increases.
CRIS-Team Scopus Importer:2023-12-15
Keywords: channel estimation; millimeter wave; multi-user systems; Reconfigurable intelligent surface; uniform planar array

Two-Stage Channel Estimation for RIS-Aided Multi-User mmWave Systems with Reduced Error Propagation and Pilot Overhead - Peng, Zhendong; Pan, Cunhua; Zhou, Gui; Ren, Hong; Jin, Shi; Popovski, Petar; Schober, Robert; You, Xiaohu (IEEE Transactions on Signal Processing, 2023)
In this paper, we propose a novel two-stage uplink channel estimation strategy with reduced pilot overhead and error propagation for reconfigurable intelligent surface (RIS)-aided multi-user (MU) millimeter wave (mmWave) multiple-antenna systems. The base station (BS) and the RIS are equipped with a uniform linear array (ULA) and a uniform planar array (UPA), respectively. Specifically, in Stage I, by carefully designing the RIS phase shift matrix and introducing a matching matrix, all users jointly transmit pilot signals for the estimation of the correlation factors between different paths of the common RIS-base station (BS) channel, which facilitates a significant MU diversity gain. Then, because of the inherent scaling and angle ambiguities of the mmWave cascaded channel, an ambiguous common RIS-BS channel composed of the estimated correlation factors is constructed. In Stage II, given the constructed ambiguous RIS-BS channel, each user independently sends a few pilots for estimating their own ambiguous user-RIS channel so as to obtain the entire cascaded channel. Simulation results demonstrate that the channel estimation accuracy of the proposed algorithm is improved as the number of users increases, and existing channel estimation algorithms are outperformed in terms of both pilot overhead and estimation accuracy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: channel estimation; Channel estimation; Correlation; Estimation; millimeter wave; Millimeter wave communication; multi-user systems; Protocols; Reconfigurable intelligent surface; Signal processing algorithms; Transmission line matrix methods

Two-Timescale Design for Reconfigurable Intelligent Surface-Aided Massive MIMO Systems with Imperfect CSI - Zhi, Kangda; Pan, Cunhua; Ren, Hong; Wang, Kezhi; Elkashlan, Maged; Di Renzo, Marco; Schober, Robert; Vincent Poor, H.; Wang, Jiangzhou; Hanzo, Lajos (IEEE Transactions on Information Theory, 2022)
This paper investigates the two-timescale transmission scheme for reconfigurable intelligent surface (RIS)-aided massive multiple-input multiple-output (MIMO) systems, where the beamforming at the base station (BS) is adapted to the rapidly-changing instantaneous channel state information (CSI), while the nearly-passive beamforming at the RIS is adapted to the slowly-changing statistical CSI. Specifically, we first consider a system model with spatially independent Rician fading channels, which leads to tractable expressions and offers analytical insights on the power scaling laws and on the impact of various system parameters. Then, we analyze a more general system model with spatially correlated Rician fading channels and consider the impact of electromagnetic interference (EMI) caused by any uncontrollable sources present in the considered environment. For both case studies, we apply the linear minimum mean square error (LMMSE) estimator to estimate the aggregated channel from the users to the BS, utilize the low-complexity maximal ratio combining (MRC) detector, and derive a closed-form expression for a lower bound of the achievable rate. Besides, an accelerated gradient ascent-based algorithm is proposed for solving the minimum user rate maximization problem. Numerical results show that, in the considered setup, the spatially independent model without EMI is sufficiently accurate when the inter-distance of the RIS elements is sufficiently large and the EMI is mild. In the presence of spatial correlation, we show that an RIS can better tailor the wireless environment. Furthermore, it is shown that deploying an RIS in a massive MIMO network brings significant gains when the RIS is deployed close to the cell-edge users. On the other hand, the gains obtained by the users distributed over a large area are shown to be modest.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Analytical models; Array signal processing; channel estimation; Channel estimation; Correlation; Electromagnetic interference; electromagnetic interference (EMI); massive MIMO; Massive MIMO; Reconfigurable intelligent surface (RIS); Rician channels; spatial correlation; two-timescale transmission scheme

UAV-Assisted Wireless Powered Relay Networks with Cyclical NOMA-TDMA - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola; Schober, Robert (IEEE Wireless Communications Letters, 2020)
We optimize the performance of an unmanned aerial vehicle (UAV)-assisted wireless powered relay network (WPRN), where the UAV is used as a radio-frequency (RF) power transmitter and as a communication relay between energy harvesting users (EHUs) and a base station (BS). The EHUs are assigned to radial service sectors, centered around the base station (BS), and employ a combination of non-orthogonal multiple access (NOMA) and time-division multiple access (TDMA), referred to as cyclical NOMA-TDMA, for multiple access. For performance optimization, maximization of the sum rate in all service sectors and maximization of the minimal sum rate per service sector are considered, and the optimal radii of the UAV's circular trajectory and the optimal allocation of the UAV's transmit power across the service sectors are determined.
CRIS-Team Scopus Importer:2020-12-25
Keywords: multiple access techniques; relaying; unmanned aerial vehicles; Wireless power transfer

Unified Design of Wireless Information and Power Transmission - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
This chapter reveals that the efficiency in fact varies with both the radio frequency (RF) input power at the rectifier and the specific RF signal waveform being used for simultaneous wireless information and power transfer (SWIPT), which has motivated to implement dual mode SWIPT. It proposes a new transceiver architecture for SWIPT with adaptive mode switching (MS) between single and multi‐tone waveforms via an adaptive power management and information decoding (PM‐ID) module to control the operational range for energy neutral operation. The chapter presents nonlinear energy harvesting (EH) models along with the measured RF‐to‐direct current power conversion efficiency (PCE), which provides useful insights for designing dual mode SWIPT. It proposes a waveform and transceiver design for multi‐tone (PAPR) based SWIPT with higher WPT efficiency and dual mode SWIPT for an increased operational range. The chapter also proposes the reconfigurable energy harvester for enlarging the linear region of the PCE over wide input power ranges.<br
Keywords: Integrated circuit modeling; Peak to average power ratio; Transceivers; Shape; Smart devices; Power transmission

Unsupervised neural decoding of signals recorded by thin-film electrode arrays implanted in muscles using autoencoding with a physiologically derived optimisation criterion - Mayer, Kenneth; Del Vecchio, Alessandro; Eskofier, Björn; Farina, Dario (Biomedical Signal Processing and Control, 2023)
We present an autoencoder that learns the discharge times of individual motor units (MU) by processing multichannel electromyogram (EMG) recordings obtained by electrode arrays implanted in muscles, thereby providing a neural interface with the spinal cord. To this end, after preprocessing of the EMG via convolutive sphering, the encoder is constrained to apply an orthogonal transformation to the spatial data and the optimisation criterion enforces a temporal sparsity constraint. These constraints are based on the theoretical modelling of EMG generation. This decomposition method was evaluated on both simulated and experimental signals. For simulated signals, with a ratio of 1.5 between observations and sources, the average detection accuracy was 94% for up to 60 sources for SNR 20 dB. Moreover, the detection accuracy did not significantly decrease when decreasing the SNR to values as low as 0 dB. Experimental signals were collected in humans with thin-film invasive electrodes implanted in the tibialis anterior muscle. The results showed an accuracy on experimental data >90%. Moreover, the proposed method outperformed a state-of-the-art blind source separation approach in terms of the number of reliably detected motor units. In conclusion, we have proposed the first fully unsupervised neural network approach to the problem of neural decoding of intramuscular EMG time series by translating the available theoretical knowledge on the signal properties into an autoencoding architecture tailored to the decomposition problem.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Autoencoder; Blind deconvolution; EMG signal decomposition; Sparse signals; Unsupervised learning

Unveiling the Importance of NOMA for Reducing AoI - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE International Conference on Communications, 2023)
The aim of this paper is to exploit cognitive-ratio inspired non-orthogonal multiple access (CR-NOMA) transmission to reduce the age of information (AoI) in wireless networks, where the key features of different data generation models are effectively utilized. Analytical results for the AoI achieved by CR-NOMA are developed to demonstrate two benefits of using NOMA to reduce the AoI in wireless networks. One is that the use of NOMA provides users more opportunities to transmit, which means that the users can update their base station more frequently. The other is that the use of NOMA can reduce access delay, i.e., the users are scheduled to transmit earlier than in the orthogonal multiple access (OMA) case, which is useful to improve the freshness of the data available in the wireless network.
CRIS-Team Scopus Importer:2023-12-15

Unveiling the Importance of SIC in NOMA Systems - Part 1: State of the Art and Recent Findings - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Communications Letters, 2020)
The key idea of non-orthogonal multiple access (NOMA) is to serve multiple users simultaneously at the same time and frequency, which can result in excessive multiple-access interference. As a crucial component of NOMA systems, successive interference cancelation (SIC) is key to combating this multiple-access interference, and is the focus of this letter, where an overview of SIC decoding order selection schemes is provided. In particular, selecting the SIC decoding order based on the users' channel state information (CSI) and the users' quality of service (QoS), respectively, is discussed. The limitations of these two approaches are illustrated, and then a recently proposed scheme, termed hybrid SIC, which dynamically adapts the SIC decoding order is presented and shown to achieve a surprising performance improvement that cannot be realized by the conventional SIC decoding order selection schemes individually.
CRIS-Team Scopus Importer:2020-11-27
Keywords: hybrid successive interference cancellation (SIC); Non-orthogonal multiple access (NOMA); outage probability error floors

Unveiling the Importance of SIC in NOMA Systems - Part II: New Results and Future Directions - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Communications Letters, 2020)
In most existing works on non-orthogonal multiple access (NOMA), the decoding order of successive interference cancellation (SIC) is prefixed and based on either the users' channel conditions or their quality of service (QoS) requirements. A recent work on NOMA assisted semi-grant-free transmission showed that the use of a more sophisticated hybrid SIC scheme can yield significant performance improvements. This letter illustrates how the concept of hybrid SIC can be generalized and applied to different NOMA applications. We first use NOMA assisted mobile edge computing (MEC) as an example to illustrate the benefits of hybrid SIC, where new results for offloading energy minimization are presented. Then, future directions for generalizing hybrid SIC with adaptive decoding order selection as well as its promising applications are discussed.
CRIS-Team Scopus Importer:2020-11-27
Keywords: hybrid successive interference cancellation (SIC); mobile edge computing (MEC); Non-orthogonal multiple access (NOMA)

Uplink and Downlink MIMO-NOMA with Simultaneous Triangularization - Krishnamoorthy, Aravindh; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
In this paper, we consider the uplink and downlink precoder design for two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) systems. We propose novel uplink and downlink precoding and detection schemes that lower the decoding complexity at the receiver by decomposing the MIMO-NOMA channels of the users into multiple single-input single-output (SISO)-NOMA channels via simultaneous triangularization (ST) of the MIMO channels of the users and low-complexity self-interference cancellation at the receivers. The proposed ST MIMO-NOMA schemes avoid channel inversion at transmitter and receiver and take advantage of the null spaces of the MIMO channels of the users, which is beneficial for the ergodic achievable rate performance. We characterize the maximum ergodic achievable rate regions of the proposed uplink and downlink ST MIMO-NOMA schemes, and compare them with respective upper bounds, baseline MIMO-NOMA schemes, and orthogonal multiple access (OMA). Our results illustrate that the proposed schemes significantly outperform the considered baseline MIMO-NOMA schemes and OMA, and have a small gap to the respective upper bounds for most channel conditions and user rates. Moreover, we show that a hybrid scheme, which performs time sharing between the proposed uplink and downlink ST MIMO-NOMA and single-user MIMO, can improve performance even further.
CRIS-Team Scopus Importer:2021-01-29

Uplink Channel Estimation in Massive MIMO Systems Using Factor Analysis - Wei, Xiao; Peng, Wei; Chen, Da; Schober, Robert; Jiang, Tao (IEEE Communications Letters, 2018)
In this letter, we consider the channel estimation problem under pilot contamination in massive multiple-input multiple-output (MIMO) systems. We propose a novel channel estimation scheme, which decomposes the space supported by the covariance matrix of the received signals into three subspaces using factor analysis. For a large number of base station antennas, a practically interference-free subspace is created, in which an accurate channel estimate can be obtained. The proposed factor analysis based scheme exploits spatial correlation to significantly reduce the computational complexity. Simulation results are provided to show the efficacy of the proposed scheme.<br
Keywords: Channel estimation; MIMO communication; Covariance matrices; Contamination; Antennas; Estimation; Computational complexity

Uplink/downlink duality in massive MIMO systems with hardware impairments - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, we provide a new framework for the uplink/downlink duality in single-cell massive multiple-input multiple-output (MIMO) systems suffering from residual hardware impairments (HWIs) at the base station and the user terminals. Using the proposed duality, complex downlink optimization problems can be converted to equivalent dual uplink problems, which are easier to solve. As an example, we apply the proposed uplink/downlink duality to derive an HWI aware minimum mean square error (HWIA-MMSE) precoder, which minimizes the sum mean square error under a sum power constraint in a single-cell massive MIMO system with residual HWIs. Thereby, we use results from random matrix theory to derive an asymptotic expression for the downlink power allocation for large numbers of antennas, which only depends on the channel statistics and not on the individual channel realizations. Analytical results for the asymptotic achievable sum rate of the proposed HWIA-MMSE precoder for a large number of BS antennas are also provided. Our simulation and analytical results show that the proposed HWIA-MMSE precoder achieves a higher sum rate than the conventional regularized zero-forcing precoder for moderately large numbers of base station antennas.<br
Keywords: Downlink; Uplink; MIMO; Antennas; Signal to noise ratio; Covariance matrices; Resource management

Uplink/downlink duality in multi-cell Mu-MIMO systems with hardware impairments - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (WSA 2016 - 20th International ITG Workshop on Smart Antennas, 2019)
In this paper, we propose an uplink/downlink duality framework for multi-cell multi-user multiple-input multiple-output (MU-MIMO) systems with residual hardware impairments (HWIs) at the base station and the user terminals. By employing the proposed uplink/downlink duality framework, complex downlink optimization problems can be transformed to equivalent dual uplink problems which are easier to solve. Thereby, for the same total transmit power, the same per-user signal-to-interference-plus-noise ratios (SINRs) are achieved in downlink and uplink. We apply the proposed uplink/downlink duality, and derive a multi-cell HWI aware minimum mean square error (MCHWA-MMSE) precoder. Our simulation results show that the proposed MCHWA-MMSE precoder achieves a substantially higher sum rate than conventional MMSE and conjugate beamforming precoders.
CRIS-Team Scopus Importer:2019-10-25

Uplink/Downlink Duality in Multi-Cell MU-MIMO Systems with Hardware Impairments - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (WSA 2016; 20th International ITG Workshop on Smart Antennas, 2016)
In this paper, we propose an uplink/downlink duality framework for multi-cell multi-user multiple-input multiple-output (MU-MIMO) systems with residual hardware impairments (HWIs) at the base station and the user terminals. By employing the proposed uplink/downlink duality framework, complex downlink optimization problems can be transformed to equivalent dual uplink problems which are easier to solve. Thereby, for the same total transmit power, the same per-user signal-to-interference-plus-noise ratios (SINRs) are achieved in downlink and uplink. We apply the proposed uplink/downlink duality, and derive a multi-cell HWI aware minimum mean square error (MCHWA-MMSE) precoder. Our simulation results show that the proposed MCHWA-MMSE precoder achieves a substantially higher sum rate than conventional MMSE and conjugate beamforming precoders.<br

User Association in 5G Networks: A Survey and an Outlook - Liu, Dantong; Wang, Lifeng; Chen, Yue; Elkashlan, Maged; Wong, Kai-Kit; Schober, Robert; Hanzo, Lajos (IEEE Communications Surveys & Tutorials, 2016)
The fifth generation (5G) mobile networks are envisioned to support the deluge of data traffic with reduced energy consumption and improved quality of service (QoS) provision. To this end, key enabling technologies, such as heterogeneous networks (HetNets), massive multiple-input multiple-output (MIMO), and millimeter wave (mmWave) techniques, have been identified to bring 5G to fruition. Regardless of the technology adopted, a user association mechanism is needed to determine whether a user is associated with a particular base station (BS) before data transmission commences. User association plays a pivotal role in enhancing the load balancing, the spectrum efficiency, and the energy efficiency of networks. The emerging 5G networks introduce numerous challenges and opportunities for the design of sophisticated user association mechanisms. Hence, substantial research efforts are dedicated to the issues of user association in HetNets, massive MIMO networks, mmWave networks, and energy harvesting networks. We introduce a taxonomy as a framework for systematically studying the existing user association algorithms. Based on the proposed taxonomy, we then proceed to present an extensive overview of the state-of-the-art in user association algorithms conceived for HetNets, massive MIMO, mmWave, and energy harvesting networks. Finally, we summarize the challenges as well as opportunities of user association in 5G and provide design guidelines and potential solutions for sophisticated user association mechanisms.<br
Keywords: 5G mobile communication; MIMO; Energy harvesting; Wireless communication; Communication system security; Resource Management; Quality of service

User-Centric Energy Efficiency Maximization for Wireless Powered Communications - Wu, Qingqing; Chen, Wen; Wing Kwan Ng, Derrick; Li, Jun; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we consider wireless powered communication networks (WPCNs) where multiple users harvest energy from a dedicated power station and then communicate with an information receiving station in a time-division manner. Thereby, our goal is to maximize the weighted sum of the user energy efficiencies (WSUEEs). In contrast to the existing system-centric approaches, the choice of the weights provides flexibility for balancing the individual user EEs via joint time allocation and power control. We first investigate the WSUEE maximization problem without the quality of service constraints. Closed-form expressions for the WSUEE as well as the optimal time allocation and power control are derived. Based on this result, we characterize the EE tradeoff between the users in the WPCN. Subsequently, we study the WSUEE maximization problem in a generalized WPCN where each user is equipped with an initial amount of energy and also has a minimum throughput requirement. By exploiting the sum-of-ratios structure of the objective function, we transform the resulting non-convex optimization problem into a two-layer subtractive-form optimization problem, which leads to an efficient approach for obtaining the optimal solution. The simulation results verify our theoretical findings and demonstrate the effectiveness of the proposed approach.<br
Keywords: Wireless communication; Resource management; Throughput; Power generation; Optimization; Quality of service; Power control

User Pairing for Multiuser SC-FDMA Transmission over Virtual MIMO ISI Channels - Ruder, Michael; Dang, Thi Uyen Ly; Gerstacker, Wolfgang (GLOBECOM 2009 - 2009 IEEE Global Telecommunications Conference, 2010)
This paper proposes different criteria for user pairing for a virtual multiple-input multiple-output (V-MIMO) single-carrier frequency-division multiple access (SC-FDMA) transmission over intersymbol interference (ISI) channels. Two users, equipped with a single antenna each, transmit their data in the same time slot and frequency band. The receiver at the base station (BS) is assumed to have two antennas and separates both users with a multiuser equalizer. For this, linear minimum mean-squared error (MMSE) equalization and successive interference cancellation (SIC), respectively, are chosen. Various pairing criteria are proposed and compared by simulations for a transmission in the uplink of E-UTRA Long Term Evolution (LTE). The simulation results indicate that well-designed user pairing strategies yield significant gains compared to random user pairing. It is shown that the proposed novel bit error rate (BER) pairing achieves a significant performance gain compared to capacity pairing for a SIC receiver and higher order modulatio

Using parasitic elements for implementing the rotating antenna for MIMO receivers - Bains, Robert; Müller, Ralf (IEEE Transactions on Wireless Communications, 2008)
We consider a new concept of a Multiple-Input-Multiple-Output (MIMO) receiver which uses one active receiving antenna and multiple parasitic elements. The parasitic elements give the possibility of creating a directive antenna beam which is rotated 360 degrees around within the duration of a symbol period. The received signal which is accessed at the antenna connector of the active antenna is expanded in frequency bandwidth compared to the transmitted signal. We show that each sub-band of the received signal consists of linearly independent combinations of the transmitted signals, and thus we have obtained a MIMO receiver. We give a few examples on how to implement this receiver and also explain the effects of sampling the wave-field at discrete angular directions. © 2008 IEEE.
Keywords: MIMO systems; Transceiver design; Transmission technology

Utilizing renewable energy resources by adopting DSM techniques and storage facilities - Samadi, Pedram; Mohsenian-Rad, Hamed; Wong, Vincent W. S.; Schober, Robert (2014 IEEE International Conference on Communications (ICC), 2014)
A common assumption in the existing literature on energy consumption scheduling in smart grid is that users are aware in advance of their daily energy consumption needs. Therefore, most existing studies along this line of research have been inherently deterministic, e.g., see [1]-[3]. However, this assumption may not hold in practice. In particular, the energy consumption scheduling (ECS) devices may face load uncertainty. If a user is equipped with a behind-the-meter renewable generator, then the optimal operation of ECS devices becomes even more challenging due to combined load and supply uncertainties. Therefore, in this paper, we formulate a stochastic optimization problem to operate an ECS device in a residential unit that is equipped with a behind-the-meter renewable generator and a local battery bank. In our problem formulation, we consider different sets of must-run and controllable appliances. Our design only requires knowledge of some estimates of the users' future demand. To reduce computational complexity, we approximate the expected load in the upcoming time slots by adopting the certainty equivalent approximation technique. Simulation results show that the proposed energy consumption scheduling algorithm can tackle the uncertainties in load and supply and it can benefit both users and the utility companies.<br
Keywords: Home appliances; Batteries; Uncertainty; Energy consumption; Power generation; Schedules; Electricity

Vector precoding for Gaussian MIMO broadcast channels: Impact of replica symmetry breaking - Zaidel, Benjamin M.; Müller, Ralf; Moustakas, Aris L.; De Miguel, Rodrigo (IEEE Transactions on Information Theory, 2012)
The "replica method" of statistical physics is employed for the large-system analysis of vector precoding for the Gaussian multiple-input multiple-output broadcast channel. The transmitter comprises a linear front-end combined with nonlinear precoding, minimizing transmit energy by means of input alphabet relaxation. For the common discrete lattice-based relaxation, the problem violates replica symmetry and a replica symmetry breaking (RSB) ansatz is taken. The limiting empirical distribution of the precoder's output and the limiting transmit energy are derived for one-step RSB. Particularizing to a "zero-forcing" (ZF) linear front-end, a decoupling result is derived. For discrete lattice-based relaxations, the impact of RSB is demonstrated for the transmit energy. The spectral efficiencies of the aforementioned precoding methods are compared to linear ZF and Tomlinson-Harashima precoding (THP). Focusing on quaternary phase shift-keying (QPSK), significant performance gains of both lattice and convex relaxations are revealed for medium to high signal-to-noise ratios (SNRs) when compared to linear ZF precoding. THP is shown to be outperformed as well. Comparing certain lattice-based relaxations for QPSK against a convex counterpart, the latter is found to be superior for low and high SNRs but slightly inferior for medium SNRs in terms of spectral efficiency. © 2012 IEEE.
Keywords: Antenna arrays; broadcast channel; decoupling principle; lattice; multiple-input multiple-output; precoding; R-transform; replica method; zero-forcing (ZF)

Vector precoding for singular MIMO channels - Gardasevic, Vesna; Müller, Ralf; Knudsen, Finn F. (2008 International Symposium on Information Theory and its Applications, ISITA2008, 2008)
We propose a method for vector precoding suited to singular multiple-input multiple-output (MIMO) channels were the number of data streams is larger than the number of transmit antennas. We calculate the probability that our method, due to the channel singularity, fails to provide the data without crosstalk to the receiver, analytically, and show that this probability goes to zero exponentially with the size of the MIMO system if the number of QPSK data streams in smaller than twice the number of transmit antennas.

Vector precoding for wireless MIMO systems and its replica analysis - Müller, Ralf; Guo, Dongning; Moustakas, Aris L. (IEEE Journal on Selected Areas in Communications, 2008)
This paper studies a nonlinear vector precoding scheme which inverts the wireless multiple-input multiple-output (MIMO) channel at the transmitter so that simple symbol-by-symbol detection can be used in lieu of sophisticated multiuser detection at the receiver. In particular, the transmit energy is minimized by relaxing the transmitted symbols to a larger alphabet for precoding, which preserves the minimum signaling distance. The so-called replica method is used to analyze the average energy savings with random MIMO channels in the large-system limit. It is found that significant gains can be achieved with complex-valued alphabets. The analysis applies to a very general class of MIMO channels, where the statistics of the channel matrix enter the result via the R-transform of the asymptotic empirical distribution of its eigenvalues. Moreover, we introduce polynomial-complexity precoding schemes for binary and quadrature phase-shift keying in complex channels by using convex rather than discrete relaxed alphabets. In case the number of transmit antennas is more than twice the number of receive antennas, we show that a convex precoding scheme, despite its polynomial complexity, outperforms NP-hard precoding using the popular Tomlinson-Harashima signaling. © 2008 IEEE.
Keywords: Multiple antennas; Multiple-input multiple-output (MIMO) systems; R-transform; Random matrices; Replica method; Spatial equalization; Tomlinson-Harashima precoding

Vector precoding in high dimensions: A replica analysis - Müller, Ralf; Guo, Dongning; Moustakas, Aris L. (2007 IEEE International Symposium on Information Theory, ISIT 2007, 2007)
We apply the replica method to analyze vector pre-coding, a method to reduce transmit power in antenna array communications, in the limit of an infinite number of dimensions of the signal vector. The analysis applies to a very general class of channel matrices. The statistics of the channel matrix enter the transmitted energy per symbol via its R-transform. We specialize our result to inversion of an i.i.d. channel and two cases of signal point optimization i) 2-point lattice pre-coding and ii) compact relaxation. In the two cases the replica symmetric transmitted energy is found to be 4.3 dB and 9.6 dB above the orthogonal case for a square channel matrix, respectively. ©2007 IEEE.

Vector precoding in wireless communications: A replica symmetric analysis - Müller, Ralf; et al. (2nd International ICST Conference on Performance Evaluation Methodologies and Tools, VALUETOOLS 2007, 2007)
We apply the replica method to analyze vector pre-coding, a method to reduce transmit power in antenna array communications, in the limit of an infinite number of dimensions of the signal vector. The analysis applies to a very general class of channel matrices. The statistics of the channel matrix enter the transmitted energy per symbol via its R-transform. Copyright 2007 ICST.
Keywords: Statistical mechanics; Wireless communications

Vehicular SUDAS for 5G High Mobility V2X Scenarios - Shrivastava, Rudraksh; Breiling, Marco; Krishnamoorthy, Aravindh; Krishnamoorthy, Aravindh (2017 IEEE Conference on Standards for Communications and Networking (CSCN), 2017)
In this paper, we present a Vehicular version of the Shared UE-side Distributed Antenna System (SUDAS) i.e. Vehicular SUDAS which enables high throughput wireless communication in high mobility Vehicle-to-X (V2X) scenarios. Vehicular SUDAS uses shared virtual antennas, termed UE-side Radio Units (URUs), which utilize both licensed sub-6 GHz band and unlicensed millimetre wave band, to achieve a virtual MIMO gain in in-vehicle UEs. A simulation study is performed to evaluate and analyze an upper bound of the maximum achievable sum rate in the downlink of the proposed system, assuming perfect Doppler spread compensation. The proposed Vehicular SUDAS shows excellent performance, positioning itself as a strong contender for next V2X communication services.

Welcome from the organizing committee - Gulliver, Aaron; Schober, Robert (IEEE Vehicular Technology Conference, 2014)
CRIS-Team Scopus Importer:2020-02-03

Windowing Schemes for Robust Speech Coding in Packet Loss Scenarios - Krishnamoorthy, Aravindh (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Wireless information and power transfer: Energy efficiency optimization in OFDMA systems - Derrick Wing Kwan Ng,; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
This paper considers orthogonal frequency division multiple access (OFDMA) systems with simultaneous wireless information and power transfer. We study the resource allocation algorithm design for maximization of the energy efficiency of data transmission (bits/Joule delivered to the receivers). In particular, we focus on power splitting hybrid receivers which are able to split the received signals into two power streams for concurrent information decoding and energy harvesting. Two scenarios are investigated considering different power splitting abilities of the receivers. In the first scenario, we assume receivers which can split the received power into a continuous set of power streams with arbitrary power splitting ratios. In the second scenario, we examine receivers which can split the received power only into a discrete set of power streams with fixed power splitting ratios. For both scenarios, we formulate the corresponding algorithm design as a non-convex optimization problem which takes into account the circuit power consumption, the minimum data rate requirements of delay constrained services, the minimum required system data rate, and the minimum amount of power that has to be delivered to the receivers. By exploiting fractional programming and dual decomposition, suboptimal iterative resource allocation algorithms are developed to solve the non-convex problems. Simulation results illustrate that the proposed iterative resource allocation algorithms approach the optimal solution within a small number of iterations and unveil the trade-off between energy efficiency, system capacity, and wireless power transfer: (1) wireless power transfer enhances the system energy efficiency by harvesting energy in the radio frequency, especially in the interference limited regime; (2) the presence of multiple receivers is beneficial for the system capacity, but not necessarily for the system energy efficiency. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy efficiency; green communications; non-convex optimization; wireless information and power transfer

Wireless information and power transfer: Theory and practice - Ng, Derrick Wing Kwan; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (wiley, 2018)
CRIS-Team Scopus Importer:2022-06-05

Wireless local area network service providers' price competition in presence of heterogeneous user demand - Kumar, Abhinav; Mallik, Ranjan K.; Schober, Robert (IET Communications, 2013)
Consider wireless local area network (WLAN) service providers (SPs) operating in an overlapping service area. The SPs compete with each other to attract users. The price charged is utilised by the SPs as a tool to maximise revenue, resulting in a price competition between the WLAN SPs. The users are assumed to be selfish, trying to maximise their individual utility. They have varied sensitivity towards quality of service experienced and the price charged. In such a scenario, the user demand distribution is the one that achieves Wardrop equilibrium. Approximate analytical expressions are obtained for the best response of SPs to each other's price. Existence of a Nash equilibrium (NE) between the competing SPs is proved and the price vector at which the NE occurs is obtained. It is found that, while in one extreme monopoly leads to very high revenue for WLAN SPs with minimal consumer surplus, in the other extreme unregulated duopoly/oligopoly leads to high consumer surplus at the cost of minimal revenue generation for the competing SPs. Thus, price regulation is proposed in the WLAN market for equitable distribution of the surplus among the SPs and the user

Wireless Powered ALOHA Networks with UAV-Mounted-Base Stations - Hadzi-Velkov, Zoran; Pejoski, Slavche; Schober, Robert; Zlatanov, Nikola (IEEE Wireless Communications Letters, 2020)
In this letter, we study wireless powered communication networks (WPCNs) with base stations (BSs) mounted on unmanned aerial vehicles (UAVs). For implementation simplicity and uncoordinated access, the energy harvesting (EH) users (EHUs) employ slotted ALOHA to transmit information at a fixed rate to a common UAV-mounted BS. The UAV flying along a circular trajectory facilitates a line of sight (LoS) between the BS and each EHU, and also mitigates the adverse double near-far effect as it periodically comes close to the EHUs. Due to the periodicity of the LoS channels, the channel can be tracked without performing energy-costly channel estimation, and the channel attenuation can be compensated to avoid channel outages. For such a WPCN, we optimize the UAV radius, the channel access probability, and the rate of each EHU to enable proportionally fair resource allocation. Our solution reveals that, when a certain UAV altitude is exceeded, proportional fairness is attained when the UAV is in the hovering mode.
CRIS-Team Scopus Importer:2020-02-04
Keywords: slotted ALOHA; unmanned aerial vehicles; Wireless powered communication networks

Wireless Power Transfer - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Large‐scale wireless networks are characterized by the existence of multi‐user interference due to the concurrent transmission of the network's terminals. In networks where the main focus is wireless power transfer (WPT), interference is beneficial as it increases the harvesting efficiency. This chapter focuses on a wireless‐powered cooperative network where the relays harvest energy from the source in order to convey its transmitted information. It deals with a simultaneous wireless information and power transfer (SWIPT) scenario, where terminals employ successive interference cancellation (SIC) techniques to boost the harvesting efficiency. The chapter studies a wireless‐powered communication network (WPCN) implementing a wireless‐powered opportunistic beamforming (OBF) protocol. Closed‐form mathematical expressions are provided for the considered performance metric of each scenario as well as numerical results with useful insights regarding the network's performance.<br
Keywords: Relays; Batteries; Wireless communication; Power system reliability; Probability; Signal to noise ratio

Wireless Power Transfer for Access Limited Wireless Underground Sensor Networks - Kisseleff, Steven; Chen, Xiaoyang; Akyildiz, Ian F.; Gerstacker, Wolfgang (IEEE International Conference on Communications (ICC), 2016)

WLAN Service Providers' Price Competition with Uncertainty in User Demand - Kumar, Abhinav; Mallik, Ranjan K.; Schober, Robert (IEEE Communications Letters, 2013)
In this letter, uncertainty in users' network selection is modeled by a Markov chain. In the presence of such uncertainty, the price competition game of wireless local area network (WLAN) service providers (SPs) is analyzed and the existence of Bayesian Nash equilibrium is proved. Using the price of anarchy as a metric of efficiency for social welfare maximization, it is shown that an increase in competition does not result in significant losses in efficiency. Compared to a monopoly, an unregulated duopoly of WLAN SPs is recommended as it results in a more equitable distribution of surplus amongst the SPs and the user

Analysis and Optimisation of Rate Assignment Algorithms for Adaptive Multi Rate (AMR) in 3G-Networks - Knopp, Gunther (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2002)

Design and Implementation of a Scheduler for Processing Tasks in the LTE Receiver - Singh, Parminder (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)

Distance Estimation for Molecular Communication - Marzouk, Mokhtar (2013)

Distributed Routing and Power Control Algorithms in Fixed Wireless Networks - Ferizi, Alban (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2007)

Equalization for FBMC/OQAM Transmission over Frequency-Selective MIMO Channels - Oriold, Daniel (2014)

Funknetzsimulator für High Speed Uplink Packet Access (HSUPA) mit Mehrantennen-Techniken - Amgalan, Gantur (2012)

Hochstufige Modulation und Turbocodierung für GSM/ EDGE - Reck, Christoph (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2007)

Hybrid Relaying Techniques in Wireless Underground Sensor Networks - Sackenreuter, Benjamin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)

Mobility Models for Cooperative Communications - Oriold, Daniel (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Multiuser MIMO Empfänger für den Uplink von Long Term Evolution (LTE) - Ruder, Michael (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2008)

Multiuser Scheduling for Simultaneous Wireless Information and Power Transfer Systems - Chynonova, Maryna (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)

Object Localization in Magnetic Induction based Wireless Underground Sensor Networks using Machine Learning - Chen, Xiaoyang (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)

Optimized (Space Time) Delay Diversity Codes for Frequency Selective Fading Channels - Hehn, Thorsten (2003)

Performance of Multi-User Detection in Systems with Multiple Antennas for OFDM-based Radio Communication - Fischer, Jörg Dieter (2005)

Power Saving Potential of Wireless Relaying - Korn, Clemens (2014)

Precoding for Physical Layer Network Coding - Ziegler, Matthias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)

Propagation Parameter Tracking using Extended Kalman Filter - Pakala, Lalitha (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2011)

Resource Allocation for a Distributed Antenna System - Goodarzi, Meysam (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)

Sensing for 3GPP LTE based Cognitive Mobile Radio - Solak, Aylin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)

Simulation Model for Performance Analysis of UMTS-Networks with Variable Data Rate - Ferizi, Alban (2006)

Single–Antenna Interference Cancellation (SAIC) for EDGE via Lp–Norm and Erasure Decoding - Lehmann, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2011)

Statistische Analyse und Auswertung von MIMO-Funkkanalmessungen - Schuh, Fabian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)

Turbo-Interferenzreduktion für Einträgersysteme - Ruder, Michael (2007)

Untersuchung der WLAN (IEEE 802.11a-OFDM) Performance im mobilen Betrieb bei hohen Relativgeschwindigkeiten - Eidloth, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2004)

Vergleich und Klassifizierung von Mappings für Bit-Interleaved Coded Modulation - Schad, Adrian (2007)

Widely-linear Transceiver Design for Interference Alignment - Ilyas, Rameez (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)